The Cultural Seascape of Wadandi Boodja: The Cultural Values of Australia’s South-west Marine Parks - Harriet Davies; Wayne Webb; Iszaac Webb; Toni Webb; David Guilfoyle; Shannon Clohessy; Griffin, Kingsley; Tim J. Langlois (2023)
This report is designed to provide cultural guidance for the understanding and management of the Australian Marine Parks on Wadandi Watturu Boodja - Saltwater Country Land and Sea. It is designed to inform managers, researchers and the general public. Partnership with Wadandi Traditional Owners and Custodians for this region provided guidance through cultural maps and knowledge to inform the discovery of remarkable biodiversity across submerged ancient coastline features, that document the dynamic history of the region. A short film will complement this report and document how cultural information has guide researchers to understand the marine biodiversity of the region. The cultural knowledge provided through partnership with Wadandi Traditional Owners and Custodians not only guided the discovery of remarkable biodiversity across submerged ancient coastline features but provided future guidance for managing the cultural and natural values of the marine parks that will be documented in future research through the National Environmental Science Programs Marine and Coastal Hub.
Keywords: Australian Marine Parks; cultural seascape; Geographe Bay; songlines; Wadandi Boodja

Extensive polyploid clonality was a successful strategy for seagrass to expand into a newly submerged environment - Edgeloe, Jane M.; Severn-Ellis, Anita A.; Bayer, Philipp E.; Mehravi, Shaghayegh; Breed, Martin F.; Krauss, Siegfried L.; Batley, Jacqueline; Kendrick, Gary A.; Sinclair, Elizabeth A. (Proceedings of the Royal Society B: Biological Sciences, 2022)
Polyploidy has the potential to allow organisms to outcompete their diploid progenitor(s) and occupy new environments. Shark Bay, Western Australia, is a World Heritage Area dominated by temperate seagrass meadows including Poseidon's ribbon weed, Posidonia australis. This seagrass is at the northern extent of its natural geographic range and experiences extremes in temperature and salinity. Our genomic and cytogenetic assessments of 10 meadows identified geographically restricted, diploid clones (2n = 20) in a single location, and a single widespread, high-heterozygosity, polyploid clone (2n = 40) in all other locations. The polyploid clone spanned at least 180 km, making it the largest known example of a clone in any environment on earth. Whole-genome duplication through polyploidy, combined with clonality, may have provided the mechanism for P. australis to expand into new habitats and adapt to new environments that became increasingly stressful for its diploid progenitor(s). The new polyploid clone probably formed in shallow waters after the inundation of Shark Bay less than 8500 years ago and subsequently expanded via vegetative growth into newly submerged habitats.
Keywords: ddRAD-seq; flow cytometry; heterozygosity; karyotyping; population genomics; Posidonia australis

Final Summary of Marine Biodiversity Hub Projects and Outputs - Nicholas J Bax; Paul T Hedge; Alan Jordan (2022)
Keywords: NESP Marine Biodiversity Hub; program; summary

Garig Gunak Barlu National Park Green Sawfish (Pristis zijsron) aggregation surveys - Christy Davies; Thomas Tothill; Jessica J. Meeuwig; PM Kyne (2022)
This report details two surveys of Green Sawfish (Pristis zijsron) at two sites in Garig Gunak Barlu National Park in the Northern Territory. Weather conditions and limited water clarity restricting usable video footage from drones at one site (Lidarnardi) during survey 2. The use of Baited Remote Underwater Videos were unsuccessful. Drones recorded Green Sawfish on 88% of survey days and 30% of transect flights. Sawfish numbers ranged from 1–8 individuals per transect and density from 3.8–30.5 per hectare (the highest density of sawfish ever reported). Sawfish ranged from 57–167 cm total length (TL), with most 60–100 cm TL, suggesting a nursery area. The surveys confirmed the presence of juvenile Green Sawfish in intertidal waters of the national park, suggesting the park waters represents critical habitat, and provides the species some refuge from major threats. However, similar inshore intertidal habitat is not well represented in northern Australian protected areas.
Keywords: BRUVs; critical habitat; drones; nursery areas; Sawfish

Guide for producing science communication videos of surveys of fish and benthic assemblages - Brooke Gibbons; Tim J. Langlois (2022)
This guide is designed for use by researchers producing underwater footage for Parks Australia/Department of Agriculture Water and the Environment (DAWE) and to provide Parks Australia/DAWE with a template for contractors to generate consistent science communication products. We present a simple approach to produce science communication videos from video surveys targeting fish and benthic assemblages (e.g. benthic stereo-baited remote underwater video systems (stereo-BRUVs), pelagic stereo-BRUVs or remotely operated vehicles). These methods can provide useful imagery for science communication, and their production is fast, easy and allows consistent formatting including the use of logos and animation sequences. The videos created using this guide will enable researchers to connect with a general audience through sharing on social media and public presentations.
Keywords: baited remote underwater stereo-video; science communication videos

National Environmental Science Program Marine Biodiversity Hub Final Report 2015-2021 - Jordan, Alan; Hedge, Paul (National Environmental Science Program Marine Biodiversity Hub, 2022)
This 100-page full-colour report showcases research conducted by the Marine Biodiversity Hub, a collaborative partnership supported through funding from the Australian Government's National Environmental Research Program (NESP). Through its 10 research partners, the Hub established a network of research agencies, research-users and Indigenous communities to identify and priority needs and contribute to the national evidence-base required to support effective marine management. The focus was on Australian Marine Parks (AMPs), sustainable resource use, threatened and migratory species and coastal habitat restoration. Research across these themes was underpinned by the development of nationally consistent approaches designed to strengthen Australia’s marine research coordination and capability. Multi-agency surveys supported by the Hub established bathymetric and ecological baselines in tropical and temperate AMPs. They facilitated the development and application of national standards for data acquisition, sharing and visualisation, transforming the accessibility and utility of research findings for researchers and research-users. For waters beyond AMPs, the Hub consolidated existing knowledge and developed mapping and predictive tools to better understand natural values, pressures and risks. Shallow-reef biodiversity state and trends, wastewater discharges, and the effects of ship noise and vessel strikes on large marine animals were explored at a national scale. Hub research supported the recovery and conservation of threatened and migratory marine species including White Sharks, sea snakes, Southern Right Whales, inshore tropical dolphins and handfishes. A key product was The Action Plan for Australian Sharks and Rays 2021: a comprehensive and consistent review of the extinction risk of all Australian sharks, rays and chimaeras. Research in coastal habitat restoration included evaluating restoration practices and economics, and supporting platforms for knowledge sharing among policy makers, practitioners and communities. Several of the Hub’s regional projects partnered with Indigenous communities to identify and advance Indigenous research interests and priorities. This engagement and knowledge sharing contributed to empowering Indigenous people in land and sea research and management.

The Action Plan for Australian Sharks and Rays 2021: poster - PM Kyne (National Environmental Science Program Marine Biodiversity Hub, 2021)
This A3 poster presents a visual summary of International Union for Conservation of Nature (IUCN) Red List Categories applied to Australia's 328 species of sharks, rays and chimaeras by The Action Plan for Australian Sharks and Rays 2021. The assessments show that sharks and their relatives are faring better in Australia than in the rest of the world, with a relatively low level of threatened species. People who manage and conserve sharks can see which species most urgently need attention, and have a benchmark for measuring future changes in their status. Related information The Action Plan for Australian Sharks and Rays 2021 [publication] Threatened shark species ‘out of sight out of mind’: first complete national assessment of Australia’s sharks and rays [media release] The Action Plan for Australian Sharks and Rays [QA fact sheet] The Action Plan for Australian Sharks and Rays 2021 [video]
Keywords: chimaeras; EPBC Act; extinction risk; rays; sharks

The Action Plan For Australian Sharks and Rays: QA fact sheet - PM Kyne (National Environmental Science Programme Marine Biodiversity Hub, 2021)
This four-page fact sheet accompanies The Action Plan for Australian Sharks and Rays 2021. It provides contextual background for the action plan by addressing these five questions: What is the Action Plan for Australian Sharks and Rays 2021? Why do we need a shark action plan? Why was the IUCN Framework used to assess the extinction risk of sharks? How does the shark action plan deal with subpopulation structure? What other plans and assessmens exist for sharks in Australia and how do they differ from the shark action plan? Related information The Action Plan for Australian Sharks and Rays 2021 [publication] Threatened shark species ‘out of sight out of mind’: first complete national assessment of Australia’s sharks and rays [media release] The Action Plan for Australian Sharks and Rays 2021 [A3 summary poster] The Action Plan for Australian Sharks and Rays 2021 [video]
Keywords: chimaeras; EPBC Act; extinction risk; rays; sharks

An annotated checklist of the chondrichthyans of South Africa - David A. Ebert; Wintner, S.P.; PM Kyne (Zootaxa, 2021)
An annotated checklist of chondrichthyan fishes (sharks, batoids, and chimaeras) occurring in South African waters is presented. The checklist is the result of decades of research and on-going systematic revisions of the regional fauna. The chondrichthyan fauna of South Africa is one of the richest in the world with 191 species, comprising 50 families and 103 genera. It consists of 30 families, 64 genera, and 111 species of sharks; 17 families, 36 genera, and 72 species of batoids; and, 3 families, 5 genera, and 8 species of chimaeras. The most species-rich shark families are the whaler sharks Carcharhinidae with 20 species followed by the deepwater catsharks Pentanchidae with 13 species. The most speciesrich batoid families are the hardnose stakes Rajidae with at least 21 species followed by the stingrays Dasyatidae with 13 species. This monograph represents the first detailed annotated checklist of chondrichthyans from South Africa in over 30 years.
Keywords: Batoids; Biodiversity; chimaeras; sharks; Southeastern Atlantic Ocean; Western Indian Ocean

Arafura Marine Park Eco-narrative - Ronen Galaiduk; Scott L Nichol; Marcus Stowar; Jamie Colquhoun; Case, M.; Puotinen, ML; Conrad W. Speed; Z Huang; Karen J Miller (2021)
This eco-narrative forms an initial description of the physical and biological features of Arafura Marine Park, located north-east of Darwin. The marine park contains a gently sloping broad shelf that grades to a series of canyons that connect the shelf to the continental slope. Seabed mapping and biodiversity surveys were undertaken by the Marine Biodiversity Hub in November 2020. The survey targeted two areas: Money Shoal, a shallow reef habitat (10 – 60 m deep) that supports corals, sponges and a diverse fish community in clear waters; and Pillar Bank on the outer shelf (150 – 200 m deep) which is characterised by a complex seabed of large ridges, valleys and plains, with turbid waters, muddy seabed and a comparatively sparse seabed biota. The region is characterised by strong tidal flows and a connection to waters delivered by the regions mesoscale currents. Nutrient levels are relatively low across most of the park, with localised higher nutrient levels close to the coast.
Keywords: Australian Marine Parks; bathymetry; benthic; Biodiversity; Coral reef; demersal fish; marine heat wave; seabed

Arafura Marine Park: Post Survey Report - K Picard; Marcus Stowar; Roberts, N; Justy Siwabessy; M. Abdul-Wahab; Ronen Galaiduk; Karen J Miller; Scott L Nichol (2021)
This technical report presents preliminary results and observations of a seabed mapping and biodiversity survey of Arafura Marine Park within the North Marine Park network, undertaken in 2020 by the Australian Institute Marine Science and Geoscience Australia. The primary audience includes researchers and managers of the North Marine Parks and traditional owners of Sea Country in the Arafura Sea region. The objective of the survey was to collect field data to build baseline information by characterising benthic habitats in shelf waters of Arafura Marine Park that will support ongoing monitoring of the park. Bathymetry mapping and underwater imagery were collected in two areas of the park, Money Shoal on the inner continental shelf and Pillar Bank on the outer shelf. These data reveal that Money Shoal supports a diverse shallow water coral and demersal fish community as evidence for the conservation values of the marine park, and which suggest it is unique within its regional setting. Pillar Bank, in contrast, is clearly a different habitat, but is an extensive area within the park that supports benthic communities on hard substrate, albeit sparse in their distribution. Further analysis will be undertaken to quantify the abundance and diversity of these biological communities and to better understand the influence of environmental gradients across the marine park. These new data provide detailed insights into the distribution of sediment-dominated and hardground habitat within Arafura Marine Park, providing a baseline for the ongoing management of the benthic conservation values of this marine protected area.
Keywords: Australian Marine Park; bathymetry; benthic; Biodiversity; demersal fish; epifauna; seabed; tropical reef

Assessing the feasibility of restoring giant kelp forests in Tasmania - Final Report - Cayne Layton; Craig Johnson (2021)
This report examines whether warm water tolerant giant kelp (Macrocystis pyrifera) exists among remnant Tasmanian giant kelp habitat, and if so, assesses their use in restoration trials. Giant kelp forests were previously common in Tasmanian waters, but ~95% declines of giant kelp cover over recent decades led to Federal listing as an endangered community. This decline is related to changes in regional oceanography and ocean warming, and while restoration is one possible conservation approach, any intervention must consider these ongoing threats. Using spores from remnant giant kelp we established a collection of 48 unique kelp cultures or ‘family-lines’. Thermal tolerance experiments found ~10% of the family-lines showed significant warm water tolerance. These ‘super kelp’ were then used in restoration trials, with several hundred juvenile giant kelp now established at two field sites. This project has progressed selective breeding of kelp and innovative restoration interventions.
Keywords: climate change; kelp; Marine; restoration; warming

Assisting recovery of seagrass in Shark Bay, Gathaagudu - Final Report - John Statton; Elizabeth A Sinclair; McNeair, S; Kendrick, A; Gary A. Kendrick (2021)
This report outlines the findings of a collaborative project between University of Western Australia scientists and the Malgana Traditional Owners to assist recovery of seagrasses in Gathaagudu (Shark Bay) following the 2011 marine heat wave. It presents the results of field-based methods designed to assist seagrass restoration and the outcomes of these efforts for restoring ecosystem function of seagrasses. Furthermore, we provide a framework for planning future restoration activities, with step-by step examples. Suggestions are provided for the next steps in assisting people and seagrass ecosystems to heal sea country.
Keywords: connectivity; genetics; Genomics; restoration; seagrass; seedlings; seeds; Traditional Owners; transplants

Beagle Marine Park Post Survey Report: South-east Marine Parks Network - Neville Barrett; Jacquomo Monk; Scott L Nichol; Falster, G; Andrew Carroll; Justy P W Siwabessy; Deane, A; Nanson, R; K Picard; Dando, N; Hulls, J; Evans, H (2021)
This report presents preliminary results from a seabed mapping and biodiversity survey of Beagle Marine Park, undertaken in 2018 by the University of Tasmania, Geoscience Australia and University of Sydney Centre for Field Robotics. The primary audience includes researchers and marine park managers. Bathymetry mapping and seabed imagery reveals the area is dominated by soft sediments, with localised areas of low-profile reef, including rare examples of relict terrestrial dunes that formed when Bass Strait was a land bridge.  The reefs provide important habitat for sessile invertebrates, while adjacent soft sediment areas include scallop beds interspersed among coarse sand, with shell fragments and extensive fields of sediment bedforms. Demersal fish were abundant and diverse, but with few commercial or recreational target species. These new data provide insights into the distribution of seabed habitats and biota within Beagle Marine Park, and provides a baseline on its natural values.
Keywords: Australian Marine Park; bathymetry; benthic; Biodiversity; demersal fish; epifauna; seabed; temperate reef

Case Study for Great Barrier Reef Cumulative Impact Guidance: Whitsundays Plan of Management - Jeffrey M. Dambacher; Piers Dunstan (2021)
A case study for the Whitsundays Plan of Management assessed cumulative impacts for coral reef ecosystems in the GBR, and included reefs surrounding Hayman, Arkhurst, Langford, Black, Bird and Hook Isles. Assessed pressures included coral bleaching, cyclonic storms and COTS outbreaks; and impacts from boat anchor damage, recreational fishing, and fin damage from snorkelling and scuba diving. An ecosystem model represented the direct effects of pressures, with the model validated against observed responses of reef biota in the assessment area following Severe Tropical Cyclone Debbie in 2017. Model predictions found impacts from recreational use alone ranged from relatively low levels of likelihood where use and activity levels are most restricted, to relatively high where use and activities levels were greatest. The inclusion of climate change and COTS outbreaks dramatically increased the likelihood that reef values could be diminished throughout a majority of the area of assessment.
Keywords: climate change; cumulative impact; GBRMPA; recreational use

Characterising anthropogenic underwater noise to improve understanding and management of acoustic impacts to marine wildlife - David Peel; Christine Erbe; Joshua N. Smith; Miles Parsons; Alec Duncan; Schoeman, Renee P.; Mark Meekan (2021)
This report examines the noise contribution of vessel traffic in Australian waters, with pristine marine soundscapes (dominated by natural, biological and physical sound) found to remain, particularly near offshore reefs and islands. Strong wind noise dominates the southern Australian coast. Underwater shipping noise dominates areas along the eastern seaboard and northwest shelf close to shipping lanes. A case study of humpback whales found noise models useful to investigate exposure levels on species of interest. Certain small non-AIS equipped vessels within a given size class and design type displayed significant differences in estimated source levels. Under specific conditions (e.g. channels, speed restrictions), Passive Acoustic Monitoring can provide estimates of small-vessel numbers in shallow water and assist in validating modelled exposure levels experienced by fauna. However, confidence is limited when multiple boats are present or where vessel behaviours vary significantly.
Keywords: shipping noise; underwater noise

Conservation of handfishes and their habitats – Final Report 2020 - Jemina F. Stuart-Smith; T P Lynch; Felicity McEnnulty; Mark Green; C Devine; Trotter, Andrew; Tyson Bessell; Lincoln Wong; Paul Hale; Andrew Martini; Rick D Stuart-Smith; Neville Barrett (2021)
This final report covers conservation work for red and spotted handfishes during 2019-2020. For red handfish this includes monitoring of juveniles in the wild immediately after their release following captive-rearing. Juveniles were recorded on all three monitoring surveys post release, indicating initial success of this conservation strategy to bolster wild population numbers. This report includes investigation into sex-determination in adults using morphometrics and found a lack of clear separation between males and females, indicating that focus should be on other methods for non-destructive sex determination.  For spotted handfish this report includes population dynamics from 22 years of monitoring and found that within the Derwent estuary, both genomics and population dynamics suggest a well-structured population, with local populations acting in isolation from each other, or small groups. There had been an overall decline in the Derwent estuary’s Spotted handfish population.
Keywords: Conservation; threatened species

Conservation Status of Tropical Inshore Dolphins - Simon Allen (2021)
The status of tropical inshore dolphins is a literature review for policy makers. Australia’s tropical inshore waters are some of the least impacted by human activities on a global scale but also a hotspot for marine mammal extinction risk. Knowledge of dolphin distribution, abundance, trends, habitat use and population structure applies only to discrete areas for some species. Anthropogenic threats align with those ranked as the greatest to marine systems globally: habitat loss and degradation via coastal development; bycatch in fishing gear and shark nets; climate change, including ocean warming, acidification and extreme weather events. Assessing conservation status remains challenging without estimates of abundance in unsurveyed areas. Scenario modelling/sensitivity analysis of the number of mature individuals in the national ‘population’ of each species should be conducted. The integration of multiple data sources will inform conservation listings in the face of uncertainty.
Keywords: bottlenose; Conservation status; humpback; inshore tropical dolphins; scenario modelling; sensitivity analysis; snubfin; spinner; uncertainty

Designing a targeted monitoring program to support evidence-based management of Australian Marine Parks A pilot in the South-east Marine Park Network - Keith R. Hayes; Piers K Dunstan; Skipton N. C. Woolley; Neville Barrett; Howe, Steffan; Samson, C. R.; Bowling, R.; Ryan, M.P.; Scott D Foster; Jacquomo Monk; David Peel; Geoffrey R. Hosack; et al. (2021)
To inform the development of a Monitoring, Evaluation, Reporting and Improvement (MERI) framework for the Australian Marine Park (AMP) estate, the Marine Biodiversity Hub has led a collaborative project with Parks Australia to move from the scoping and planning stages of the adaptive management cycle to the do, evaluate, report and improve stages. This involved defining a common language across natural values, socio-economic and cultural benefits, anthropogenic pressures and key drivers. A vulnerability assessment was undertaken across the South-east marine region, with cumulative impacts providing the basis for a monitoring prioritisation in this region. Monitoring questions and high-level indicators were then developed for ecosystems identified as priorities, which were also informed by ecosystem conceptual models. This report documents the outcomes of this evaluation process, and provides the framework for applying this across other AMP network regions and the Coral Sea.
Keywords: Australian Marine Park monitoring

Determining effective acoustic array design for monitoring presence of white sharks Carcharodon carcharias in nearshore habitats - Gabriel, Sofia M.; T. A. Patterson; Eveson, J. P.; Semmens, J. M.; David Harasti; Butcher, P. A.; J. L. Y. Spaet; R. W. Bradford (Marine Biology, 2021)
Inferences regarding animal presence from passive acoustic receiver arrays are driven by the spatial confguration of receivers. Large, dense arrays provide more information, but maintenance of multiple receivers is costly. Confguring acoustic receiver arrays to maximise coverage while minimising cost is therefore paramount. This study used data from a dense acoustic receiver array within a white shark Carcharodon carcharias nursery area on the east coast of Australia to assess how detection data of tagged white sharks in the area was afected by reducing the array size. Receivers were sub-sampled post hoc by simple random sampling, clustered random sampling, and sampling of the top performing receivers. Using the top performing receivers, array size could be reduced by 60% (10 out of 25 receivers) while still detecting a median of 100% of white sharks detected with the full array. With random and clustered sampling methods, a 40% reduction in array size (15 out of 25 receivers) detected a median of 100% of sharks. Reducing the array size by 60% using the top performing receivers resulted in a 35% decrease in the median number of detections per visit of the tagged sharks (67 out of 102.5 detections). In comparison, reducing the array by the same amount with random and clustered sampling methods resulted in a 57% decrease (44 out of 102.5 detections). The post hoc sampling methods used in this study are an empirical approach for optimising placement of limited receiver resources with broad application for establishing cost-efective monitoring.
Keywords: acoustic array; white shark

Distribution and habitat suitability of Threatened and Migratory Marine Species in Northern Australia - Vinay Udyawer; Michele Thums; Ferreira, L; Tulloch, V; PM Kyne (2021)
The North Marine Bioregion is home to a diversity of threatened and data-poor marine species. In the absence of critical data on species’ distributions, population connectivity, and essential habitat, decision-making to progress the current ‘Developing the North’ agenda has the potential to negatively impact Matters of National Environmental Significance. Data compiled across multiple sources were used to model and map the distribution of 16 priority Threatened and Migratory marine species. The objective of the project was to improve the current data-poor species distribution maps held by DAWE to assist with policy decisions for these species. We used a spatial distribution modelling approach based on presence data for these species from 121 spatial datasets and associated, remotely sensed environmental variables. The output is a series of distribution maps to enhance decision-makers’ ability to assess potential impacts of development proposals in Northern Australia under the EPBC Act.
Keywords: habitat association; species distributions; threatened species

An eco-narrative of South-west Corner Marine Park - Capes region - Tim J. Langlois; Jacquomo Monk; A. Giraldo Ospina; Brooke Gibbons; Sims, H; Zhi Huang; Scott L Nichol; Neville Barrett (2021)
This report is part of a series of eco-narrative documents that synthesize our existing knowledge of Australia’s individual Marine Parks. This series is a product of the National Environmental Science Program Marine Biodiversity Hub Project D3, which seeks to determine the status of marine biodiversity assets on the continental shelf to inform monitoring of Australian Marine Parks. The South-west Corner Marine Park contains large areas of high biodiversity and benthic productivity, although most of the Marine Park still remains to be surveyed. The Park is defined by extensive plains across the continental shelf covered by mixed communities of macroalgae, seagrasses and sponges. Since these plains cover ~95% of the surveyed area, such communities account for a large proportion of benthic productivity and biodiversity in the region. Black and octocorals, hydroids and bryozoans are present in deeper areas of the continental shelf, while areas deeper than 120 m are mostly formed by soft sediments. A total of 140 fish species across 61 families were identified in the Marine Park, including several shark species and other commercially targeted species. The Park is also habitat for numerous seabirds and migratory passage for several cetacean species.
Keywords: fish; macroalgae; seagrasses; sharks; South-west Corner Marine Park; sponges

An eco-narrative of the Gascoyne Marine Park, North-west marine region - Alix Post; Rachel Przeslawski; Z Huang; Smith, Deb; Kirkendale, Lisa; Wilson, Nerida (2021)
This report is one in a series of eco-narratives that synthesise our existing knowledge of Australian Marine Parks. Eco-narratives are intended to enable managers and practitioners to rapidly ascertain the ecological characteristics of each park, and to highlight knowledge gaps for future research focus. Gascoyne Marine Park is dominated by two submarine canyons that incise the continental slope of the western Australian margin and provide some degree of connectivity between the continental shelf and abyssal plain. The park is characterised by a range of benthic environments, including near-vertical cliffs of exposed bedrock in the canyons, and sediment covered slopes on the continental slope that grade to abyssal plains that occupy the greater proportion of the park.
Keywords: Arafura Marine Park Survey

Effects of human footprint and biophysical factors on body-size structure of fished marine species - Bosch, Nestor E.; Monk, Jacquomo; Goetze, Jordan; Wilson, Shaun; Babcock, Russell C.; Neville Barrett; Clough, Jock; ‐Randall, Leanne M.; Fairclough, David V.; Fisher, Rebecca; Gibbons, Brooke A.; David Harasti; et al. (Conservation Biology, 2021)
Marine fisheries in coastal ecosystems in many areas of the world have historically removed large-bodied individuals, potentially impairing ecosystem functioning and the long-term sustainability of fish populations. Reporting on size-based indicators that link to foodweb structure can contribute to ecosystem-based management, but the application of these indicators over large (cross-ecosystem) geographical scales has been limited to either fisheries-dependent catch data or diver-based methods restricted to shallow waters (<20 m) that can misrepresent the abundance of large-bodied fished species. We obtained data on the body-size structure of 82 recreationally or commercially targeted marine demersal teleosts from 2904 deployments of baited remote underwater stereo-video (stereo-BRUV). Sampling was at up to 50 m depth and covered approximately 10,000 km of the continental shelf of Australia. Seascape relief, water depth, and human gravity (i.e., a proxy of human impacts) were the strongest predictors of the probability of occurrence of large fishes and the abundance of fishes above the minimum legal size of capture. No-take marine reserves had a positive effect on the abundance of fishes above legal size, although the effect varied across species groups. In contrast, sublegal fishes were best predicted by gradients in sea surface temperature (mean and variance). In areas of low human impact, large fishes were about three times more likely to be encountered and fishes of legal size were approximately five times more abundant. For conspicuous species groups with contrasting habitat, environmental, and biogeographic affinities, abundance of legal-size fishes typically declined as human impact increased. Our large-scale quantitative analyses highlight the combined importance of seascape complexity, regions with low human footprint, and no-take marine reserves in protecting large-bodied fishes across a broad range of species and ecosystem configurations.
Keywords: baited remote underwater stereo-video (stereo-BRUV); fish body size; Marine Park; MPA

Effects of Ignoring Survey Design Information for Data Reuse - Foster, Scott D.; Vanhatalo, Jarno; Trenkel, Verena M.; Schulz, Torsti; Lawrence, Emma; Przeslawksi, Rachel; Hosack, G.R. (Journal of Applied Ecology, 2021)
Data are currently being used, and reused, in ecological research at an unprecedented rate. To ensure appropriate reuse however, we need to ask the question: “Are aggregated databases currently providing the right information to enable effective and unbiased reuse?” We investigate this question, with a focus on designs that purposefully favor the selection of sampling locations (upweighting the probability of selection of some locations). These designs are common and examples are those designs that have uneven inclusion probabilities or are stratified. We perform a simulation experiment by creating data sets with progressively more uneven inclusion probabilities and examine the resulting estimates of the average number of individuals per unit area (density). The effect of ignoring the survey design can be profound, with biases of up to 250% in density estimates when naive analytical methods are used. This density estimation bias is not reduced by adding more data. Fortunately, the estimation bias can be mitigated by using an appropriate estimator or an appropriate model that incorporates the design information. These are only available however, when essential information about the survey design is available: the sample location selection process (e.g., inclusion probabilities), and/or covariates used in their specification. The results suggest that such information must be stored and served with the data to support meaningful inference and data reuse.
Keywords: accessible; Bias; data; database; findable; Horvitz-Thompson estimator; inclusion probability; interoperable; model; population density estimate; reusable data; reuse; Survey design

Enhancement, connectivity and interoperability of spatial portals - Tim J. Langlois; Brooke Gibbons; Jacquomo Monk (2021)
Map-based portals are increasingly being recognised for their use in marine science communication, with enhancement, connectivity and interoperability of data between map-based portals a key challenge. This report outlines the results of consultations with data experts on a pathway for map-based portals to adopt Open Geospatial Consortium (OGC) and ISO compliant standards to enable the discovery of raw data, summarised and curated data products. A case study using the GlobalArchive.org platform is presented using the ‘FishNClips’ and ‘Visualiser’ tools. This report provides a pathway for the future enhancement, connectivity and interoperability of map-based portals to meet standards to enable the discovery of data and communication products such as interactive imagery and data visualisations.
Keywords: fish and shark video surveys; map-based portals; science communication

Estimation of population abundance and mixing of southern right whales in Australian and New Zealand regions - Karen Evans; Claire Charlton; Andy Townsend; Mandy Watson; Emma Carroll; Mike Double; Judy Upston; Kris Carlyon; Rachael Alderman (2021)
This report provides an overview of key photo-identification datasets of southern right whales and evaluation of their population dynamics and connectivity/structuring in Australian waters. This includes evaluating progress on national Conservation Management Plan targets in Australian waters and prioritising conservation efforts at the state level. Overall, sightings data of individuals supports current understanding of habitat use and migration pathways of two sub-populations within Australia. Analysis of population trends show that while the south-west sub-population continues to increase, there are signs of a slowing recovery rate, with a potential emerging cyclical pattern of years of low sightings of females with calves. The opportunistic data from the south-east region and inability to account for varying effort on sightings currently limits robust population trend estimation either at the sub-population or national scales. Several recommendations are provided for further work.
Keywords: Australian Right Whale Photo Identification Catalogue; population parameters; Population trends; Southern right whale; spatial connectivity

Fly-through of the Arafura Marine Park - Scott L Nichol; Warouw, D.; Marcus Stowar; Kim Picard; Justy Siwabessy; Roberts, J.; M. Abdul-Wahab (2021)
Link to Fly-through =>  Fly-through of the Arafura Marine Park 2020 This fly-through video explores the seabed environments within Arafura Marine Park, offshore northern Australia. In November 2020, Geoscience Australia and the Australian Institute of Marine Science completed a voyage to map and characterise two areas of the park, Money Shoal and Pillar Bank.  Money Shoal is a shallow carbonate reef within the southern part of the park that supports a diverse range of corals and an abundant fish community, including reef sharks and grouper. In contrast, Pillar Bank is in deeper water (150 – 200 m) on the outer shelf and is characterised by sparse benthic communities of filter feeders on local rock outcrop and a relatively low diversity of fish. Funding for the survey was provided by the Australian Government’s National Environmental Science Program Marine Biodiversity Hub, with co-investment by GA and AIMS. Further information: https://www.nespmarine.edu.au/document/arafura-marine-park-post-survey-report and https://northwestatlas.org/nwa/money-shoal
Keywords: Australian Marine Park; bathymetry; benthic; Biodiversity; demersal fish; epifauna; seabed; tropical reef

Fly-through of the Gascoyne Marine Park - Geoscience Australia (2021)
This flythrough combines bathymetry with high-resolution imagery to highlight canyon environments within the Gascoyne Marine Park located offshore northwestern Australia. The Cape Range Canyon is a relatively narrow, linear canyon that initiates on the continental slope, but is connected to the shelf via a narrow channel. The walls of the canyon are steep and reveal a history of slumping and retrogressive failure, that have broadened the canyon over time. The floor contains a series of deep plunge pools, indicative of the action of sediment-laden turbidity currents in further eroding this canyon. Epibenthos within the canyons was relatively sparse and likely regulated by disturbance associated with sedimentation in the canyons. Rock overhangs often supported the highest densities of benthic suspension feeders, including glass sponges, octocorals and ascidians. Link to video:    Seafloor Bathymetry of the Gascoyne Marine Park
Keywords: Australian Marine Park; flythrough; multibeam; ROV

Genetic diversity and restricted genetic connectivity in an endangered marine fish (Brachionichthys hirsutus) provides a model for conservation management in related and data-deficient species - Sharon A Appleyard; T P Lynch; Mark Green; Encinas-Viso, Francisco (Marine and Freshwater Research, 2021)
Determining the genetic diversity and differentiation among populations is a critical element of conservation biology, but for many aquatic, data-deficient species with small population sizes, this is not possible. Closely related species may therefore provide a model. For the first time, using over 4000 single-nucleotide polymorphism loci, we characterise the population genetic diversity and structure of one of the world’s rarest marine fish, the spotted handfish (Brachionichthys hirsutus), a species which is also a member of the most threatened marine bony fish family (Brachionichthyidae). Fin clips were taken from 170 live spotted handfish across seven disjunct sites within the only known estuary (in Tasmania, Australia) where multiple populations of the species are found. Spatially discrete populations clustered into three genetic groupings and a significant variance in allele frequencies among populations (overall FST = 0.043), even at the small scale of the estuary, was observed. Furthermore, low contemporary migration rate estimates suggest low genetic homogeneity between locations. Because of the low genetic connectivity, population clusters of spotted handfish within the estuary should be considered as separate conservation management units. This insight should be considered for management and conservation strategies of other data-deficient and threatened species in the family.
Keywords: Population structure; SNP; Spotted handfish; threatened species

Ghosts of the Ocean – biodiversity, fisheries, and extinction risk ghost sharks - Finucci, Brittany; Cheok, Jessica; David A. Ebert; Herman, Katelyn B.; PM Kyne; N K Dulvy (Fish and Fisheries, 2021)
Ghost sharks (subclass Holocephali) remain a largely data-poor group of cartilaginous fishes. The general paucity of attention may partially be related to identification and unresolved taxonomic issues, occurrence in the deep oceans, and their low value and interest in fisheries (which some notable exceptions). Here, we synthesize and assess the extinction risk of all known extant ghost sharks (52 species) by applying the IUCN Red List of Threatened Species Categories and Criteria. Ghost sharks have a low proportion of threatened (8%) and Near Threatened (8%) species, with most species (69%) assessed as Least Concern. The group still exhibits some data deficiency (15%), and biological information is lacking for most species. Endemism is high, with 37% of species known from only one location or one country. Species richness was highest in the Northeast Atlantic, off the northwest coast of Africa (Morocco to Mauritania), the East China Sea, New Zealand and off the northwest coast of South America (Ecuador and Peru). Ghost sharks are predominately taken as by-catch, but some targeted fishing and/or retention for the liver oil trade occurs. Species-specific reporting, monitoring and management are required to assess population trends, and further investigation is needed on trade and use, particularly for higher risk species including the sicklefin chimaeras (genus Neoharriotta) and the American Elephantfish (Callorhynchus callorhynchus, Callorhinidae).

Habitat loss and range shifts contribute to ecological generalisation amongst reef fishes - Rick D Stuart-Smith; Camille Mellin; Amanda E. Bates; Graham J. Edgar (Nature Ecology & Evolution, 2021)
Human activities are altering the structure of ecological communities, often favouring generalists over specialists. For reef fishes, increasingly degraded habitats and climate-driven range shifts may independently augment generalization, particularly if fishes with least-specific habitat requirements are more likely to shift geographic ranges to track their thermal niche. Using a unique global dataset on temperate and tropical reef fishes and habitat composition, we calculated a species generalization index that empirically estimates the habitat niche breadth of each fish species. We then applied the species generalization index to evaluate potential impacts of habitat loss and range shifts across large scales, on coral and rocky reefs. Our analyses revealed consistent habitat-induced shifts in community structure that favoured generalist fishes following regional coral mortality events and between adjacent sea urchin barrens and kelp habitats. Analysis of the distribution of tropical fishes also identified the species generalization index as the most important trait in predicting their poleward range extent, more so than body or range size. Generalist tropical reef fishes penetrate further into subtropical and temperate zones than specialists. Dynamic responses of reef fishes to habitat degradation imply loss of specialists at local scales, while generalists will be broadly favoured under intensifying anthropogenic pressures. An increased focus on individual requirements of specialists could provide useful guidance for species threat assessments and conservation actions, while ecosystem and multi-species fisheries models should recognize increasing prevalence of generalists.
Keywords: citizen science; climate change; Coral reefs; kelp forests; Reef life survey

Half a century of global decline in oceanic sharks and rays - Pacoureau, Nathan; Cassandra L. Rigby; PM Kyne; Sherley, Richard B.; Winker, Henning; John K. Carlson; Sonja V. Fordham; Barreto, Rodrigo; Fernando, Daniel; Malcolm P. Francis; Rima W. Jabado; Herman, Katelyn B.; et al. (Nature, 2021)
Overfshing is the primary cause of marine defaunation, yet declines in and increasing extinction risks of individual species are difcult to measure, particularly for the largest predators found in the high seas. Here we calculate two well-established indicators to track progress towards Aichi Biodiversity Targets and Sustainable Development Goals: the Living Planet Index (a measure of changes in abundance aggregated from 57 abundance time-series datasets for 18 oceanic shark and ray species) and the Red List Index (a measure of change in extinction risk calculated for all 31 oceanic species of sharks and rays). We fnd that, since 1970, the global abundance of oceanic sharks and rays has declined by 71% owing to an 18-fold increase in relative fshing pressure. This depletion has increased the global extinction risk to the point at which three-quarters of the species comprising this functionally important assemblage are threatened with extinction. Strict prohibitions and precautionary science-based catch limits are urgently needed to avert population collapse, avoid the disruption of ecological functions and promote species recovery.
Keywords: extinction risk; IUCN Red List; pelagic fishes; rays; sharks

High Level Summary of Technical Report describing Guidelines for analysis of cumulative impacts and risks to the Great Barrier Reef for Environmental Standards, DAWE. - Piers K Dunstan; Jeffrey M Dambacher (2021)
The high level summary summarises the key points in the Guidelines for cumulative impact assessment for Environmental Standards, DAWE, and links to the key policy documents supporting cumulative impact assessment. It also provides examples of practical steps that describe the potential necessary data and methods to complete a cumulative impact assessment within a standard risk assessment framework.
Keywords: cumulative impact assessment

High Level Summary of Technical Report describing Guidelines for analysis of cumulative impacts and risks to the Great Barrier Reef for GBRMPA. - Piers K Dunstan; Jeffrey M Dambacher (2021)
The high level summary summarises the key points in the Guidelines for cumulative impact assessment for GBRMPA and links to the key policy documents supporting cumulative impact assessment. It also provides examples of practical steps that describe the potential necessary data and methods to complete a cumulative impact assessment within a standard risk assessment framework.
Keywords: cumulative impact assessment

Increased connectivity and depth improve the effectiveness of marine reserves - Jordan S. Goetze; Shaun Wilson; Ben Radford; Fisher, Rebecca; Tim J. Langlois; Jacquomo Monk; Nathan A. Knott; Hamish A. Malcolm; Leanne M. Currey Randall; Ierodiaconou, Daniel; David Harasti; Neville Barrett; et al. (Global Change Biology, 2021)
Marine reserves are a key tool for the conservation of marine biodiversity, yet only ~2.5% of the world's oceans are protected. The integration of marine reserves into connected networks representing all habitats has been encouraged by international agreements, yet the benefits of this design has not been tested empirically. Australia has one of the largest systems of marine reserves, providing a rare opportunity to assess how connectivity influences conservation success. An Australia-wide dataset was collected using baited remote underwater video systems deployed across a depth range from 0 to 100 m to assess the effectiveness of marine reserves for protecting teleosts subject to commercial and recreational fishing. A meta-analytical comparison of 73 fished species within 91 marine reserves found that, on average, marine reserves had 28% greater abundance and 53% greater biomass of fished species compared to adjacent areas open to fishing. However, benefits of protection were not observed across all reserves (heterogeneity), so full subsets generalized additive modelling was used to consider factors that influence marine reserve effectiveness, including distance-based and ecological metrics of connectivity among reserves. Our results suggest that increased connectivity and depth improve the aforementioned marine reserve benefits and that these factors should be considered to optimize such benefits over time. We provide important guidance on factors to consider when implementing marine reserves for the purpose of increasing the abundance and size of fished species, given the expected increase in coverage globally. We show that marine reserves that are highly protected (no-take) and designed to optimize connectivity, size and depth range can provide an effective conservation strategy for fished species in temperate and tropical waters within an overarching marine biodiversity conservation framework.
Keywords: fished species; marine parks; meta-analysis; no-take marine reserve; stereo-BRUV

Initial baseline survey of deepwater fish in the Ningaloo Marine Park (Commonwealth waters) - John Keesing; Anthea Donovan; Simon Collings; Tim J. Langlois; Emma Lawrence; Russell Babcock (2021)
This technical report is likely to be of interest to policy makers, managers, researchers and the general public. The Ningaloo Marine Park (NMP) is one of the few commonwealth marine parks readily accessible to large numbers of recreational fishers in small vessels. This project aimed to determine the composition and abundance of fish, especially those targeted by recreational fishers in deeper areas of the NMP including the National Park Zone (NPZ) at Point Cloates. Fish species composition, abundance and size composition were studied using baited remote underwater stereo-videos. The study recorded a total of 169 fish species. Recreationally targeted fish were more abundant with increasing distance from boat ramps, even allowing for the fact that water depth increases with distance from shore. The relatively remote location of the NPZ off Point Cloates explains why there are generally more fish within the NPZ than more easily accessible areas of the NMP. The report recommends follow-up surveys every 3 years, to allow comparisons between fished and unfished given that this study has provided a baseline near to the time of the establishment of the NPZ.
Keywords: baited remote video; fish; Ningaloo Marine Park; recreational fishing

It Often Howls More Than It Chugs: Wind versus Ship Noise Underwater in Australia’s Maritime Regions - Christine Erbe; Schoeman, Renee P.; David Peel; Joshua N. Smith (Journal of Marine Science and Engineering, 2021)
Marine soundscapes consist of cumulative contributions by diverse sources of sound grouped into: physical (e.g., wind), biological (e.g., fish), and anthropogenic (e.g., shipping)—each with unique spatial, temporal, and frequency characteristics. In terms of anthropophony, shipping has been found to be the greatest (ubiquitous and continuous) contributor of low-frequency underwater noise in several northern hemisphere soundscapes. Our aim was to develop a model for ship noise in Australian waters, which could be used by industry and government to manage marine zones, their usage, stressors, and potential impacts. We also modelled wind noise under water to provide context to the contribution of ship noise. The models were validated with underwater recordings from 25 sites. As expected, there was good congruence when shipping or wind were the dominant sources. However, there was less agreement when other anthropogenic or biological sources were present (i.e., primarily marine seismic surveying and whales). Off Australia, pristine marine soundscapes (based on the dominance of natural, biological and physical sound) remain, in particular, near offshore reefs and islands. Strong wind noise dominates along the southern Australian coast. Underwater shipping noise dominates only in certain areas, along the eastern seaboard and on the northwest shelf, close to shipping lanes.
Keywords: Australian EEZ; fish chorus; marine soundscape; ship noise; whale song; wind noise

Life history of the Critically Endangered largetooth sawfish: a compilation of data for population assessment and demographic modelling - PM Kyne; Oetinger, M; Michael I. Grant; Pierre Feutry (Endangered Species Research, 2021)
The largetooth sawfish Pristis pristis is a Critically Endangered, once widespread shark-like ray. The species is now extinct or severely depleted in many former parts of its range and is protected in some other range states where populations persist. The likelihood of collecting substantial new biological information is now low. Here, we review all available life history information on size, age and growth, reproductive biology, and demography as a resource for population assessment and demographic modelling. We also revisit a subset of historical data from the 1970s to examine the maternal size−litter size relationship. All available information on life history is derived from the Indo-West Pacific (i.e. northern Australia) and the Western Atlantic (i.e. Lake Nicaragua-Río San Juan system in Central America) subpopulations. P. pristis reaches a maximum size of at least 705 cm total length (TL), size-at-birth is 72−90 cm TL, female size-at-maturity is reached by 300 cm TL, male size-at-maturity is 280−300 cm TL, age-at-maturity is 8−10 yr, longevity is 30−36 yr, litter size range is 1−20 (mean of 7.3 in Lake Nicaragua), and reproductive periodicity is suspected to be biennial in Lake Nicaragua (Western Atlantic) but annual in Australia (Indo-West Pacific). There was a weak relationship between litter size and maternal size in Lake Nicaragua, and lifetime reproductive output for an individual female from Lake Nicaragua was estimated as 73 pups. Future demographic models should aim to capture the variability and uncertainty in life history parameters for P. pristis and we encourage a conservative approach to any application for conservation and management.
Keywords: age and growth; Demography; Pristis pristis; reproductive biology; threatened species

Map-Based Portals for Marine Science Communication and Discovery - Report from July 2019 Workshop - Tim J. Langlois; Jacquomo Monk; Vanessa Lucieer; Brooke Gibbons (2021)
Map-based portals are important to ensure current, relevant and reliable marine ecological data is readily available to a wide-range of users and stakeholders. This report describes the outcomes of a Marine Biodiversity Hub workshop held in July 2019 that hosted a discussion on “Map Based Portals for Marine Science Communication and Discovery”. Sixteen existing map-based web portals were presented and discussed with a range of end users to review and learn from the national experience. The users requirements were captured through the narrative of “User stories”, which provided useful information of explanations of the different portal features. We mapped the synergies between existing services, and using the “The Marine Data Landscape” presented at the workshop identified a variety of gaps, and captured new suggestions for future developments, including an assessment on the priority and feasibility of these new initiatives. Recommendations are provided to progress portal development.
Keywords: portal; science communication; spatial data management

Marine Acoustic Zones of Australia - Christine Erbe; David Peel; Joshua N. Smith; Schoeman, Renee P. (Journal of Marine Science and Engineering, 2021)
Underwater sound is modelled and mapped for purposes ranging from localised environmental impact assessments of individual offshore developments to large-scale marine spatial planning. As the area to be modelled increases, so does the computational effort. The effort is more easily handled if broken down into smaller regions that could be modelled separately and their results merged. The goal of our study was to split the Australian maritime Exclusive Economic Zone (EEZ) into a set of smaller acoustic zones, whereby each zone is characterised by a set of environmental parameters that vary more across than within zones. The environmental parameters chosen reflect the hydroacoustic (e.g., water column sound speed profile), geoacoustic (e.g., sound speeds and absorption coefficients for compressional and shear waves), and bathymetric (i.e., seafloor depth and slope) parameters that directly affect the way in which sound propagates. We present a multivariate Gaussian mixture model, modified to handle input vectors (sound speed profiles) of variable length, and fitted by an expectation-maximization algorithm, that clustered the environmental parameters into 20 maritime acoustic zones corresponding to 28 geographically separated locations. Mean zone parameters and shape files are available for download. The zones may be used to map, for example, underwater sound from commercial shipping within the entire Australian EEZ.
Keywords: acoustic zone; Australian EEZ; multivariate mixture model; ship noise; sound propagation modelling; underwater noise

Marine and coastal restoration database - Jemma Purandare; Ian M. McLeod; De Sousa De Saboya, R; Le Port, A; Boström-Einarsson, L.; Reeves, S; Van Kampen, P; MacCreadie, P; Carnell, P; Wartman, M.; Eger, A; Bayraktarov, E (2021)
The Australian Coastal Restoration Network (ACRN) restoration projects database compiles data from numerous coastal and marine restoration projects located in Australia and New Zealand. As a first version, the data was obtained from publicly available data sources and publications, and from organisations that are conducting restoration projects on corals, mangroves, saltmarsh, seagrass, kelp and shellfish reefs. The ACRN Database is an evolving tool that will be periodically updated with new projects and outputs as they are submitted. Version 1 of the database represents the final deliverable for the NESP Marine Biodiversity Hub Project E5 'The role of restoration in conserving matters of national environmental significance'. Link to database:         www.acrn.org.au/database
Keywords: coastal ecosystems; restoration; database; australia; new zealand

MBHdesign: an R-package for efficient spatial survey designs - Scott D Foster (Methods in Ecology and Evolution, 2021)
A considered survey design will generate data that are representative of the population that the sample is taken from. All good design takes is a little thought, some information and some good software tools. Spatially balanced randomisation with unequal inclusion probabilities is a modern and efficient design method. These designs are embedded within sampling theory and should be easy to generate. The R-package MBHdesign allows field researchers easy access to these designs. It implements point-based and transect-based methods and allows for the incorporation of legacy sites. The functionality of the package is illustrated with example designs in an environmentally heterogeneous region.
Keywords: field sampling; monitoring (community ecology); monitoring (disease ecology); sampling; surveys

Molecular analysis of newly-discovered geographic range of the threatened river shark Glyphis glyphis reveals distinct populations - PM Kyne; Christy Davies; Floriaan Devloo-Delva; Grant Johnson; Yolarnie Amepou; Michael I. Grant; Aaran Green; R. Gunasekera; Alistair V Harry; Theresa Lemon; Rob Lindsay; Travis Maloney; et al. (2021)
This technical report is aimed at providing policy makers, fisheries managers, and conservation agencies with information on the population structure of a threatened shark of northern Australia, the Speartooth Shark. The identification of population boundaries is key to determining the appropriate spatial scale for the conservation and management of wildlife. The major river drainages (Wenlock River, Alligator Rivers, Adelaide River) comprising the species’ known range have been shown previously to be distinct genetic populations. Recent surveys have revealed a wider range than previously documented with newly-identified populations in the Daly River of the Northern Territory and the Ord River of Western Australia as well as the species’ rediscovery in Papua New Guinea (PNG). Here we aimed to test the hypothesis that the newly identified rivers (Daly and Ord Rivers), along with the Kikori River in southern PNG, also represent distinct populations given their isolation from known populations. The analysis revealed that the Ord and Kikori Rivers represent distinct populations. Results from the Daly River also suggest that this is a distinct population, although sample size was small and power limited to infer statistical significance. Each river system within the range of the Speartooth Shark should be treated as a separate management unit.
Keywords: connectivity; DArTseq; euryhaline; mitogenomics; Population structure; Speartooth shark

Money Shoal, Arafura Marine Park: An eco-narrative - Puotinen, ML; Ronen Galaiduk; Scott L Nichol; Marcus Stowar; Colquhoun, J.; Case, M.; Speed, C.; Z Huang; Karen J Miller (2021)
This online article is a summary of one in a series of eco-narrative documents that synthesise our existing knowledge of Australian Marine Parks. Eco-narratives are intended to enable managers and researchers to ascertain the ecological characteristics of each park, and highlight knowledge gaps for future research focus. The information in this eco-narrative forms an initial characterisation of the physical, oceanographic and biological character of Arafura Marine Park, with a focus on results from a biodiversity and mapping survey undertaken by the NESP Marine Biodiversity Hub in 2020. This survey targeted two areas in the marine park: Money Shoal as an example of shallow coral reef habitat, and Pillar Bank as an example of a deeper water mixed seabed environments. This article focuses on survey results from Money Shoal. Link to article: www.northwestatlas.org/nwa/money-shoal
Keywords: Australian Marine Park; bathymetry; benthic; Biodiversity; demersal fish; epifauna; seabed; tropical reef

Monitoring Population Dynamics of ‘Western’ Right Whales off Southern Australia 2018-2021; Final Report on activities for 2020 - Joshua N. Smith; Diana Jones; Kenny Travouillon; Natalie Kelly; M C Double; John Bannister (2021)
This is a technical report on the results from the 2021 aerial survey of southern right whales off southern Australia, specifically aimed at researchers and policy makers within the government. Collection of these data is a ‘high priority’ in the Australian EPBC Act Recovery Plan (Conservation Management Plan 2011-2021) to assess the current status of this threatened species and assess the effectiveness of federal and state management approaches that aim to facilitate this species’ recovery and range expansion. The whale count data from 2021 shows a significant decrease in overall sightings that has not been observed for over 13 years when compared to long term trend data for the population; last seen in 2007 (N = 286 individuals). The subsequent population estimate for the Australian ‘western’ subpopulation is 2,585 whales, which is also a significant decrease in estimated population size from 3,164 in 2019. The extremely low number of unaccompanied adults (N = 68) had the greatest impact on the overall number of sightings in 2020, and is the lowest number sighted since 1993 (N = 47). Previous surveys in 2007 and 2015 have been noted as years of low whale counts that had been deemed anomalous years, although the low numbers from this survey questions this and may suggest the 3-year female breeding cycle is becoming more unpredictable. Considerable inter-annual variation in whale numbers, and cycles in population growth, severely inhibits our ability to identify immediate threats to the population and strongly supports continued annual population surveys.
Keywords: aerial surveys; photographic identification; Southern right whale

NESP Marine Biodiversity Hub Final Report (2015-2021) - Jordan, A; Hedge, P; Gracie, S; Bryony Bennett (2021)
Since July 2015, the NESP Marine Biodiversity Hub has provided evidence and tools to help the Australian Government, state governments, Indigenous communities, industry and the community to better understand, manage and conserve Australia’s marine environment. The Hub research partners have worked closely with the Department to align their co-investment towards key management and policy priorities, and have established enduring partnerships to deliver fit-for-purpose scientific advice and tailored outputs to meet the needs of research end-users. The final year of the Hub research program, delivered through Research Plan Version 6 (2020), presented the Hub’s researchers challenges that required them to adapt and respond to travel restrictions associated with COVID-19, and manage program level risks associated with delayed milestones. With a total of 29 active research projects in 2020, delayed milestones extending into 2021 were spread across a number of projects, and the Hub executive worked closely with the project leaders and end-users to ensure the needs of decision makers were met. Highlights during 2020 include leading and supporting Australian Marine Park (AMP) seabed mapping and biodiversity surveys and analysis covering the Hunter, Lord Howe, Ningaloo, Arafura, Wessels, Beagle, Gascoyne and South-west Corner Marine Parks. These surveys extended the Hubs program of inventory and baselines, with large areas of high-resolution multibeam sonar surveys of the seafloor allowing detailed bathymetric mapping. Biotic data on benthic assemblages and fish surveyed using stereo camera systems on Autonomous Underwaters Vehicles, Remotely Operated Vehicles, towed systems and baited cameras has provided a raft of new insights into patterns of marine habitats and biodiversity around the country and across large depth ranges in Australia’s extensive marine estate. These surveys have applied the Hub's Field Manuals for Marine Sampling to Monitor Australian Waters, version 2, which are endorsed by experienced researchers, managers and technicians from multiple agencies. The field manuals are a critical requirement for nationally coordinated marine research and monitoring, and are used by Parks Australia as part of approving scientific sampling in marine parks. Much of this work has also contributed to projects supporting the development of the AMP Monitoring, Evaluation, Reporting and Improvement System, which has also incorporated mapping of pressures and evaluation of risks to natural values, and common approaches to evaluate social and economic values associated with AMPs. All of this work has been built on effective collaboration between researchers and marine park managers, and has raised the bar for achievements with co-designed and co-delivered practical research for Australian Marine Parks. An important focus for much of the work of the Hub has been to support the recovery and conservation of a number of threatened and migratory marine species. Projects have aimed to strengthen Australia’s capacity to effectively meet the requirements of regional, national, and international conservation policies. One of the Hub’s key products soon to be published is “The Action Plan for Australian Sharks and Rays 2021” for Australian cartilaginous fishes, which provides a comprehensive and consistent review of the extinction risk of all Australian sharks, rays, and chimaeras. This publication provides a benchmark from which changes in population and risk can be measured; and to help guide management for their conservation. The Action Plan also serves to raise the profile of their diversity and conservation needs. Another area of important development over the life of the Hub relates to coastal habitat restoration where research investment is generating national research capacity and a better evidence base to target and accelerate restoration research in Australia. Our work with stakeholders and research users, in particular through the Australian Coastal Restoration Network, is forging nationally coordinated approaches to the repair of shellfish reefs and saltmarshes, and testing methods for enhancing recovery and survival of temperate seagrasses and giant kelp forests. This includes evaluating restoration practices and economics, working with traditional owners, and supporting platforms for knowledge sharing among policy makers, practitioners and communities. Cutting across these research areas the Hub has progressively increased Indigenous engagement and partnerships to deliver a broad range of regionally focused projects to identify and advance Indigenous research interests and priorities. This work has contributed to empowering Indigenous people in land and sea research and management, including championing partnerships with Indigenous organisations and the Australian Marine Science Association (AMSA) to convene four annual Indigenous engagement workshops. These were designed to showcase collaborative projects and share information and perspectives on Indigenous Sea Country rights and aspirations, successful research partnerships, and the importance of culturally appropriate engagement based on accepted standards. The first part of a fifth Indigenous workshop was held at the AMSA 2021 annual conference in June, with the second part of the workshop delayed due to re-introduced COVID-19 restrictions prior to the conference. It is to be rescheduled for late 2021. Other key Hub successes includes a substantial contribution to national environmental reporting within the 2016 and 2021 national State of the Environment (SoE) reports in relation to data quality and standards; providing datasets, case studies, analyses and better use of existing quantitative data. This continues to build confidence in the reporting process and product, and increases its influence and value to end-users, stakeholders and the broader community. Effective collaboration and capacity development both within the existing Hub and across the broader science community in general, made possible by co-investment in NESP, has been a key factor in the success of the current Hub. This has enhanced the national capacity for marine science (meeting a number of National Marine Science Plan priorities), and also enabled cross-discipline collaborations to enhance regional capability by skill-sharing and postgraduate training opportunities. It has also enabled collaborative data analysis, storage and visualisation tools developed with significant Hub input (e.g. AusSeabed, AMP Science Atlas). Hub members have also had considerable, and growing, multidisciplinary expertise in collaborations with Indigenous communities.  All of these aspects are essential to maintain and further develop the capacity, investment and partnerships to ensure management of marine ecosystems and resulting community benefits are based on the best available science. The Marine Biodiversity Hub has made an important contribution to achieving this goal. The Hub has effectively managed the financial aspects of the program, with research partner matching co-investment consistently meeting program requirements, and appropriate investment made across areas of communications, knowledge brokering and data management.  It is anticipated that there will be a small underspend, and specific details of this will be provided in the final financial statement. Overall, research conducted within Marine Biodiversity Hub programs has provided foundational scientific evidence for biodiversity conservation and sustainable use in Australia’s marine environment, and partnerships and processes established by the Hub will continue to serve the needs of end-users engaged in emerging initiatives and protecting conservation priorities.

NESP Marine Biodiversity Hub Interim Report (2020) - Alan Jordan; Paul Hedge; Sarah Gracie (2021)
Letter from the Hub Leader (Dr Alan Jordan) Despite the challenges faced during the first half of 2020 associated with COVID-19 restrictions, Hub researchers have adapted to the current circumstances and maintained a busy schedule to deliver on project milestones and maintain a steady stream of outputs and end-user engagement. The Hub Executive have continued to focus on implementing Research Plan Version 6 (2020) (including synthesis projects), managing program level risks, and completing the interim progress report. The re-designed Marine Biodiversity Hub website was made live in May in order to make research outputs, stories and links to data and imagery more accessible to research-users and stakeholders (https://www.nespmarine.edu.au/). It includes landing pages for Australian Marine Parks and World Heritage Areas, threatened and migratory marine species, restoring coastal habitat, Indigenous engagement and science for sustainable use. One of the Hub’s key products, the Shark Action Plan (to be published in October 2020), aims to provide a comprehensive and consistent review of the extinction risk of all Australian cartilaginous fishes (Class Chondrichthyes: sharks, rays, and chimaeras); provide a benchmark from which changes in population and risk can be measured; and to help guide management for their conservation. The Shark Action Plan also serves to raise the profile of their diversity and conservation needs. The Hub has continued to progress its focus on marine restoration, recognising it as an important option for climate mitigation and adaptation. An ‘Australian Coastal Habitat Restoration’ webinar was held with Department of Agriculture, Water and Environment (DAWE) end-users in June led by Dr Ian McLeod from JCU and Dr Piers Dunstan from CSIRO. Presentations were provided on the following topics: UN Decade of Ecological Restoration 2021-30, progress with restoring giant kelp in waters off South-east Tasmania and seagrass in Shark Bay, advances with rebuilding shellfish reefs, costs and benefits of agricultural land conversion to coastal wetlands, return on investment for blue restoration projects, and the role of restoration for matters of national environmental significance. The presentations (these are available on the Hub’s website) and the question and answer session that followed generated a shared understanding among the 40 attendees about advances, challenges and opportunities with coastal and marine habitat restoration in Australia and oversees. Extending the Hub’s earlier work to develop national field standards, Version 2 of the Field Manuals for Marine Sampling to Monitor Australian Waters was released in July 2020. The manuals aim to ensure that data collected by marine sampling platforms at different times and places across Australia are directly comparable. The manuals are accessible through the website at: https://marine-sampling-field-manual.github.io. Major changes to the entire field manual package for Version 2 include amalgamation of the original Version 1 multibeam manual with the Australian Multibeam Guidelines from AusSeabed and the inclusion of a new manual for data collection with remotely operated underwater vehicles. There are 26 active Hub research projects, with 35% of 2020 milestones completed. Around 25% of the 2020 milestones have been flagged as amber because they have not been delivered on the date specified in the research plan. One milestone has been flagged as red (A10 – spotted handfish) signifying it will not be delivered, noting other arrangements have been made to redirect funds (see attachment A for further details). Delayed milestones are spread across 16 projects (A8, A11, A13, A14, A15, C1, C4, D2, D3, D4, D5, D6, E1, E2, E3, and E7). Milestone delays for most of these projects are minor in nature and not anticipated to have a material impact on research-users. Delays or risks of not delivering milestones for remaining projects have been examined closely to ensure milestones/deliverables are effectively reviewed/refined/approved due to the effects of COVID-19 (projects A10 - spotted handfish, A12 - field work and molecular sequencing in labs, A15 - review of conservation status of tropical inshore dolphins, D3 - SW Corner survey and Arafura survey, and D6 - social-economic benchmarks for AMPs), or because of extended delays with milestone delivery (C1 - state/territory fisheries data summaries, and E2 - underwater noise map). These delays have been discussed with the relevant research end-users and extensions for the following two projects have already been approved by DAWE; project A13 to complete Southern Right Whale population estimates, and project D3 to complete Australian Marine Park surveys. Requests for extensions for the remaining four projects are included in Attachment A, they are; project A11 to complete the Shark Action Plan, project A15 to review the conservation status of tropical inshore dolphins, project C1 to deliver output for state and territory fisheries data, and project D6 to complete boat ramps surveys. Additional project oversight has been commenced for projects D3 and E2, including ongoing formal meetings with project leaders and DAWE representatives where relevant. The Research Leadership Team have moved from monthly to fortnightly meetings for the rest of the Hub in order to manage the increase in oversight required for all projects during the final year. In relation to Hub finances, the Hub remains on track to ensure all NESP funds are spent or committed by 30 June 2021 and is monitoring the budget regularly to identify potential savings for reallocation. This includes some savings in administration and research facilitation budgets due to travel savings in 2020. Savings are expected to be within the Hub category limits of 10% of budget or $50,000. The commitment to support an Indigenous Workshop at the Australian Marine Science Association 2020 conference has been carried-over to the 2021 conference which is scheduled to be held in Sydney in June. All partners have been informed that project funds held at partner organisations must be spent by 31 Dec 2020, with the only exception being for projects where DAWE have approved an extension to the project end date beyond December 2020. The following points have also been communicated with partners: • All partners will be required to report grant funds spent, cash and in-kind contributed by project for 2020 activity as usual, due on 21st February 2021. • For those projects with approved extensions to 2021, there’ll be an additional acquittal required covering 2021 activity due 22 April 2021. • In addition, the Hub will require whole of life acquittals for each project covering grant funding received, cash and in-kind contributed. In relation to end of Hub reporting and communications, it is anticipated that a Hub glossy final report on projects, outcomes and outputs will be produced by June 2021, and aims to be shorter than previous Marine Biodiversity Hub final reports, reflecting the publication of the Hub Impact Report in September 2020. The Hub is regularly reviewing and updating its approach to knowledge brokering and communication, and will continue to develop opportunities for producing non-technical communication material, Hub showcase webinars, media stories and end-user engagement.

Overfishing and habitat loss drives range contraction of iconic marine fishes to near extinction - Yan, Helen F.; PM Kyne; Rima W. Jabado; Leeney, Ruth H.; L N K Davidson; Derrick, Danielle H.; Finucci, Brittany; Robert Freckleton; Sonja V. Fordham; N K Dulvy (Science Advances, 2021)
Extinctions on land are often inferred from sparse sightings over time, but this technique is ill-suited for wide-ranging species. We develop a space-for-time approach to track the spatial contraction and drivers of decline of sawfishes. These iconic and endangered shark-like rays were once found in warm, coastal waters of 90 nations and are now presumed extinct in more than half (n = 46). Using dynamic geography theory, we predict that sawfishes are gone from at least nine additional nations. Overfishing and habitat loss have reduced spatial occupancy, leading to local extinctions in 55 of the 90 nations, which equates to 58.7% of their historical distribution. Retention bans and habitat protections are urgently necessary to secure a future for sawfishes and similar species.
Keywords: Conservation status; critically endangered; doomed; Endangered; Extinction; Sawfish; threats

Papua New Guinea: A potential refuge for threatened Indo–Pacific river sharks and sawfishes - Grant, Michael I.; White, William T.; Amepou, Yolarnie; Appleyard, Sharon A.; Baje, Leontine; Floriaan Devloo-Delva; Pierre Feutry; Ibana, Dotty; Jogo, Dick J.; Jogo, Stanley; PM Kyne; Mana, Ralph; et al. (Frontiers in Conservation Science, 2021)
The conservation of threatened elasmobranchs in tropical regions is challenging due to high local reliance on aquatic and marine resources. Due primarily to fishing pressure, river sharks (Glyphis) and sawfishes (Pristidae) have experienced large population declines in the Indo-Pacific. Papua New Guinea (PNG) may offer a refuge for these species, as human population density is low, and river shark and sawfish populations are thought to persist. However, few data are available on these species in PNG, and risk posed by small-scale fishers is poorly understood. This study observed elasmobranch catches in small-scale fisheries in riverine and coastal environments in the East Sepik (northern region), Gulf, and Western Provinces (southern region) of PNG. Surveys were conducted over a period of weeks to months in each region, during the dry season across seven field trips from 2017 to 2020. We observed a total of 783 elasmobranchs encompassing 38 species from 10 families. River sharks made up 29.4% of observations in the southern region, while sawfishes made up 14.8 and 20.3% in the northern and southern regions, respectively. River sharks were commonly caught by small-scale fishers in lower riverine environments in southern PNG, while sawfishes were generally less common and mainly observed through dried rostra. The primary threat to river shark and sawfish populations is their capture by small-scale fishers targeting teleosts for swim bladder. Persisting populations of river sharks and sawfishes indicate that PNG is the second known nation with viable populations of multiple species in the Indo-Pacific. However, populations are declining or at high risk of decline, and fisheries management and conservation are required to realize the potential of PNG as a long-term refuge.
Keywords: Glyphis; Pristidae; riverine; small-scale fisheries; swim bladder; threatened species

Pinpointing drivers of extirpation in sea snakes: a synthesis of evidence from Ashmore Reef - Somaweera, Ruchira; Vinay Udyawer; Guinea, Michael L.; Daniela Ceccarelli; Clarke, Rohan H.; Glover, Michelle; Hourston, Mathew; Keesing, John; Rasmussen, Arne Redsted; Sanders, Kate; Shine, Richard; Thomson, Damian P.; et al. (Frontiers in Marine Science, 2021)
Over the past decade, vertebrate populations globally have experienced significant declines in distribution and abundance. Understanding the reasons behind these population declines is the first step in implementing appropriate management responses to improve conservation outcomes. Uncovering drivers of extirpation events after the fact, however, requires a careful forensic approach to prevent similar declines elsewhere. The once abundant and species-rich sea snake fauna of Ashmore Reef Marine Park, in the Timor Sea, collapsed dramatically in the early 2000s. No such decline has occurred on surrounding reefs. We synthesise the evidence for this collapse and the subsequent slow recovery and evaluate the plausibility of potential drivers for the declines, as well as provide evidence against certain explanations that have been proposed in the past. Our systematic review shows that of seven possible hypotheses considered, at least three are credible and require additional information: (1) stochastic environmental events may have increased the snakes’ susceptibility to pathogens, (2) a resurgence in the abundance of top predators may have induced a localised change in trophic structure, and (3) an acute increase in local boat traffic may have had negative physical impacts. One or more of these factors, possibly acting in combination with as yet other unidentified factors, is the most plausible explanation for the precipitous decline in sea snake populations observed. Based on this position, we identify future research directions with a focus on addressing critical gaps in knowledge to inform and prioritise future management actions.
Keywords: apex predator; Extinction; hydrophiids; pathogen; shark; species decline; trophic cascade

Population structure of Narrow Sawfish (Anoxypristis cuspidata) across northern Australia - Pierre Feutry; Adrianne Laird; Christy-Louise Davies; Floriaan Devloo-Delva; Gary Fry; Grant Johnson; Rasanthi M Gunasekara; James Marthick; PM Kyne (2021)
This report is aimed at fishery and threatened species managers, and industry. Defining management units is critical for the globally Endangered Narrow Sawfish Anoxypristis cuspidate, and genomic approaches were used to analyse the species population structure across northern Australia. Samples were obtained from bycatch of commercial fisheries in collaboration with the Northern Prawn Fishery. Barriers to gene flow were evident between all regions where there were more than three samples, demonstrating female philopatric behaviour at finer spatial scales than previously suspected. In contrast, no evidence of population structure was detected using nuclear markers, suggesting male-biased dispersal. Sampling of neonates in nursery areas would help characterise the species philopatric behaviour. Results indicate that each region should be treated as a discrete management unit, with risk of population depletion if local bycatch mortality was to exceed the species biological productivity.
Keywords: connectivity; DArTseq; dispersal trawling; mitogenomics; Philopatry; sex-biased

Potential of electric fields to reduce bycatch of highly threatened sawfishes - K Abrantes; Barnett, A; Soetaert, M; PM Kyne; Adrianne Laird; Squire, L; Seymour, J; Wueringer, BE; Sleeman, J; Charlie Huveneers (Endangered Species Research, 2021)
Sawfishes are among the most threatened families of marine fishes and are susceptible to incidental capture in net fisheries. Since bycatch reduction devices currently used in trawl fisheries are not effective at reducing sawfish catches, new methods to minimise sawfish bycatch are needed. Ideally, these should affect sawfish behaviour and prevent contact with the fishing gear. We tested the effects of electric fields on sawfish behaviour to assess the potential of electric pulses in mitigating sawfish bycatch. Experiments were conducted in a tank where 2 electrodes were suspended in the water column, connected to a pulse generator, and placed across the swimming path of sawfish. Two largetooth sawfish Pristis pristis were tested in control conditions, in the presence of a baseline pulse, and of 5 variations of that pulse where 1 parameter (polarity, voltage, frequency, pulse shape, pulse duration) was altered at a time. Conditional inference trees were used to identify the effects of various parameters (e.g. treatment, individual) on reaction type, re action distance, twitching presence and duration, and inter-approach times. Sawfish reacted to electric fields, but reaction distances were small (typically <1.2 m), and no field tested consistently led to reactions conducive to escaping from moving nets. The following parameters induced the most response in both individuals: bipolar current, rectangular shaped, 5−10 Hz, ~1500 μs duration, and 100 V. We recommend further research focussing on moving nets, testing a V-shaped electric array preceding the net mouth by at least 5 m, and testing a setup similar to electrotrawling.
Keywords: Bycatch reduction devices; Electric repellents; Prawn fisheries; Pristis pristis; Sawfish; Trawl fisheries

Preliminary river outfalls assessment - Qurratu A. Rohmana; Andrew M Fischer; John Gemmill; Ian Wright (2021)
This report provides a preliminary data analysis of the river outfalls around the Hawkesbury-Nepean coastal catchment areas located in central NSW, and ranks them according to the total flow volume and nutrient load to determine the potential health and environmental impact.  The main targeted audiences are decision makers, water authorities and general public.  The key points of this report are 1) higher nutrient discharged is mainly in the lower catchment areas, 2) larger capacity Waste Water Treatment Plants (WWTP's) discharge the highest nutrients load into the catchment areas, 3) inconsistency within the datasets which makes the analysis difficult to conclude the extent of nutrient impacts in the inland river.  Improved Australia-wide inland outfalls monitoring is needed to identify the extent outfalls impact on water quality and riverine ecosystems.  A standardised format of dataset is required to help researchers and stakeholders to assess water quality data of WWTP outfalls.
Keywords: effluent; marine environment; outfalls; river

Progress towards a nationally integrated benthic biodiversity monitoring program for Australia’s marine realm - Neville Barrett; Jacquomo Monk (2021)
This report provides an overview of key Australian benthic biodiversity monitoring programs and datasets able to be utilised nationally to form the background to broader integrated programs for reporting on the State of the marine environment and similar end-user needs. It includes an overview of the associated databases, that together with the background programs, provide a suitable framework for establishing and supporting a nationally-integrated monitoring program. It will inform future decisions on how to best further develop the tools and programs. The report identified significant progress in benthic surveys in recent years, including development of appropriate, open-access databases. A key limitation for many programs is the lack of adequate support for access to cost-effective coastal research vessels with the capability of deploying scientific equipment or supporting remote operations. There is also a need for greater levels of integration between the agencies.
Keywords: auv; benthic biodiversity; BRUV; integrated monitoring; marine databases; national programs; NMSC; UVC

Quality control and interoperability of fish annotation data - Tim J. Langlois; Brooke Gibbons; Jacquomo Monk; Vanessa Lucieer (2021)
This report presents a case study of how to improve the quality control and interoperability of marine spatial data, and focuses on the quality control of fish and shark annotations from baited remote underwater stereo-video (stereo-BRUV) imagery. The GlobalArchive-CheckEM service conducts a series of quality control checks on annotation data against life-history information, based on the Codes for Australian Aquatic Biota (CAAB). This report provides a ‘how-to guide’ for CheckEM and we propose that, in addition to review by expert fish ecologists, any fish and shark image annotations collected in Australia should be validated using CheckEM. Data validation, quality control and interoperability of spatial data are key to enable data discovery and re-use for biodiversity reporting and science communication. This report outlines how Findable Accessible Interoperable Reproducible (FAIR) aspects of marine data can be improved and implemented at a national scale.
Keywords: baited remote underwater stereo-video; fish; sharks; stereo-BRUV

Seagrass science inspires Malgana artist - Elizabeth A Sinclair; Oxenham, Tiahna; Wolfgang Lewandrowski (For people and plants : Friends of Kings Park quarterly magazine, 2021)
Gathaagudu (two waters), also known as Shark Bay, is the traditional country of Malgana peoples. It is also home to expansive seagrass (wirriya jalyanu) meadows. This article, published in Issue 114 of the Friends of King's Park magazine For People and Plants, takes you on a high-resolution journey to the surface of seagrass leaves and the individual cells giving life and colour within them. Exploring the anatomical structures of seagrasses (and comparative works with eucalypt species) provides inspiration for environmental science student and emerging Malgana artist, Tiahna Oxenham. In keeping with cultural heritage protocols, art works are created from plant material collected on Malgana Country, keeping her connection to country alive.
Keywords: seagrass; Shark Bay Malgana Indigenous Community

Seagrass (wirriya jalyanu): giving life to sea country of Shark Bay (Gathaagudu) - Fact sheet 2021 - Elizabeth A Sinclair (Marine Biodiversity Hub, 2021)
Researchers at The University of Western Australia (UWA) are working with the Malgana Aboriginal Corporation and rangers to assist the natural recovery of seagrasses affected by an extreme marine heatwave at Shark Bay. The widespread loss of seagrass resulting from the 2010/2011 marine heatwave caused declines in many species, including those of cultural significance. These include green sea turtles  (buyungurra), dugong (wuthuga), shags (wanamalu) and bottlenose dolphins (irrabuga). Malgana Rangers and scientists have participated in four training workshops to develop and trial simple, cost-effective methods to assist the recovery of seagrass. The methods use adult plants, seeds and seedlings, depending on the species. Measuring the success of a restoration project takes time. However, seaweeds and algae are starting to grow on seagrass transplants, tropical seagrasses are colonising the surrounding bare sand, and fish and invertebrates are starting to use the new habitat.
Keywords: coastal restoration; Gathaagudu; Indigenous engagement; Malgana Rangers; seagrasses; Shark Bay

Seamounts Survey Voyage Report (2021)
The ‘Huon’ and ‘Tasman Fracture’ areas off southern Tasmania contain seamounts that support unique deep-sea coral reefs, which are part the Australian Marine Park network. This report presents findings of the RV Investigator voyage V06. The surveys aimed to determine the extent of deep-sea coral communities in and adjacent to the Huon and Tasman Fracture parks, and quantify changes in the communities on these seamounts since 1997 and 2007. The survey also sampled the St. Helens Seamount in north-east Tasmania which was previously surveyed in 2008. The study found that coral reefs extend from seamounts onto adjacent rocky areas, and also occur on small areas on the continental shelf edge, expanding their previously known distribution. The results will provide important data on recovery and resilience to bottom trawling on deep sea coral communities and improve our understanding of the dynamics of deep-sea communities. The Marine Biodiversity Hub provided scientific leadership and communication support for this voyage. Link to Investigator Post Voyage Report => INV 2018_06 Voyage Summary Link to Voyage Blogs => Blogging the Seamounts 23 Nov - 19 Dec 2018

Social and economic benchmarks of the Australian Marine Parks - Matt Navarro; Tim J. Langlois; M Burton; A Hegarty; Aston, C; Kragt, M.E; Rogers, A (2021)
We present a national social and economic benchmark for the Australian Marine Parks (AMPs), focussing on four key groups: the general public, recreational fishers, non-extractive recreational users, and charter operators. Establishing this benchmark involved conducting four integrated surveys nationally reaching approximately 4,000 respondents. The AMP benchmarks established here are amongst the most comprehensive globally in terms of the spatial extent and stakeholder groups considered. Overall, the surveys highlight the substantial values associated with the AMPs, and generally positive perceptions and attitudes towards the parks. The surveys also highlight potential areas for survey improvement, and data was collected to help address these (e.g. preferred modes of contact). The information is intended to inform management of the AMPs in ways that align with the preferences of stakeholders and the broader community.
Keywords: Attitudes; Australian Marine Parks; Awareness; Marine Park; marine protected area; no-take marine reserve; non-market valuation; Socio-economics

South-west Corner Marine Park Post Survey Report - Tim J. Langlois; Jacquomo Monk; A. Giraldo Ospina; Brooke Gibbons; Adams K.; Neville Barrett; Sims, H.; Aero Lepastrier; Boyd, M.; Justy Siwabessy; Scott L Nichol (2021)
The South-west Corner Marine Park survey used standardised methods to characterise seabed habitats and fish populations to support the ongoing monitoring of the marine park. Several small isolated high-profile reefs exist in depths of ~30-50 m in the south-east of the National Park Zone, with the majority of mid-shelf habitat consisting of flat pavement reefs interspersed with sand sediments. Both reef types supported diverse assemblages of macroalgae, seagrass, soft corals and sponges. Further offshore, ledge features at ~100 m depth support diverse filter feeders dominated by hard bryozoans, hydroids, black and octocorals and sponges. Dense filter feeding assemblages on the edge of the shelf break down to 250 m depth were populated by aggregations of hapuka (Polyprion oxygeneios). A potential aggregation site for grey nurse sharks (Carcharias taurus) within the National Park Zone was also found. Additional image annotation and analysis aims to provide further details on assemblages.
Keywords: grey nurse shark; hapuka; kelp; seagrass; sponges

A standardised national assessment of the state of coral and rocky reef biodiversity - Camille Mellin; Graham J. Edgar; Emslie, Michael J.; Neville Barrett; Turak, E.; Gilmour, J.; Rick D Stuart-Smith (2021)
This technical report summarises three sets of data analysis based on monitoring of shallow reef biodiversity around the entire Australian continent. It is relevant to policy makers, managers and the research community. Key findings include a very clear impact of climate change on Australian reefs in the form of changing compositions of reef fishes and coral communities, and declines in some populations of temperate mobile invertebrates and tropical reef fishes. Relevant components have already been reported to the State of the Environment team in a national reefs case study and contributions to other relevant assessments. Follow up work using these results will be relevant to the Australian Government (e.g. with respect to threatened species and Australian Marine Parks) and the Great Barrier Reef Marine Park Authority. Improved models are required to quantify the relative impact of gradual warming and marine heatwaves on coral and rocky reef ecosystems.
Keywords: AIMS long-term monitoring; Australian Temperate Reef Collaboration; indicators; Reef life survey; reefs; State of the Environment

Towards a national standard and guidelines for reporting wastewater treatment plant outfall data - John Gemmill; Andrew M Fischer; Qurratu A. Rohmana (2021)
This report primarily targets water authorities and state/territory-based environmental protection agencies. It provides a pathway forward for establishing a national standard for reporting outfall wastewater treatment plant data. Key findings from our survey of water treatment authorities (WTAs) are:  (1) the majority of WTAs agreed on participating in further discussions to develop standards, (2) WTAs supported the concept of annual reporting used for the National Outfall Database (NOD), and (3) WTAs are willing to collaborate to develop outfall report cards. The pathway forward is to establish a consultative process with key stakeholders to develop and implement the second phase of the NOD. Establishing a network of key stakeholders in the national wastewater sector will be important for developing a national reporting standard.
Keywords: environment; Marine; National Outfall Database; policy; reporting standard

Underwater noise signatures of ships in Australian waters - Christine Erbe; Alec Duncan; David Peel; Joshua N. Smith (2021)
The National Environmental Science Program's Marine Biodiversity Hub supported a project to quantify underwater noise from ships in Australian waters, with the ultimate goal of guiding the assessment and management of noise impacts on marine fauna. As part of this project, ship noise was recorded and archival recordings of ships from the Integrated Marine Observing System (IMOS) acoustic observatories were analysed to build a catalogue of ship noise signatures in Australian waters. These signatures will then be used to inform a spatial model of ship noise around Australia. This technical report will be of interest to researchers working on ship noise, and presents the field recordings and the methodology developed for computing ship source spectra and source levels. The results of applying the software to recordings from an initial set of five IMOS deployments spanning a total of 1463 days are presented.

Wirriya Jalyanu Seagrass Festival - celebrating Malgana language, art and science of Shark Bay's Seagrass Ecosystems - Elizabeth A Sinclair (2021)
This article about the Wirriya Jalyanu Seagrass Festival was published online in the April 2021 edition of the Shark Bay CRC online publication Inscription Post. Seagrass is an important element of the Shark Bay World Heritage Site. The Wirriya Jalyanu Festival promoted connections through learning about the seagrass ecosystem. Activities at the Festival included science, archaeology, cooking, art, dance, land management, and Malgana language.  Science talks provided a context for the Festival events. Three invited speakers presented passionately about their research. UWA’s Prof Gary Kendrick spoke about seagrass ecosystems: the foundation of Shark Bay’s fragile marine environment and the impacts of heat waves. Malgana woman and artist Bianca McNeair spoke about turtle tagging fieldwork with Malgana women on Wirruwanna (Dirk Hartog Island), and UWA researcher Dr Ana Sequeira spoke about tracking the movements of turtles and dugong.
Keywords: seagrass; Shark Bay; Shark Bay Malgana Indigenous Community; Shark Bay world heritage area

Acoustic characteristics of small research vessels - Miles Parsons; Mark Meekan (Journal of Marine Science and Engineering, 2020)
Vessel noise is an acute and chronic stressor of a wide variety of marine fauna. Understanding, modelling and mitigating the impacts of this pollutant requires quantification of acoustic signatures for various vessel classes for input into propagation models and at present there is a paucity of such data for small vessels (<25 m). Our study provides this information for three small vessels (<6 m length and 30, 90 and 180 hp engines). The closest point of approach was recorded at various ranges across a flat, ≈10 m deep sandy lagoon, for multiple passes at multiple speeds (≈5, 10, 20, 30 km h−1 ) by each vessel at Lizard Island, Great Barrier Reef, Australia. Radiated noise levels (RNLs) and environment-affected source levels (ASLs) determined by linear regression were estimated for each vessel and speed. From the slowest to fastest speeds, median RNLs ranged between 153.4 and 166.1 dB re 1 µPa m, whereas ASLs ranged from 146.7 to 160.0 dB re 1 µPa m. One-third octave band-level RNLs are provided for each vessel–speed scenario, together with their interpolated received levels with range. Our study provides data on source spectra of small vessels to assist in understanding and modelling of acoustic exposure experienced by marine fauna.
Keywords: monopole source levels; propagation loss; radiated noise levels; vessel noise

Baseline genomic data collection and assisting natural recovery of seagrass meadows - John Statton; Elizabeth A Sinclair; Kendrick, A; McNeair, S; Gary A. Kendrick (2020)
The goal of NESP Project E6 is to work alongside the Malgana Traditional Owners to assist recovery of the dominant seagrasses, Amphibolis antarctica and Posidonia australis following the 2011 marine heat wave.  Therefore, this project has been developed and implemented with consultation and collaboration between UWA scientists and the Malgana people. Collectively, we have established strong lines of communication and coordinated processes for conducting field work, organising and implementing workshops, engaging in ecological and restoration training exercises and practice, as well as brainstorming and organising upcoming community events, including the seagrass festival to be held in April 2021 in Denham, Shark Bay.  Our project successfully (i) developed baseline restoration genetic diversity and connectivity data of the two impacted seagrasses which was used to select plants and sites for restoration, and (ii) by incorporating the baseline genetic information, assisted the natural recovery of seagrass meadows through the collection of reproductive and vegetative propagules for on-ground restoration activities within selected sites.
Keywords: Biodiversity; Carbon; Genomics; Malgana; restoration; seagrass; Shark Bay

Charting two centuries of transformation in a coastal social-ecological system: A mixed methods approach - Ruth Thurstan; Ben K Diggles; Chris L Gillies; Strong, Michael K.; Kerkhove, Ray; Buckley, Sarah M.; King, Robert A.; Smythe, Vince; Gideon Heller-Wagner; Weeks, Rebecca; Palin, Fred; Ian M. McLeod (Global Environmental Change, 2020)
Oyster reef ecosystems used to form significant components of many temperate and subtropical inshore coastal systems but have suffered declines globally, with a concurrent loss of services. The early timing of many of these changes makes it difficult to determine restoration targets which consider interdecadal timeframes, community values and shifted baselines. On the Australian continent, however, the transition from Indigenous (Aboriginal) to Westernized resource use and management occurred relatively recently, allowing us to map social-ecological changes in detail. In this study, we reconstruct the transformations in the Sydney rock oyster (Saccostrea glomerata) wild commercial industry of central and southeast Queensland, and by extension its reef ecosystems, as well as the changing societal and cultural values related to the presence and use of the rock oyster through time.
Keywords: Cultural history; Environmental history; Historical ecology; Moreton Bay; oyster; Shifting baseline syndrome

Conservation impact scores identify shortfalls in demonstrating benefits of threatened wildlife displays in zoos and aquaria - K. A. Buckley; L. D. G. Smith; D. A. Crook; Richard D. Pillans; PM Kyne (2020)
Zoos and public aquaria globally display numerous wild harvested, threatened species. To validate conservation credentials, displays are often associated with research projects, educational interpretation, or conservation-related activities. However, accompanying conservation benefits are rarely assessed. In this study, an approach to evaluate conservation benefits of captive wildlife experiences is modelled by assessing four Australian aquarium displays of the Critically Endangered largetooth sawfish Pristis pristis. Conservation impact scores were calculated for research, education, and conservation-related activities. In a novel approach, sawfish-related education (gaining knowledge, changing attitudes, and intentions to change behaviours) was evaluated using a before and after study design (n¼2 229), and conservation impact scores were calculated using effect sizes. Although visitors to all aquariums demonstrated significant positive attitudinal changes, and at one site gained knowledge, no significant change in behavioural intentions were detected. Educational messages addressing attitudes and behaviours were mostly generalised and untargeted. Formative and ongoing evaluations are needed to develop and maintain targeted and relevant messages. With one exception, research projects and conservation activities were unlikely to contribute substantially to sawfish conservation due to limited support from the aquaria. We recommend that increased support is directed to projects that are targeted towards impactful conservation goals.
Keywords: Aquarium; education; Largetooth sawfish; Pristis pristis; threatened species

Conservation of handfish and their habitats – Annual Report 2019 - T P Lynch; Sharon A Appleyard; Lincoln Wong; Andrew Martini; Tyson Bessell; Jemina F. Stuart-Smith; Leah Soo; Stefanie Faber; C Devine; Lauren Hardiman (2020)
We have completed and analysed performance assessment surveys at nine local population sites for spotted handfish in the Derwent estuary from 2015-2019. To this time series we have also incorporated historic data for individual sites back to 1998. Local populations generally show stability of occurrence but with some difference in abundance (as measured by estimates of fish densities per habitat) by years.
Keywords: artificial spawning habitat; Conservation; DNA; environmentally sensitive mooring; handfish; survey

A cross continental scale comparison of Australian offshore charter boat and tournament recreational fisheries research and its applications to Marine Park and fisheries management - T P Lynch; C B Smallwood; Joel Williams; F Ochwada-Doyle; C Devine (2020)
Recreational fisheries are complex at many levels. One specific area of complexity is reporting on various components of the sector. Alongside state-wide surveys of the general shore- and boat-based recreational fishery, two other components, the charter boat (tour operator) fishery and the tournament game fishery are assessed through logbook returns in some jurisdictions. The functionality of these returns was investigated for their potential use by Australian Marine Parks (AMPs) and the Australian Fisheries Management Authority (AFMA), with Western Australia (WA) and New South Wales (NSW) used as case studies.
Keywords: Australian Marine Park monitoring; charter boat fishing; recreational fishing; surveys; tournament game fishery

Data Discoverability and Accessibility: Report from July 2019 Workshop on Marine Imagery - Rachel Przeslawski; Neville Barrett; Narissa Bax; Andrew Carroll; Scott D Foster; Michelle R. Heupel; Jan Jansen; Tim J. Langlois; Tim Moltmann; Pocklington, Jacqui B.; Rick D Stuart-Smith; Wyatt, Mathew (2020)
There are increasing incentives for marine researchers to share their data, but the will of the marine community to share data has often not yet caught up with our capabilities. Marine imagery and associated annotation, for example, can be collected and analysed with various gear and digital platforms, and there is a large body of legacy imagery and an increasing rate of image collection due to technological advances. As the volume of marine imagery grows, so has the need to establish a national workflow for making it discoverable and accessible. To meet this need, a series of workshops on data discoverability and accessibility were coordinated by the NESP Marine Hub in 2018 and 2019. This report focuses on the Marine Imagery Discoverability & Accessibility Workshop II held on 25 July 2019 at CSIRO, Hobart. The overarching aim of the 2019 marine imagery workshop was to 1) assess the progress made in the past year regarding the discoverability and accessibility of marine imagery and 2) to refine the 2018 recommendations to specify priority, feasibility, and responsibility. The workshop included a range of presentations, activities, and discussions designed to shift participants’ thinking to end users, rather than their own perspectives based on their roles in the marine imagery pipeline. Workshop participants identified the top five barriers to making marine imagery discoverable and accessible: Limited institutional support or long-term funding for some digital platforms, Lack of a centralised image and annotation repository or tracking system to ensure FAIR (findable, accessible, interoperable, reusable) data, No governance or oversight for the entire marine imagery community, Bottlenecks during processing, imagery upload, and annotation in digital platforms, Limited communication between major Australian marine imagery groups. For each of the challenges, a set of revised recommendations and actions was developed. The highest-priority actions were to 1) establish a governance body or oversight group to provide broad strategic direction as related to the general marine science community, and 2) establish an ongoing marine imagery node to develop a national workflow to ensure the discoverability and accessibility of marine imagery (i.e. progress the actions listed in the current report). All other recommendations listed in this report are underpinned by the establishment, operation, and collaboration between an oversight group and an implementation group. Importantly, marine imagery and annotation are means to an end, and the primary focus needs to be on understanding and meeting requirements for science and management, not on the sampling gear or digital platforms themselves. There appears much to be gained by AIMS and the IMOS community (which includes AIMS) working closely together to ensure that workflows and infrastructures across their initiatives (e.g. Squidle+, Benthobox/ReefCloud) are compatible and interoperable as required. It is now evident that marine imagery acquisition and annotation, for still and video and for both mono and stereo imagery, is reaching a level of maturity within Australia that would benefit from a more facilitated national approach. The recommendations listed in this report provide such a way forward, but they will require sustained effort and drive to progress, at both the individual and organisational level.
Keywords: FAIR data; open data; underwater imagery

Deep-sea temperate-tropical faunal transition across uniform environmental gradients - Tim O'Hara; Williams, Alan; Woolley, Skipton N.C.; Nau, Amy W.; Nicholas J. Bax (Deep Sea Research Part I: Oceanographic Research Papers, 2020)
The biogeography of the deep-sea benthic fauna is uncertain due to the vast size and incomplete exploration of these environments. While shallow water assemblages are differentiated into tropical, temperate and polar faunas, it is unknown whether these units extend to lower depths. Here we use model-based statistics to analyse megafaunal benthic samples along a 2,300 km transect off the eastern Australian continental margin. We show that a temperate-tropical transition between 33-31˚S occurs at both lower bathyal (~2500 m) and abyssal (~4000 m) depths. This transition occurs despite almost uniform temperature, salinity and dissolved oxygen concentrations occurring across latitudes at these depths. Conversely, the patterns are consistent with the flux of organic matter to the seafloor, which varies from being relatively high in the productive temperate off SE Australia to low levels in more-oligotrophic tropical waters. Biodiversity is not uniform across the deep-sea and regional-scale heterogeneity needs to be incorporated into marine park designs.
Keywords: abyss; Australia; benthos; continental margins; megafauna; Tasman Sea

Description and genetic characterisation of Pulchrascaris australis n. sp. in the scalloped hammerhead shark, Sphyrna lewini (Griffin & Smith) in Australia - Shamsi, Shokoofeh; D Barton; Zhu, Xiaocheng (Parasitology Research, 2020)
Being listed in the IUCN Red List of Threatened Species, knowledge on the biology, health and diseases of the scalloped hammerhead, Sphyrna lewini (Griffith & Smith) is limited; this is especially true for its parasites. In this paper, a new species, Pulchrascaris australis, is morphologically described followed by genetic characterisation based on the sequence of the ITS region. The new species can be easily differentiated from its congeners based on the morphology of the mouthpart, spicules, plectanes, eggs and vulva. Phylogenetic analyses clearly distinguish specimens in the present study from other parasitic nematodes found in the Australasian waters and elsewhere. The sequencing data also suggest that Terranova larval type I found previously in various fish from New Caledonian and Australian (Queensland) waters also belong to Pulchrascaris australis n. sp.
Keywords: Anisakidae; Nematoda; shark

Digital Platforms for Marine Science Data and Information (infographic) - Rachel Przeslawski; Bryony Bennett; Bell, L (2020)
Australia has numerous digital platforms that host, analyse, and visualise marine data collected from various gear and environments. It can often be overwhelming or confusing to identify suitable digital platforms. This infographic offers a relatively simple visual representation of national data portals that will clarify current capabilities to better manage Australia’s oceans. <img alt="A graphic overview of marine science data and information platforms relevant to Australia" height="1200" src="/sites/default/files/Digital_Platforms_infographic_FINAL_Medium-Res_Aug6_2020.png" width="614" />
Keywords: Decision support tools

Distribution, fisheries interactions and assessment of threats to Australia’s sea snakes - Vinay Udyawer; Oxenham, Katie; Hourston, Mathew; Michelle R. Heupel (2020)
This project integrated existing sea snake occurrence data, field surveys and trawl interaction data to define the habitat suitability, distribution and area of occurrence of 27 species of sea snakes within the Australian Economic Exclusion Zone (EEZ). Areas of high diversity and endemism within the North-west and Northern marine region were defined, identifying south-west Gulf of Carpentaria as a region with the highest diversity, with the North-west Shelf region (i.e. Scott Reef and the north-west shoals) as a region of high sea snake endemism. Habitat suitability model spatial outputs were overlayed with annual fishing effort data using Automated Identification System (AIS) data from fishing vessels, to assess sea snake species exposure to trawl fishing. Overlap analysis identified regions along the Pilbara coastline and within the Gulf of Carpentaria as regions with significant overlap between trawl fishing effort and highly suitable habitats for sea snakes. Species with restricted ranges that fell within fishing grounds within the North-west marine region were identified to have high levels of spatial exposure to fishing activities.
Keywords: Fisheries Bycatch; Hydrophiinae; Marine protected areas; marine reserves; Population trends; Threat Mapping

Earth Observation for monitoring of Australian Marine Parks and other off-shore Marine Protected Areas - S. Sagar; I. Falkner; A. Dekker; Z Huang; D. Blondeau-Patissier; C. Phillips; Rachel Przeslawski (2020)
EO satellites provide a wide array of data types, services and products that have a well recognised potential to feed into the monitoring of environmental variables in a systematic and repeatable manner. However, to date there has been limited uptake of EO products for systematic Marine Park monitoring and reporting in Australia, despite there being a long history of marine scientific product development both globally and within Australia, from a range of EO data sources. In this report we begin by introducing EO data and science products in the context of marine monitoring, and give an overview of data availability in Australia (Section 1). In Section 2, we provide a more detailed overview of core EO scientific products in the marine space, with a focus on Australian applications and programs including ocean colour, sea surface temperature and coastal water applications. Section 3 focuses on human induced pressures on the marine environment and uses a range of case studies to illustrate the role EO scientific products can play in more effective mapping, monitoring and assessment of the impacts of these pressures. In Section 4 we highlight some of the future trends and developments in marine EO data, products and infrastructure, and discuss the potential impacts and opportunities from a MPA monitoring perspective. In a summary discussion, we revisit the challenges that exist for the adoption and uptake of EO products for MPA monitoring. We focus on the importance and benefit of increased communication and engagement between Marine Park managers and EO technical practitioners, particularly in the earlier stages of the products development cycle. Attention is drawn to one of the key themes of this report, that EO data and products have the highest potential impact in Marine Park monitoring when used as a complimentary data source, within a collaborative and multi-disciplinary environment.
Keywords: Earth observation; satellite imagery; fisheries; marine debris; marine heat waves; ocean colour

Evidence of diverse movement strategies and habitat use by white sharks, Carcharodon carcharias, off southern Australia - R. W. Bradford; T. A. Patterson; P. J. Rogers; McAuley, R.; Mountford, S.; Charlie Huveneers; Robbins, R.; Fox, A.; Bruce, B. D. (Marine Biology, 2020)
Large endothermic pelagic sharks are highly migratory and use habitats spanning a broad range of coastal, neritic and oceanic areas. This study aimed to resolve the current lack of information on the movements and habitat use of white sharks, Carcharodon carcharias, between shelf, slope and oceanic areas located off southwestern Australia. Movement behaviours, spatial distribution patterns and vertical habitat use of juvenile, sub-adult and adult white sharks ranging in size from 1.9 to 5.7 m total length were examined using 43 satellite tags deployed over 15 years. Pop-up satellite archival tags and satellite-linked radio tags collected 3663 days and > 109,900 km of tracking data over periods of up to 381 days. We demonstrated sex-based differences in movement and distribution patterns of male (21) and female (19) white sharks. Female dispersal was broader and extended further offshore than males, which largely remained in neritic and gulf habitats. Female white sharks experienced a narrower range of water temperatures (F = 9.0–19.0 °C; M = 10.4–24.8 °C). Despite these subtle differences, both sexes showed an affinity to the Neptune Island Group and the shelf slope canyons of the eastern Great Australian Bight, which are productive and oceanographically complex regions that support known prey of white sharks. This study highlighted that the southern-western Australian population of white sharks use off-shelf habitat to a greater extent than previously identified. Findings have potential implications for: ecological risk assessments of fisheries that operate in these offshore habitats and for monitoring and managing marine protected areas.
Keywords: Dispersal; Great Australian Bight; segregation; white shark

Examination of connectivity of hammerhead sharks in northern Australia - Michelle R. Heupel; Colin Simpfendorfer; A Chin; Sharon A Appleyard; D Barton; Mark Green; Johnson, G; McAuley, R; White, W (2020)
There is increasing concern about the conservation and sustainable use of hammerhead sharks nationally and globally, with documented declines in many parts of their range. Several hammerhead species have been recently added to international conventions such as the Convention on International Trade in Endangered Species (CITES), and the Convention on the Conservation of Migratory Species of Wild Animals (CMS). Within northern Australia, three species of hammerhead regularly occur: scalloped hammerhead (Sphyrna lewini), great hammerhead (Sphyrna mokarran) and winghead shark (Eusphyra blochii). A key information gap in managing Australia’s hammerhead sharks is whether Australian stocks are shared with neighbouring countries, especially Indonesia and Papua New Guinea, where there is heavy fishing pressure. Hammerhead sharks are known to be highly migratory and the extent of connectivity between countries is relevant to management approaches. Synthesis of findings from three methods for scalloped hammerheads showed there was some evidence to suggest stock structuring and limited movement between Australia, Indonesia, and PNG, but this finding is subject to uncertainty. Uncertainty is driven largely by the failure to encounter large (i.e. > 3 m) individuals which are most likely to move the greatest distances and create connectivity. Tracking and parasite fauna data suggest limited movement for individuals up to ~2.8 m, while genetic data indicate connectivity, but limited gene flow between some areas, specifically between Western Australia and other parts of Australia and Indonesia/PNG.
Keywords: animal movement; conservation assessment; cross-jurisdictional fisheries; population genetics and genomics

Expanding our spatial knowledge of marine biodiversity to support future best practice reviews - Tim O'Hara (2020)
Bioregionalisations are spatial frameworks that have been used to identify areas that have particular conservation values, describe ecosystem boundaries, delineate bioregional planning activities, organise environmental inventories, contextualise environmental assessments, and map the marine domain. The Integrated Marine and Coastal Regionalisation of Australia (IMCRA) products have informed the creation of a National Representative System of Marine Protected Areas (NRSMPA) and provided a spatial framework for marine bioregional planning. This report argues that a new marine biodiversity spatial management system would be more cost effective and useful than a dedicated updated IMCRA bioregionalisation process. A more informative approach going forward is to develop a fine-scale (km) system of species distributional data which could be used to both address current management priorities AND produce a new provincial-scale bioregionalisation, when and if required. Such a system could be largely constructed from existing databases, analyses and decision support tools.
Keywords: bioregionalisation; Integrated Environmental Assessment; IMCRA

The Fate of Deep-Sea Coral Reefs on Seamounts in a Fishery-Seascape: What Are the Impacts, What Remains, and What Is Protected? - Williams, Alan; Althaus, Franziska; Maguire, Kylie; Mark Green; Untiedt, Candice; Alderslade, Phil; Malcolm R Clark; Nicholas J. Bax; Thomas A Schlacher (Frontiers in Marine Science, 2020)
Environmental harm to deep-sea coral reefs on seamounts is widely attributed to bottom trawl fishing. Yet, accurate diagnoses of impacts truly caused by trawling are surprisingly rare. Similarly, comprehensive regional assessments of fishing damage rarely exist, impeding evaluations of, and improvements to, conservation measures. Here we report on trawling impacts to deep-sea scleractinian coral reefs in a regional (10–100s of km) fishery seascape off Tasmania (Australia). Our study was based on 148 km of towed camera transects (95 transects on 51 different seamounts with 284,660 separate video annotations and 4,674 “on-seamount” images analysed), and commercial trawling logbook data indexing fishing effort on and around seamounts. We detect trawling damage on 88% (45 of 51) of seamounts. Conversely, intact deep-sea coral reefs persist in refuge areas on about 39% (20 of 51) of the seamounts, and extend onto rocky seabed adjacent to seamounts. Depth significantly shapes the severity of trawl damage. The most profound impacts are evident on shallow seamounts (those peaking in < 950 m depths) where recent and repeated trawling reduced reefs built by scleractinian corals to rubble, forming extensive accumulations around seamount peaks and flanks. At intermediate depths (∼950–1,500 m), trawling damage is highly variable on individual seamounts, ranging from substantial impacts to no detection of coral loss. Deep seamounts (summit depth > 1,500 m) are beyond the typical operating depth of the trawl fishery and exceed the depth range of living deep-sea coral reefs in the region. Accurately diagnosing the nature and extent of direct trawling impacts on seamount scleractinian coral reefs must use stringent criteria to guard against false positive identifications of trawl impact stemming from either (1) misidentifying areas that naturally lacked deep-sea coral reef as areas where coral had been removed, or (2) attributing trawling as the cause of natural processes of reef degradation. The existence of sizeable deep-sea coral reef refuges in a complex mosaic of spatially variable fishing effort suggests that more nuanced approaches to conservation may be warranted than simply protecting untrawled areas, especially when the biological resources with conservation value are rare in a broader seascape context.
Keywords: fisheries management; indicators; scleractinian coral; Solenosmilia; towed-camera; VME; vulnerable marine ecosystem

A field and video annotation guide for baited remote underwater stereo-video surveys of demersal fish assemblages - Tim J. Langlois; Jordan S. Goetze; Bond, Todd; Jacquomo Monk; Abesamis, Rene A.; Asher, Jacob; Neville Barrett; Anthony T F Bernard; Phil J. Bouchet; Birt, Matthew J.; Cappo, Mike; Leanne M. Currey Randall; et al. (Methods in Ecology and Evolution, 2020)
1. Baited remote underwater stereo-video systems (stereo-BRUVs) are a popular tool to sample demersal fish assemblages and gather data on their relative abundance and body size structure in a robust, cost-effective and non-invasive manner. Given the rapid uptake of the method, subtle differences have emerged in the way stereo-BRUVs are deployed and how the resulting imagery is annotated. These disparities limit the interoperability of datasets obtained across studies, preventing broadscale insights into the dynamics of ecological systems.  2. We provide the first globally accepted guide for using stereo-BRUVs to survey demersal fish assemblages and associated benthic habitats. 3. Information on stereo-BRUVs design, camera settings, field operations and image annotation are outlined. Additionally, we provide links to protocols for data validation, archiving and sharing. 4. Globally, the use of stereo-BRUVs is spreading rapidly. We provide a standardized protocol that will reduce methodological variation among researchers and encourage the use of Findable, Accessible, Interoperable and Reusable workflows to increase the ability to synthesize global datasets and answer a broad suite of ecological questions.
Keywords: baited video; BRUV; fish; monitoring (population ecology); population ecology; sampling

Field Manuals for Marine Sampling to Monitor Australian Waters, Version 2 - Rachel Przeslawski; Scott D Foster (2020)
The Marine Biodiversity Hub has released the second version of a suite of field manuals to ensure that data collected by marine sampling platforms at different times and places across Australia are directly comparable. The Marine Sampling Field Manuals for Monitoring Australia’s Marine Waters support the national-scale monitoring and observing of Australia’s marine environment. With more than 136 contributors from 53 agencies, the manuals include information on marine survey design, pre-survey planning, gear deployment and retrieval, and data management. They provide consistent, defensible methods for collecting data that can be compared with other regional and national collections and are endorsed by researchers, managers, and technicians from multiple agencies with a variety of experience and subject-matter expertise. Major updates for Version 2 include a new online platform for accessibility and version control, a new manual on Remotely Operated Vehicles (ROVs), and a merger of the multibeam manual with national guidelines developed by AusSeabed. Web-link to "Field Manuals for Marine Sampling to Monitor Australian Waters" (Version 2)
Keywords: standard operating procedures

Final report: A14 Identification of near-shore habitats of juvenile white sharks in south-western Australia - R. W. Bradford; D Holman; T. A. Patterson; P. J. Rogers (2020)
Understanding the spatial dynamics and behaviour of the juvenile life stage of the white shark, Carcharodon carcharias, from the southern-western Australian (SWA) population is crucial to deriving a total abundance estimate and informing future management plans. The Head of the Great Australian Bight, including several marine parks – Great Australian Bight, Murat, Western Eyre (Commonwealth) and Nuyts Archipelago (State) Marine Parks, appear to be important habitat for white sharks of all life stages. However, further on-water activity and an expansion of the UAV survey into waters west of the Head of Bight would assist with characterising the diversity of this region and provide greater opportunity for deeper engagement with the Traditional Owners of Country.  Although difficult to establish effective offshore monitoring, targeted surveys of the Murat (e.g. around Yatala Reef) and Western Eyre Marine Parks would also increase our understanding of white shark distribution as well as biodiversity in the GAB.
Keywords: Carcharodon carcharias; Great Australia Bight; Unmanned Aerial Vehicle (UAV) survey; white shark

First national-scale snapshot of how marine researchers engage with Aboriginal and Torres Strait Islander communities - Paul T Hedge; Ingrid van Putten; Cass Hunter; Fischer, Mibu (Marine Biodiversity Hub, 2020)
Australian marine scientists demonstrate positive aspirations to engage Aboriginal and Torres Strait Islander people in research. Many scientists are unsure about where the responsibility for engagement lies, however, and what research is of interest to Indigenous communities. These are key findings of a Marine Biodiversity Hub study that surveyed 128 marine scientists to understand how they had engaged with Indigenous communities during their research careers. The survey has established a baseline for monitoring future changes in the scientists’ motivations, perceptions and practices. The study team included Hub deputy director, Paul Hedge, and scientists Ingrid van Putten, Cass Hunter, and Mibu Fischer of CSIRO.
Keywords: Indigenous engagement; infographic; poster; survey

Fish body sizes change with temperature, but not all species shrink with warming - Asta Audzijonyte; Richards, Shane A.; Rick D Stuart-Smith; Gretta Pecl; Graham J. Edgar; Neville Barrett; Payne, Nicholas; Julia L. Blanchard (Nature Ecology & Evolution, 2020)
Scientists have assumed that warming seas lead to smaller fish body sizes, on average. This analysis uses the Reef Life Survey and Australian Temperate Reef Collaboration data to look at whether this is true or not. It looks at how the size of individuals of 335 fish species varies along the Australian coastline (from cool to warm temperatures across their geographic ranges) and also through time and long-term reef monitoring sites. It surprisingly finds that fish size does change significantly with temperature, but not all in the same direction. Some species are larger in warmer seas, others become smaller. This is important for managing fisheries in the modern era of rapidly changing ocean climate, as well as for the way coral and rocky reef ecosystems function. Full text link to article https://rdcu.be/ceAzK
Keywords: citizen science; climate change; long-term monitoring; reef habitat; Reef life survey

Gascoyne Marine Park Post-survey report, RV Falkor, FK200308 - Alix Post; Rachel Przeslawski; Z Huang; Smith, Deb; Kirkendale, Lisa; Wilson, Nerida (2020)
In early 2020, a team aboard the RV Falkor explored two deep-sea canyons within the Gascoyne Marine Park. More than 30 new species were discovered, 2570 seafloor images were annotated, and 11,250 km2 were mapped. This survey confirmed that canyons within Gascoyne Marine Park are ecologically important systems, supporting numerous deep-sea species, many of which were discovered to be new to science. The advanced capabilities of the ROV SuBastian to navigate and image complex (near vertical) walls and overhangs within the canyons revealed patterns in the distribution of the seafloor taxa consistent with small-scale environmental variability. Repeat multibeam mapping revealed a dynamic canyon system that continues to be shaped by turbidity currents. The occurrence of reworked seagrass blades within the canyons provided a new understanding of these canyon systems as an active conduit between shallow shelf and abyssal environments. The distribution of the seabed biota revealed through quantitative ROV transects emphasised the importance of disturbance patterns in shaping the canyon ecosystems.
Keywords: Australian Marine Parks; benthic imagery; canyon habitats; deep sea; multibeam; remotely operated vehicles; Taxonomy

Guidelines for analysis of cumulative impacts and risks to the Great Barrier Reef - Piers K Dunstan; Jeffrey M Dambacher; Thornborough, K; Marshall, N; Rick D Stuart-Smith (2020)
The purpose of this document is to provide guidance on the assessment of cumulative risks and impacts in the Great Barrier Reef (GBR). The guidance is intended to be applied at a regional or plan of management level, and at a development application level. The guidance details the necessary concepts and outlines a series of steps to work through and link multiple pressures with their impacts on identified values. It is not meant to replace existing frameworks and guidance for standard environmental risk assessments, rather it is intended as a supplement to these approaches that facilitates the understanding and assessment of cumulative impacts in complex ecosystems of the GBR. For each step, this guidance provides criteria to select the appropriate tools or methods to use in cumulative impact analysis. The tools and methods identified will provide robust assessments and will reduce the uncertainty at each step. While a full and rigorous environmental risk assessment can take various forms and have many steps, this guidance is specifically designed to address analysis of cumulative impacts within a standard risk assessment framework. Beyond the guidance provided in this work, we anticipate the need for a “tool-box”, largely internet based, to provide access to existing and developing resources and approached for completing the more technically challenges steps of the risk assessment. This report (Part 1) describes the steps in the guidelines and their application. Part 2 will describe a detailed case study from the GBRMPA region and a plain language summary that can be used by proponents and regulators as an entry point to the technical guidelines contain summaries, specific to GBRMPA, QLD State Government and DAWE.
Keywords: cumulative; impacts; risk assessment

Increased Transparency and Resource Prioritization for the Management of Pollutants From Wastewater Treatment Plants: A National Perspective From Australia - Qurratu A. Rohmana; Andrew M Fischer; John Cumming; Blackwell, Boyd D.; John Gemmill (Frontiers in Marine Science, 2020)
With increasing human populations in coastal regions, there is growing concern over the quality of wastewater treatment plant (WTP) discharge and its impacts on coastal biodiversity, recreational amenities, and human health. In Australia, the current system of WTP monitoring and reporting varies across states and jurisdictions leading to a lack of data transparency and accountability, leading to a reduced ability to comprehensively assess regional and national scale biodiversity impacts and health risks. The National Outfall Database (NOD) was developed to provide a centralized spatial data management system for sharing and communicating comprehensive, national-scale WTP pollutant data. This research describes the structure of the NOD and through self-organizing maps and principal component analysis, provides a comprehensive, national-scale analysis of WTP effluent. Such a broad understanding of the constituents and level of pollutants in coastal WTP effluent within a public database provides for improved transparency and accountability and an opportunity to evaluate health risks and develop national water quality standards.
Keywords: effluent; environment; human health; impacts; outfalls; pollutants; spatial data management

The lower bathyal and abyssal seafloor fauna of eastern Australia - Tim O'Hara; Williams, Alan; Ahyong, Shane T.; Alderslade, Philip; Alvestad, T; Bray, D; Burghardt, Ingo; Budaeva, N; Criscione, F; Crowther, AL; Ekins, M; Eleaume, M; et al. (Marine Biodiversity Records, 2020)
Background: Our knowledge of the benthic fauna at lower bathyal to abyssal (LBA, > 2000 m) depths off Eastern Australia was very limited with only a few samples having been collected from these habitats over the last 150 years. In May–June 2017, the IN2017_V03 expedition of the RV Investigator sampled LBA benthic communities along the lower slope and abyss of Australia’s eastern margin from off mid-Tasmania (42°S) to the Coral Sea (23°S), with particular emphasis on describing and analysing patterns of biodiversity that occur within a newly declared network of offshore marine parks. Methods: The study design was to deploy a 4m (metal) beam trawl and Brenke sled to collect samples on soft sediment substrata at the target seafloor depths of 2500 and 4000m at every 1.5 degrees of latitude along the western boundary of the Tasman Sea from 42° to 23°S, traversing seven Australian Marine Parks. Results: The biological sampling included 35 beam trawls, 28 Brenke sleds, 8 box cores, 20 surface meso-zooplankton tows, and 7 Deep Towed Camera transects. In total, 25,710 specimens were identified to 1084 taxonomic entities, including 847 species-level, 144 genus-level and 69 family-level and 24 higher-level taxa. Of the species-level taxa, only 457 were assigned species-level taxonomic names, which implies that up to 58% of the collected fauna is undescribed. In addition, the ranges of numerous species have been extended to include the western Tasman Sea. Conclusions: The lower bathyal and abyssal fauna of soft sediment seafloors off eastern Australia has been systematically surveyed for the first time. The resultant collections will provide the foundation for much future ecological, biogeographical, phylogenetic and taxonomic research.
Keywords: Australia; Biodiversity; Biogeography; deep sea; epifauna; infauna; Tasman Sea; Taxonomy

Mapping and characterising reef habitat and fish assemblages of the Hunter Marine Park - Joel Williams; T Ingleton; Michael Sutherland; Peter Davies; Jacquomo Monk; Neville Barrett; Alan Jordan (2020)
This is a technical report for the Hunter Marine Park surveys as part of the NESP Marine Biodiversity Hub D3 project. The report summarises five years worth of multibeam echo sounder, towed video, stereo-baited remote underwater video and remotely operated vehicle surveys to provide Parks Australia with baseline information for the Hunter Marine Park. The Hunter Marine Park is located of the mid-NSW coast and continental shelf rocky reef was identified as a key ecological feature of the Park. The MBES surveys mapped 30% of the continental shelf component of the Marine Park and identified approximately 5.5km2 of rocky reef. Towed video surveys found these reefs to covered in a diverse range of sessile invertebrate assemblages. The stereo-BRUV surveys focused on three distinct regions across a depth range of 35-120 m. Up to 112 species of fish were identified, including three threatened and protected species. Each of the three locations were deemed to support a unique species assemblages. However, the patterns in distribution where highly species specific and often related to reef structure and season. These are the first mapping and biological surveys of the Hunter Marine Park region.
Keywords: fish; Hunter Marine Park; invertebrates; Mapping; mesophotic; multibeam; NSW; rocky reef; ROV; shelf; Spatially Balanced Design; stereo-BRUVs; survey; towed video

Measures for Social and Economic Monitoring of the Australian Marine Parks - Matt Navarro; Tim J. Langlois; M Burton; Kragt, M.E; Abbie A Rogers (2020)
In this report, we develop a set of recommended measures to monitor the social and economic dimensions of the Australian Marine Parks. Our recommendations are based on a review of approaches used nationally and internationally, and a series of regional workshops with marine park managers and experts from around Australia. The report provides a long-overdue synthesis of approaches used to monitor the social and economic dimensions of marine parks in Australia and should be useful both for informing monitoring of the Australian Marine Parks as well as state-managed marine parks.
Keywords: Australian Marine Parks; Economics; marine parks; monitoring; Social

Microplastics in the Australian Marine Environment: Issues and Options - Marcus Haward; Joanna Vince; Valeriya Komyakova (2020)
The paper centres on analysis of key sources: personal care, cosmetics, and cleaning products (PCCPs), synthetic materials (microfibers), tyres, fertilisers and biosolids; and key pathways that include wastewater and sewerage treatment plants. It explores mitigation and management approaches; focussing on circular economy approaches, product stewardship, extended producer responsibility, consumer behaviour and regulatory options. The paper concludes by outlining possible policy options for managing and mitigating impacts of microplastics in the Australian marine environment.

Monitoring Population Dynamics of ‘Western’ Right Whales off Southern Australia 2018-2021 - Final Report on activities for 2019 - Joshua N. Smith; Diana Jones; Kenny Travouillon; N. Kelly; M C Double; John Bannister (2020)
Annual aerial surveys of Australia’s ‘western’ population of southern right whales have been conducted between Cape Leeuwin, WA, and Ceduna, SA, since 1993 to monitor recovery from commercial whaling. The latest Hub-funded survey extended for seven days in August 2019. In 40 flying hours, 1111 right whales were sighted, including 425 calves, and 299 images were selected for computer-assisted ‘matching’ via the ARWPIC catalogue. The resulting population size estimate for ‘western’ Australian sub-population is 3164 whales. Estimates from 2018 and 2019 are the largest for the population since 1993 and are consistent with an increasing population trend of approximately 6% per year (based on counts of cow/calf pairs). Considerable annual variation in whale numbers, and cycles in population growth, makes it difficult to detect reliable annual changes in abundance and supports a continued sampling frequency of annual surveys.
Keywords: aerial survey; John Bannister; photo-identification; population trend; Southern right whale

Monitoring Population Dynamics of ‘Western’ Right Whales off Southern Australia 2018-2021 - Progress Report on activities for 2019 - Joshua N. Smith; Diana Jones; Kenny Travouillon; N. Kelly; M C Double; John Bannister (2020)
Annual aerial surveys of Australia’s ‘western’ population of southern right whales have been conducted between Cape Leeuwin WA and Ceduna SA since 1993 to monitor recovery from commercial whaling. The latest Hub-funded survey extended for seven days in August 2019. Over 40 flying hours, 1111 right whales were sighted, including 425 calves, and 299 images were selected for computer-assisted ‘matching’ via the ARWPIC catalogue. The resulting population size estimate for ‘western’ Australian sub-population is 3164 whales. Estimates from 2018 and 2019 are the largest for the population since 1993 and are consistent with an increasing population trend of approximately 6% per year (based on counts of cow/calf pairs).
Keywords: aerial survey; commercial whaling; Southern right whale

Monitoring the resilience of a no-take marine reserve to a range extending species using benthic imagery - Nicholas R. Perkins; Hosack, G.R.; Scott D Foster; Jacquomo Monk; Neville Barrett (PloS One, 2020)
IMAS, as part of NESP Hub-related research, have been monitoring reefs on Tasmanian east coast over the past decade or more, using an Autonomous Underwater Vehicle supplied by IMOS. The vehicle takes high resolution images of the seabed at a wide range of depths, especially at depths below which we can survey via our standard dive-based monitoring programs. these images are analysed to generate biodiversity and habitat data from the shallowest reefs down to the deepest parts of east coast reef systems (in excess of 60 m). In this paper we use this data to examine the extent that urchin barrens formed by overgrazing by the extension of Centrostephanus rodgersii (Long-spined urchin) has impacted east coast reef systems, how this varies with depth, and how this has changed with time. Importantly we also contrast the response between a no-take marine reserve at Governor Island (off Bicheno) and identical habitats in adjacent fished areas. We found that the large lobster population that has built up in the MPA has helped the reserve be resilient to the urchin invasion, with barren being far less common in the reserve than outside. Despite the good news that natural populations in protected areas are able to offer significant resistance to urchin invasion, there is also the bad news that urchin barrens are continuing to increase through time on eastern Tasmanian reefs, and their cover has essentially doubled over the five year period of the surveys (2011-2016). This equates going from around 0.3% to 0.8% cover within the park, and from around 3% to around 7% outside the park over that time period (although this varied between locations surveyed). Dr Nick Perkins and colleagues used a complex modelling approach to deal with a range of spatial issues in the sampling design to ensure the significance of the patterns observed was tested properly. This design is probably the most important part of the paper from the science perspective, but the ecological results have important implications for MPA, off-reserve biodiversity and fisheries management.
Keywords: auv; barren climate change; benthic imagery; Centrostephanus rodgersii kelp loss; temperate reef; time-series; urchin

National Outfall Database Ranking Report 2018-2019 Financial Year - Qurratu A. Rohmana; Andrew M Fischer; John Gemmill; John Cumming (2020)
This report provides an analysis of the Australian coastal outfalls and ranks them according to the total flow volume and nutrients load to prioritize the potential degree of impact of each source to the environment and human health. The pollutant contribution index, based on nitrogen and phosphorous loads, was calculated for each outfall. Outfalls were ordered from lowest to highest index value to rank them according to their relative pollutant contribution to the coastal and marine environment. The index is based on a total nutrient load discharge using the variables of flow, nitrogen and phosphorous. The ranked loads throughout Australia were mapped by quartiles. The top quartile (lowest nutrient load) of outfalls seem to be more prevalent in regional areas and discharge less nitrogen and phosphorus loads into the coastal and marine environment. The bottom quartile, on the other hand, with higher nutrient loads principally occur around the major cities. This ranking of nutrient loads from Australian outfalls by site at a national scale can therefore be useful in prioritizing treatment upgrade resources to manage biodiversity impacts and human health concerns.
Keywords: environment; Marine; outfalls; Pollution; wastewater

NESP Marine Biodiversity Hub Annual Progress Report 5 (2019) - Nicholas J. Bax; Alan Jordan; Paul Hedge; Gracie, S. (2020)
Letter from the Hub Leader (Professor Nic Bax) We started 2019 well with a publication in the prestigious international journal Nature on the origins of deep-sea biodiversity from tropical Australia to Antarctica. The article is the first indication that biodiversity in the deep ocean, where the majority of Australian Marine Parks (AMPs) are located, is evolving from polar latitudes and not tropical latitudes where shallower marine biodiversity originates. Tropical deep-water AMPs harbour a museum of old lineages that warrant special consideration. It is gratifying to see this kind of research coming to fruition as it is the result of the Marine Biodiversity Hub’s emphasis on building national information streams and expertise since 2007. Some of the first outputs of the Marine Biodiversity Hub were predictions of national marine biogeography (provincial structure, depth structure and geomorphology) requested by the Environmental Resources Information Network (ERIN). These predictions were based on the restricted information available at the time, including early Russian commercial fish surveys obtained from Vladivostok, but were essential to the design of what has become the AMP network. Twelve years later we have the data that validate those predictions (and AMP design) at the macro level, and which can be used to further improve spatial management of the Australian Exclusive Economic Zone (EEZ). This is just one example of the national capacity developed by the Marine Biodiversity Hub, as a result of which marine scientists from partner agencies have been able to engage in both significant national programs and international programs and negotiations supporting the Department of Agriculture, Water and Environment (DAWE) and the Department of Foreign Affairs and Trade (DFAT)  in areas including the Convention on Biological Diversity (CBD), the Convention on International Trade of Endangered Species, the United Nations (UN) negotiations on Biodiversity Beyond National Jurisdiction, the UN Decade on Ocean Science for Sustainable Development, the Global Ocean Observing System, the Global Climate Observing System, the Global Coral Reef Monitoring Network and the Intergovernmental Oceanographic Commission of the United Nations Educational, Scientific and Cultural Organization (IOC-UNESCO) Ocean Best Practices portal to name just some. While the National Environmental Science Program (NESP), and earlier Commonwealth Environment Research Facilities (CERF) and National Environmental Research Program (NERP), have built the capacity for Australia’s marine community to engage in these initiatives, international activities are funded externally, increasing the Hub’s influence at no cost to the program, showcasing the NESP program to the world, and bringing back additional ideas and perspectives that improve our capability to support Australian researchers and managers. At the end of 2019, Hub researchers supported the Department in accessing regional input to the CBD post-2020 framework that will develop the global biodiversity goals and metrics for the next decade, and attended the post-2020 marine thematic, including facilitating the workshop on marine restoration and its role in climate mitigation and adaptation, an increasingly active area for the Hub. While the Marine Biodiversity Hub works at the national scale in driving consistency in measurement, such as through a leadership role on the National Marine Science Committee (NMSC), Marine Monitoring and Baselines working group, or through national inventories of opportunities for marine restoration, work is often started on a regional basis, and through its network into the marine community it becomes nationally relevant. The Integrated Monitoring Framework that provides the basis for the Great Barrier Reef (GBR) Reef 2050 Integrated Monitoring and Reporting Program is now being used to inform monitoring program design across the New South Wales (NSW) marine estate and the Parks Australia Monitoring, Evaluation, Reporting and Improvement (MERI) framework. Similarly, the cumulative impacts framework developed for the GBR now informs the Hub’s Northern Australia Seascape program, Parks Australia’s MERI framework and potentially the cross-Hub Integrated Environmental Assessment. This sequential regional approach used by the Hub, where knowledge gained in one regional implementation is built on in subsequent implementations has proven to be a sound model for Hub research, but it is important to ensure that the national perspective is part of initial planning so that the process developed for each region is relevant nationally. An important synthesis product this year will be applying these regional approaches nationally, to provide an assessment of pressures, assets and the resulting cumulative risk at 1kmP2P resolution all around Australia. A notable success in 2019 was the Hub working through the Australian Marine Sciences Association (AMSA) to bring together regional Indigenous representatives from the Kimberley to Esperance for the first time in their history to meet with representatives from research agencies operating in Western Australia. This is the culmination of 4 years of learning with Indigenous experts through workshops in New Zealand, Darwin and Adelaide, each building expectations and trust, until finally in Perth last year we were able to understand the breakthroughs in regional collaboration that will be needed to support the expanding engagement in a respectful and sustained manner. A key outcome was to realize that it is not only Indigenous groups that need to coordinate among themselves to develop agreed standards of engagement, but also the research agencies that will need to improve their consistency and standards so that the capacity of Indigenous groups is not swamped by a variety of alternative approaches and protocols. This result was facilitated by the attendance of all major Hub partners who represent the major Western Australian and national research providers.  The outcomes of the 2019 Perth meeting will this year be built upon for the eastern seaboard by a different group working with advice from the Hub deputy director. This sixth and final year of NESP promises to be an exciting and productive year with many projects releasing their results and the Hub engaging in a series of interactions (which will use new engagement tools and products during the period of COVID-19 travel restrictions). One of the Hub’s early synthesis products is the Shark Action Plan designed to support a strategic and effective approach to the conservation and management of this vulnerable group of species. While the Policy Report has already been developed with the Protected Species and Community Branch, preparing the large amount of data on listing status of the 328 species of sharks and rays present in Australian waters to International Union for Conservation of Nature (IUCN) standard has taken longer. The complete Shark Action Plan will be delivered this year, together with the first population estimate for the Australian population of Southern Right Whales being developed by an international team, and updated information on the status (including newly found populations) and recovery opportunities for seasnakes, hammerhead sharks, and red and spotted handfish. A second synthesis product is the analysis of coral reef surveys from Reef Life Survey. This program was supported in CERF and has since had continued support by the Marine Biodiversity Hub through NERP and NESP. It has had spectacular National and global success, providing the most important biological dataset in the 2016 State of the Environment (SoE) Report and many high profile papers from their global surveys, resulting in the research leader being made an ARC Future Fellow and becoming a member of the IOC/UNESCO Global Ocean Observing System (GOOS). It is surprising that of all the reef monitoring occurring in Australia, this (and the long-term temperate reef survey program that it grew from) are the only reef surveys which discriminate communities at the species level. The synthesis product will compare reefs across Northern Australia (including Ningaloo, GBR and the Coral Sea) to determine which coral species have been affected by bleaching events and which have survived. This species-level approach will be vital to inform ongoing and substantial government investments in coral reef restoration. Targeting delivery of our scientific products to meet the Department’s needs for effectively administering the Environment Protection and Biodiversity Conservation (EPBC) Act is an important component of the Hub’s research design and delivery strategies, especially working with the Protected Species and Communities Branch and Parks Australia, and more generally in particularly challenging areas such as developing a framework to address cumulative impacts for jurisdictions (in 2019 for the Great Barrier Reef Marine Park Authority (GBRMPA) and in 2020 for NSW) that are ready to apply them. The Hub has been steadily developing a focus on marine restoration, recognising it as an important option for climate mitigation and adaptation. Carbon sequestration is much higher for coastal communities like mangroves, saltmarsh, seagrass and kelp than terrestrial communities and there are clear biodiversity benefits. The Hub started its restoration research by developing and supporting a national audit of coastal restoration and is now focussing on developing restoration options with direct benefits to marine biodiversity and communities, including Traditional Owners. Identifying where restoration fits into the Department’s legislative requirements under the EPBC Act was the focus of a 2018 research workshop that resulted in a report characterised as “a really good piece of research/writing to inform work in the Department.” A follow-up workshop planned for March 2020 has been postponed due to COVID-19. It is an ongoing focus of Hub research to map how restoration research will support management of Matters of National Environmental Significance (MNES) including AMPs, how we can promote international policy in this area (through the CBD post-2020 agenda), and how we can work with Australian communities (including Indigenous) to make coastal restoration a key Australian deliverable to enhance ecosystem services and mitigate biodiversity losses resulting from human activity and climate change. Finally, I would like to end on a personal note and thank the Department, research users, partners and researchers for the opportunity to lead the Marine Biodiversity Hub since 2007. It has been a privilege to be given the opportunity to impact the way that marine science can be made most accessible and useful to Australian managers and policy makers, and satisfying to understand and effect (with my most able Deputy Director Paul Hedge), the increased value from joint development of marine science questions by Hub researchers and research users. I look forward to hearing of the Marine Biodiversity Hub’s continued successes.

NESP Marine Biodiversity Hub Research Plan - 2020 RPv6 - Project Proposals - Nicholas J. Bax; Paul Hedge (2020)
This Research Plan for 2020 (RPv6) has been developed by the Marine Biodiversity Hub, in consultation with the Department of the Environment and Energy and other key stakeholders. The purpose of the Research Plan is to outline: the research priorities the Hub is funded to investigate the research projects that will address these priorities how the output of the research will be communicated and brokered to key stakeholders how the impact of the research will be measured how Hubs will work collaboratively within and across Hubs This Research Plan also lists key staff and research organisations, and the risks needing to be monitored to ensure success. Please note: This plan includes new and revised research projects for 2020. Project durations vary and may extend over a number of years. If the project you are interested in is not listed in the Item field of this research plan, it will be included in an earlier year as an ongoing, unchanged project. Where a project proposal involves significant changes, it will be updated and included in subsequent research plans.
Keywords: annual research plan; RPv6

Northern River Shark project summary fact sheet - PM Kyne; Bryony Bennett; Pierre Feutry (2020)
A fact sheet synthesising Marine Biodiversity Hub research on the Northern River Shark. A decade of Marine Biodiversity Hub Research led by Charles Darwin University shows the Northern River Shark to be more wide-ranging than previously thought, with new populations documented in several northern rivers. In 2010, the species was known from only 32 records in six rivers/estuaries; now more than 600 individuals have been recorded in 12 rivers/estuaries. Five genetically distinct populations were identified: four in Australia and one in Papua New Guinea. CSIRO close-kin mark-recapture analyses enabled the first population size estimates for one of these populations: the Northern Territory’s Van Diemen Gulf population size was estimated to be only ~600–1100 adults. The research provides monitoring and population assessment capability directly relevant to managing the recovery of the Northern River Shark and underpins environmental assessments under the EPBC Act in the context of northern Australia’s development.
Keywords: Glyphis garricki; close-kin mark-recapture; northern river shark; Van Diemen Gulf; Northern Territory; population size; population structure; threatened species

Northern River Shark project summary poster - PM Kyne; Bell, L; Bryony Bennett; Pierre Feutry (2020)
A poster providing a summary of the Marine Biodiversity Hub research on the Northern River Shark. A decade of Marine Biodiversity Hub Research led by Charles Darwin University shows the Northern River Shark to be more wide-ranging than previously thought, with new populations documented in several northern rivers. In 2010, the species was known from only 32 records in six rivers/estuaries; now more than 600 individuals have been recorded in 12 rivers/estuaries. Five genetically distinct populations were identified: four in Australia and one in Papua New Guinea. CSIRO close-kin mark-recapture analyses enabled the first population size estimates for one of these populations: the Northern Territory’s Van Diemen Gulf population size was estimated to be only ~600–1100 adults. The research provides monitoring and population assessment capability directly relevant to managing the recovery of the Northern River Shark and underpins environmental assessments under the EPBC Act in the context of northern Australia’s development.
Keywords: Glyphis garricki; close-kin mark-recapture; northern river shark; Van Diemen Gulf; Northern Territory; population size; population structure; threatened species

One panel to rule them all: DArTcap genotyping for population structure, historical demography, and kinship analyses, and its application to a threatened shark - Pierre Feutry; Floriaan Devloo-Delva; Adrien Tran Lu Y; Mona, Stefano; R. Gunasekera; Grant Johnson; Richard D. Pillans; Jaccoud, Damian; Kilian, Andrzej; David L Morgan; Thor Saunders; Nicholas J. Bax; et al. (Molecular Ecology Resources, 2020)
With recent advances in sequencing technology, genomic data are changing how important conservation management decisions are made. Applications such as Close‐Kin Mark‐Recapture demand large amounts of data to estimate population size and structure, and their full potential can only be realised through ongoing improvements in genotyping strategies. Here we introduce DArTcap, a cost‐efficient method that combines DArTseq and sequence capture, and illustrate its use in a high resolution population analysis of Glyphis garricki, a rare, poorly known and threatened euryhaline shark. Clustering analyses and spatial distribution of kin pairs from four different regions across northern Australia and one in Papua New Guinea, representing its entire known range, revealed that each region hosts at least one distinct population. Further structuring is likely within Van Diemen Gulf, the region that included the most rivers sampled, suggesting additional population structuring would be found if other rivers were sampled. Coalescent analyses and spatially explicit modelling suggest that G. garricki experienced a recent range expansion during the opening of the Gulf of Carpentaria following the conclusion of the Last Glacial Maximum. The low migration rates between neighbouring populations of a species that is found only in restricted coastal and riverine habitats show the importance of managing each population separately, including careful monitoring of local and remote anthropogenic activities that may affect their environments. Overall we demonstrated how a carefully chosen SNP panel combined with DArTcap can provide highly accurate kinship inference and also support population structure and historical demography analyses, therefore maximising cost‐effectiveness.
Keywords: Close‐Kin Mark‐Recapture; coalescent simulations; connectivity; Glyphis garricki; RAD; sequence capture

Perceptions, motivations and practices for Indigenous engagement in marine science in Australia - Paul Hedge; van Putten, Elizabeth Ingrid; Cass Hunter; Fischer, Mibu (Frontiers in Marine Science, 2020)
Australian science has evolved to include a number of initiatives designed to promote and guide ethical and culturally appropriate Indigenous participation and engagement. While interest and overall engagement between Indigenous people and marine scientists appears to have grown in the last decade there are also signs that some researchers may not be setting out to engage with Indigenous Australians on the right foot. This research seeks to move beyond anecdotal evidence about engagement of marine researchers with Indigenous Australians by gathering empirical information from the scientists’ perspective. Our survey of 128 respondents showed that 63% (n = 79) of respondents have engaged with Indigenous communities in some way throughout their career, however, most marine research projects have not included Indigenous engagement and when it occurs it is often shorter than 3 years in duration. Responses indicated that the majority of marine scientists see mutual benefits from engagement, do not avoid it and believe it will become more important in the future. We identify a number of challenges and opportunities for marine research institutions, marine researchers and Indigenous communities if positive aspirations for engagement are to be converted to respectful, long-term and mutually beneficial engagement.

Post survey report for the Coral Sea Australian Marine Park 2019 - Vanessa L Lucieer; Beaman, R; Woehler, E; Horowitz, J; Nau, A; Vandenbossche, P (2020)
EXECUTIVE SUMMARY This post survey report details the data collected within the Coral Sea Australian Marine Park onboard the RV Investigator (IN2019_V04) between the 7th of August and the 3rd of September 2019 associated with the primary voyage Hotspot dynamics in the Coral Sea- connections between the Australian plate and deep Earth’ (Whittaker 2020). The data and preliminary results in this report pertain to ongoing research to examine spatial patterns in deep-water seafloor biodiversity, in particular, how organisms are related to geomorphic features within the Coral Sea Australian Marine Park (AMP). The seafloor biodiversity and associated geomorphic habitats in this AMP are poorly understood, and given the recent release of the AMP rezoning, it is particularly important to understand the spatial variability of seafloor biodiversity and associated habitats to better quantify the biological assets within the AMP.
Keywords: Coral Sea; Geomorphology; multibeam

Primary microplastics in the marine environment: scale of the issue, sources, pathways and current policy - Valeriya Komyakova; Joanna Vince; Marcus Haward (2020)
This paper analyses research on microplastic pollution, specifically focussingon intentionally added microplastics. Intentionally added microplastics are found in industrial and domestic cleaning products, medicines, synthetic clothing, personal care and cosmetic products (PCCPs), construction materials and car tyres. Studies have reported that over 50,000 microplastic particles can be found in one gram of PCCPs product and as many as 17,700,000 fibres can be released during single 5kg washing. This paper reviews the policies that address microplastic pollution in the European Union (EU), the United States (USA) and Australia. The EU is a leader in the development of plastic pollution policies, and in particular, intentionally added microplastics and provides a useful framework for understanding how this issue can be addressed by a federation such as Australia.
Keywords: Australia; governance; Intentionally added microplastics; Microplastics

Prioritising search effort to locate previously unknown populations of endangered marine reptiles - Vinay Udyawer; Somaweera, Ruchira; Nitschke, Charlotte; ’Anastasi, Blanche; Sanders, Kate; Webber, Bruce L.; Hourston, Mathew; Michelle R. Heupel (Global Ecology and Conservation, 2020)
Strategies aimed to conserve and manage rare species are often hindered by the lack of data needed for their effective design. Incomplete and inaccurate data on habitat associations and current species distributions pose a barrier to effective conservation and management for several species of endemic sea snakes in Western Australia that are thought to be in decline. Here we used a correlative modelling approach to understand habitat associations and identify suitable habitats for five of these species (Aipysurus apraefrontalis, A. foliosquama, A. fuscus, A. l. pooleorum and A. tenuis). We modelled speciesspecific habitat suitability across 804,244 km2 of coastal waters along the North-west Shelf of Western Australia, to prioritise future survey regions to locate unknown populations of these rare species. Model projections were also used to quantify the effectiveness of current spatial management strategies (Marine Protected Areas) in conserving important habitats for these species. Species-specific models matched well with the records on which they were trained, and identified additional regions of suitability without records. Subsequent field validation of the model projections uncovered a previously unknown locality for A. fuscus within the mid-shelf shoal region, outside its currently recognised global range. Defining accurate geographic distributions for rare species is a vital first step in defining more robust extent of species occurrence and range overlap with threatening processes.
Keywords: Conservation prioritisation; Environmental correlates; Habitat suitability; Hydrophiinae; Marine protected areas; Marine snake; MaxEnt; range expansion

Qualitative Models of Northern Seascapes - Piers K Dunstan; Skipton N. C. Woolley; Jeffrey M Dambacher (2020)
We describe the pressures, values and conceptual models for ecosystems in the Northern Marine Region. To do this, we implement the first three of five steps of the GBR Cumulative Impact Guidelines (Dunstan et al. 2019):  1) understanding pressures; 2) understanding values; and 3) the description of conceptual models of ecosystems. These first three steps provide a systematic hazard assessment for the Northern Marine Region, adding a consistent spatial component to earlier hazard assessments. Progressing from this hazard assessment to a cumulative impact assessment requires the subsequent or final two steps of the GBR Cumulative Impact Guidelines: 4) dose-response curves and 5) quantitative assessment. Parks Australia has recently described a set of ecosystem complexes we spatially mapped in the Northern Marine Region using a number of different data layers generated from previous NESP work to provide the values (Step 1). The data on pressures (Step 2) was also obtained from previous work completed by the NESP Marine Biodiversity Hub. Finally (Step 3), a workshop was held in Darwin in September 2019 to describe the conceptual models for each ecosystem complex, namely the ecosystem components and the pressures that are acting on each component. This analysis is designed to identify which ecosystem components should be examined in the future to assess the significance of cumulative impacts (ie through a formal risk assessment). The outputs from this first stage have identified the key natural values in the ecosystem complexes that may be at risk of unsustainable impacts. These outputs will also be useful in identifying potential indicators for the ecosystem complexes described by Parks Australia
Keywords: cumulative impact; ecosystems; northern seascapes; pressures; qualitative models

Regional-scale patterns of deep seafloor biodiversity for conservation assessment - Tim O'Hara; Williams, Alan; Althaus, Franziska; Ross, Andrew S.; Nicholas J. Bax (Diversity and Distributions, 2020)
Aim Mining and petroleum industries are exploring for resources in deep seafloor environments. Lease areas are often spatially aggregated and continuous over hundreds to thousands of kilometres. Sustainable development of these resources requires an understanding of the patterns of biodiversity at similar scales, yet these data are rarely available for the deep sea. Here, we compare biodiversity metrics and assemblage composition of epibenthic megafaunal samples from deep‐sea benthic habitats from the Great Australian Bight (GAB), a petroleum exploration zone off southern Australia, to similar environments off eastern Australia. Location The Great Australian Bight (34–36°S, 129–134°E) and south‐eastern (SE) and north‐eastern (NE) Australian continental margins (23–42°S, 149–155°E) in depths of 1,900–5,000 m. Methods A species–sample matrix was constructed from invertebrate and fish megafauna collected from beam trawl samples across regions at lower bathyal (1,900–3,200 m) and abyssal (>3,200 m) depths, and analysed using multivariate, rarefaction and model‐based statistics. We modelled rank abundance distributions (RAD) against environmental factors to identify drivers of abundance, richness and evenness. Results Multivariate analyses showed regional and bathymetric assemblage structure across the region. There was an almost complete turnover of sponge fauna between the GAB and SE. SE samples had the highest total faunal abundance and species richness. RAD models linked total abundance and species richness to levels of carbon flux. Evenness was associated with seasonality of net primary production. Conclusions Significant assemblage structure at regional scales is reported for the first time at lower bathyal and abyssal depths in the southern Indo‐Pacific region along latitudinal and longitudinal gradients. The GAB fauna was distinct from other studied areas. Relatively high species richness, previously reported from the GAB continental shelf, did not occur at lower bathyal or abyssal depths. Instead, the abundance, richness and evenness of the benthic fauna are linked to surface primary production, which is elevated off SE Australia.
Keywords: benthos; conservation assessment; deep sea; key ecological features; rank abundance distribution

Restoration Showcase June 2020 - Webinar Presentation - "Assessing the feasibility of restoring giant kelp forests in Eastern Tasmania" - Layton, Cayne (2020)
"Assessing the feasibility of restoring giant kelp forests in Eastern Tasmania" - a presentation for the Restoration Showcase June 2020. Webinar Link - Restoration Showcase June 2020 - Cayne Layton

Restoration Showcase June 2020 - Webinar Presentation - "Assisting restoration of ecosystem engineers through seed-based and shoot-based programs in the Shark Bay World Heritage Site" - John Statton (2020)
"Assisting restoration of ecosystem engineers through seed-based and shoot-based programs in the Shark Bay World Heritage Site" - a presentation for the Restoration Showcase June 2020. Webinar Link - Restoration Showcase June 2020 - John Statton

Restoration Showcase June 2020 - Webinar Presentation - "How can we target investment for healthier habitats" - Abbie A Rogers (2020)
"How can we target investment for healthier habitats" - a presentation for the Restoration Showcase June 2020. Webinar Link - Restoration Showcase June 2020 - Abbie Rogers

Restoration Showcase June 2020 - Webinar Presentation - "Rebuilding Australia's lost shellfish reefs" - Ian M. McLeod (2020)
"Rebuilding Australia's lost shellfish reefs" - a presentation for the Restoration Showcase June 2020. Webinar Link - Restoration Showcase June 2020 - Ian McLeod

Restoration Showcase June 2020 - Webinar Presentation - "Rebuilding coastal wetland ecosystems in Great Barrier Reef catchments - Waltham, Nathan (2020)
"Rebuilding coastal wetland ecosystems in Great Barrier Reef catchments" - a presentation for the Restoration Showcase June 2020. Webinar Link - Restoration Showcase June 2020 - Nathan Waltham

Restoration Showcase June 2020 - Webinar Presentation - "United Nations Decade on Ecosystem Restoration 2021-2030" - Grimsditch, Gabriel (2020)
"United Nations Decade on Ecosystem Restoration 2021-2030" - a presentation for the Restoration Showcase June 2020. Webinar Link - Restoration Showcase June 2020 - Gabriel Grimsditch

Seagrass restoration is possible: Insights and lessons from Australia and New Zealand. - Yi Mei Tan; Oliver Dalby; Gary A. Kendrick; John Statton; Elizabeth A Sinclair; Matthew W Fraser; Peter I. Macreadie; Chris L Gillies; Rhys A Coleman; Michelle Waycott; Kor-jent van Dijk; Vergés, Adriana; et al. (Frontiers in Marine Science, 2020)
Seagrasses are important marine ecosystems situated throughout the world’s coastlines. They are facing declines around the world due to global and local threats such as rising ocean temperatures, coastal development and pollution from sewage outfalls and agriculture. Efforts have been made to reduce seagrass loss through reducing local and regional stressors, and through active restoration. Seagrass restoration is a rapidly maturing discipline, but improved restoration practices are needed to enhance the success of future programs. Major gaps in knowledge remain, however, prior research efforts have provided valuable insights into factors influencing the outcomes of restoration and there are now several examples of successful large-scale restoration programs. A variety of tools and techniques have recently been developed that will improve the efficiency, cost effectiveness, and scalability of restoration programs. This review describes several restoration successes in Australia and New Zealand, with a focus on emerging techniques for restoration, key considerations for future programs, and highlights the benefits of increased collaboration, Traditional Owner (First Nation) and stakeholder engagement. Combined, these lessons and emerging approaches show that seagrass restoration is possible, and efforts should be directed at upscaling seagrass restoration into the future. This is critical for the future conservation of this important ecosystem and the ecological and coastal communities they support.
Keywords: climate change; coastal; marine plants; restoration; seagrass ecosystems

Social media posts reveal the geographic range of the Critically Endangered Clown Wedgefish Rhynchobatus cooki - McDavitt, Matthew T.; PM Kyne (Journal of Fish Biology, 2020)
The shark-like rays of the family Rhinidae (wedgefishes) are one of the most threatened group of marine fishes globally. The poorly-known Clown Wedgefish Rhynchobatus cooki has historically only been recorded from fish markets in Singapore and Jakarta, Indonesia. Its natural geographic range has until now gone undocumented. Intentional searches of social media posts describing wedgefish catches in Indonesia and Malaysia revealed the first wild records of this Critically Endangered species. A total of six catch records from small-scale fisheries were located from Lingga and Singkep Islands in Indonesia (1 from 2015, 4 from 2019, 1 from 2020). It remains unknown if the species is a micro-endemic to this small area of the Malay Archipelago, or if it is wider ranging. These results demonstrate the utility of social media searches to identify biogeographic records of cryptic and data-poor species.
Keywords: Conservation; Elasmobranchs; Indonesia; Rhinidae; rhino rays; threatened species

The thin edge of the wedge: extremely high extinction risk in wedgefishes and giant guitarfishes - PM Kyne; Rima W. Jabado; Cassandra L. Rigby; Dharmadi; Gore, Mauvis A.; Caroline M. Pollock; Herman, Katelyn B.; Cheok, Jessica; David A. Ebert; Colin Simpfendorfer; N K Dulvy (Aquatic Conservation: Marine and Freshwater Ecosystems, 2020)
Wedgefishes and giant guitarfishes have overtaken sawfishes as the most imperilled marine fish families globally, with all but one of the 16 species facing an extremely high risk of extinction through a combination of traits: limited biological productivity; presence in shallow waters overlapping with some of the most intense and increasing coastal fisheries in the world; and overexploitation in target and by-catch fisheries, driven by the need for animal protein and food security in coastal communities and the trade in meat and high-value fins. Two species with very restricted ranges, the clown wedgefish (Rhynchobatus cooki) of the Malay Archipelago and the false shark ray (Rhynchorhina mauritaniensis) of Mauritania, may be very close to extinction. Only the eyebrow wedgefish (Rhynchobatus palpebratus) is not assessed as Critically Endangered, with it occurring primarily in Australia where fishing pressure is low and some management measures are in place. Australia represents a ‘lifeboat’ for the three wedgefish and one giant guitarfish species occurring there. To conserve populations and permit recovery, a suite of measures will be required that will need to include species protection, spatial management, by-catch mitigation, and harvest and international trade management, all of which will be dependent on effective enforcement.
Keywords: Elasmobranchs; Historical ecology; IUCN Red List; Red List Index; shark-like rays; threatened species; wildlife trade

Trail camera video systems: investigating their utility in interpreting patterns of marine, recreational trailer-boat fishers’ access to an offshore Marine Park in differing weather conditions. - T P Lynch; Foster, S; C Devine; A Hegarty; Felicity McEnnulty; M Burton; Lyle, J M (ICES Journal of Marine Science, 2020)
When monitoring marine recreational fishers at sub-bio-regional scales—for example those who are accessing a Marine Park—on-site sampling is often required. This poses various logistical challenges, such as the efficient timing of intercept interviews. Here, we examine these challenges, combining trail cameras, closed-circuit television (CCTV), weather stations, and interviews at boat ramps that bracket an offshore Marine Park. Trail camera results were similar to those from a CCTV system co-located at one of the boat ramps. Fishers’ boat launches peaked early, but return times varied considerably by ramp and weather. Both the numbers of launches and trip durations were strongly responsive to good weather, particularly at ramps used for offshore fishing. Weather was a more important factor to predict the likelihood of intercept interview opportunities than holiday period, which may reflect changing dynamics in work culture and improvements in weather prediction. Interviewed fishers reported preferences to individual ramps over the fishing season and nearly all trips to the Marine Park were reported by fishers accessing just one ramp. The strong relationships between fishing, weather, and ramp, observed by the trail camera and correlated with the weather station data, may allow for the efficient targeting of intercept interviews and potentially the modelling of fishing effort.
Keywords: anglers; interviews; Marine Park; marine social science research; MPA; offshore fisheries; sensor array; the human dimension; weather; wildlife biology

True size matters for conservation: deep-sea coral reefs are typically small and estimates of their size are remarkably robust to a method used to define them - Williams, Alan; Althaus, Franziska; Mark Green; Maguire, Kylie; Untiedt, Candice; Mortimer, Nick; Jackett, Chris J.; Malcolm R Clark; Nicholas J. Bax; Pitcher, Roland; Thomas A Schlacher (Frontiers in Marine Science, 2020)
Protection of vulnerable marine ecosystems (VME) is a critical goal for marine conservation. Yet, in many deep-sea settings, where quantitative data are typically sparse, it is challenging to correctly identify the location and size of VMEs. Here we assess the sensitivity of a method to identify coral reef VMEs based on bottom cover and abundance of the stony coral Solenosmilia variabilis on deep seamounts, using image data from a survey off Tasmania, Australia, in 2018. Whilst there was some detectable influence from varying coral cover and the abundance of live coral heads, the distribution of coral reef VMEs was not substantially shifted by changing these criteria or altering the attributes of a moving window used to spatially aggregate coral patches. Whilst applying stricter criteria for classifying VMEs predictably produced smaller areas of coral reef VME, these differences were not sizeable and were often negligible. Coral reef VMEs formed large contiguous “blankets,” mainly on the peaks and flanks of seamounts, but were absent from the continental slope where S. variabilis occurred at low abundance (cover) and/or had no living colonies. The true size of the Tasmanian coral reef VMEs ranged from 0.02 to 1.16 km2 ; this was relatively large compared to reefs of S. variabilis mapped on New Zealand seamounts, but is small compared to the scales used for regional model predictions of suitable habitat (typically 1 km2 grid cell), and much smaller than the smallest units of management interest (100s–1000s km2 ). A model prediction of the area of suitable habitat for coral reef in the Tasmanian area was much greater than the area of coral reef estimated in this study. That the method to estimate VME size is not overly sensitive to the choice of criteria is highly encouraging in the context of designing spatial conservation measures that are robust, although its broader application, including to other VME indicator taxa, needs to be substantiated by scenario testing in different environments. Importantly, these results should give confidence for stakeholder uptake and form the basis for better predictive VME models at larger spatial scales and beyond single taxa.
Keywords: coral; deep sea; fisheries management; seamount; Solenosmilia; towed-camera; VME; vulnerable marine ecosystem

UN Decade on Ecosystem Restoration 2021-2030 - What Chance for Success in Restoring Coastal Ecosystems? - Waltham, Nathan J.; Elliott, Michael; Lee, Shing Yip; Lovelock, Catherine; Duarte, Carlos M.; Buelow, Christina; Simenstad, Charles; Nagelkerken, Ivan; Claassens, Louw; Wen, Colin K-C; Barletta, Mario; Connolly, Rod M.; et al. (Frontiers in Marine Science, 2020)
This paper looks at whether the United Nations Declaration of the UN Decade on Ecosystem Restoration 2021-2030 can be properly applied to coastal ecosystems. The paper describes what coastal ecosystems are, why they are important, what is currently threatening them and why they are declining. The authors examine what will be required to restore coastal ecosystems successfully over the next decade, including the capability and capacity of states to conduct restoration, the availability of trans-disciplinary teams, policy, and funding availability.
Keywords: blue carbon; coastal ecosystems; mangroves; restoration; seagrass; United Nations; wetlands

Wessel Marine Park Post-Survey Report for IN2019T02 - Rachel Przeslawski; Beaman, R; Fava, L; Scott L Nichol; Woehler, E; Yule, C (2020)
In October 2019, opportunistic mapping and imagery of the Wessel Marine Park on the RV Investigator revealed a localised band of high biodiversity linked to a unique and culturally important geomorphological feature in the otherwise uniform seascape prevalent in the Wessel Marine Park. Our findings help contribute to an understanding of the values of a northern marine park, including an inventory of communities and habitats as well as potential relationships to geomorphic features and culturally important sites. This has national significance to the implementation of the northern marine park management plan, as well as informing future monitoring programs in northern Australia.
Keywords: Australian Marine Parks; Indigenous engagement; multibeam; towed video

2019 AMSA Indigenous Workshop - Summary Report - Paul Hedge; Bessen, B (2019)
Between 2016 and 2018, the NESP Marine Biodiversity Hub has worked closely with Australian Marine Sciences Association (AMSA) to plan, facilitate and sponsor workshops aimed at advancing Indigenous engagement and participation in marine science. The Fremantle 2019 workshop, convened 10-11 July, was designed to build on previous AMSA Indigenous engagement workshops by focusing discussion and interactions on collaborative partnerships for sea country research and monitoring in Western Australia (WA). There is a growing number of Indigenous groups in Western Australia with achievements and aspirations for participation in sea country research and monitoring. At the same time numerous marine research providers (i.e. marine research institutions and marine management agencies) operating in WA have, or intend to invest in the development of policies, guides or other documentation to guide their marine researchers with Indigenous engagement, with varying degrees of Indigenous input. While this is an encouraging sign for collaborative partnerships in sea country research and monitoring, we are reaching the point where there is likely to be considerable duplication between research providers and where Indigenous organisations are struggling to resource their engagement in numerous bespoke engagement processes or protocols. An alternative way forward is the development of a common approach to Indigenous engagement that provides a standard that all Indigenous groups and research providers working on sea country could agree to (or aspire to). The workshop brought together approximately 60 invited Indigenous and marine science participants to share their experiences and thoughts about the development of a common standard for Indigenous engagement in sea country research and monitoring in WA - better ways of working together on sea country. Furthermore, the workshop provided a good opportunity to explore and identify opportunities for collaborative and respectful partnerships for sea country research and monitoring in WA.
Keywords: Indigenous engagement; Marine Science; partnerships; standards; Western Australia

Acanthocephalans from Australian elasmobranchs (Chondrichthyes) with a description of a new species in the genus Gorgorhynchus Chandler, 1934 (Rhadinorhynchidae) - Smales, Lesley R.; D Barton; Chisholm, Leslie A. (Systematic Parasitology, 2019)
Gorgorhynchus occultus n. sp. is described from Sutorectus tentaculatus (Peters) (Orectolobidae) collected off Bunbury, Western Australia in 1986. The new species differs from all other species of Gorgorhynchus Chandler, 1934 by having a suite of characters including a proboscis hook formula of 18–20 rows of 8–9 hooks, a well-developed neck, irregular circles of small spines in a single anterior field, the male reproductive system limited to the posterior quarter of the trunk and three cement glands. In a survey of 284 sharks collected between 2015 and 2018 from 10 localities in Australian waters, 11 individuals were infected with acanthocephalan cystacanths. One individual of Sphyrna mokarran (Rupell) (Sphyrnidae) was infected with Corynosoma cetaceum Johnston & Best, 1931. Serrasentis sagittifer (Linton, 1889) (Rhadinorhynchidae) was found in five individuals of S. mokarran, four individuals of Syphyrna lewini (Griffith & Smith) and one individual of Carcharhinus coatesi (Whitley) (Carcharhinidae). These infections may be accidental because it has been suggested that acanthocephalans cannot tolerate the high levels of urea used by marine and esturine elasmobranchs for osmoregulation. The two most common host species examined, S. mokarran and S. lewini had the highest intensities and prevalences of infection with S. sagittifer. Although more individuals of S. lewini were examined, S. mokarran had the higher prevalence of infection. As part of the Springer Nature SharedIt initiative, you can now publicly share a full-text view-only version of your paper by using the link https://rdcu.be/bONmO
Keywords: Acanthocephalans; elasmobranch; Gorgorhynchus; new species

Australian coastal sewage outfalls and data transparency - Public access to government information - John Gemmill; Andrew M Fischer; Qurratu A. Rohmana (2019)
To improve management of the environment, governments and managers need to know what other researchers and agencies have found and how they have found it. Accurate data and transparent methods are needed for governments to make good policy decisions and for the general public. Providing a comprehensive understanding of nutrient and pollutant loads into the marine environment around Australia is difficult given the different sampling and reporting requirements. The aim of the National Outfall Database (NOD) was to facilitate cross-institutional data sharing among federal, state, local governments and the community to promote transparency and openness of governance for managing pollutants from WWTPs. The NOD also provides data and information that could be helpful for integrating infrastructure planning and decision making of sewage effluent impacts on marine environment. This categorizes outfall types and summarizes data collection from water treatment authorities for each outfall type. Of the seven states and territories examined there were 42 WTAs and 181 outfalls. Queensland has the highest number of WTAs at 18 followed by NSW at 12 and Victoria at 8. Water quality parameters monitored at each of the outfall sites varies and depended on the conditions set out in the Environmental Protection Authority licenses. However, at all sites, nutrient concentration and flow rates were reported. NOD data collection has been running since 2015. After the fourth year of data collection (2018) most WTAs (98%) have met these basic criteria for supplying the data. The data collection is comprehensively presented in a public database which facilitates transparency and data sharing among water treatment authorities, government agencies and the general public. Promoting the transparency of monitoring data and pollutants entering the marine environment is important for managing marine biodiversity. This report highlights several needs and challenges that have been overcome and that still need to be addressed in order to provide easily accessible data and help promote insight-driven decisions and reduce pollutant impacts to the marine environment.
Keywords: citizen science; coastal management; ocean pollution; Sewage; waste management; waste water; water treatment

Benefits and costs of alternate seagrass restoration approaches - Abbie A Rogers; Michael P. Burton; John Statton; Matthew W Fraser; Gary A. Kendrick; Elizabeth A Sinclair; Gorman, D; Vanderklift, M; Verduin, J; Ian M. McLeod (2019)
Integrated economic frameworks can be used to understand the trade-offs between different marine habitat restoration projects, and establish which restoration configurations will deliver the largest benefits relative to costs. Here we use a benefit-cost analysis to explore how key factors influence the viability of seagrass restoration projects in Western Australia. We compared the costs of: replanting and reseeding methods, professional and volunteer-based methods, urban and remote locations, and, different spatial extents. Economic benefits were estimated for the carbon sequestration capabilities of restored meadows, and for the non-market (intangible) values that seagrass habitats generate. With the exclusion of the professional-labour replanting scenarios, where costs exceeded benefits, all scenarios had positive net present values. Contingent on the assumptions made, the most worthwhile investments are larger-scale, volunteer-based restoration projects that employ the reseeding method.
Keywords: benefit-cost analysis; integrated economic framework; non-market value; restoration; seagrass; valuation

Broad-scale movements of juvenile white sharks Carcharodon carcharias in eastern Australia from acoustic and satellite telemetry - Barry Bruce; David Harasti; K. A. Lee; C. Gallen; R. W. Bradford (Marine Ecology Progress Series, 2019)
The advent of electronic tagging has seen vast advances in our understanding of marine top-order predator movements over broad spatial scales. However, most studies are restricted to short temporal scales. We examine movements of 43 juvenile white sharks (1.7 to 3.2 m total length) in eastern Australia via satellite linked radio tags (SLRT) and internally implanted long-life acoustic tags, the latter monitored by receiver arrays spanning a continental-scale and across international boundaries. Although SLRT data were restricted to less than two years, the study registered approximately 182,000 detections of acoustic-tagged white sharks on 287 receivers over seven years, with individual tracking periods of up to five years. Data reveal complex movement patterns over distances of thousands of kilometres and 13 degrees of latitude, with sharks ranging from the southern Great Barrier Reef, Queensland, to Tasmania and across the Tasman Sea to New Zealand. Sharks showed a variety of movement patterns including annual fidelity to spatially restricted nursery areas, directed seasonal coastal movements, intermittent areas of temporary nearshore residency and offshore excursions into the Tasman Sea. Movements east to west through Bass Strait were restricted, further supporting the two-population model for the species in Australian waters. The latitudinal range of movements increased with years at liberty and female sharks were more commonly encountered than males in nearshore waters. Long-term monitoring of acoustic-tagged sharks via data sharing through collaborative national and international receiver arrays offers future promise to examine movements over periods relevant to ontogenetic changes and at scales providing context to interannual variability.
Keywords: Australia’s Integrated Marine Observing System (IMOS); nursery area; migration

Can bivalve habitat restoration improve degraded estuaries? - Ian M. McLeod; Zu Ermgassen, P.S.E.; Chris L Gillies; Hancock, Boze; Humphries, Austin (Coasts and Estuaries - The Future, 2019)
Bivalve habitats have, until recent times, been generally overlooked as an important estuary habitat type. Historically, complex, three-dimensional habitats made up of dense aggregations of bivalves, their shells, associated species, and accumulated sediments were a dominant habitat type in temperate and subtropical estuaries around the world (Stenzel, 1971). These habitats were generally engineered by oyster (generally referred to as reefs) or mussel (generally referred to as beds) species. Until recent times these habitats were primarily managed as an important fisheries resource. Their historical extent and importance are difficult to estimate because bivalve habitats were often decimated before fisheries records were collected systematically, and there may be no remaining visible functioning bivalve habitats. Through the process of historical amnesia, or shifting baselines, successive generations of local people, and managers have grown accustomed to the new norm and have forgotten about the former abundant bivalve habitats
Keywords: environmental management; estuary; oyster; oyster reef; restoration

Categorising use patterns of non-marine environments by elasmobranchs and a review of their extinction risk - Michael I. Grant; PM Kyne; Colin Simpfendorfer; William T White; A Chin (Reviews in Fish Biology and Fisheries, 2019)
As the state of non-marine aquatic environments (freshwater and estuarine environments with salinities ≤ 30 ppt) continues to decline globally, there is increasing concern for elasmobranchs (sharks and rays) that use them at critical stages of their life history. Due to a range of impediments including unresolved taxonomy, lack of fisheries data, and poor public perception, our knowledge of elasmobranchs in non-marine environments has lagged behind marine species. Here, we refine previous categorisations of elasmobranchs that occur in non-marine environments by reviewing the timing and duration of freshwater (≤ 5ppt) and/or estuarine (> 5 to ≤ 30 ppt) habitat use throughout each species’ life history. We identified five categories describing elasmobranchs in non-marine environments: (1) freshwater obligates (43 spp.); (2) euryhaline generalists (10 spp.); (3) estuarine generalists (19 spp.); (4) non-marine transients; (5) non-marine vagrants. Criteria for species inclusion is provided for all categories, and species lists are presented for categories 1–3. Euryhaline and estuarine generalists had the highest number of species that are threatened with extinction on the IUCN Red List of Threatened Species (50% and 65%, respectively), and freshwater obligate species have a very high portion of Data Deficient and Not Evaluated species (77%). The refinement of non-marine elasmobranch categories will aid in our understanding of elasmobranchs that occur in non-marine environments, helping facilitate more strategic conservation and management initiatives. Research on the biology of elasmobranchs and their human interactions in non-marine environments are suggested, as this will lead to better availability of information for conservation and management. Shareable Link Anyone you share the following link with will be able to read this content: https://rdcu.be/bRuYx Provided by the Springer Nature SharedIt content-sharing initiative.
Keywords: Conservation; Elasmobranchs; estuaries; euryhaline; freshwater; management

Challenges for global ocean observation: the needfor increased human capacity - Miloslavich, Patricia; Seeyave, Sophie; Muller-Karger, Frank; Nicholas J. Bax; Ali, Elham; Delgado, Claudia; Evers-King, Hayley; Loveday, Benjamin; Lutz, Vivian; Newton, Jan; Nolan, Glenn; Peralta Brichtova, Ana C.; et al. (Journal of Operational Oceanography, 2019)
Sustained global ocean observations are needed to recognise, understand, and manage changes in marine biodiversity, resources and habitats, and to implement wise conservation and sustainable development strategies. To meet this need, the Global Ocean Observing System (GOOS), a network of observing systems distributed around the world and coordinated by the Intergovernmental Oceanographic Commission (IOC) has proposed Essential Ocean Variables (EOVs) that are relevant to both the scientific and the broader community, including resource managers. Building a network that is truly global requires expanding participation beyond scientists from well-resourced countries to a far broader representation of the global community. New approaches are required to provide appropriate training, and resources and technology should follow to enable the application of this training to engage meaningfully in global observing networks and in the use of the data. Investments in technical capacity fulfil international reporting obligations under the UN Sustainable Development Goal 14A. Important opportunities are emerging now for countries to develop research partnerships with the IOC and GOOS to address these obligations. Implementing these partnerships requires new funding models and initiatives that support a sustained research capacity and marine technology transfer.
Keywords: capacity development; EOVs; essential ocean variables; global ocean observing system; GOOS; ocean observations; sustainable development goal 14 (SDG14)

Close-Kin Mark-Recapture population size estimate of Glyphis garricki in the Northern Territory - Mark Bravington; Pierre Feutry; Richard D. Pillans; Hillary, Rich; Grant Johnson; Thor Saunders; R. Gunasekera; Nicholas J. Bax; PM Kyne (2019)
The Endangered Northern River Shark Glyphis garricki (family Carcharhinidae) is found only in northern Australia and southern Papua New Guinea. It is a euryhaline species inhabiting tidal rivers and estuaries with all life stages (neonates to adults) recorded in rivers, while adults have also been recorded in marine waters. During surveys under the National Environmental Research Program (NERP) and the National Environmental Science Program (NESP), samples were collected in the Northern Territory in the rivers of Van Diemen Gulf (VDG) and the Daly River, and in the Kimberley region of Western Australia, from Cambridge Gulf and King Sound. Previously, the species was only known from a very limited number of records (~40) and these surveys have shown its range to be more widespread than initially documented. It is also likely that the species will be recorded in other rivers and estuaries with suitable habitat as more surveys are undertaken. For the purpose of this report, the VDG encompasses the Alligator Rivers region west to the Adelaide River. Based on recent genetic population structure research, the VDG population appears demographically separate from other known populations in the western part of its range, which in turn are separate to each other. The aim of this study was to apply Close-Kin Mark-Recapture (CKMR) to G. garricki to estimate population size within the Northern Territory. Samples were collected from six rivers and creeks flowing into VDG (from east to west): East Alligator River, South Alligator River, West Alligator River (collectively, these three rivers make up the ‘Alligator Rivers’), Wildman River, Sampan Creek, and the Adelaide River. While sampling has been conducted across the Australian range of the species (i.e. Daly River, Cambridge Gulf, King Sound), limited sample size outside the VDG prohibited the application of a CKMR model and therefore the focus of this study is the VDG.
Keywords: close-kin mark-recapture; Northern River Shark; Northern Territory; population size; threatened species; Van Diemen Gulf

Code Red Project Handfish - Rick D Stuart-Smith; T P Lynch; Jemina F. Stuart-Smith; Bryony Bennett (2019)
Tasmania’s Red Handfish and Spotted Handfish are Critically Endangered and human activities are intensifying in much of their remaining coastal habitat. Only swift, coordinated action backed by research, government, industry and the community can save them from extinction. The Marine Biodiversity Hub is helping to facilitate these activities, which are part of the Handfish Conservation Project. Related information: News item - One patch two patch: last stand for the Red Handfish? Request a copy of the poster Download a pdf of the poster at Item link below Marine Hub Project A10 - Conservation of spotted handfish and their habitat Handfish Conservation Project - www.handfish.org Download the Fact Sheet - Conserving the Critically Endangered Red Handfish
Keywords: critically endangered; eco-moorings; fish; habitat restoration; handfish

Conservation of handfish and their habitats – Annual Report 2018 - T P Lynch; Tyson Bessell; Alexander Hormann; C Devine (2019)
In 2018 we completed the fourth round of annual performance assessment surveys for spotted handfish across the 9 Derwent Estuary study sites. This provides 62 data points in total, with 36 points from our NESP work building on our 26 data points from previous studies. Two results of interest from this year were the discovery of fish, after a year’s absence, at the Ralphs Bay site and a continued decline in numbers at Mary Anne Bay. For the Ralphs Bay site the fish are still in very low numbers, which is consistent with what we have observed since 2015. This suggests that when densities of fish dip below 3-5 fish per hectare then the monitoring program does not have the sensitivity to reliably detect their presence. For the Mary Anne Bay site the recent trend has seen a decline in numbers back to levels that are more commonly seen at numerous other sites. Several student projects this year provided important context to both this results and conservation of the species in general. The first of these were some preliminary results from Mr Alex Hormanns’ UTAS Masters project. This involved the planting of 5000 Artificial Spawning Habitats (ASH) into 5 site based arrays, made up of 50:50 mixes of plastic and ceramic ASH. When we surveyed the arrays numerous eggs masses were being guarded by fish who had spawned onto ASH, with the fish showing a preference for ceramic over plastic ASH. The relative use of ceramic ASH was also higher than the raw numbers suggested as ceramics had a lower survival rate than plastic, with 1964 plastic and 1524 ceramic ASH or 3488 out of the 5000 remaining at the end of the surveys. One variable that seems to explain the amount of ASH used at a particular site was the densities of stalked ascidian which provide natural spawning habitat. Sites that had ascidian densities larger than 0.05 per m2 saw very low ASH use. The sites that saw the most ASH use had relatively low densities of both ascidians and spotted handfish. We have now incorporated ascidian counts into the monitoring program and will use these data to plan further ASH planting. The second piece of information was from Mr Tyson Bessell’s UTAS honours project (first class), ‘Biological Parameters of the Spotted Handfish’. This work demonstrated the accuracy of the I3S autonomous pattern recognition program for identifying spotted handfish – this allowed us to exclude technical issues as a reason for low recapture rates. Tyson then used both recapture data of repeated length measurements of wild fish in combination with a small number of opportunistically collected otoliths to model the age of the fish. The oldest fish in the population appear to be 10 years old, however based on length frequency data only 10% of the fish within the sample population are older than 5 years. Sexual maturity occurs around 2 years of age so most fish will have a 1-3 year window of opportunity to reproduce. Important caveats to this work are that it is based on a limited number of both recaptures (n=13) and otoliths (n = 7) and only one otolith was from a female. From our new insights into handfish biology and conservation we are starting to be able to develop an understanding of the species local population dynamics. Aspect of our monitoring program that have previously remained un-explained were: trends of declines across years, variability between years and increases in densities between the current and historic data, as well as low recapture rates. These site population dynamics and re-capture rates may now be explainable based on the relatively short lifespan of the species and spawning success related to the availability of natural or artificial spawning habitat. While our monitoring program can provide density estimates, the likelihood of recapturing an individual with is low due to rapid natural mortality (90% dead two years after first capture) when placed in the context of annual sampling. Also, if stalked ascidians density are by nature stochastic then there will be problems with recruitment, especially if stochasticity increases or there is a long-term average decrease in ascidians or other natural spawning habitat due to grazing by introduced marine pests or changes to catchment processes. If spawning fails or is reduced then declines over time periods 1-4 years will occur as cohorts pass through their breeding period and natural mortality cumulatively removes most individuals from local populations. This relatively short lifespan is also of importance to efforts to captive breed the species. While animals bred in captivity in 2017, none did in 2018. Clearly solutions to enhance breeding will need to be found quite quickly before the brood stock and captive bred fish die.
Keywords: Spotted handfish

Conserving the Critically Endangered Red Handfish - Fact Sheet - Rick D Stuart-Smith (2019)
The Red Handfish (Thymichthys politus) is arguably one of the rarest marine fish species in the world, with an adult population estimated at about 100 in 2019. The species used to be common across south-eastern Tasmania and on the north coast, and was collected and painted at the Port Arthur penal colony in the 1800s. But extensive surveys in the past 15 years at historical sighting locations across its former range found populations at only two patches of shallow rocky reef in Frederick Henry Bay, each less than 70 metres long. Conservation The Red Handfish is listed under Australia’s Environment Protection and Biodiversity Conservation Act 1999 as Critically Endangered and is therefore protected in Tasmania. The International Union for the Conservation of Nature Red List of Threatened Species is being updated to recognise Red Handfish as Critically Endangered (considered to be facing extremely high risk of extinction in the wild). The National Handfish Recovery Team coordinates research and conservation efforts for the Red Handfish, as well as for the Spotted Handfish and Ziebell’s Handfish, through the Handfish Conservation Project (handfish.org.au). Related information Handfish Conservation Project www.handfish.org.au Poster - Code Red Project Handfish

Contrasting processes drive ophiuroid phylodiversity across shallow and deep seafloors - Tim O'Hara; Andrew F. Hugall; Skipton N. C. Woolley; Guadalupe Bribiesca-Contreras; Nicholas J. Bax (Nature, 2019)
Our knowledge of the distribution and evolution of deep-sea life is limited, impeding our ability to identify priority areas for conservation. Here we analyse, for the first time, large integrated phylogenomic and distributional datasets of seafloor fauna from sea surface to abyss and equator to pole of the Southern Hemisphere for an entire class of invertebrates (Ophiuroidea). We find that latitudinal diversity gradients are assembled through contrasting evolutionary processes for shallow (0-200m) and deep (> 200m) seas. The shallow-water tropical-temperate realm broadly reflects a tropical diversification-driven process but with exchange in both directions. Diversification rates are reversed for the realm containing the deep sea and Antarctica, being highest at polar and lowest at tropical latitudes, and net exchange is from high to low latitudes. The tropical upper bathyal (200-700m deep), with its rich ancient phylodiversity, is characterised by relatively low diversification and moderate immigration rates. Conversely, the young specialised Antarctic fauna is inferred to be rebounding from regional extinction associated with the rapid cooling of polar waters over the mid-Cenozoic. Media release - Research reveals new species are evolving fastest in Antarctica - 24 January 2019
Keywords: Antarctic speciation; Biogeography; phylodiversity

Coral reef monitoring, reef assessment technologies, and ecosystem-based management - Obura, David O.; Aeby, Greta; Amornthammarong, Natchanon; Appeltans, Ward; Nicholas J. Bax; Bishop, Joe; Brainard, Russell E.; Chan, Samuel; Fletcher, Pamela; Gordon, Timothy A. C.; Gramer, Lew; Gudka, Mishal; et al. (Frontiers in Marine Science, 2019)
Coral reefs are exceptionally biodiverse and human dependence on their ecosystem services is high. Reefs experience significant direct and indirect anthropogenic pressures, and provide a sensitive indicator of coastal ocean health, climate change, and ocean acidification, with associated implications for society. Monitoring coral reef status and trends is essential to better inform science, management and policy, but the projected collapse of reef systems within a few decades makes the provision of accurate and actionable monitoring data urgent. The Global Coral Reef Monitoring Network has been the foundation for global reporting on coral reefs for two decades, and is entering into a new phase with improved operational and data standards incorporating the Essential Ocean Variables (EOVs) (www.goosocean.org/eov) and Framework for Ocean Observing developed by the Global Ocean Observing System. Three EOVs provide a robust description of reef health: hard coral cover and composition, macro-algal canopy cover, and fish diversity and abundance. A data quality model based on comprehensive metadata has been designed to facilitate maximum global coverage of coral reef data, and tangible steps to track capacity building. Improved monitoring of events such as mass bleaching and disease outbreaks, citizen science, and socio-economic monitoring have the potential to greatly improve the relevance of monitoring to managers and stakeholders, and to address the complex and multi- dimensional interactions between reefs and people. A new generation of autonomous vehicles (underwater, surface, and aerial) and satellites are set to revolutionize and vastly expand our understanding of coral reefs. Promising approaches include Structure from Motion image processing, and acoustic techniques. Across all systems, curation of data in linked and open online databases, with an open data culture to maximize benefits from data integration, and empowering users to take action, are priorities. Action in the next decade will be essential to mitigate the impacts on coral reefs from warming temperatures, through local management and informing national and international obligations, particularly in the context of the Sustainable Development Goals, climate action, and the role of coral reefs as a global indicator. Mobilizing data to help drive the needed behavior change is a top priority for coral reef observing systems.
Keywords: climate change; Coral reef; ecological monitoring; Essential Ocean Variables (EOV); GOOS; social-ecological system

A cross continental scale comparison of Australian offshore recreational fisheries research and its applications to Marine Park and fisheries management - T P Lynch; C B Smallwood; Ochwada-Doyle, F A; Lyle, J; Joel Williams; K L Ryan; C Devine; Gibson, B; Alan Jordan (ICES Journal of Marine Science, 2019)
Recreational fishing is popular in Australia and is managed by individual states in consultation with the Commonwealth for those fisheries that they regulate and also for Australian Marine Parks (AMPs). Fishers regularly access both state and offshore Commonwealth waters but this offshore component of the recreational fishery is poorly understood. Our study tested the functionality of existing state-based surveys in Western Australia (WA) and New South Wales (NSW) to better inform Commonwealth fisheries and AMP managers about recreational fishing in their jurisdictions. Catch estimates for nine species of interest to the Commonwealth were developed and two case study AMPs [Ningaloo (WA) and The Hunter (NSW)] were also chosen to test the ability of the state survey data to be disaggregated to the park scale. As each state’s fishery survey designs were contextual to their own management needs, the application of the data to Commonwealth jurisdictions were limited by their statistical power, however aspects of each states surveys still provided useful information. Continued evolution of state-wide survey methods, including collection of precise spatial data, and regional over-sampling would be beneficial, particularly where there are multiple stakeholder and jurisdictional interests. National coordination, to temporally align state surveys, would also add value to the existing approaches. This free access link may be posted to your personal/institutional website. However, the article should only be viewed from the Oxford Academic website and not posted to your own personal/institutional web site or that of other third parties:  https://academic.oup.com/icesjms/advance-article/doi/10.1093/icesjms/fsz092/5513323?guestAccessKey=2fa16258-0c95-4961-8ceb-89ded3296082
Keywords: cross-jurisdictional fisheries; Hunter Marine Park; marine protected areas (MPAs); marine recreational fisheries (MRFs); national survey; Ningaloo Marine Park; offshore fisheries

Data discoverability and accessibility: Report from workshops on marine imagery and biological specimen data - Rachel Przeslawski; Falkner, Inke; Scott D Foster; Sebastien Mancini; Bainbridge, Scott; Narissa Bax; Andrew Carroll; Flukes, Emma; Gonzalez-Riviero, Manuel; Tim J. Langlois; Kirrily Moore; Rehbein, Mark; et al. (2019)
As the rate of marine data acquisition increases, so too does the need for that data to abide by the FAIR (findable, accessible, interoperable, reusable) principles. From the nation’s perspective, a coherent and assessable data source(s) enables smarter use and management of our marine estate. From a researcher’s perspective, open data can be advantageous by increasing citations, media attention, collaborations, jobs and funding opportunities. It is therefore vital that researchers and research organisations strive to release all marine metadata and data so that it is discoverable and accessible by the public. With the development of national standards (Field Manuals for Marine Sampling to Monitor Australian Waters), it became clear that we were unable to advocate a national standard for data release for many data types (bathymetry, marine imagery, biological specimen data) because we either do not yet have suitable digital infrastructure or clear links between existing infrastructure. To meet these challenges, workshops were held in the months following the release of the field manuals, focusing on issues with data discoverability and accessibility for two major data types: Marine imagery was the focus of a Data Discoverability and Accessibility Workshop hosted by the NESP Marine Hub and the Australian Ocean Data Network (AODN) on 6-7 September 2018 at Geoscience Australia in Canberra. Biological specimen data was the focus of a Data Discoverability and Accessibility Workshop hosted by the NESP Marine Hub and the AODN on -77 September 2018 at CSIRO in Hobart. This report describes the findings of these two workshops.
Keywords: biological specimens; open data; underwater imagery

Description and characterisation of Terranova pectinolabiata n. sp. (Nematoda: Anisakidae) in great hammerhead shark, Sphyrna mokarran (Rüppell, 1837), in Australia - Shamsi, Shokoofeh; D Barton; Zhu, Xiaocheng (Parasitology Research, 2019)
Terranova pectinolabiatan. sp. is described from the great hammerhead, Sphyrna mokarran, from Australian waters. This represents the first report of a species of Terranova from the host species. The new species is characterised by the morphology of the caudal plates and labia. ITS sequences were obtained for 20 specimens which were identical, despite morphological variation that has traditionally been indicative of separation of species. Additionally, genetic analyses confirmed the identification of the larval Terranova Type II previously reported in Australian and New Caledonian waters as Terranova pectinolabiatan. sp. As part of the Springer Nature SharedIt initiative, you can now publicly share a full-text view-only version of your paper by using the link <a href="http://antispam.csu.edu.au:32224/?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" rel="nofollow">https://rdcu.be/bFC04

Description of Piscicapillaria bursata sp. nov. (Capillariidae) and Redescription of Parascarophis sphyrnae Campana-Rouget, 1955 (Cystidicolidae), Two Nematode Parasites of Hammerhead Sharks (Sphyrna spp.) off Australia - Moravec, F; D Barton (Acta Parasitologica, 2019)
Purpose Data on helminth parasites in hammerhead sharks are scarce and, therefore, new examinations of these hosts are needed to recognize the species composition of their parasites, including nematodes. Methods Helminthological examinations of hammerhead sharks, Sphyrna lewini (Griffith et Smith) (209 specimens) and Sphyrna mokarran (Rüppell) (57 specimens) (Sphyrnidae, Carcharhiniformes), from off the northern coast of Australia revealed one new and one insufficiently known species of intestinal nematode parasites. These were studied with the use of light and scanning electron microscopy. Results Both nematode species are described. Piscicapillaria bursata sp. nov. (Capillariidae) from S. mokarran (type host) and S. lewini differs from its congeners mainly in the spicule length (330 µm), body length of gravid females 12.80–21.26 mm and in possessing a subterminal female anus. The specimens of Parascarophis sphyrnae Campana-Rouget, 1955 (Cystidicolidae) (type species of Parascarophis Campana-Rouget, 1955) collected from S. lewini made it possible to redescribe the female and, for the first time, to describe the male; the same species was also found in S. mokarran. Amended diagnosis of Parascarophis is provided. Parascarophis is mainly characterized by the presence of lateral alae, a unique feature within the Cystidicolidae, and by the cephalic structures (presence of a cuticular hood and a pair of anterolateral plate-like structures in the mouth). Conclusions In addition to the discovery of a new nematode species, Pi. bursata sp. nov., the finding of Pa. sphyrnae in Australian waters represents a new geographical record of this parasite outside the Atlantic Ocean. The species of Parascarophis previously described from teleosts, P. bharatii Agrawal, 1965, P. oteroi Arya, 1992 and P. mulloidi Imam, Tawfik et Abdel Hady, 1982, are designated as species inquirendae and incertae sedis. The finding of P. sphyrnae in Australian waters represents a new geographical record of this parasite outside the Atlantic Ocean. Pa. sphyrnae had not been reported previously from beyond the Atlantic Ocean.
Keywords: Australian waters; Habronematoidea; Parasitic nematode; Sphyrnidae; Trichinelloidea

Designing Monitoring Programs for Marine Protected Areas Within an Evidence Based Decision Making Paradigm - Keith R. Hayes; G.R. Hosack; E Lawrence; Paul Hedge; Neville Barrett; Rachel Przeslawski; Caley, M.J.; Scott D Foster (Frontiers in Marine Science, 2019)
The Evidence Based Decision Making (EBDM) paradigm encourages managers to base their decisions on the strongest available evidence, but it has been criticized for placing too much emphasis on the choice of study design method without considering the types of questions that are being addressed as well as other relevant factors such as how well a study is implemented. Here we review the objectives of Australia’s Marine Park network, and identify the types of questions and data analysis that would address these objectives. Critically, we consider how the design of a monitoring program influences our ability to adequately answer these questions, using the strength of evidence hierarchy from the EBDM paradigm to assess the adequacy of different design strategies and other sources of information. It is important for conservation managers to recognize that the types of questions monitoring programs are able to answer depends on how they are designed and how the collected data are analyzed. The socio-political process that dictates where protected areas are placed typically excludes the strongest types of evidence, Random Controlled Trials (RCTs), for certain questions. Evidence bases that are stronger than ones commonly employed to date, however, could be used to provide a causal inference, including for those questions where RCTs are excluded, but only if appropriate designs such as cohort or case-control studies are used, and supported where relevant by appropriate sample frames. Randomized, spatially balanced sampling, together with careful selection of control sites, and more extensive use of propensity scores and structured elicitation of expert judgment, are also practical ways to improve the evidence base for answering the questions that underlie marine park objectives and motivate long-term monitoring programs.
Keywords: causality; design methodology; EBDM; marine protected area; monitoring

The eastern Australian Marine Parks: biodiversity, assemblage structure, diversity and origin - Tim O'Hara (2019)
The IN2017_V03 expedition of Australia’s premier research vessel ‘Investigator’ was the first to systematically sample lower bathyal to abyssal habitats (2000-5000 m) in Australia’s Exclusive Economic Zone. It traversed seven newly declared marine parks in Commonwealth waters off the eastern margin of Australia from 15th May to 16th June 2017, including Freycinet, Flinders, East Gippsland, Jervis, Hunter, Central Eastern and Coral Sea Marine Parks. The voyage mapped much of the deeper water habitats of these parks using high resolution multi-beam data and systematically sampled the habitats, principally using video transects, small beam trawls and epibenthic sleds. The scientific objectives of the voyage included: Describe latitudinal and bathymetric patterns of biodiversity of Australia’s eastern bathyal (1000-2500 m) and abyssal (4000 m) fauna from 42 to 24°S. Test whether patterns of latitudinal turnover described for the shelf and upper bathyal are replicated at deeper depths. Survey and photograph the lower-bathyal and abyssal ecosystem of Commonwealth marine parks for the first time. Describe the faunal communities and correlate biodiversity patterns against measured and modelled oceanographic and geological environmental factors. Sequence DNA of selected species to examine the evolutionary history of the fauna. Convey the excitement of deep-sea marine science and the conservation importance of Australian Marine Parks to the general public by having specialised science communicators on the voyage. A further objective of the NESP Marine Biodiversity hub was to compare the community composition and richness of beam trawl samples between the IN2017_V03 survey and the various surveys (IN2015_C01, IN2015_C02, IN2017_C01) recently conducted in the Great Australian Bight. We report here on a diverse set of products and outcomes ranging from real-time information products, delivered through daily blogs and YouTube videos, to a new fundamental understanding of the origins of deep sea biodiversity over the last 100 million years based on new and existing data. This diversity of products was only possible because of the resources and effort given to collaborations, both with communication experts and management agencies (especially Parks Australia) for the extensive communication products, and ecologists and taxonomists over many years for the biogeographic products. Consistent approaches, best practice and verified taxonomies are just some of the tools needed to support these long-term collaborations that enable the results from this “voyage to the abyss” to have a far greater and more enduring impact than might be expected from a single marine survey. This report contains the analyses and results from these objectives and is structured as follows. Chapter 1: contains descriptions, maps, seafloor imagery and representative animals that were found to occur in the seven Marine Parks surveyed. These samples provide a baseline for understanding how AMPs are distributed with regard to deep sea biogeography. Chapter 2: describes the novel biodiversity highlights of the voyage across the dominant faunal groups from sponges to fish. Taxonomic investigations are ongoing, but to date the total number of taxa identified is 1061 from 25,661 specimens, predominantly from the 35 beam trawl samples but also including some taxonomic groups from the 28 Brenke sled samples. Of these taxa, only 405 could be assigned scientific names, indicating that up to 60% of the fauna is new to science. This chapter has been submitted for publication in the scientific journal “Marine Biodiversity Records”. Chapter 3: uses model-based statistics to explore patterns of latitudinal diversity along the east continental margin of Australia at bathyal and abyssal depths. The results indicate that separate faunas occur at each bathymetric layer analysed (~1000, 2500 and 4000 m) and that each of these bathymetric assemblages is separated into a temperate and tropical subgroups. The results are of international significance as this is the first time a temperate-tropical transition has been reported from the deep-sea. This transition occurs despite almost uniform temperature, salinity and dissolved oxygen concentrations occurring across latitudes at these depths. Conversely, the flux of organic matter to the seafloor does vary with latitude, from being relative high in the productive temperate off Tasmania and Bass Strait to low in more-oligotrophic tropical waters, and may drive large scale faunal distribution patterns. This chapter has been submitted for publication in the scientific journal “Deep Sea Research I”. Chapter 4: uses model-based statistics to analyse the difference in abundance, richness and evenness for lower bathyal and abyssal beam trawl samples from the Great Australian Bight and from off the east Australian margin. The results indicate that samples from off SE Australia have the highest abundance and species richness. These indices are correlated with levels of particulate organic carbon flux to the seafloor, which is higher under the seasonal plankton bloom around Tasmania and Bass Strait. The greater abundance leads to increased species richness. Evenness was most closely associated with the seasonality of net primary production. The samples from the Great Australian Bight were collected north of the enhanced temperate plankton belt and thus do not show elevated abundance or richness. However, they are compositionally distinct from samples from the east coast. Some taxonomic groups, such as sponges, are represented by an almost totally distinct set of species. The lower bathyal and abyssal fauna of the Great Australian Bight is thus compositionally different from other sampled regions. Additional sampling, particularly from off the south-western Australian coast and western Bass Strait, is required to determine the spatial extent of this fauna. This chapter has been submitted for publication in the scientific journal “Diversity and Distributions”. Appendix A: is a pre-print of a paper published in the scientific journal Nature in January 2019 1. This paper combined DNA sequences from animals collected on the IN2017_V03 voyage with a large dataset accumulated for a previous Marine Biodiversity Hub project (on marine phylogenetic endemism) to examine the origin and regional evolutionary trajectory of the marine fauna from Australia to Antarctica. This project focused on brittle stars, a group of echinoderms that are abundant across the seafloors and make an ideal group to research large scale patterns of marine biodiversity. The results show that patterns of diversity in the deep sea (seafloors deeper than 200 m) were profoundly different from those in shallow water. Although the number of species and genetic diversity were much higher in the tropics at all depths, evolution appears to have proceeded differently in shallow and deep seas. Shallow water patterns were like those that occur on land, tropical regions were generating more species than colder areas. This conforms to the well-known theory that higher temperatures increases evolutionary processes. However, the reverse was true for the deep sea. Speciation rates were highest in the coldest region (Antarctica) and lowest in the tropical deep sea.
Keywords: abyssal; Bathyal; Biodiversity; Central Eastern MP; Coral Sea MP; East Gippsland MP; Flinders MP; Freycinet MP; Hunter MP; Jervis MP; Seaflooor

An eco-narrative Kimberley Marine Park - North west marine region - Puotinen, ML; Ronen Galaiduk; Karen J Miller; Nanson, Rachel; Z Huang; Scott L Nichol (2019)
This report is one in a series of eco-narrative documents that synthesise our existing knowledge of Australia’s individual Marine Parks. This series is a product of the National Environmental Science Program Marine Biodiversity Hub Project D1, which seeks to collate, synthesise and visualise biophysical data within the parks. These documents are intended to enable managers and practitioners to rapidly ascertain the ecological characteristics of each park, and to highlight knowledge gaps for future research focus. Kimberley Marine Park is characterised by a gently sloping seabed comprising platforms and terraces, crossed by a series of valleys and channels that incise 20 – 50 m into the seabed. These valleys define the ancestral pathways of the larger rivers that drain to the modern Kimberley coast, and where mapped in high resolution preserve the form of coastal estuaries. Today, these rivers do not supply large volumes of sediment to the offshore, with sediments in the marine park dominated by relict marine carbonates. Areas of stable hardground are restricted to small, flat-topped banks that rise to several metres above surrounding seabed. The oceanographic regime of the park is characterised by strong tidal currents, with the additional dynamic of internal waves that set-up strong currents with the capacity to transport sand as bedload. Together, these hydrodynamic conditions produce relatively turbid conditions and fields of large bedforms up to 8 m high. The regional-scale Holloway Current that feeds warm, oligotrophic waters from the north also influences the oceanography of the park. As a result, the surface waters have relatively low primary productivity. The marine fauna observed within the park include a range of megafauna, notably humpback whales, dugong and turtles. The latter include a variety of turtle species that nest on islands outside Kimberley Marine Park (e.g. Lacepede Islands), but which have been tracked moving through the park. Similar tracking of humpback whales provides evidence that the park overlaps their migration route. Information on demersal fish and sharks within the park is lacking and is based on regional studies that suggest a high degree of endemism among the offshore fish species. Evidence of climate change influence in the Kimberley offshore region is provided in the sea surface temperature record, which shows a clear warming trend that is slightly higher than the national average; coupled with the impact of marine heat waves. The benthic biological communities within Kimberley Marine Park include sessile and infaunal communities that are broadly typical of tropical northern Australia, though our knowledge of these assemblages is limited to a small number of surveys in targeted areas (e.g. Lynher Bank in the south of the park). These surveys observed relatively sparse epifauna communities, but included a number of species of coral and sponge that were observed for the first time in the park. It is therefore likely that the diversity of corals and sponges remains underestimated. Further sampling of these benthic communities is therefore warranted. The information in this eco-narrative forms an initial characterisation of Kimberley Marine Park.
Keywords: Geomorphology; megafauna; North-west marine region; seabed; shelf habitats

An eco-narrative of Huon Marine Park - South-east marine region - Vanessa L Lucieer; Jacquomo Monk; Z Huang; Scott L Nichol; Karen J Miller; Williams, Alan (2019)
This report is one in a series of eco-narrative documents that synthesise our existing knowledge of individual Australian Marine Parks. This series is a product of the National Environmental Science Program Marine Biodiversity Hub Project D1, which seeks to collate, synthesise and visualise biophysical data within the parks. These documents are intended to enable managers and practitioners to rapidly ascertain the ecological characteristics of each park, and to highlight knowledge gaps for future research focus. Huon Marine Park is characterised by a diversity of seabed habitats, ranging from low profile reefs and sediment plains on the continental shelf to a cluster of seamounts on the continental slope and low gradient plains on the continental rise. The shelf reefs and seamounts are the better documented habitats within the park and are the focus of this initial characterisation of the park. Recent opportunistic seafloor surveying and accumulated transit data from the Marine National Facility (MNF) has revealed an extensive rocky reef system in the north east corner of the park that extends from the reserve boundary (~53 m depth) to around the 100 m depth contour. Whilst there has been little biological survey effort to characterise these reef systems, some information is available from occasional IMOS Autonomous Underwater Vehicle (AUV) surveys and a small number of video tows. These data indicate a moderate to high-profile reef system that is generally deeper than the photic zone and is predominantly covered in a dense but low-profile mix of sessile invertebrates, including sponges, bryozoans, soft corals and seawhips. This sponge-dominated invertebrate community appears to be heavily “pruned” by the influence of high energy Southern Ocean swells (wave heights more than 10 m) that regularly impact this region which presumably remove the larger invertebrates due to drag and/or sand-blasting. In the shallower northern boundary region of the park there is sufficient light for some red algal growth, however, this is at the margins of photic depth and primarily restricted to a low cover of encrusting coralline algae. Overall, the surface waters of Huon Marine Park are characterised by moderate to high productivity, as shown by satellite-derived measures of chlorophyll-a that show the park is among the top 10 for productivity of all Australian Marine Parks. Satellite data also show the park is experiencing a clear trend of warming within its surface waters and is within the reach of marine heat waves through connectivity with the East Australian Current. Despite the high wave energy environment, the shelf reef habitats of the Huon Marine Park appear to be quite productive. This productivity is evident on the shelf reefs, where a high-density lobster population is recorded, both from counts in AUV surveys (53-85 m depth) and the regular use by the Tasmanian lobster fishing industry. Less is known about associated fish assemblages on these reefs, although from the limited video footage available, key species include schooling butterfly perch and rosy wrasse. For the deep water habitats of the seamounts, a series of biodiversity voyages have documented a rich benthic fauna, notably across their upper slopes. The most recent benthic habitat survey was conducted on RV Investigator voyage IN2018-V06 during November-December 2018, titled “Status and recovery of deep-sea coral communities on seamounts in iconic Australian marine reserves” it included areas first surveyed 20 years ago, some of which were subsequently closed to trawling. The voyage found some indications of change among benthic fauna on seamounts that had been previously trawled and are now protected within the park. Further research is needed to adequately describe the resident fish assemblages on shelf reef and sediments in the Huon Marine Park, as well as improving our understanding of shelf-break habitats and biological assemblages where there is currently very little available knowledge. This additional research could include a re-survey of the seamounts to monitor for recovery of previously trawled areas of the park.
Keywords: Biodiversity; Huon marine park; Seamounts; southeast marine park network

An eco-narrative of Joseph Bonaparte Gulf Marine Park – North marine region - Ronen Galaiduk; Z Huang; Karen J Miller; Nanson, Rachel; Rachel Przeslawski; Scott L Nichol (2019)
This report is one in a series of eco-narrative documents that synthesise our existing knowledge of individual Australian Marine Parks. This series is a product of the National Environmental Science Program Marine Biodiversity Hub Project D1, which seeks to collate, synthesise and visualise biophysical data within the parks. These documents are intended to enable managers and practitioners to rapidly ascertain the ecological characteristics of each park, and to highlight knowledge gaps for future research focus. Joseph Bonaparte Gulf Marine Park is representative of the broad inner continental shelf of tropical northern Australia that is influenced by seasonal river inflow, strong tidal currents and regular cyclones. This combination produces a dynamic oceanographic setting within the marine park, characterised by high turbidity, rich nutrient levels and active sediment transport. The seabed within the park incorporates incised valleys and channels, tidal sand bars, gently sloping plains and small areas of localised reef. The valleys provide bathymetric relief of up to 40 m and define the ancestral pathways of the large rivers that drain into Joseph Bonaparte Gulf, including the Ord, Victoria and Daly Rivers. These offshore valleys were last active as rivers during the last ice age (ca. 18,000 – 10,000 years ago) when global sea level was tens of meters lower than present. Today, these valleys provide a conduit for the tidal transport of terrestrial sediments, mixed with carbonate marine sands. Tidal currents also shape the sand bars, which rise up to 15 m above the seabed and extend up to 20 km offshore. Reefs are restricted to small patch reefs in the northern part of the park, where they rise to within 2-3 m of the sea surface. Our knowledge of biological communities associated with these features is limited. By inference from other studies further offshore in the Gulf, the patch reefs are likely to support sparse sponge and soft coral communities. Similar sessile assemblages are also expected to occur along the steeper side of incised river valleys. The park intersects the known distribution area for a range of pelagic megafauna, including a variety of dolphins and turtles. However, the park is not expected to be a major area for dugong, given the lack of seagrass, and the area is too shallow for whales. With proximity to coastal estuaries, the park overlaps the known range for the endangered Northern River shark, sawfish, stingray and catfish; plus a range of demersal tropical fish species. The park is not without environmental pressures, with evidence for a consistent trend of warming surface waters and marine heat waves which can affect the health of the ecosystem at upper trophic levels. The region is also impacted by recreational and commercial fishing activities. The former are concentrated offshore from the Ord River mouth (Cambridge Gulf), whereas the latter range across the Joseph Bonaparte Gulf targeting prawns, barramundi and threadfin salmon. All these fishing activities result in some degree of direct and indirect impacts, including bycatch of a range of fish, invertebrates, sea snakes and sea birds. The information in this eco-narrative forms an initial characterisation of Joseph Bonaparte Marine Park. Related information Australian Marine Parks Science Atlas
Keywords: Australian Marine Parks; eco-narrative; ecological values

Estimating growth in juvenile white sharks using stereo baited remote underwater video systems (stereo-BRUVs) - Final report - David Harasti; Joel Williams; R. W. Bradford (2019)
This report provides a summary of a two-year study using stereo baited remote underwater video stations (stereo-BRUVs) to assess the viability of using this sampling method to obtain estimates of growth in juvenile white sharks. Surveys were conducted off Bennetts Beach, Hawks Nest, on the New South Wales mid-north coast monthly from January 2017 to December 2018 with six stereo-BRUV units deployed three times each month. A total of 2,160 hours of video footage was collected and analysed for the presence of white sharks. Over the two year period, a total of 142 white shark sightings were recorded on the stereo-BRUVs. The abundance of white sharks observed on the stereo-BRUVs was highest in November with an average of 4.3 ± 1.1 sightings per day. Overall significantly fewer sharks were sighted during autumn (March to May) than in other seasons, with no significant difference in sightings detected among the other seasons. The average size of white sharks observed on stereo-BRUVs was 191.1 cm ± 2.4 cm, with no significant difference in average size detected between seasons. A total of seven white sharks tagged with acoustic transmitters were observed on the stereo-BRUVs. Of these, the largest observed growth in a white shark occurred for a shark first tagged in October 2015 at 198 cm (fork length) that was remeasured at 259 cm in November 2017, giving an increase in length of 61 cm over the ~700 day period between tagging and stereo-BRUV measurement. This study demonstrates that stereo-BRUVs are a useful sampling method for recording the presence of white sharks in an area, and that stereo-BRUVs provide a useful non-intrusive method to obtain estimates of shark length and growth.
Keywords: BRUVs; Carcharodon carcharias; nursery area; Port Stephens; sharks

Estimating the value of tropical coastal wetland habitats to fisheries: Caveats and assumptions - K Abrantes; Sheaves, Marcus; Fries, Jakob (PLOS ONE, 2019)
Habitat valuation can provide an objective basis for the prioritisation of conservation and restoration actions. The attribution of fisheries production to particular habitat units is an important measure of value, but is difficult to estimate. Using the case study of habitat use by juvenile banana prawns in a tropical estuary, we assessed the potential to produce valid value estimates at two spatio-conceptual scales: estuary reach and whole estuary. Additionally, we also explore the potential to produce meaningful value estimates at the scale of whole estuary contribution to the offshore fisheries stock. A diversity of potential and actual sources of error and logical problems means that quantification at any scale is at best of uncertain validity and produces estimates that are likely to produce unreliable results if treated as quantitative inputs to production models. Estimates for the whole estuary were the most viable, although still requiring substantial assumptions that may or may not be reasonable in particular situations. Estimates for individual habitats required the unreasonable assumption of limited prawn movement, while estimates of contribution of an estuary to the fishery required difficult-to-obtain and usually unavailable information. Because low occupancy habitats can have trophic value, we also used stable isotope analysis to assess the importance of mangroves and saltmarshes to prawn nutrition. No particular habitat was of critical trophic importance, again suggesting that the habitat-production link is most usefully assessed at the whole-of-estuary scale. While valuable and required to support targeted ecosystem management and protection and restoration efforts, valid estimates of the contribution of particular units to fisheries are likely to be unachievable in many situations.
Keywords: banana prawns; Conservation; habitat evaluation; restoration; tropical estuary; wetlands

The extinction risk of New Zealand chondrichthyans - Finucci, Brittany; Duffy, Clinton A.J.; Malcolm P. Francis; Gibson, Claudine; PM Kyne (Aquatic Conservation: Marine and Freshwater Ecosystems, 2019)
The national extinction risk of 103 New Zealand chondrichthyans (sharks, rays, and chimaeras), ~10% of the global chondrichthyan fauna, was evaluated for the first time using the International Union for Conservation of Nature Red List of Threatened Species Categories and Criteria. Across 32 families, 103 species were assessed. New Zealand holds a high degree of species endemism (20%) with deepwater species dominating the fauna (77%). Sharks were the most speciose group with 68 species (66%), followed by 24 rays (23%), and 11 chimaeras (10%). Most species were assessed as Least Concern (60%, 62 species) or Data Deficient (32%, 33 species), with four (3.8%) species listed as Near Threatened and four (3.8%) in a threatened category (Vulnerable, Endangered, Critically Endangered). Threatened species are all oceanic pelagic, of which two are only visitors to New Zealand waters, and their status the result of broader regional declines. These results are in stark contrast to other recent regional assessments in Europe and the Arabian Sea and adjacent areas, where up to half of species were listed in a threatened category. However, given New Zealand's extensive deepwater fishing effort and rapid collapses of deepwater chondrichthyan fisheries elsewhere, it is possible that New Zealand populations of many deepwater species are the remnants of previously reduced populations that are now at a low, yet stable level. Ongoing species‐level catch monitoring will be required to ensure these species do not become threatened. Recommendations for future research and conservation efforts include resolving taxonomic uncertainties, understanding habitat use, and increasing regional collaborations to better understand the effects of fishing on wider‐ranging species. Full text link to article https://rdcu.be/bOXYf Or view Postprint version at Item field below.
Keywords: chimaera; Conservation; deep water; IUCN Red List of Threatened Species; marine management; ray; shark

Garig Gunak Barlu Cobourg Marine Park Green Sawfish Project: Scoping Trip Report - Christy Davies; Alan Withers; PM Kyne (2019)
Drone footage captured in late 2018 showing a Green Sawfish (Pristis zijsron) aggregation in the shallow waters of Garig Gunak Barlu Cobourg Marine Park footage was unprecedented anywhere in the wide Indo-West Pacific range of the species and suggested that this site may not only be nationally, but also internationally significant for this highly threatened species. Drones and Baited Remote Underwater Videos (BRUVs) will be used to characterise recently-identified sawfish aggregation areas within the Garig Gunak Barlu Cobourg Marine Park. A scoping trip was undertaken during the period 15–22 March 2019 which aimed to assist in planning field surveys. From the scoping trip it is apparent that there are likely to be numerous locations throughout the Marine Park where Green Sawfish aggregate (several of which could be surveyed using the proposed methods), and the Marine Park is likely to be a hotspot for elasmobranch diversity generally. This report outlines access and permits required to undertake research in the Park, environmental conditions as they relate to undertaking planned research, potential sampling sites, future sampling trips, and risk associated with the planned research.
Keywords: BRUVs; drones; elasmobranch; Green Sawfish; nursery areas; Pristis zijsron

A global assessment of the direct and indirect benefits of marine protected areas for coral reef conservation - Strain, Elisabeth M. A.; Graham J. Edgar; Daniela Ceccarelli; Rick D Stuart-Smith; G.R. Hosack; Russell J. Thomson (Diversity and Distributions, 2019)
Aim Marine protected areas (MPAs) are increasingly implemented to conserve or restore coral reef biodiversity, yet evidence of their benefits for enhancing coral cover is limited and variable. Location 30 MPAs worldwide and nearby sites (within 10 km). Taxa Cover of key functional groups for coral (total, branching, massive and tabular), and algae (total, filamentous, foliose) and total biomass of reef fish trophic groups (excavator, scraper, browser, higher carnivore). Methods We used a global dataset obtained using standardized survey methods at 465 sites associated with 30 MPAs in 28 ecoregions to test the effects of five key MPA attributes (>10 years old, well‐enforced, no‐take, large and isolated) on coral cover, algal cover and reef fish biomass. We also tested the direct (reducing disturbance by human activities) versus indirect pathways (increasing grazing potential through recovering populations of herbivorous fishes) by which MPAs can influence coral and algal cover. Results Only well‐enforced, no‐take and old (>10 years) MPAs had higher total coral cover (response ratio 1.08–1.19×) than fished sites, mostly due to the increased cover of massive coral growth forms (1.34–2.06×). This effect arose through both the direct influence of protection and indirect benefits of depressed algal cover by recovering herbivorous fish biomass. Neither the direct (standardized coefficient = 0.06) nor indirect effects (standardized coefficient = 0.04) of no‐take protection on coral cover were particularly strong, likely reflecting regional differences in fishing gear, targeted species and trophic webs. Conclusions MPAs promote the persistence of some functional groups of corals, and thus represent an important management tool, globally.
Keywords: algal cover; fish biomass; herbivorous fishes; impacts of fishing; marine reserves; predatory fishes; Reef life survey

Globally consistent quantitative observations of planktonic ecosystems - Lombard, Fabien; Boss, Emmanuel; Waite, Anya M.; Vogt, Meike; Uitz, Julia; Stemmann, Lars; Sosik, Heidi M.; Schulz, Jan; Romagnan, Jean-Baptiste; Picheral, Marc; Pearlman, Jay; Ohman, Mark D.; et al. (Frontiers in Marine Science, 2019)
In this paper we review the technologies available to make globally quantitative observations of particles in general—and plankton in particular—in the world oceans, and for sizes varying from sub-microns to centimeters. Some of these technologies have been available for years while others have only recently emerged. Use of these technologies is critical to improve understanding of the processes that control abundances, distributions and composition of plankton, provide data necessary to constrain and improve ecosystem and biogeochemical models, and forecast changes in marine ecosystems in light of climate change. In this paper we begin by providing the motivation for plankton observations, quantification and diversity qualification on a global scale. We then expand on the state-of-the-art, detailing a variety of relevant and (mostly) mature technologies and measurements, including bulk measurements of plankton, pigment composition, uses of genomic, optical and acoustical methods as well as analysis using particle counters, flow cytometers and quantitative imaging devices. We follow by highlighting the requirements necessary for a plankton observing system, the approach to achieve it and associated challenges. We conclude with ranked action-item recommendations for the next 10 years to move toward our vision of a holistic oceanwide plankton observing system. Particularly, we suggest to begin with a demonstration project on a GO-SHIP line and/or a long-term observation site and expand from there, ensuring that issues associated with methods, observation tools, data analysis, quality assessment and curation are addressed early in the implementation. Global coordination is key for the success of this vision and will bring new insights on processes associated with nutrient regeneration, ocean production, fisheries and carbon sequestration.
Keywords: autonomous platforms; ECVs; EOVs; global observing; imaging; OceanObs; plankton

Habitat value of Sydney rock oyster (Saccostrea glomerata) reefs on soft sediments - Ian M. McLeod; Lisa Bostrom-Einarsson; Creighton, C.; D'Anastasi, B.; Ben K Diggles; Dwyer, P. G.; Firby, L.; Le Port, A.; Luongo, A.; Martínez-Baena, F.; McOrrie, S.; Gideon Heller-Wagner; et al. (Marine and Freshwater Research, 2019)
Estimates of the ecological and economic value of ecosystems can provide important information for the prioritisation of conservation and restoration actions. Oyster reefs that were once common in temperate coastal waters have now been largely degraded or lost. Oyster reefs provide a suite of ecological services, including habitat and a food supply for a range of other species. In Australia, there is growing interest in oyster reef restoration, but there are knowledge gaps with regard to their structure and habitat value. Here, we describe the structure of eight remnant Sydney rock oyster (Saccostrea glomerata) reefs and estimate the density, biomass, productivity and composition of mobile macroinvertebrate and infaunal communities associated with them. The oyster reefs had a distinct assemblage of macroinvertebrates, with fivefold higher density of larger (≥2 mm) macroinvertebrates, fivefold higher biomass and almost fivefold higher productivity, than that of adjacent bare sediments. The productivity of infaunal communities was twice as high under oyster reefs than in adjacent bare sediments. Therefore, S. glomerata reef restoration is likely to provide important habitat for macroinvertebrate communities and boost local secondary production.
Keywords: ecosystem services; productivity

An introduction to MBHdesign - Scott D Foster (2019)
This is a tutorial, or a "vignette", using R terminology, to support the R-package for spatially balanced survey design.  It guides a new user through the process of setting up MBHdesign and producing a survey design. A robust scientific conclusion is the result of a rigorous scientific process. In observational ecology, this process involves making inferences about a population from a sample. The sample is crucial, and is the result of implementing a survey design. A good survey design ensures that the data from the survey is capable of answering the research question. Better designs, such as spatially balanced designs, will also be as precise as possible given the constraints of the budget. Project D2 of the NESP marine biodiversity hub have been researching and have implemented spatially balanced designs into the R-package "MBHdesign" (for Marine Biodiversity Hub Design). MBHdesign incorporates addition of legacy sites and also designs for transects, and is available on CRAN (https://cran.r-project.org/package=MBHdesign).
Keywords: balanced adaptive sampling; GRTS; R; spatially correlated Poisson sampling; spatially-balanced survey design; transect

Lost before found: A new species of whaler shark Carcharhinus obsolerus from the Western Central Pacific known only from historic records - William T White; PM Kyne; Harris, Mark (PLOS ONE, 2019)
Carcharhinus obsolerus is described based on three specimens from Borneo, Thailand and Vietnam in the Western Central Pacific. It belongs to the porosus subgroup which is characterised by having the second dorsal-fin insertion opposite the anal-fin midbase. It most closely resembles C. borneensis but differs in tooth morphology and counts and a number of morphological characters, including lack of enlarged hyomandibular pores which are diagnostic of C. borneensis. The historic range of C. obsolerus sp. nov. is under intense fishing pressure and this species has not been recorded anywhere in over 80 years. There is an urgent need to assess its extinction risk status for the IUCN Red List of Threatened Species. With so few known records, there is a possibility that Carcharhinus obsolerus sp. nov. has been lost from the marine environment before any understanding could be gained of its full historic distribution, biology, ecosystem role, and importance in local fisheries.
Keywords: description; new species; shark species; Taxonomy

Monitoring Population Dynamics of ‘Western’ Right Whales off Southern Australia 2018-2021 - Progress Report on activities for 2018 - Diana Jones; Kenny Travouillon; M C Double; Joshua N. Smith (2019)
Now endangered under the EPBC Act, unsustainable whaling during the 19th and 20th centuries reduced southern right whales to a few hundred animals. They now seem to be recovering slowly in most areas. Since 1993 annual aerial surveys between Cape Leeuwin (WA) and Ceduna (SA) have provided counts and photo-identification data for Australia’s south-western population aggregating close inshore during calving and nursing. To add to this long term dataset, an aerial survey between Cape Leeuwin to Ceduna, with an additional leg between Augusta and Perth up the west coast, was undertaken successfully between 18th and 27th August 2018. A total of 1095 animals were sighted including 381 calves (includes double counts). Counts comparable to previous years are 789 individuals of which 279 were cows accompanied by calves of the year. From 6005 photographic images obtained, 456 have been selected for computer -assisted ‘matching’ with those already available in the catalogue.
Keywords: abundance; aerial survey; distribution; Southern right whale; trend analysis

Monitoring Population Dynamics of ‘Western’ Right Whales off Southern Australia 2018-2021 - Final Report on activities for 2018 - Diana Jones; Kenny Travouillon; Natalie Kelly; M C Double; Joshua N. Smith (2019)
To continue an annual series of aerial surveys since 1993 off the southern Australian coast between Cape Leeuwin WA and Ceduna SA, a survey was undertaken over five days from 18-23 August, 2018. A total of 1095 southern right whales were sighted, including 381 calves; these include double counts given that each flying leg is covered twice, ‘outward’ and ‘inward’. An additional 17 humpback whales (including three calves) were recorded during the survey. A comparison of the maximum counts for each survey leg with previous years, resulted in 2018 having a total of 789 whales and 279 cow/calf pairs which were both lower than in 2017 although still higher than any of the other previous years since 1993. The maximum counts for cow/calf pairs are used to obtain a population size estimate, which for 2018 is 3191 whales. This population estimate is for the ‘western’ Australian subpopulation which is considered to represent the majority of the ‘Australian’ population. The population trend analysis indicates a continued increase in whale numbers by approximately 6% per year (based on counts of cow/calf pairs), with no apparent slowdown in the population growth rate. From 6005 photographic images obtained, 329 have been selected for computer -assisted ‘matching’ with those (some 9000 images of over 2000 individuals) already available in the catalogue. All photo-identification and sightings data have been included and archived in existing databases.
Keywords: Australian Western population; Population recovery; Southern right whale

National Outfall Database - Prospectus Report 2019 - John Gemmill; Qurratu A. Rohmana; Andrew M Fischer; Blackwell, Boyd; John Cumming (2019)
Wastewater disposal into the marine environment is one of the main factors leading to the deterioration of coastal water quality. Poorly managed disposal can lead to increased concentrations of nutrients, organic and inorganic pollutants, as well as alter levels of turbidity, pH and bacteria (Carey and Migliaccio, 2009; Beck and Birch, 2012; Cheung et al., 2015). An increase in the level of pollutants can have an impact on coastal ecology and biodiversity and affect the health of recreational users (Schwarzenbach et al., 2010; Burd et al., 2012; Eugenia et al., 2016; Boehm et al., 2017). The Australia State of Environment Report (2016) identified a significant deterioration in a number of components of the coastal environment (Clark and Johnston, 2017). A key finding of the Coasts chapter highlights that the current degradation of the coastal environment is “tightly correlated” with human population, and agriculture or industrial development. These stressors may impact coastal systems in complex and synergistic ways across a variety of temporal and spatial scales. In addition, other key findings state that, “data are insufficient to assess many aspects of the state of the environment of the coast.” The “Coastal Waters” section of the chapter highlighted the two pathways for nutrients to enter the coastal waters. These were sewage outfalls and the diffuse sources, such as runoff. These inputs can lead to degraded states in the coastal environment such as eutrophication, harmful algal blooms, low-oxygen dead zones, the disruption of biogeochemical cycling and disturbance of the ecological balance of marine ecosystems (e.g. crown-of-thorns) (Clark and Johnston, 2017). Providing a comprehensive understanding of nutrient and pollutant loads into the marine environment around Australia is difficult given the different sampling and reporting requirements. The lack of consistency across reporting methods exemplifies the lack of transparency or openness in governance, which can have negative consequences on Australia’s coastal environment. Australia is obligated to manage resources of National Interest and as a signatory to the Convention on Biological Diversity, is required to safeguard its biological diversity, as well as manage the impacts of nutrients on ecosystem function and structure (Aichi Biodiversity Targets (8)) (NRMMC, 2010). An improvement in reporting requirements that aligns with national and regional interests, MNES, transboundary pollution and environmental concerns is warranted. In order to reduce water quality degradation, there is a need to increase communication between the relevant stakeholders and the general community. The effectiveness of science communication will enable the general public to make a sound choice regarding the environmental issues as well as helping the decision makers to improve the marine environment management (Mea et al., 2016). Public notifications, particularly in relation to water quality events, play an active role in managing health risks for both humans and the environment. However, public notification or mis-notification can be fraught with errors (Thoe et al., 2014). For instance, clean beaches can be closed inadvertently because managers may feel unsure of the spatial extent of water contamination. On the other hand, contaminated beaches may remain open, due to the time mismatch between sampling and notification (Pendleton, 2008). Around the world, programs have been developed to notify the public about water quality issues, for instance, the Beachwatch monitoring program in NSW, which was started in 1989 in response to community concern about sewage pollution washing up on Sydney’s beaches (Beder, 1991; OEH, 2019). However, communication practices among the programs are variable and lack formal evaluation of their effectiveness (Pratap et al., 2011). The National Outfall Database (NOD), developed by the Clean Ocean Foundation (COF) in collaboration with States and Territories Governments, provides policy makers with a guide to help prioritise outfall reform and identify public and private sector opportunities for wastewater recycling (Marine Biodiversity Hub, 2015). In collaboration with the National Environmental Science Programme – Marine Biodiversity Hub, the NOD also provides Australian water authorities and the public an accessible database to help identify pollutant loads and assess any potential health and environmental impact risks of sewerage outfalls on the marine environment and surrounding communities. The NOD provides an unprecedented national collection of water quality data, collected by water authorities and Local Governments according to guidelines set out in Environmental Protection Authority (EPA) licenses. Given the NOD’s centralized collection of national scale water quality data, the opportunity to examine the comprehensive impacts of sewerage outfalls at regional scales becomes possible. The aim of the NOD was to facilitate cross-institutional data sharing among federal, state, local governments and the community to promote transparency and openness of governance for managing pollutants from WWTPs. The NOD also provides data and information that could be helpful for integrating infrastructure planning and decision making of sewage effluent impacts on marine environment.
Keywords: marine environment; ocean outfall; wastewater

National Outfall Database Ranking Report 2017-2018 - Qurratu A. Rohmana; Andrew M Fischer; John Gemmill; John Cumming (2019)
This report provides an analysis of the Australian coastal outfalls and ranks them according to the total flow volume and nutrients load to prioritise the potential degree of impact of each source to the environment and human health. Water quality data were collected from 42 Water Treatment Authorities (WTAs) around Australia by either downloading the water quality data reports directly from WTA websites or by formally requesting the data through email. The pollutant contribution index, based on nitrogen and phosphorous loads, was calculated for each outfall. Nitrogen and phosphorous loads were calculated according to the Load Calculation Protocol of New South Wales Department of Environment and Climate Change. Outfalls were ordered from lowest to highest index value to rank them according to their relative pollutant contribution to the coastal and marine environment. The index is based on a total nutrient load discharge using the variables of flow, nitrogen and phosphorous. The results showed that total nutrient load from individual outfalls sites around Australia ranged from 90.4 to 14,324,559.1 kg with a mean of 420,398.19 kg. The ranked loads throughout Australia were mapped by quartiles. The top quartile (lowest nutrient load) of outfalls seem to be more prevalent in regional areas and discharge less nitrogen and phosphorus loads into the coastal and marine environment. The bottom quartile, on the other hand, with higher nutrient loads appear to occur around the major cities. The phosphorous concentrations contribute less to the overall outfall nutrient load and vary less between outfall site. Nitrogen, on the other hand has a higher median contribution and high variability across the sites. In general, the outfalls contributing higher nitrogen and phosphorous loads vary more than those delivering lower loads. There may be many reasons for this, but it could be related to the capacities of the treatment plants and storm water management in urban areas, resulting in increased in discharge at metropolitan outfall sites. There are some exceptions to this pattern with rural/regional sites contributing higher nutrient loads than urban areas. The reasons for them may vary, however, they may primarily be due to the conditions set out in their licenses. This ranking of nutrient loads from Australian outfalls by site at a national scale can therefore be useful in prioritizing treatment upgrade resources to manage biodiversity impacts and human health concerns.
Keywords: nitrogen pollution; ocean outfall; ocean pollution; outfall; outfall ranking; phosphorous pollution; Sewage; waste water

NESP Marine Biodiversity Hub Annual Progress Report 4 (2018) - Nicholas J. Bax; Paul Hedge; Sarah Gracie (2019)
Letter from the Hub Leader, Prof Nic Bax 2018 saw an increase in the rate of delivery of products to the Department. An early delivery was the first estimate of population size and trend for the white shark populations on the east and west coasts, generating considerable media interest and providing a sound basis for the Department to respond to many conflicting proposals on the control and protection of this species. The new and intensive genetic approach – close kin genetics – used for this estimate provided the first statistically valid population estimate for this species worldwide. Its development for rare and threatened species started with the freshwater sawfish in 2012 (insufficient animals could be caught to provide a valid estimate), switched to speartooth shark in 2014 and was extended to grey nurse shark in 2015. Population estimates for all species are now with the Department. Of course there are many species of sharks and rays in Australia and not all can have the resources expended for a quantitative population estimate. Hub researchers worked closely with the Department in 2018 to develop a comprehensive shark action plan, building on a previous national assessment. The plan indicated that 38 of the 328 shark species in Australia were threatened and in need of protection although the status of a further 30 was uncertain due to lack of data. This is one of the lowest proportions of threatened sharks and rays globally and assisted the Department in developing a process to prioritise action on the threatened species. It may already be too late to restore populations of the critically endangered handfish populations in their once natural environment, although trials are underway to improve the quantity and quality of artificial spawning habitat. Working with industry, a captive rearing population of the spotted handfish was established in 2018, which successfully produced the first captive-born generation. Meanwhile an emergency response was put into action to remove an egg mass from the red handfish, of which only about 100 fish survive worldwide, in an attempt to establish a captive rearing population for this species. Much more work needs to be done in closing the life-cycle for these two species, but the essential first steps have been taken through a collaboration of researchers, managers and industry, supported by the Hub. There are insufficient resources to work to recover all listed marine species in Australia, so the Hub has been working with the Department on two initiatives to support these other species. The first stage of an integrated management project was completed in Northern Australia with the aim of managing the landscape which supports many species, and following a national evaluation and prioritisation exercise, including responsibilities under the EPBC Act, restoration activities were started for the listed giant kelp community off Tasmanian and seagrass in the Shark Bay World Heritage Area, two keystone species that support many other vulnerable species. A major impetus of the Hub has been to help access and promote the many diverse Australian marine data collection initiatives so that they support, at little additional cost to the taxpayer, the ongoing information needs of marine managers in the Department and beyond. An important approach has been promote standardisation of data collection and sharing for the many marine environmental surveys occurring every year in Australian waters. The Hub worked with the National Marine Science Committee to hold the first Marine Baselines and Monitoring Group that is identifying the opportunities for national coordination of marine environmental data collection so that Australia will be able to profit in the future from sustained time series data, the lack of which is regularly identified in State of Environment reports. Hub researchers led over 65 researchers from 30 institutions to develop and publish Standard Operating Procedures for major data collection platforms and collaborated with national infrastructure initiatives to ensure that some of the major data streams used for Marine Park and SOE reporting will come under national archiving and FAIR data initiatives. Global interest in these approaches have led to their inclusion in the Ocean Best Practices repository and current prioritisation for inclusion in the global ocean observing system. Earlier data syntheses by the Hub have now been picked up through major national initiatives supporting improved data accessibility for managers including SeaMap Australia, AusSeabed and the Parks Australia Science Atlas. Collating and improving access to existing data, while setting the standards for future data collection is very useful but going to sea to collect new information is considerably more fun, and given the paucity of knowledge of what the new Australian Marine Parks contain, equally useful. Marine surveys in the Beagle and Hunter Marine Parks provided a good opportunity to test and refine these national approaches while the year ended with a 27-day voyage to the southern seamounts in and adjacent to the Huon and Tasman Fracture Marine Parks developed collaboratively with Parks Australia, CSIRO and NIWA (New Zealand) and including students and early career researchers from universities and museums around Australia. The presence of Parks Australia on board throughout the voyage allowed an almost unprecedented level of engagement between managers and early career researchers that will provide ongoing benefit for the future baseline and monitoring of Australian Marine Parks. The survey itself generated a larger set of data on coldwater corals on deep-water coral reefs than exists anywhere else in the world, that together with similar, although less intensive, surveys 10 and 20 years ago will result in new understandings of how these vulnerable coldwater coral communities and structured through depth and their potential for recovery from physical disturbances including fishing. It is a rare privilege these days to receive six-years dedicated funding for a body of research such as marine biodiversity. The value of this approach is witnessed by our increasing engagement with departmental officers as we now have the information and resources to ensure that the data collected by scientists is prepared and delivered in a form that is useful to managers in the Department and beyond. This extended engagement between researchers and the Department has enabled Australia’s marine research organisations to build their scientific capacity and this manifests as increasing expert advice to the Department. Hub researchers support departmental officers in preparing for and representing their scientific priorities in national fora including the National Marine Science Committee, and the review into allocation of ship-time for the Marine National Facility. Hub researchers support, and in some cases represent the government (as scientific experts with DoEE and DFAT) at international negotiations including the Convention for Biological Diversity, the UN dialogue on developing a new implementing agreement for managing biodiversity beyond national jurisdiction, the UN Convention on Migratory Species, and the Convention on International Trade of Endangered Species. Hub research is now being used in studies funded by the Australian Government (ARC, DFAT), the German Government, and the Fisheries and Agriculture Organisation of the United Nations to develop new bioregional and bathymetry maps for the Indian, South Pacific and Antarctic oceans, and support environmental reporting through the State of Environment Report and the World Ocean Assessment. In the last two years of the Hub, our researchers are working with the Department and stakeholders to identify and develop synthesis projects that will further focus and deliver our research and the combined expertise of the research collaborations that we have developed into products that are of immediate and of long-term value to the Department and marine stakeholders in general.
Keywords: annual progress report

NESP Marine Biodiversity Hub - Governance - Nicholas J. Bax; Paul Hedge; Annabel Ozimec (2019)
The NESP Marine Biodiversity Hub responsibilities and commitments include to: Design and deliver research that meets the agreed NESP research priorities and strategic interests of the Hub’s research partners and stakeholders Meet agreed milestones in the research plans on time and within budget Manage and acquit Hub finances and other contractual issues in accordance with the NESP funding agreement, sub-contracts and research plans Promote uptake of the Hub’s research by end-users Contribute to national collaboration on marine biodiversity research Provide a succession plan to sustain the Marine Biodiversity Hub into the future The role of the Hub’s governance is to provide the oversight, direction and guidance to ensure the Hub delivers its responsibilities and commitments effectively and efficiently. This will include: Approval of the Hub’s Annual Research Plan and the strategies to deliver these Monitoring progress in meeting the Hub’s commitments to the NESP, including the approval annual reports on Hub performance to the NESP Approval of the annual allocation of resources across the research priorities, including approval of allocation of significant new resources or material departures in resource allocation between partners and priorities (under or over eg 10+% variation?) Review and endorsement of key Hub policies, plans and procedures, including the Communication and Monitoring and Evaluation Plans, Advise and support the Director in effective engagement with key stakeholders and potential new partners and end users Oversight of the key risks to the effective delivery of the Hub’s commitments Review and advise the Hub partners on opportunities to broaden the uptake of the Hub’s research and to extend the capacity and continuation of the Hub beyond its NESP contract
Keywords: governance

NESP Marine Biodiversity Hub Research Plan - 2019 RPv5 - Project Proposals - Nicholas J. Bax; Paul Hedge (2019)
This Research Plan for 2019 (RPv5) has been developed by the Marine Biodiversity Hub, in consultation with the Department of the Environment and Energy and other key stakeholders. The purpose of the Research Plan is to outline: the research priorities the Hub is funded to investigate the research projects that will address these priorities how the output of the research will be communicated and brokered to key stakeholders how the impact of the research will be measured how Hubs will work collaboratively within and across Hubs This Research Plan also lists key staff and research organisations, and the risks needing to be monitored to ensure success. Please note: Project durations vary and may extend over a number of years.  If the project you are interested in is not listed in the Item field of this research plan, it will be included in an earlier year as an ongoing, unchanged project. Where a project proposal involves significant changes, it will be updated and included in subsequent research plans.
Keywords: annual research plan; RPv5

Northern Australia Hammerhead Shark Tagging Program - Fact Sheet (Update January 2019) - A Chin (2019)
Northern Australia has two large species of hammerhead sharks, the scalloped hammerhead and the great hammerhead. Scalloped hammerheads are listed as “Conservation Dependent” under Australian law, meaning that governments, industries, and communities need to consider how to better manage this species. Managers therefore need to know how both species move between state and international waters and how much populations overlap, so that threats can be identified and appropriate management actions put in place. Since December 2016, a team from the National Environmental Science Program Marine Biodiversity Hub has been tagging and tracking hammerhead sharks to find out how the sharks are moving through northern Australian waters. The tagging team includes scientists from the Australian Institute of Marine Science, Western Australian Fisheries, Northern Territory Fisheries and James Cook University (JCU). Commercial and charter fishers have been advising the team on where to find the sharks, and Indigenous rangers from the Girringun Aboriginal Corporation, Yuku Baja Muliku, and Yirrganydji Traditional Owners joined some of the tagging expeditions in Queensland.
Keywords: fisheries; hammerhead; Indigenous tracking; shark; tag

Perceptions and information disclosure of water quality issues in Australia 2019 - Qurratu A. Rohmana; Andrew M Fischer; John Gemmill (2019)
Changes to marine environment health in the coastal zone are becoming more complex, pervasive and are occurring at a much faster rate, primarily due to human-related activities (Cloern et al., 2016). Wastewater disposal into the marine environment is a key factor leading to the deterioration of coastal water quality. Poorly managed disposal can lead to increased concentrations of nutrients, organic and inorganic pollutants, as well as alter levels of turbidity, pH and bacteria (Beck and Birch, 2012, Carey and Migliaccio, 2009, Cheung et al., 2015). An increase in the level of pollutants can have an impact on coastal ecology and biodiversity and affect the health of recreational users (Boehm et al., 2017, Reopanichkul et al., 2009, Schwarzenbach et al., 2010). Often the marine-related businesses, such as oyster farm, are also affected due to high level of bacteria contamination which causes less production during harvest season (Campos et al., 2015). In order to reduce water quality degradation, there is a need to increase communication between the relevant stakeholders and the general community. The effectiveness of science communication will enable the general public to make a sound choice regarding the environmental issues as well as helping the decision makers to improve the marine environment management (Mea et al., 2016). Public notifications, particularly in relation to water quality events, play an active role in managing health risks for both humans and the environment. However, public notification or mis-notification can be fraught with errors (Thoe et al., 2014), For instance clean beaches can be closed inadvertently because managers may feel unsure of the spatial extent of water contamination. On the other hand, contaminated beaches may remain open, because due to the time mismatch between sampling and notification (Pendleton, 2008). Around the world, programs have been developed to notify the public about water quality issues. For instance, the Beachwatch monitoring program NSW, which was started in 1989 in response to community concern about sewage pollution washing up on Sydney’s beaches (Beder, 1991, OEH, 2019). However, amongst the programs, communication practices are variable and lack formal evaluations for their effectiveness (Pratap et al., 2011). Consideration of public perception is important for assessing the effectiveness of notification programs and managing the risks and behaviour of the public with regard to recreational water usage. Public perception research is critical in this regard as a means of assessing science and policy initiatives (Gelcich et al., 2014, Jefferson et al., 2015, Treise and Weigold, 2002). The purpose of this research is to gain an understanding of user perceptions and information disclosure of water quality events around Australian coastal regions. Water quality changes may be caused by different events such as sewage release and stormwater run-off into an estuary or the coastal ocean. This may cause declines in water quality and potential health issues through contact with the affected water. Sewage runoff may occur in dry weather because of problems with, for example, mechanical failure at wastewater treatment plants. Wet weather may also cause the capacity of the wastewater treatment plants to be exceeded because of large volumes of stormwater in the sewer system. Sewage run-off has some characteristics, which may be detected by odour, sight, water discoloration, turbidity, and oily films. This research aims to gather information about community perception of where water quality events occur, whether they are linked to weather events, and the effectiveness of communication efforts to notify the community of the occurrence of these events. This research is important as it assesses an understanding of perceptions, behaviours and expectations of the community using water bodies that may be affected by water quality events. Research has found that improved knowledge and communication of water quality in coastal areas can improve individual’s management of health risk associated with bypass events.
Keywords: environmental health; ocean outfall; ocean pollution; recreational users; Sewage; waste management; waste water

Promoting partnerships for Sea Country Research and Monitoring in Western Australia: A snapshot of Indigenous, science and management agency partners - Lincoln, Gina; Paul Hedge (2019)
The potential benefits of collaborative science projects on Saltwater Country in Western Australia (WA) are many. Examples of successful collaborations between Indigenous and non-Indigenous partners that deliver a suite of co-benefits were showcased at recent events such as the 2019 AMSA conference. The common elements of these success stories include the establishment of trusted relationships built on cross cultural understanding, clearly defined engagement processes, research agreements, and allocation of adequate resources to achieve agreed objectives. In some parts of the state where capacity allows and governance structures are well established, there has been investment in developing culturally appropriate research protocols from community standards. In other areas, recently recognised Native Title holders are working hard to develop the capacity required to undertake science activities. Yet other saltwater groups are progressing through the lengthy process of seeking recognition of their Native Title rights. This wide variability in the development, resourcing and capacity of Indigenous groups to participate and lead science projects on their saltwater Country is an important consideration for research institutions and management agencies looking to develop collaborative projects. Similarly, it is important for Indigenous communities to understand and evaluate the partnership opportunities among the various marine science institutions and management agencies operating within Western Australia. While this document will not address all of the challenges, it aims to provide a big picture perspective of potential partners for Sea Country science in WA by providing simple, overview information of both Indigenous saltwater groups and western science agendas within the state. In the following pages, we provide time-bound snapshots of thirty Western Australian saltwater Native Title holders and claimant groups; eight government agencies with significant marine science agendas; four major marine science collaborations; three professional organisations; and four major WA universities. Due to the rapidly evolving nature of Sea Country science, as well as the growing number of marine science institutions and management agencies seeking Indigenous input and engagement, we acknowledge that the information provided will become progressively outdated. The document should not be seen as a complete representation of all Indigenous groups or land and sea capacity, or of marine science and management programs in WA. Nonetheless, we hope that it is one of many tools supporting Indigenous communities, science institutions and marine managers to develop collaborative and respectful partnerships enabling science that provides important benefits to people and their Country.
Keywords: Indigenous engagement; Marine Science; partnerships; Western Australia

Prospects for seascape repair: three case studies from eastern Australia - Creighton, Colin; Prahalad, Vishnu N.; Ian M. McLeod; Sheaves, Marcus; Taylor, Matthew D.; Terry Walshe (Ecological Management & Restoration, 2019)
Three case studies spanning tropical, subtropical and temperate environments highlight the minimum potential benefits of investing in repair of coastal seascapes. Fisheries, a market benefit indicator readily understood by a range of stakeholders from policymakers to community advocates, were used as a surrogate for ecosystem services generated through seascape habitat restoration. For each case study, while recognising that biological information will always remain imperfect, the prospects for seascape repair are compelling.
Keywords: Coastal wetlands; ecological restoration; ecosystem services; fisheries; saltmarshes

Quantification of risk from shipping to large marine fauna across Australia: Final Report - David Peel; Joshua N. Smith; Christine Erbe; T. A. Patterson; Simon Childerhouse (2019)
Substantial and ongoing growth in coastal and port development, recreational boating and commercial shipping around Australia is increasing the potential for adverse interactions with marine species. This is exacerbated by growing populations of some whale species such as humpback whales. For large marine fauna, the two major risks are vessel collisions (particularly for marine mammals and turtles) and cumulative exposure to chronic noise (across a wide range of species). Greater research focus and better methodological frameworks are needed to quantify the time and location that these risks are high, to help direct resources and monitoring toward developing and implementing appropriate management strategies. This project combined existing data such as vessel density, speed and noise levels with species distribution/habitat models to identify Biological Important Areas (BIAs) and produce fine-scale relative spatial risk profiles. These risk profiles can be used to identify when and where marine fauna and shipping overlap, and to work through a question and answer process designed to help minimise the risk (see Table 9 in the main document). This includes evaluating relative risk, research and resourcing options, and the likely effects of management/mitigation approaches.
Keywords: Vessel strike; ocean noise; shipping

Recreational fishing in Commonwealth waters - T P Lynch; C B Smallwood; Ochwada-Doyle, F; Joel Williams; K L Ryan; C Devine; Gibson, B; Burton, Michael; A Hegarty; Lyle, J; Scott D Foster; Alan Jordan (2019)
Recreational fishers regularly access both state and offshore Commonwealth waters but offshore fishing is poorly understood. There has been recent global and Australian growth in offshore Marine Protected Areas (MPAs) and a better understanding of recreational fishers accessing both these MPAs, as well as offshore stocks of fish more generally, is important for sustainability of catch, communication and compliance. Recreational fishing is popular in Australia and is managed by individual States in collaboration with the Commonwealth agencies: the Australian Fisheries Management Authority (AFMA) and Australian Marine Parks (AMP). Our study investigated two methodological approaches to gain a better understanding of recreational fishing in Commonwealth waters (>3 nautical miles offshore). First, we undertook a pan-continental scale comparison of Australian offshore recreational fisheries research and its applications to fisheries and marine park management. In the absence of data collection on recreational fishing in offshore waters by the Commonwealth, we examined two state-wide Marine Recreational Fishery (MRF) surveys, conducted throughout Western Australia (WA) and New South Wales (NSW), to see if they could meet the Commonwealth’s information needs. The specific aims included (1) a comparison of state-based approaches for data collection in WA and NSW, (2) estimates (with associated uncertainty) of catch occurring state-wide for nine species of interest to AFMA and (3) estimates (with associated uncertainty) of fishing effort and catch (all species) occurring within two AMP: Ningaloo Marine Park (NMP) in WA and the Hunter Marine Park (HMP) in NSW. We also undertook smaller scale on-site surveys along the east coast of Tasmania over a busy holiday period using a novel application of trail cameras combined with interviews on boat ramps of marine recreational trailer-boat fishers. We did this to investigate fishers’ behaviours, perceptions and distributions in relation to a well-established offshore marine park. Our aims were to (1) trial the usefulness of trail cameras to collect novel primary data that can be used in management, (2) to guide collection of on-site interview data for anglers, especially those fishing offshore, and (3) to test an interview questionnaire for usefulness in investigating perceptions and catch of fishers.
Keywords: climate change; Commonwealth waters; fishing effort; harvest; Offshore recreational fishing

Remote reefs and seamounts are the last refuges for marine predators across the Indo-Pacific - Tom B. Letessier; Mouillot, David; Phil J. Bouchet; Vigliola, Laurent; Fernandes, Marjorie C.; Thompson, Chris; Boussarie, Germain; Turner, Jemma; Juhel, Jean-Baptiste; Maire, Eva; M Julian Caley; Koldewey, Heather J.; et al. (PLOS Biology, 2019)
Since the 1950s, industrial fisheries have expanded globally, as fishing vessels are required to travel further afield for fishing opportunities. Technological advancements and fishery subsidies have granted ever-increasing access to populations of sharks, tunas, billfishes, and other predators. Wilderness refuges, defined here as areas beyond the detectable range of human influence, are therefore increasingly rare. In order to achieve marine resources sustainability, large no-take marine protected areas (MPAs) with pelagic components are being implemented. However, such conservation efforts require knowledge of the critical habitats for predators, both across shallow reefs and the deeper ocean. Here, we fill this gap in knowledge across the Indo-Pacific by using 1,041 midwater baited videos to survey sharks and other pelagic predators such as rainbow runner (Elagatis bipinnulata), mahi-mahi (Coryphaena hippurus), and black marlin (Istiompax indica). We modeled three key predator community attributes: vertebrate species richness, mean maximum body size, and shark abundance as a function of geomorphology, environmental conditions, and human pressures. All attributes were primarily driven by geomorphology (35%−62% variance explained) and environmental conditions (14%−49%). While human pressures had no influence on species richness, both body size and shark abundance responded strongly to distance to human markets (12%−20%). Refuges were identified at more than 1,250 km from human markets for body size and for shark abundance. These refuges were identified as remote and shallow seabed features, such as seamounts, submerged banks, and reefs. Worryingly, hotpots of large individuals and of shark abundance are presently under-represented within no-take MPAs that aim to effectively protect marine predators, such as the British Indian Ocean Territory. Population recovery of predators is unlikely to occur without strategic placement and effective enforcement of large no-take MPAs in both coastal and remote locations.

A response to scientific and societal needs for marine biological observations - Nicholas J. Bax; Miloslavich, Patricia; Muller-Karger, Frank Edgar; Allain, Valerie; Appeltans, Ward; Sonia D. Batten; Benedetti-Cecchi, Lisandro; Buttigieg, Pier Luigi; Chiba, Sanae; Costa, Daniel Paul; Duffy, J. Emmett; Daniel C. Dunn; et al. (2019)
Development of global ocean observing capacity for the biological EOVs is on the cusp of a step-change. Current capacity to automate data collection and processing and to integrate the resulting data streams with complementary data, openly available as FAIR data, is certain to dramatically increase the amount and quality of information and knowledge available to scientists and decision makers into the future. There is little doubt that scientists will continue to expand their understanding of what lives in the ocean, where it lives and how it is changing. However, whether this expanding information stream will inform policy and management or be incorporated into indicators for national reporting is more uncertain. Coordinated data collection including open sharing of data will help produce the consistent evidence-based messages that are valued by managers. The GOOS Biology and Ecosystems Panel is working with other global initiatives to assist this coordination by defining and implementing Essential Ocean Variables. The biological EOVs have been defined, are being updated following community feedback, and their implementation is underway. In 2019, the coverage and precision of a global ocean observing system capable of addressing key questions for the next decade will be quantified, and its potential to support the goals of the UN Decade of Ocean Science for Sustainable Development identified. Developing a global ocean observing system for biology and ecosystems requires parallel efforts in improving evidence-based monitoring of progress against international agreements and the open data, reporting and governance structures that would facilitate the uptake of improved information by decision makers.
Keywords: capacity development; EOV; essential ocean variable; GOOS; ocean observing; Sustainable Development Goals; UN Decade

Review of decision support tools and their potential application in the management of Australian Marine Parks - Terry Walshe; Fiona Dempster; Pascoe, Sean; Jennings, Sarah (2019)
The purpose of this report is to provide an appraisal of the strengths and weaknesses of a suite of decision-support tools for the kinds of problems encountered by marine park policy-makers and managers. In organisations around the world, the process by which many decisions are made is unstructured. The most common method of organisational decision-making is through open dialogue in a committee setting. This may be entirely adequate for the many problems that involve small consequences, but it is unlikely to be appropriate where the stakes are high. Even where detailed information and analyses are marshalled to support the committee meeting process, unstructured conversation is prey to the frailties of groupthink, deference to authority, and a bias towards retaining the status quo. Meetings typically exceed the cognitive limits of the human brain. Psychologists have clearly demonstrated that our minds are incapable of processing more than about seven things at any one time. A committee discussion typically involves dozens of things, including issues, alternatives, pros, cons, objectives and criteria. To the extent that they capture sound logic, formal decision support tools have advantages over unaided decision-making. Apart from buffering against cognitive limitations and negative group dynamics, a documented and traceable protocol will encourage decision-makers to be clear about judgments and assumptions. Many predictive tools and models, often based on empirical observation, provide partial decision support. They account for the consequences of a set of alternative policies or actions. Formal decision support tools go beyond the empirical estimation of consequences to address the development of creative alternatives for dealing with a problem, wrestling with trade-offs, coping with uncertainty, and identifying optimal solutions for an individual decision-maker or acceptable solutions for multiple co-managers or stakeholders. Specific tools vary in their emphases on these and other elements. This report describes a suite of tools and techniques that structure decision elements in ways that promote improved outcomes consistent with organisational objectives, focusing on management needs for Australian Marine Parks (AMPs). Through recently released management plans for AMPs, Parks Australia have articulated core objectives and listed key values, pressures and potential actions. Although there is a dearth of information describing many values and pressures in any detail, and the effectiveness of candidate actions in some instances requires further evaluation, Parks Australia is now in a position to begin to utilise the tools and techniques of structured decision-making. Section 1 of this report is targeted at AMP managers. It is a primer on decision-making in marine parks, highlighting the imperative for decision-making under uncertainty and how to go about it. Section 2 makes up the bulk of this report. It is a compendium of tools and techniques that can be deployed in two broad classes of decisions:
Keywords: cost-effectiveness; Decision support tools; multi-criteria analysis; prioritisation; scenario planning

The scientist abroad: maximising research impact and effectiveness when working as a visiting scientist - A Chin; Baje, Leontine; Donaldson, Terrance; Karin Gerhardt; Rima W. Jabado; PM Kyne; Ralph Mana; Mescam, Gauthier; Mourier, Johann; Planes, Serge; Wen, Colin (Biological Conservation, 2019)
Conservation science is crucial to global conservation efforts, and often involves projects where foreign scientists visit a host country to conduct research. Science can significantly contribute to conservation efforts in host countries. However, poorly conceived and implemented projects can lead to poor conservation outcomes, cause negative impacts on communities, and compromise future research. This paper presents guidance from scientists, managers, and conservation practitioners following the 10th Indo-Pacific Fish Conference, the region's largest ichthyology meeting where delegates presented many examples of collaborative research. The guidance provided focuses on issues regarding planning and preparation, collaboration and reciprocity, and conduct and protocol. The intent is to provide conservation scientists with practical advice from locally based and experienced conservation scientists and practitioners about how to maximise research effectiveness and conservation benefits when working abroad. A range of activities and approaches are suggested that visiting scientists can adopt and implement to build the relationships and trust needed for effective collaboration with local actors. Building effective collaborations between local actors and visiting scientists can maximise research effectiveness and impact by ensuring that projects address the most important issues and conservation concerns, involve the appropriate people, use suitable methods and approaches, and carefully consider local contexts and ethics. Such projects are more likely to provide lasting benefits to both parties, and enhance conservation outcomes. However, both visiting scientists and local actors need to communicate clearly, be accommodating, and commit to a genuine partnership to realise these benefits.
Keywords: engagement; International collaboration; research

Scoping of new field manuals for marine sampling in Australian waters - Rachel Przeslawski; Lev Bodrossy; Carroll, Andrew; Cheal, Alistair J.; Martial Depczynski; Scott D Foster; Denise Hardesty; Paul Hedge; Ana Lara-Lopez; Aero Lepastrier; Sebastien Mancini; Karen J Miller; et al. (2019)
A suite of field manuals was released by the NESP Marine Hub in early 2018 to facilitate a national monitoring framework, with a focus on seven marine sampling platforms: multibeam sonar, autonomous underwater vehicles, baited remote underwater video (pelagic and demersal), towed imagery, sleds and trawls, and grabs and box corers. These platforms were identified based on frequency of use in previous open water sampling and monitoring programs. Stakeholder feedback revealed several key sampling platforms and data types not included in the original release, as well as a possible need for field manuals related to cultural or socioeconomic standard operating procedures (SOPs). The current report scopes the need and feasibility of developing new field manuals as related to monitoring Australia’s waters for the following: Remote operating vehicles (ROVs) Passive acoustic monitoring (PAM) Sub-bottom profiling (SBP) Drones Satellite imagery Marine plastics Environmental DNA (e-DNA) Plankton Sampling for Sea Country Socioeconomic monitoring Based on recommendations provided here, an ROV field manual seems necessary and achievable for the NESP Marine Hub program in 2019-2020, while the new NESP Project D6 will provide foundations in 2019-2020 from which a new SOP on socioeconomic monitoring may eventuate. A further six SOPs and associated field manuals may be developed in the future (UVC, PAM, SBP, drones, e-DNA, plankton), assuming suitable resources are secured, including a champion to chair a collaborative working group and lead the development of a field manual. Recommendations from this report indicate that three of the scoped SOPs are not needed, either due to a scope too broad to allow a national SOP (satellite imagery) or other initiatives that are already in advanced development stages (marine plastics, sampling for Sea Country).
Keywords: aerial survey; Indigenous engagement; marine debris; ROV; sampling methods; social science; sub-bottom profile; underwater visual census; video survey method

Shark Action Plan Policy Report - Michelle R. Heupel; PM Kyne; William T White; Colin Simpfendorfer (2019)
Conservation of chondrichthyan species (sharks, rays and ghost sharks) is an increasing priority globally as evidence of overexploitation of many species becomes increasingly apparent. While there are a range of potential stressors to chondrichthyan species, their primary threat comes from interactions with fisheries. Therefore, to improve the status of these species on national and international scales requires effective fisheries management. However, management and conservation of chondrichthyan species is complicated. A number of chondrichthyans are fishery targets and as such subjected to directed fishing effort, while others are encountered as bycatch in fisheries targeting other high value species (e.g. tuna). Species taken as bycatch are often retained as byproduct if they can be sold. The type of management applied, and amount of data collected vary depending on whether the species is target or byproduct. Finally, some species interact with fisheries but are discarded with little or no data are recorded on the number of interactions or condition of individuals. These differences in the amount and type of data available complicate management decisions and the situation is made even more complex by the broad distributions of some species which span national and international boundaries. As such, concerted efforts to understand population status and trends are required to facilitate management and conservation of chondrichthyan species. Here we examined the status of chondrichthyan species within Australian waters in an effort to understand how well current protections are working. This work is placed in the context of national and international conservation measures. We also explore additional threats such as climate change, shark control programs and habitat loss relative to the current and future status of these species. Finally, we explore a framework for managing information and responses to international obligations for at-risk species. Overall, the status of Australian chondrichthyan species is good. The majority of assessed Australian chondrichthyans were determined not to be in a threatened category and were assess as Near Threatened (9.8%) or Least Concern (69.4%). A further 9.2% are currently Data Deficient (insufficient information to assess their status). Thus 11.6% of assessed species fell within a threatened category. This is one of the lowest threat rates when compared to other regional or national level assessments for chondrichthyans. Of the 22 species identified as Critically Endangered or Endangered, all but five of these species are already protected in Australia or previously considered for protection. Five of 17 species considered Vulnerable are already protected in Australia. However, some of the Vulnerable species qualify for listing based on small distributions rather than as a result of an immediate direct threat. The national analysis confirmed the main threat to Australian chondrichthyan species is commercial fishing pressure through targeted harvest or bycatch mortality.
Keywords: Chondrichthyan; climate change; Conservation; fisheries

The success of water refill stations reducing single-use plastic bottle litter - Kathryn Willis; Chris Wilcox; Joanna Vince; Denise Hardesty (Sustainability, 2019)
Bottled water is one sector of the beverage industry that has recently experienced substantial growth. The littering of plastic water bottles and the carbon emissions produced from bottled water production results in harmful effects on the environment. To reduce the harm of bottled water production and litter, government and non-government organisations have implemented litter abatement and behavioural change strategies targeting bottled water consumption and subsequent loss of bottles to the environment. Our study evaluated the success of one of these strategies, which is a filtered water refill station, implemented along the Brisbane River in Queensland, Australia. We found plastic bottle litter decreased after a water refill station was put into operation. However, given the location of the refill station, we suggest the behavioural change strategy employed did not reach its full potential. We highlight factors that could be employed to achieve maximum benefits when implementing similar behavioural change strategies.
Keywords: behavioural change; litter; plastic bottle; river; waste minimisation; water refill station

Successful communication for shellfish reef restoration projects - Ian M. McLeod (The Nature Conservancy, 2019)
Effective communication with a variety of stakeholders is essential for the success of shellfish reef restoration projects. It is most often a permitting and funding requirement and, when done well, helps people feel connected to and excited about the project. In contrast, if communication and engagement are not done early and well, this can lead to misunderstanding and mistrust, causing problems and delays. Effective communication needs to be budgeted for and incorporated directly into the project planning. This section of the report describes the key elements of an effective communication strategy for a shellfish reef restoration project. Related information: Download Chapter 9 at Item link below - McLeod, I. (2019). Successful communication for shellfish reef restoration projects IN: Restoration Guidelines for Shellfish Reefs (eds. J. Fitzsimons, S. Branigan, R.D. Brumbaugh, T. McDonald and P.S.E. zu Ermgassen), pp. 2-6. The Nature Conservancy, Arlington VA, USA. View the full report - Fitzsimons, J., Branigan, S., Brumbaugh, R.D., McDonald, T. and zu Ermgassen, P.S.E. (eds) (2019). Restoration Guidelines for Shellfish Reefs. The Nature Conservancy, Arlington VA, USA. https://www.natureaustralia.org.au/content/dam/tnc/nature/en/documents/australia/TNC_Shellfish_Reef_Restoration_Guidelines_WEB.pdf The Nature Conservancy Australia partnering with the NESP Marine Biodiversity Hub and James Cook University
Keywords: oyster; restoration; science communication; shellfish

A suite of field manuals for marine sampling to monitor Australian waters - Rachel Przeslawski; Scott D Foster; Jacquomo Monk; Neville Barrett; Phil J. Bouchet; Andrew Carroll; Tim J. Langlois; Vanessa L Lucieer; Joel Williams; Nicholas J. Bax (Frontiers in Marine Science, 2019)
One of the main challenges in assessing marine biodiversity is the lack of consistent approaches to monitor it. This threatens to undermine ocean best practice in marine monitoring, as it impedes a reduction in the bias and variance of sampled data and restricts the confidence in the advice that can be given. In particular, there is potential for confounding between the monitoring methods, their measured ecological properties, and the questions they seek to answer. Australia has developed significant long-term marine monitoring and observing programs and has one of the largest marine estates, including the world’s largest representative network of marine parks. This new network will require ongoing monitoring and evaluation, beyond what direct funding can support, which needs to be integrated in a standardized way with other national programs to develop sufficient monitoring capacity. The aim of this paper is to describe the process undertaken in developing a suite of field manuals that provide Standard Operating Procedures (SOPs) for marine sampling in Australian waters so that data are comparable over time and space, thereby supporting a robust, cost-effective, and objective national monitoring program. We encourage readers to refer to the complete manuals of interest at www.nespmarine.edu.au/field-manuals. We generally limit SOP development to benthic or demersal sampling, (multibeam, autonomous underwater vehicles, baited remoted underwater video (BRUV), towed imagery, grabs and box corers, sleds and trawls), with a few exceptions (e.g., pelagic BRUVs). Collaboration was a key characteristic of our approach so rather than single groups trying to impose their standards, more than 70 individuals from over 30 organizations contributed to the first version of this field manual package. We also discuss the challenges that arose while developing these national SOPs, the associated solutions that were implemented, and the plans for ensuring their long-term maintenance and national and international uptake. We anticipate that this paper will contribute to international collaborations by evoking valuable suggestions and sharing of lessons learnt from other national initiatives so that we might work toward a global ocean best practice for biological and geoscientific monitoring of the marine environment.
Keywords: Autonomous underwater vehicle; box core; BRUVs; grab; monitoring; Multibeam sonar; sled; Spatially Balanced Design; standard protocols; towed video

A systematic review of remotely operated vehicle surveys for visually assessing fish assemblages - Sward, Darryn; Jacquomo Monk; Neville Barrett (Frontiers in Marine Science, 2019)
Anthropogenic activities and greater demands for marine natural resources has led to increases in the spatial extent and duration of pressures on marine ecosystems. Remotely operated vehicles (ROVs) offer a robust survey tool for quantifying these pressures and tracking the success of management intervention while at a range of depths, including those inaccessible to most SCUBA diver-based survey methods (~>30 m). As the strengths, limitations, and biases of ROVs for visually monitoring fish assemblages remain unclear, this review aims to evaluate ROVs as a survey technique and to suggest optimal sampling strategies for use in typical ROV-based studies. Using the search engines Scopus™ and Google Scholar™, 119 publications were identified that used ROVs for visual surveys of fish assemblages. While the sampling strategies and sampling metrics used to annotate the imagery in these publications varied considerably, the total abundance of fish recorded over strip transects of varying dimensions was the most common sampling design. The choice of ROV system appears to be a strong indicator of both the types of surveys available to studies and the success of ROV deployments. For instance, larger, more powerful working-class systems can complete longer and more complex designs (e.g., swath, cloverleaf, and polygonal transects) at greater depths, whereas observation-class systems are less expensive and easier to deploy, but are more susceptible to delays or cancelations of deployments. In more severe sea state conditions, radial transects, or strip transects that employ live-boating or a weight to anchor the tether to the seafloor, can be used to improve the performance of observation-class systems. As these systems often employ shorter tethers, radial transects can also be used to maximize sampling area at greater depths and on large vessels that may rotate substantially while anchored. For highly mobile species, and in survey designs where individuals are likely to be recounted (e.g., transects along oil and gas pipelines), relative abundance (MaxN) may be a more robust sampling metric. By identifying subtle, yet important, differences in the application of ROVs as a tool for visually surveying deep-water marine ecosystems, we identified key areas for improvement for best practice for future studies.
Keywords: autonomous observing; comparison of methods; non-destructive; observation-class ROV; standardized operating protocols; video survey method; working-class ROV

Taking a deeper look: Quantifying the differences in fish assemblages between shallow and mesophotic temperate rocky reefs - Joel Williams; Alan Jordan; David Harasti; Peter Davies; T Ingleton (PLOS ONE, 2019)
The spatial distribution of a species assemblage is often determined by habitat and climate. In the marine environment, depth can become an important factor as declining light and water temperature leads to changes in the biological habitat structure. To date, much of the focus of ecological fish research has been based on reefs in less than 40 m with little research on the ecological role of mesophotic reefs. We deployed baited remote underwater stereo video systems (stereo-BRUVS) on temperate reefs in two depth categories: shallow (20-40 m) and mesophotic (80-120 m), off Port Stephens, Australia. Sites were selected using data collected by swath acoustic sounder to ensure stereo-BRUVS were deployed on reef. The sounder also provided rugosity, slope and relief data for each stereo-BRUVS deployment. Multivariate analysis indicates that there are significant differences in the fish assemblages between shallow and mesophotic reefs, primarily driven by Ophthalmolepis lineolatus and Notolabrus gymnogenis only occurring on shallow reefs and schooling species of fish that were unique to each depth category: Atypichthys strigatus on shallow reefs and Centroberyx affinis on mesophotic reefs. While shallow reefs had a greater species richness and abundance of fish when compared to mesophotic reefs, mesophotic reefs hosted the same species richness of fishery-targeted species. Chrysophrys auratus and Nemodactylus douglassii are two highly targeted species in this region. While C. auratus was numerically more abundant on shallow reefs, mesophotic reefs provide habitat for larger fish. In comparison, N. douglassii were evenly distributed across all sites sampled. Generalized linear models revealed that depth and habitat type provided the most parsimonious model for predicting the distribution of C. auratus, while habitat type alone best predicted the distribution of N. douglassii. These results demonstrate the importance of mesophotic reefs to fishery-targeted species and therefore have implications for informing the management of these fishery resources on shelf rocky reefs.
Keywords: BRUVs; Fish ecology; fisheries; Habitat; Hunter; management; marine parks; marine reserves; mesophotic; Port Stephens; reefs

Advancing marine biological observations and data requirements of the complementary essential ocean variables (EOVs) and essential biodiversity variables (EBVs) frameworks - Muller-Karger, Frank E.; Miloslavich, Patricia; Nicholas J. Bax; Simmons, Samantha; Costello, Mark J.; Sousa Pinto, Isabel; Canonico, Gabrielle; Turner, Woody; Gill, Michael; Montes, Enrique; Best, Benjamin D.; Pearlman, Jay; et al. (Frontiers in Marine Science, 2018)
Measurements of the status and trends of key indicators for the ocean and marine life are required to inform policy and management in the context of growing human uses of marine resources, coastal development, and climate change. Two synergistic efforts identify specific priority variables for monitoring: Essential Ocean Variables (EOVs) through the Global Ocean Observing System (GOOS), and Essential Biodiversity Variables (EBVs) from the Group on Earth Observations Biodiversity Observation Network (GEO BON) (see Data Sheet 1 in Supplementary Materials for a glossary of acronyms). Both systems support reporting against internationally agreed conventions and treaties. GOOS, established under the auspices of the Intergovernmental Oceanographic Commission (IOC), plays a leading role in coordinating global monitoring of the ocean and in the definition of EOVs. GEO BON is a global biodiversity observation network that coordinates observations to enhance management of the world's biodiversity and promote both the awareness and accounting of ecosystem services. Convergence and agreement between these two efforts are required to streamline existing and new marine observation programs to advance scientific knowledge effectively and to support the sustainable use and management of ocean spaces and resources. In this context, the Marine Biodiversity Observation Network (MBON), a thematic component of GEO BON, is collaborating with GOOS, the Ocean Biogeographic Information System (OBIS), and the Integrated Marine Biosphere Research (IMBeR) project to ensure that EBVs and EOVs are complementary, representing alternative uses of a common set of scientific measurements. This work is informed by the Joint Technical Commission for Oceanography and Marine Meteorology (JCOMM), an intergovernmental body of technical experts that helps international coordination on best practices for observing, data management and services, combined with capacity development expertise. Characterizing biodiversity and understanding its drivers will require incorporation of observations from traditional and molecular taxonomy, animal tagging and tracking efforts, ocean biogeochemistry, and ocean observatory initiatives including the deep ocean and seafloor. The partnership between large-scale ocean observing and product distribution initiatives (MBON, OBIS, JCOMM, and GOOS) is an expedited, effective way to support international policy-level assessments (e.g., the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services or IPBES), along with the implementation of international development goals (e.g., the United Nations Sustainable Development Goals).
Keywords: essential biodiversity variables; essential ocean variables; global ocean observing system; GOOS; marine biological observations

Aerial visual survey of cetaceans and other megafauna in the Bremer Marine Park and surrounding areas - Phil J. Bouchet; Wellard, R; Christine Erbe; Jessica J. Meeuwig (2018)
Cetaceans are some of the most iconic animals on the planet, yet few of the 45 species of whales, dolphins and porpoises known to occur in Australian waters have been extensively studied to date. Historical commercial whaling records and recent modelling studies suggest that the submarine canyons within and around the Bremer Marine Park provide favourable habitats for a number of cetaceans, including sperm, beaked, and killer whales. The latter have been reported to concentrate in unprecedented numbers in the Bremer Sub-Basin over the austral summer months, forming what is likely the largest seasonal aggregation of the species in the Southern Hemisphere. However, little data on the animals’ ecology, population abundance, or movements currently exist, and while the majority of killer whale encounters have occurred around the heads of the Knob and Henry Canyons to date, it remains unclear whether this area represents a discrete and unique hotspot or whether the Bremer Marine Park may support additional aggregations. Under the NESP Emerging Priorities scheme, the Minister for the Environment and Energy, the Honourable Josh Frydenberg MP, accordingly committed research funds to the Marine Biodiversity Hub (MBH) to assess the extent and likely drivers of the Bremer megafauna hotspot, which is currently fuelling a rapidly growing tourism industry. As part of the programme, aerial surveys were implemented to assess the presence, numbers, behaviour and distribution of large air-breathing vertebrates throughout the region. The resulting data provide a critical baseline for understanding when and how cetaceans and other charismatic predators use the Bremer Marine Park. Such knowledge is key to helping managers and policy-makers meet national legislative requirements regarding the adequate conservation of Environment Protection and Biodiversity Conservation Act 1999 (EPBC Act) listed species
Keywords: aerial survey; cetaceans; killer whales; marine parks; megafauna

Assessing the size of Australia's white shark populations - Nicholas J. Bax (A unique combination of acoustic tagging and genetic and statistical advances has produced the first evidence-based population estimates for Australia’s white sharks., 2018)
A unique combination of acoustic tagging and genetic and statistical advances has produced the first evidence-based population estimates for Australia’s white sharks. Providing reliable information on the size and trend of Australia’s white shark populations has hitherto been an impossible task. Advances being made in this research ─ building coordinated national sampling regimes to measure key biological parameters using close-kin mark recapture, and conducting electronic tagging and targeted surveys, and combining these in population models ─ will significantly improve our understanding of white shark populations in Australia.

Australian shellfish ecosystems: Past distribution, current status and future direction - Chris L Gillies; Ian M. McLeod; Alleway, Heidi K.; Cook, Peter; Crawford, Christine; Colin Creighton; Ben K Diggles; Ford, John; Hamer, Paul; Gideon Heller-Wagner; Lebrault, Emma; Le Port, ès; et al. (PLOS ONE, 2018)
We review the status of marine shellfish ecosystems formed primarily by bivalves in Australia, including: identifying ecosystem-forming species, assessing their historical and current extent, causes for decline and past and present management. Fourteen species of bivalves were identified as developing complex, three-dimensional reef or bed ecosystems in intertidal and subtidal areas across tropical, subtropical and temperate Australia. A dramatic decline in the extent and condition of Australia’s two most common shellfish ecosystems, developed by Saccostrea glomerata and Ostrea angasi oysters, occurred during the mid-1800s to early 1900s in concurrence with extensive harvesting for food and lime production, ecosystem modification, disease outbreaks and a decline in water quality. Out of 118 historical locations containing O. angasi-developed ecosystems, only one location still contains the ecosystem whilst only six locations are known to still contain S. glomerata-developed ecosystems out of 60 historical locations. Ecosystems developed by the introduced oyster Crasostrea gigas are likely to be increasing in extent, whilst data on the remaining 11 ecosystem-forming species are limited, preventing a detailed assessment of their current ecosystem-forming status. Our analysis identifies that current knowledge on extent, physical characteristics, biodiversity and ecosystem services of Australian shellfish ecosystems is extremely limited. Despite the limited information on shellfish ecosystems, a number of restoration projects have recently been initiated across Australia and we propose a number of existing government policies and conservation mechanisms, if enacted, would readily serve to support the future conservation and recovery of Australia’s shellfish ecosystems.
Keywords: mussel; oyster; Reef; restoration; shellfish

Avoiding the collision course - David Peel; Joshua N. Smith; Simon Childerhouse (ECO Magazine, 2018)
Attitudes about collisions between whales and vessels have changed drastically since this account from a newspaper in 1891. Rather than sensational, we now view such incidents as tragic, and internationally, vessel strikes are recognized as a potential threat to whale populations. Worldwide, the main species affected by vessel collisions are fin whales, followed by humpback, northern right, gray, minke, sperm, southern right and blue whales. During the last two centuries of whaling almost all of these species were brought to the brink of extinction. The recovery of these species and their local populations has varied considerably from place to place. Many populations of these whales are still dangerously small (e.g., northern right, western grey, blue whales). For these small populations, vessel collision is primarily an issue of conservation. But, it is also an animal welfare and ethical issue. This is particularly relevant for populations such as the Australian humpback whale which, while showing strong recovery from commercial whaling, is still impacted by vessel strike. Ironically, their healthy return towards pre-whaling numbers is likely to make vessel strikes more common in the future due to more whales being in the ocean. In addition to the immense changes experienced by whale populations over the last 100 years, worldwide shipping has also seen extensive change over this same period. Shipping is the life blood of modern economies, connecting and providing the mass transportation for over 80 percent of global goods and resources. Consequently, there has been a massive increase in the overall volume of global shipping traffic. For example, the number of vessels in the worldwide merchant fleet has increased by 13 percent in the last seven years (UNCTAD 2018) and future projections show this growth will continue. There have also been considerable changes in the size, type, and speed of vessels. This is relevant to vessel strike as different vessels have different risk profiles. This change is reflected in our collated data of vessel strikes in Australian waters which showed a steady increase in the average length of vessels colliding with whales between 1890 and 1950. Interestingly, fewer reports of large vessel collisions were made after the 1950s. This is possibly because there are fewer crew on-board the newer vessels, raising the important question of how many collisions are going unnoticed.
Keywords: vessel strikes; whales

Benefit-cost analysis for marine habitat restoration: a framework for estimating the viability of shellfish reef repair projects - Abbie A Rogers; Chris L Gillies; Hancock, Boze; Ian M. McLeod; Nedosyko, Anita; Reeves, Simon; Soloranzo, Luis; Michael P. Burton (2018)
Coastal habitat loss is a global problem, including degradation of shellfish reefs, coral reefs, seagrass meadows, salt marshes, and kelp and mangrove forests. A growing interest has developed in the ability to restore these habitats as a means to replace lost habitat, restore ecosystem productivity and reduce the impacts of coastal hazards such as erosion and inundation (McLeod et al. 2018). A delegation of experts at the Australian Coastal Restoration Symposium identified numerous key factors affecting the advancement of restoration projects in Australia.
Keywords: benefit-cost; coastal restoration; project prioritisation; project viability; shellfish reef

Benefit-cost analysis of the Windara shellfish reef restoration project - Abbie A Rogers; Anita Nedosyko; Ian M. McLeod; Chris L Gillies; Michael Burton (2018)
Windara Reef is the largest underwater marine habitat restoration attempt made in Australia to construct a native oyster reef. There has been wide-scale loss of shellfish habitats globally, and they are functionally extinct in many parts of Australia including South Australia where the Windara construction is located. Restoration is therefore important for the survival of these habitats, but requires significant financial investment. To justify investments of this nature, it is important to identify the economic benefits and costs of restoration projects, and wherever possible to ensure that these assessments include as many of the non-market values as possible. Using benefit-cost analysis, we have undertaken an integrated economic assessment of the viability of the Stage Two 16ha restoration project led by The Nature Conservancy. This analysis was inclusive of the tangible, market-based outcomes of the project and also the intangible, non-market social and environmental outcomes. Specifically, the following costs and benefits were included in the analysis:
Keywords: benefit-cost analysis; economic assessment; non-market value; Reef restoration

Bremer Canyon - Final report - Phil J. Bouchet; Jessica J. Meeuwig; Christine Erbe; Salgado-Kent, Chandra; Wellard, R; Pattiaratchi, Charitha (2018)
Approximately 70 kilometres south-east of Bremer Bay (119.4°E, 34.4°S) off southern Western Australia’s coast lies a group of submarine canyons that incise the continental slope, plunging to depths of more than 1,000 metres. Charismatic pelagic organisms such as cetaceans, sharks, seabirds and squid are known to concentrate in high abundance above these features. In particular, the canyons are the site of the largest reported seasonal aggregation of killer whales (Orcinus orca) in the Southern Hemisphere, with over 100 identified individuals in the local population, many of which are regularly sighted. Existing data suggest that the majority of killer whale encounters occur west of the Bremer Marine Park, around the heads of the Knob and Henry Canyons. It is unclear, however, whether this area represents a discrete and unique killer whale hotspot or whether the park may support other aggregations, be they from separate individuals or the same animals frequenting the hotspot. Furthermore, the mechanisms underpinning ocean productivity in these otherwise relatively oligotrophic waters remain largely unresolved.
Keywords: acoustics; aerial survey; glider oceanography; mid-water video cameras; orca

Changes in pressures on the marine environment over three decades - Piers K Dunstan (2018)
Pressures in the marine environment will change the status and trends of many different values (ecological, social and economic). However, an understanding of how pressure has changed around Australia has not been available until now. This analysis shows that pressure in all the marine regions (Temperate-East, South-East, South-West, North-West and North) is highly variable and changes as a function of regulatory, social and economic interests. There is a general pattern of decreases in fisheries and increases in oil and gas and shipping activities. Increased cumulative pressure especially evident in the South-West due to increases in some fisheries, anthropogenic noise and climate change. However, all other marine regions show increases in many combinations of pressure and climate change remains present in all regions. The overlaps with matters of national environmental significance (MNES) are identified and may be responsible for changes in their status. It is recommended that the next stage of this work is to identify which pressures affect each MNES (and by how much) and use this information to develop national heat maps that identify for each MNES where the cumulative pressures are greatest. The pressure data has been collated, supplied to the Department of the Environment and Energy (DoEE), available through web services, and used in the 2016 State of the Environment (SOE) report.
Keywords: cumulative pressure; pressure

A close-kin mark-recapture estimate of the population size and trend of east coast grey nurse shark - R. W. Bradford; Russell J. Thomson; Mark Bravington; Foote, D; R. Gunasekera; Barry Bruce; David Harasti; Otway, N; Pierre Feutry (2018)
A close-kin mark-recapture estimate of the population size and trend of east coast grey nurse shark - was initiated to provide a contemporary population estimate of the eastern grey nurse shark (Carcharias taurus) using emerging genetic and statistical techniques. It follows on from the successful National Assessment of the Status of White Sharks (A3) project and uses a modification of the population-dynamics model used to derive a population estimate for white sharks. Importantly, due to the absence of age estimates as well as the unreliable length estimates of the sampled grey nurse shark (GNS), the GNS model had to be more elaborate to account for greater kinship possibilities. The grey nurse shark, Carcharias taurus (GNS), is distributed primarily within the continental shelf zones of tropical and temperate regions of the North and South Atlantic, Indian and western Pacific oceans (Last & Stevens, 2009) to depths of at least 230 m (Otway and Ellis 2011). In Australia, two distinct subpopulations are recognised, one along the eastern seaboard of Australia, the other along the western seaboard. Within Australia the distribution of the eastern population extends approximately 2,700 km from central Queensland south to at least the New South Wales (NSW)/Victorian border (Otway et al. 2003; Bansemer 2009; Otway and Ellis 2011). The western population extends across a similar distance of the West Australian coastline from the North West Shelf south to at least Cocklebiddy in the Great Australian Bight (McAuley et al. 2002; Cavanagh et al. 2003; Chidlow et al. 2005). This project was focussed on deriving an abundance estimate of the eastern Australian GNS population.   The species is listed as “vulnerable” on the IUCN Red List of Threatened Species (Pollard & Smith 2009) as a result of observed declines in GNS numbers worldwide. The eastern Australian population has been declared “critically endangered” under the Australian Environment Protection and Biodiversity Conservation Act 1999 (EPBC Act) and as such is the subject of an on-going recovery plan. This publication addresses Objective 1 of the 2014 recovery plan: Develop and apply quantitative monitoring of the population status (distribution and abundance) and potential recovery of the grey nurse shark in Australian waters (Australian Government Department of the Environment 2014).
Keywords: close-kin mark-recapture; grey nurse shark

Comparative assessment of pelagic sampling methods used in marine monitoring - Phil J. Bouchet; Phillips, Claire; Z Huang; Jessica J. Meeuwig; Scott D Foster; Rachel Przeslawski (2018)
Australia’s Exclusive Economic Zone (EEZ) is the third largest maritime territory in the world. Monitoring its dynamics is fundamental to understanding and reporting on how the ocean is responding to human pressures and global environmental change. Increasingly stringent conservation budgets, however, are placing a strong emphasis on strategic resource allocation. Faced with mounting pressures to build accountability, managers and policy advisors must now more than ever make monitoring investment decisions that are both impactful and cost-effective. This can be challenging given the smorgasbord of modern survey tools currently available, most of which differ widely in costs, capabilities, mobilisation constraints, resolution, or sensitivity, and are evolving rapidly without always being critically evaluated or compared.
Keywords: Marine protected areas; monitoring; pelagic ecosystems; sampling methods; standard protocols

Comparative assessment of seafloor sampling platforms - Rachel Przeslawski; Scott D Foster; Jacquomo Monk; Tim J. Langlois; Vanessa L Lucieer; Rick D Stuart-Smith (2018)
The Australian Marine Parks are the largest network of marine protected areas in the world, and their establishment means that Australia is now tasked with managing an area almost 3.3 million km2. In addition, Australia has the third largest exclusive economic zone in the world, with an extensive geographic area on which to report for State of Environment. The vastness of Australia’s marine estate means that appropriate, efficient, and comparable sampling methods are crucial to meet management and reporting obligations. The overarching objectives of environmental monitoring are to assess condition and detect trends, and numerous marine sampling platforms exist to acquire data to meet these needs. It is daunting to consider all marine sampling platforms in the context of a single monitoring program and to ensure that the most appropriate methods are used for a given purpose. There is thus a need to synthesise and compare these platforms as they relate to the design and implementation of monitoring programs. The purpose of the current study is to describe and comparatively assess common seafloor sampling platforms. We do this by conducting a qualitative assessment and comprehensively reviewing the available literature to identify their potential limitations and advantages. For the purposes of this report, marine sampling platforms include those that acquire seafloor data using underwater equipment or methods. We focus on sampling platforms near (i.e. demersal) or at (i.e. benthic) the seafloor because the habitat and associated biota targeted by these platforms are usually fixed and can be revisited, making them well-suited to monitoring activities.
Keywords: acoustics; auv; box core; BRUV; drop camera; grab; multibeam; ROV; sled; towed video; trawl; UVC

Desktop review of Indigenous research and management priorities for threatened and migratory species - Christy Davies; PM Kyne (North Australian Indigenous Land and Sea Management Alliance, 2018)
This report aims to provide a brief overview of marine animal species of importance to Indigenous communities in the Northern Territory, including the Gulf of Carpentaria andwestern Cape York (collectively encompassing the North Marine Bioregion), based primarily on a desktop study of readily available written materials. Following this desktop component, information from this review will be considered alongside the outcomes of consultations with Indigenous community members/groups to provide a more comprehensive view of ‘priority’ marine fauna for future research. To effectively inform research and management actions, a complementary purpose in this report (and project more broadly) is to identify local practical responses to species specific research and management needs, articulated through the kind of social and cultural context summarised above. This includes discussion about appropriate principles for engaging Indigenous individuals and organisations in discussion about and research on their country. This work is part of a broader collaborative research project titled “Scoping a seascape approach to managing and recovering northern Australian threatened and migratory marine species” (herein referred to as ‘the Northern Seascapes project’) being delivered under the Marine Biodiversity Hub of the Commonwealth Government’s National Environmental Science Program (NESP). The project is led by Charles Darwin University (CDU) and involves the Australian Institute of Marines Science (AIMS), the Commonwealth Scientific and Industrial Research Organisation (CSIRO) and Geoscience Australia. The purpose of the Northern Seascapes Project is to scope research needs and directions for a 3-year (2018-2020) collaborative, multi-disciplinary NESP Northern Seascape project by synthesising the (albeit preliminary) findings of constitutive scoping components to inform future research strategies and identify future research hotspots. The geographical scope of the project is the North Marine Bioregion, from coastal and estuarine habitats to the edge of the Australian Exclusive Economic Zone, and there is a focus on Environment Protection and Biodiversity Conservation Act 1999 (EPBC Act) listed Threatened and Migratory Marine species (TMMS).
Keywords: Indigenous engagement; Northern Australia; threatened species

Developing indicators and a baseline for monitoring demersal fish in data-poor offshore Marine Parks using probabilistic sampling - Nicole A. Hill; Neville Barrett; Jessica H. Ford; David Peel; Scott D Foster; E Lawrence; Jacquomo Monk; Althaus, Franziska; K Hayes (Ecological Indicators, 2018)
The number of Marine Protected Areas (MPAs) has increased globally as concerns over the impact that human activities are having on the world’s oceans have also increased. Monitoring is a key requirement to determine if MPAs are meeting their objectives. However, many recently declared MPA’s are large, offshore, or form part of an expansive network and spatial information about the habitats, communities and species that they contain is often lacking. This presents challenges for deciding exactly what to monitor and developing strategies on how to monitor it efficiently. Here we examine these issues using the Flinders Marine Park in Australia as a case study. We trial a two-stage version of a spatially-balanced, probabilistic sampling design combined with Baited Remote Underwater Videos (BRUVs) to perform an initial inventory, and we evaluate the potential of six commercially and ecologically important demersal fish as indicators within the Marine Park. Using this approach we were able to (1) quantitatively describe the distribution of the fish species in the Marine Park; (2) establish quantitative and representative estimates of their abundance throughout the Marine Park to serve as a baseline for future monitoring; (3) conduct power analyses to estimate the magnitude of increase we may be able to detect with feasible levels of sampling effort. Power analysis suggested that for most of our potential indicator species, detecting increases in abundance as small as 50% from present values should be feasible if sampling is restricted to a species’ preferred habitat and the same sites are sampled through time. Our approach is transferrable to other regions where monitoring programs must be designed based on limited spatial and biological data, assisting with decisions on what and how to monitor.
Keywords: Baited Remote Underwater Videos (BRUV); Generalised Random Tessellation Stratified (GRTS) sampling; Marine Protected Area (MPA); Spatially-balanced sampling

Differential vulnerability to climate change yields novel deep-reef communities - Marzloff, Martin Pierre; Oliver, Eric C. J.; Neville Barrett; Holbrook, Neil J.; James, Lainey; Wotherspoon, Simon J.; Craig R. Johnson (Nature Climate Change, 2018)
The effects of climate-driven ocean change on reef habitat-forming species are diverse and can be deleterious to the structure and functioning of seafloor communities. Although responses of shallow coral- or seaweed-based reef communities to environmental changes are a focus of ecological research in the coastal zone, the ecology of habitat-forming organisms on deeper mesophotic reefs remains poorly known. These reefs are typically highly biodiverse and productive as a result of massive nutrient recycling. Based on seafloor imagery obtained from an autonomous underwater vehicle8, we related change in community composition on deep reefs (30–90 m) across a latitudinal gradient (25–45° S) in southeastern Australia to high-resolution environmental and oceanographic data, and predicted future changes using downscaled climate change projections for the 2060s. This region is recognized as a global hotspot for ocean warming. The models show an overall tropicalization trend in these deep temperate reef communities, but different functional groups associate differentially to environmental drivers and display a diversity of responses to projected ocean change. We predict the emergence of novel deep-reef assemblages by the 2060s that have no counterpart on reefs today, which is likely to underpin shifts in biodiversity and ecosystem functioning. View-only version of paper freely provided by publisher <a href="http://em.rdcu.be/wf/click?upn=lMZy1lernSJ7apc5DgYM8bYwGwT41nJutpRmTS4NIEc-3D_GjRFCNGdMNqdt7rSVIqdHzwjccuoZxbWrX1hfuXZ-2BhiTqoD9U9xSTHNMalYIp7vxWump4v6sxGVRQaiXXJWrk-2BwYv7ljwHwlR-2FPjsvFavWcbI0oYHVGsmW9PKKYjcDVsBMqKWBN3WUoqfG-2FjK9wi-2BcE-2FYq1049lyGiQKnkQouCvncVwOTjsbOUD8HSsK7YEVs6sjPrcvalXj7lm-2FaDuQtsepyUCZBGanXJcFognjf6T8BEt5faqDwDni4o9GaHNP2LaKk5X7m5pYY-2FYiFQpBbg-3D-3D" rel="nofollow">https://rdcu.be/7Dg3
Keywords: Autonomous underwater vehicle; climate prediction; continental shelf reef; imagery; morphospecies; sessile marine invertebrates

An eco-narrative of Geographe Marine Park - South-west marine region - Ronen Galaiduk; Nanson, Rachel; Z Huang; Scott L Nichol; Karen J Miller (2018)
This report is one in a series of eco-narrative documents that synthesise our existing knowledge of Australia’s individual Marine Parks. This series is a product of the National Environmental Science Program Marine Biodiversity Hub Project D1, which seeks to collate, synthesise and visualise biophysical data within the parks. These documents are intended to enable managers and practitioners to rapidly ascertain the ecological characteristics of each park, and to highlight knowledge gaps for future research focus. Geographe Marine Park contains areas of high biodiversity and benthic productivity, although much of the Marine Park has not been surveyed. The Park contains some of the largest continuous seagrass meadows in Australia. These act as feeding, breeding, resting and nursery grounds for migratory and threatened seabirds, whales and numerous fish species. Because seagrass communities are particularly susceptible to changes in water quality, they are under constant threat from a range of potential stressors. These include an increase in human population on the adjacent coastline, high levels of regional nutrient flow from runoff, growth in tourism, recreational and commercial fishing, introduced marine pests, and global climate change. While our existing knowledge of these threats is insufficient to detect the full extent of current impacts or to predict future ones, an overall loss in the shallow water seagrass cover from 2004 and 2007 has occurred. The information in this eco-narrative collates all the existing information to form an initial characterisation of Geographe Marine Park to help better understand its ecosystem structure. However, most of our knowledge of ecosystems in the marine park are those based on seagrass. We know very little about other ecosystems, particularly deeper offshore habitats which represent approximately 50% of the marine park. Related information Australian Marine Parks Science Atlas
Keywords: Australian Marine Parks; eco-narrative; ecological values

An eco-narrative of Gifford Marine Park - Temperate East marine region - Nanson, Rachel; Andrew Carroll; Z Huang; Scott L Nichol; Karen J Miller (2018)
This report is one in a series of eco-narrative documents that synthesise our existing knowledge of Australia’s individual Marine Parks. This series is a product of the National Environmental Science Program Marine Biodiversity Hub Project D1, which seeks to collate, synthesise and visualise biophysical data within the parks. These documents are intended to enable managers and practitioners to rapidly ascertain the ecological characteristics of each park, and to highlight knowledge gaps for future research focus. The Gifford Marine Park is dominated by two submerged flat-topped seamounts (guyots) that rise up to three kilometres above the surrounding abyssal plain and provide a diversity of benthic environments. These range from gently sloping plains atop the seamount plateaus to near-vertical towering cliffs of exposed bedrock that encircle both seamounts, and abyssal plains that characterise the northern third of the park. Depositional cones and mass movement scars alternate around the upper to mid slopes of the seamounts, and illustrate the processes by which these extant volcanic features are undergoing escarpment retreat. The information in this eco-narrative forms an initial characterisation of Gifford Marine Park. The key gaps in our knowledge of the park are its specific oceanographic processes and its ecological significance; only limited ecological and oceanographic sampling has been undertaken within the park. Surveys have revealed lower than expected species richness and abundance, likely linked to the nutrient-poor waters over the Gifford guyot. Nevertheless, the extensive escarpment surfaces and the relatively shallow plateau surfaces do provide important habitat for sparse epibenthic communities. Sea surface temperatures within the park display only a slight warming trend since 2002, at an annual rate of 0.016oC. Targeted oceanographic and more extensive biological surveys over both seamounts are needed to develop a more informed overall assessment of the biological significance of the park ecosystem and identify potential anthropogenic threats to park health. Related information Video - Flythrough of seafloor bathymetry of the Gifford Marine Park Australian Marine Parks Science Atlas
Keywords: Australian Marine Parks; eco-narrative; ecological values

An eco-narrative of Perth Canyon Marine Park - South-west marine region - Nanson, Rachel; Z Huang; Phil J. Bouchet; Scott L Nichol; Karen J Miller (2018)
This report is one in a series of eco-narrative documents that synthesise our existing knowledge of Australia’s individual Marine Parks. This series is a product of the National Environmental Science Program Marine Biodiversity Hub Project D1, which seeks to collate, synthesise and visualise biophysical data within the parks. These documents are intended to enable managers and practitioners to rapidly ascertain the ecological characteristics of each park, and to highlight knowledge gaps for future research focus. Perth Canyon Marine Park encompasses a diversity of benthic environments, ranging from gently sloping soft sediment plains to near-vertical towering cliffs of exposed bedrock. This geodiversity extends from the head of Perth Canyon at the shelf break to the slope-confined submarine canyons that dissect the lower continental slope. Spanning almost 4.5 km of ocean depths, Perth Canyon dominates the park and has a significant influence on the local ecosystem across the food chain. The size and location of the canyon is such that it promotes upwelling from the deep ocean, leading to plankton blooms that attract seasonal aggregations of larger pelagic fish, including whales. Over geological time, the canyon has evolved to provide extensive areas of benthic habitat suitable for deep-sea corals and sponges. The park is not without environmental pressures, however, with evidence that marine heat waves can affect the health of the ecosystem at upper trophic levels. The information in this eco-narrative forms an initial characterisation of Perth Canyon Marine Park. Our knowledge of the park and of Perth Canyon in particular, is such that we can now better understand its ecosystem structure, which can be used to inform management and monitoring into the future. The key gap in our scientific knowledge of the park ecosystem is in the deepest areas, particularly for benthic communities on the lower continental slope to abyss. Targeted oceanographic and biological surveys covering these deep-water locations and to understand links between the deepest areas and the Perth Canyon in particular would contribute to an improved overall understanding of the park ecosystem. The importance of Perth Canyon Marine Park to seabird communities is also a recognised gap in our knowledge of this ecosystem. Related information Video - Seafloor bathymetry of the Perth Canyon Marine Park Australian Marine Parks Science Atlas
Keywords: Australian Marine Parks; eco-narrative; ecological values

Ecosystem restructuring along the Great Barrier Reef following mass coral bleaching - Rick D Stuart-Smith; Christopher Brown; Daniela Ceccarelli; Graham J. Edgar (Nature, 2018)
Global warming is dramatically changing diverse coral reef ecosystems through an increasing frequency and magnitude of mass bleaching events. How local impacts scale up over affected regions depends on numerous factors, including patchiness in coral mortality, metabolic effects of extreme temperatures on populations of reef-dwelling species, and interactions between taxa. Here we use ‘before and after’ data to evaluate ecological change in corals, algae, fishes and mobile invertebrates at 186 sites along the full latitudinal span of the Great Barrier Reef and western Coral Sea following the 2016 mass bleaching event. One year post-bleaching, reductions in live coral cover of up to 51% were observed on surveyed reefs that experienced extreme temperatures, but regional patterns of coral mortality were patchy. Consistent declines of coral-feeding fishes were evident at the most heavily impacted reefs, whereas few other short-term responses of reef fishes and invertebrates could be attributed directly to changes in coral cover. Nevertheless, substantial region-wide ecological changes occurred that were largely independent of coral loss, and instead appeared directly linked to sea temperatures. Community-wide trophic restructuring was evident, with weakening of strong pre-existing latitudinal gradients in the diversity of fishes, invertebrates and their functional groups. In particular, fishes that scrape algae from reef surfaces, considered important for recovery following bleaching, declined on northern reefs, whereas other herbivorous groups increased on southern reefs. The full impact of the 2016 bleaching event may not be realised until dead corals erode through the next decade, but our short-term observations suggest that recovery processes, and the ultimate scale of impact, are affected by functional changes in communities, which in turn depend on the thermal affinities of local reef-associated fauna. Such change will vary geographically, and may be particularly acute at locations where many fishes and invertebrates are close to their thermal distribution limits.

Essential ocean variables for global sustained observations of biodiversity and ecosystem changes - Miloslavich, Patricia; Nicholas J. Bax; Simmons, Samantha E.; Klein, Eduardo; Appeltans, Ward; Aburto-Oropeza, Octavio; Andersen Garcia, Melissa; Sonia D. Batten; Benedetti-Cecchi, Lisandro; David Checkley; Chiba, Sanae; Duffy, J. Emmett; et al. (Global Change Biology, 2018)
Sustained observations of marine biodiversity and ecosystems focused on specific conservation and management problems are needed around the world to effectively mitigate or manage changes resulting from anthropogenic pressures. These observations, while complex and expensive, are required by the international scientific, governance and policy communities to provide baselines against which the effects of human pressures and climate change may be measured and reported, and resources allocated to implement solutions. To identify biological and ecological essential ocean variables (EOVs) for implementation within a global ocean observing system that is relevant for science, informs society, and technologically feasible, we used a driver‐pressure‐state‐impact‐response (DPSIR) model. We examined relevant international agreements to identify societal drivers and pressures on marine resources and ecosystems, evaluated the temporal and spatial scales of variables measured by 100+ observing programs, and analysed the impact and scalability of these variables and how they contribute to address societal and scientific issues. EOVs were related to the status of ecosystem components (phytoplankton and zooplankton biomass and diversity, and abundance and distribution of fish, marine turtles, birds and mammals), and to the extent and health of ecosystems (cover and composition of hard coral, seagrass, mangrove and macroalgal canopy). Benthic invertebrate abundance and distribution and microbe diversity and biomass were identified as emerging EOVs to be developed based on emerging requirements and new technologies. The temporal scale at which any shifts in biological systems will be detected will vary across the EOVs, the properties being monitored and the length of the existing time‐series. Global implementation to deliver useful products will require collaboration of the scientific and policy sectors and a significant commitment to improve human and infrastructure capacity across the globe, including the development of new, more automated observing technologies, and encouraging the application of international standards and best practices.
Keywords: driver-pressure-state-impact-response; essential ocean variables; framework for ocean observing; global ocean observing system; marine biodiversity changes; Marine Biodiversity Observation Network; ocean change

Estimating the potential fishery benefits from targeted habitat repair: a case study of School Prawn (Metapenaeus macleayi) in the lower Clarence River Estuary - Taylor, Matthew D.; Creighton, Colin (Wetlands, 2018)
Development around estuaries leads to degradation of tidal wetlands and alteration of tidal flows, which impacts on fishery productivity. Contemporary management seeks to lessen land-use impacts on aquatic environments and restore ecosystem services, and knowledge of potential benefits will inform investment and galvanize community action. We present a framework to estimate the potential benefits that may be derived from wetland repair, demonstrated through a case study for School Prawn (Metapenaeus macleayi) in Lake Wooloweyah, Clarence River estuary. Under a scenario of good School Prawn recruitment, habitat repair could yield a benefit of ~94 kg ha−1 of subtidal creek habitat, equating to a gross value of around AUD876 ha−1 and total output of around AUD5,175 ha−1 annually. Upscaling these calculations to reflect a scenario restoring 27.6 ha of subtidal channels at the mouth of Lake Wooloweyah would contribute an expected annual yield of 2569 kg in School Prawn harvest. These estimates are conservative, not accounting for the economic outcomes derived from other species directly utilising the additional habitat, or the outwelling of additional saltmarsh-derived productivity. Simple models such as this are useful for assessing the potential benefits of habitat repair, and supporting investment of resources into on-ground works.
Keywords: fisheries productivity; habitat rehabilitation; habitat restoration; mangrove; recruitment; salt marsh

An evaluation of the error and uncertainty in epibenthos cover estimates from AUV images collected with an efficient, spatially-balanced design - Jacquomo Monk; Neville Barrett; David Peel; E Lawrence; Nicole A. Hill; Vanessa L Lucieer; K Hayes (PLOS ONE, 2018)
Efficient monitoring of organisms is at the foundation of protected area and biodiversity management. Such monitoring programs are based on a systematically selected set of survey locations that, while able to track trends at those locations through time, lack inference for the overall region being “monitored”. Advances in spatially-balanced sampling approaches offer alternatives but remain largely untested in marine ecosystems. This study evaluated the merit of using a two-stage, spatially-balanced survey framework, in conjunction with generalized additive models, to estimate epifauna cover at a reef-wide scale for mesophotic reefs within a large, cross-shelf marine park. Imagery acquired by an autonomous underwater vehicle was classified using a hierarchical scheme developed under the Collaborative and Automated Tools for Analysis of Marine Imagery (CATAMI). At a realistic image subsampling intensity, the two-stage, spatially-balanced framework provided accurate and precise estimates of reef-wide cover for a select number of epifaunal classes at the coarsest CATAMI levels, in particular bryozoan and porifera classes. However, at finer hierarchical levels, accuracy and/or precision of cover estimates declined, primarily because of the natural rarity of even the most common of these classes/morphospecies. Ranked predictor importance suggested that bathymetry, backscatter and derivative terrain variables calculated at their smallest analysis window scales (i.e. 81 m2) were generally the most important variables in the modeling of reef-wide cover. This study makes an important step in identifying the constraints and limitations that can be identified through a robust statistical approach to design and analysis. The two-stage, spatially-balanced framework has great potential for effective quantification of epifaunal cover in cross-shelf mesophotic reefs. However, greater image subsampling intensity than traditionally applied is required to ensure adequate observations for finer-level CATAMI classes and associated morphospecies.
Keywords: Autonomous underwater vehicle; benthos cover; Flinders Australian Marine Park; Multibeam sonar; underwater imagery; upscaling

Expanding fish productivity in Tasmanian saltmarsh wetlands through tidal reconnection and habitat repair - Vishnu Prahalad; Harrison-Day, Violet; McQuillan, Peter; Colin Creighton (Marine and Freshwater Research, 2018)
Fish use of coastal saltmarsh wetlands has been documented for many parts of Australia with the notable exception of Tasmania. An initial investigation to examine the diversity, density and patterns of fish use in the Circular Head coast saltmarshes of north-west Tasmania was undertaken. To aid decision making in repair strategies, the effect of saltmarsh condition on fish assemblages was studied using paired sites of predominantly unaltered and altered saltmarshes where levees were present. In all, 851 fish from 11 species were caught in 37 of the 48 pop nets. Three species, Aldrichetta forsteri, Arripis truttaceus and Rhombosolea tapirina, are important to commercial and recreational fisheries and contributed ~20% of the total catch numbers. The mean density of >72 fish per 100 m2 is the highest yet reported from Australian studies and indicates that Tasmanian saltmarshes provide higher value habitat for fish compared with elsewhere in Australia, likely due to more frequent and prolonged flooding, and the lack of adjacent mangroves. There was no significant difference in fish assemblages between unaltered and altered marshes. The results suggest that restoring basic saltmarsh structure through tidal reconnection will deliver substantial benefits for fish productivity through habitat expansion.
Keywords: Biodiversity; coastal management; ecological restoration; ecosystem services; salt marsh; seascapes; temperate fish communities; wetland conservation

Field manuals for marine sampling to monitor Australian waters - Rachel Przeslawski; Scott D Foster; Vanessa L Lucieer; Jacquomo Monk; Phil J. Bouchet; Tim J. Langlois; Andrew Carroll; Joel Williams; Neville Barrett; Althaus, Franziska; Beaman, Robin J.; Berents, Penny; et al. (2018)
Australia has one of the world’s largest marine estates that includes many vulnerable habitats and a high biodiversity, with many endemic species crossing a wide latitudinal range. The marine estate is used by a variety of industries including fishing, oil & gas, and shipping, in addition to traditional, cultural, scientific and recreational uses. The Commonwealth government has recently established the Australian Marine Parks (AMPs), the largest network of marine protected areas in the world, complementing existing networks in State and Territory waters. Monitoring the impacts of these uses on the marine environment is a massive shared responsibility that can only be achieved by making the best use of all the information that is collected. Australia now has a number of significant long-term marine monitoring and observing programs, as well as a national ocean data network. Without some common and agreed standards, much of the information collected will not be comparable with other areas or sectors. This may reduce its value to regional and national management, while the individual project or survey may lose the opportunity to interpret results in a regional or national context. We have therefore developed a suite of field manuals for the acquisition of marine benthic (i.e. seafloor) data from a variety of frequently-used sampling platforms so that data can become directly comparable in time and through space, thus supporting nationally relevant monitoring in Australian waters and the development of a monitoring program for the AMP network. This objective integrates with one of the eight high-level priorities identified by the National Marine Science Plan (2015-25): the establishment of national baselines and long-term monitoring. Related information Chapters can also be downloaded individually Field manual flyer
Keywords: monitoring; standard operating procedures; survey methods

Fish assemblages on reefs in the Hunter Marine Park and adjacent waters - Joel Williams; Alan Jordan; David Harasti (2018)
Rocky reefs form an important habitat on Australia’s continental shelf and are recognised as a Key Ecological Feature (KEF) in the Marine Bioregional Plans of which developing the Australian Marine Parks was one objective. Despite the national significance of rocky habitat on Australia’s continental shelf, very little is known about these systems beyond their value to the fishing industry. The Hunter Marine Park (HMP) located in the Temperate East management zone is situated between Port Stephens and Foster in New South Wales. The HMP is unique in that it borders the State-managed Port Stephens – Great Lakes Marine Park (PSGLMP), with the HMP extending from the state waters boundary at 3 nm offshore to across the continental shelf. Earlier research has revealed areas of reef in 80-100 m of water (mesophotic zone), within the HMP, although very little is known about the fish assemblages that inhabits reefs at these depths in this region. Stereo baited remote underwater video (stereo-BRUV) was used to sample the fish assemblages and benthic habitats on rocky reefs within the HMP and PSGLMP. To date we have completed three of the four intended surveys from 2016 to 2018. Preliminary results have shown that the fish assemblages of mesophotic rocky reefs are different to those which were recorded on shallower reefs in the PSGLMP. Despite this significant difference there were some similarities. This included a similar relative abundance of fishery-targeted species in the HMP when compared to the shallower sites within the PSGLMP. This milestone report outlines the surveys undertaken in the HMP and adjacent reefs in the PSGLMP in 2016 and 2017.
Keywords: BRUV; fish; Habitat; Mapping; Marine Park; Reef; Hunter

Flyer - Field manuals for marine sampling to monitor Australian waters - Rachel Przeslawski; Scott D Foster (2018)
The NESP Marine Biodiversity Hub has developed a suite of field manuals to describe a nationally consistent and defensible approach to marine data acquisition. With over 70 contributors from 30 agencies, the field manuals include information on marine survey design, pre-survey planning, gear deployment and retrieval, and data management. We encourage all users (or potential users) to give feedback and suggestions for future versions and manuals via our online questionnaire here. The field manuals can be downloaded in their entirety or as individual chapters.

Future directions in the research and management of marine snakes - Vinay Udyawer; Barnes, Peter; Bonnet, Xavier; Brischoux, çois; Crowe-Riddell, Jenna M.; ’Anastasi, Blanche; Fry, Bryan G.; Gillett, Amber; Goiran, Claire; Guinea, Michael L.; Heatwole, Harold; Michelle R. Heupel; et al. (Frontiers in Marine Science, 2018)
Marine snakes represent the most speciose group of marine reptiles and are a significant component of reef and coastal ecosystems in tropical oceans. Research on this group has historically been challenging due to the difficulty in capturing, handling, and keeping these animals for field- and lab-based research. Inexplicable declines in marine snake populations across global hotspots have highlighted the lack of basic information on this group and elevated multiple species as conservation priorities. With the increased interest in research on marine snakes, we conducted a systematic survey of experts to identify twenty key questions that can direct future research. These questions are framed across a wide array of scientific fields to produce much-needed information relevant to the conservation and management of marine snakes. View sea snake Images in the Hub catalogue
Keywords: Conservation; endangered species; management; policy; research priorities; sea krait; sea snake

Gear Up - Field manuals for marine sampling - Rachel Przeslawski; Scott D Foster (2018)
The NESP Marine Biodiversity Hub has developed a suite of field manuals to describe a nationally consistent and defensible approach to marine data acquisition. With over 70 contributors from 30 agencies, the field manuals include information on marine survey design, pre-survey planning, gear deployment and retrieval, and data management. Related information: Request a copy of the poster Download the Field manuals and flyer (and provide feedback via the questionnaire) Read the news story Marine sampling field manuals support biodiversity monitoring at a national scale. Download a pdf of the poster at Item link below
Keywords: monitoring; standard operating procedures; survey methods

Genetic relatedness reveals total population size of white sharks in eastern Australia and New Zealand - R. M. Hillary; Mark Bravington; T. A. Patterson; Grewe, P.; R. W. Bradford; Pierre Feutry; R. Gunasekera; Peddemors, V.; Werry, J.; Malcolm P. Francis; Duffy, C. A. J.; Bruce, B. D. (Scientific Reports, 2018)
Conservation concerns exist for many sharks but robust estimates of abundance are often lacking. Improving population status is a performance measure for species under conservation or recovery plans, yet the lack of data permitting estimation of population size means the efficacy of management actions can be difficult to assess, and achieving the goal of removing species from conservation listing challenging. For potentially dangerous species, like the white shark, balancing conservation and public safety demands is politically and socially complex, often leading to vigorous debate about their population status. This increases the need for robust information to inform policy decisions. We developed a novel method for estimating the total abundance of white sharks in eastern Australia and New Zealand using the genetic-relatedness of juveniles and applying a close-kin mark-recapture framework and demographic model. Estimated numbers of adults are small (ca. 280–650), as is total population size (ca. 2,500–6,750). However, estimates of survival probability are high for adults (over 90%), and fairly high for juveniles (around 73%). This represents the first direct estimate of total white shark abundance and survival calculated from data across both the spatial and temporal life-history of the animal and provides a pathway to estimate population trend. News story - Sibling DNA matches provide key data for white shark population estimates - 8 February 2018

Global patterns of change and variation in sea surface temperature and chlorophyll a - Piers K Dunstan; Scott D Foster; King, Edward; Risbey, James; ’Kane, Terence J.; Monselesan, Didier; Alistair J Hobday; Hartog, Jason R.; Thompson, Peter A. (Scientific Reports, 2018)
Changes over the scale of decades in oceanic environments present a range of challenges for management and utilisation of ocean resources. Here we investigate sources of global temporal variation in Sea Surface Temperature (SST) and Ocean Colour (Chl-a) and their co-variation, over a 14 year period using statistical methodologies that partition sources of variation into inter-annual and annual components and explicitly account for daily auto-correlation. The variation in SST shows bands of increasing variability with increasing latitude, while the analysis of annual variability in Chl-a shows mostly mid-latitude high variability bands. Covariation patterns of SST and Chl-a suggests several different mechanisms impacting Chl-a change and variance. Our high spatial resolution analysis indicates these are likely to be operating at relatively small spatial scales. There are large regions showing warming and rising of Chl-a, contrasting with regions that show warming and decreasing Chl-a. The covariation pattern in annual variation in SST and Chl-a reveals broad latitudinal bands. On smaller scales there are significant regional anomalies where upwellings are known to occur. Over decadal time scales both trend and variation in SST, Chl-a and their covariance is highly spatially heterogeneous, indicating that monitoring and resource management must be regionally appropriate. This article uses methods developed previously by the NERP Marine Biodiversity Hub as published in the 2014 article Twenty years of high-resolution sea surface temperature imagery around Australia: inter-annual and annual variability

Indigenous knowledge and cultural values of hammerhead sharks in Northern Australia - Karin Gerhardt (2018)
Sharks and rays are culturally significant animals for many Aboriginal and Torres Strait Islander groups. The roles they play in the lives of saltwater people are bound in the Indigenous knowledge that has been passed down from generation to generation. Hammerhead sharks are perhaps one of the sharks most easily recognised as having cultural significance for Indigenous people in Australia. The Indigenous knowledge that is available about hammerhead sharks is predominantly from the Torres Strait and that outcome may be attributed to the charismatic displays of hammerheads in art pieces, dances and stories that Torres Strait Island people share with the wider community. Indigenous knowledge (IK) is a place-based knowledge system, so IK from one island or mainland community is relevant only to that area, and rarely scales up to cover multiple language groups. IK is also predominantly an oral form of knowledge and is managed (or protected) through a complex lore system that may restrict its sharing or retelling to certain groups (e.g. women only, or young men going through initiation). There are two main language systems within the straits (Meriam mer and Kala Lagaw Ya) with 6 different dialects spoken at an island level. Torres Strait creole (Ailen tok) is a common language spoken across all parts of the Torres Strait to allow for trade and communication. IK from the Torres Strait is often shared through artwork, dance and songs. Many of the hammerhead references within these media not only have a spiritual base but involve descriptions of ecological processes e.g. hunting behaviours, seasonal timing, predator-prey interactions. Projects that seek to understand the breadth of knowledge that sits within local communities should aspire to meaningful and genuine collaboration and engagement with Traditional Owners. A major strength of the NESP Hammerhead project was recognising that Traditional Owner priorities may not align with the project objectives, timeline or research outcomes. In recognising this, multiple options for involvement and engagement were developed to ensure that Traditional Owners were aware of what research was going on in their sea country, and that there were a range of opportunities for involvement, and skill and knowledge transfer between all parties. The Indigenous communication and engagement component of the project was very successful. Involving Indigenous rangers in tagging field trips on their sea country was considered respectful and beneficial for both the scientists and rangers involved (e.g. skill exchange and relationship building). The detailed local knowledge that rangers were able to provide to the researchers in the Dunk Island area was extremely beneficial and resulted in successful tagging trips. Detailed observations from Torres Strait Islander people would have benefit to any future tagging/ecological studies that might be conducted in the Torres Strait.
Keywords: hammerhead shark; Sea Country; traditional ecological knowledge

Linking capacity development to GOOS monitoring networks to achieve sustained ocean observation - Nicholas J. Bax; Appeltans, Ward; Brainard, Russell; Duffy, J. Emmett; Piers K Dunstan; Hanich, Quentin; Harden Davies, Harriet; Hills, Jeremy; Miloslavich, Patricia; Muller-Karger, Frank Edgar; Simmons, Samantha; Aburto-Oropeza, O.; et al. (Frontiers in Marine Science, 2018)
Developing enduring capacity to monitor ocean life requires investing in people and their institutions to build infrastructure, ownership, and long-term support networks. International initiatives can enhance access to scientific data, tools and methodologies, and develop local expertise to use them, but without ongoing engagement may fail to have lasting benefit. Linking capacity development and technology transfer to sustained ocean monitoring is a win-win proposition. Trained local experts will benefit from joining global communities of experts who are building the comprehensive Global Ocean Observing System (GOOS). This two-way exchange will benefit scientists and policy makers in developing and developed countries. The first step toward the GOOS is complete: identification of an initial set of biological Essential Ocean Variables (EOVs) that incorporate the Group on Earth Observations (GEO) Essential Biological Variables (EBVs), and link to the physical and biogeochemical EOVs. EOVs provide a globally consistent approach to monitoring where the costs of monitoring oceans can be shared and where capacity and expertise can be transferred globally. Integrating monitoring with existing international reporting and policy development connects ocean observations with agreements underlying many countries’ commitments and obligations, including under SDG 14, thus catalyzing progress toward sustained use of the ocean. Combining scientific expertise with international capacity development initiatives can help meet the need of developing countries to engage in the agreed United Nations (UN) initiatives including new negotiations for the conservation and sustainable use of marine biological diversity of areas beyond national jurisdiction, and the needs of the global community to understand how the ocean is changing.
Keywords: capacity development; essential ocean variables; global ocean observing system; GOOS; international reporting; monitoring; SDG14; technology transfer

Local densities and habitat preference of the critically endangered spotted handfish (Brachionichthys hirsutus): Large scale field trial of GPS parameterised underwater visual census and diver attached camera - Lincoln Wong; T P Lynch; Neville Barrett; Wright, Jeffrey T.; Mark Green; Flynn, David J. H. (PLOS ONE, 2018)
The critically endangered spotted handfish (Brachionichthys hirsutus) is restricted to a limited number of locations in south-eastern Tasmania, Australia. As is often the case for rare species, conducting statistically adequate surveys for B. hirsutus can be costly and time consuming due to the low probability of encountering individuals. For the first time we used a highly efficient and rigorous Global Positioning System (GPS) parameterised underwater visual census (GUVC) to survey B. hirsutus abundance within all nine known local populations in the Derwent Estuary within one season. In addition, a benthic microhabitat assessment was conducted simultaneously using a GoPro® camera attached to diver to determine B. hirsutus microhabitat preferences. B. hirsutus local populations varied between sites, with densities ranging from 1.58 to 43.0 fishes per hectare. B. hirsutus demonstrates a strong preference for complex microhabitat features, such as depressions and ripple formations filled with biogenic substrates (e.g. shells) but avoids simple, low relief microhabitats (e.g. sand flats) and areas dominated by ephemeral, filamentous algae. Complex microhabitats may enable B. hirsutus to avoid predators, increase forage opportunities or provide higher quality spawning sites. This first wide-scale application of GUVC for B. hirsutus allowed us to survey a larger number of sites than previously possible to provide a robust reference point for future long-term monitoring.
Keywords: action camera; habitat selection; power analysis; south-east Tasmania; species-habitat relationships; Underwater visual census (UVC)

Monitoring Population Dynamics of ‘Western’ Right Whales off Southern Australia - Final Report on activities for 2017 - John Bannister (2018)
To continue an annual series of aerial surveys off the southern Australian coast between Cape Leeuwin WA and Ceduna SA since 1993, a survey was undertaken over five days, 23-27 August, 2017. A total of 1546 animals was sighted, including 506 calves and 4 ‘yearlings’; these include double counts, given that each flying leg is covered twice, ‘outward’ and ‘inward’. Additionally 13 humpback whales, including three calves, were recorded (Table 1). For comparison with previous years’ results, maximum counts for each leg are taken; for the 2017 survey, the comparable counts are 847 individuals of which 303 were cows accompanied by calves of the year. The 2017 counts are the highest yet in the series. From 5603 photographic images obtained, 487 have been selected for computer-assisted ‘matching’ with those (some 9000 images of over 2000 individuals) already available in the catalogue. Regression analysis of log number against year for 1993-2017 gives increase rates for all animals of 0.0547 (95% CI 0.0392-0.0703) equivalent to a percentage increase of 5.62 (95% CI 4.00-7.28) per annum and for cow/calf pairs of 0.0603 (95% CI 0.0382-0.0824) or 6.22 (3.89-8.59) per annum respectively. Current population size, for this, the ‘western’ Australian subpopulation, is estimated at 2474. A Progress Report on the 2017 survey was provided as required under the funding Agreement, on 31 December 2017. Further funding, for three years from 2018, is now being provided by the Australian Government through the NESP Marine Biodiversity Hub, Project A7.
Keywords: numbers; right whale population trends

Monitoring population dynamics of Western right whales - Progress Report on activities for 2017 - John Bannister (2018)
To continue an annual series of aerial surveys off the southern Australian coast between Cape Leeuwin WA and Ceduna SA since 1993, a survey was undertaken over five days, 23-27 August, 2017. A total of 1546 animals was sighted, including 506 calves and 4 ‘yearlings’; these include double counts, given that each flying leg is covered twice, ‘outward’ and ‘inward’. For comparison with previous years’ results, maximum counts for each leg are taken; for the 2017 survey, the comparable counts are 780 individuals of which 294 were cows accompanied by calves of the year. From 5603 photographic images obtained, 487 have been selected for computer-assisted ‘matching’ with those (some 8000 images of over 2000 individuals) already available in the catalogue. Full details, including trend analysis since 1993, current population size, and distribution information, will be included in the Final Report due on 30 March 2018.
Keywords: numbers; right whale population trends

Morphological diagnoses of higher taxa in Ophiuroidea (Echinodermata) in support of a new classification - Tim O'Hara; Stohr, Sabine; Andrew F. Hugall; Thuy, Ben; Alexander Martynov (European Journal of Taxonomy, 2018)
A new classification of Ophiuroidea, considering family rank and above, is presented. The new family and superfamily taxa in O’Hara et al. (2017) were proposed to ensure a better readability of the new phylogeny but are unavailable under the provisions of the ICZN. Here, the morphological diagnoses to all 33 families and five superfamilies are provided. Ten new families, Ophiosphalmidae fam. nov., Ophiomusaidae fam. nov., Ophiocamacidae fam. nov., Ophiopteridae fam. nov., Clarkcomidae fam. nov., Ophiopezidae fam. nov., Ophiernidae fam. nov., Amphilimnidae fam. nov., Ophiothamnidae fam. nov. and Ophiopholidae fam. nov., are described. The family Ophiobyrsidae Matsumoto, 1915, not yet discovered in the previous publication, is added, based on new molecular data. A new phylogenetic reconstruction is presented. Definitions of difficult-to-apply morphological characters are given.
Keywords: morphology; nomenclature; Phylogeny; taxonomy; brittle-stars

Moving beyond trophic groups: evaluating fishing-induced changes to temperate reef food webs - Soler, GA; Graham J. Edgar; Rick D Stuart-Smith; Smith, ADM; Russell J. Thomson (Marine Ecology Progress Series, 2018)
Fish capture has far-reaching but inadequately assessed implications for marine food webs. At the community level, such effects are typically investigated using dynamic models that rely on partially subjective categorization of species into trophic groups and that mostly overlook the substantial contribution of ontogenetic dietary variation within fish species. Here, we estimate consumption by fish communities at 376 southern Australian sites by applying a recently developed statistical model that predicts diet for individual fish based on their body size and taxonomic identity, with predicted diets then summed to estimate total community consumption. Impacts of fishing and human population density as top-down pressures on shallow reef communities were thereby resolved at fine taxonomic scales. Fishes were estimated to consume 71% more prey biomass in southern Australian no-take marine protected areas (MPAs) relative to fished sites. Consumption of algae and sessile invertebrates was unexpectedly high in MPAs, an outcome not apparent with fish species allocated into pre-defined trophic groups. Extension of this individual size-structured modelling approach provides an opportunity to fill important knowledge gaps in understanding human impacts on marine food webs.
Keywords: Australia; Fish diets; Herbivores; Marine protected areas; marine reserves; trophic cascades

A national assessment of the status of white sharks - B Bruce; R. W. Bradford; Mark Bravington; Pierre Feutry; P Grewe; R. Gunasekera; David Harasti; R. M. Hillary; T. A. Patterson (National Environmental Science Program Marine Biodiversity Hub, 2018)
This report provides an overview of the key findings on Australasian white shark (Carcharodon carcharias) abundance and population dynamics which have superseded the initial estimates in Hillary et al. (2018). Both the submitted paper and the updated work detailed herein constitute the first robust estimates of Australasian white shark abundance and demographic rates (survival and trend) ever undertaken, and employ a variety of cutting-edge methods and novel data from across the Australian/New Zealand range of the species. Importantly, these estimates do not rely on the highly uncertain historical catch data for this species. To our knowledge, no similar study has been conducted worldwide. The results and methods employed, represent a step-change in capacity to assess otherwise difficult to monitor species, such as white sharks.

National Outfall Database - Community Report for August 2018 - John Gemmill (2018)
This Community Report for August 2018 provides an update on the National Outfall Database (developed by the Clean Ocean Foundation), which tracks the volume and composition of wastewater discharged to Australia’s ocean and estuaries. Data gathered in 2016 from 109 ocean and 67 estuarine outfalls provide the second annual national snapshot of these discharges to Australia’s coastal environment. Related information Report at Item field below or download directly https://www.cleanocean.org/2018-nod-summary.html News item - First national snapshot of wastewater discharged to Australia's oceans - 29 August 2018 Clean Ocean Foundation https://www.cleanocean.org/ Clean Ocean Foundation - information about National Outfall Database including information sheets and media releases https://www.cleanocean.org/national-outfall-database.html National Outfall Database - reports and supporting data analysis https://www.outfalls.info/about/publications
Keywords: aquatic pollution; citizen science; environment; ranking; sewerage

NESP Marine Biodiversity Hub Research Plan - 2018 RPv4 - Project Proposals - Nicholas J. Bax; Paul Hedge (2018)
This Research Plan for 2018 (RPv4) has been developed by the Marine Biodiversity Hub, in consultation with the Department of the Environment and Energy and other key stakeholders. The purpose of the Research Plan is to outline: the research priorities the Hub is funded to investigate the research projects that will address these priorities how the output of the research will be communicated and brokered to key stakeholders how the impact of the research will be measured how Hubs will work collaboratively within and across Hubs This Research Plan also lists key staff and research organisations, and the risks needing to be monitored to ensure success. Please note: Project durations vary and may extend over a number of years.  If the project you are interested in is not listed in the Item field of this research plan, it will be included in an earlier year as an ongoing, unchanged project. Where a project proposal involves significant changes, it will be updated and included in subsequent research plans.
Keywords: annual research plan; RPv4

Options for assessing cumulative impact and risk to environmental values in Matters of National Environmental Significance and Australian Marine Parks - Piers K Dunstan; Jeffrey M Dambacher (2018)
Understanding the existing impacts and the risks of new impacts on Matters of National Environmental Significance (MNES) and Australian Marine Parks (AMPs) remains a significant challenge for all stakeholders who have an interest in the Marine Environment. Coasts and oceans provide a range of vital services such as food, transport, recreation, waste disposal and cultural inspiration. These services are under a range of pressures, including harvesting, habitat loss, pollution, and climate change, while the demands of a growing human population continue to rise. Managing pressures in this complicated ecological, social and economic environment is challenging and it will not always be possible to achieve agreed objectives. Many coastal environments are expected to degrade given the increasing strength of external factors, including climate change, that cannot be managed locally, which will diminish these ecosystems and the services that they provide. Successful management that can slow or even reverse these trends requires understanding the long-term capacity of ocean ecosystems to respond to increasing or new pressures, identifying appropriate tools that communities, industry and government are able and willing to use to determine sustainable resource use, and providing access to this information. One of the key sets of tools available to ensure that long term outcomes are sustainable are through Environmental Impact Assessments and incorporating tools to assess cumulative impacts into EIA remains a challenge.
Keywords: cumulative impact; risk

Origin of high density seabed pockmark fields and their use in inferring bottom currents - K Picard; Radke, Lynda; Williams, David; Nicholas, William; Siwabessy, P.; Howard, Floyd; Gafeira, Joana; Rachel Przeslawski; Z Huang; Scott L Nichol (Geosciences, 2018)
Some of the highest density pockmark fields in the world have been observed on the northwest Australian continental shelf (>700/km2) where they occur in muddy, organic-rich sediment around carbonate banks and paleochannels. Here we developed a semi-automated method to map and quantify the form and density of these pockmark fields (~220,000 pockmarks) and characterise their geochemical, sedimentological and biological properties to provide insight into their formative processes. These data indicate that pockmarks formed due to the release of gas derived from the breakdown of near-surface organic material, with gas accumulation aided by the sealing properties of the sediments. Sources of organic matter include adjacent carbonate banks and buried paleochannels. Polychaetes biodiversity appears to be affected negatively by the conditions surrounding dense pockmark fields since higher biodiversity is associated with low density fields. While regional bi-directionality of pockmark scours corresponds to modelled tidal flow, localised scattering around banks suggests turbulence. This multi-scale information therefore suggests that pockmark scours can act as proxy for bottom currents, which could help to inform modelling of benthic biodiversity patterns.
Keywords: Bonaparte Basin; carbonate banks; Multibeam sonar; Northwestern Australia; Oceanic Shoals Australian Marine Park; polychaete; semi-automated mapping; Timor Sea

The phylogenomic position of the Critically Endangered Largetooth Sawfish Pristis pristis (Rhinopristiformes, Pristidae), inferred from the complete mitochondrial genome - PM Kyne; Wang, Jun-Jie; Xiang, Dan; Chen, Xiao; Pierre Feutry (Mitochondrial DNA Part B, 2018)
The complete mitogenome of the Critically Endangered Largetooth Sawfish Pristis pristis (Rhinopristiformes, Pristidae) is presented in this study. The genome is 16,912 bp in length with a nucleotide base composition of 32.0% A, 26.5% C, 13.2% G, and 28.3% T, containing 37 genes typical of vertebrates. Two start (GTG and ATG) and two stop (TAG and TAA/T) codons are found in the protein-coding genes. The 22 tRNA genes range from 66 bp (tRNA-Ser2) to 75 bp (tRNA-Leu1). The tRNA-Pro gene is duplicated with an unknown sequence between the two copies. Bayesian phylogenetic reconstruction showed that P. pristis clusters with the Pristis clade with strong posterior probability (100%).
Keywords: Mitochondrial genome; Pristidae; Pristis pristis; threatened species

Phylogenomics, life history and morphological evolution of ophiocomid brittlestars - Tim O'Hara; Andrew F. Hugall; Cisternas, Paula A.; Boissin, Emilie; Guadalupe Bribiesca-Contreras; Sellanes, Javier; Paulay, Gustav; Byrne, Maria (Molecular Phylogenetics and Evolution, 2018)
Brittlestars in the family Ophiocomidae are large and colourful inhabitants of tropical shallow water habitats across the globe. Here we use targeted capture and next-generation sequencing to generate robust phylogenomic trees for 39 of the 43 species in order to test the monophyly of existing genera. The large genus Ophiocoma, as currently constituted, is paraphyletic on our trees and required revision. Four genera are recognised herein: an expanded Ophiomastix (now including Ophiocoma wendtii, O. occidentalis, O. endeani, O. macroplaca, and Ophiarthrum spp), Ophiocomella (now including the non-fissiparous Ophiocoma pumila, aethiops and valenciae) and Breviturma (now including Ophiocoma pica, O. pusilla, O. paucigranulata and O. longispina) and a restricted Ophiocoma. The resulting junior homonym Ophiomastix elegans is renamed O. brocki. The genus Ophiomastix exhibits relatively high rates of morphological disparity compared to other lineages. Ophiomastix flaccida and O. (formerly Ophiarthrum) pictum have divergent mitochondrial genomes, characterised by gene-order rearrangements, strand recoding, enriched GT base composition, and a corresponding divergence of nuclear mitochondrial protein genes. The new phylogeny indicates that larval and developmental transitions occurred rarely. Larval culture trials show that species with abbreviated lecithotrophic larval development occur only within Ophiomastix, although the possible monophyly of these species is obscured by the rapid early radiation within this genus. Asexual reproduction by fission is limited to one species-complex within Ophiocomella, also characterised by elevated levels of allelic heterozygosity, and which has achieved a relatively rapid global distribution. The crown ages of the new genera considerably predate the closure of the Tethyan seaway and all four are distributed in both the Atlantic and Indo-Pacific Oceans. Two species pairs appear to reflect the closure of the Panama Seaway, although their fossil-calibrated node ages (12–14 ± 6 my), derived from both concatenated sequence and multispecies coalescent analyses, considerably predate the terminal closure event. Ophiocoma erinaceus has crossed the East Pacific barrier and is recorded from Clipperton Island, SW of Mexico.
Keywords: Asexual reproduction; Exon-capture; Larval development; Ophiocomidae; Ophiuroidea

Polychaetes (Annelida) of the Oceanic Shoals region, northern Australia: considering small macrofauna in marine management - Rachel Przeslawski; Glasby, Christopher J.; Scott L Nichol (Marine and Freshwater Research, 2018)
Northern Australia has been the focus of recent marine biodiversity research to support natural resource management for both industry and conservation, including management of the Oceanic Shoals Australian Marine Park (AMP). Much of this research has targeted habitat-forming sessile invertebrates and charismatic megafauna, but smaller macrofauna and infauna may also be important because of their roles in ecosystem functions. In this study we characterised the biodiversity of polychaetes collected from four marine surveys to the Oceanic Shoals AMP between 2009 and 2012 from which sediment samples were elutriated (500 μm) to separate macrofauna. We used this species-level inventory to examine several questions related to marine management, namely: (1) do polychaete assemblages vary among surveys; (2) can environmental variables or geomorphology explain differences in community structure; and (3) how do ecological patterns change according to taxonomic resolution (species, family) and functional group (feeding, habitat, mobility)? A total of 2561 individual polychaetes were collected from 266 samples, representing 368 species and 43 families, including new species and genera, as well as new family records for Australia (Iospilidae, Lacydoniidae). Polychaete species assemblages and functional groups showed variation among the surveys, but this was not observed at the family level. Species and family assemblages were weakly related to environmental factors, but functional groups showed stronger relationships. Plains and banks each supported distinct polychaete assemblages, although the latter showed temporal variation. The results provide baseline biodiversity and ecological data about polychaetes on the northern Australian shelf, and these are discussed in relation to marine management strategies. Notably, intersurvey and environmental patterns differ from those of larger sessile fauna (sponges) collected on the same surveys, highlighting the need to consider small macrofauna in monitoring programs of marine protected areas.
Keywords: bathymetry; Geomorphology; Key ecological feature; marine baselines; Seabed mapping; soft sediment ecology

Polychaetes from Australia’s Eastern Abyss - Gunton, Laetitia; Kupriyanova, Elena; Hutchings, Pat; Wilson, Robin; Murray, Anna; Paxton, Hannelore; Burghardt, Ingo; Zhang, Jinghuai; Tim O'Hara (2018)
More than 90 species of polychaete worms collected during the 2017 ‘Sampling the Abyss’ voyage are thought to be new to science. CSIRO’s RV Investigator took the first ever biological samples from the large abyssal environments in Australian Marine Parks – from Tasmania to Queensland – on the voyage led by Museums Victoria and supported by the Marine Biodiversity Hub. Scientists from four agencies have identified 114 species from 33 families among the 2357 specimens. Polychaetes dominate many seafloor communities, and scientists have formally named 12 000 species. Patterns in the distribution of all the polychaetes sampled will be studied to understand how deep-sea populations are connected along Australia’s eastern abyss, and how the Australian abyss compares with abyssal environments worldwide. The new polychaete species from Australia’s abyss will also be formally described. These results were summarised in a presentation led by Laetitia Gunton of the Australian Museum at the 15th Deep Sea Biology Symposium held at Monterey, California, USA, in September 2018.
Keywords: Australian Eastern Abyss; polychaete worms

Procedures and methods for establishment of captive breeding populations of spotted handfish - T P Lynch; Lincoln Wong; Tim Fountain; C Devine (2018)
Brood stocks were established at two institutes, with 10 animals each to Seahorse World and SEA LIFE Melbourne Aquarium. Both institutes are known to have at least one fertile pair due to breeding occurring in captivity following collection. The captive population is now 116 fish (30/12/2017) of which 20 are adults or sub-adults and 96 are captive bred juveniles. No fish have died during this process which was unexpected as previously high mortality occurred for juveniles. Our use of marine-tank chiller units, which have become cheaply available since the previous captive breeding work in the mid-1990s, may be responsible for this low mortality. Knowledge transfer to industry partners (Seahorse World and SEA LIFE Melbourne Aquarium) by CSIRO officers for captive breeding of handfish was made through personal visits, phone calls and the provision of all reports and laboratory notes. A standard operating procedure was developed for data processing and transfer of animals via freight. A stud book was also established - Spotted handfish ambassador fish program: captive fish studbook. See References. Compared to previous years, similar results were obtained for fish densities at the nine long-term monitoring sites, however this year the observed decline at Ralphs Bay continued to its conclusion with no fish observed during 2017.
Keywords: captive breeding; Spotted handfish

A rare contemporary record of the Critically Endangered Ganges Shark, Glyphis gangeticus - Rima W. Jabado; PM Kyne; Nazareth, E.; Sutaria, D. N. (Journal of Fish Biology, 2018)
The first record of the Ganges shark Glyphis gangeticus from anywhere in its range in over a decade is reported from the Arabian Sea. One female specimen was recorded at Sassoon Docks in Mumbai, India in February 2016, measuring 266 cm total length. In light of the Critically Endangered status of this species and its rarity, urgent management actions are needed to determine population size and trends in abundance in combination with fisher education and awareness campaigns.

Rethinking approaches to valuation in marine systems - Russell Gorddard; Michael Dunlop; Wise, Russell; Piers K Dunstan (2018)
Understanding the range of values that are held and ascribed to the marine environment is key to supporting sustainable management across environmental, social and economic dimensions. The work builds on a wide range of literature on values in environmental management and on the authors’ experiences in addressing the roles that values (of individuals, communities and industry) play in climate adaptation problems in a range of terrestrial, coastal and, to a more limited extent, marine environments. This report focuses on presenting a conceptual and analytical framework designed to help stakeholders understand, interrogate and deliberate over: 1) the concept of values; 2) the dependence or conditionality of values on the magnitudes of environmental change and the decision-making context of stakeholders; 3) the roles that values do, can or should play in environmental research, management and governance; and 4) what this means for future marine systems research and governance. We propose that the next steps flowing from this work might involve testing and revising this conceptual framework with a range of stakeholders in the marine research and policy space to identify key issues and potential case studies for further work.
Keywords: impact; pressure; risk

Reviewing the EBSA process: Improving on success - Johnson, David E.; Frojan, Christopher Barrio; Turner, Phillip J.; Weaver, Philip; Gunn, Vikki; Daniel C. Dunn; Halpin, Patrick; Nicholas J. Bax; Piers K Dunstan (Marine Policy, 2018)
This paper reviews key aspects of the implementation of the Convention on Biological Diversity's Ecologically or Biologically Significant Area (EBSA) process to date, anticipating global marine coverage of that process in so far as is possible by the end of 2018. EBSAs merge marine and coastal physical, biological and biogeographical information held by States, diverse scientific institutions and individual experts to identify inherent value of marine biodiversity, as well as providing a focus for either States or international organisations with sectoral competences to apply potential management measures to protect and sustainably manage biodiversity. In assessing information made available at dedicated EBSA Regional Workshops, several common patterns emerged, both in the data made available and in the gaps in information. The latter include missing information, representation of taxa and features of interest, and specialist expertise. The review exercise detailed here has highlighted the value and efficacy of the EBSA process and the information it has generated, despite some recognised shortcomings. It further suggests that there is potential to strengthen the EBSA portfolio by (i) adding some selected new areas yet to be described, (ii) revisiting existing EBSAs to add both new and existing information, and (iii) reconsidering some areas previously deemed to not meet the EBSA criteria by incorporating both new and existing information. Improving the systematic assessment of areas against the EBSA criteria could be achieved using a combination of (i) spatially precise systematic conservation approaches, supported by (ii) predictive modelling and biogeographic multi-criteria approaches based on expert judgement.
Keywords: CBD; EBSA; Ecologically or Biologically Significant Area; marine environment; onvention on Biological Diversity

The role of restoration in conserving matters of national environmental significance in marine and coastal environments - Ian M. McLeod; Lisa Bostrom-Einarsson; Craig R. Johnson; Gary A. Kendrick; Cayne Layton; Abbie A Rogers; John Statton (2018)
Healthy coastal habitats like seagrass meadows, coastal saltmarsh, kelp forests, coral and shellfish reefs, and mangrove forests (‘blue infrastructure’) are essential to the economic and social well-being of coastal communities. These habitats drive coastal productivity supporting our fisheries and other industries associated with recreation in marine environments, improve water quality, sequester carbon, protect shorelines from erosion, and support thriving biodiversity, including threatened species. These habitats are under pressure from coastal development, climate change, pollution, invasive species and other anthropogenic pressures, which have led to drastic declines in many of our important marine and coastal habitats. Under the division of powers between the Australian Government and the states under the Australian Constitution, states and territories have the primary responsibility for environmental protection of coastal habitats within three nautical miles of the coastline. The Environment Protection and Biodiversity Conservation Act 1999 (C’th) (the EPBC Act) enables the Australian Federal Government to join with the states and territories in providing a national scheme of environment and heritage protection and biodiversity conservation. The EPBC Act focuses Australian Government interests on the protection of nine Matters of National Environmental Significance (MNES). These include World Heritage Areas and Ramsar wetlands, threatened and endangered species and habitats, and migratory species protected through international agreements, and Commonwealth Marine Areas. Given the current state of decline in natural ecosystems, there is a general consensus that there are two paths to conserve critical habitats; habitats can either be protected from extractive or destructive human influences (e.g. through national parks, marine reserves, fishery closures, gear restrictions or riparian conservation), and/or actively rehabilitated towards a preferred healthy state (i.e. restoration). Early environmental conservation was primarily focused on the former of these methods, with the establishment of national parks and conservation areas globally, and sector-based management of remaining pressures. However, despite these intensive interventions, many habitats have continued to decline over the past half century. There is increasing recognition that protection by itself is no longer sufficient and interest and demand for rehabilitation in the form of interventions and restoration has been growing. Restoration is now seen as a key element in achieving conservation and environmental management goals internationally. In recent decades, nations such as the United States, Canada and the United Kingdom have embraced the need for large-scale marine and coastal restoration. Further, restoration also produces economic benefits. For example, restoration activities were recently estimated to contribute almost US$25 billion and 221,000 jobs annually to the United States economy. In this report we review the state of four ecologically critical coastal marine habitats in Australia; seagrass meadows, kelp forests, shellfish reefs, and coastal saltmarsh wetlands, and evaluate (1) the Commonwealth responsibility for the habitat under the EPBC Act, (2) capacity of habitat restoration to insulate against loss and degradation of MNES, through restoration of key habitats and the species they support, (3) recent advances in restoration with the potential to improve outcomes associated with MNES. This report demonstrates that each of the four habitats fall under up to six of the nine MNES, by being directly listed as or supporting threatened species or ecosystems, providing habitat for listed migratory species, and being important components of World Heritage Areas, Commonwealth waters, the Great Barrier Reef Marine Park, and Ramsar wetlands. For example, giant kelp (Macrocystis pyrifera) forests are listed as an endangered ecological community; temperate and subtropical saltmarshes are listed as a vulnerable ecological community and three saltmarsh species are listed as vulnerable. In addition, the habitats formed by the two primary reef-forming oyster species are under consideration for listing as endangered ecological communities under the EPBC Act. Coastal saltmarshes provide critical habitat for listed threatened species, such as the green and golden bell frog (Litoria aurea) and the orange-bellied parrot (Neophema chrysogaster), and migratory species such as the eastern curlew (Numenius madagascariensis), the Pacific golden plover (Pluvialis fulva), the sharp-tailed sandpiper (Calidris acuminata), and the red-necked stint (Calidris ruficollis). Seagrass habitats make up a large proportion of the Great Barrier Reef Marine Park and World Heritage Area and support listed turtle species and dugong. Similarly, kelp forests support a disproportionately high number of endemic species, including several listed under the EPBC At, including the spotted handfish (Brachionichthys hirsutus, critically endangered), red handfish (Thymichthys politus, critically endangered), Ziebell’s handfish (Brachiopsilus ziebelli, vulnerable), black rockcod (Epinephelus daemelii, vulnerable) and members of the Syngnathidae family (seadragons, seahorses and pipefish).
Keywords: ecosystem services; EPBC; kelp; natural resource management; restoration; Saltmarsh; seagrass; shellfish reef

Scoping a seascape approach to managing and recovering northern Australian threatened and migratory marine species - PM Kyne; Michele Thums (2018)
Northern Australia is currently the focus of substantial economic development, which also has the potential to impact biodiversity and cultural values. The Northern Seascape scoping project (NESP Marine Biodiversity Hub Project A12 Phase 1) assessed the state of knowledge of Commonwealth Environment Protection and Biodiversity Conservation Act 1999 (EPBC)-listed Threatened and Migratory marine species, and pressures, Indigenous priorities, coastal habitats, and fisheries bycatch in relation to them across the North Marine Bioregion. The focus was at a multiple taxa level, including elasmobranchs (sharks and rays), shorebirds, marine turtles, Dugong, and cetaceans. The project scoped the research needs and directions for a broad Northern Seascapes project for the years 2018–2020. Click on Item link below to download the full report. You can also view the species maps from Chapter 2 by clicking on the figure links below. Figure 2 Northern River Shark and Speartooth Shark Figure 3 Green Sawfish and Dwarf Sawfish Figure 4 Largetooth Sawfish Figure 5 Hawksbill Turtle and Olive Ridley Turtle Figure 6 Curlew Sandpiper and Eastern Curlew Figure 7 Great Knot and Red Knot Figure 8 Greater Sand-Plover and Lesser Sand-Polover Figure 9 Dugong Figure 10 Australian Humpback Dolphin and Australian Snubfin Dolphin
Keywords: Indigenous sea-country; marine turtles; migratory species; rapid assessment; sawfishes; shorebirds; threatened species

A seasonally dynamic estuarine ecosystem provides a diverse prey base for elasmobranchs - Every, Sharon L.; Fulton, Christopher J.; Pethybridge, Heidi R.; PM Kyne; Crook, David A. (Estuaries and Coasts, 2018)
Tropical river and estuarine food webs sustain diverse biodiversity values and are important sources of nutrients and energy for connected aquatic and terrestrial ecosystems. High-order predators, such as euryhaline elasmobranchs, play critical roles in these food webs, but a lack of detailed information on food web structure limits our ability to manage these species within their ecosystems. We analysed stable carbon (δ13C) and nitrogen (δ15N) isotopes (SI) and fatty acid (FA) biochemical tracers from putative prey species in the estuary of the South Alligator River, northern Australia. These were compared with existing data on four species of elasmobranch from the system to examine food web structure and infer dietary linkages over wet and dry seasons along an environmental gradient of sites. Layman’s SI community metrics indicated that upstream food webs had the greatest trophic diversity, and analyses of FAs revealed distinct prey habitat associations that changed seasonally. Mixing models of SI indicated that most Glyphis glyphis and Glyphis garricki had similar freshwater and mid-river diets whilst Carcharhinus leucas and Rhizoprionodon taylori had largely marine signatures. Multivariate analyses of FA revealed some intraspecific differences, although specialisation indices suggested that the four shark species are trophic generalists. Our results show that riverine food webs can display complex spatiotemporal variations in trophic structure and that coastal and euryhaline mobile elasmobranchs forage in a range of coastal and freshwater habitats, demonstrating their influence on these food webs.
Keywords: Elasmobranchs; estuary; Fatty acids; Food webs; Stable isotopes

Seven pearls of wisdom: advice from Traditional Owners to improve engagement of local Indigenous people in shellfish ecosystem restoration - Ian M. McLeod; Schmider, Joann; Colin Creighton; Chris L Gillies (Ecological Management & Restoration, 2018)
Oysters, mussels and other shellﬁsh are culturally and economically important resources for coastal communities globally. In Australia, Aboriginal and Torres Strait Islander peoples have engaged in the harvest, consumption, ecological management and trade of shellﬁsh and shellﬁsh products for millennia. Shellﬁsh ecosystems have been severely reduced in Australia since European settlement through overharvest using destructive ﬁshing practices, pollution and disease. There is growing interest in the restoration of shellﬁsh ecosystems in Australia to bring back a vastly reduced natural ecosystem, and the ecosystem services they provide such as providing habitat for other species, water ﬁltration and shoreline protection.
Keywords: marine restoration; mussel; oyster; Sea Country; shellfish

Sizing up Australia’s eastern Grey Nurse Shark population - R. W. Bradford (2018)
A new estimate of adult population size for Australia’s eastern Grey Nurse Shark drew on widespread genetic sampling and forensic exploration of family trees. Grey nurse sharks are found across tropical and temperate regions of the North and South Atlantic, Indian and western Pacific oceans, to depths of at least 230 metres. Internationally, they are listed as Vulnerable on the International Union for Conservation of Nature Red List of Threatened Species. Australia has distinct eastern and western populations, each inhabiting an approximate 2700 kilometre stretch of coastal waters. The eastern population ranges from central Queensland to at least the New South Wales/Victoria border and the western population ranges from Western Australia’s North West Shelf to at least Cocklebiddy in the Great Australian Bight. The eastern population is listed as Critically Endangered under the Australian Environment Protection and Biodiversity Conservation Act 1999. Objective 1 of the 2014 national recovery plan for the Grey Nurse Shark is to: Develop and apply quantitative monitoring of the population status (distribution and abundance) and potential recovery of the Grey Nurse Shark in Australian waters. Previous population estimates for Grey Nurse Shark in 2009 and 2010 relied on photo identification, but this technique can have challenges relating to covering the full geographic range of the population, and the accuracy of matching the sharks’ spot markings. This CSIRO-led project, funded by the National Environmental Science Program Marine Biodiversity Hub, built on data collections and analytical techniques developed in a suite of related projects completed under this partnership.

The South-east Commonwealth Marine Reserves Network — public knowledge, perceptions and values survey - Michael P. Burton; Jennings, Sarah; Fragnol, Ludovic; Marre, Jean-Baptiste; Samantha Parades; Pascoe, Sean; Abbie A Rogers; Yamazaki, Satoshi (2018)
Commonwealth marine reserve networks play a central role in supporting important conservation objectives and also contribute to economic and social values. Efficient design and effective management of reserve networks requires consideration of the costs and benefits of alternatives, and should include measurement of the preferences of the general public who, even if they do not make direct use of the marine estate, may still hold existence values for assets protected by these networks. An online survey of 1122 residents of the South-east marine region (South Australia, Victoria and Tasmania) was undertaken to identify the public’s knowledge and perceptions of the South-east Commonwealth Marine Reserves Network, and to investigate the values that they hold for various features protected by the Network. We also determine the effect of providing information about these key features in different ways on the measured public preferences, and of explicitly explaining the importance of affording protection to a representative range of features through a network of reserves. Respondents were drawn from an online research panel and the survey was conducted in June 2015.
Keywords: community attitudes; marine reserves; non-market valuation

Spatial properties of sessile benthic organisms and the design of repeat visual survey transects - Nicholas R. Perkins; G.R. Hosack; Scott D Foster; Hill, Nicole A.; Neville Barrett (Aquatic Conservation: Marine and Freshwater Ecosystems, 2018)
Monitoring the impacts of pressures, such as climate change, on marine benthic ecosystems is of high conservation priority. Novel imaging technologies, such as autonomous underwater vehicles (AUVs), remotely operated vehicles (ROVs), and towed systems, now give researchers the ability to monitor benthic ecosystems over large spatial and temporal scales. The design of monitoring programmes that use such technologies is currently hindered by a lack of information about the typical abundance and spatial distributions of target indicators and the level of sampling required to detect changes. A further complicating factor is that these sampling platforms are often not able to be exactly relocated when conducting repeat surveys. How the spatial properties of benthic organisms influence the estimates of cover, given alternative designs that vary in the geolocation precision of transects and the sampling intensity of images, is explored. A geostatistical modelling approach is used to quantify the spatial distribution of 20 key deep‐water invertebrate species at a long‐term monitoring site. The parameter estimates from these models are then used to simulate repeat transects with geolocation error and different levels of sampling. Results suggest that species with short effective ranges (i.e. those with strong spatial dependence over relatively short distances) and large spatial variance, which suggests strong spatial dependence effects, will require greater sampling effort to achieve a given standard of precision. Spatial offsets of 2 m, typical of an AUV, are unlikely to have dramatic impacts on the precision of estimates when sufficient images are sampled, but offsets of 10 m that are typical of towed systems may require a prohibitively high sampling effort for some species. These findings have important implications for benthic monitoring programmes, and highlight the importance of considering the interactions between sampling design, the technical limitations of survey equipment, and the spatial properties of indicator species.
Keywords: Autonomous underwater vehicle; Freycinet Commonwealth Marine Reserve; marine imagery sampling annotation shelf reef AUV IMOS

Symposium report: Inaugural Australian Coastal Restoration Symposium - Ian M. McLeod; Jemma Purandare; Chris L Gillies; Adam Smith; Burrows, Damien (Ecological Management & Restoration, 2018)
Globally, coastal habitat restoration is growing in recognition as a viable management tool to repair and reinstate valuable coastal habitats and species, such as mangrove and macroalgae forests, salt marshes, seagrass meadows, shellfish and coral reefs (Aronson & Alexander (2013), Restoration Ecology, 293; Anthony et al. (2017) Nature Ecology and Evolution, 1420; TNC (2017) Caribbean: A revolution to save coral reefs in the Caribbean and beyond). In Australia, there is increasing interest and investment in coastal restoration and habitat conservation, particularly with respect to growing national concerns around habitat loss, coastal inundation and erosion, loss of fisheries and climate change (Maggini et al. (2013) Protecting and restoring habitat to help Australia's threatened species adapt to climate change; GBRMPA (2017) Reef summit sets new course of action for the Great Barrier Reef). This has led to new community of practices being formed for shellfish reef restoration (Shellfish Reef Restoration Network shellfishrestoration.org.au), seagrass restoration (Seagrass Restoration Network seagrassrestoration.net), and saltmarsh and mangrove (Saltmarsh and Mangrove Network, amsn.net.au) conservation. However, despite this interest, there has been no national coordination, network or society with coastal restoration as a primary focus. The inaugural Australian Coastal Restoration Symposium brought together 60 Australian restoration practitioners, researchers and managers at James Cook University, Townsville for three days from the 31st of August 2017. The symposium goals were to enhance collaboration and national coordination amongst coastal restoration projects and practitioners, as well as to connect researchers and practitioners working in the restoration space with one another. Three international keynote speakers shared their experiences and advice. Delegates were enthusiastic about continuing to meet at future symposiu, meetings and workshops, and noted the value of being able to connect, share project experiences and learnings, and collaborate. The Australian Coastal Restoration Network has been formed with the goal of meeting annually to continue to share knowledge and improve collaboration. View a video about the symposium by following this link – https://www.youtube.com/watch?v=lukSpo3mM-4
Keywords: coastal; coral; mangrove; restoration; seagrass

Transferring biodiversity models for conservation: Opportunities and challenges - Sequeira, A M M; Phil J. Bouchet; Yates, K L; Mengersen, K; M Julian Caley (Methods in Ecology and Evolution, 2018)
After decades of extensive surveying, knowledge of the global distribution of species still remains inadequate for many purposes. In the short to medium term, such knowledge is unlikely to improve greatly given the often prohibitive costs of surveying and the typically limited resources available. By forecasting biodiversity patterns in time and space, predictive models can help fill critical knowledge gaps and prioritize research to support better conservation and management. The ability of a model to predict biodiversity metrics in novel environments is termed ‘transferability’, and models with high transferability will be the most useful in this context. Despite their potential broad utility, little guidance exists on what confers high transferability to biodiversity models. We synthesise recent advances in biodiversity model transfers to facilitate increased understanding of what underpins successful model transferability, demonstrating that a consistent approach has so far been lacking but is essential for achieving high levels of repeatability, transparency, and accountability of model transfers. We provide a set of guidelines to support efficient learning and the improvement of model transferability.
Keywords: Biodiversity; Conservation; extrapolation; forecasting; modelling

Trialling suitable indicator metrics of change for baited remote underwater video station datasets - progress report - Jacquomo Monk; Tim J. Langlois; Neville Barrett (2018)
This report provides a progress update on the development of suitable metrics and datasets for State of the Environment (SoE) reporting and Ecosystem-Based Fisheries Management (EBFM) assessment based on Baited Remote Underwater Video stations (BRUVs). Initial work has focussed on facilitating the collation and cleaning/standardisation of an extensive range of BRUVs datasets held by research agencies around Australia. This stage has been undertaken as a collaboration with an AODN funded project to collate BRUV data and add it to the national database “Global Archive” that AODN are developing to enhance storage and analysis capabilities. While all available BRUV data has now been uploaded to Global Archive (www.globalarchive.org), nuances in the collection and annotation of data has provided considerable challenges for the standardisation necessary for analysis at the national level. Nevertheless, this process has been essential for identifying future minimum standards (standard operating protocols) we recommend in monitoring programs to ensure data generated is suitable for analysis at national, as well as local scales. The data collation has now been completed with a final “clean” dataset of 18,568 deployments now ready for trialling of potential SoE metrics. In addition to data collection and cleaning, scoping of potential metrics has also been completed, with 44 metrics identified, covering fisheries, ocean warming, community-level and life history based metrics (discussed with the BRUV research communities in workshops in WA in July 2017 and February 2018). Identification of potential covariates for spatial analysis of these metrics has also been completed (and discussed at the workshops above), with the subsequent collation and generation of spatially located (i.e. at drop level) data for 189 covariates, which are now stored in a single geodatabase. Covariates were selected based on their ability to represent human pressures (e.g. distance to township or boat ramp), habitat (e.g. distance to reef), climate (e.g. changes in sea surface temperature) and protection (e.g. distance to marine protected area). Initial trialling of effective reporting metrics is currently underway, with some elucidating key protection effects on fish communities (e.g. biomass of targeted species >20 cm). In addition, as a part of the NCRIS funding for the Global Archive Marine RDC project, work is currently underway to turn the SoE metrics into a reporting app that will link directly with Global Archive and enable end-users to interactively explore SoE/EBFM metrics. A meeting/workshop on this SoE reporting app is being scheduled for August 2018 in Hobart.
Keywords: baited remote underwater video; fish; marine protected area; State of the Environment reporting; time series

Troubled waters: Threats and extinction risk of the sharks, rays and chimaeras of the Arabian Sea and adjacent waters - Rima W. Jabado; PM Kyne; Pollom, Riley A.; David A. Ebert; Colin Simpfendorfer; Ralph, Gina M.; Al Dhaheri, Shaikha S.; Akhilesh, K. V.; Ali, Khadeeja; Ali, Mohamud Hassan; Al Mamari, Tariq M. S.; Bineesh, K. K.; et al. (Fish and Fisheries, 2018)
The extinction risk of sharks, rays and chimaeras is higher than that for most other vertebrates due to low intrinsic population growth rates of many species and the fishing intensity they face. The Arabian Sea and adjacent waters border some of the most important chondrichthyan fishing and trading nations globally, yet there has been no previous attempt to assess the conservation status of species occurring here. Using IUCN Red List of Threatened Species Categories and Criteria and their guidelines for application at the regional level, we present the first assessment of extinction risk for 153 species of sharks, rays and chimaeras. Results indicate that this region, home to 15% of described chondrichthyans including 30 endemic species, has some of the most threatened chondrichthyan populations in the world. Seventy‐eight species (50.9%) were assessed as threatened (Critically Endangered, Endangered or Vulnerable), and 27 species (17.6%) as Near Threatened. Twenty‐nine species (19%) were Data Deficient with insufficient information to assess their status. Chondrichthyan populations have significantly declined due to largely uncontrolled and unregulated fisheries combined with habitat degradation. Further, there is limited political will and national and regional capacities to assess, manage, conserve or rebuild stocks. Outside the few deepsea locations that are lightly exploited, the prognosis for the recovery of most species is poor in the near‐absence of management. Concerted national and regional management measures are urgently needed to ensure extinctions are avoided, the sustainability of more productive species is secured, and to avoid the continued thinning of the regional food security portfolio.
Keywords: chondrichthyans; extinction risk; fisheries; IUCN Red List; population decline; species diversity

Utilisation of a recovering wetland by a commercially important species of penaeid shrimp - Hart, Craig; Gaston, Troy F.; Taylor, Matthew D. (Wetlands Ecology and Management, 2018)
Penaeid shrimp represent an important group of valuable exploited species known to either directly utilise saltmarsh habitat, or utilise saltmarsh-derived productivity. Consequently, both areal coverage and primary productivity of saltmarsh habitat has direct consequences for the productivity of these important fisheries, and they are likely to be key beneficiaries of habitat repair. This study aimed to establish quantitative estimates of abundance of School Prawn, Metapenaeus macleayi, across a recovering wetland system; Hexham wetland in the Hunter River. Six surveys were conducted across the wetland using a specialised benthic sled, and absolute abundance of School Prawn was estimated. School Prawn were consistently more abundant in certain areas of the wetland (the highest abundance site supported 1017 prawns per 100 m2), and the average density across the wetland was 244 prawns per 100 m2. All areas of the wetland (except the area closest to the wetland mouth) supported the full range of size classes, and multiple cohorts of prawns moved through the system during the sampling program. The asymmetry observed in the distribution of prawns across the wetland is likely to be due to a combination of water quality and inter-specific interactions. These results show that the recovering wetland is supporting a high abundance of School Prawn. Our estimates of recruitment for School Prawn will also be useful in gauging the potential increases in fisheries productivity arising from habitat repair in this, and other systems. As part of the Springer SharedIt initiative, you can now share a full-text view-only version of this paper by using the link https://rdcu.be/bO8RD
Keywords: fisheries productivity; habitat rehabilitation; habitat restoration; mangrove; recruitment; salt marsh

Workshop report from the inaugural National MPA Science/Management Network meeting - Neville Barrett (2018)
A one-day forum was held in Hobart in October 2017 to establish a MPA Science/Management network, and undertake the first formal meeting of the network. The forum was attended by representatives of MPA science and management agencies from most Australian States and the Commonwealth, in response to a long-recognised need for sharing of information and experience across agencies, and to facilitate cooperation, collaboration, standardisation and integration, particularly with respect to monitoring/inventory programs. In addition to sharing information about MPA management on a State-by-State basis, a range of discussions centred around how various agencies matched monitoring programs with management needs, and the extent to which these were driven by formal analysis of risks, values and pressures. Currently these range from the detailed state-wide risk assessment recently undertaken by NSW, and a similar program in the GBR (RIMREP) by the GBRMPA, through to Tasmania, where there are no formal MPA management and monitoring policies in place. The value of building socio-economic studies into the management information framework (and including socio-economic researchers in the network/forum) was discussed, and some examples from South Australian studies highlighted the value of well-targeted socio-economic information for network management. A range of updates on nationally important programs applicable to MPA management and research were presented and discussed. These included: development of nationally consistent standard operating protocols for typical monitoring methods (to aid in national integration); development of a range of national working groups (e.g. AUV, BRUV and MBES) to facilitate uptake of SOPs and aid collaboration and integration of programs; the Essential Environmental Measures Program (and how it aids integration of information for SOE reporting); development of national shared databases (Squidle + and Global Archive), and the need to improve this area where it is currently failing (e.g. MBES data management and sharing). The new Seamap Australia website was also showcased, where all available habitat maps (digitised polygons in habitat classes) from coastal and shelf waters can be viewed. Finally, the formation of an ongoing network and forum was discussed. The aim is to address the recognised need by developing a similar structure to the National Estuaries Network and associated annual forum. After much discussion around the broad or narrow focus of the forum it was decided to start as the narrower MPA Science Management Network (and forum) and assess options for broadening the focus through time. The initial intent is for the network itself to consist of a core of representatives from State and national MPA management agencies and associated major science providers. The network would hold biannual meetings, one by phone/online and one at an annual, one day, face-to-face meeting. As per the National Estuaries Network, the annual one day meeting would be followed by a one day open forum, with a specific topic each year, and open to the wider community to attend. The annual meeting/forum, would be hosted by a different State each year, and organisation/leadership each year would be led by the host State organisation. Next year’s first formal network meeting and forum is proposed for Hobart, with support from the Marine Biodiversity Hub to initiate the process.
Keywords: Australian Marine Park (AMP); management; Marine Protected Area (MPA); network; science

Workshop report from the National BRUV Forum – Perth, 18-19 July 2017 - Neville Barrett (2018)
A two-day forum was held in Perth in July 2017 to establish a national working group to progress cooperation and collaboration between agencies and universities involved in BRUV-based research and monitoring programs. Such cooperation and collaboration is essential to ensure acquired data is suitable for national objectives, such as SOE reporting and monitoring of Australian Marine Parks. It is also essential for the establishment of shared data infrastructure, such as “Global Archive”, and adoption of standard operating protocols as widely as possible, allowing fullest integration of data and monitoring programs between State and Commonwealth agencies. The forum reviewed current programs around Australia to familiarise participants with the widely varying adoption nationally, as well as the range of protocols currently in use. It identified major gaps in spatial coverage that needed filling as a high priority, including the Great Australian Bight, the Coral Sea, and northern waters from Darwin to the Gulf of Carpentaria. When reviewing protocols, it found that most agencies are adopting broadly similar protocols, and that some differences, such as bait types, are often unavoidable (but may not overly bias results). Some of the major differences related to the use of mono vs stereo, and use of subsets of species for length and/or abundance estimates. Possible reporting metrics for State of the Environment (SOE) and similar programs were discussed, and it was agreed that many of the metrics recently developed/reviewed for UVC surveys by the NESP Marine Biodiversity Hub were also highly applicable to BRUV data. However, as many of these metrics involve biomass estimation, and estimates across the full set of species present, it was realised that many of the current programs do not have sufficient data across these measures to allow indicator metrics to be readily developed at national scales without revisiting the acquired video (and size is not possible from mono video, prohibiting biomass estimation). A review of the extent of temporal datasets that may be of use for SOE reporting indicated that many jurisdictions were in an early stage of development, with few programs having data series in excess of three years. The notable exception being NSW MPAs, with a 7-year time series. Hence, BRUV programs are as yet a few years away from making a significant contribution to SOE assessment at national scales, but are likely to do so in the future, particularly as MPA networks and associated monitoring programs (State and Commonwealth) provide the spatial and management frameworks necessary to underpin sound SOE assessments.
Keywords: BRUV; fish; monitoring

2017 AMSA Indigenous Engagement Workshop Summary - Paul Hedge (2017)
The 2017 Australian Marine Science Association (AMSA) Indigenous Engagement Workshop was convened in Darwin on 7 July 2017 to promote Indigenous engagement in marine science by sharing information on successes and identifying what can be done to advance meaningful collaboration. The 2017 workshop created a space for cross-cultural learning about what is needed to develop collaborations through: Sharing examples of successful engagement: how did the partners get started on their collaborative research projects, why do they think these collaborations worked, how did the partners work together to troubleshoot problems along their journey and what were some potential road blocks that could have stopped their collaboration? Providing marine scientists with information on some key resources that are available to help them begin their journey of appropriate Indigenous engagement. Panel discussion around how and when to engage and what is still required to have successful engagement in sea country research collaborations. Presentations and discussions provided a valuable learning experience about the ways Indigenous communities are engaging in marine science projects and programs in Australia. Engagement is a big topic with many considerations. But we need to learn from what works, and what doesn’t, and proceed with no fear. The keys to effective engagement in projects and programs were identified along with valuable insights into things we can do (i.e. as individuals, institutions and through collaborations) above the level of research projects and programs to create a richer Indigenous engagement in marine science.

Abundance and local-scale processes contribute to multi-phyla gradients in global marine diversity - Graham J. Edgar; Alexander, Timothy J.; Lefcheck, Jonathan S.; Amanda E. Bates; Stuart J. Kininmonth; Russell J. Thomson; Duffy, J. Emmett; Costello, Mark J; Rick D Stuart-Smith (Science Advances, 2017)
Among the most enduring ecological challenges is an integrated theory explaining the latitudinal biodiversity gradient, including discrepancies observed at different spatial scales. Analysis of Reef Life Survey data for 4127 marine species at 2406 coral and rocky sites worldwide confirms that the total ecoregion richness peaks in low latitudes, near +15°N and −15°S. However, although richness at survey sites is maximal near the equator for vertebrates, it peaks at high latitudes for large mobile invertebrates. Site richness for different groups is dependent on abundance, which is in turn correlated with temperature for fishes and nutrients for macroinvertebrates. We suggest that temperature-mediated fish predation and herbivory have constrained mobile macroinvertebrate diversity at the site scale across the tropics. Conversely, at the ecoregion scale, richness responds positively to coral reef area, highlighting potentially huge global biodiversity losses with coral decline. Improved conservation outcomes require management frameworks, informed by hierarchical monitoring, that cover differing site- and regional-scale processes across diverse taxa, including attention to invertebrate species, which appear disproportionately threatened by warming seas.

Application of random forest, generalised linear model and their hybrid methods with geostatistical techniques to count data: Predicting sponge species richness - Jin Li; Alvarez, Belinda; Justy P W Siwabessy; Maggie Tran; Z Huang; Rachel Przeslawski; Radke, Lynda; Howard, Floyd; Scott L Nichol (Environmental Modelling & Software, 2017)
Spatial distribution of sponge species richness (SSR) and its relationship with environment are important for marine ecosystem management, but they are either unavailable or unknown. Hence we applied random forest (RF), generalised linear model (GLM) and their hybrid methods with geostatistical techniques to SSR data by addressing relevant issues with variable selection and model selection. It was found that: 1) of five variable selection methods, one is suitable for selecting optimal RF predictive models; 2) traditional model selection methods are unsuitable for identifying GLM predictive models and joint application of RF and AIC can select accuracy-improved models; 3) highly correlated predictors may improve RF predictive accuracy; 4) hybrid methods for RF can accurately predict count data; and 5) effects of model averaging are method-dependent. This study depicted the non-linear relationships of SSR and predictors, generated spatial distribution of SSR with high accuracy and revealed the association of high SSR with hard seabed features.
Keywords: Feature selection; Machine learning; Model selection; Predictive accuracy; Spatial prediction; Spatial predictive model

ARMADA: A marine data aggregator and visualisation tool to support management of Australia’s Commonwealth Marine Area - David Watts; Neville Barrett; Flukes, Emma; Vanessa L Lucieer; Keith R Hayes (2017)
The ability to discover and access historical datasets is a significant challenge for many agencies charged with managing spatially defined marine areas. Unless data have been previously aggregated by (for example) method it is difficult to discover historic datasets as many of these have yet to be made available through the existing national data infrastructure. This need led to the development of the Australian Region MArine Data Aggregation (ARMADA) tool through the NESP Marine Biodiversity Hub partners. ARMADA provides a comprehensive snapshot in time of data available through individual research agency’s geoservers, providing government agencies, industry and other stakeholders a more complete listing and access biological and physical data within Australia’s national marine estate. While this prototype tool was developed to meet a specific user case (Australian Government Department of the Environment and Energy (DOEE) data identification for all biological samples that fall within the boundaries of an irregular shaped polygon, such as the boundaries of a Commonwealth Marine Reserve, Key Ecological Feature or Biologically Important Area) it has clear user benefits for any management or research agencies in identifying the spatial extent of historical research. In developing this tool, the primary aims have been to meet a specific user need and to demonstrate/test the utility of a spatial data aggregation tool. While it appears there is a clear end user need, this tool does require ongoing support and development, and ideally will be incorporated into national data infrastructure such as the AODN network. Differences in software architecture and the challenge of getting research agencies to publish their data in compatible formats may limit immediate adoption by AODN, however, a clear recommendation from this work is that the Hub partners and AODN/IMOS work towards a single source for accessing this marine data in the future. Currently, a significant limiting factor in data discovery and aggregation is that existing data served by WFS through the AODN Portal lack harmonisation, as each provider is free to use any data structure and convention that can be delivered by their map server. While AODN has developed a single controlled ‘parameter’ vocabulary intended to be used for all Australian marine metadata, ARMADA overcame this limitation via a manual process of creating shared vocabularies across similar datasets (thus facilitating aggregation of the data itself), however, this was a significant, and time-consuming technical challenge. We recommend that such a challenge be overcome and automated by development of a national standard for data served via web feature services (WFS), and ongoing discussions and development of controlled vocabularies to structure WFS and annotate metadata records supplied to AODN. Overall, the ARMADA development process has demonstrated pathway to aggregate data from many research agencies across a defined set of data types/gear types within defined spatial boundaries. It highlights a clear need in the existing national data infrastructure, that ideally would be filled via ongoing development within the existing AODN infrastructure.
Keywords: aggregation; AODN; data; discovery; spatial

Assessing national biodiversity trends for rocky and coral reefs through the Integration of citizen science and scientific monitoring programs - Rick D Stuart-Smith; Graham J. Edgar; Neville Barrett; Amanda E. Bates; Baker, Susan C.; Nicholas J. Bax; Becerro, Mikel A.; Just Berkhout; Julia L. Blanchard; Danny Brock; Clark, Graeme J; Cooper, A T; et al. (BioScience, 2017)
Reporting progress against targets for international biodiversity agreements is hindered by a shortage of suitable biodiversity data. We describe a cost-effective system involving Reef Life Survey citizen scientists in the systematic collection of quantitative data covering multiple phyla that can underpin numerous marine biodiversity indicators at high spatial and temporal resolution. We then summarize the findings of a continental- and decadal-scale State of the Environment assessment for rocky and coral reefs based on indicators of ecosystem state relating to fishing, ocean warming, and invasive species and describing the distribution of threatened species. Fishing impacts are widespread, whereas substantial warming-related change affected some regions between 2005 and 2015. Invasive species are concentrated near harbors in southeastern Australia, and the threatened-species index is highest for the Great Australian Bight and Tasman Sea. Our approach can be applied globally to improve reporting against biodiversity targets and enhance public and policymakers’ understanding of marine biodiversity trends.

Assessing the effectiveness of waste management in reducing the levels of plastics entering Australia's marine environment - Denise Hardesty; Kathryn Willis; Qamar Schuyler; T J Lawson; Chris Wilcox (2017)
This preliminary report and plain English summary for this emerging priorities project is intended to be a high-level document that synthesises existing knowledge on the relationship between debris in the marine environment and litter data from nearby sites, and the pathways through which litter moves into the marine environment. Maps showing leakage points and litter or debris concentrations (e.g. hotspots) are also provided.
Keywords: hotspots; litter; marine debris

Assessing the effectiveness of waste management in reducing the levels of plastics entering Australia's marine environment - Final Report December 2017 - Denise Hardesty; Qamar Schuyler; Kathryn Willis; T J Lawson; Chris Wilcox (2017)
Marine debris (or marine litter) is a growing issue of international concern. Defined as any persistent, manufactured or processed solid material discarded, disposed of or abandoned in the marine and coastal environment (UN Environment Program, 2009), it results in a multitude of impacts in coastal and marine environments. Not only does debris impact wildlife, have detrimental economic consequences, result in navigation hazards and transport invasive species, but it also has aesthetic and toxicological impacts on communities and wildlife, respectively. Common items that end up as marine debris include plastic bottles, food packaging, fishing nets or gear, cigarette butts and plastic bags. Marine debris and its upstream source, land-based waste, is a growing environmental, economic and social issue that spans council, state, national and international boundaries. Addressing this complex issue and reducing waste inputs to the marine environment is a challenging undertaking. Managing the issue will benefit from understanding the plastic pollution problem from a large-scale, holistic perspective. This involves conceptualizing the sources and drivers, the distribution and dynamics of debris in the environment as well as identifying and quantifying the impacts on wildlife and humans, and identifying and assessing a suite of potential management responses.
Keywords: hotspots; litter; marine debris

An assessment of alternative management interventions for treatment of Tropical Fire Ants on Ashmore Reef - Terry Walshe (2017)
This report describes outcomes of deliberations of a group of experts and managers in a workshop held on 11 July 2017. In arriving at preferred alternatives among seven candidates (comprising four options for eradication, two for control and a monitor only option), each of ten workshop participants articulated trade-offs among the following set of objectives: Conserve seabirds (more is better) Conserve turtles (more is better) Protect character and naturalness (more is better) Avoid adverse side effects (more is better) Cost of implementation (less is better) The outcome of those trade-offs was broad support for an eradication strategy involving ten bait applications over two years, with subsequent detection, mop-up and monitoring operations.
Keywords: Ashmore; tropical fire ants

Baseline biogeochemical data from Australia’s continental margin links seabed sediments to water column characteristics - Lynda Radke; Nicholas, Tony; Peter A. Thompson; Jin Li; Raes, Eric; Carey, Matthew; Atkinson, Ian; Z Huang; Trafford, Janice; Scott L Nichol (Marine and Freshwater Research, 2017)
Surficial marine sediments are an important source of nutrients for productivity and biodiversity, yet the biogeochemistry of these sediments is poorly known in Australia. Seabed samples were collected at >350 locations in Australia’s western, northern and eastern continental margins during Federal Government surveys (2007–14). Parameters analysed included measures of organic matter (OM) source (δ13C, δ15N and C : N ratios), concentration (percentage total organic carbon, %TOC, and surface area-normalised TOC, OC : SA) and bioavailability (chlorin indices, total reactive chlorins, total oxygen uptake, total sediment metabolism (TSM), sediment oxygen demand (SOD) and SOD and TSM normalised against TOC). The aim of the present study was to summarise these biogeochemical ‘baseline’ data and make contextualised inferences about processes that govern the observed concentrations. The OM was primarily from marine sources and the OC : SA broadly reflected water column productivity (based on Moderate Resolution Imaging Spectroradiometer, MODIS). Approximately 40% of sediments were organic poor by global standards, reflecting seawater oligotrophy; ~12% were organic rich due to benthic production, high water column productivity and pockmark formation. OM freshness varied due to pigment degradation in water columns and dilution with refractory OM in reworked sediments. δ15N values confirmed the importance of N2 fixation to Timor Sea productivity, and point to recycling of fixed nitrogen within food chains in Western Australia.
Keywords: diazotroph; Fe; particulate organic carbon; total nitrogen; Trichodesmium

Biological and habitat feature descriptions for the continental shelves of Australia’s temperate-water marine parks- including collation of existing mapping in all AMPs - Jacquomo Monk; Joel Williams; Neville Barrett; Alan Jordan; Vanessa L Lucieer; Althaus, Franziska; Scott L Nichol (2017)
Understanding the distribution of reef habitats and associated biota on the continental shelf is important for managing Australia’s Marine Park (AMP) network. This is because reef habitats on the continental shelf are highly productive when compared abysal habitats, and are often subjected to disproportionate pressures from fishing, oil and gas and shipping sectors. This report documents the collation, synthesis and location of publically available datasets describing the distribution of reef habitats and associated sessile and mobile biota on the continental shelf regions of AMPs in the Temperate east, South-east, and South-west marine planning regions. Additionaly, this project has also been the identification of key gaps in our understanding of the physical mapping and sampling of reef-affiliated biota to assist in the prioritisation of future research programmes.
Keywords: AMP; biodiversity patterns; Habitat mapping; knowledge synthesis; reef habitat

Bremer Canyon Progress Report - Jessica J. Meeuwig; Turner, Jemma (2017)
In October 2016, researchers, park managers and a tourist operator interested in the Bremer Bay region came together at the University of Western Australia with the aim of assessing the extent and likely drivers of a megafauna aggregation, including orca Orcinus orca, long-finned pilot whales Globicephala melas, sperm whales Physeter microcephalus and several shark species that are currently the focus of tourism activities in an area inside and adjacent to the western margin of the Bremer Commonwealth Marine Reserve (CMR) (Meeuwig et al. 2016). The Minister for Environment and Energy, the Honourable Josh Frydenberg, committed $100,000 to the National Environmental Science Programme’s Marine Biodiversity Hub (MBH) to (1) convene a scientific workshop to design a research plan that may help answer these core questions and (2) conduct priority research in a short time frame. The October 2016, workshop participants identified two areas of priority over the short term as relevant to the needs of the Minister. These were: What is the distribution of marine mammals beyond the recognised aggregation and in relation to the Bremer CMR? What science communication tools do we need to assist in decision making? As a way forward, the following high priority actions were identified: Design a sampling strategy to estimate the distribution of orcas at the aggregation site and within the CMR. Identify with Parks Australia, key communication tools stemming from this new research and in relation to existing research. Parks Australia offered an additional $50,000 to extend the survey options and communication possibilities. The NESP Marine Biodiversity Hub and Integrated Marine Observing System (IMOS) supported deployment of a Seaglider at the time of the aggregation. Researchers from numerous institutions including but not exclusive to the University of Western Australia (UWA), Curtin University, Marine Information and Research Group (MIRG) Australia and IMOS, conducted an array of sampling methods from February 2017, with the aim of capturing the key actions identified at the workshop. This report summarises the current outcomes of these research programs.
Keywords: acoustics; aerial survey; glider oceanography; mid-water video cameras; orca

Broad-scale coastal movements of white sharks off Western Australia described by passive acoustic telemetry data - McAuley, R. B.; Barry D. Bruce; Keay, I. S.; Mountford, S.; Pinnell, T.; Whoriskey, F. G. (Marine and Freshwater Research, 2017)
Movements of 89 acoustically tagged subadult and adult white sharks (Carcharodon carcharias) were monitored off the south and west coasts of Western Australia (WA) between December 2008 and May 2016 by a network of up to 343 passive acoustic receivers. In all, 290 inter-regional movements, totalling 185 092 km were recorded for 73 of these sharks. Estimated rates of movement in excess of 3 km h–1 (mean 1.7 km h–1; maximum 5.6 km h–1) were common, even over distances of thousands of kilometres. Detections indicated that white sharks may be present off most of the south and lower west coasts of WA throughout the year, although they are more likely to be encountered during spring and early summer and are least likely to be present during late summer and autumn. There was limited evidence of predictable return behaviour, seasonal movement patterns or coordination of the direction and timing of individual shark’s movements. Nevertheless, the data suggest that further analyses of movements in relation to ecological factors may be useful predictors of shark activity at local scales. It is hoped that these data may be useful for informing public safety initiatives aimed at mitigating the risks associated with human encounters with white sharks off the WA coast.

Changes in deep reef benthic community composition across a latitudinal and environmental gradient in temperate Eastern Australia - James, Lainey Clare; Marzloff, M P; Neville Barrett; Friedman, A; Craig R. Johnson (Marine Ecology Progress Series, 2017)
Deep reef assemblages in south-eastern Australia are poorly described, and have been surveyed by only a few studies conducted over small spatial scales. Here, we characterize the composition of deep (∼30?90 m depth) sessile invertebrate communities from sub-tropical (27° S) to temperate eastern Australia (43° S). We estimated the cover of 51 preselected invertebrate types from over 1700 seafloor images collected by an autonomous underwater vehicle from >105 km of transects across the study region. Seafloor images were assessed using 3 alternative schemes reflecting different resolution of benthic invertebrate groupings, including the broadlevel Colla borative and Automated Tools for Analysis of Marine Imagery project (CATAMI) classification recently developed as a generic scoring approach for seafloor imagery. Ordination using canonical analysis of principal coordinates indicated a clear latitudinal gradient in benthic community composition and, particularly when based on individual morphotypes, 3 distinct community types (sub-tropical, warm temperate and cool temperate). Changes in community structure mostly correlated with primary productivity and the temperature climatology, while local-scale variability in community composition was most related to depth. Along with the gradual shift in deep reef community composition across latitudes, region-specific sessile invertebrates might serve as useful indicators of change in these deep benthic communities under future changes in ocean climate in the region, which has been identified as a global hotspot for ocean warming. Our methodological approach has general applicability for large-scale surveying and monitoring of benthic communities using underwater imagery.
Keywords: Autonomous underwater vehicle; auv; Benthic invertebrate; climate change; community composition; deep marine reef

Characterising northern estuaries using the Digital Earth Australia - Phillips, Claire; Lymburner, Leo; Brendan P Brooke (2017)
This report provides a preliminary assessment of the utility of a satellite remote sensing approach for the identification and characterisation of coastal habitats that are critical for threatened and migratory species in northern Australia. This work is part of the Habitats research theme in the A12 Northern Seascapes Scoping Project. The Australian Landsat archive in the Digital Earth Australia (DEA) analysis platform for satellite imagery was utilised to demonstrate its potential for mapping intertidal areas and mangrove extent, and changes over time in the extent of coastal landforms and habitats. Seven estuaries were examined, Darwin Harbour and the Keep, Daly, Roper, Macarthur, Flinders and Gilbert River estuaries. The estuaries were selected by the A12 Project team because they are known to provide important areas for the species of interest. Features of importance to shorebird populations were a focus. The focus of this scoping work was to utilise the DEA Landsat archive to build understanding of the effects of tidal dynamics on intertidal habitats across this region of large and complex tides, examine approaches to mapping the extent of key coastal habitats, and test the potential of the archive to detect coastal habitat change, in particular mangrove. In northern Australia, cloud interference can make it difficult to obtain clear satellite imagery. To avoid this issue, the geometric median of surface reflectance values was used with tide-tagged imagery, subset by tide height and date, to produce crisp, cloud-free composite images that depict the maximum and minimum observed tidal extent in the seven estuaries. Tide-tagging of satellite imagery was also successfully employed to allow any tide induced change to be removed from change-detection analyses and clearly depict the intertidal extent. Application of the Intertidal Extent Model in the DEA enabled the extent and morphology of estuarine intertidal environments to be mapped. The DEA also enabled habitat change detection using the fully processed, high density, three decade long Landsat time series. The results clearly depict the dynamic nature of some areas, including large-scale rapid island growth and mangrove expansion (e.g. Keep River and Gilbert River estuaries), gradual long-term expansion of mangrove (Flinders River and McArthur River estuaries), and estuaries with areas of rapid recent die back of mangrove (Roper River and Flinders estuaries). This information is important for the management of key species as well decisions around coastal developments. With Landsat and new satellite data streams (e.g. Sentinel 2) continually being added to the DEA, this time-series analysis approach could be developed into an effective habitat extent and condition monitoring tool for northern Australia. The image products and analysis tools employed in this study demonstrate the potential utility of DEA for mapping the extent and dynamics of key coastal and estuarine habitats utilised by threatened and migratory species. To better inform the management of these species, a key next step in this approach is to utilise ground-validation data to enable these habitats to be robustly classified and quantified using the Landsat archive. This analysis should provide important baseline information and enable the extent and condition of key habitats to be monitored.
Keywords: coastal habitats; migratory species; Satellite remote sensing; threatened species

Colours of the Coral Sea - Rick D Stuart-Smith; Graham J. Edgar (2017)
Surveys by Reef Life Survey divers reveal Coral Sea reef communities to be unique in Australia. Many of the dominant Coral Sea fish and invertebrates, while different from those usually seen on the Great Barrier Reef, are common around Pacific islands more than 1500 km distant, such as Tonga and Samoa. This may be due to the extreme isolation of Coral Sea reefs compared with other Australian reef systems, and /or their greater distance from land-based sediments and nutrients. These photographs were taken by divers participating in Reef Life Survey, a citizen science initiative in which trained volunteer SCUBA divers collect scientific data on the biodiversity of shallow reefs worldwide. Photographers: Graham Edgar, Andrew Green, Ian Shaw, Rick Stuart-Smith, Ken Trebilco Reef Life Survey website http://reeflifesurvey.com/ Download the poster at Item link below Request a copy of the poster and postcard

Community acceptance of marine biodiversity offsets in Australia: results from national surveys - Michael P. Burton; Abbie A Rogers (2017)
In Australia policy exists at both Commonwealth and State levels to govern how environmental offsets can be used to provide an avenue for development to proceed while protecting the environment. This policy is largely driven by scientific considerations about what actions can achieve no net loss in environmental condition. A relatively under-researched question is the degree to which the public accepts the use of offsets, and what elements of the policy design may improve or reduce community acceptance. report presents the results of two national surveys of the general public, aimed at gauging acceptance of offsets in the marine environment. It does so using a hypothetical development in the north of WA, that requires an offset for it to proceed. A clear outcome from the study is that respondents prefer to see offsets being implemented close to the location where the impact occurred, and that concern is highest if the offset is based overseas, even though there may be good ecological and economic reasons for that occurring. There is also some evidence of an endowment effect: those who live in WA are particularly sensitive to the offset being moved out of the state, suggesting they want to see local offsets to compensate for local damage.
Keywords: choice; community; discrete; Marine; offsets

A comparison of genetic connectivity in two deep sea corals to examine whether seamounts are isolated islands or stepping stones for dispersal - Karen J Miller; R. Gunasekera (Nature Scientific Reports, 2017)
Ecological processes in the deep sea are poorly understood due to the logistical constraints of sampling thousands of metres below the ocean’s surface and remote from most land masses. Under such circumstances, genetic data provides unparalleled insight into biological and ecological relationships. We use microsatellite DNA to compare the population structure, reproductive mode and dispersal capacity in two deep sea corals from seamounts in the Southern Ocean. The solitary coral Desmophyllum dianthus has widespread dispersal consistent with its global distribution and resilience to disturbance. In contrast, for the matrix-forming colonial coral Solenosmilia variabilis asexual reproduction is important and the dispersal of sexually produced larvae is negligible, resulting in isolated populations. Interestingly, despite the recognised impacts of fishing on seamount communities, genetic diversity on fished and unfished seamounts was similar for both species, suggesting that evolutionary resilience remains despite reductions in biomass. Our results provide empirical evidence that a group of seamounts can function either as isolated islands or stepping stones for dispersal for different taxa. Furthermore different strategies will be required to protect the two sympatric corals and consequently the recently declared marine reserves in this region may function as a network for D. dianthus, but not for S. variabilis.

A conceptual surrogacy framework to evaluate the habitat potential of submarine canyons - Z Huang; Thomas A Schlacher; Scott L Nichol; Williams, Alan; Althaus, Franziska; Kloser, Rudy (Progress in Oceanography, 2017)
The seascape of the vast Australian continental margin is characterised by numerous submarine canyons that represent an equally broad range of geomorphic and oceanographic heterogeneity. Theoretically, this heterogeneity translates into habitats that may vary widely in their ecological characteristics. Here we describe the methodology to develop a framework to broadly derive estimates of habitat potential for pelagic and epibenthic species (including demersal fishes), and benthic infauna in all of Australia’s known submarine canyons. Our analysis shows that the high geomorphic and oceanographic diversity of Australian submarine canyons creates a multitude of potential habitat types. In general, it appears that canyons may be particularly important habitats for benthic species. Canyons that incise the shelf tend to score higher in habitat potential than those confined to the slope. Canyons with particularly high habitat potential are located mainly offshore of the Great Barrier Reef and the NSW coast, on the eastern margin of Tasmania and Bass Strait, and on the southern Australian margin. Many of these canyons have complex bottom topography, are likely to have high primary and secondary production, and have less intense disturbance to sediment. The framework presented here can be applied – once refined and comprehensively validated with ecological data – to help managers make informed conservation decisions, especially for high value canyons.
Keywords: continental margin; Fauna environmental association; Habitat diversity; Niches; Predictions; Spatial planning

Conserving Critically Endangered spotted handfish - Fact Sheet - T P Lynch (2017)
Unique and quirky, spotted handfish (Brachionichthys hirsutus) are recognisable by their modified fins that resemble human hands. Once common in southern Tasmania’s Derwent estuary, spotted handfish experienced a severe decline in the 1980s. In 1996 they became the first marine fish to be listed as Critically Endangered by the IUCN Red List of Threatened Species. They are also listed as Critically Endangered under the Commonwealth Environment Protection and Biodiversity Conservation Act 1999, and Endangered under Tasmania's Threatened Species Protection Act 1995. CSIRO, University of Tasmania (UTAS), the Tasmanian and Australian governments and the Derwent Estuary Program (DEP) have been working together to conserve spotted handfish since the mid-1990s.
Keywords: actions; anglerfish; Conservation; direct recruitment; handfish

Continental-scale hotspots of pelagic fish abundance inferred from commercial catch records - Phil J. Bouchet; Jessica J. Meeuwig; Z Huang; Tom B. Letessier; Scott L Nichol; M Julian Caley; Watson, Reg A. (Global Ecology and Biogeography, 2017)
Protected areas have become pivotal to the modern conservation planning toolbox, but a limited understanding of marine macroecology is hampering their efficient design and implementation in pelagic environments. We explored the respective contributions of environmental factors and human impacts in capturing the distribution of an assemblage of commercially valuable, large-bodied, open-water predators (tunas, marlins and mackerels). News item - Researchers discover Australian canyons are hotspots for fish life - UWA, 25 August 2017
Keywords: catch rate standardization; fisheries data; geomorphometrics; hotspot; marine reserves; pelagic fishes; random forest; spatial modelling; Submarine canyons; topography

Continental-scale tracking of threats to shallow Australian reef ecosystems - Indicator report - Rick D Stuart-Smith; Graham J. Edgar; Scott D Ling; Neville Barrett; Russell J. Thomson; Sweatman, Hugh P.A. (2017)
Understanding human pressures and their impacts on marine ecosystems, including how these threats may change in space and time, is important for developing and prioritising management of marine natural resources, overarching biodiversity and associated ecological services. To achieve this goal, the capacity to monitor and detect change, in combination with understanding underlying mechanisms of impact, are both fundamental. However, achieving broad spatial and temporal data coverage, and knowing which key indicators of biodiversity reflect directional change related to specific pressures at local and regional scales represent significant challenges. For this report, we combined the three largest long-term monitoring datasets for Australia’s shallow reef communities that provide high taxonomic resolution for tropical and temperate fish, invertebrate and algal species: (1) the Australian Institute of Marine Science Long Term Monitoring Program (AIMS LTM; 276 sites, 23 yrs); (2) Reef Life Survey (RLS; 1,294 sites, up to 9 yrs); and (3) the University of Tasmania Long Term Marine Protected Area Monitoring Programs (LTMPA; 182 sites, up to 25 yrs). All sites and monitoring locations are shown in the map below. These datasets were integrated and analysed with information on major human pressures (fishing, rising sea temperature, introduced/ habitat-modifying species, and pollution) in order to identify impacts and biological indicators most sensitive to these pressures. This comprised the first continental-scale analysis of biogeographic patterns, ecosystem function and the tracking of ecological impacts generated by human-related pressures, and was designed to contribute to State-of-the-Environment (SoE) reporting.   Related information: Reef Life Survey website
Keywords: indicators; pressures; Reef life survey; shallow reefs; State of the Environment

Crossing lines: a multidisciplinary framework for assessing connectivity of hammerhead sharks across jurisdictional boundaries - A Chin; Colin Simpfendorfer; William T White; Johnson, G. J.; McAuley, R. B.; Michelle R. Heupel (Scientific Reports, 2017)
Conservation and management of migratory species can be complex and challenging. International agreements such as the Convention on Migratory Species (CMS) provide policy frameworks, but assessments and management can be hampered by lack of data and tractable mechanisms to integrate disparate datasets. An assessment of scalloped (Sphyrna lewini) and great (Sphyrna mokarran) hammerhead population structure and connectivity across northern Australia, Indonesia and Papua New Guinea (PNG) was conducted to inform management responses to CMS and Convention on International Trade in Endangered Species listings of these species. An Integrated Assessment Framework (IAF) was devised to systematically incorporate data across jurisdictions and create a regional synopsis, and amalgamated a suite of data from the Australasian region. Scalloped hammerhead populations are segregated by sex and size, with Australian populations dominated by juveniles and small adult males, while Indonesian and PNG populations included large adult females. The IAF process introduced genetic and tagging data to produce conceptual models of stock structure and movement. Several hypotheses were produced to explain stock structure and movement patterns, but more data are needed to identify the most likely hypothesis. This study demonstrates a process for assessing migratory species connectivity and highlights priority areas for hammerhead management and research.

Description of the egg cases of Dentiraja polyommata (Rajiformes: Rajidae) and Asymbolus pallidus (Carcharhiniformes: Scyliorhinidae) from Queensland, Australia - Cassandra L. Rigby; William T White; PM Kyne (Zootaxa, 2017)
Descriptions of the egg cases of Dentiraja polyommata (n = 16) and Asymbolus pallidus (n = 44) are provided from egg cases collected from a commercial trawl fishery off Swain Reefs, central Queensland, Australia. Egg cases of D. polyommata are rectangular, convex and golden-tan in colour and those of A. pallidus elongate, vase-shaped and golden. To determine if a comparative statistical non-metric multi-dimensional scaling approach could identify egg cases of species taken in the same region and fishery, egg cases were compared with the skate D. endeavouri and catsharks A. analis, A. rubiginosus and Figaro boardmani. The statistical approach clearly discriminated the species based on five proportional measurements and identified the morphometrics that separated genera and species. This approach is valuable in a fisheries context for accurate identification of visually similar egg cases that can assist management of oviparous chondrichthyans. A rare incidence of intraspecific chondrichthyan cannibalism was noted for A. pallidus males that consumed egg cases of their own species.
Keywords: cannibalism; comparative morphology; egg capsule; oviparous; shark; skate

Does membership matter? Individual influences in natural resource management decision making - Pascoe, Sean; Dichmont, Catherine M. (Marine Policy, 2017)
Increasingly, natural resource management decision making is being undertaken by management committees that consist of a range of stakeholder groups. Representatives on these committees potentially have widely differing objective preferences. Consequently, there exists the potential for management decisions to be affected not only by the type of representation, but by the individuals themselves. In this paper, the robustness of management decision making to both the stakeholder representation and the individual representatives is tested using the case of fisheries management, for which a number of studies have been undertaken in Australia to assess objective preferences within a multi-objective framework. The results suggest that, in most cases, management decisions are robust to membership, but in a small number of instances the actual composition of individuals in a committee may result in different decisions.
Keywords: Decision making; influence; management advisory groups

Ecosystem Understanding to Support Sustainable Use, Management and Monitoring of Marine Assets in the North and North-West Regions: Final Report 2016 - Karen J Miller; Puotinen, ML; Rachel Przeslawski; Z Huang; Phil J. Bouchet; Ben Radford; Jin Li; Johnathan T. Kool; K Picard; Michele Thums; Jessica J. Meeuwig; Scott L Nichol (2017)
Effective management of marine assets requires an understanding of ecosystems and the processes that influence patterns of biodiversity. Project D1 of the NESP Marine Biodiversity Hub has been collating and synthesising existing data through 2015/16, focusing on Commonwealth Marine Reserves (CMRs) and Key Ecological Features (KEFs) of the North and North-west regions of Australia’s marine estate, with three main objectives: Increase the accessibility of existing research and data products to end users including managers, regulators and the general public Identify knowledge gaps and develop strategies to address these Improve ecosystem understanding of KEFS and CMRS through predictive modelling Building on the North West Atlas (www.northwestatlas.org) as a communication platform, we collated 179 data sets for the North and NW Regions, and these are now accessible online. Targeted syntheses of knowledge for the Oceanic Shoals CMR and the Ancient Coastline KEF were used to demonstrate the value of this approach for informing marine planning and management and highlighting uncertainty. Based on collated data sets, we undertook a formal gap analysis across CMRs and KEFs of the North and NW regions to identify those areas for which there exists sufficient data to underpin spatial predictive modelling in future years. Our results highlight the patchiness of available biophysical information, and large differences in coverage among taxa across the CMR network. We considered that the Kimberly CMR was the only area across the North and NW region for which existing data might underpin accurate spatial predictive modelling in the future. Our gap analysis did highlight CMRs and KEFs for which information coverage is greatest, as well as areas in which targeted empirical data collection would both inform future management and planning and enhance our capacity to use predictive models for ecological inference. We used the Oceanic Shoals CMR as a case study for assessing the value of spatial predictive models in delivering knowledge of habitats and species distributions in remote, unsampled areas. We predicted the distribution of a range of biological and physical characteristics across the entire CMR, including benthic habitats, pelagic species, sponge diversity, and sediment type and hardness. This exercise shows the value of this approach for identifying assets in the marine estate where it is impossible to collect comprehensive data, and is a guide for stakeholders in identifying future data needs and tools required to adopt a similar approach nationally. The Oceanic Shoals predictive modelling example also provides a perspective on how modelling performance needs to be considered in the interpretation of predictive model outputs and maps. Innovative science continues to support the effective management of Australia’s marine estate. In addition to the data collation, synthesis and modelling, the Project D1 team has been developing a range of manuscripts for publication in the peer-reviewed literature. A summary of key findings and progress of eight papers that collectively value-add to past NERP and present NESP research in the North and NW Regions is provided. Novel science discoveries include the identification of pelagic fish hotspots, environmental predictors of flatback turtle behaviour, impacts of cyclones on turtle movements, and descriptions of potential biological and geomorphic values in the Oceanic Shoals CMR. The work undertaken to date as part of Project D1 has created an easily accessible knowledge framework for the Oceanic Shoals CMR and the Ancient Coastline KEF that will directly inform the development of management and monitoring plans in these areas. We have demonstrated how spatial predictive modelling can be used to fill knowledge gaps and hence form a foundation for the evolution from precautionary management based on minimal information to more effective management based on a more rigorous scientific understanding of ecosystems. We also identified CMRs and KEFs where similar approaches can be implemented easily or with minimal additional investment in field data capture. The methods illustrated here for the North and NW regions provide a template for the application of similar approaches to other regions of Australia, where similar data are available or could be obtained, in particularly for supporting additional KEF characterisation and CMR monitoring and management.
Keywords: CMR; gap analysis; north region; north west region; predictive modelling

Enhancing access to relevant marine information – developing a service for searching, aggregating and filtering collections of linked open marine data - final report - Johnathan T. Kool (2017)
This is a summary of outcomes from NESP Project B3, Enhancing access to relevant marine information – developing a service for searching, aggregating and filtering collections of linked open marine data. As part of the project, software was developed capable of tagging unstructured collections of documents (including Word documents, PDFs, spreadsheets, presentations, metadata and images among others) using an arbitrary vocabulary (term list), and then being able to structure, search, and deliver those documents through a web service. A demonstration web page interface was developed to highlight the capabilities of the service, and the results have been presented to NESP partner organisations, including representatives of: the Department of the Environment and Energy (DoEE), Parks Australia (under DoEE), IMOS/AODN, the Australian Institute of Marine Science (AIMS), and the Great Barrier Reef Marine Park Authority (GBRMPA). The capabilities of the software can be replicated and integrated into partner websites (e.g. the North West Atlas, and the NESP website).
Keywords: data management; hydroid; linked data; search; semantic

Environmental predictors of foraging and transit behaviour in flatback turtles (Natator depressus) - Michele Thums; Waayers, D; Z Huang; Pattiaratchi, C; Bernus, J; Mark Meekan (Endangered Species Research, 2017)
Sea turtles migrate between nesting beaches and foraging grounds, but little is known about the cues they use to direct these migrations, and the habitats that define their foraging grounds. Here, we used satellite telemetry to follow the movements of 11 flatback turtles Natator depressus after nesting on islands in the waters off the coast of the Kimberley region of northern Australia. State-space models were used to objectively define inter-nesting, migration and foraging behaviour during the 327 ± 315 d (mean ± SD) that the turtles were tracked. These animals migrated along the coast in water depths of 63 ± 5 m to foraging grounds on the mid-Sahul Shelf in the Timor Sea in average water depths of 74 ± 12 m, 135 ± 35 km from shore. Distribution modelling showed that flatback turtles preferred foraging and transiting in clear waters (suspended material <0.06 g m−3), 60 to 90 m deep and in association with complex, benthic geomorphology (banks, shoals, terraces, deep holes and valleys) thought to support a high abundance of sessile invertebrates, the likely targets of their foraging. Distance to the tidal front was also a strong predictor of turtle migratory behaviour, with the animals potentially following tidal fronts along the Kimberley coast. Our study identified both critical habitats for this species and the environmental variables that predict their migration and foraging. This information is important to aid spatial planning of conservation for this data-deficient species that is endemic to northern Australia.
Keywords: Key ecological feature; Kimberley; Lacepede Islands; migration; Sahul Shelf; Satellite tracking; State-space model; Telemetry; Tidal fronts; ·Inter-nesting

Factors influencing the use of decision support tools in the development and design of conservation policy - Gibson, Fiona L.; Abbie A Rogers; Smith, Anthony D.M.; Roberts, Anna; Possingham, Hugh; McCarthy, Michael; Pannell, David J. (Environmental Science & Policy, 2017)
There are many examples of decision support tools used to analyse information with the intention of assisting conservation managers and policy makers in their decision making. We used structured interviews to collect information on seven case studies from Australia and New Zealand to identify the factors that led to the use (or non-use) of decision support tools when developing conservation policies. The interviews explored hypotheses derived from existing literature on the use of decision support tools in conservation policy. Qualitative analysis of the interviews indicated that key factors influencing the uptake of a decision support tool in conservation policy include the alignment of the tool with the objectives and context of a policy, and its ability to be useful even in the presence of missing data. Two other factors that had been suggested in past literature were not perceived by interviewees to be as important as the above two: the presence of a champion for the decision support tool within the management agency, and the time required to apply the tool. The interviews also revealed a number of additional factors that influenced use or non-use of decision support tools that we had not extracted from existing literature: ambiguity about policy objectives, the autonomy of the agency, and the employee time costs of applying the decision support tool.
Keywords: Conservation policy; Decision making; Decision support tools; Marxan

How successful are waste abatement campaigns and government policies at reducing plastic waste into the marine environment? - Kathryn Willis; Maureaud, Clémentine; Chris Wilcox; Denise Hardesty (Marine Policy, 2017)
Plastic production is increasing globally and in turn there is a rise of plastic waste lost into the coastal and marine environment. To combat this issue, there is an increase in policies that target specific types of plastic waste (such as microbeads and plastic shopping bags). Given that such anthropogenic waste have environmental impacts, reduce the tourism income of an area and result in human health issues, identifying effective abatement policies is imperative to reducing waste and litter before it enters the ocean. Within Australia, state and local governments employ a plethora of policies, campaigns and strategies to target abatement and reduce litter and waste inputs to the environment. Waste managers were interviewed from 40 local councils around Australia on waste abatement strategies and investments implemented in their council. Generalised linear models (GLMs) were used to compare outreach programs (such as ‘Don’t be a Tosser’, Clean Up Australia and Bin your Butts cigarette campaign) and state-enacted policies (e.g. Plastic Shopping Bag Ban, Zero Waste Strategy and Recycling Strategy) aimed at targeting human behaviour to reduce waste. Investments in campaigns led to larger reductions of waste in the environment than did investment in policies. Illegal dumping, litter prevention, recycling, education and Clean Up Australia programs all significantly reduced waste along a council's coastline. Additionally, councils that invested in a coastal waste management budget had fewer littered or waste items on the coastline within their jurisdictions.
Keywords: abatement campaigns; litter; local government; policy; waste effectiveness

The importance of offshore origination revealed through ophiuroid phylogenomics - Guadalupe Bribiesca-Contreras; Verbruggen, Heroen; Andrew F. Hugall; Tim O'Hara (Proceedings of the Royal Society B: Biological Sciences, 2017)
Our knowledge of macro-evolutionary processes in the deep sea is poor, leading to much speculation about whether the deep sea is a source or sink of evolutionary adaptation. Here, we use a phylogenetic approach, on large molecular (688 species, 275 kbp) and distributional datasets (104 513 records) across an entire class of marine invertebrates (Ophiuroidea), to infer rates of bathymetric range shift over time between shallow and deep water biomes. Biome conservation is evident through the phylogeny, with the majority of species in most clades distributed within the same bathome. Despite this, bathymetric shifts have occurred. We inferred from ancestral reconstructions that eurybathic or intermediate distributions across both biomes were a transitional state and direct changes between shallow and deep sea did not occur. The macro-evolutionary pattern of bathome shift appeared to reflect micro-evolutionary processes of bathymetric speciation. Results suggest that most of the oldest clades have a deep-sea origin, but multiple colonization events indicate that the evolution of this group conforms neither to a simple onshore–offshore hypothesis, nor the opposite pattern. Both shallow and deep bathomes have played an important role in generating the current diversity of this major benthic class.
Keywords: bathome shifts; brittle stars; macro-evolutionary patterns; onshore–offshore

An integrated monitoring framework for the Great Barrier Reef World Heritage Area - Paul Hedge; Molloy, F.; Sweatman, H.; Hayes, K.R.; Jeffrey M Dambacher; Chandler, J.; Nicholas J. Bax; Gooch, M.; K. Anthony; Elliot, B. (Marine Policy, 2017)
Monitoring provides important feedback on how social and environmental systems are tracking and whether or not human activities, including management activities, are having an impact. This paper describes an approach applied to develop an integrated monitoring framework to inform adaptive management of the Great Barrier Reef World Heritage Area, a complex, multi-jurisdictional, multi-sectoral marine system of international importance. It identifies the gaps and opportunities to integrate the existing long-term, short-term and compliance-related monitoring and reporting initiatives to provide the information for more effective and efficient (adaptive) management of the Great Barrier Reef World Heritage Area. And as importantly it aligns expectations among different agencies about how monitoring will inform management. Fifty two high priority values, processes and pressures for management were identified along with 65 existing monitoring programs. Developing the monitoring framework was useful in several ways. First it brought together scientists, policy-makers, managers, and other interested stakeholders with different agendas, philosophies and incentives and established a common purpose, lexicon and language for an integrated monitoring program. Second, it highlighted the importance and usefulness of qualitative conceptual models as a framework for focused discussion around a set of hypotheses with relevance for management. Third, the process started an important conversation about defining and setting a realistic number of monitoring priorities for management. Finally, it has provided direction for how to build on existing initiatives to develop an integrated monitoring program for a globally significant world heritage area. Related information: Download the report published in 2013 commissioned by the Department of the Environment
Keywords: adaptive management; Coral reef; Decision making; environmental monitoring; marine reserve

Juvenile white sharks Carcharodon carcharias use estuarine environments in south-eastern Australia - David Harasti; K. A. Lee; Barry Bruce; C. Gallen; R. W. Bradford (Marine Biology, 2017)
Estuarine environments are known to provide important feeding, breeding, resting and nursery areas for a range of shark species, including some which are considered dangerous to humans. Juvenile white sharks (<3 m) are known to frequent inshore environments, particularly ocean beaches, but their presence in and use of estuaries and coastal embayments is unclear. Given that estuarine environments are often surrounded by highly populated areas, understanding how white sharks use these environments will not only assist with their conservation management, but also inform public safety policies. The use of estuarine environments by acoustic-tagged white sharks was investigated from 2009 to 2015 at Port Stephens, New South Wales and Corner Inlet, Victoria, both of which adjoin known nursery areas for the species. Juvenile white sharks were detected within both estuaries, with 20 individuals recorded within the Port Stephens estuary, including four on one day. Only one tagged shark was detected within Corner Inlet; however, monitoring effort and local tagging in the area was more restricted. Detections in Port Stephens were predominantly from October to January and peaked in November. This study demonstrates that the footprint of known nursery areas for white sharks in eastern Australia should be expanded to include their adjacent estuarine environments. Consequently, there is clear potential for them to be exposed to a range of anthropogenic estuarine impacts, and that human interactions are more likely over warmer periods (summer), when human use of such waterways is more prevalent.
Keywords: Carcharodon carcharias; Corner Inlet; estuary; Marine; nursery area; Port Stephens; threatened species

Malak Malak Sawfish Patrol & Relocation Protocol - Christy Davies; PM Kyne; Green, Aaron; Shields, Amos; Lindsay, Rob (2017)
The Largetooth Sawfish (scientific name Pristis pristis language name Tyemirerriny) can be found in the freshwater section of big rivers in north Australia and so some people also call it the Freshwater Sawfish. It used to be found in many regions across the world, but these days they have disappeared from many of these, and north Australia is now one of the last places where there are still good numbers anywhere in the world. The population has gone down so much that they are said to be ‘Critically Endangered’ on a global scale, meaning scientists think they could go extinct in the near future. Because of this, they have been given special legal protection in Australia. This sawfish has a very interesting lifecycle, and can be found in different places at different ages. The mothers give birth to babies (called pups) in an estuary. The pups then swim upstream to the freshwater section of rivers, where they live for several years (up to 4–5 years). Once they are older they swim downstream and back out to the ocean where they live as adults. When they are old enough to breed the females come back to the same estuary where they were born to have their own babies. While they are living in the freshwater they sometimes follow flood waters out of the main river channels and into waterholes. As water levels recede in the dry season, they are forced into remaining isolated waterholes, where they become stuck until the next wet season. This is a natural process, and it normal that some of them might die if they waterhole they are in dries up before the next wet season arrives. But there are two problems these days: 1) There aren’t many sawfish left to keep the population going; and 2) the weather is changing so they are drying out more often and the waterholes that do still hold water are not as safe anymore, and feral buffalo and pigs are making the water unhealthy.
Keywords: Malak Malak sawfish patrol and relocation; threatened sawfish

Monitoring of Spotted Handfish (Brachionichthys hirsutus) populations and on ground conservation actions - Lincoln Wong; T P Lynch (2017)
Spotted handfish are a critically endangered species with limited data available to track their conservation trajectory. In 2016 we completed a second meta-population scale survey of all known local populations of spotted handfish within the Derwent Estuary and conducted exploratory surveys in the D’Entrecasteaux Channel. We also consolidated all historic density estimates from these sites to provide trend data for this species. This has delivered a scientifically robust monitoring program to track conservation trajectories and performance of the recently signed recovery plan across all known local populations (Recovery plan actions 4a, 4b, 4d and 4e). Collecting this data is crucial for informed implementation of policy such as further targeted placement of artificial spawning habitat (ASH) (Actions 1c and 1d) and to determine minimum population size to inform sustainable capture of brood-stock for an 'ambassador fish' project to build capacity to undertake a captive breeding project with industry (Action 3b-c). Other on-ground conservation outcomes include purchasing eco-friendly moorings for placement into critical handfish habitat (Action 2c), and engagement with the broader community through talks, outreach and publications (Action 6a).
Keywords: coastal; endangered species; Spotted handfish

Monitoring Population Dynamics of ‘Western’ Right Whales off Southern Australia - final report on activities for 2016 - John Bannister (2017)
To continue an annual series of aerial surveys off the southern Australian coast between Cape Leeuwin WA and Ceduna SA since 1993, an aerial survey was undertaken over three days, 24-29 August 2016. Because of bad weather, and for the first time in the annual series since 1993, only ‘outward’ flying legs were possible. For comparison with previous results, counts were obtained of 628 individuals including 228 calves of the year. The 2016 counts were higher than the very low count in 2015 but still below the recent trend line. From 4305 photographic images obtained, 323 have been selected for computer-assisted ‘matching’ with those (some 7000 images of over 2000 individuals) already available in the catalogue, and 197 data sightings sheets have been added to the sightings database, currently totalling 3741 sightings sheets. Regression analysis of log number against year for the period 1993-2016 gives increase rates for all animals of 0.0541 (95% CI 0.0371, 0.0710) equivalent to an increase of 5.55% (95% CI 3.78, 7.36) per annum, and for cow/calf pairs 0.0584 (0.0343, 0.0824) or 6.01% (3.49, 8.59) per annum, respectively. Current population size, for this the ‘western’ Australian subpopulation, is estimated at 2195. A Progress Report on the 2016 survey was provided on 31 December 2016. This is the Final Report on the 2016 survey and associated activities. News article - Southern right whale count tallies record numbers off south coast - ABC, 29 August 2017

NESP Marine Biodiversity Hub Research Plan - 2017 RPv3 - Project Proposals - Nicholas J. Bax; Paul Hedge (2017)
This Research Plan for 2017 (RPv3) has been developed by the Marine Biodiversity Hub, in consultation with the Department of the Environment and Energy and other key stakeholders. The purpose of the Research Plan is to outline: the research priorities the Hub is funded to investigate the research projects that will address these priorities how the output of the research will be communicated and brokered to key stakeholders how the impact of the research will be measured how Hubs will work collaboratively within and across Hubs This Research Plan also lists key staff and research organisations, and the risks needing to be monitored to ensure success. Please note: Project durations vary and may extend over a number of years.  If the project you are interested in is not listed in the Item field of this research plan, it will be included in an earlier year as an ongoing, unchanged project. Where a project proposal involves significant changes, it will be updated and included in subsequent research plans.
Keywords: annual research plan; RPv3

A new wave of marine evidence-based management: emerging challenges and solutions to transform monitoring, evaluating, and reporting - P F E Addison; Collins, D J; Trebilco, R; Howe, S; Nicholas J. Bax; Paul Hedge; Jones, G; Miloslavich, Patricia; Roelfsema, C; Sams, M; Rick D Stuart-Smith; Scanes, P; et al. (ICES Journal of Marine Science, 2017)
Sustainable management and conservation of the world’s oceans requires effective monitoring, evaluation, and reporting (MER). Despite the growing political and social imperative for these activities, there are some persistent and emerging challenges that marine practitioners face in undertaking these activities. In 2015, a diverse group of marine practitioners came together to discuss the emerging challenges associated with marine MER, and potential solutions to address these challenges. Three emerging challenges were identified: (i) the need to incorporate environmental, social and economic dimensions in evaluation and reporting; (ii) the implications of big data, creating challenges in data management and interpretation; and (iii) dealing with uncertainty throughout MER activities. We point to key solutions to address these challenges across MER activities: (i) integrating models into marine management systems to help understand, interpret, and manage the environmental and socio-economic dimensions of uncertain and complex marine systems; (ii) utilizing big data sources and new technologies to collect, process, store, and analyze data; and (iii) applying approaches to evaluate, account for, and report on the multiple sources and types of uncertainty. These solutions point towards a potential for a new wave of evidence-based marine management, through more innovative monitoring, rigorous evaluation and transparent reporting. Effective collaboration and institutional support across the science–management–policy interface will be crucial to deal with emerging challenges, and implement the tools and approaches embedded within these solutions.
Keywords: adaptive management; Biodiversity; collaboration; environment; environmental impact assessment; fisheries; modelling; monitoring; socio-economic

Niche metrics suggest euryhaline and coastal elasmobranchs provide trophic connections among marine and freshwater biomes in northern Australia - Every, S L; Pethybridge, H R; Fulton, C J; PM Kyne; Crook, D A (Marine Ecology Progress Series, 2017)
Tropical elasmobranchs could play significant roles in connecting coastal and river ecosystems, yet few studies have explored the trophic ecology of elasmobranch species that may link these biomes. We investigated the trophic niches of 7 such species in northern Australia during the tropical monsoonal wet and dry seasons, using stable carbon (δ13C) and nitrogen (δ15N) isotopes (SI), and fatty acid (FA) biomarkers taken from muscle tissue. Both SI and FA metrics suggested significant niche partitioning between species, with 2 distinct guilds: a marine food web based on epiphytes and seagrass (low δ13C), and an estuarine/freshwater food web with a seston base (higher δ13C). A large overlap in SI niche areas and higher mean trophic positions (4.1−4.8) were evident in species accessing marine diets (Carcharhinus leucas, Rhizoprionodon taylori) when compared with species predominantly feeding in estuaries (3.2−3.6; Glyphis garricki, G. glyphis). Across all seasons, G. garricki had the greatest FA niche space, and variable overlap with 2 other species (R. taylori, C. leucas). Although limited seasonal effects were apparent for individual FA biomarkers, SI niche metrics revealed greater niche areas and inter-specific partitioning during the dry season for 3 species. Subtle differences in niche metrics derived from SI and FAs were likely due to disparate turnover times, and the statistical approach of each metric (2-dimensional versus multi-dimensional). Collectively, our analyses suggest that these tropical coastal and euryhaline elasmobranchs consume prey from a range of sources to provide trophic connections across marine, estuarine and freshwater biomes.

Northern Australia Hammerhead Shark Tagging Program - Fact Sheet - A Chin (2017)
Northern Australia has two large species of hammerhead sharks, the scalloped hammerhead and great hammerhead. They can migrate long distances. This makes it difficult to manage them, because impacts in one place may affect the whole population. To properly understand and manage the threats facing hammerhead sharks, we need to learn how the sharks move across all of the northern Australian states, including any movements between Papua New Guinea and Indonesia. We will tag hammerhead sharks with satellite tags to track where they go, and collect small tissue samples to help see which populations are connected.
Keywords: fisheries; hammerhead; Indigenous tracking; shark; tag

Palaeoshorelines on the Australian continental shelf: morphology, sea-level relationship and applications to environmental management and archaeology - Brendan P Brooke; Scott L Nichol; Z Huang; R J Beaman (Continental Shelf Research, 2017)
Palaeoshorelines that lie submerged on stable continental shelves are relict coastal depositional and erosional structures formed during periods of lower sea level. An analysis of the well-dated Late Quaternary (0–128 ka) sea-level record indicates that the most persistent (modal) lower sea levels were at 30 – 40 m below present, which occurred between 97 and 116 ka and at approximately 85 ka and 10 ka. A secondary modal position was at 70–90 m that occurred mostly during a period of fluctuating sea level between 30 and 60 ka, as well as at around 87 ka (70 – 80 m only) and 12−15 ka. For the tectonically stable Australian continental shelf, we show that a range of shorelines formed at each of these sea level modal positions and their morphology and degree of preservation depends on composition (carbonate vs siliciclastic) and oceanographic setting (wave, tide and wind energy). These ancient coasts record a range of oceanographic and geological regimes that existed during relatively long periods of lower sea level and provide a guide to the general depth zones in which similar features likely occur on other shelves globally. Australian palaeoshorelines represent distinctive benthic habitats that strongly influence the distribution of biodiversity across the shelf. Accurate mapping of these features provides a robust geospatial framework for investigations of marine species distributions and environmental change monitoring. These data also enable the better targeting of relict coastal areas that potentially include sand resources and sites of human occupation during periods of lower sea level.

Recreational fishing impacts on threatened river sharks: A potential conservation issue - PM Kyne; Pierre Feutry (Ecological Management & Restoration, 2017)
The Adelaide River in Australia's Northern Territory is a popular recreational fishing area, as well as habitat for threatened and protected river sharks (Glyphis species). Both the Critically Endangered Speartooth Shark (Glyphis glyphis) and Endangered Northern River Shark (Glyphis garricki) are identified here in illegal catches from recreational angling. The identification of a decayed shark specimen using a DNA barcoding-like approach is the first such application to the identification of protected sharks in a recreational fishery. While the extent of catches by recreational anglers is unknown, the threatened status of these sharks, their suspected low population sizes, restricted distributions and importance of the Adelaide River as a nursery area call for the consideration of this as a potential conservation issue. As such, appropriate measures should be taken to reduce interactions with recreational anglers. The primary target species in the river is the iconic sportfish, Barramundi, which is predominantly caught by unbaited lure. Sharks are rarely caught on lure, allowing an opportunity for mitigation to focus on a fishing activity (baited hooks) which would limit any regulatory impact on popular lure fishing. Potential mitigation measures range from increased angler education and compliance checks, to the implementation of a spatial closure to baited hook fishing (a lure-only zone). Such measures may assist in meeting a stated objective of the Australian Government's river shark Recovery Plan to ‘reduce and, where possible, eliminate adverse impacts of recreational fishing'.
Keywords: Adelaide River; DNA barcoding; Glyphis garricki; Glyphis glyphis; protected species.

Repairing and conserving Australia’s saltmarshes and seascapes - Colin Creighton; Terry Walshe; Ian M. McLeod; Vishnu Prahalad; Sheaves, Marcus; Taylor, Matt (2017)
Australia's coastal marine biodiversity and accompanying benefits such as fisheries have been markedly reduced due to loss of essential inshore habitats. These coastal habitats provide a nursery ground for a multitude of animals, including fish, prawns and birds. Many species depend on inshore habitat during critical early life-stages characterised by rapid growth and development (coastal dependency). These coastal tidally linked wetlands (commonly known as ‘seascapes’) comprise mangrove-lined channels, salt marshes, mud flats, sedge lands and sub tidal and inter tidal channels and gutters. Much of the losses in habitat have occurred as a function of Australia's development for urban, infrastructure and agricultural uses - all of benefit to Australia's economy. While better planning and management could have reduced the impact on our coastal marine biodiversity much of the task ahead for Australia is about land use optimisation - seeking the best patterns of use and management that will maximise overall community benefits. Essentially re-creating or repairing key components of coastal habitat for benefits whether it is commercial or recreational fishing, water quality, biodiversity or carbon sequestration. If these restoration efforts are planned and implemented carefully Australia can maximise benefits from its coastal resources while achieving urban, infrastructure and agricultural development.
Keywords: coastal; fishery; prawn; restoration; Saltmarsh

Report from workshop on characterising underwater shipping noise in Australia - David Peel; Joshua N. Smith; Christine Erbe (2017)
The objective of the meeting was to present and discuss the initial results from the current project related to mapping of shipping noise. The meeting also provided an opportunity to discuss the future proposed project that will be extending this work and coordinate research with stakeholders and their management priorities to ensure the project delivers useful tools for management. Specifically:   Provide a brief overview of noise mapping projects overseas and the underlying management imperatives Present preliminary findings of shipping noise maps from current NESP C5 project Identify management priorities related to underwater noise by relevant stakeholders Provide an overview of the future proposed NESP shipping noise project Discuss future direction and development of noise maps for Australia
Keywords: noise; shipping; Workshop

Restoring Angasi oyster reefs: What is the endpoint ecosystem we are aiming for and how do we get there? - Chris L Gillies; Crawford, Christine; Hancock, Boze (Ecological Management & Restoration, 2017)
Three-dimensional reefs and beds created predominately by the native Angasi Oyster or Flat Oyster (Ostrea angasi) were once common across its range in Australia's southern coastal waters but were lost during the mid-late1800s and early 1900s due to a combination of destructive fishing practices, overfishing and changes to estuarine conditions. Despite the continued presence of low densities of individuals and cessation of commercial fishing, reefs structures and their associated communities have shown little signs of natural recovery. Since 2014, a range of oyster reef restoration projects have commenced in Australia, guided by international restoration protocols that prioritise the re-establishment of the keystone species on artificial stable substrates placed in locations where natural oyster reefs have previously existed. These projects invariably need clear and realistic goals and objectives for restoration, which are aided by the use of a reference ecosystem as a model or target, for the local oyster reef ecosystem being restored, yet few reference sites exist. Reefs, established by Angasi, are absent from much or all of its geographical distribution, and the ecosystem has been poorly studied to date; hence, the application of restoration target ecosystems will largely depend on deriving a model based on historical descriptions and observation of what remains. Here, we develop an interim reference model to help set restoration objectives and recommended procedural framework for Angasi reef restoration based on available knowledge of the ecology, biology and aquaculture of the keystone species. We use the Port Phillip Bay oyster reef restoration project as a case study for using the reference model to guide interventions and evaluate the progress of recovery.
Keywords: coastal; coral; mangrove; restoration; seagrass

Sawfishes in Papua New Guinea: a preliminary investigation into their status and level of exploitation - William T White; Sharon A Appleyard; PM Kyne; Ralph Mana (Endangered Species Research, 2017)
The status of sawfishes (family Pristidae), and indeed most sharks and rays, in Papua New Guinea (PNG) is largely unknown due to the paucity of detailed catch and observational records available, both historic and contemporary. This paper provides the first comprehensive review of the published and unpublished literature on sawfish records in PNG. It also collates information for all sawfish specimens in the holdings of museum and fisheries collections, dating back to the late 1800s. Opportunistic sampling during a shark and ray biodiversity project in PNG has resulted in contemporary records for all 4 sawfish species known to occur in the region (i.e. Anoxypristis cuspidata, Pristis clavata, P. pristis and P. zijsron) and identification of suitable habitat for the species across PNG. A review of the literature shows that declines in sawfish populations have occurred in a number of locations. Detailed surveys of the key areas highlighted in this study are urgently required to assess the current status of sawfish in PNG. This information is crucial for developing a global strategy for sawfish conservation and fisheries management, given the apparent persistence of all 4 Indo-Pacific species in PNG.

Scoping report: Comparative assessment of benthic sampling platforms - Rachel Przeslawski (2017)
Marine monitoring of Commonwealth reserves requires sampling of biological and environmental factors over space and time in order to assess status and detect trends. There is a huge range of methods used to sample benthic biota and environments, some of which are frequently used and well-established (Hopkins 1964), and others that are new or contentious (Rhoads et al. 2001). For biological sampling at the seafloor, sampling methods can be broadly grouped into destructive epifaunal samplers (sleds, trawls, dredges), destructive infaunal samplers (grabs, corers,), and non-destructive samplers (imagery systems) (Bowden et al. 2015). There is also a range of acoustic methods that can be used to map the seafloor (multibeam sonar, sidescan sonar, single-beam sonar) (Brown et al. 2011). Although these usually don’t provide biological data, they are the foundation for monitoring activities in large regions, as they facilitate extensive and precise descriptions of physical habitat. A number of established protocols for marine sampling exist for various regions, habitats, and objectives (reviewed in Coggan et al. 2005) and have been nationally standardised and implemented for shallow Australian waters (e.g. Reef Life Survey (Stuart-Smith et al. 2017) and pelagic megafauna (e.g. Animal Tracking Facility). It can be daunting to consider all marine sampling platforms in the context of a monitoring program and to ensure that the most appropriate methods are adapted for a given purpose. There is thus a need for a synthesis of benthic marine sampling platforms as they relate to the design and implementation of monitoring programs. As part of the NESP Project D2 (‘Standard Operating Procedures for survey design, condition assessment and trend detection’), this scoping report will provide the basic framework for a subsequent report comparing benthic marine sampling platforms, including their suitability for use with different monitoring objectives. A complementary scoping report exists for pelagic platforms (Bouchet et al. 2017).
Keywords: auv; BRUV; multibeam grab; trawl

Scoping report: Comparative assessment of pelagic sampling platforms - Phil J. Bouchet; Jessica J. Meeuwig; Scott D Foster; Rachel Przeslawski (2017)
Despite being the most voluminous of the planet’s biomes, the pelagic ocean is chronically underexplored and drastically data-deficient . Australia, for instance, boasts the third biggest ocean territory in the world (by surface area), yet knowledge of both benthic and pelagic biodiversity values and processes throughout this vast estate remains largely incomplete. Monitoring activities are fundamental to bridging these knowledge gaps by generating the data necessary to assess, understand and document trends in natural communities throughout the country’s Marine Commonwealth Area (MCA), in response to both environmental pressures and spatial management measures. In an era of unprecedented concern about global marine defaunation, increasingly modest conservation budgets are placing a strong emphasis on strategic resource allocation. Faced with mounting pressures to build accountability, managers and policy advisors must now more than ever make investment decisions that are not only wise but also cost-effective. This can be challenging given the smorgasbord of modern survey tools currently available, most of which differ widely in costs, capabilities, mobilisation constraints, resolution or sensitivity, and are evolving very rapidly without always being critically evaluated or compared. In recent years, novel technologies for sampling pelagic organisms and/or habitats such as drifting videography, environmental DNA, unmanned (airborne or waterborne) vehicles, or wireless sensor networks (among many others) have emerged and have been gaining traction. They can supplement (or sometimes replace) more traditional and longer-established pelagic sampling approaches like midwater trawling, aerial and vessel-based visual transects, passive and active acoustics, electronic telemetry, or remote sensing, yet protocols for choosing optimal combinations of methods for a given region, taxonomic/indicator group, or environment remain generally unavailable. Additionally, the few published studies that weigh up the merits and caveats of multiple sampling gears typically do not report explicit cost estimates, thereby undermining their potential to match research and management needs. This scoping report provides the basic framework for a subsequent comparative synthesis report aimed at critically appraising a range of pelagic sampling platforms, particularly with respect to their suitability for supporting the long-term monitoring of the national Commonwealth Marine Reserve (CMR) network within the Australian marine estate. It is an output from the National Environmental Science Programme (NESP) expanded Project D2 (‘Standard Operating Procedures for survey design, condition assessment and trend detection’), and is complemented by a similar report focused on benthic sampling techniques.

Sensitivity of fine-scale species distribution models to locational uncertainty in occurrence data across multiple sample sizes - Mitchell, Peter J.; Jacquomo Monk; Laurenson, Laurie (Methods in Ecology and Evolution, 2017)
Species distribution models are increasingly being used by conservation practitioners to provide information on the distribution of organisms. Such models require the accurate co-location of occurrence data with environmental variables. A common assumption is that species occurrence data are accurately georeferenced, which is unverified. This study investigates whether locational uncertainty and sample size affect the performance and interpretation of fine-scale species distribution models in the marine environment. Results suggest that seemingly high-performing fine-scale models can be generated from data containing locational uncertainty, although interpreting their predictions can be misleading if the predictions are interpreted at scales similar to the spatial errors. This study demonstrates the need to consider predictions across geographic space rather than performance alone.
Keywords: georeferencing error; kelp; model performance; Multibeam sonar; occurrence data accuracy

Social preferences for the design of biodiversity offsets for shorebirds in Australia - Abbie A Rogers; Michael P. Burton (Conservation Biology, 2017)
Understanding the social acceptability of biodiversity offsets is important to the design of offset policy. We used a discrete choice experiment to quantify preferences of Australians for a migratory shorebird offset in the context of an oil and gas development project. We surveyed a nationally representative sample of 1371 respondents on their preferences for current and prospective offset-policy characteristics via an online questionnaire to inform policy design of the social dimensions related to offset acceptability. The majority of respondents accepted offsetting as a means to allow economic development; the option to reject development (and an offset) was selected in 13% of possible offset scenarios. Substituting protection of a species affected by the development with protection of a more endangered species was a desirable policy characteristic, as was having the offset implemented by a third party or the government rather than the company responsible for the development. Direct offset activities (e.g., improving degraded habitat) were preferred over indirect activities (e.g., a research program), and respondents were strongly against locating the offset at a site other than where the impact occurred. Positive and negative characteristics of offsets could be traded off by changing the number of birds protected by the offset. Our results show that Australians are likely to support increased flexibility in biodiversity-offset policies, particularly when undesirable policy characteristics are compensated for.
Keywords: choice experiment; community acceptance; migratory shorebirds; nonmarket valuation; offset policy

Spatial and temporal patterns in sea snake populations on the North West Shelf - Progress Report - Vinay Udyawer; Michelle R. Heupel (2017)
This progress report provides details on fieldwork and analyses conducted for NESP Project A8 ‘Exploring the status of Western Australia’s sea snakes’ between the period of May 2017 – December 2017. Snorkel, research trawl and baited remote underwater video station (BRUVS) surveys were conducted by Hub researchers and collaborators between May and October 2017 that were combined with existing datasets to update occurrence records and conduct spatial and time-series analyses. Data from BRUVS were used to assess sea snake assemblages in multiple locations within Australian Marine Parks (AMPs) and in locations where repeated sampling was conducted to construct species distribution models (SDMs) for all sea snake sightings and three priority species (Aipysurus apraefrontalis, A. foliosquama and A. fuscus).
Keywords: Australian Marine Parks; BRUVs; sea snakes; Species distribution models

Spatially balanced designs that incorporate legacy sites - Scott D Foster; G.R. Hosack; E Lawrence; Rachel Przeslawski; Paul Hedge; M Julian Caley; Neville Barrett; Williams, Alan; Jin Li; T P Lynch; Jeffrey M Dambacher; H Sweatman; et al. (Methods in Ecology and Evolution, 2017)
A robust scientific conclusion is the result of a rigorous scientific process. In observational ecology, this process involves making inferences about a population from a sample. The sample is crucial, and is the result of implementing a survey design. A good survey design ensures that the data from the survey are capable of answering the research question. Better designs, such as spatially balanced designs, will also be as precise as possible given the constraints of the budget. Many study areas will have previously sampled ‘legacy sites’ that already have accumulated a time series of observations. For estimating trent, it is often beneficial to include these sites within a new survey. In this paper, we propose a method to incorporate the locations of legacy sites into new spatially balanced survey designs to ensure spatial balance among all sample locations. Simulation experiments indicate that incorporating the spatial location of legacy sites increases spatial balance and decreases uncertainty in inferences (smaller standard errors in mean estimates) when compared to designs that ignore legacy site locations. We illustrate the process of incorporating legacy sites using a proposed survey of a large marine reserve in South-Eastern Australia, although the method is applicable to all environments. Our approach allows for integration of legacy sites into a new spatially balanced design, increasing efficiency. Scientists, managers and funders alike will benefit from this methodology – it provides a tool to provide efficient survey designs around established ones, including in-the-field adjustments. In this way, it can aid integrated monitoring programmes. An R-package that implements these methods, called MBHdesign, is available from CRAN.
Keywords: balanced accept ance sampling; environment al samp ling; quasi-random; spatial bal ance; Survey design; unequal probability sample

Species Overview: Largetooth Sawfish Pristis pristis - PM Kyne; Richard D. Pillans (2017)
Under NESP Marine Biodiversity Hub Project A1 Northern Australian hotspots for the recovery of threatened euryhaline species, the Euryhaline Shark & Ray Working Group met in Brisbane on 21 February 2017 (Attachment 1). Actions arising from that Working Group included the preparation of a briefing document on the current status and future research and management needs of the EPBC-listed Largetooth Sawfish Pristis pristis. This document provides a review of knowledge gained from NERP and NESP Marine Biodiversity Hub projects and an overview of discussions on this species from that Working Group.
Keywords: emerging issues; EPBC; Euryhaline species; Sawfish; threatened species

Sustainability of threatened species displayed in public aquaria, with a case study of Australian sharks and rays - Kathryn A. Buckley; Crook, David A.; Richard D. Pillans; Smith, Liam; PM Kyne (Reviews in Fish Biology and Fisheries, 2017)
Zoos and public aquaria exhibit numerous threatened species globally, and in the modern context of these institutions as conservation hubs, it is crucial that displays are ecologically sustainable. Elasmobranchs (sharks and rays) are of particular conservation concern and a higher proportion of threatened species are exhibited than any other assessed vertebrate group. Many of these lack sustainable captive populations, so comprehensive assessments of sustainability may be needed to support the management of future harvests and safeguard wild populations. We propose an approach to identify species that require an assessment of sustainability. Species at risk of extinction in the wild were considered to be those assessed as threatened (CR, EN or VU) on the IUCN Red List of Threatened Species, or data deficient species that may be at an elevated risk of extinction due to life history traits and habitat associations. We defined sustainable captive populations as self-maintaining, or from a source population that can sustain harvest levels without risk of population declines below sustainable levels. The captive breeding and wild harvest records of at risk species displayed by Australian aquaria were examined as a case study. Two species, largetooth sawfish Pristis pristis and grey nurse shark Carcharias taurus, were found to have unsustainable captive populations and were identified as high priorities for comprehensive sustainability assessments. This review highlights the need for changes in permitting practices and zoo and aquarium record management systems to improve conservation outcomes for captive elasmobranchs. Media Release - Research informs wild harvests for aquarium displays - Charles Darwin University, Thursday 16 November 2017

A taxonomic revision of Anthothela (Octocorallia: Scleraxonia: Anthothelidae) and related genera, with the addition of new taxa, using morphological and molecular data - Kirrily Moore; Alderslade, Philip; Karen J Miller (Zootaxa, 2017)
A complete taxonomic revision of the genus Anthothela (Anthothelidae) and closely related taxa is presented herein, based on original type material of nominal species and additional specimens from multiple deep-water surveys. A multi-disciplinary approach was used, combining morphological characteristics such as colonial branching patterns, polyp structure, and sclerite form and arrangement, together with phylogenetic reconstructions using two mitochondrial gene regions (mtMutS and igr1–cox1). The genus Anthothela, with seven nominal species globally, is here divided into four genera, two of which are new. Three of the original species of Anthothela are validated (A. grandiflora Sars, 1856, A. pacifica Kükenthal, 1913 and A. tropicalis Bayer, 1961), Spongioderma (?) vickersi Benham, 1928 is reassigned to Anthothela and two new species, A. aldersladei and A. quattriniae, are described. Anthothela argentea Studer, 1894, A. macrocalyx (Nutting, 1911) and A. nuttingi Bayer, 1956 are reassigned to Victorgorgia López-González & Briand, 2002 and two new species of this genus, V. eminens and V. nyahae are described. A new family, Victorgorgiidae is described for Victorgorgia due to clear morphological and genetic differences from Anthothela, the type genus of Anthothelidae. A new genus, Williamsium (Anthothelidae), is described for A. parviflora Thomson, 1916 which is restricted to South African waters. A number of North Atlantic Ocean specimens that have traditionally been mistaken for Anthothela grandiflora were found to be synonymous with Alcyonium grandiflorum (Tixier-Durivault & d'Hondt, 1974) and a second new genus, Lateothela (Anthothelidae), is erected for these specimens based on morphological and molecular evidence that Alcyonium grandiflorum was incorrectly placed in the genus Alcyonium Linnaeus. There is good congruence between morphological characteristics and molecular data at a generic level but at a species level, the degree of congruence was inconclusive as morphological and genetic variation is very low. Anthothela and Lateothela n. gen. are found to be closely related to some nominal Alcyonium species, and the family Anthothelidae and subfamily Anthothelinae are shown to be paraphyletic. These are the first records of Anthothela and Victorgorgia from Australian waters.
Keywords: Alcyonacea; Cnidaria; Coelenterata; Deep-sea; gorgonian; octocoral; soft coral; Southern Ocean

Theme D Project showcase and future research prioritisation workshop report - Neville Barrett; Brendan P Brooke; Z Huang; Karen J Miller; Scott L Nichol; Scott D Foster; Rachel Przeslawski; Vanessa L Lucieer; Tim O'Hara (2017)
The NESP Marine Biodiversity Hub held a two day workshop in Hobart on 27-28th March 2017 to showcase work undertaken so far in Theme D since the beginning of the Hub, outline future proposed work within the theme, and work with key stakeholders to align research with management needs. All four of the Themes four projects are designed to be closely integrated with management needs and with each other, to provide the required knowledge to manage and monitor the Commonwealth Marine Reserve (CMR) network. Feedback from the workshop participants (including a significant Parks Australia representation) indicated that the work was indeed closely aligned with information needs, and that work to data, as well as proposed future work, was progressing along lines that met management expectations. Discussions on day 1 included overviews of linked data visualisation products developed outside the Hub (e.g. SeaMap Australia and FishMap) that build on Hub research to further meet information needs. An overview of Marine Protected Areas (MPA) science and management links within NSW was informative in evaluating how a mature science program can meet management needs. Likewise, an overview of the Reef Integrated Monitoring and Reporting Program (RIMREP) developed by the Great Barrier Reef Marine Park Authority (GBRMPA) was informative of how mature monitoring programs can be evaluated and integrated into the adaptive management process. This initiated discussion on the need to develop a similar process for the CMR network, albeit one at a much earlier stage in the process of management and monitoring than that in the GBR. Day 2 of the workshop focussed on refining plans for the D1 and D3 projects within the Theme. This was guided by presentations from Parks Australia (PA) on research priorities, including those for CMR surveys as well as data visualisation tools such as a CMR eAtlas. The extensive discussions that followed assisted in the restructuring of D1 and D3 programs to best meet the needs of Parks Australia and the wider Department of the Environment and Energy (DOEE). As PA are now funding the development of the CMR eAtlas, D1 discussions focussed on how to best deliver the information required by the atlas, rather than developing an atlas itself. This discussion was informed significantly by a list of research and information priorities supplied by PA. For D3, discussions around prioritisation of future surveys focussed on a framework of key drivers, including a nationally consistent approach using Standard Operating Procedures (SOP), integration with management needs and national programs, and meeting priorities identified by Parks Australia. Hub partners will now take these guidelines to develop a package of potential surveys to be supported by the Hub and undertaken over the 2018-20 period, with decisions on survey priorities to be made by the Hub leadership.
Keywords: CMR; NESP; planning; Theme D; Workshop

Thermal limits to the geographic distributions of shallow-water marine species - Rick D Stuart-Smith; Graham J. Edgar; Amanda E. Bates (Nature Ecology & Evolution, 2017)
Temperature profoundly affects species’ geographic ranges, but the extent to which it limits contemporary range edges has been difficult to assess from laboratory experiments of thermal tolerance. The persistence of populations depends on temperature-mediated outcomes of ecological and demographic processes across all stages of a species’ life history, as well as any adaptation to local temperature regimes. We assessed the relationships between sea temperature and observed distributional ranges for 1,790 shallow-water marine species from 10 animal classes and found remarkable consistencies in trends in realized thermal limits among taxa and ocean basins, as well as general agreement with previous laboratory findings. Realized thermal niches increase from the Equator towards cold–temperate locations, despite an opposite trend in geographic range size. Species’ cool distribution limits are best predicted by the magnitude of seasonality within their range, while a relatively firm thermal barrier exists on the equatorward range edge for temperate species. Our findings of consistencies in realized thermal limits indicate potential limits to adaptation among common marine species and highlight the value of realized thermal niches for predicting species’ distributional dynamics in warming seas.
Keywords: Biodiversity; Ecophysiology; Macroecology

Towards a value based approach to cumulative risk and impact analysis - Piers K Dunstan (2017)
Understanding the pressures and impacts on Australia’s marine environment is critical to effective biodiversity conservation and sustainable resource use. The marine environment in Australia is influenced by a wide range of different pressures that impact on different parts of the marine ecosystem in different ways. Managers, regulators and proponents are grappling to provide practical approaches that can effectively assess the cumulative risks and impacts to ecosystems. Such approaches must be able to respond to a diversity of uses and provide: an understanding of the state and trends of shared values of the marine environment, an understanding of the state and trends of the pressures and uses acting on values and options for assessing cumulative risks to environmental values that can accommodate a range of spatial and data contexts. Practical and repeatable guidance for how to conduct an assessment of cumulative risk and impact The NESP Marine Biodiversity Hub has been progressing research to establish understanding in first three of requirements to support Australia’s marine managers, regulators and proponents by providing. This document provides a snapshot of our progress to delivering on these requirements.
Keywords: cumulative impact; pressure; values

Towards quantitative condition assessment of biodiversity outcomes: Insights from Australian marine protected areas - P F E Addison; Flander, Louisa B.; Cook, Carly N. (Journal of Environmental Management, 2017)
Protected area management effectiveness (PAME) evaluation is increasingly undertaken to evaluate governance, assess conservation outcomes and inform evidence-based management of protected areas (PAs). Within PAME, quantitative approaches to assess biodiversity outcomes are now emerging, where biological monitoring data are directly assessed against quantitative (numerically defined) condition categories (termed quantitative condition assessments). However, more commonly qualitative condition assessments are employed in PAME, which use descriptive condition categories and are evaluated largely with expert judgement that can be subject to a range of biases, such as linguistic uncertainty and overconfidence. Despite the benefits of increased transparency and repeatability of evaluations, quantitative condition assessments are rarely used in PAME. To understand why, we interviewed practitioners from all Australian marine protected area (MPA) networks, which have access to long-term biological monitoring data and are developing or conducting PAME evaluations. Our research revealed that there is a desire within management agencies to implement quantitative condition assessment of biodiversity outcomes in Australian MPAs. However, practitioners report many challenges in transitioning from undertaking qualitative to quantitative condition assessments of biodiversity outcomes, which are hampering progress. Challenges include a lack of agency capacity (staff numbers and money), knowledge gaps, and diminishing public and political support for PAs. We point to opportunities to target strategies that will assist agencies overcome these challenges, including new decision support tools, approaches to better finance conservation efforts, and to promote more management relevant science. While a single solution is unlikely to achieve full evidence-based conservation, we suggest ways for agencies to target strategies and advance PAME evaluations toward best practice.
Keywords: Conservation; Evidence-based management; long term monitoring; protected area management effectiveness evaluation; reporting

Translating local benthic community structure to national biogenic reef habitat types - Cresswell, Anna K.; Graham J. Edgar; Rick D Stuart-Smith; Russell J. Thomson; Neville Barrett; Craig R. Johnson (Global Ecology and Biogeography, 2017)
Aim Marine reef habitats are typically defined subjectively. We provide a continental-scale assessment of dominant reef habitats through analysis of macroalgae and sessile animal taxa at sites distributed around Australia. Relationships between reef habitats and environmental and anthropogenic factors are assessed, and potential changes in the future distribution and persistence of habitats are considered. Location Shallow rocky and coral reefs around the Australian coast. Methods Cover of 38 sessile biota functional groups was recorded in diver-based surveys using quadrats at 1,299 sites. Classification analyses based on the functional groups were used to identify an unambiguous set of ‘biogenic habitat types’. Random forest and distance-based linear modelling were used to investigate correlations between these habitats and environmental and anthropogenic variables. Results Cluster analyses revealed tropical and temperate ‘realms’ in benthic substratum composition, each with finer-scale habitats: four for the temperate realm (canopy algae, barren, epiphytic algae–understorey and turf) and five for the tropical realm (coral, coral–bacterial mat, turf–coral, calcified algae–coral and foliose algae). Habitats were correlated with different sets of environmental and anthropogenic conditions, with key associations in the temperate realm between mean sea temperature and canopy-forming algae (negative) and barren habitat (positive). Variation in sea temperature was also an important correlate in the tropical realm. Main conclusions Quantitative delineation of inshore reef habitats at a continental scale identifies many of the same habitat types traditionally recognized through subjective methods. Importantly, many biogenic reef habitats were closely related to environmental parameters and anthropogenic variables that are predicted to change. Consequently, habitats have differing likelihood of persistence. Structurally complex habitats in the temperate realm are at greater risk than more ‘two-dimensional’ habitats (e.g., canopy-forming versus turfing algae). In the tropical realm, offshore and coastal habitats differed greatly, highlighting the importance of large-scale oceanic conditions in shaping biogenic structure.
Keywords: Australia; Biogeography; climate change; habitat type; Macroecology; marine management

Ubiquity of microplastics in coastal seafloor sediments - Ling, S.D.; Sinclair, M.; Levi, C.J.; Reeves, S.E.; Graham J. Edgar (Marine Pollution Bulletin, 2017)
Microplastic pollutants occur in marine environments globally, however estimates of seafloor concentrations are rare. Here we apply a novel method to quantify size-graded (0.038–4.0 mm diam.) concentrations of plastics in marine sediments from 42 coastal and estuarine sites spanning pollution gradients across south-eastern Australia. Acid digestion/density separation revealed 9552 individual microplastics from 2.84 l of sediment across all samples; equating to a regional average of 3.4 microplastics·ml− 1 sediment. Microplastics occurred as filaments (84% of total) and particle forms (16% of total). Positive correlations between microplastic filaments and wave exposure, and microplastic particles with finer sediments, indicate hydrological/sediment-matrix properties are important for deposition/retention. Contrary to expectations, positive relationships were not evident between microplastics and other pollutants (heavy metals/sewage), nor were negative relationships with neighbouring reef biota detected. Rather, microplastics were ubiquitous across sampling sites. Positive associations with some faunal-elements (i.e. invertebrate species richness) nevertheless suggest high potential for microplastic ingestion.
Keywords: estuary; Heavy metals; Marine plastic; Pollution; Reef; Sewage

Underpinning the repair and conservation of Australia’s threatened coastal-marine habitats: Shellfish restoration research - Mid-project update - Ian M. McLeod; Chris L Gillies; Colin Creighton (2017)
Shellfish reef ecosystems were historically overfished to near extinction and their natural recovery is inhibited by a loss of suitable substrate and recruitment. Active repair is therefore required and efforts have begun with the promise of significant benefits. These projects (and future efforts), however, require a detailed understanding of the ecology and benefits to develop appropriate repair methods and to set targets based on natural reference conditions. This research is focused on the reef-forming shellfish complex dominated by the Sydney rock oyster (Saccostrea glomerata) dominated reefs, which, of the eight known reef-forming species documented in Gillies et al. (2015), are, along with Ostrea angasi (native flat oyster) the most imperilled and have the highest restoration potential. This work will directly support and underpin the management and restoration objectives of existing shellfish reef repair projects and will assist future projects and management decision-making by developing appropriate methods and setting of repair targets based on natural reference conditions. This work will also quantify some of the benefits of shellfish reefs to inform the business case for shellfish restoration in Australia being developed as part of this project.
Keywords: coastal; fishery; oyster; restoration; shellfish

Warriewood Monitoring Summary - John Gemmill (2017)
Samples of water were collected by surfers at Warriewood and Turimetta Beaches (north and south of the Warriewood outfall) in North Sydney, on three occasions in the surf zone by members of Surfrider as part of citizen science research conducted for the National Outfall Database. The intention of the pilot survey was to determine if variations in water quality caused by a known outfall could be scientifically detected by recreational water users/citizen scientists. Beaches either side of the Warriewood outfall, North Sydney, were selected for monitoring due to: Existing concerns acknowledged by two stakeholders Sydney Water and Surfrider An existing notification system for by-pass events making potential changes in water quality to easier to detect. Warriewood beach having no other major source of local runoff contributing to contamination (ie. stormwater outfalls, creeks etc.)
Keywords: aquatic; citizen science; coastal; environment; sewerage

Analysing uncertainty in multibeam bathymetry data and the impact on derived seafloor attributes - Vanessa L Lucieer; Z Huang; Justy P W Siwabessy (Marine Geodesy, 2016)
Multibeam bathymetric data provides critical information for the modelling of seabed geology and benthic biodiversity. The accuracy of these models is dependent on the accuracy of the bathymetric data which contains uncertainties that are stochastic at individual soundings but exhibit a distinct spatial distribution with increasing magnitude from nadir to the outer beams. A restricted spatial randomness method which simulates both the stochastic and spatial characteristics of the data uncertainty performed better than a complete spatial randomness method in analysing the impact of bathymetric data uncertainty on derived seafloor attributes.

Analysis of Approaches for Monitoring Biodiversity in Commonwealth Waters - Field work report - Althaus, Franziska; Neville Barrett; Jeffrey M Dambacher; P Davies; Renata Ferrari; Jessica H. Ford; Keith R Hayes; Nicole A. Hill; G.R. Hosack; Renae Hovey; Z Huang; J Hulls; et al. (2016)
The overall objective of this project was to contribute to a blue-print for a sustained national environmental monitoring strategy for monitoring biodiversity in the Commonwealth Marine Areas. The approach would apply to Key Ecological Features (KEFs) and the Commonwealth Marine Reserve (CMR) Network, focusing initially on the Southeast Marine Region. CMRs and KEFs are large, remote and poorly known, so this project focussed on identifying flexible, statistically robust approaches to survey design and data collection that could result in comprehensive descriptions of the surveyed area and at the same time provide a statistical baseline for future repeat surveys in the same area. Given the conservation status and values of these areas, non-destructive sampling tools were prioritized, including remote sensing using acoustics (e.g. multibeam) that provide information on seafloor characteristics (bathymetry, hardness and texture), and direct observation using video and camera stills, taken by towed units, autonomous units or baited units. The final report is of necessity highly technical, reporting on the design and analytical issues addressed by this project. This executive summary is designed to provide an overview of the project and highlight the key findings relevant to policy makers and managers, omitting most of the technical detail. Readers interested in technical detail are referred to the main body of this report or the many research papers resulting from this work that are listed at the end of this summary. Three field programs were undertaken. The largest survey was for the Flinders Commonwealth Marine Reserve (CMR) located offshore, northeast of Tasmania. This provided a baseline of the continental shelf, in the multiple use zone of this reserve, on which future monitoring can be built, and provides an initial characterization of the upper slope areas in the same zone of this CMR. A smaller survey targeted at known shelf reefs features in the Solitary Islands Marine Park (SIMP) and Solitary Islands Marine Reserve (SIMR) was designed to address specific sampling issues including: extending State-based research to this Commonwealth KEF, comparing autonomous and towed platforms for capturing video imagery, and examining statistical issues associated with the use of baited underwater remote videos (BRUVs). The third survey in the KEF east of the Houtman-Abrolhos islands was an exploratory survey designed to identify whether coral-kelp and other shelf reef communities in the State MPA extended into this KEF, and explore whether seabird diet could be used as a reliable indicator of pelagic ecosystem health.

Application of NERP Biodiversity Hub survey methodology to Geographe Commonwealth Marine Reserve - E Lawrence; Renae Hovey; Gary A. Kendrick; Keith R Hayes (2016)
This report provides a summary of the design and analysis of the survey undertaken in Geographe Commonwealth Marine Reserve (CMR) from December 2014 to May 2015. The report summarises data collected by previous field studies in Geographe Bay on the distribution and characteristics of key habitat types (seagrasses, corals, rocky reefs and soft sediments), and the benthic invertebrate and vertebrate communities associated with them. This information was taken into consideration when developing the survey objectives and methodology. The survey design applies some of the techniques developed by Theme 1 (Monitoring and Report) of the Marine Biodiversity Hub, funded by the Australian Government’s National Environmental Research Program.

Biodiversity enhances reef fish biomass and resistance to climate change - Duffy, J. Emmett; Lefcheck, Jonathan S.; Rick D Stuart-Smith; Navarrete, Sergio A.; Graham J. Edgar (Proceedings of the National Academy of Sciences, 2016)
Fishes are the most diverse group of vertebrates, play key functional roles in aquatic ecosystems, and provide protein for a billion people, especially in the developing world. Those functions are compromised by mounting pressures on marine biodiversity and ecosystems. Because of its economic and food value, fish biomass production provides an unusually direct link from biodiversity to critical ecosystem services. We used the Reef Life Survey’s global database of 4,556 standardized fish surveys to test the importance of biodiversity to fish production relative to 25 environmental drivers. Temperature, biodiversity, and human influence together explained 47% of the global variation in reef fish biomass among sites. Fish species richness and functional diversity were among the strongest predictors of fish biomass, particularly for the large-bodied species and carnivores preferred by fishers, and these biodiversity effects were robust to potentially confounding influences of sample abundance, scale, and environmental correlations. Warmer temperatures increased biomass directly, presumably by raising metabolism, and indirectly by increasing diversity, whereas temperature variability reduced biomass. Importantly, diversity and climate interact, with biomass of diverse communities less affected by rising and variable temperatures than species-poor communities. Biodiversity thus buffers global fish biomass from climate change, and conservation of marine biodiversity can stabilize fish production in a changing ocean.
Keywords: fisheries; functional diversity; global change; Macroecology; structural equation model

Bright spots among the world’s coral reefs - Cinner, Joshua E.; Huchery, Cindy; Aaron M MacNeil; Graham, Nicholas A.J.; McClanahan, Tim R.; Maina, Joseph; Maire, Eva; Kittinger, John N.; Hicks, Christina C.; Mora, Camilo; Allison, Edward H.; D’Agata, Stephanie; et al. (Nature, 2016)
Ongoing declines in the structure and function of the world’s coral reefs require novel approaches to sustain these ecosystems and the millions of people who depend on them. A presently unexplored approach that draws on theory and practice in human health and rural development is to systematically identify and learn from the ‘outliers’—places where ecosystems are substantially better (‘bright spots’) or worse (‘dark spots’) than expected, given the environmental conditions and socioeconomic drivers they are exposed to. Here we compile data from more than 2,500 reefs worldwide and develop a Bayesian hierarchical model to generate expectations of how standing stocks of reef fish biomass are related to 18 socioeconomic drivers and environmental conditions. We identify 15 bright spots and 35 dark spots among our global survey of coral reefs, defined as sites that have biomass levels more than two standard deviations from expectations. Importantly, bright spots are not simply comprised of remote areas with low fishing pressure; they include localities where human populations and use of ecosystem resources is high, potentially providing insights into how communities have successfully confronted strong drivers of change. Conversely, dark spots are not necessarily the sites with the lowest absolute biomass and even include some remote, uninhabited locations often considered near pristine. We surveyed local experts about social, institutional, and environmental conditions at these sites to reveal that bright spots are characterized by strong sociocultural institutions such as customary taboos and marine tenure, high levels of local engagement in management, high dependence on marine resources, and beneficial environmental conditions such as deep-water refuges. Alternatively, dark spots are characterized by intensive capture and storage technology and a recent history of environmental shocks. Our results suggest that investments in strengthening fisheries governance, particularly aspects such as participation and property rights, could facilitate innovative conservation actions that help communities defy expectations of global reef degradation.

Close-Kin Mark-Recapture - Mark Bravington; Skaug, Hans J.; Anderson, Eric C. (Statistical Science, 2016)
Mark-recapture (MR) methods are commonly used to study wildlife populations. Taking advantage of modern genetics one can generalize from “recapture of self” to “recapture of closely-related kin”. Abundance and other demographic parameters of adults can then be estimated using, if necessary, only samples from dead animals (live-release is optional). This greatly widens the scope of MR, e.g. to commercial fisheries where large-scale tagging is impractical, and enhances the power of conventional MR studies where live release and tissue sampling is possible. We give explicit formulae for kinship (i.e., recapture) probabilities in general and specific cases. These yield a pseudo-likelihood based on pairwise comparisons of individuals in the samples. It is shown that the pseudo-likelihood approximates the full likelihood under sparse sampling of large populations. Experimental design is addressed via the principle of maximizing the Fisher information for parameters of interest. Finally, we discuss challenges related to kinship determination from genetic data, focusing on current limitations and future possibilities.
Keywords: Demography; genetics; kinship; mark-recapture; pseudo-likelihood

Coastal change detection tools utilising 28 years of Earth Observation data in the Australian Geoscience Data Cube (AGDC) - S Sagar; Tan, Peter; Roberts, Dale A. (2016)
The ability to detect, measure and monitor change in coastal and marine environments can assist in both informing management decision processes and evaluating the results of management interventions. Change detection utilising satellite data requires robust time-series data at temporal and spatial scales that can provide context for meaningful interpretations of coastal and marine ecosystem processes. Previously, this analysis has employed time consuming methods that hampered the efficient extraction of key information on environmental change and trends. The recently developed Australian Geoscience Data Cube (AGDC) provides a quantum step forward in our ability to utilise satellite data for environmental monitoring. The AGDC provides a platform for efficient processing and analysis of these data, enabling quantitative information to be extracted from the full 28-year time series of the Landsat data archive. Also, this approach can be applied to a wide range of current and future satellite data streams (e.g. Sentinel series of satellites) to provide rapid, robust environmental monitoring. We have developed a flexible diagnostic change detection tool, able to extract change events from classified variables derived from 28 years of Landsat data in the AGDC. In this report we describe how we apply the algorithm to a water detection problem, and show the broadscale application using examples of coastal change and estuarine drying events in Moreton Bay and the Murray Mouth and Lower Lakes. We also introduce tools which can then be used for further analysis of the detected change events. The algorithm is flexible enough to be applied to a range of variables in the coastal zone, and we discuss further applications and potential future linkages to extend this work for the examination of important ecological communities.

Collation of existing shelf reef mapping data and gap identification - Phase 1 Final Report Shelf reef key ecological features - Vanessa L Lucieer; R. Porter-Smith; Scott L Nichol; Jacquomo Monk; Neville Barrett (2016)
This report details the collation of all of the existing Australian continental shelf mapping data, methods used for reef habitat mapping and classification, and documentation of the spatial data products. It presents summary statistics of the distribution and extent of mapping surveys conducted on the continental shelf. The collation of these data has generated a valuable understanding of the distribution and extent of this key habitat around Australia, as well as a quantitative description of the current extent, nature and spatial location of mapping programs in shelf waters. The latter component both informs our understanding of the significant gaps in our current knowledge, and provides ready access to existing mapping data from which more detailed local scale maps can be generated from individual QGIS files will can be downloaded from the Australian Online Data Network (AODN). The project has made significant inroads towards building collaboration across agencies to share habitat mapping data for the public good, as well as furthering discussions on mechanisms to making data more widely available. We have made a number of recommendations in this report relating to the need for data standards, central data storage, and tools for data visualisation. All of these recommendations are readily achievable, and discussions are progressing on all fronts, including visualisation of much of the data collated through this project by the AODN via its SeaMap Australia project (in development). Successful adoption of the recommendations will significantly enhance the planning process for future surveys across all jurisdictions and management needs, as well as the uptake of such information into future spatial management. Critically, if the CMR network is to form the backbone of a national integrated monitoring program that includes shelf waters, these processes, and the information generated by appropriately targeted surveys, are going to be essential to underpin planning of biological surveys to ensure they are regionally relevant and representative of important habitat features.

Communications Plan - Paul Hedge (2016)
This plan outlines communication objectives and approaches for the Hub, and highlights actions intended to build communication capacity and effectiveness. It provides the foundation for a shared understanding among Hub research partners, researchers and their research-users and stakeholders including the Department of the Environment. Version 1.1

Community acceptance of biodiversity offsets: evidence from a choice experiment - Burton, Michael; Abbie A Rogers; Richert, Claire (Australian Journal of Agricultural and Resource Economics, 2016)
This study of the community's acceptance of biodiversity offsets in Australia provides insights relevant to future revisions of offset policies of both State and Commonwealth Governments. A choice experiment was used to measure preferences for the general acceptability of offsetting, and for a number of attributes that define how an offset can be implemented. Based on a sample of 204 respondents from Perth, WA, we found that the majority of respondents did not object to the practice of biodiversity offsetting in general. A minority of respondents preferred that offset actions be direct, but most accepted a combination of direct and indirect actions. Individuals generally preferred that the offset be located near the site of impact, and it became more unacceptable the further away that it was located. However, there was heterogeneity in preferences for protecting the impacted species or a more endangered one.
Keywords: Biodiversity offsets; choice experiment; migratory birds

Comparison of fin and muscle tissues for analysis of signature fatty acids in tropical euryhaline sharks - Every, Sharon L.; Pethybridge, Heidi R.; Crook, David A.; PM Kyne; Christopher J. Fulton (Journal of Experimental Marine Biology and Ecology, 2016)
Fatty acid (FA) analysis can provide an effective, non-lethal method of elucidating the trophic ecology of fish. One method utilised in the field is to collect biopsied muscle tissue, but this can be problematic in live sharks due to a thick dermal layer with extensive connective tissue. The aim of this research was to determine whether fin and muscle tissue yield similar FA profiles in three species of tropical euryhaline sharks: Carcharhinus leucas, Glyphis garricki and Glyphis glyphis. Fatty acid profiles were detectable in fin clips as small as 20 mg (~ 5 mm × 6 mm) and muscle biopsies > 10 mg mass. Overall profiles in relative (%) FA composition varied significantly between fin and muscle tissues for C. leucas and G. garricki (global R-values = 0.204 and 0.195, P < 0.01), but not G. glyphis (global R-value = 0.063, P = 0.257). The main FAs that contributed to these differences were largely 18:0 for C. leucas, 20:4 ω6 for G. garricki and 20:5 ω3 for G. glyphis, which reflect the different physiological functions and turnover rates of the two tissues. Notably, no significant differences were detected between tissue types for the major classes of FAs and abundant dietary essential FAs. It was concluded that FA profiles from either fin clips or muscle tissue may be used to examine the trophic ecology of these tropical euryhaline sharks when focusing on dietary essential FAs. Given that some non-essential FAs were different, caution should be applied when comparing FA profiles across different tissue types.
Keywords: Biochemical tracers; Carcharhinus; Elasmobranchs; Glyphis; Trophic ecology

Data Management Framework - Flukes, Emma; Paul Hedge (2016)
It is imperative that Marine Biodiversity Hub research outputs are made freely available to Government, the science community, and to the public. Providing easy access to the Hub’s research outputs (data sets, reports, journal articles, maps etc.) is an important step on the pathway to impact and achieving outcomes.  The Hub is also contractually obligated to make its information outputs available to the public. The administrator of the NESP, the Department of the Environment, has also published the NESP Data and Accessibility Guidelines to clarify its expectations and provide guidance for meeting contractual obligations. The Hub has two separate mechanisms to provide access to its research outputs.  The first mechanism is the Hub’s website, which is used to provide access to reports, papers, and other written information. The second is the Australian Ocean Data Network (AODN), which is the aggregation point for all spatial and non-spatial Hub data which can include maps, video, images, and models. Hub data must be accompanied by a descriptive metadata record which links to the data access (download) point, and is published in a catalogue harvested by the AODN. The Hub has appointed a Data Manager role to assist with making Hub research data outputs available to the public. The Data Manager is responsible for implementing and refining this framework document, supporting researchers to publish their data, and overseeing quality control of published Hub data outputs. Compliance with this data management framework enables the Hub to take a systematic and standards-based approach to identifying, cataloguing, packaging, and presenting its research outputs to stakeholders and the public.

Deep-sea diversity patterns are shaped by energy availability - Skipton N. C. Woolley; Tittensor, Derek P.; Piers K Dunstan; Guillera-Arroita, Gurutzeta; Lahoz-Monfort, J.; Wintle, Brendan A.; Worm, Boris; Tim O'Hara (Nature, 2016)
The deep ocean is the largest and least-explored ecosystem on Earth, and a uniquely energy-poor environment. The distribution, drivers and origins of deep-sea biodiversity remain unknown at global scales1–3. Here we analyse a database of more than 165,000 distribution records of Ophiuroidea (brittle stars), a dominant component of sea-floor fauna, and find patterns of biodiversity unlike known terrestrial or coastal marine realms. Both patterns and environmental predictors of deep-sea (2,000–6,500 m) species richness fundamentally differ from those found in coastal (0–20 m), continental shelf (20–200 m), and upper-slope (200–2,000 m) waters. Continental shelf to upper-slope richness consistently peaks in tropical Indo-west Pacific and Caribbean (0–30°) latitudes, and is well explained by variations in water temperature. In contrast, deep-sea species show maximum richness at higher latitudes (30–50°), concentrated in areas of high carbon export flux and regions close to continental margins. We reconcile this structuring of oceanic biodiversity using a species–energy framework, with kinetic energy predicting shallow-water richness, while chemical energy (export productivity) and proximity to slope habitats drive deep-sea diversity. Our findings provide a global baseline for conservation efforts across the sea floor, and demonstrate that deep-sea ecosystems show a biodiversity pattern consistent with ecological theory, despite being different from other planetary-scale habitats.

Dendrogramma is a siphonophore - Tim O'Hara; Andrew F. Hugall; MacIntosh, Hugh; Naughton, Kate M.; Williams, Alan; Adnan Moussalli (Current Biology, 2016)
Dendrogramma was the iconic deep-sea animal of 2014, voted among the top-ten new species described that year. The two species described are mushroom shaped animals, diploblastic, with an apparent gastrovascular system that extends from the base of the stalk to bifurcating canals that radiate through the flat disc . The authors could not assign the new genus to any known animal group with certainty, leading to numerous media reports that it belonged to an entirely new phylum. Here we use phylogenomic data from newly collected specimens to show that Dendrogramma is a cnidarian, specifically a benthic siphonophore in the family Rhodaliidae. Although an entire Dendrogramma colony has not been found, we hypothesise that the mushroom-like bodies are bracts, possibly used to aid buoyancy or as defensive appendages to protect feeding gastrozooids or gonads. "Dendrogramma: A taxonomic mystery solved", Museum Victoria Collections, 2016 "Solved mystery of the deep-sea mushroom just raises new questions", The Conversation, 7 June 2016

Determining the size and trend of the west coast white shark population - Barry Bruce (2016)
This project provides vital prerequisite information required to identify options for estimating white shark abundance and trends in Australia’s western population. It is designed to guide a follow-up project within the National Environmental Science Program (NESP). The current project does not, by itself, provide such an estimate of population size or trends for the west and doing so was specifically identified as being out of the project’s scope, but its goal is to identify a strategy for doing so. The project’s objectives were to see if nursery areas for white sharks could be identified in waters west of Bass Strait, to secure existing tissue samples and to establish an ongoing shark tissue sampling program for future Close-Kin Mark-Recapture based estimates of population size. Finding discrete nursery areas would allow techniques developed in eastern Australia for estimating population size of white sharks to be directly applied to the western population. A lack of defined nursery areas would require a modified approach to achieve this goal.

Ecosystem understanding to support sustainable use, management and monitoring of marine assets in the North and North-west regions - Stakeholder workshop report April 2016 - Rachel Przeslawski; Karen J Miller; Jessica J. Meeuwig (2016)
A stakeholder workshop for NESP Project D1 ‘Ecosystem understanding to support sustainable use, management and monitoring of marine assets in the North and North-west regions’ was held at the University of Western Australia, Perth, on 21 April 2016. The objective of the workshop was to identify stakeholder information needs in the North and North-west regions and use these to guide research activities in Project D1. Stakeholders from State and Local Government departments, Industry, Fisheries, Conservation, and Indigenous groups each explained their priorities and issues in the North and North-west region, after which geographic focus, research scope, and data delivery needs were discussed across the group and prioritised through a post-workshop online survey (30% response rate). From a stakeholder perspective based on the workshop discussion and online survey, the geographic focus of research should be prioritised towards large shelf areas under the highest pressures (e.g. Kimberley and Gascoyne Commonwealth Marine Reserves (CMRs)). In the workshop, stakeholders considered that research in Project D1 should be targeted towards using predictive models to characterise and map benthic habitats and demersal fish species, while the online survey revealed more research effort should be applied to benthic areas compared to pelagic. Common themes were the importance of whole ecosystem processes, pressures, threatened species, CMRs (and associated KEFs and BIAs), and accessibility and communication of information particularly related to industry. There was positive feedback from Stakeholders regarding the Northwest Atlas as a platform for the communication of research outcomes and as a repository for information relevant to management of the regions, with a number of suggestions made for making information more readily searchable within that framework and expanding it to include the North region. Combined outcomes from the D1 Stakeholder Workshop and the earlier D1 Science Workshop will provide direction for future research within Project D1 and contribute to the National Prioritisation workshop with Project D3.

Environmental DNA detects Critically Endangered largetooth sawfish in the wild - Colin Simpfendorfer; PM Kyne; Noble, TH; Goldsbury, J; Basiita, RK; Lindsay, R; Shields, A; Perry, C; Jerry, DR (Endangered Species Research, 2016)
Environmental DNA (eDNA) is a relatively new tool for the detection of rare, threatened and invasive species in water bodies. In this study we investigated the utility of an eDNA approach in detecting the Critically Endangered largetooth sawfish Pristis pristis in freshwater habitats in northern Australia. Water samples were collected from large aquaria mesocosms containing largetooth sawfish and other aquatic species, and floodplain waterholes and the main river channel of the Daly River, Northern Territory. Water samples were filtered using a 20 µm nylon filter. DNA was extracted from filters and analysed with PCR using species-specific mitochondrial cytochrome c oxidase subunit I (COI) primers designed to amplify only largetooth sawfish DNA. PCR products were cleaned and the COI gene sequenced to confirm the species identity. Using 3 aquaria, with one containing a largetooth sawfish, this method positively identified sawfish only in the correct aquarium. In the field water samples, 7 of 8 floodplain waterholes produced a sawfish eDNA PCR product, while eDNA was not detected in the main river channel. Based on gillnet sampling and traditional ecological knowledge, largetooth sawfish were known to occur at half of the waterhole and floodplain sites that tested positive for sawfish eDNA. These results demonstrated that an eDNA approach to detecting largetooth sawfish can produce reliable outcomes and can be used as a survey tool to help with conservation efforts for this and other threatened elasmobranchs.

Exploring the status of Western Australia’s sea snakes - Vinay Udyawer; D'Anastasi, B; McAuley, R; Michelle R. Heupel (2016)
All sea snakes are listed marine species under the EPBC Act and three Australian endemic species are listed as Critically Endangered or Endangered, and as such are a national conservation priority. Recent findings of two Critically Endangered sea snake species (Aipysurus apraefrontalis and Aipysurus foliosquama) in locations outside of their previously defined ranges have highlighted the lack of information on species distributions along the North West coast of Australia. Data on sea snake sightings on previously collected baited remote underwater video surveys (BRUVS) and fisheries independent trawl surveys were used to assess the utility of these methodologies to accurately define relative abundance and distribution patterns of sea snakes in the North West Marine Region (NWMR), including within Commonwealth Marine Reserves (CMRs), to refine species’ status. Presence/absence data from BRUVS were used to predict locations that are likely important habitats for sea snake populations within the NWMR, which included mid-shelf and oceanic shoals along the Kimberley and Pilbara coasts. Limited fisheries-independent trawl sampling data collected in Shark Bay and Exmouth Gulf highlighted patterns of interaction between sea snakes and trawl fishing, with survivorship curves indicating that most sea snake species encountered within these regions may be able to sustain low to moderate levels of trawl fishing. Trawl survey data also highlighted the need for additional fisheries interaction data to accurately assess the species-specific influence of fishing activities (e.g. trawl and trap fishing) on different life stages of sea snakes susceptible to incidental capture (bycatch). This project highlights the need for more data on sea snakes in regions lacking information (e.g. mid-shelf shoals of Kimberley coast, Pilbara coast and Rowley Shoals). In addition, further research is also required to assess the degree of connectivity between sea snake populations from offshore reefs that have seen recent declines, and those on adjacent mid-shelf and oceanic shoals.
Keywords: BRUV; distribution; threatened species

Extinct flagships: linking extinct and threatened species - PM Kyne; Adams, Vanessa M. (Oryx, 2016)
Despite much effort to promote the conservation and recovery of threatened species, the extent of the current list of threatened vertebrates (> 7,600 species) underscores the need to develop novel communication and marketing tools to raise awareness and funding for their conservation. Although flagship species have been widely used in conservation marketing, the flagship role of extinct species has been largely overlooked and the status of lost species is rarely associated with the status of extant species facing a high risk of extinction. Some extinct species (e.g. the dodo Raphus cucullatus and the thylacine Thylacinus cynocephalus) are cultural and commercial icons and therefore familiar, and may appeal to the public as conservation flagships. We propose a wider use of extinct flagships to raise awareness for the conservation of threatened species by making a direct link between already extinct species and extant species at risk of extinction. We present examples of publicly recognized and iconic extinct species that could be used in marketing for the conservation of threatened species. These extinct species are familiar and may be readily linked to threatened species or species groups. We outline a roadmap for testing their appeal under the extinct flagship concept, through market research. If research identifies that a cognitive link is made between the fate of an extinct species (i.e. they went extinct from human causes) and what may happen to threatened species (i.e. they are at risk of extinction from human causes), extinct species may well have a wider role to play as conservation flagships. Cambridge University Press blog item (13 May 2016) http://blog.journals.cambridge.org/2016/05/13/extinct-species-as-conservation-champions/

Forecasting marine invasions under climate change: Biotic interactions and demographic processes matter - Camille Mellin; Lurgi, M.; Matthews, S.; MacNeil, M.A.; M Julian Caley; Nicholas J. Bax; Rachel Przeslawski; D. A. Fordham (Biological Conservation, 2016)
Biological invasions are one of the most significant threats to marine biodiversity, and can be facilitated and amplified by climate change. Among all aspects of invasion biology, biotic interactions between invaders and native species are of particular importance. They strongly influence the invasion velocity as well as species responses to climate-induced stressors. Yet the effects of biotic interactions and other important demographic processes remain overlooked among most studies of climate-mediated invasions. We critically assessed current modelling techniques for forecasting marine invasions under climate change, with a particular focus on their ability to account for important biotic interactions and demographic processes. We show that coupled range dynamics models currently represent the most comprehensive and promising approach for modelling and managing marine invasions under climate change. We show, using the crown-of-thorns seastar (Acanthaster planci), why model architectures that account for biotic interactions and demographic and spatial processes (and their interaction) are required to provide ecologically realistic predictions of the distribution and abundance of invader species, both under present-day conditions and into the future. We suggest potential solutions to inform data-poor situations, such as Bayesian parameter estimation and meta-analysis, and identify strategic and targeted gaps in marine invasion research.
Keywords: Acanthaster planci; Alien species; Climate change; Crown-of-thorns seastar; Biotic interactions; Exotic species; Marine biodiversity; Metapopulation model; Non-indigenous species; range shift

Geomorphological classification of reefs: draft framework for an Australian standard - Scott L Nichol; Z Huang; Howard, F; R. Porter-Smith; Vanessa L Lucieer; Neville Barrett (2016)
Reefs are recognised as seabed features that potentially support a diverse range of benthic and demersal biota and are recognised by the Australian Government as conservation values (i.e. Key Ecological Features) within marine bioregional plans. To support the ongoing monitoring and management of reef systems, the Marine Biodiversity Hub is undertaking a project to identify and collate all available mapping data for reefs on the continental shelf of Australia. This report presents a draft framework for describing the geomorphology of reefs based on the best available bathymetric data as the proposed standard for the classification of reefs in the Australian context. The classification incorporates a vocabulary of terms that describe reef origin, physical form (shape, relief, slope, rugosity) and substrate type (rock, unconsolidated, sediment texture). The broad environmental setting of a reef is also represented by categories of climatic region and shelf bathymetric zone. The classification is therefore intended for application to both rocky and biogenic reefs at the national scale, and links conceptually to the mapping of reef geomorphic features that forms part of the national benthic biogregionalisation (IMCRA). It is intended that the geomorphic classification presented here will be subsequently linked to a biological classification scheme for reef biota, thereby providing a comprehensive and integrated approach to the description of reef habitats.
Keywords: bathymetry reef; Continental shelf; Geomorphology; seabed

Historical Data on Australian Whale Vessel Strikes - International Whaling Commission June 2016 - David Peel; Joshua N. Smith; Simon Childerhouse (International Whaling Commission, 2016)
Based on existing data of the occurrence of vessel strike in Australia, Australian records represent approximately 7% of all worldwide vessel strikes reported to the International Whaling Commission. However, to date there has not been a dedicated Australian collation of historical data sources. Therefore we conducted a search of historical newspapers and other sources to discover reports of vessel strikes in Australian waters. This updated analysis uncovered a significant number of new and previously unreported records which means that Australia’s contribution of worldwide reported vessel strike has now increased to approximately 17%. It is very important to note from the outset that this does not necessarily reflect the actual proportion of global vessel strikes that have occurred in Australia, as national and international vessel strike data have inherent reporting biases and unknown coverage. However, the additional data collected in this study does challenge the notion that historically Australia has had low numbers of vessel strikes relative to the rest of the world. This data is yet to be cross-checked and validated but we present a preliminary summary and exploration of the data. One interesting finding was a distinct absence of large vessels in modern data but after examination we believe this is most likely a reflection of under-reporting due to large modern vessels possibly not detecting collisions.

Humans and seasonal climate variability threaten large-bodied coral reef fish with small ranges - Camille Mellin; Mouillot, D.; Kulbicki, M.; McClanahan, T. R.; Vigliola, L.; C. J. A. Bradshaw; Brainard, R. E.; Chabanet, P.; Graham J. Edgar; D. A. Fordham; Friedlander, A. M.; Parravicini, V.; et al. (Nature Communications, 2016)
Coral reefs are among the most species-rich and threatened ecosystems on Earth, yet the extent to which human stressors determine species occurrences, compared with biogeography or environmental conditions, remains largely unknown. With ever-increasing human-mediated disturbances on these ecosystems, an important question is not only how many species can inhabit local communities, but also which biological traits determine species that can persist (or not) above particular disturbance thresholds. Here we show that human pressure and seasonal climate variability are disproportionately and negatively associated with the occurrence of large-bodied and geographically small-ranging fishes within local coral reef communities. These species are 67% less likely to occur where human impact and temperature seasonality exceed critical thresholds, such as in the marine biodiversity hotspot: the Coral Triangle. Our results identify the most sensitive species and critical thresholds of human and climatic stressors, providing opportunity for targeted conservation intervention to prevent local extinctions. News item Media release - Most vulnerable tropical reef fish identified in new study, Australian Institute of Marine Science (AIMS), 3 February 2016
Keywords: Biological sciences; Ecology; Oceanography

Identification and collation of Australia’s shelf mapping datasets and development of a national geomorphological classification scheme for reef systems - Phase 1 Workshop Report - Vanessa L Lucieer; Z Huang; R. Porter-Smith; Scott L Nichol; Neville Barrett; Keith R Hayes (2016)
Rocky reefs form an important habitat on the continental shelf and are subject to disproportionate fishing pressure given the high productivity of this habitat relative to adjacent sandy seabed. Despite this, little is known of the extent and nature of these systems beyond their value to the fishing industry. This project collates all known mapping data from government and industry (including data acquired during CERF and NERP Hubs) to provide an updated map of this key habitat around Australia, and will identify critical gaps in this knowledge to be filled by targeted surveys. This will significantly improve the knowledge of these environmental assets within state waters and the Commonwealth Marine Area, improve our understanding of assets in marine protected areas and inform environmental assessment of proposed activities and developments required by environmental legislation. Collated information also contributes to development of a blueprint for monitoring key ecological features of the Commonwealth Marine Area. A geomorphological classification system is also being developed for these reefs, and associated cross-shelf habitats with the aim of it being accepted and adopted nationally, and it is being tested and refined for biological applicability. This milestone report documents the major outcomes of a national workshop intended to identify existing shelf-reef datasets, key stakeholders and develop a pathway to sharing our current data holdings nationally, and identifying priority knowledge gaps to prioritise future research projects in this space. It also documents workshop outcomes focussed on developing a nationally accepted classification for cross-shelf reef systems and associated habitats, and progress made subsequently in refining a scheme suitable for Australian conditions and agencies.

Image subsampling and point scoring approaches for large-scale marine benthic monitoring programs - Nicholas R. Perkins; Scott D Foster; Nicole A. Hill; Neville Barrett (Estuarine, Coastal and Shelf Science, 2016)
Benthic imagery is an effective tool for quantitative description of ecologically and economically important benthic habitats and biota. The recent development of autonomous underwater vehicles (AUVs) allows surveying of spatial scales that were previously unfeasible. However, an AUV collects a large number of images, the scoring of which is time and labour intensive. There is a need to optimise the way that subsamples of imagery are chosen and scored to gain meaningful inferences for ecological monitoring studies. We examine the trade-off between the number of images selected within transects and the number of random points scored within images on the percent cover of target biota, the typical output of such monitoring programs. We also investigate the efficacy of various image selection approaches, such as systematic or random, on the bias and precision of cover estimates. We use simulated biotas that have varying size, abundance and distributional patterns. We find that a relatively small sampling effort is required to minimise bias. An increased precision for groups that are likely to be the focus of monitoring programs is best gained through increasing the number of images sampled rather than the number of points scored within images. For rare species, sampling using point count approaches is unlikely to provide sufficient precision, and alternative sampling approaches may need to be employed. The approach by which images are selected (simple random sampling, regularly spaced etc.) had no discernible effect on mean and variance estimates, regardless of the distributional pattern of biota. Field validation of our findings is provided through Monte Carlo resampling analysis of a previously scored benthic survey from temperate waters. We show that point count sampling approaches are capable of providing relatively precise cover estimates for candidate groups that are not overly rare. The amount of sampling required, in terms of both the number of images and number of points, varies with the abundance, size and distributional pattern of target biota. Therefore, we advocate either the incorporation of prior knowledge or the use of baseline surveys to establish key properties of intended target biota in the initial stages of monitoring programs.
Keywords: Autonomous underwater vehicle; Bias; Image selection; Point count; Precision; Survey design

Indigenous Engagement and Participation Strategy - Paul Hedge (2016)
The document addresses the NESP Indigenous Engagement Strategy Guidelines (Guidelines) prepared by the Department of the Environment (Department) to ensure effective integration of Indigenous aspirations and outcomes in the National Environmental Science Programme (NESP).

Inferring contemporary and historical genetic connectivity from juveniles - Pierre Feutry; Berry, Oliver; PM Kyne; Richard D. Pillans; R. M. Hillary; Grewe, Peter M.; Marthick, James R.; Grant Johnson; R. Gunasekera; Nicholas J. Bax; Mark Bravington (Molecular Ecology, 2016)
Measuring population connectivity is a critical task in conservation biology. While genetic markers can provide reliable long-term historical estimates of population connectivity, scientists are still limited in their ability to determine contemporary patterns of gene flow, the most practical time frame for management. Here, we tackled this issue by developing a new approach that only requires juvenile sampling at a single time period. To demonstrate the usefulness of our method, we used the Speartooth shark (Glyphis glyphis), a critically endangered species of river sharks found only in tropical northern Australia and southern Papua New Guinea. Contemporary adult and juvenile shark movements, estimated with the spatial distribution of kin pairs across and within three river systems, was contrasted with historical long-term connectivity patterns, estimated from mitogenomes and genome-wide SNP data. We found strong support for river fidelity in juveniles with the within-cohort relationship analysis. Male breeding movements were highlighted with the cross-cohort relationship analysis and female reproductive philopatry to the river systems was revealed by the mitogenomic analysis. We show that accounting for juvenile river fidelity and female philopatry is important in population structure analysis and that targeting sampling in nurseries and juveniles aggregation should be included in the genomic toolbox of threatened species management.

Knowledge Brokering and Communication Strategy - Paul Hedge (2016)
This document addresses the National Environmental Science Program (NESP) requirement to develop a knowledge brokering and communication strategy. Knowledge brokering and communication activities are recognised as essential to the success of the NESP. The key objective of the NESP is to deliver accessible results that inform decisions leading to positive environmental change through an improved understanding of Australia’s environment. The NESP Guidelines state the knowledge brokering and communication strategy should illustrate how the hub will contribute to building relationships and knowledge-sharing networks between researchers, government, industry and communities. The strategy should also detail how the hub will facilitate adoption of research outcomes by environmental decision makers across government, industry and communities.

Mapping shelf rocky reef habitats in the Hunter Commonwealth Marine Reserve - P Davies; T Ingleton; Alan Jordan; Neville Barrett (2016)
This report documents results of a targeted acoustic field survey of areas on the continental shelf of the Hunter Commonwealth Marine Reserve undertaken as part of Hub research to improve our understanding of the nature and distribution of shelf rocky reefs found within the reserve, and, by inference, are likely to be found in adjacent east Australian shelf waters. It was also intended to identify areas of reef habitat suitable for subsequent biological inventory and monitoring. Shelf rocky reefs are identified as Key Ecological Features (KEFS) within the Commonwealth marine bioregional planning framework, and improving the knowledge of the distribution of this KEF within the Hunter CMR, the only Temperate East region CMR with significant shelf representation, was identified as a high priority in a Hub planning workshop (Lucieer et al. 2015).

Marine Biodiversity Hub banner 2016 - Annabel Ozimec (2016)
The NESP Marine Hub banner is available for workshops, conferences and other events.  Researchers should contact info@nespmarine.edu.au

Marine protected areas increase resilience among coral reef communities - Camille Mellin; Aaron M MacNeil; Cheal, Alistair J.; Emslie, Michael J.; M Julian Caley (Ecology Letters, 2016)
With marine biodiversity declining globally at accelerating rates, maximising the effectiveness of conservation has become a key goal for local, national and international regulators. Marine protected areas (MPAs) have been widely advocated for conserving and managing marine biodiversity yet, despite extensive research, their benefits for conserving non-target species and wider ecosystem functions remain unclear. Here, we demonstrate that MPAs can increase the resilience of coral reef communities to natural disturbances, including coral bleaching, coral diseases, Acanthaster planci outbreaks and storms. Using a 20-year time series from Australia's Great Barrier Reef, we show that within MPAs, (1) reef community composition was 21–38% more stable; (2) the magnitude of disturbance impacts was 30% lower and (3) subsequent recovery was 20% faster that in adjacent unprotected habitats. Our results demonstrate that MPAs can increase the resilience of marine communities to natural disturbance possibly through herbivory, trophic cascades and portfolio effects.
Keywords: Acanthaster planci; benthos; Biodiversity; bleaching; crown-of-thorns starfish; cyclone; disturbance; fish; Great Barrier Reef; marine reserves

Monitoring Australia's oceans: towards a blueprint - brochure - Paul Hedge (2016)
Monitoring Australia’s Commonwealth Marine Area is fundamental to understanding and reporting on how the ocean is changing in response to human pressures. In Towards a blueprint, the national Marine Biodiversity Hub distils the findings of more than eight years of research supported by the Australian Government. Towards a blueprint shows how Australia can expand its institutional capacity to meet the reporting needs of the Department of the Environment. It identifies existing data for areas where monitoring can begin, and assesses Australia’s capability to collect new monitoring data as a basis for decision making. This evidence-based approach is essential to understanding why ocean systems are changing across the third largest ocean territory in the world. Also view the full report - Towards a blueprint for monitoring Key Ecological Features in the Commonwealth Marine Area

Monitoring population dynamics of Western right whales - Final report on activities 30 March 2016 - John Bannister (2016)
To continue an annual series of aerial surveys off the southern Australian coast between Cape Leeuwin WA and Ceduna SA since 1993, an aerial survey was undertaken as planned over six days, 2-6 September, 2015. For comparison with previous results, counts were obtained of 462 individuals including 97 calves of the year. From 3679 photographic images obtained, 377 have been selected for computer-assisted ‘matching’ with those (some 6600 images of 2175 individuals) already available in the catalogue, and 126 data sightings sheets have been added to the sightings database, currently totalling 3670 sightings sheets. The 2015 counts were considerably lower than in recent years, particularly for cow calf pairs, which were the lowest recorded since 2007. Regression analysis of log number against year for the period 1993-2015 gives increase rates, for all animals of 0.0563 (95% CI 0.0380, 0.0747) (exponential rate) or 5.79 (95% CI 3.87, 7.75) (percent), and for cow/calf pairs 0.0588 (0.0324, 0.0852) or 6.06 (3.29, 8.89) respectively. Current population size, for this the ‘western’ Australian subpopulation, is estimated at 2266.

Monitoring population dynamics of Western right whales - Progress report on activities for 2016 - John Bannister (2016)
To continue an annual series of aerial surveys off the southern Australian coast between Cape Leeuwin WA and Ceduna SA since 1993, an aerial survey was undertaken over three days, 24-29 August 2016. Because of bad weather, and for the first time in the annual series since 1993, only ‘outward’ flying legs were possible. For comparison with previous results, counts were obtained of 628 individuals including 228 calves of the year. From 4305 photographic images obtained, 323 have been selected for computer-assisted ‘matching’ with those (some 7000 images of over 2000 individuals) already available in the catalogue, and 197 data sightings sheets have been added to the sightings database, currently totalling 3741 sightings sheets. Full details, including trend analysis since 1993, current population size, and distribution information, will be included in the Final Report due on 30 March 2017.
Keywords: numbers; Righrt whale population trends

NESP Marine Biodiversity Hub Research Plan - 2016 RPv2 - Project Proposals - Nicholas J. Bax; Paul Hedge (2016)
This Research Plan for 2016 (RPv2) has been developed by the Marine Biodiversity Hub, in consultation with the Department of the Environment and Energy and other key stakeholders. The purpose of the Research Plan is to outline: the research priorities the Hub is funded to investigate the research projects that will address these priorities how the output of the research will be communicated and brokered to key stakeholders how the impact of the research will be measured how Hubs will work collaboratively within and across Hubs This Research Plan also lists key staff and research organisations, and the risks needing to be monitored to ensure success. Please note: Project durations vary and may extend over a number of years.  If the project you are interested in is not listed in the Item field of this research plan, it will be included in an earlier year as an ongoing, unchanged project. Where a project proposal involves significant changes, it will be updated and included in subsequent research plans.
Keywords: annual research plan; RPv2

NESP Marine Biodiversity Hub Strategic Plan 2017-2021 - Paul Hedge (2016)
Purpose of strategic plan This document articulates the Hub’s strategy to enhance understanding of Australia’s marine environment. This strategy, together with the National Environmental Science Program (NESP) research priorities, will inform the development and review of the Hub’s research plans and investments. Background The NESP Marine Biodiversity Hub is a national collaboration of researchers formed to achieve the objectives and fulfil the outcomes of the NESP (see Attachment A). The national collaboration includes partners and collaborators that support the collection, analysis and interpretation of marine environmental data and information to enhance understanding of, and capacity to manage and conserve Australia’s marine environment The Hub’s research is funded by NESP and by research partner contributions under a 50:50 funding arrangement. Research plans are developed to address the NESP research priorities (Attachment B) and to further the marine research interests of the Hub’s partners. The NESP program emphasises the importance of engagement and participation of research users, stakeholders and Indigenous communities and traditional owners in developing and implementing research plans. This strategic plan articulates the strategic direction for the Hub’s research efforts for the period 2015-2021. The first version of the strategic plan was initiated in 2015 by the Steering Committee, developed by the Hub Leadership group (director, deputy director and chairperson) with input from the Partners Committee and Research Leadership Team. The second version of the plan was refined in 2016 to inform development of the 2017 and subsequent Research Plans. It will be periodically reviewed as required.

New approaches to marine conservation through scaling up of ecological data - Graham J. Edgar; Amanda E. Bates; Bird, Tomas J.; Jones, Alun H.; Stuart J. Kininmonth; Rick D Stuart-Smith; Webb, Thomas J. (Annual Review of Marine Science, 2016)
In an era of rapid global change, conservation managers urgently need improved tools to track and counter declining ecosystem conditions. This need is particularly acute in the marine realm, where threats are out of sight, inadequately mapped, cumulative, and often poorly understood, thereby generating impacts that are inefficiently managed. Recent advances in macroecology, statistical analysis, and the compilation of global data will play a central role in improving conservation outcomes, provided that global, regional, and local data streams can be integrated to produce locally relevant and interpretable outputs. Progress will be assisted by (a) expanded rollout of systematic surveys that quantify species patterns, including some carried out with help from citizen scientists; (b) coordinated experimental research networks that utilize large-scale manipulations to identify mechanisms underlying these patterns; (c) improved understanding of consequences of threats through the application of recently developed statistical techniques to analyze global species’ distributional data and associated environmental and socioeconomic factors; (d ) development of reliable ecological indicators for accurate and comprehensible tracking of threats; and (e) improved data-handling and communication tools.
Keywords: biological diversity; citizen science; ecological monitoring; ecosystem management; Macroecology; underwater visual census

New opportunities for conservation of handfishes (Family Brachionichthyidae) and other inconspicuous and threatened marine species through citizen science - Graham J. Edgar; Rick D Stuart-Smith; Antonia T. Cooper; Jacques, Michael; Valentine, Joe (Biological Conservation, 2016)
Volunteer divers participating in the Reef Life Survey (RLS) program actively assist species conservation efforts by generating data for threat assessments and population trend monitoring, through in-water restoration efforts, and through outreach of marine conservation messages. Up to 2014, standardised underwater visual survey data provided by RLS divers described densities of 495 cryptic fish species at over 1200 sites distributed around Australia. Each species was recorded on 34 separate transect blocks on average, allowing the first assessments of population trends for many species. These data highlight the threatened and data deficient status of endemic Australian handfish species. At least five shallow-water handfish species are potentially threatened, including the smooth handfish Sympterichthys unipennis, which has not been sighted for over 200 years, but is yet to be included on any threatened species list. RLS divers undertook directed searches at key historical locations for two handfish species, the red handfish Thymichthys politus, now only known from a single reef, and Ziebell's handfish Brachiopsilus ziebelli, with no confirmed sighting for over a decade. From a total of 100 h of underwater search effort, only four red handfish were recorded, all at a site threatened by adjacent human activity. These and other handfish species should be considered for inclusion on the IUCN Red List given that populations are either very small or have vanished, spawning substrates have probably declined, and the species lack a larval dispersal stage. More importantly, the absence of information on the conservation status of the majority of marine species needs urgent attention, including through expanded citizen science efforts, if management intervention is to occur and extinctions minimised.
Keywords: Population monitoring; Reef life survey; State-of-the-environment reporting; tasmania; underwater visual census

A new species of wedgefish Rhynchobatus cooki (Rhinopristiformes, Rhinidae) from the Indo–West Pacific - Last, Peter R.; PM Kyne; L J V Compagno (Zootaxa, 2016)
A new dwarf wedgefish, Rhynchobatus cooki sp. nov. is described from a single female from a Jakarta fish market (Indonesia) and 11 specimens collected at Jurong fish market (Singapore). First collected in 1934, the broader ichthyological community have been aware of this distinctive but little known ray since the late 1990’s. Rhynchobatus cooki is the smallest of the wedgefishes (to 81 cm TL) and has the lowest vertebral count (fewer than 107 centra). It is also distinguishable from its congeners based on its long, hastate snout, very strongly undulate anterior pectoral-fin margin, coloration and aspects of its squamation. The dorsal coloration is mainly dark and distinctively marked with white blotches, spots and streaks, and has a dark cruciate marking on the interorbit and a prominent white border around the body margin. Unlike most other wedgefish species, the snout tip lacks dark blotches and there is no black pectoral-fin marking. It shares well-developed rostral spines with a much larger Atlantic species (Rhynchobatus luebberti), but these spines are confined to the snout tip (rather than being more numerous and extending in paired rows along the rostral ridges nearly to the eyes). No additional specimens have been observed since 1996, despite an increased recent effort to survey the chondrichthyan fauna of South-East Asia and collect biological data for species, raising concerns over its conservation status.

NZMSS-AMSA 2016 Conference - Indigenous engagement panel discussion - Cass Hunter; Ratana, Kelly (2016)
This is a summary of the Indigenous Engagement Panel Discussion held at the joint NZMSS-AMSA Conference in 2016. He moana pukepuke, e ekengia e te waka – Mountainous seas can be navigated in a canoe Nā Kingi Ihaka, Te Ao Hou, No. 22 (April 1958) The Māori proverb above highlights that working together to achieve a common and agreed objective is the most effective way forward. Meaningful engagement between indigenous peoples and the science sector provides many opportunities to resolve some of the complex issues we face today, but these must be founded upon an open and genuine desire to work together. Following on from the NZMSS-AMSA 2016 Plenary delivered by Rawiri Smith, and the presentation session on cross-cultural research, this panel discussion aims to open up a dialogue between indigenous peoples (practitioners, researchers and leaders) and the marine science community. It also aims to strengthen learnings and relationships across the Tasman. Over many generations, indigenous communities have developed a deep an enduring connection to, and custodial relationship with the marine ecosystems that support their livelihoods and well-being. Recent shifts towards ecosystem-based management have emphasised the unique and vital contribution that indigenous peoples, values and knowledge bring to the conversation about socio-ecological systems. Engaging with indigenous communities is often a significant component of marine science, and cultural competency can often be the key to successful and meaningful research. Cultural competency and responsiveness requires learning, identifying challenges, and seeking solutions to improve both indigenous engagement with science and science engagement with indigenous communities. Indigenous engagement within the New Zealand science system is promoted through national governmental policy (the Vision Mātauranga Policy1) that seeks to support “unlocking the potential of Māori knowledge, resources and people,” by “supporting research that concerns distinctive issues and needs arising within Māori communities.” This means that in New Zealand a great deal of research moves past engagement and into a collaborative and co-production space. This is not always the case, or an easy journey, and our panellists will provide insight into the challenges and successes of their journey from an experienced iwi (tribal)/Māori perspective. As a tribal people, one framework for engagement does not fit all, meaning it is often through shared learning, experiences and open communication that research succeeds. In Australia, Indigenous engagement within the science system is currently promoted through a number of different mechanisms, including Traditional Owner driven processes, agencies, working groups, and ethical committees across the country. Australia differs to New Zealand as there is no national policy to help ensure Indigenous values, Indigenous knowledge systems and community priorities are recognised and responded to meaningfully through research that is inclusive, relevant, and beneficial. In Australia, we need to move on from having the same repetitive discussions about improving Indigenous engagement to actually establishing an Indigenous driven and led research agenda that establishes the guidelines for building collaborative partnerships across Australian Indigenous communities. For best practice to spread across Australia, important messages about cross-cultural research needs to be recognised and shared amongst all relevant bodies in order to grow those existing collaborative partnerships beyond a few Australian Indigenous communities. The Australian Indigenous panellists will share their experiences and insights into strengthening and advancing collaborative relationships. This panel discussion will lead into a further workshop to be held during the AMSA conference in Darwin, Australia, during July 2017. We hope that by beginning the discussions in this panel session between indigenous peoples who have been engaged in the science system from both countries, and involving the audience at the conference, we can highlight the successes and consider some of the issues that have arisen in the past, to enable us to navigate the mountainous seas ahead. Related information: New Zealand Marine Sciences Society (NZMSS) https://nzmss.org/ Australian Marine Sciences Association (AMSA) https://www.amsa.asn.au/ Joint NZMSS and AMSA conference 2016 https://www.amsa.asn.au/2016-wellington Enquiries about this summary: Cass Hunter cass.hunter@csiro.au
Keywords: Indigenous engagement; Marine Science

Outcropping reef ledges drive patterns of epibenthic assemblage diversity on cross-shelf habitats - Jacquomo Monk; Neville Barrett; Nicole A. Hill; Vanessa L Lucieer; Scott L Nichol; Justy P W Siwabessy; Williams, Stefan B. (Biodiversity and Conservation, 2016)
Seafloor habitats on continental shelf margins are increasingly being the subject of worldwide conservation efforts to protect them from human activities due to their biological and economic value. Quantitative data on the epibenthic taxa which contributes to the biodiversity value of these continental shelf margins is vital for the effectiveness of these efforts, especially at the spatial resolution required to effectively manage these ecosystems. We quantified the diversity of morphotype classes on an outcropping reef system characteristic of the continental shelf margin in the Flinders Commonwealth Marine Reserve, southeastern Australia. The system is uniquely characterized by long linear outcropping ledge features in sedimentary bedrock that differ markedly from the surrounding low-profile, sand-inundated reefs. We characterize a reef system harboring rich morphotype classes, with a total of 55 morphotype classes identified from the still images captured by an autonomous underwater vehicle. The morphotype class Cnidaria/Bryzoa/Hydroid matrix dominated the assemblages recorded. Both α and β diversity declined sharply with distance from nearest outcropping reef ledge feature. Patterns of the morphotype classes were characterized by (1) morphotype turnover at scales of 5 to 10s m from nearest outcropping reef ledge feature, (2) 30 % of morphotype classes were recorded only once (i.e. singletons), and (3) generally low levels of abundance (proportion cover) of the component morphotype class. This suggests that the assemblages in this region contain a considerable number of locally rare morphotype classes. This study highlights the particular importance of outcropping reef ledge features in this region, as they provide a refuge against sediment scouring and inundation common on the low profile reef that characterizes this region. As outcropping reef features, they represent a small fraction of overall reef habitat yet contain much of the epibenthic faunal diversity. This study has relevance to conservation planning for continental shelf habitats, as protecting a single, or few, areas of reef is unlikely to accurately represent the geomorphic diversity of cross-shelf habitats and the morphotype diversity that is associated with these features. Equally, when designing monitoring programs these spatially-discrete, but biologically rich outcropping reef ledge features should be considered as distinct components in stratified sampling designs.

Perspectives in visual imaging for marine biology and ecology: from acquisition to understanding - Durden, J; Schoening, T; Althaus, Franziska; Friedman, Ariell; Garcia, R; Glover, A G; Greinert, J; Stout, J; Jones, J O B; Jordt, A; Kaeli, W; Koser, K; et al. (Oceanography and Marine Biology: Annual Review, 2016)
Marine visual imaging has become a major assessment tool in the science, policy and public understanding of our seas and oceans. The technology to acquire and process this imagery has significantly evolved in recent years through the development of new camera platforms, camera types, lighting systems and analytical software. These advances have led to new challenges in imaging, including storage and management of ‘Big Data’, enhancement of digital photos, and the extraction of biological and ecological data. The need to address these challenges, within and beyond the scientific community, is set to substantially increase in the near future, as imaging is increasingly used in the designation and evaluation of marine conservation areas, and for the assessment of environmental baselines and impact monitoring of various marine industries. We review the state of the theory, techniques and technologies associated with each of the steps of marine imaging for observation and research, and to provide an outlook on the future from the perspective of current active science and engineering developers and users.
Keywords: image annotation; imaging technology; marine imaging; Survey design

The phylogenomic position of the Winghead Shark Eusphyra blochii (Carcharhiniformes, Sphyrnidae) inferred from the mitochondrial genome - Pierre Feutry; PM Kyne; Xiao Chen (Mitochondrial DNA Part B, 2016)
The complete mitogenome of the Winghead Shark Eusphyra blochii (Carcharhiniformes: Sphyrnidae) is determined in this study, which is 16,727 bp with a nucleotide base composition: 31.6% A, 25.7% C, 13.0% G and 29.7% T, containing 37 genes with the typical gene arrangement pattern and translate orientation in vertebrates. Two start codons (ATG and GTG) and two stop codons (TAG and TAA/T) are found in the protein-coding genes. The 22 tRNA genes range from 67 bp (tRNA-Cys and tRNA-Ser2) to 75 bp (tRNA-Leu1). The phylogenetic position showed that E. blochii clustered with the Sphyrna clade with strong posterior probability (100%). The hammerhead sharks (family Sphyrnidae) are a small but a highly distinctive group of tropical to temperate coastal and pelagic sharks. The family faces an elevated risk of extinction with several species assessed as threatened on the IUCN Red List of Threatened Species (IUCN 2015). There is also evidence for cryptic species in the Atlantic Ocean (Abercrombie et al. 2005), which presents issues for the identification and monitoring of catches. Molecular identification of hammerhead products can assist catch identification (Abercrombie et al. 2005; Chapman et al. 2009 ) and is becoming increasingly important as conservation and management measures are implemented for these species, such as the 2013 listing of the three larger-bodied species on the Convention on International Trade in Endangered Species (CITES 2013).
Keywords: Eusphyra blochii; Mitochondrial genome; Sphyrnidae; threatened species

Population trend in right whales off southern Australia 1993-2015 - International Whaling Commission June 2016 - John Bannister; Hammond, Phil; M C Double (International Whaling Commission, 2016)
Annual flights to survey southern right whales in winter/spring on the coast of southern Australia, between Cape Leeuwin (Western Australia) and Ceduna (South Australia) have been conducted over a 23-year period 1993-2015. These surveys have provided evidence of a population trend of around 6% per year, and a current (at 2014) population size of approximately 2300 of what has been regarded as the ‘western’ Australian right whale subpopulation. With estimated population size in the low thousands, it is presumed to be still well below carrying capacity. No trend information is available for the ‘eastern’ subpopulation of animals occurring around the remainder of the southern Australian Coast, to at least as far as Sydney, New South Wales and the populations size is relatively small, probably in the low hundreds. A lower than expected ‘western’ count in 2015 gives weak evidence that the growth rate may be starting to show signs of slowing, though an exponential increase remains the best description of the data. If the low 2015 count is anomalous, future counts may be expected to show an exponential increase, but if it is not, modelling growth as other than simple exponential may be useful to explore in future.

Reproductive parameters of rhinobatid and urolophid batoids taken as by-catch in the Queensland (Australia) east coast otter-trawl fishery - PM Kyne; Courtney, A. J.; Jacobsen, I. P.; Bennett, M. B. (Journal of Fish Biology, 2016)
Reproductive variables are provided for batoids regularly taken as by-catch in the east coast otter-trawl fishery on the inner-mid continental shelf off the south-east and central coasts of Queensland, Australia. Total length at maturity (LT50 and 95% c.i.) for the eastern shovelnose ray Aptychotrema rostrata was 639·5 mm (617·6–663·4 mm) for females and 597·3 mm (551·4–648·6 mm) for males. Litter size (n = 9) ranged from nine to 20 (mean ± s.e. = 15·1 ± 1·2). This species exhibited a positive litter size–maternal size relationship. Disc width at maturity (WD50 and 95% c.i.) for the common stingaree Trygonoptera testacea was 162·7 mm (155·8–168·5 mm) for females and 145·9 mm (140·2–150·2 mm) for males. Gravid T. testacea (n = 6) each carried a single egg in the one functional (left) uterus. Disc width at maturity (WD50 and 95% c.i.) for the Kapala stingaree Urolophus kapalensis was 153·7 mm (145·1–160·4 mm) for females and 155·2 mm (149·1–159·1 mm) for males. Gravid U. kapalensis (n = 16) each carried a single egg or embryo in the one functional (left) uterus. A single female yellowback stingaree Urolophus sufflavus carried an embryo in each uterus. A global review of the litter sizes of shovelnose rays (Rhinobatidae) and stingarees (Urolophidae) is provided.

Restructuring higher taxonomy using broad-scale phylogenomics: The living Ophiuroidea - Tim O'Hara; Andrew F. Hugall; Thuy, Ben; öhr, Sabine; Martynov, Alexander V. (Molecular Phylogenetics and Evolution, 2016)
The power and throughput of next-generation sequencing is instigating a major transformation in our understanding of evolution and classification of life on our planet. The new trees of life are robust and comprehensive. Here we provide a landmark phylogeny of the living ophiuroids and use it as the basis for a major revision of the higher classification of this class of marine invertebrates. We used an exon-capture system to generate a 1484 exon (273 kbp) data-matrix from DNA extracted from ethanol-preserved museum samples. We successfully obtained an average of 90% of our target sequence from 576 species spread across the known taxonomic diversity. The topology of the major lineages was robust to taxon sampling, exon-sampling, models and methods. However, estimates of node age were much less precise, varying by about a quarter of mean age. We used a combination of phylogenetic distinctiveness and temporal-banding to guide our revision of the family-level classification. Empirically, we determined that limiting family crown age to 110 ± 10 Ma (mid Cretaceous) selected phylogenetically distinct nodes while minimising disruption to the existing taxonomy. The resulting scheme of 32 families and six orders considerably expands the number of higher taxa. The families are generally longitudinally widespread across the world’s oceans, although 17 are largely confined to temperate and equatorial latitudes and six to relatively shallow water (less than 1000 m depth).
Keywords: deep sea; Exon capture; invertebrates; Marine; Ophiuroidea; phylogenomics; Temporal-banding

Scoping of potential species for ship strike risk analysis - David Peel; Natalie Kelly; Joshua N. Smith; Simon Childerhouse (2016)
This report provides the results from the Phase 1 of the NESP project C5/A2 Quantification of risk from shipping to large marine fauna.  The objective of the first phase of the project was to complete a review of large marine fauna species to identify a subset of species that a risk analysis could be undertaken on in Phase 2. A systematic approach was used to evaluate each species in terms of priority and feasibility, based on the following: Priority -  This assessment was to provide an evaluation of species for which the national modelling of risk would be both useful from a management context (e.g. a species has a high threat status) and that ship strike has been established as a known risk, and Feasibility - This assessment was used to indicate how practical an analysis of the species would be within the project timeframe. The main aspect is availability of suitable data that could be used to model risk for that species at a national level. To ensure that the research is most useful in management context, it is important to balance Priority and Feasibility to determine achievable projects. Once Priority and Feasibility had been assessed, then these were combined to determine overall Suitability for national modelling of the risk of vessel strike.

Seafloor biota, rock lobster and demersal fishes assemblages of the Tasman Fracture Commonwealth Marine Reserve Region: determining the influence of the shelf sanctuary zone on population demographics - Jacquomo Monk; Neville Barrett; J Hulls; James, Lainey; G.R. Hosack; Elizabeth S. Oh; Martin, Tara; Edwards, Stuart; Nau, Amy; Heaney, Bernadette; Scott D Foster (2016)
The Tasman Fracture Commonwealth Marine Reserve (CMR) is the southernmost CMR within the Australian CMR network in continental waters. The Tasman Fracture CMR, as part of its zoning arrangements, includes a no-take zone on the continental shelf. This is the only area of continental shelf habitat included within the south-eastern CMR network that completely prohibits fishing activities through the establishment of a Sanctuary Zone. Despite being protected for over 7-years, little was known about the range of habitats and associated biological diversity occurring on the shelf waters within this CMR, or the extent that protection had influenced the biota of the CMR. In this study, we take a multi-step approach to first identifying the types and distribution of benthic habitats within, and adjacent to the CMR, and then focussing on reef habitat, to use a range of biological sampling tools to describe the associated reef biota. These surveys included contrasts of the biota in, and adjacent to the no-take zone, to determine the extent that the biota may have responded to the 7 years of protection within the CMR. Reef habitat was targeted due to its overall greater species diversity than adjacent soft sediments, and this habitat was known to be actively targeted by fishing activities, including those for southern rock lobster.

Sharks and Rays of Northern Australian Rivers - PM Kyne (2016)
Poster Populations of sawfishes and river sharks in the Northern Territory (NT) are thought to have declined dramatically in recent decades, raising concerns about their viability. Research under the National Environmental Research Program (NERP) has provided information on the distribution, ecology and population dynamics of sharks and rays of northern Australian rivers to assist in their conservation, management and recovery. This project has generated a better ecological understanding of the habitat use and habitat requirements, short and long-term movements, connectivity and spatial dynamics of these species and collected tissue samples for population structure and abundance estimation. Fisheries-independent surveys in selected river systems were conducted using gillnets and rod and line. Captured sharks were tagged and monitored with acoustic telemetry. This uses networks of moored acoustic receivers to detect tagged fish when they pass within range of a receiver. Extensive arrays of acoustic receivers provide long-term monitoring of tagged animals. Mitochondrial genome sequencing of Speartooth Sharks and Largetooth Sawfish was used to help profile their population structure. The mitogenome, which is inherited through the mother, offers clues to how widely females disperse to breed (for example, between river systems). This new two-sided poster now features indigenous artwork by Graham Rostrom, a cultural teacher, artist, dancer, musician and song man. The Marine Biodiversity Hub works with indigenous communities and ranger groups in northern Australia to manage and recover threatened sawfishes and river sharks This poster supports the project "Supporting management of listed and rare species". Visit the sawfish project webpages for resources such as videos, species information sheets and news stories Download a low resolution version of the poster at the Item link below. Request a copy of the poster and postcard (with information about artist, Graham Rostron)

Sharks and Rays of Northern Australian Rivers - Postcard - PM Kyne (2016)
This postcard supports the poster Sharks and Rays of Northern Australian Rivers which features indigenous artwork by Graham Rostron and photos of critically endangered river sharks and sawfishes. The Marine Biodiversity Hub works with indigenous communities and ranger groups in northern Australia to manage and recover threatened sawfishes and river sharks. <img alt="Berelh Copyright Graham Rostron" src="/sites/nerpmarine.edu.au/files//Berelh%20GrahamRostron%20Sharks%20and%20Rays%20of%20Northern%20Australian%20rivers.jpg" style="width:400px; height:267px; float:right" />The art - Berelh Berelh is the Kunay word for the flat one, ‘stingray’. This is a female one. In the day she stays down in the sand ground, where it is cool. At night she swims around looking for tucker, looking for prawn, crab and other tucker. All night she swims, then goes back and rests herself, she covers herself back up with sand. This stingray is swimming around, she sees the sawfish, the shark and the prawn. The sawfish we call Djenkundamen, he is dangerous when we are hunting so we be careful. The shark, he’s dangerous too, same like crocodile. The shark we call Wamba. The little prawn, he’s a day time, night time man, walking around under the water enjoying himself. These all live in the river where they hunt tucker. They are all tucker for us too on our country. The artist - Graham Rostron Name - Graham Rostron Date of Birth - 28-01-1980 Clan - Baraba Skin - Balang Language - Kunay Mother’s Country - Kutji Father’s Country - Korlorbirrahda Dreaming - Narin (Quiet Snake) Graham Rostron is a cultural teacher, artist, dancer, musician and song man. ‘My Father died when I was just crawling. I did not know him. Then we were living at Madjinbardi. Then we went to Maningrida to be with family, following my mother. My second dad brought me up at his outstation at Korlorbirrahda. His name is Tom Noytuna- you may have seen a photograph of him on an orange phone with lots of ceremonial paint on his face. Korlorbirrahda is a long way out into the Great Arnhem Plateau. He was keeping me when I was little and he showed me hunting and painting and explaining to me everything. He gave me confidence.’ Request a copy of the poster and postcard

Shellfish reef habitats: a synopsis to underpin the repair and conservation of Australias environmental, social and economically important bays and estuaries - Chris L Gillies; Colin Creighton; Ian M. McLeod (2016)
This report describes the historic extent and current knowledge of Australian shellfish reefs and identifies knowledge gaps and future research priorities with the aim of supporting restoration efforts. Shellfish reefs are complex, three-dimensional living structures, which provide food, shelter and protection for a range of other invertebrate and fish species. They occur in bays, estuaries and nearshore coastal waters in both tropical and temperate regions across every state within Australia. Shellfish reefs largely occur in the intertidal and upper subtidal regions of bays, estuaries and nearshore waters with the exception of the native flat oyster (Ostrea angasi) which can form reefs at depths of up to 30 m. There are more than 2000 bivalve species likely to occur in Australian coastal waters, yet only eight oyster and mussel species are known to form clearly defined reef structures across multiple locations and at scale. Prior to the 20th century, shellfish reefs were common features of estuarine and coastal systems and were of importance as a food source for Indigenous Australians, with considerable quantities of reef-forming species occurring in coastal food middens. Early maritime explorers such as Cook, Flinders, Eyre and Vancouver regularly referred to extensive shellfish reefs in voyage reports and journals. From early European settlement of Australia, vast quantities of oysters and mussels were harvested for food and as a source of lime for mortar used in the early construction of roads and buildings. Throughout the 1800s and early 1900s, dredge and hand-harvest oyster fisheries were likely to have occurred in over 150 locations across eastern and southern Australia, including major coastal embayments such as Moreton Bay, Sydney Harbour, Port Phillip Bay, Gulf St Vincent, Derwent River and Princess Royal Harbour. As shellfish resources closest to Australia’s first settlements rapidly became depleted, shellfish fisheries expanded to include more distant bays and estuaries. Whilst the total State or or Australia-wide catch for any one year is unknown, records from single estuaries (e.g. 10 tonnes per week for Western Port, Victoria; 22 million oysters per year from 5 estuaries in Tasmania) indicate oyster fishing constituted some of the largest and most valuable fisheries, and indeed one of the most valuable marine industries, of the 1800s. From historical fishery reports and media articles it is clear that early harvesting efforts were unsustainable, which led to the regulation of shellfish fisheries from as early as 1853 in Tasmania and South Australia. The oyster industry was the first (of any) fishery to be regulated by legislation in South Australia, Tasmania and Victoria, with New South Wales, Queensland and Western Australia to follow within 30 years. Yet the regulation of shellfish harvesting did little to halt the destruction of shellfish reefs and by the late 20th century, shellfish reefs had all but disappeared, with all major oyster fisheries closed by 1960. Today, only a fraction of natural shellfish reefs still survive, notably in Hinchinbrook Channel (Queensland) Sandon River (NSW) and Georges Bay (Tasmania). Poor water quality and sedimentation as a result of catchment clearance, urbanisation and industrial pollution and diseases such as Queensland Unknown (QX) and Bonamia likely exacerbated the loss of historic shellfish reefs and may hinder their natural revival. Examples from the United States and elsewhere have demonstrated that when restoration occurs at large scales, ecological function can be repaired and ecosystem services can be restored. The process of restoring shellfish reefs can provide both short- and long-term employment opportunities and established reefs can provide long-term economic gains for coastal communities, particularly in fishing tourism and coastal protection. The benefits provided by shellfish reefs include food provision, water filtration, fish production, coastal protection and habitat for other species. Several projects (in Queensland, New South Wales, Victoria, South Australia and Western Australia) have recently begun the process of restoring shellfish reefs for the purpose of recovering a near extinct habitat and to improve fish habitat, water quality and coastal protection. Momentum is continuing to build, with a number of other shellfish reef restoration projects expected to begin across Australia within the next 12-24 months.   Related information: The Shellfish Reef Restoration Project - James Cook University and TropWATER - Tropical Water & Aquatic Ecosystem Research

Spatiotemporal modelling of crown‐of‐thorns starfish outbreaks on the Great Barrier Reef to inform control strategies - Vanhatalo, Jarno; G.R. Hosack; H Sweatman (Journal of Applied Ecology, 2016)
Cyclical outbreaks of pests can impact the functioning of entire ecosystems. An eminent example is outbreaks of crown‐of‐thorns starfish (COTS; Acanthaster planci) that cause substantial coral mortality on the Great Barrier Reef (GBR). We analyse COTS abundance and outbreaks with a Bayesian spatiotemporal model applied to a long‐term survey of the GBR (1985–2014). We assess the relative increase in COTS abundance beyond that explained by a reef's location and explanatory covariates, and thereby incorporate local reef characteristics into the identification of outbreaks, while allowing for both randomness and predictable patterns in the development of outbreaks. The model results confirm that waves of COTS outbreaks originate near Lizard Island (14·67⁰S) and progress in a northwesterly or southeasterly direction, with the southward wave progressing about 60 km year−1. The model reveals several previously unidentified hotspots with high average COTS abundance. The abundance of COTS may also have decreased on reefs protected from fishing after an expansion of protected areas within the GBR Marine Park in 2004, which suggests that closing reefs to fishing may help control COTS. Synthesis and applications. In this study, we use 30 years of data from the Great Barrier Reef to show that the timing and geographic location of crown‐of‐thorns starfish (COTS) outbreaks can be modelled by incorporating covariates, spatial and spatiotemporal dependence within a single coherent framework. The model can be used to identify areas of high average COTS abundance, to assess the impact of fishery management actions such as no‐take areas and to identify areas where waves of outbreaks may originate. The identification of outbreaks from noisy long‐term spatially extensive data may help managers choose appropriate control strategies. This modelling approach is applicable to other ecosystems where outbreaks of damaging pests occur. Wiley Content Sharing shareable link to full text version https://rdcu.be/bPJiz
Keywords: crown-of-thorns starfish; functional response; Gaussian process; Great Barrier Reef; hierarchical model; long-term ecological monitoring; marine parks; no-take areas; spatiotemporal dependence; time series

The status of human-shark interactions and initiatives to mitigate risk in Australian waters (2016)
Considerable political, public and media attention in Australia has recently been focussed on the interactions between sharks and humans in the marine environment and specifically surrounding shark attack and ways to mitigate this risk. This has initiated considerable investment at the State Government level in new technologies, techniques and their operational testing, as well as publicly accessible information that supplement existing strategies in an attempt to reduce the risks of shark-human interactions.

Sustainable management of Australia’s coastal seascapes: a case for collecting and communicating quantitative evidence to inform decision-making - Wegscheidl, Carla J.; Sheaves, Marcus; Ian M. McLeod; Paul Hedge; Chris L Gillies; Colin Creighton (Wetlands Ecology and Management, 2016)
Australia’s developed coasts are a heavily competed space, subject to urban, industrial and agricultural development. A diversity of habitats, such as mangroves, saltmarshes and seagrasses, comprise Australia’s coastal seascape and provide numerous benefits including fish productivity, carbon sequestration, nutrient cycling, coastal protection and recreation. Decision makers need to be able to weigh up the relative costs and benefits of coastal development, protection or repair and to do this they need robust, accessible and defensible data on the ecological function and economic value of Australia’s coastal seascapes. We reviewed the published literature, with a focus on saltmarsh as a vulnerable ecological community, to determine the availability of information on key ecological functions that could inform ecosystem service valuation. None of the publications we reviewed quantified nutrient cycling, coastal protection or recreation functions. Only 13 publications presented quantitative information on carbon sequestration and fish productivity. These were limited geographically, with the majority of studies on sub-tropical and temperate saltmarsh communities between south-east Queensland and Victoria. This demonstrates a lack of quantitative information needed to substantiate and communicate the value of Australia’s saltmarshes in different locations, scales and contexts. Research should focus on addressing these knowledge gaps and communicating evidence in a relevant form and context for decision-making. We discuss four principles for research funding organisations and researchers to consider when prioritising and undertaking research on key ecological functions of Australia’s saltmarshes, and coastal seascapes more broadly, to support sustainable coastal development, protection and repair for long-term economic and community benefit.
Keywords: Ecosystem service; Function; mangrove; Saltmarsh; Seascape

A taxonomic revision of the genus Primnoisis Studer [& Wright], 1887 (Coelenterata: Octocorallia: Isididae) using morphological and molecular data - Kirrily Moore; Alderslade, Philip; Karen J Miller (Zootaxa, 2016)
A complete taxonomic revision of the genus Primnoisis (Isididae) is presented herein, based on original type material of all nominal species and additional specimens from deep-water surveys in sub-temperate and Antarctic waters. A multi-disciplinary approach was used combining morphological characteristics such as colonial branching patterns, polyp structure, sclerite form and arrangement, together with phylogenetic reconstructions using two mitochondrial gene regions (mtMutS and igr1–cox1). The genus Primnoisis is retained with 7 of the 8 nominal species validated (P. antarctica Wright & Studer, 1889, P. rigida Wright & Studer, 1889, P. ambigua Wright & Studer, 1889, P. delicatula Hickson, 1907, P. fragilis Kükenthal, 1912, P. formosa Gravier, 1913 and P. mimas Bayer & Stefani, 1987), with the eighth (P. sparsa Wright & Studer, 1889), synonymised with P. antarctica. In addition, the species Mopsea gracilis Gravier, 1913 is reassigned to Primnoisis and an additional five new species are described (P. chatham n. sp., P. erymna n. sp., P. millerae n. sp., P. niwa n. sp. and P. tasmani n. sp). Most of the species fell into two clear groups, defined both by morphology and genetic grouping, for which two new sub-genera are proposed (P. (Primnoisis) n. subg. and P. (Delicatisis) n. subg.). Three species, P. ambigua, P. mimas and P. tasmani, could not be placed reliably in either sub-genus due to distinctive morphological features or genetic dissimilarity. It was not possible to confirm the monophyly of the genus due to unresolved relationships with the closely related genus Notisis Gravier, 1913 and an undescribed genus of Mopseinae.
Keywords: Alcyonacea; Antarctica; Cnidaria; Coelenterata; Deep-sea; gorgonian; octocoral; soft coral; Southern Ocean

Towards an IMCRA 5 - Tim O'Hara; Daniel C Gledhill; Scott L Nichol; Rachel Przeslawski; Paul Hedge; Nicholas J. Bax (2016)
Australia is a world leader in spatial conservation planning. The IBRA (terrestrial) and IMCRA (marine) bioregionalisation programs were significant conservation management achievements. However, such initiatives require periodic review and updating in order to incorporate new data and tools. While IBRA is in its seventh version, the IMCRA marine bioregionalisation is in its second substantial version. It was last updated in 2006 (IMCRA v4.0) with the recommendation that it not be updated before 2010.  Triggers identified for updating IMCRA v4.0 were: 1) substantial new biodiversity or process data; 2) jurisdictional need, and 3) international obligations. Areas that could be addressed to improve the utility of IMCRA were: conceptual classification models; improved data coverage, and improved ecosystem understanding, including the role of surrogates. New biodiversity data collated since 2006 have identified numerous inconsistencies in the formation of existing marine bioregions, particularly for inshore areas and island territories. There has been a considerable accumulation of national biological and environmental datasets and the development of new analytical tools. Our understanding of processes that structure biodiversity at large scales has also changed, with an increased emphasis on the importance of depth, carbon flux and connectivity. Some of this new knowledge, including identification of Key Ecological Features, was used in designing the Commonwealth Marine Reserve (CMR) network, but the data were never added to IMCRA. New observations have refined our understanding of when surrogates are useful.  New genetic datasets have provided a novel conceptual model that distinguishes long term evolutionary change and shorter term ecological processes. These scientific advances justify revising IMCRA. It would be useful to have a revised IMCRA available to inform reviews of marine reserves and reserve networks and marine bioregional plans, for example the South-east CMR Network Management Plan is expected to be reviewed in 2023 when it expires. Up to date and improved versions of IMCRA also have the potential to inform ongoing environmental impact assessments of new or planned activities.  In working towards a best-practice bioregionalisation, a number of challenges remain. This includes filling large remaining biological data gaps, finalising national datasets of important environmental variables, and extending analytical techniques so that they can rigorously incorporate biological data from mixed sampling regimes (e.g. most museum data), historical (genetic) information and connectivity (dispersal) data.

Urogymnus acanthobothrium sp. nov., a new euryhaline whipray (Myliobatiformes: Dasyatidae) from Australia and Papua New Guinea - Last, Peter R.; William T White; PM Kyne (Zootaxa, 2016)
Urogymnus acanthobothrium sp. nov. is described from a single specimen taken from the Cambridge Gulf, Western Australia, and from images of 10 other specimens from northern Australia and Papua New Guinea (all observed but not collected). It is a very large ray that attains at least 161 cm disc width, making it amongst the largest of the whiprays. The ventral tail below the caudal sting has a low, short-based fold. A ventral tail fold (or a dorsal fold) has not been recorded for any other himanturin stingray in the Indo-West Pacific. Molecular data suggest it is most closely related to a similar but more widely distributed cognate, U. granulatus. Both of these species share a suboval disc shape, similar squamation patterns, and the tail posterior to the sting is entirely white (at least in small individuals). U. acantho-bothrium sp. nov. differs from U. granulatus in having a longer and more angular snout, longer tail, more posteriorly in-serted caudal sting, lacks white flecks on the dorsal surface, and the ventral disc is uniformly white (rather than white with a broad black margin). It co-occurs with two other morphologically distinct Urogymnus in the region (U. asperrimus and U. dalyensis). Like U. dalyensis it occurs in both brackish and marine waters. A key is proved to the members of the genus Urogymnus. Related information News item - Giant stingray comes out of hiding - 1 August 2016 CSIRO blog
Keywords: Australia; Dasyatidae; giant whipray; new species; Papua New Guinea; Urogymnus acanthobothrium

Use of otolith chemistry and acoustic telemetry to elucidate migratory contingents in barramundi Lates calcarifer - Crook, D. A.; Buckle, D. J.; Allsop, Q.; Baldwin, W.; Thor Saunders; PM Kyne; Woodhead, J. D.; Maas, Roland; Roberts, Brien; Douglas, M. M. (Marine and Freshwater Research, 2016)
Migration is a fundamental aspect of the life history of many fish and must be well understood for targeted conservation and management. We used acoustic telemetry and otolith 87Sr/86Sr analysis, in conjunction with annual ageing, to study intraspecific variation in barramundi Lates calcarifer migration in the Northern Territory, Australia. Acoustic transmitters were implanted into 25 barramundi (420–1010-mm total length (TL); median 510 mm TL) from freshwater reaches of the South Alligator River and their movements tracked over >2 years. 87Sr/86Sr transect analysis was also conducted on otoliths of 67 barramundi from the Daly, Mary, South Alligator and Roper rivers. Acoustic telemetry showed that most fish remained in fresh water across wet and dry seasons. Higher rates of movement occurred during the wet season and a minority of fish moved into the estuary during high flows. Otolith chemistry analyses revealed high diversity in salinity histories among individuals. We integrated the telemetry and otolith chemistry data to examine migration as a function of the stage of sexual development, and have proposed a revised life history model that identifies three migratory contingents. We conclude that anthropogenic disturbance, including modified river hydrology, has the potential to alter the frequency of life history contingents in barramundi populations.
Keywords: biochronology; contingent hypothesis; diadromy; fish migration

Use of stereo baited remote underwater video systems to estimate the presence and size of white sharks (Carcharodon carcharias) - David Harasti; K. A. Lee; Laird, R.; R. W. Bradford; B. Bruce (Marine and Freshwater Research, 2016)
Stereo baited remote underwater video systems (stereo-BRUVs) are commonly used to assess fish assemblages and, more recently, to record the localised abundance and size of sharks. The present study investigated the occurrence and size of white sharks (Carcharodon carcharias) in the near-shore environment off Bennett’s Beach, part of a known nursery area for the species in central New South Wales, Australia. Six stereo-BRUV units were deployed approximately fortnightly between August and December 2015 for periods of 5 h in depths of 7–14 m. Stereo-BRUVs successfully recorded 34 separate sightings of 22 individual white sharks. The highest number of individuals detected during a single day survey was eight. All C. carcharias observed on stereo-BRUVs were juveniles ranging in size from 1.50 to 2.46-m total length (mean ± s.e., 1.91 ± 0.05 m; n = 22). The time to first appearance ranged from 15 to 299 min (mean ± s.e., 148 ± 15 min). This study demonstrates that the use of stereo-BRUVs is a viable, non-destructive method to obtain estimates of the size and presence of white sharks, and may be useful in estimating relative abundance in near-shore environments where white sharks are known to frequent.
Keywords: beach; elasmobranch; nursery area; Port Stephens; stereo camera

Using ecologically or biologically significant marine areas (EBSAs) to implement marine spatial planning - Piers K Dunstan; Nicholas J. Bax; Jeffrey M Dambacher; Keith R. Hayes; Paul Hedge; Smith, David C.; Smith, Anthony D.M. (Ocean & Coastal Management, 2016)
The Convention on Biological Diversity (CBD) agreed in 2008 on the need to identify Ecologically or Biologically Significant Marine Areas (EBSAs) in the world's oceans to focus future conservation and management efforts. From 2010 to 2014, 9 workshops had described 204 areas meeting the EBSA criteria in approximately 68% of the world's oceans. The workshops comprised experts nominated by more than 100 governments and a similar number of regional and global non government and intergovernmental organizations, supported by a technical team that collated data and provided mapping expertise. Despite this progress, there is uncertainty about how to use EBSA in Marine Spatial Planning (MSP). We review a suite of the existing MSP, Ecosystem Based Management, fisheries and conservation frameworks to determine their common elements and suggest how they can be synthesized. We propose an adaptive hierarchical approach that takes key elements from existing frameworks and show how EBSA can be used to support this approach within national jurisdictions and in areas beyond national jurisdiction. The adaptive hierarchical process encourages early implementation of MSP/EBM using available scientific knowledge and governance and supports the gradual progress to more complex and information rich structures as needed and appropriate. The EBSA process provides a sound basis for developing the scientific advice to support national and international management of the world's oceans by identifying marine systems and the criteria for which they are valued by regional experts.

Aerial survey monitors right whales off southern Australia - Fact sheet - Nicholas J. Bax (2015)
A long-term aerial survey of right whales of southern Australia is charting the recovery of the species and providing a basis for monitoring the effects of environmental change. Southern right whales, Eubalaena australis, were hunted almost to extinction in the Southern Hemisphere during the 19th Century. Signs of recovery have been apparent since the 1950s, particularly since the mid-1970s when their harvest was ceased. The rate of recovery has been monitored off southern Australia since 1993 in an annual survey led by WA Museum.

Altered niche of an ecologically significant species, Centrostephanus rodgersii, in its extended range revealed using an Autonomous Underwater Vehicle - Nicholas R. Perkins; Nicole A. Hill; Scott D Foster; Neville Barrett (Estuarine, Coastal and Shelf Science, 2015)
Poleward range shifts of species as a result of global climate change are being increasingly documented. As species extend into new ranges their ecological impacts and the niches that they occupy may be unpredictable. We use benthic imagery obtained from the broad-scale deployment of an Autonomous Underwater Vehicle (AUV) to quantify the depth distribution of barrens habitat formed by a recent range extension of the sea urchin species, Centrostephanus rodgersii, a known ecosystem engineer. AUV transects covering similar depths from both the historical range of New South Wales, Australia, and from the range extension area of the east coast of Tasmania were examined for the presence of barrens. We find that C. rodgersii occupies a different realised niche in its extended range, with barrens habitat occurring significantly deeper in Tasmanian waters (16–58 m) compared to NSW waters (7–27 m). The expansion of barrens habitat has devastating impacts on biodiversity, with flow-on effects to ecosystem services and local fisheries, and in Tasmania this threat extends to deeper, invertebrate-dominated habitats. This finding has important management implications, in particular the need to incorporate deeper reef systems into planning, with increased barrens expected under future climate change predictions. One conservation management approach is the use of no-take Marine Protected Areas (MPAs) to prevent barren establishment in representative habitats by rebuilding viable populations of urchin predators. We also examine the correlation between MPA status and the occurrence of barrens within a small, no-take Tasmanian reserve and adjacent control sites. We find that there is suggestive, but inconclusive, evidence for fewer barrens in the MPA (p = 0.07). Our study highlights the utility of a novel technology for conducting large-scale benthic surveys and monitoring the impacts of range extending species.
Keywords: auv; barrens; climate change; marine protected area; niche shift; range shift; realised niche

Are we missing the boat? Current uses of long-term biological monitoring data in the evaluation and management of marine protected areas - P F E Addison; Flander, L.B.; Cook, C.N. (Journal of Environmental Management, 2015)
Protected area management agencies are increasingly using management effectiveness evaluation (MEE) to better understand, learn from and improve conservation efforts around the globe. Outcome assessment is the final stage of MEE, where conservation outcomes are measured to determine whether management objectives are being achieved. When quantitative monitoring data are available, best-practice examples of outcome assessments demonstrate that data should be assessed against quantitative condition categories. Such assessments enable more transparent and repeatable integration of monitoring data into MEE, which can promote evidence-based management and improve public accountability and reporting. We interviewed key informants from marine protected area (MPA) management agencies to investigate how scientific data sources, especially long-term biological monitoring data, are currently informing conservation management. Our study revealed that even when long-term monitoring results are available, management agencies are not using them for quantitative condition assessment in MEE. Instead, many agencies conduct qualitative condition assessments, where monitoring results are interpreted using expert judgment only. Whilst we found substantial evidence for the use of long-term monitoring data in the evidence-based management of MPAs, MEE is rarely the sole mechanism that facilitates the knowledge transfer of scientific evidence to management action. This suggests that the first goal of MEE (to enable environmental accountability and reporting) is being achieved, but the second and arguably more important goal of facilitating evidence-based management is not. Given that many MEE approaches are in their infancy, recommendations are made to assist management agencies realize the full potential of long-term quantitative monitoring data for protected area evaluation and evidence-based management.
Keywords: Conservation; Evidence-based management; long-term monitoring; Management effectiveness evaluation; marine protected area; Outcome assessment

Assessing habitat use by snapper (Chrysophrys auratus) from baited underwater video data in a coastal marine park - Terres, Maria A.; E Lawrence; G.R. Hosack; Haywood, Michael D. E.; Russell Babcock (PLOS ONE, 2015)
Baited Underwater Video (BUV) systems have become increasingly popular for assessing marine biodiversity. These systems provide video footage from which biologists can identify the individual fish species present. Here we explore the relevance of spatial dependence and marine park boundaries while estimating the distribution and habitat associations of the commercially and recreationally important snapper species Chrysophrys auratus in Moreton Bay Marine Park during a period when new Marine National Parks zoned as no-take or “green” areas (i.e., areas with no legal fishing) were introduced. BUV studies typically enforce a minimum distance among BUV sites, and then assume that observations from different sites are independent conditional on the measured covariates. In this study, we additionally incorporated the spatial dependence among BUV sites into the modelling framework. This modelling approach allowed us to test whether or not the incorporation of highly correlated environmental covariates or the geographic placement of BUV sites produced spatial dependence, which if unaccounted for could lead to model bias. We fitted Bayesian logistic models with and without spatial random effects to determine if the Marine National Park boundaries and available environmental covariates had an effect on snapper presence and habitat preference. Adding the spatial dependence component had little effect on the resulting model parameter estimates that emphasized positive association for particular coastal habitat types by snapper. Strong positive relationships between the presence of snapper and rock habitat, particularly rocky substrate composed of indurated freshwater sediments known as coffee rock, and kelp habitat reinforce the consideration of habitat availability in marine reserve design and the design of any associated monitoring programs.

Australia’s protected area network fails to adequately protect the world’s most threatened marine fishes - Devitt, Karen R.; Adams, Vanessa M.; PM Kyne (Global Ecology and Conservation, 2015)
In order to maintain ecosystems and biodiversity, Australia has long invested in the development of marine and terrestrial protected area networks. Within this land- and sea-scape, northern Australia represents a global population stronghold for four species of the world’s most threatened marine fish family, the sawfishes (family Pristidae). The distribution of sawfishes across northern Australia has previously only been coarsely estimated, and the adequacy of their representation in protected areas has not been evaluated. The calculated range of each species was intersected with Australia’s marine and terrestrial protected area datasets, and targets of 10% marine and 17% inland range protection were used to determine adequacy of sawfish range protection. Marine targets have been achieved for all species, but the inland range protection targets have not been met for any species. Results indicate that further protection of inland habitats is required in order to improve sawfish protection and habitat connectivity.
Keywords: marine reserves; National parks; Pristidae; Protected areas; Sawfish

Australian sea-floor survey data, with images and expert annotations - Bewley, Michael; Friedman, Ariell; Renata Ferrari; Nicole A. Hill; Renae Hovey; Neville Barrett; Oscar R. Pizarro; Figueira, Will; Meyer, Lisa; Russell Babcock; Bellchambers, Lynda; Byrne, Maria; et al. (Scientific Data, 2015)
This Australian benthic data set (BENTHOZ-2015) consists of an expert-annotated set of georeferenced benthic images and associated sensor data, captured by an autonomous underwater vehicle (AUV) around Australia. This type of data is of interest to marine scientists studying benthic habitats and organisms. AUVs collect georeferenced images over an area with consistent illumination and altitude, and make it possible to generate broad scale, photo-realistic 3D maps. Marine scientists then typically spend several minutes on each of thousands of images, labeling substratum type and biota at a subset of points. Labels from four Australian research groups were combined using the CATAMI classification scheme, a hierarchical classification scheme based on taxonomy and morphology for scoring marine imagery. This data set consists of 407,968 expert labeled points from around the Australian coast, with associated images, geolocation and other sensor data. The robotic surveys that collected this data form part of Australia's Integrated Marine Observing System (IMOS) ongoing benthic monitoring program. There is reuse potential in marine science, robotics, and computer vision research.
Keywords: Biodiversity; Coral reefs; fisheries; Ocean sciences

Australias saltmarshes: a synopsis to underpin the repair and conservation of Australias environmentally, socially and economically important bays and estuaries - Colin Creighton; Chris L Gillies; Ian M. McLeod (2015)
Saltmarshes in this report refers to the mosaic of coastal wetland ecosystems that occupy areas of low energy, intermittent tidal inundation, typically in bays, inlets and estuaries, on sheltered soft substrate foreshores, often at the foreshore in southern Australia and occurring behind mangroves in tropical Australia. Functional role of saltmarshes Saltmarshes serve multiple functions including sediment trapping, nutrient cycling, dissipation of wave energy, fish and prawn nursery, net primary production, carbon sequestration and resting and feeding areas for birds. Saltmarshes are a key component of our estuaries and coastal landscapes and provide connectivity between freshwater to brackish to tidal and sub-tidal ecosystems. This synopsis This report summarises key attributes about our saltmarshes for Queensland (Qld), New South Wales (NSW), Victoria (Vic), Tasmania (Tas) and South Australia (SA) including: Current extent; Losses and changes to the saltmarsh landscapes; Vegetation types and nature of this mosaic landscape; Role in net primary productivity and in Australia’s seascapes; Legislation, regulations and protection mechanisms in each state; Simple indices to represent their benefits and as a basis for developing return on Investment analysis; and Priorities for repair. Resources for preparation of this report were limited. Thus, the study focus could not extend to include temperate saltmarshes in Western Australia and tropical saltmarshes in Western Australia and the Northern Territory. Key findings This report has found that the challenges Australia faces to repair saltmarshes for the benefit of Australian coastal communities are substantial. Key aspects include: Different saltmarsh community types with accompanying different roles and functions occur within and across different states; Knowledge (i.e. extent, mapping and definition) and protection (i.e. legislation, planning and regulations) of saltmarsh community types also vary amongst states, so that a “one size fits all” approach to conservation and to restoration is not appropriate; Community knowledge and appreciation of the value of saltmarshes is low, inhibiting protection, conservation and restoration; and Australia does have some good examples and demonstrations of successful saltmarsh restoration that can serve to underpin the scale-up of restoration activities. Related information Repairing Australia's Saltmarshes - James Cook University and TropWATER - Tropical Water & Aquatic Ecosystem Research Caption - The sun sets over saltpan habitat in north Queensland

Biodiversity: sharks and rays in peril too - PM Kyne; Nicholas J. Bax; N K Dulvy (Nature, 2015)
Your status report on fauna biodiversity (Nature 516, 158–161; 2014) overlooks a group that is causing serious concern among conservationists — sharks, rays and chimaeras. These are particularly vulnerable to fishing and by-catch, in part because they mature late and produce few young. An estimated 24% of this group, known as chondrichthyan fish, are threatened with extinction under the Red List criteria of the International Union for Conservation of Nature. This exceeds the percentage for birds and is comparable to that for mammals. There are insufficient data to determine status in 47% of chondrichthyan fish, and models predict that many of these could also be under threat, given their similar life history and morphology to the listed chondrichthyans. Extinction of ocean fish is hard to verify. There is as yet no documented global extinction of a chondrichthyan, but many populations are locally or regionally extinct (such as sawfishes (Pristidae family); see N. K. Dulvy et al. Aquat. Conserv. http://doi.org/zkc; 2014). Some critically endangered species, including the Pondicherry shark (Carcharhinus hemiodon) in the Indo-West Pacific, have not been recorded in decades and may already be extinct.
Keywords: Conservation biology; fisheries; Research data

Broad-scale impacts of salmon farms on temperate macroalgal assemblages on rocky reefs - Elizabeth S. Oh; Graham J. Edgar; Kirkpatrick, J.B.; Rick D Stuart-Smith; Neville Barrett (Marine Pollution Bulletin, 2015)
Intensive fish culture in open sea pens delivers large amounts of nutrients to coastal environments. Relative to particulate waste impacts, the ecological impacts of dissolved wastes are poorly known despite their potential to substantially affect nutrient-assimilating components of surrounding ecosystems. Broad-scale enrichment effects of salmonid farms on Tasmanian reef communities were assessed by comparing macroalgal cover at four fixed distances from active fish farm leases across 44 sites. Macroalgal assemblages differed significantly between sites immediately adjacent (100 m) to fish farms and reference sites at 5 km distance, while sites at 400 m and 1 km exhibited intermediate characteristics. Epiphyte cover varied consistently with fish farm impacts in both sheltered and exposed locations. The green algae Chaetomorpha spp. predominated near fish farms at swell-exposed sites, whereas filamentous green algae showed elevated densities near sheltered farms. Cover of canopy-forming perennial algae appeared unaffected by fish farm impacts.
Keywords: Aquaculture; Benthic macrofauna; Fishes; invertebrates; Organic pollution; tasmania

Can marine reserves conserve vulnerable sharks in the deep-sea? A case study of Centrophorus zeehaani (Centrophoridae) examined with acoustic telemetry - Ross K Daley; Williams, Alan; Mark Green; Bruce A Barker; Brodie, Pamela (Deep Sea Research Part II: Topical Studies in Oceanography, 2015)
Centrophorus zeehaani is one of at least 10 deep-sea shark species globally suffering major population declines attributable to expanding human resource use. Spatial closures have the potential to contribute to recovery of populations if home range and movements can be studied and understood. We implemented the first passive acoustic tracking study of sharks in the deep ocean (300–700 m depths) to evaluate the effectiveness of a large (~100 km long) fishery closure off southern Australia implemented to protect C. zeehaani. Using an array of 21 moored acoustic receivers, we passively tracked 71 tagged individuals over a 15-month period. Sixty-one sharks were detected repeatedly over an average duration of 408±153 days. The average along-slope range was 19.2±12.2 km and the maximum was 75 km – the full width of the array. Each month an average of 0.71 fewer males were detected; the number of females detected did not vary significantly between months. Individual males left the closure, but returned during the study period. Movement along-slope was influenced by month and release point, with shifts south and eastward occurring during austral winter – particularly by some males. Detection depth was strongly correlated with seafloor depth confirming that synchronous diel vertical migration (night time ascent) between population average depths of 640 m and 340 m occurred mainly on the seafloor. Different individuals occupied different depths on the seafloor. We conclude that the closure studied is effectively located to help conserve C. zeehaani because it has sufficient along-slope extent and depth range to encompass the home range of a high proportion of the individuals in the local population. Our work demonstrates the utility and uncertainties associated with acoustic tracking in the deep ocean, and the need to evaluate species movement and behaviour when relying on spatial closures to meet conservation objectives.
Keywords: Biodiversity; Conservation; Ecology; Migrations; movement; Reproduction

Characterising sediments of a tropical sediment-starved shelf using cluster analysis of physical and geochemical variables - Lynda Radke; Jin Li; Douglas, Grant; Rachel Przeslawski; Scott L Nichol; Justy P W Siwabessy; Z Huang; Trafford, Janice; Watson, Tony; Whiteway, Tanya (Environmental Chemistry, 2015)
Baseline information on habitats is required to manage Australia's northern tropical marine estate. This study aims to develop an improved understanding of seafloor environments of the Timor Sea. Clustering methods were applied to a large data set comprising physical and geochemical variables that describe organic matter (OM) reactivity, quantity and source, and geochemical processes. Arthropoda (infauna) were used to assess different groupings. Clusters based on physical and geochemical data discriminated arthropods better than geomorphic features. Major variations among clusters included grain size and a cross-shelf transition from authigenic-Mn–As enrichments (inner shelf) to authigenic-P enrichment (outer shelf). Groups comprising raised features had the highest reactive OM concentrations (e.g. low chlorin indices and C : N ratios, and high reaction rate coefficients) and benthic algal δ13C signatures. Surface area-normalised OM concentrations higher than continental shelf norms were observed in association with: (i) low δ15N, inferring Trichodesmium input; and (ii) pockmarks, which impart bottom–up controls on seabed chemistry and cause inconsistencies between bulk and pigment OM pools. Low Shannon–Wiener diversity occurred in association with low redox and porewater pH and published evidence for high energy. Highest β-diversity was observed at euphotic depths. Geochemical data and clustering methods used here provide insight into ecosystem processes that likely influence biodiversity patterns in the region.
Keywords: ANOSIM; Backscatter; carbonate banks; Commonwealth Marine Reserve; conceptual model; epifauna; Marine; rare earth elements; subsurface seepage

Comparison of sampling methods to assess benthic marine biodiversity:Are spatial and ecological relationships consistent among sampling gear? - Flannery, Emma; Rachel Przeslawski (Geoscience Australia, 2015)
Marine benthic biodiversity can be measured using a range of sampling methods, including benthic sleds or trawls, grabs, and imaging systems, each of which targets a particular community or habitat. Due to the high cost and logistics of benthic sampling, particularly in the deep sea, studies are often limited to only one or two biological sampling methods. Results of biodiversity studies are used for a range of purposes, including species inventories, environmental impact assessments, and predictive modelling, all of which underpin appropriate marine resource management. However, the generality of marine biodiversity patterns identified among different sampling methods is unknown, as are the associated impacts on management decisions. This report reviews studies that have used two or more sampling methods in order to determine the consistency of their results among gear types, as well as the optimum combination of gear types. In addition, we directly analyse data that were acquired using multiple gear types to examine the consistency of biodiversity patterns among different gear types. These data represent two regions: 1) Joseph Bonaparte Gulf (JBG) in northern Australia, and 2) Icelandic waters as part of the Benthic Invertebrates of Icelandic Waters (BIOICE) program. For each dataset, we investigate potential patterns of biodiversity (measured by species richness, diversity indices, abundance, and community structure) in relation to environmental variables such as depth, geomorphology, and substrate.

Complete mitochondrial genome of the Critically Endangered Smalltooth Sawfish Pristis pectinata (Rajiformes: Pristidae) - Xiao Chen; Wiley, Tonya; PM Kyne; Pierre Feutry (Mitochondrial DNA, 2015)
In this study we describe the first complete mitochondrial sequence of the Critically Endangered Smalltooth Sawfish Pristis pectinata. It is 16,802 bp in length and contains all 37 genes found in typical vertebrate mitogenomes. The nucleotide composition of the coding strand is 31.1% A, 26.0% C, 13.1% G and 28.9% T. There are 29 bp overlaps and 38 short intergenic spaces dispersed in the mitogenome. Two start codons (ATG and GTG) and two stop codons (TAG and TAA/T) were found in the protein-coding genes. The length of the 22 tRNA genes range from 67 bp (tRNASer2) to 75 bp (tRNALeu1). The control region is 1102 bp in length with high A + T (62.0%) and poor G (13.5%) content.
Keywords: Mitochondrial genome; Pristis pectinata; threatened species

Complete mitochondrial genome of the Endangered Narrow Sawfish Anoxypristis cuspidata (Rajiformes: Pristidae) - Xiao Chen; PM Kyne; Richard D. Pillans; Pierre Feutry (Mitochondrial DNA, 2015)
In this study, we describe the first complete mitochondrial sequence for the Endangered Narrow Sawfish Anoxypristis cuspidata. It is 17,243 bp in length and contains 13 protein-coding genes, two rRNA genes, 22 tRNA genes, and a control region with the common vertebrate mitogenomic organization. A total of 30 bp overlaps and 28 bp short intergenic spaces are located between all genes. The overall base composition is 32.7% A, 25.7% C, 12.9% G, and 28.6% T. Two start codons (ATG and GTG) and two stop codons (TAG and TAA/T) were used in all protein-coding genes. The origin of L-strand replication (OL) sequence (38 bp) formed a hairpin structure (13 bp stem and 12 bp loop) to initiate the replication of L-strand. Read More: http://informahealthcare.com/doi/abs/10.3109/19401736.2014.1003898
Keywords: Mitochondrial genome; noxypristis cuspidata; threatened species

The cumulative effect of trawl fishing on a multispecies fish assemblage in south-eastern Australia - Scott D Foster; Piers K Dunstan; Althaus, Franziska; Williams, Alan (Journal of Applied Ecology, 2015)
Summary  Understanding the effect of anthropogenic pressure on animal assemblages over time is a challenging problem that integrates human activities and community ecology. Our ability to make informed decisions for managing pressures depends on estimating their ecological effects, and a rigorous and objective approach should be used. There are three requirements for this type of approach to be successful: sufficient biological and ecological data, congruent data describing human activity and an appropriate statistical method that can link the ecological information to the pressures. In this work, we explore the effects of cumulative bottom-trawl fishing on fish assemblages over a 20-year period. The analysis captures assemblage responses during the early period of the fishery's development and shows the changes in the abundance of many species as a small and coherent set of ‘archetypical’ responses to cumulative pressure.  The effect of the cumulative pressure is heterogeneous: some archetypical responses show consistent decline with increased fishing effort, some are less sensitive, and some show an increase in abundance.  Some, but not all, archetypical response groups are composed of species with similar ecological and life-history traits. Most obviously, the archetype showing greatest decline in abundance is made up of species that have the highest mean values of generation time, oldest age at maturity and longest life span.  Applications of the methods include identifying spatially explicit system-level trade-offs – between species, species groups (archetypes) and fishery subareas – for ecosystem-based management.  Synthesis and applications The impact of fishing pressure, accumulated over time, induces heterogeneous patterns of change in fish assemblage composition. The patterns of change are grouped into ‘archetypical response groups’ to provide an interpretable and robust description. The composition of the species groups show that life-history traits are indicative but do not always provide a complete description of how a species might respond to the pressure.
Keywords: cumulative impacts; ecosystem-based fisheries management; fish assemblage; multispecies; Species archetype model; species traits; trawl fishing

Defining the connectivity of Australia’s hammerhead sharks - Fact sheet - Nicholas J. Bax (2015)
Defining the boundaries of hammerhead shark populations will bring scientists closer to assessing the status of these unique and susceptible species.   Hammerhead sharks are known to swim large distances, including across the open ocean. Sharks from Australia may therefore mix with sharks from Indonesia, Papua New Guinea and islands of the Pacific. Understanding these connections is central to providing information on the status of hammerhead shark populations to support Australian and international conservation and management initiatives. A project led by the Australian Institute of Marine Science will use tagging and genetic sampling to see how hammerhead sharks are connected. The project findings will be combined with biological, ecological and fisheries data to assess the stock structure and population status of hammerhead sharks in Australian waters. The project is part of the National Environmental Science Programme (NESP) Marine Biodiversity Hub, an Australian Government initiative that aims to improve the knowledge of key marine species and ecosystems to underpin their management and protection.

Demographic history and the South Pacific dispersal barrier for school shark (Galeorhinus galeus) inferred by mitochondrial DNA and microsatellite DNA mark - Hernandez, Sebastian; Ross K Daley; Walker, Terry; Braccini, Matias; Varela, Andrea; Malcolm P. Francis; Ritchie, Peter A. (Fisheries Research, 2015)
We used mitochondrial DNA (mtDNA) control region (CR) sequences and genotypes from eight microsatellite DNA (msatDNA) loci to determine the genetic structure of the school shark (Galeorhinus galeus) in New Zealand, Australia and Chile. The estimates of mtDNA haplotype and nucleotide diversity were very similar in New Zealand (h = 0.735 ± 0.032, π = 0.001 ± 0.001) and Australia (h = 0.729 ± 0.027, π = 0.001 ± 0.001), but in Chile they were higher (h = 0.800 ± 0.089, π = 0.002 ± 0.001). The haplotype genealogy showed evidence of two distinct clades, New Zealand and Australia combined (clade 1), and Chile (clade 2). A power analysis suggested that sample sizes were large enough to detect any significant differences within clade 1. Neutrality test, mismatch distribution, and demographic reconstructions based on a coalescence approach, suggested that the Oceania population (clade 1) went through a period of population expansion, whereas the population size of the Chile population (clade 2) has been relatively stable over the last 20,000 years. Data from microsatellite loci also supported the separation of the Oceania and Chile populations. Principal component analysis suggested that there might also be a separation of groups within clade 1, which was not statistically significant (P = 0.434). The genetic data reported in this study supported the model of a single G. galeus stock in New Zealand and Australia. Our findings were consistent with previous tagging data that showed individual G. galeus migrate across the Tasman Sea between Australia and New Zealand, and at least some of these migration events result in successful reproduction.
Keywords: Genetic connectivity; Genetic structure; Population; Stock

Designing Environmental Research for Impact - Campbell, C.A.; Lefroy, E.C.; Caddy-Retalic, S.; Nicholas J. Bax; Doherty, P.J.; Douglas, M.M.; Johnson, D.; Possingham, H.P.; Specht, A.; Tarte, D.; West, J. (Science of The Total Environment, 2015)
Transdisciplinary research, involving close collaboration between researchers and the users of research, has been a feature of environmental problem solving for several decades, often spurred by the need to find negotiated outcomes to intractable problems. In 2005, the Australian government allocated funding to its environment portfolio for public good research, which resulted in consecutive four-year programmes (Commonwealth Environmental Research Facilities, National Environmental Research Program). In April 2014, representatives of the funders, researchers and research users associated with these programmes met to reflect on eight years of experience with these collaborative research models. This structured reflection concluded that successful multi-institutional transdisciplinary research is necessarily a joint enterprise between funding agencies, researchers and the end users of research. The design and governance of research programmes need to explicitly recognise shared accountabilities among the participants, while respecting the different perspectives of each group. Experience shows that traditional incentive systems for academic researchers, current trends in public sector management, and loose organisation of many end users, work against sustained transdisciplinary research on intractable problems, which require continuity and adaptive learning by all three parties. The likelihood of research influencing and improving environmental policy and management is maximised when researchers, funders and research users have shared goals; there is sufficient continuity of personnel to build trust and sustain dialogue throughout the research process from issue scoping to application of findings; and there is sufficient flexibility in the funding, structure and operation of transdisciplinary research initiatives to enable the enterprise to assimilate and respond to new knowledge and situations.
Keywords: Collaborative; Flexible; Knowledge brokering; Knowledge management; Multi-institutional; Participatory; Research strategy; Transdisciplinary

Developing a toolbox of predictive models for the monitoring and management of KEFs and CMRs in the North and North-west regions - Scientific Workshop Report - Rachel Przeslawski; Karen J Miller; Scott L Nichol; Phil J. Bouchet; Z Huang; Johnathan T. Kool; Ben Radford; Michele Thums (2015)
A scientific workshop for NESP Project D1 ‘Developing a toolbox of predictive models for the monitoring and management of KEFs and CMRs in the North and North-west regions’ was held at Geoscience Australia 9-10 September 2015. The objectives of the workshop were to discuss future research priorities for the North and North-West regions and to define current knowledge gaps by consolidating existing datasets from AIMS, GA and UWA. Several robust datasets for the North and North-West region were identified which may be used to validate, refine, or extend existing models, particularly in the Oceanic Shoals CMR and along the North-west coastline, including the Kimberley CMR. There are still large regions for which very little scientific information exists, notably the Argo Rowley Terrace CMR and other deep-sea areas. However, when balanced against stakeholder interests and marine management priorities, data-poor CMRs closer to the coast such as the Kimberley and 80 Mile Beach CMRs are the most likely candidates for future research.

Distinguishing geographical range shifts from artefacts of detectability and sampling effort - Amanda E. Bates; Bird, Tomas J.; Rick D Stuart-Smith; Wernberg, Thomas; Sunday, Jennifer M.; Neville Barrett; Graham J. Edgar; Frusher, Stewart; Alistair J Hobday; Gretta Pecl; Smale, Dan A.; McCarthy, Michael (Diversity and Distributions, 2015)
Aim The redistribution of species with climate change is well documented. Even so, the relative contribution of species detectability to the variation in measured range shift rates among species is poorly understood. How can true range shifts be discerned from sampling artefacts? Methods We simulate range shifts for species which differ in their abundance for comparison to patterns derived from empirical range shift data from two regional-scale (100s km) empirical studies. We demonstrate the use of spatial occupancy data in a distance-to-edge (DTE) model to assess changes in geographical range edges of fish species within a temperate reef fish community. Results Simulations identified how sampling design can produce relatively larger error in range shift estimates in less abundant species, patterns that correspond with those observed in real data. Application of the DTE model allowed us to estimate the location of the true range edge with high accuracy in common species. In addition, upper confidence bounds for range edge estimates identified species with range edges that have likely shifted in location. Conclusions Simulation and modelling approaches used to quantify the level of confidence that can be placed in observed range shifts are particularly valuable for studies of marine species, where observations are typically few and patchy. Given the observed variability in range shift estimates, the inclusion of confidence bounds on estimates of geographical range edges will advance our capacity to disentangle true distributional change from artefacts of sampling design.
Keywords: Climate warming; extreme value statistics; range edge estimation; sampling methodology

Drifting baited stereo-videography: a novel sampling tool for surveying pelagic wildlife in offshore marine reserves - Phil J. Bouchet; Jessica J. Meeuwig (Ecosphere, 2015)
We present a novel system of drifting pelagic baited stereo-video cameras that operate in deep-water, topographically complex environments typically considered inaccessible for sampling. The instruments are portable, semi-autonomous and inexpensive, allowing the recording of high-definition video footage in near-real time and over broad stretches of ocean space. We illustrate their benefits and potential as non-extractive monitoring tools for offshore marine reserves with a pilot study conducted within the newly established Perth Canyon Commonwealth Marine Reserve, southwestern Australia (328 S, 1158 E). Using occupancy and maximum entropy models, we predict the distribution of midwater fishes and sharks and show that their most suitable habitat encompasses a wider fraction of the canyon head than is covered by park boundaries. Our proof-of-concept study demonstrates that drifting pelagic stereo-video cameras can serve as appropriate field platforms for the construction of species distribution models with implications for ocean zoning and conservation planning efforts.
Keywords: biodiversity monitoring; marine reserve; marine spatial planning; MaxEnt; mid-water BRUVS; occupancy modeling; offshore sampling; pelagic fish and sharks; Perth Canyon; stereo-videography; Western Australia; wildlife conservation

Enhancing access to relevant marine information: Developing a service for searching, aggregating and filtering collections of linked open marine data – Scoping study - Johnathan T. Kool (2015)
This project seeks to improve the searchability, discoverability and delivery of marine information through the development of an online service capable of searching, filtering and organizing linked open marine data. The service would also provide the capability of forwarding the collections of discovered data to web services for subsequent processing into products of higher utility.  This work will improve access to existing data collections, and will facilitate the development of new applications by acting as an aggregator of links to sources of marine information.  The work will benefit managers (i.e. Department of the Environment staff) by providing fast and simple access to a wide range of relevant marine information products, and offering a means of quickly synthesizing and aggregating information from multiple sources.

An exon-capture system for the entire class Ophiuroidea - Andrew F. Hugall; Tim O'Hara; Hunjan, Sumitha; Nilsen, Roger; Adnan Moussalli (Molecular Biology and Evolution, 2015)
Exon-capture studies have typically been restricted to relatively shallow phylogenetic scales due primarily to hybridization constraints. Here, we present an exon-capture system for an entire class of marine invertebrates, the Ophiuroidea, built upon a phylogenetically diverse transcriptome foundation. The system captures approximately 90% of the 1,552 exon target, across all major lineages of the quarter-billion-year-old extant crown group. Key features of our system are 1) basing the target on an alignment of orthologous genes determined from 52 transcriptomes spanning the phylogenetic diversity and trimmed to remove anything difficult to capture, map, or align; 2) use of multiple artificial representatives based on ancestral state reconstructions rather than exemplars to improve capture and mapping of the target; 3) mapping reads to a multi-reference alignment; and 4) using patterns of site polymorphism to distinguish among paralogy, polyploidy, allelic differences, and sample contamination. The resulting data give a well-resolved tree (currently standing at 417 samples, 275,352 sites, 91% data-complete) that will transform our understanding of ophiuroid evolution and biogeography.
Keywords: Echinodermata; hybrid enrichment; phylogenomics

Exploring the Oceanic Shoals Commonwealth Marine Reserve Brochure - Fact sheet - M Julian Caley (2015)
Information and knowledge for much of the North and North-west regions of the Commonwealth Marine Reserve network is severely limited. In September 2012, the Marine Hub undertook a 21 day survey on the AIMS vessel RV Solander which included the Oceanic Shoals CMR, with the aim of contributing knowledge to support the Australian Government’s marine bioregional plans. Now that most of the follow-on research from this survey has been completed, a full-colour brochure has been produced that reports on the highlights of this voyage including sponge hotspots, vulnerable or near threatened hard coral species, new banks and pinnacles.  The brochure has been designed to present the highlights of what was learned in a way that is readily accessible to both managers of Australia’s marine estate and the general public that has an interest in marine habitats, in this case, one for which there is very little public awareness or educational resources.  Where can I get a copy? <a href="mailto:info@nespmarine.edu.au?subject=Please%20send%20me%20a%20copy%20of%20the%20Oceanic%20Shoals%20Commonwealth%20Marine%20Reserve%20brochure&body=Name%3A%0AAddresss%3A%0ANumber%20of%20copies%3A%0A%0AHow%20did%20you%20find%20out%20about%20the%20brochure%3F%0A%0AThanks!" rel="nofollow">Request a copy of the brochure "Exploring the Oceanic Shoals Commonwealth Marine Reserve" or download a pdf version

Exploring the status of Australia’s hammerhead sharks - Michelle R. Heupel; William T White; Colin Simpfendorfer (2015)
Hammerhead sharks are the focus of conservation management in Australian waters as the result of recent listing on CITES and CMS. However, the state of knowledge of hammerhead sharks in Australia requires further exploration. Data on hammerhead interactions with fisheries, life history and ecology have been gathered to address this need. Data revealed significant gaps in areas sampled and limited understanding of the dynamics of species presence/distribution relative to habitat features or environmental conditions. Use of different habitats by different sex or size groups makes refining the distribution and abundance of hammerhead species difficult. Collected data were used to construct a series of conceptual models of population structure of hammerhead sharks in Australia and adjacent countries. This exercise revealed an urgent need to define connectivity of hammerhead shark populations within and beyond Australia to ensure management can be applied at the appropriate scope and scale.

Fostering the repair of Australia’s saltmarshes and shellfish reefs - Fact sheet - Nicholas J. Bax (2015)
Scientists are charting the challenges and benefits of repairing nearshore ecosystems to inspire and guide the resurgence of these wellsprings of marine health and productivity. Shellfish reefs and saltmarshes are vital to the health of Australia’s bays and estuaries, supporting marine life and fish production, regulating water quality and curbing coastal erosion. But these valuable nearshore eco-systems are in serious decline due to coastal development and activities such as intensive agriculture. Reparation efforts have begun in some locations, with the promise of significant benefits. Further projects, however, hinge on increasing awareness and joint investment among governments, businesses and the community.

Four-dimensional connectivity modelling with application to Australia's north and northwest marine environments - Johnathan T. Kool; Scott L Nichol (Environmental Modelling & Software, 2015)
A fully four-dimensional (3D × time) object-oriented biophysical dispersal model was developed to simulate the movement of marine larvae over semi-continuous surfaces. The model is capable of handling massive numbers of simulated larvae, can accommodate diverse life history patterns and distributions of characteristics, and saves point-level information to a relational database management system. The model was used to study Australia's northwest marine region, with attention given to connectivity patterns among Australia's north-western Commonwealth Marine Reserves (CMRs). Animations of larval movement near the Gascoyne canyon CMR, dispersal surfaces over depth and time for CMRs and Key Ecological Features in the northwest, as well as matrices of connectivity values among CMRs are shown. The matrices are further analysed to identify the sensitivity and elasticity of their values. The results generated by this model can aid in designing and managing marine protected area networks that incorporate extensive and complex benthic terrain (including the identification of marine ‘corridors’), and for developing targeted field sampling strategies.
Keywords: Australia; connectivity; Dispersal; Individual-based model; Marine; Seascape

Freshwater sharks and rays - Lucifora, Luis O.; Carvalho, Marcelo R. de; PM Kyne; William T White (Current Biology, 2015)
Hang on, I thought sharks and rays only live in the ocean? That’s true for about 95%. However, there are species of elasmobranchs (sharks and rays) that occur regularly at low salinities, often beyond the tidal reaches of the sea. These make up around 5% of living elasmobranchs (roughly 56 out of 1154 described species). Species that are confined to freshwaters are termed obligate freshwater species, and comprise all the freshwater stingrays (family Potamotrygonidae) and several stingrays (Dasyatidae). Species that can tolerate a wide range of salinities, from freshwater to brackish and/or marine waters, are termed ‘euryhaline species’. Euryhaline species include sawfishes (Pristidae), several whaler sharks (Carcharhinidae), one skate (Rajidae), and a number of stingrays (Dasyatidae). They range in maximum size from only 20–30 cm disc width in several freshwater stingrays, to at least 6.5 m total length in the Largetooth Sawfish (Pristis pristis).

Functional traits reveal early responses in marine reserves following protection from fishing - Coleman, M. A.; Amanda E. Bates; Rick D Stuart-Smith; Hamish A. Malcolm; David Harasti; Alan Jordan; Nathan A. Knott; Graham J. Edgar; Kelaher, B. P. (Diversity and Distributions, 2015)
Aim Evaluating the effectiveness of marine reserves in achieving conservation goals is challenged by the decadal scales over which biological systems respond following protection. Given that trophic interactions underpin community responses following protection and that complex ecological interactions make responses difficult to identify, quantifying changes in species traits may provide detail missed by traditional diversity measures, including information relevant to ecosystem functioning. We determine whether this is the case by comparing community metrics based on functional traits to taxonomic diversity measures associated with ‘no take’ marine reserves and partially protected, fished areas along eight degrees of latitude. Location Eighteen ‘no take’ marine reserves and 14 partially protected, fished areas along the east coast of Australia. Method We use two independent datasets from shallow and deep coastal rocky reefs to analyse trait-based metrics and taxonomic diversity from sites inside reserves to sites in partially protected, fished areas. Results Taxonomic diversity (species diversity and richness) and trait-based multimetrics (functional richness and dispersion) showed no difference with level of protection. Total fish abundance responded positively to protection, but only on shallow reefs. Comparing values of individual functional traits implied a return of larger bodied species of fish in protected areas and an increase in trophic level. The latter was significant on deeper reefs and was strongly correlated with age of protected area. Thus, recovery responses were largely associated with community mean functional trait values, highlighting the value of trait-based approaches for detecting change, when no differences in traditional taxonomic diversity measures were apparent. Main conclusions We empirically demonstrate that functional traits can elucidate early conservation outcomes, when traditional multimetric diversity indices do not distinguish protected and fished communities. Ecologically relevant but sensitive metrics are fundamental to allow information to be incorporated into adaptive management strategies, which often occur on political rather than biological time-scales.
Keywords: Conservation; effectiveness; fish; marine reserve; Protected areas

A hierarchical risk assessment framework for ecosystem based management - Piers K Dunstan; Jeffrey M Dambacher; Nicholas J. Bax; Tony Smith; Elizabeth A. Fulton; Paul Hedge; Alistair J Hobday; Scott D Foster (2015)
There is general agreement that assessment of risk in the marine environment needs to move toward an ecosystem approach to account for the single and cumulative impacts from multiple sectors that operate within the world’s oceans. Despite there being fewer marine activities than in terrestrial environments, marine systems are challenging to manage on an ecosystem basis as a result of their complexity, high degree of connectivity and difficulties associated with observing ocean processes, flora and fauna. These challenges can make it difficult for researchers to know how to make best-use of available scientific information to inform policy makers about options for ecosystem management. A broad range of scientific tools and approaches have emerged to attempt to meet these differing needs and together these challenges and choices have stymied decision makers. There is a clear need to develop a process that can assist governments and other decision makers to reduce the uncertainty around the risks of significant impacts in ecosystem based management. An important consideration in developing a framework for risk-based approach to ecosystem management is clarifying the terminology associated with the assessment, this is particularly important for facilitating collaboration between researchers and policy makers. We suggest that a productive way to approach this would be to use a hierarchical approach where a range of tools can be used to identify activities that have a high risk of significant impact. We use values (eg conservation, resource or community) that have been described through an expert process to identify the relevant subsystem for management. The first level builds a conceptual model of the relevant subsystem and identifies the pressures that act on that subsystem. The second level uses mathematical qualitative models to refine the understanding of the system and to reduce the uncertainty around the system structure. The final level uses quantitative and qualitative models to identify specific thresholds, management trigger points and scenarios. Each level reduces the uncertainty in decisions but increase the costs and time taken. The hierarchical framework proposed in this paper provides scientists and policy makers with guidance and a common lexicon for assessing cumulative risks and estimating impacts to marine ecosystems. The framework provides for a cost-effective and consistent approach to assessments, accommodating a broad range of marine environment assessment cases, leading to priorities for action. The approach acknowledges the importance of ecosystem models for estimating cumulative risks and provides a frame for understanding how they can be cost-effectively and consistently applied to estimate impacts and improve understanding.

Identifying indicators and essential variables for marine ecosystems - K.R. Hayes; Jeffrey M Dambacher; G.R. Hosack; Nicholas J. Bax; Piers K Dunstan; Elizabeth A. Fulton; Peter A. Thompson; Hartog, J.R.; Alistair J Hobday; R. W. Bradford; Scott D Foster; Paul Hedge; et al. (Ecological Indicators, 2015)
Identifying essential biological variables in marine ecosystems is harder than essential ocean variables because choices about the latter are guided by the needs of global oceanic models, and the number of candidate variables to choose from is much smaller. We present a process designed to assist managers identify biological indicators and essential variables for marine ecosystems, and demonstrate its application to Australia's Exclusive Economic Zone. The process begins with a spatially explicit description of key ecological systems and predicts how these systems are impacted by anthropogenic pressures. The process does not require experts to agree on the system's structure or the activities that threaten the ecosystem. Rather it defines a suite of pressure scenarios that accommodate uncertainty in these aspects, and seeks to identify indicators that are predicted to respond in a consistent fashion across these scenarios. When the process is applied at national or regional scales, essential biological variables emerge as the set of consistent indicators that are common to similar but spatially distinct systems.
Keywords: ecological indicators; Essential variables; Monitoring; Ecosystem health

Implications of sponge biodiversity patterns for the management of a marine reserve in northern Australia - Rachel Przeslawski; Alvarez, Belinda; Johnathan T. Kool; Tom Bridge; M Julian Caley; Scott L Nichol (PLOS ONE, 2015)
Marine reserves are becoming progressively more important as anthropogenic impacts continue to increase, but we have little baseline information for most marine environments. In this study, we focus on the Oceanic Shoals Commonwealth Marine Reserve (CMR) in northern Australia, particularly the carbonate banks and terraces of the Sahul Shelf and Van Diemen Rise which have been designated a Key Ecological Feature (KEF). We use a species-level inventory compiled from three marine surveys to the CMR to address several questions relevant to marine management: 1) Are carbonate banks and other raised geomorphic features associated with biodiversity hotspots? 2) Can environmental (depth, substrate hardness, slope) or biogeographic (east vs west) variables help explain local and regional differences in community structure? 3) Do sponge communities differ among individual raised geomorphic features? Approximately 750 sponge specimens were collected in the Oceanic Shoals CMR and assigned to 348 species, of which only 18% included taxonomically described species. Between eastern and western areas of the CMR, there was no difference between sponge species richness or assemblages on raised geomorphic features. Among individual raised geomorphic features, sponge assemblages were significantly different, but species richness was not. Species richness showed no linear relationships with measured environmental factors, but sponge assemblages were weakly associated with several environmental variables including mean depth and mean backscatter (east and west) and mean slope (east only). These patterns of sponge diversity are applied to support the future management and monitoring of this region, particularly noting the importance of spatial scale in biodiversity assessments and associated management strategies.

Isolation by resistance across a complex coral reef seascape - Luke Thomas; Kennington, W. Jason; Stat, Michael; Wilkinson, Shaun P.; Johnathan T. Kool; Gary A. Kendrick (Proceedings of the Royal Society B: Biological Sciences, 2015)
A detailed understanding of the genetic structure of populations and an accurate interpretation of processes driving contemporary patterns of gene flow are fundamental to successful spatial conservation management. The field of seascape genetics seeks to incorporate environmental variables and processes into analyses of population genetic data to improve our understanding of forces driving genetic divergence in the marine environment. Information about barriers to gene flow (such as ocean currents) is used to define a resistance surface to predict the spatial genetic structure of populations and explain deviations from the widely applied isolation-by-distance model. The majority of seascape approaches to date have been applied to linear coastal systems or at large spatial scales (more than 250 km), with very few applied to complex systems at regional spatial scales (less than 100 km). Here, we apply a seascape genetics approach to a peripheral population of the broadcast-spawning coral Acropora spicifera across the Houtman Abrolhos Islands, a high-latitude complex coral reef system off the central coast of Western Australia. We coupled population genetic data from a panel of microsatellite DNA markers with a biophysical dispersal model to test whether oceanographic processes could explain patterns of genetic divergence. We identified significant variation in allele frequencies over distances of less than 10 km, with significant differentiation occurring between adjacent sites but not between the most geographically distant ones. Recruitment probabilities between sites based on simulated larval dispersal were projected into a measure of resistance to connectivity that was significantly correlated with patterns of genetic divergence, demonstrating that patterns of spatial genetic structure are a function of restrictions to gene flow imposed by oceanographic currents. This study advances our understanding of the role of larval dispersal on the fine-scale genetic structure of coral populations across a complex island system and applies a methodological framework that can be tailored to suit a variety of marine organisms with a range of life-history characteristics.
Keywords: Acropora spicifera; connectivity; Dispersal; spatial conservation management

Large-Scale Geographic Variation in Distribution and Abundance of Australian Deep-Water Kelp Forests - Marzinelli, Ezequiel M.; Williams, Stefan B.; Russell Babcock; Neville Barrett; Craig R. Johnson; Alan Jordan; Gary A. Kendrick; Oscar R. Pizarro; Smale, Dan A.; Peter D. Steinberg (PLOS ONE, 2015)
Despite the significance of marine habitat-forming organisms, little is known about their large-scale distribution and abundance in deeper waters, where they are difficult to access. Such information is necessary to develop sound conservation and management strategies. Kelps are main habitat-formers in temperate reefs worldwide; however, these habitats are highly sensitive to environmental change. The kelp Ecklonia radiate is the major habitat-forming organism on subtidal reefs in temperate Australia. Here, we provide large-scale ecological data encompassing the latitudinal distribution along the continent of these kelp forests, which is a necessary first step towards quantitative inferences about the effects of climatic change and other stressors on these valuable habitats. We used the Autonomous Underwater Vehicle (AUV) facility of Australia’s Integrated Marine Observing System (IMOS) to survey 157,000 m2 of seabed, of which ca 13,000 m2 were used to quantify kelp covers at multiple spatial scales (10–100 m to 100–1,000 km) and depths (15–60 m) across several regions ca 2–6° latitude apart along the East and West coast of Australia. We investigated the large-scale geographic variation in distribution and abundance of deep-water kelp (>15 m depth) and their relationships with physical variables. Kelp cover generally increased with latitude despite great variability at smaller spatial scales. Maximum depth of kelp occurrence was 40–50 m. Kelp latitudinal distribution along the continent was most strongly related to water temperature and substratum availability. This extensive survey data, coupled with ongoing AUV missions, will allow for the detection of long-term shifts in the distribution and abundance of habitat-forming kelp and the organisms they support on a continental scale, and provide information necessary for successful implementation and management of conservation reserves.

Lessons learned at the interface of marine ecology and environmental management in Australia - Johnathan T. Kool; Sharon A Appleyard; Nicholas J. Bax; Ford, John; Hillman, Karen; Howe, Steffan; Emma L Jackson; Kirkman, Hugh; Parr, Amanda; Slawinski, Dirk; Stafford-Bell, Richard (Bulletin of Marine Science, 2015)
Marine scientists and environmental managers engaged in a roundtable discussion at the Australian Marine Sciences Association conference in July 2014 to identify areas where linkages could be improved between the two groups. Here, we summarize the key themes and outcomes from the discussion, including the need to clearly define management objectives, to identify the scale of the issue, to conduct effective science communication, to address uncertainty, and to perform iterative engagement. We also discuss some of the challenges inherent in establishing new linkages, and provide a set of examples where effective collaborations have been achieved between marine ecologists and environmental managers working in Australia.

Loss of native rocky reef biodiversity in Australian metropolitan embayments - Rick D Stuart-Smith; Graham J. Edgar; Jemina F. Stuart-Smith; Neville Barrett; Fowles, Amelia E.; Nicole A. Hill; Antonia T. Cooper; Myers, Andrew P.; Elizabeth S. Oh; Pocklington, Jacqui B.; Russell J. Thomson (Marine Pollution Bulletin, 2015)
Urbanisation of the coastal zone represents a key threat to marine biodiversity, including rocky reef communities which often possess disproportionate ecological, recreational and commercial importance. The nature and magnitude of local urban impacts on reef biodiversity near three Australian capital cities were quantified using visual census methods. The most impacted reefs in urbanised embayments were consistently characterised by smaller, faster growing species, reduced fish biomass and richness, and reduced mobile invertebrate abundance and richness. Reef faunal distribution varied significantly with heavy metals, local population density, and proximity to city ports, while native fish and invertebrate communities were most depauperate in locations where invasive species were abundant. Our study adds impetus for improved urban planning and pollution management practises, while also highlighting the potential for skilled volunteers to improve the tracking of changes in marine biodiversity values and the effectiveness of management intervention.
Keywords: Anthropogenic stressors; Ecology; Heavy metals; Invasive species; Temperate; Urbanisation

Low-cost action cameras can be used for accurate underwater stereo measurements of fish - Tom B. Letessier; Juhel, Jean-Baptiste; Vigliola, Laurent; Jessica J. Meeuwig (Journal of Experimental Marine Biology and Ecology, 2015)
Small action cameras have received interest for use in underwater videography because of their low-cost, standardised housing, widespread availability and small size. Here, we assess the capacity of GoPro action cameras to provide accurate stereo-measurements of fish in comparison to the Sony handheld cameras that have traditionally been used for this purpose. Standardised stereo-GoPro and Sony systems were employed to capture measurements of known-length targets in a pool to explore the influence of the type of camera, distance to camera rig, angle to the optical axis and target speed on measurement accuracy. The capacity to estimate fish length in situ was also compared by measuring the same fish on a coral reef with two baited remote underwater video systems, each fitted with both a GoPro and a Sony camera system. Pool trials indicated that the GoPros were generally less accurate than the Sonys. Accuracy decreased with increased angles and distance for both systems but remained reasonably low (< 7.5%) at 5 m distance and 25° angle for GoPros. Speed of target movement did not result in any consistent decrease in accuracy. In situ measurements revealed a strong correlation (R2 = 0.94) between Sony and GoPro length measurements of the same individual fish, with a slope not different from 1 and an intercept not different from 0, suggesting that GoPro measurement errors do not result in a consistent bias at the level of individual fish. Moreover, the investigation of kernel density functions of the length distribution of the entire fish assemblage indicated that difference in measurement accuracy becomes negligible for purposes of comparing population size structure. We suggest a measurement protocol for the use of GoPro stereo-camera systems that improves accuracy, where distance to target is limited to 5 m and angle to optical axis is restricted to 25°. For distances up to 7 m, angles should be restricted to 15°. This protocol supports the use of small action cameras such as the GoPro system, providing reductions in cost and increases in effective sampling efforts, compared with traditional rigs based on relatively expensive handheld cameras.
Keywords: body size; length; monitoring; stereo-photogrammetry; videography

Mapping habitats and developing baselines in offshore marine reserves with little prior knowledge: a critical evaluation of a new approach - E Lawrence; Keith R Hayes; Vanessa L Lucieer; Scott L Nichol; Jeffrey M Dambacher; Nicole A. Hill; Neville Barrett; Johnathan T. Kool; Justy P W Siwabessy (PLOS ONE, 2015)
he recently declared Australian Commonwealth Marine Reserve (CMR) Network covers a total of 3.1 million km2 of continental shelf, slope, and abyssal habitat. Managing and conserving the biodiversity values within this network requires knowledge of the physical and biological assets that lie within its boundaries. Unfortunately very little is known about the habitats and biological assemblages of the continental shelf within the network, where diversity is richest and anthropogenic pressures are greatest. Effective management of the CMR estate into the future requires this knowledge gap to be filled efficiently and quantitatively. The challenge is particularly great for the shelf as multibeam echosounder (MBES) mapping, a key tool for identifying and quantifying habitat distribution, is time consuming in shallow depths, so full coverage mapping of the CMR shelf assets is unrealistic in the medium-term. Here we report on the results of a study undertaken in the Flinders Commonwealth Marine Reserve (southeast Australia) designed to test the benefits of two approaches to characterising shelf habitats: (i) MBES mapping of a continuous (~30 km2) area selected on the basis of its potential to include a range of seabed habitats that are potentially representative of the wider area, versus; (ii) a novel approach that uses targeted mapping of a greater number of smaller, but spatially balanced, locations using a Generalized Random Tessellation Stratified sample design. We present the first quantitative estimates of habitat type and sessile biological communities on the shelf of the Flinders reserve, the former based on three MBES analysis techniques. We contrast the quality of information that both survey approaches offer in combination with the three MBES analysis methods. The GRTS approach enables design based estimates of habitat types and sessile communities and also identifies potential biodiversity hotspots in the northwest corner of the reserve’s IUCN zone IV, and in locations close to shelf incising canyon heads. Design based estimates of habitats, however, vary substantially depending on the MBES analysis technique, highlighting the challenging nature of the reserve’s low profile reefs, and improvements that are needed when acquiring MBES data for small GRTS locations. We conclude that the two survey approaches are complementary and both have their place in a successful and flexible monitoring strategy; the emphasis on one method over the other should be considered on a case by case basis, taking into account the survey objectives and limitations imposed by the type of vessel, time available, size and location of the region where knowledge is required.

Measuring the extent of a Social License to Operate: The influence of marine biodiversity offsets in the oil and gas sector in Western Australia - Richert, Claire; Abbie A Rogers; Burton, Michael (Resources Policy, 2015)
Mining companies throughout the world often face a high socio-political risk, in particular because of their impact on the environment. A key indicator of exposure to such risk is a company׳s Social License to Operate (SLO). If a company meets its consumer, shareholders and other stakeholders׳ expectations regarding environmental management, it can gain a SLO. The SLO is an implicit contract between parties which reduces the risk of socio-political challenges to the actions of the company. Here, we apply this concept to a case study of the oil and gas sector in Western Australia, where we evaluate the strength of the SLO granted by the West Australian population to this industry. Our results suggest that, on average, people are not likely to oppose oil and gas projects, because they are economically beneficial for the State. However, it does not achieve as high an evaluation on social legitimacy. We subsequently examine whether the use of marine biodiversity offsets by the oil and gas sector influences SLO. This serves to clarify the social acceptability of offsets as tools to protect the environment. We find that the use of marine biodiversity offsets would improve the SLO of the sector.
Keywords: Biodiversity offset; Oil and gas sector; Social License to operate

Monitoring Population Dynamics of ‘Western’ Right Whales off Southern Australia Progress Report - John Bannister (2015)
To continue an annual series of aerial surveys off the southern Australian coast between Cape Leeuwin WA and Ceduna SA since 1993, an aerial survey was undertaken as planned over six days, 2-6 September, 2015. For comparison with previous results, counts were obtained of 462 individuals including 97 calves of the year. From 3679 photographic images obtained, 377 have been selected for computer-assisted ‘matching’ with those (some 5000 images of some 2000 individuals) already available in the catalogue, and 126 data sightings sheets have been added to the sightings database, currently totalling 3670 sightings sheets. Full details, including trend analysis since 1993 and current population size, will be included in the Final Report due on 30 March 2016

Monitoring Population Dynamics of ‘Western’ Right Whales off Southern Australia Milestone Report - John Bannister (2015)
To continue an annual series of aerial surveys off the southern Australian coast between Cape Leeuwin WA and Ceduna SA since 1993, an aerial survey was undertaken as planned over six days, 2-6 September, 2015. For comparison with previous results, counts were obtained of 462 individuals including 97 calves of the year. From 3679 photographic images obtained, 377 have been selected for computer-assisted ‘matching’ with those (some 5000 images of some 2000 individuals) already available in the catalogue, and 126 data sightings sheets have been added to the sightings database, currently totalling 3670 sightings sheets. Full details, including trend analysis since 1993 and current population size, will be included in the Final Report due on 30 March 2016

Multi-species distribution modeling using penalized mixture of regressions - Hui, Francis K. C.; Warton, David I.; Scott D Foster (The Annals of Applied Statistics, 2015)
Multi-species distribution modeling, which relates the occurrence of multiple species to environmental variables, is an important tool used by ecologists for both predicting the distribution of species in a community and identifying the important variables driving species co-occurrences. Recently, Dunstan, Foster and Darnell [ Ecol. Model. 222 (2011) 955–963] proposed using finite mixture of regression (FMR) models for multi-species distribution modeling, where species are clustered based on their environmental response to form a small number of “archetypal responses.” As an illustrative example, they applied their mixture model approach to a presence–absence data set of 200 marine organisms, collected along the Great Barrier Reef in Australia. Little attention, however, was given to the problem of model selection—since the archetypes (mixture components) may depend on different but likely overlapping sets of covariates, a method is needed for performing variable selection on all components simultaneously. In this article, we consider using penalized likelihood functions for variable selection in FMR models. We propose two penalties which exploit the grouped structure of the covariates, that is, each covariate is represented by a group of coefficients, one for each component. This leads to an attractive form of shrinkage that allows a covariate to be removed from all components simultaneously. Both penalties are shown to possess specific forms of variable selection consistency, with simulations indicating they outperform other methods which do not take into account the grouped structure. When applied to the Great Barrier Reef data set, penalized FMR models offer more insight into the important variables driving species co-occurrence in the marine community (compared to previous results where no model selection was conducted), while offering a computationally stable method of modeling complex species–environment relationships (through regularization).
Keywords: Lasso; multi-species distribution models; Species archetype

NERP Marine Biodiversity Hub Final Report 2011-2015 - Nicholas J. Bax; Paul Hedge (University of Tasmania, 2015)
This Marine Biodiversity Hub Final Report documents research undertaken between 2011 and 2015 for the Australian Government's National Environmental Research Program.   The report focuses on approaches, key findings, new knowledge and opportunities, outputs and outcomes, in the following areas: Protecting conservation values in the Commonwealth marine area Supporting the recovery of threatened, endangered and protected species Management of Commonwealth marine reserves and the Great Barrier Reef World Heritage Area International extension   The overall objective for the NERP Marine Biodiversity Hub was to ‘provide scientific information and advice that will support (the Department of the Environment) in decision making in the marine environment, specifically to: implement and monitor marine bioregional plans; develop the National Representative System of Marine Protected Areas (NRSMPA); support the information needs of the Environmental Resources information Network (ERIN) and Approvals and Wildlife Division (AWD); and provide key baseline information for the Heritage Division’. How can I obtain a copy? There are three versions of the report available – printed hard copy - <a href="mailto:info@nespmarine.edu.au?subject=Please%20mail%20me%20a%20copy%20of%20your%20NERP%20Marine%20Biodiversity%20Hub%20final%20Report&body=Name%3A%0AAddress%3A%0A%0ANo.%20of%20copies%3A" rel="nofollow">request a copy pdf version - download at Item link below click your way through the interactive version - play the videos, investigate by research area, explore by geographic region, or trawl our imagery and maps - http://nerpmarinebiodiversity2015.report/

NESP Marine Biodiversity Hub Research Plan - 2015 RPv1 - Project Proposals - Nicholas J. Bax; Paul Hedge (2015)
This Research Plan for 2015 (RPv1) has been developed by the Marine Biodiversity Hub, in consultation with the Department of the Environment and Energy and other key stakeholders. The purpose of the Research Plan is to outline: the research priorities the Hub is funded to investigate the research projects that will address these priorities how the output of the research will be communicated and brokered to key stakeholders how the impact of the research will be measured how Hubs will work collaboratively within and across Hubs This Research Plan also lists key staff and research organisations, and the risks needing to be monitored to ensure success. Please note: Project durations vary and may extend over a number of years.  Where a project proposal involves significant changes, it will be updated and included in subsequent research plans.
Keywords: annual research plan; RPv1

Occurrence of a Sharksucker Echeneis naucrates on a Northern River Shark Glyphis garricki in a tidal riverine habitat - PM Kyne (Northern Territory Naturalist, 2015)
Remoras (family Echeneidae) are teleost fishes adapted to hitchhiking behaviour on a variety of marine taxa. Three species have been documented in the waters of the Northern Territory, including the Sharksucker ('Echeneis naucrates'). Sharks are a preferred host for adult 'E. naucrates'. An additional host species, the Northern River Shark ('Glyphis garricki'), is reported here. A small (178 mm total length) 'E. naucrates' was found attached to a 'G. garricki' in tidal reaches of the West Alligator River in Kakadu National Park in October 2014. This is the first report of an echeneid fish on a shark of the genus 'Glyphis' ('river sharks').

Oceanic Shoals Commonwealth Marine Reserve – a guide / Fact sheet - M Julian Caley; Scott L Nichol; Rachel Przeslawski; Johnathan T. Kool; Jessica J. Meeuwig; Phil J. Bouchet (2015)
This guide has been developed for policy makers and managers to communicate the key findings of the three recent surveys of the Oceanic Shoals Commonwealth Marine Reserve, and its relevance to decision making and management. The document is a synthesis designed to transfer relevant knowledge from scientists to managers and decision makers and will continue to evolve in response to further discussion with researchers and managers and as new information becomes available.

Oceanic Shoals Commonwealth Marine Reserve survey reveals new records of xanthid crabs (Crustacea: Brachyura: Xanthidae) from northern Australia - Iwasa-Arai, Tammy; Anna W McCallum; Taylor, Joanne (Memoirs of Museum Victoria, 2015)
Sampling in 2012 (SOL5650 and SS2012t07) by the RV Solander and RV Southern Surveyor resulted in a small collection of decapod crustaceans, including brachyuran crabs. The surveys were undertaken on the shelf off northern Australia, including within the Oceanic Shoals Commonwealth Marine Reserve as part of the Australian Government’s National Environmental Research Program Marine Biodiversity Hub. Here we report on nine species of Xanthidae collected during these surveys, including specimens from the subfamilies Actaeinae, Euxanthinae, Liomerinae and Zosiminae. Two species are reported for the first time in Australian waters (Acteodes mutatus (Ortmann, 1894) and Atergatopsis granulata A. Milne Edwards, 1865).

Of sets of offsets: Cumulative impacts and strategies for compensatory restoration - Thebaud, Olivier; Boschetti, Fabio; Jennings, Sarah; Smith, Anthony D.M.; Pascoe, Sean (Ecological Modelling, 2015)
Biodiversity offsets are increasingly advocated as a flexible approach to managing the ecological costs of economic development. Arguably, however, this remains an area where policy-making has run ahead of science. A growing number of studies identify limitations of offsets in achieving ecologically sustainable outcomes, pointing to ethical and implementation issues that may undermine their effectiveness. We develop a novel system dynamic modelling framework to analyze the no net loss objective of development and biodiversity offsets. The modelling framework considers a marine-based example, where resource abundance depends on a habitat that is affected by a sequence of development projects, and biodiversity offsets are understood as habitat restoration actions. The model is used to explore the implications of four alternative offset management strategies for a regulator, which differ in how net loss is measured, and whether and how the cumulative impacts of development are considered. Our results confirm that, when it comes to offsets as a conservation tool, the devil lies in the details. Approaches to determining the magnitude of offsets required, as well as their timing and allocation among multiple developers, can result in potentially complex and undesired sets of economic incentives, with direct impacts on the ability to meet the overall objective of ecologically sustainable development. The approach and insights are of direct interest to conservation policy design in a broad range of marine and coastal contexts.
Keywords: Bio-economic modelling; Biodiversity offsets; Compensatory restoration; cumulative impacts; Habitat-resource interactions; Social acceptability

Options for managing impacts of climate change on a deep-sea community - Thresher, Ronald E.; Guinotte, John M.; Matear, Richard J.; Alistair J Hobday (Nature Climate Change, 2015)
The deep sea hosts some of the world’s largest, oldest, and most sensitive ecosystems. Climate change and ocean acidification are likely to have severe implications for many deep-sea ecosystems and communities, but what, if anything, can be done to mitigate these threats is poorly understood. To begin to bridge this gap, we convened a stakeholder workshop to assess and prioritize options for conserving legislatively protected deep-sea coral reefs off southeast Australia that, without management intervention, are likely to be severely degraded within decades as a result of climate change. Seventeen possible options were explored that span biological, engineering and regulatory domains and that differed widely in their perceived costs, benefits, time to implementation, and risks. In the short term, the highest priority identified is the need to urgently locate and protect sites globally that are, or will become, refugia areas for the coral and its associated community as climate change progresses. The findings published in this article were generated in a workshop facilitated by the Marine Biodiversity Hub in 2013, bringing together ideas of CSIRO scientists and Parks Australia officers.

Rediscovery of the threatened river sharks, Glyphis garricki and G. glyphis, in Papua New Guinea - William T White; Sharon A Appleyard; Sabub, Benthly; PM Kyne; Harris, Mark; Lis, Rickson; Baje, Leontine; Usu, Thomas; Smart, Jonathan J.; Corrigan, Shannon; Yang, Lei; Gavin J. P. Naylor (PLOS ONE, 2015)
Recent surveys of the shark and ray catches of artisanal fishers in the Western Province of Papua New Guinea (PNG) resulted in the rediscovery of the threatened river sharks, Glyphis garricki and Glyphis glyphis. These represent the first records of both species in PNG since the 1960s and 1970s and highlight the lack of studies of shark biodiversity in PNG. Two individuals of G. garricki and three individuals of G. glyphis were recorded from coastal marine waters of the Daru region of PNG in October and November 2014. The two G. garricki specimens were small individuals estimated to be 100–105 cm and ~113 cm total length (TL). The three G. glyphis specimens were all mature, one a pregnant female and two adult males. These are the first adults of G. glyphis recorded to date providing a more accurate maximum size for this species, i.e. ~260 cm TL. A single pup which was released from the pregnant female G. glyphis, was estimated to be ~65 cm TL. Anecdotal information from the fishers of pregnant females of G. glyphis containing 6 or 7 pups provides the first estimate of litter size for this species. The jaws of the pregnant female G. glyphis were retained and a detailed description of the dentition is provided, since adult dentition has not been previously documented for this species. Genetic analyses confirmed the two species cluster well within samples from these species collected in northern Australia.
Keywords: dentition; freshwater fish; jaw; marine fish; Papua New Guinea; pregnancy; rivers; sharks

Reef fishes at all trophic levels respond positively to effective marine protected areas - Soler, German A.; Graham J. Edgar; Russell J. Thomson; Stuart J. Kininmonth; Campbell, Stuart J.; Dawson, Terence P.; Neville Barrett; Anthony T F Bernard; án, David E.; Willis, Trevor J.; Alexander, Timothy J.; Rick D Stuart-Smith (PLOS ONE, 2015)
Marine Protected Areas (MPAs) offer a unique opportunity to test the assumption that fishing pressure affects some trophic groups more than others. Removal of larger predators through fishing is often suggested to have positive flow-on effects for some lower trophic groups, in which case protection from fishing should result in suppression of lower trophic groups as predator populations recover. We tested this by assessing differences in the trophic structure of reef fish communities associated with 79 MPAs and open-access sites worldwide, using a standardised quantitative dataset on reef fish community structure. The biomass of all major trophic groups (higher carnivores, benthic carnivores, planktivores and herbivores) was significantly greater (by 40% - 200%) in effective no-take MPAs relative to fished open-access areas. This effect was most pronounced for individuals in large size classes, but with no size class of any trophic group showing signs of depressed biomass in MPAs, as predicted from higher predator abundance. Thus, greater biomass in effective MPAs implies that exploitation on shallow rocky and coral reefs negatively affects biomass of all fish trophic groups and size classes. These direct effects of fishing on trophic structure appear stronger than any top down effects on lower trophic levels that would be imposed by intact predator populations. We propose that exploitation affects fish assemblages at all trophic levels, and that local ecosystem function is generally modified by fishing.

Remotely Sensed Spatial and Temporal Dynamics of the Leeuwin Current using Time-series MODIS Data - Z Huang; Feng, Ming (Remote Sensing of Environment, 2015)
The Leeuwin Current is an anomalous poleward-flowing eastern boundary current that transports warm tropical waters southward and imposes significant ecological influences on the coastal marine ecosystems off Western Australia. In this study, we attempt to map the spatial structure of the sea surface temperature (SST) signature of the Leeuwin Current using MODIS satellite data, which is used to investigate the spatial and temporal variability of the Leeuwin Current for the period July 2002 to December 2012. A topographic Position Index (TPI) method is used to map the Leeuwin Current's SST signature from the MODIS SST images. The semi-automatic classification process involves automatically identifying areas occupied by warm SST waters of the Leeuwin Current and manually discarding detached Leeuwin Current features. The TPI mapping results enabled us to quantitatively examine the spatial and temporal variability of the Leeuwin Current's SST signature, including its spatial structure, extent, and cross-shelf migration, as well as its associated surface chlorophyll a characteristics. This study showed that the TPI mapping is able to capture the complex spatial structures of the Leeuwin Current, including its meanders, offshoots and eddies along its path, as reflected in the SST data. Using an eddy-resolving, data-assimilating numerical ocean model, we were able to relate the Leeuwin Current's SST signature with its surface current speed signature, though generally the speed signature is on the offshore side of the SST signature by about 25 to 30 km. Temporal wavelet analyses indicated that the variability of the Leeuwin Current's SST structure is dominated by seasonal cycle. During austral winter, the warm SST signature of the current is close to the shelf break, having greater spatial extent and higher chlorophyll a concentrations. In contrast, during austral summer, the SST signature of the current moves offshore, with reduced spatial extent and chlorophyll a concentrations. The Leeuwin Current also has notable inter-annual variation, to a large extent in response to ENSO variability in the Pacific. In El Niño years the current's SST signature tends to have reduced spatial extent, move further inshore, and increase its chlorophyll a concentrations. The opposite occurs during the La Niña years, especially after the unprecedented 2010–11 La Niña/Ningaloo Niño event when there was a significant reduction of the surface chlorophyll a concentration within the Leeuwin Current's SST signature. The mapping method developed in this study will be also useful in detecting climate driven variability of other ocean boundary current systems.
Keywords: Chlorophyll a concentrations; Cross-shelf movement; Marine; Ocean current; Satellite remote sensing; SST; Western Australia

Residency and local connectivity of White sharks at Liguanea Island: A second aggregation site in South Australia? - Robbins, Rachel; Enarson, M; R. W. Bradford; Robbins, W D; Fox, Andrew (The Open Fish Science Journal, 2015)
White sharks show a high degree of residency to specific aggregation sites, to which they return regularly over multiple years. Australian research has historically focused on single aggregation areas within each of the southern states where white sharks occur, but other key habitats likely exist and if so, will be important to identify to effectively monitor and protect threatened white shark populations. This study is the first to describe Liguanea Island as a second white shark aggregation site within South Australia, with residency periods and return visits recorded by multiple individuals. Eight sharks were detected at both Liguanea Island and the other known aggregation area in the state, the Neptune Islands, demonstrating movement between these locations. Sustained residency periods were recorded at both sites, although high periodic site fidelity was apparent with many individuals showing preference for the location at which they were tagged. Individual differences in site fidelity and residency patterns were found, although two sub-adult individuals were found to follow similar movement patterns. The implications of white shark movements, and the suggested identification of a second aggregation areas in close proximity are discussed.
Keywords: Acoustic telemetry; Carcharodon carcharias; movement; site fidelity; white shark

A review and meta-analysis of the effects of multiple abiotic stressors on marine embryos and larvae - Rachel Przeslawski; Byrne, Maria; Camille Mellin (Global Change Biology, 2015)
Marine organisms are simultaneously exposed to anthropogenic stressors with likely interactive effects, including synergisms in which the combined effects of multiple stressors are greater than the sum of individual effects. Early life stages of marine organisms are potentially vulnerable to the stressors associated with global change, but identifying general patterns across studies, species and response variables is challenging. This review represents the first meta-analysis of multistressor studies to target early marine life stages (embryo to larvae), particularly between temperature, salinity and pH as these are the best studied. Knowledge gaps in research on multiple abiotic stressors and early life stages are also identified. The meta-analysis yielded several key results: (1) Synergistic interactions (65% of individual tests) are more common than additive (17%) or antagonistic (17%) interactions. (2) Larvae are generally more vulnerable than embryos to thermal and pH stress. (3) Survival is more likely than sublethal responses to be affected by thermal, salinity and pH stress. (4) Interaction types vary among stressors, ontogenetic stages and biological responses, but they are more consistent among phyla. (5) Ocean acidification is a greater stressor for calcifying than noncalcifying larvae. Despite being more ecologically realistic than single-factor studies, multifactorial studies may still oversimplify complex systems, and so meta-analyses of the data from them must be cautiously interpreted with regard to extrapolation to field conditions. Nonetheless, our results identify taxa with early life stages that may be particularly vulnerable (e.g. molluscs, echinoderms) or robust (e.g. arthropods, cnidarians) to abiotic stress. We provide a list of recommendations for future multiple stressor studies, particularly those focussed on early marine life stages.
Keywords: arthropod; cnidarian; combined effect; echinoderm; meta-analysis; mollusc; multifactor

The role of peripheral endemism and habitat associations in the evolution of the Indo-West Pacific tuskfishes (Labridae: Choerodon) - Puckridge, Melody; Last, Peter R.; Andreakis, Nikos (Molecular Phylogenetics and Evolution, 2015)
The unrivalled level of biodiversity across the tropical Indo-Australian Archipelago (IAA) has been the subject of wide debate. Attempts to understand its origins have focussed on the timing of speciation, rates of diversification and the directionality of colonisation across geographical and climatic gradients in an array of marine groups. We investigate origins and evolution in the Choerodon tuskfishes, a group of labrids whose centre of diversity coincides with this region. Mitochondrial (COI, 16S) and nuclear (RAG2, Tmo4c4) molecular phylogenies and biogeographic analyses, coupled with molecular clock dating, were inferred from 19 of the 23 valid Choerodon species. Two additional, undescribed Choerodon species were also included, showing reciprocal monophyly in both genomes, confirming their species level status. Choerodon diverged from their ancestral sister group, the Odacines, at the onset of the Miocene, coinciding with the collision of the Australian and Eurasian Plates when extensive areas of shallow-water habitat formed. Despite subsequent evolutionary patterns being partially obscured by overlapping distribution ranges between many species and a lack of clear evidence for climatically driven lineage divergences, our data support an evolutionary scenario of peripheral endemics budding from once widespread populations across this biodiversity hotspot. Interestingly, these peripheral endemics tend to occupy more specialised reef or non-reef habitats whereas widespread groups appear to generally take advantage of both reef and non-reef environments. Our results are discussed in light of the most accredited hypotheses proposed to explain species richness in the IAA, with some support for processes such as centrifugal speciation.
Keywords: biodiversity hotspot; Biogeography; Centrifugal speciation; Indo-West Pacific; Tuskfishes

Sampling mobile oceanic fishes and sharks: implications for fisheries and conservation planning - Tom B. Letessier; Phil J. Bouchet; Jessica J. Meeuwig (Biological Reviews, 2015)
Tuna, billfish, and oceanic sharks [hereafter referred to as ‘mobile oceanic fishes and sharks’ (MOFS)] are characterised by conservative life-history strategies and highly migratory behaviour across large, transnational ranges. Intense exploitation over the past 65 years by a rapidly expanding high-seas fishing fleet has left many populations depleted, with consequences at the ecosystem level due to top-down control and trophic cascades. Despite increases in both CITES and IUCN Red Listings, the demographic trajectories of oceanic sharks and billfish are poorly quantified and resolved at geographic and population levels. Amongst MOFS trajectories, those of tunas are generally considered better understood, yet several populations remain either overfished or of unknown status. MOFS population trends and declines therefore remain contentious, partly due to challenges in deriving accurate abundance and biomass indices. Two major management strategies are currently recognised to address conservation issues surrounding MOFS: (i) internationally ratified legal frameworks and their associated regional fisheries management organisations (RFMOs); and (ii) spatio-temporal fishery closures, including no-take marine protected areas (MPAs). In this context, we first review fishery-dependent studies relying on data derived from catch records and from material accessible through fishing extraction, under the umbrella of RFMO-administrated management. Challenges in interpreting catch statistics notwithstanding, we find that fishery-dependent studies have enhanced the accuracy of biomass indices and the management strategies they inform, by addressing biases in reporting and non-random effort, and predicting drivers of spatial variability across meso- and oceanic scales in order to inform stock assessments. By contrast and motivated by the increase in global MPA coverage restricting extractive activities, we then detail ways in which fishery-independent methods are increasingly improving and steering management by exploring facets of MOFS ecology thus far poorly grasped. Advances in telemetry are increasingly used to explore ontogenic and seasonal movements, and provide means to consider MOFS migration corridors and residency patterns. The characterisation of trophic relationships and prey distribution through biochemical analysis and hydro-acoustics surveys has enabled the tracking of dietary shifts and mapping of high-quality foraging grounds. We conclude that while a scientific framework is available to inform initial design and subsequent implementation of MPAs, there is a shortage in the capacity to answer basic but critical questions about MOFS ecology (who, when, where?) required to track populations non-extractively, thereby presenting a barrier to assessing empirically the performance of MPA-based management for MOFS. This sampling gap is exacerbated by the increased establishment of large (>10000 km2) and very large MPAs (VLMPAs, >100000 km2) - great expanses of ocean lacking effective monitoring strategies and survey regimes appropriate to those scales. To address this shortcoming, we demonstrate the use of a non-extractive protocol to measure MOFS population recovery and MPA efficiency. We further identify technological avenues for monitoring at the VLMPA scale, through the use of spotter planes, drones, satellite technology, and horizontal acoustics, and highlight their relevance to the ecosystem-based framework of MOFS management.

Segregation or aggregation? Sex-specific patterns in the seasonal occurrence of white sharks Carcharodon carcharias at the Neptune Islands, South Australia - Barry Bruce; R. W. Bradford (Journal of Fish Biology, 2015)
The seasonal patterns of occurrence of male and female white sharks Carcharodon carcharias at the Neptune Islands in South Australia were reviewed. Analyses of a 14 year data series indicate that females seasonally aggregate in late autumn and winter coinciding with the maximum in-water availability of lactating female long-nose fur seals and seal pups. During this period, observed male:female sex ratios were similar; whereas during late spring and summer, males continued to visit, but females were rarely recorded. There was no evidence for segregation by sex or size at the Neptunes, but the highly focused seasonal pattern of occurrence of females compared with the year-round records of males suggests that there are likely to be differences between the sexes in overall distribution and movement patterns across southern Australia. It is suggested that foraging strategies and prey selection differ between sexes in C. carcharias across the life-history stages represented and that sex-specific foraging strategies may play an important role in structuring movement patterns and the sex ratios observed at such aggregation sites. Differences between sexes in distribution, movement patterns and foraging strategies are likely to have implications for modelling the consequences of fisheries by-catch between regions or jurisdictions and other spatially or temporally discrete anthropogenic effects on C. carcharias populations. Such differences urge for caution when estimating the size of C. carcharias populations based on observations at pinniped colonies due to the likelihood of sex-specific differences in movements and patterns of residency. These differences also suggest a need to account for sex-specific movement patterns and distribution in population and movement models as well as under conservation actions.
Keywords: forage selection hypothesis; predator–prey interactions; seasonal and annual trends; sex-specific distribution

Setting conservation management thresholds using a novel participatory modeling approach - P F E Addison; de Bie, K.; Rumpff, L. (Conservation Biology, 2015)
We devised a participatory modeling approach for setting management thresholds that show when management intervention is required to address undesirable ecosystem changes. This approach was designed to be used when management thresholds: must be set for environmental indicators in the face of multiple competing objectives; need to incorporate scientific understanding and value judgments; and will be set by participants with limited modeling experience. We applied our approach to a case study where management thresholds were set for a mat-forming brown alga, Hormosira banksii, in a protected area management context. Participants, including management staff and scientists, were involved in a workshop to test the approach, and set management thresholds to address the threat of trampling by visitors to an intertidal rocky reef. The approach involved trading off the environmental objective, to maintain the condition of intertidal reef communities, with social and economic objectives to ensure management intervention was cost-effective. Ecological scenarios, developed using scenario planning, were a key feature that provided the foundation for where to set management thresholds. The scenarios developed represented declines in percent cover of H. banksii that may occur under increased threatening processes. Participants defined 4 discrete management alternatives to address the threat of trampling and estimated the effect of these alternatives on the objectives under each ecological scenario. A weighted additive model was used to aggregate participants’ consequence estimates. Model outputs (decision scores) clearly expressed uncertainty, which can be considered by decision makers and used to inform where to set management thresholds. This approach encourages a proactive form of conservation, where management thresholds and associated actions are defined a priori for ecological indicators, rather than reacting to unexpected ecosystem changes in the future.
Keywords: expert elicitation; management threshold; scenario planning; state-dependent management; structured decision making; uncertainty

Simulated larval connectivity among Australia’s South-west submarine canyons - Johnathan T. Kool; Z Huang; Scott L Nichol (Marine Ecology Progress Series, 2015)
A biophysical dispersal model was used to simulate hydrodynamic connectivity among canyons located within Australia’s southwest marine region using ophiuroid (brittlestars) larvae as a model species. The results show that exchange among canyons in this area is greatly influenced by the Leeuwin Current, transporting larvae in a unidirectional manner around Cape Leeuwin, and continuing eastwards along the Great Australian Bight. Larvae within canyons tend to remain within them; however, if they are transported above the canyon walls, they then have the opportunity to be transported significant distances (thousands of km). Analysis of the variability in connectivity patterns reveals concentrated larval flow near the shelf break, with increasing levels of variability in larval flow leading offshore from the canyons. While the average potential larval flow distance and duration (unweighted by dispersal probability values) between canyons were approximately 550 km and 33 d, respectively, the average realized larval flow distance and duration (weighted by dispersal probability values) were approximately 20 km and 5 d, respectively. This study provides the first consideration of larval connectivity among submarine canyons and will help improve management of these features by providing a better understanding of larval movement, transboundary exchange and the potential spread of invasive species.
Keywords: connectivity; Dispersal; Leeuwin Current; Southwest Australia; Submarine canyons

Spatial scale and geographic context in benthic habitat mapping: review and future directions - Lecours, V; Devillers, R; Schneider, DC; Vanessa L Lucieer; Brown, CJ; Edinger, EN (Marine Ecology Progress Series, 2015)
Understanding the effects of scale is essential to the understanding of natural ecosystems, particularly in marine environments where sampling is more limited and sporadic than in terrestrial environments. Despite its recognized importance, scale is rarely considered in benthic habitat mapping studies. Lack of explicit statement of scale in the literature is an impediment to better characterization of seafloor pattern and process. This review paper highlights the importance of incorporating ecological scaling and geographical theories in benthic habitat mapping. It reviews notions of ecological scale and benthic habitat mapping, in addition to the way spatial scale influences patterns and processes in benthic habitats. We address how scale is represented in geographic data, how it influences their analysis, and consequently how it influences our understanding of seafloor ecosystems. We conclude that quantification of ecological processes at multiple scales using spatial statistics is needed to gain a better characterization of species-habitat relationships. We offer recommendations on more effective practices in benthic habitat mapping, including sampling that covers multiple spatial scales and that includes as many environmental variables as possible, adopting continuum-based habitat characterization approaches, using statistical analyses that consider the spatial nature of data, and explicit statement of the scale at which the research was conducted. We recommend a set of improved standards for defining benthic habitat. With these standards benthic habitats can be defined as ‘areas of seabed that are (geo)statistically significantly different from their surroundings in terms of physical, chemical and biological characteristics, when observed at particular spatial and temporal scales’.
Keywords: benthic habitat mapping; Marine ecology; Multiscale; Spatial analysis; spatial scale; Spatial statistics; species distribution modelling; Surrogacy

Species traits and climate velocity explain geographic range shifts in an ocean-warming hotspot - Sunday, Jennifer M.; Gretta Pecl; Frusher, Stewart; Alistair J Hobday; Nicole A. Hill; Holbrook, Neil J.; Graham J. Edgar; Rick D Stuart-Smith; Neville Barrett; Wernberg, Thomas; Reg A. Watson; Smale, Dan A.; et al. (Ecology Letters, 2015)
Species' ranges are shifting globally in response to climate warming, with substantial variability among taxa, even within regions. Relationships between range dynamics and intrinsic species traits may be particularly apparent in the ocean, where temperature more directly shapes species' distributions. Here, we test for a role of species traits and climate velocity in driving range extensions in the ocean-warming hotspot of southeast Australia. Climate velocity explained some variation in range shifts, however, including species traits more than doubled the variation explained. Swimming ability, omnivory and latitudinal range size all had positive relationships with range extension rate, supporting hypotheses that increased dispersal capacity and ecological generalism promote extensions. We find independent support for the hypothesis that species with narrow latitudinal ranges are limited by factors other than climate. Our findings suggest that small-ranging species are in double jeopardy, with limited ability to escape warming and greater intrinsic vulnerability to stochastic disturbances.
Keywords: benthic invertebrates; climate change; climate response; Fishes; functional traits; invasion; range expansion; range shifts; range size

A standardised vocabulary for identifying benthic biota and substrata from underwater imagery: the CATAMI classification scheme - Althaus, Franziska; Nicole A. Hill; Renata Ferrari; Edwards, Luke; Rachel Przeslawski; Schönberg, Christine H. L.; Rick D Stuart-Smith; Neville Barrett; Graham J. Edgar; Jamie Colquhoun; Maggie Tran; Alan Jordan; et al. (PLOS ONE, 2015)
Imagery collected by still and video cameras is an increasingly important tool for minimal impact, repeatable observations in the marine environment. Data generated from imagery includes identification, annotation and quantification of biological subjects and environmental features within an image. To be long-lived and useful beyond their project-specific initial purpose, and to maximize their utility across studies and disciplines, marine imagery data should use a standardised vocabulary of defined terms. This would enable the compilation of regional, national and/or global data sets from multiple sources, contributing to broad-scale management studies and development of automated annotation algorithms. The classification scheme developed under the Collaborative and Automated Tools for Analysis of Marine Imagery (CATAMI) project provides such a vocabulary. The CATAMI classification scheme introduces Australian-wide acknowledged, standardised terminology for annotating benthic substrates and biota in marine imagery. It combines coarse-level taxonomy and morphology, and is a flexible, hierarchical classification that bridges the gap between habitat/biotope characterisation and taxonomy, acknowledging limitations when describing biological taxa through imagery. It is fully described, documented, and maintained through curated online databases, and can be applied across benthic image collection methods, annotation platforms and scoring methods. Following release in 2013, the CATAMI classification scheme was taken up by a wide variety of users, including government, academia and industry. This rapid acceptance highlights the scheme’s utility and the potential to facilitate broad-scale multidisciplinary studies of marine ecosystems when applied globally. Here we present the CATAMI classification scheme, describe its conception and features, and discuss its utility and the opportunities as well as challenges arising from its use.

Submarine Canyons: their role in shaping biodiversity patterns on the Australian margin - Fact sheet - Scott L Nichol; Johnathan T. Kool; Z Huang (2015)
As part of a national study of submarine canyons, Marine Hub researchers have produced a summary fact sheet describing the distribution of canyons on the Australian margin, their relationship to Commonwealth Marine Reserves and the degree to which canyons are connected through the exchange of marine larvae. This latter aspect has been explored through connectivity modelling and provides a proxy for understanding the role that canyons play in influencing marine biodiversity patterns. Two case studies are presented in the fact sheet, the Albany Canyons (South-west region) and Cape Range Canyons (North-west region). These examples highlight the strong influence of ocean currents in larval transport across groups of canyons and moreover that the larger, more topographically complex canyons have a greater capacity to function as a source for larvae for canyons nearby. This in turn has implications for identifying those canyons that have greater relative importance as potential biodiversity hotspots. Related information Fact sheet - Submarine Canyons: their role in shaping biodiversity patterns on the Australian margin, March 2015 Datasets - National Submarine Canyons of Australia dataset published by Geoscience Australia Journal article - Classification of submarine canyons of the Australian continental margin, Marine Geology, 2014 Poster - Submarine Canyon Mapping, Nov 2014   Also see other Information Sheets from the Marine Hub

Thermal biases and vulnerability to warming in the world's marine fauna - Rick D Stuart-Smith; Graham J. Edgar; Neville Barrett; Stuart J. Kininmonth; Amanda E. Bates (Nature, 2015)
A critical assumption underlying projections of biodiversity responses to global warming is that species distributions are at equilibrium with their environment. Nevertheless, most species occupy a broad thermal distribution, and overall community-level outcomes of local mismatches between species’ thermal limits and environmental temperatures have not yet been considered. Here we examine the geographic and thermal distributions of marine species worldwide, and identify large-scale spatial thermal mismatches, or biases, where communities are dominated by species with warmer or cooler affinity than local environmental temperatures. We combine information on the magnitude of this thermal bias with local warming rates to predict vulnerability of ecological communities to local warming-related loss of species. We find that proximity to thermal limits, as inferred from present-day species distributional ranges, far outweighs spatial variation in warming rates in contributing to the proportion of species predicted to be lost from ecological communities under projected ocean warming over the next century. News story - Citizen scientists change understanding of how global warming affects marine biodiversity - 11 November 2015

Towards a blueprint for monitoring Key Ecological Features in the Commonwealth Marine Area - Keith R Hayes; Jeffrey M Dambacher; Paul Hedge; David Watts; Scott D Foster; Peter A. Thompson; G.R. Hosack; Piers K Dunstan; Nicholas J. Bax (2015)
The Australian Government Department of the Environment is seeking to strengthen the evidence base to protect, sustainably manage and report on the health of the Commonwealth Marine Area (CMA). The Department is also (but initially in a terrestrial and freshwater context) trying to improve the availability of timely and meaningful information on trends in the state of the environment through a new initiative, called the Essential Environmental Measures for Australia, under the National Plan for Environmental Information (NPEI). This document supports these objectives by providing options for monitoring of, and reporting on, Key Ecological Features (KEFs) to help the Department identify a limited set of Essential Environmental Measures and strengthen the evidence base for reporting on the health of the CMA: it represents the first step towards a blueprint for a sustained approach to environmental monitoring and reporting. Also view the brochure - Monitoring Australia's oceans: towards a blueprint

Towards a national population assessment for white sharks - Fact sheet - Nicholas J. Bax (2015)
A unique combination of acoustic tagging and genetic and statistical analysis is contributing to the first evidence-based estimates of white shark population size and status in Australia. White sharks are listed as vulnerable under the Commonwealth Environment Protection and Biodiversity Act 1999 and actions to assist their recovery and long-term viability are prescribed in a national recovery plan for the species. A priority action is to develop an effective means of estimating the size of white shark populations and monitor their status (population trend). This would provide a scientific basis for assessing recovery actions, and for local policies governing human-shark interactions: an issue of significant public concern.

Whole mitogenome sequencing refines population structure of the Critically Endangered sawfish Pristis pristis - Pierre Feutry; PM Kyne; Richard D. Pillans; Chen, X; Marthick, J; David L Morgan; Grewe, PM (Marine Ecology Progress Series, 2015)
The Largetooth Sawfish Pristis pristis is a highly threatened euryhaline elasmobranch that in recent times has undergone a significant range contraction. It now only remains in a few areas with northern Australia being the main stronghold. Previous work using a single mitochondrial gene approach suggested the existence of regional barriers to gene flow in northern Australia. In this study, whole mitochondrial sequences of 92 P. pristis from seven river drainages across northern Australia were used to refine the population structure. This approach revealed barriers to gene flow at a scale as fine as between adjacent river drainages. Except for those flowing into the Gulf of Carpentaria, all river drainages appeared to host a genetically distinct population. The apparent genetic homogeneity in the Gulf is probably due to freshwater connectivity between river drainages, either during the last glaciation event when the Gulf was a freshwater lake or through contemporary wet season flooding. These results suggest that each river drainage across the species’ range should be considered a discrete management unit unless there is evidence of freshwater connectivity. More broadly, the improved resolution of population structure obtained with whole mitogenome analysis compared to single mitochondrial gene approaches, suggests that female reproductive philopatry may have been overlooked in previous studies of some elasmobranch species.

Australia’s deep-water octocoral fauna: historical account and checklist, distributions and regional affinities of recent collections - Alderslade, Philip; Althaus, Franziska; Felicity McEnnulty; Karen Gowlett-Holmes; Williams, Alan (Zootaxa, 2014)
The number of deep-water (>80 m) octocoral species recorded from Australian waters has more than tripled from 135 to 457 following six surveys undertaken between 1997 and 2008 on the deep continental margin of south-eastern, western and north-western Australia and the Tasman Sea.  This rapid increase in knowledge follows a slow accumulation of records since the earliest collections were made by vessels such as the Géographe and the Naturaliste in the early years of the 19th century. Consistent identification and alpha-labelling of the octocoral fauna between surveys has permitted a multi-region description and comparison.  We detail the identities, distributions and regional affinities of 457 octocoral species in 131 genera and 28 families from the orders Alcyonacea and Pennatulacea, including 69 new species, 17 new genera and 43 first records for Australia. Five of the more common genera were widely distributed (present at 35 and 66 sampling stations spanning all of the 4 survey regions), but two were restricted to south-eastern Australia—Pleurogorgia Versluys, 1902 and Tokoprymno Bayer, 1996—and were only sampled from depths below 700 m.  The great majority of species (81%) and nearly half of all genera (47%) were only sampled once or twice.  The highest average number of species per sampling station (3.2) was reported from the outer shelf. The proportion of new species was highest (>22%) on the upper and lower slope bathomes, intermediate (13–15%) on the mid-slope bathome and lowest (8%) on the outer shelf bathome.  Species overlap between bathomes was low, but all families were shared across bathomes. Most described species (55 of 69) have an Indo-West Pacific affinity, 20 have an Indian Ocean affinity, while three were previously recorded from the Atlantic Ocean only; 20 appear to be Australian endemics. Octocorals can now be added to an emerging set of taxon-specific data sets—including fishes, ophiuroids and galatheids—that permit regional-scale analysis of biodiversity distributions to support Australia’s efforts in marine conservation management. However, because so much of the world octocoral literature is inadequate for accurate identifications to species level, there is a pressing need for taxonomic revisions using modern morphological and molecular techniques to fine-tune the current use of octocorals as indicators of vulnerable marine ecosystems in many national and high seas conservation initiatives.

Baited videography reveals remote foraging and migration behaviour of sea turtles - Tom B. Letessier; Phil J. Bouchet; Reisser, J.; Jessica J. Meeuwig (Marine Biodiversity, 2014)
Studying sea turtles when they leave coastal areas is a particular challenge for research and conservation. As part of a large-scale fish-monitoring programme, we have deployed mid-water stereo baited remote underwater video systems (BRUVS, Letessier et al. 2013) at 181 sites around northwestern Australia. From 27 turtle observations, we identified 11 green turtles (Chelonia mydas) around Dirk Hartog Island, west of Shark Bay (April 2012) and three olive ridley turtles (Lepidochelys olivacea) on the Australian shelf of the Timor Sea (September 2012, Fig. 1). Turtle encounter rates were 37 % inside the shallow Dirk Hartog pass (mean depth 11 m) compared with 0 % on the seaward side of the island, and 2.5 % in the Timor Sea (mean depth 113 m). Straight carapace length (SCL) was measured for one olive ridley (70.0 cm, an adult female) and four green turtles (SCL =40.6–89.5 cm). At least two olive ridleys and three greens actively inspected the bait (see electronic supplementary material).

Choosing between strategies for designing surveys: autonomous underwater vehicles - Scott D Foster; G.R. Hosack; Nicole A. Hill; Neville Barrett; Vanessa L Lucieer (Methods in Ecology and Evolution, 2014)
Autonomous underwater vehicles (AUV), which collect images of marine habitats, are now an established sampling tool. The use of AUVs is becoming more widespread as they offer a non-destructive method to survey substantial spatial areas. The design of AUV surveys has historically been based on expert knowledge and AUV-specific considerations, such as reducing geolocation error. The expert knowledge encompasses intuition, previous surveying experiences and holistic knowledge of the study region. We investigate the statistical aspects to AUV survey design for estimation of percentage cover of key benthic biota. We investigate the presence of spatial autocorrelation in AUV data using model-based geostatistics and examine the effect of autocorrelation on survey design by examining different design strategies – methods for placing AUV transects. The design strategies are assessed by inspecting the expected bias and the expected standard deviation of model predictions, where the model depends on the choice of design. The AUV data exhibited a wide range of autocorrelation, from non-existent to substantial. The design strategies varied in their statistical performance and nearly all strategies had shortcomings. Design strategies that were consistently poor performers had (i) transects placed in parallel in a single spatial dimension and (ii) made no attempt to spread out the transects in space. The superior design types had more transect-to-transect separation (but not too much) and effectively spanned important covariates. The results give guidelines to researchers designing AUV surveys for biological mapping and for monitoring. In particular, we demonstrate that any spatial design should seek spatial balance, such as would be introduced by a systematic or stratified component within a randomized design. Knowledge of the system under study should be incorporated and, if possible, should be done so in a formal manner that is objective and repeatable.
Keywords: autocorrelation; autonomous underwater vehicles; Geostatistics; GRTS; integrated nested laplace approximation; matérn; model-based design; temperate reef

Classification of submarine canyons of the Australian continental margin - Z Huang; Scott L Nichol; Harris, Peter T.; M Julian Caley (Marine Geology, 2014)
Submarine canyons influence oceanographic processes, sediment transport, productivity and benthic biodiversity from the continental shelf to the slope and beyond. However, not all canyons perform the same function. The relative influence of an individual canyon on these processes will, in part, be determined by its form, shape and position on the continental margin. Here we present an analysis of canyon geomorphic metrics using an updated national dataset of 713 submarine canyons surrounding mainland Australia. These metrics (attributes) for each canyon are used to classify them into canyon types across a hierarchy of physical characteristics separately for shelf-incising (n= 95) and slope-confined (blind; n = 618) canyons. We find that the canyon metrics describe a wide variety of canyon form and complexity that is consistent with a population of canyons that has evolved at different rates around the Australian margin since the break-up of Gondwana. The large number of slopeconfined canyons is interpreted to reflect dominance of slope mass-wasting processes over erosive turbidity flows from fluvial and shelf sources on an arid continent. The distribution of submarine canyons around the Australian margin is not regular, with clusters occurring in the east, southeast, west and southwest where the margin is steepest. The classification result provides a quantitative framework for describing canyon heterogeneity for application in studies of geological controls on individual canyons, canyon oceanography and canyon biodiversity.
Keywords: Australia; bathymetry; hierarchical classification; morphometrics; Submarine canyons

A climate of uncertainty: accounting for error and spatial variability in climate variables for species distribution models - Stoklosa, Jakub; Daly, Christopher; Scott D Foster; Ashcroft, Michael B.; David I. Warton (Methods in Ecology and Evolution, 2014)
Summary Spatial climate variables are routinely used in species distribution models (SDMs) without accounting for the fact that they have been predicted with uncertainty, which can lead to biased estimates, erroneous inference and poor performances when predicting to new settings – for example under climate change scenarios. We show how information on uncertainty associated with spatial climate variables can be obtained from climate data models. We then explain different types of uncertainty (i.e. classical and Berkson error) and use two statistical methods that incorporate uncertainty in climate variables into SDMs by means of (i) hierarchical modelling and (ii) simulation–extrapolation. We used simulation to study the consequences of failure to account for measurement error. When uncertainty in explanatory variables was not accounted for, we found that coefficient estimates were biased and the SDM had a loss of statistical power. Further, this bias led to biased predictions when projecting change in distribution under climate change scenarios. The proposed errors-in-variables methods were less sensitive to these issues. We also fit the proposed models to real data (presence/absence data on the Carolina wren, Thryothorus ludovicianus), as a function of temperature variables. The proposed framework allows for many possible extensions and improvements to SDMs. If information on the uncertainty of spatial climate variables is available to researchers, we recommend the following: (i) first identify the type of uncertainty; (ii) consider whether any spatial autocorrelation or independence assumptions are required; and (iii) attempt to incorporate the uncertainty into the SDM through established statistical methods and their extensions.
Keywords: climate maps; errors-in-variables; hierarchical statistical models; Measurement error; prediction error; PRISM; SIMEX

Community acceptance of marine biodiversity offsets in Australia: a pilot study - Abbie A Rogers; Burton, Michael; Richert, Claire; Kay, Alexandra (2014)
Biodiversity offsets are used to account for environmental damages caused by development. In Australia, there are offset policies operating at the State and Commonwealth Government levels. An offset policy becomes relevant when residual environmental damages are likely to result from a proposed development; that is, when damages are likely to remain after all avoidance and mitigation measures have been undertaken. In such a case, the proponent must propose to offset the residual damages by protecting or improving equivalent environmental matter elsewhere. In theory, this should result in no net loss to the environment. If the proponent can reasonably show that the proposed offset will avoid a net loss, then the development may be considered for approval.  The relevant State offset policy applies to any residual environmental damages resulting from development (e.g. Government of Western Australia 2011). In addition, if a matter of national environmental significance is affected, the Commonwealth’s Environmental Protection and Biodiversity Conservation (EPBC) Act Offset Policy also applies (Australian Government 2012). Matters of national environmental significance include species listed as threatened or migratory under the EPBC Act. The EPBC Offset Policy was released in 2012, following a period of comment on a draft version of the policy. In drafting and revising this policy, the science and economic efficiencies of offsetting were addressed. However, little is known about the social acceptability of biodiversity offsets. If offsets are to become common practice in environmental management and policy, it is important that they are designed in a way that satisfies the scientific, economic and social dimensions. This study will examine the preferences of the Australian community with respect to how marine biodiversity offsets are implemented. In particular, community reaction to the following policy characteristics (or attributes) are of interest: the proportion of direct versus indirect  offset;  the type of offset activity; the location of the offset, relative to the development site; the species protected by the offset; the implementer of the offset; or, whether co-benefits are likely to result from the offset.

Complete mitochondrial genome of the Freshwater Whipray Himantura dalyensis - Pierre Feutry; PM Kyne; Peng, Zaiqing; Pan, Lianghao; Xiao Chen (Mitochondrial DNA, 2014)
The complete mitochondrial genome of the Freshwater Whipray Himantura dalyensis is presented in this study. It is 17,693 bp in length and contains 37 genes in typical gene order and transcriptional orientation observed in vertebrates. There were a total of 86 bp short intergenic spacers and 22 bp overlaps in the genome. The overall base composition was 31.4% A, 25.5% C, 13.2% G and 29.9% T. Two start codons (GTG and ATG) and two stop codons (TAG and TAA/T) were found in 13 protein-coding genes. The length of 22 tRNA genes ranged from 68 (tRNA-Cys and tRNA-Ser2) to 75 bp (tRNA-Leu1). The origin of L-strand replication (OL) was found between the tRNA-Asn and tRNA-Cys genes. The base composition of the control region (1940 bp) was similar to the whole mitogenome. Read More: http://informahealthcare.com/doi/abs/10.3109/19401736.2014.958682
Keywords: Dasyatidae; Himantura dalyensis; mitochondrion

Complete mitochondrial genome of the Pigeye Shark Carcharhinus amboinensis (Carcharhiniformes: Carcharhinidae) - Pierre Feutry; Every, Sharon L.; PM Kyne; Sun, Renjie; Xiao Chen (Mitochondrial DNA, 2014)
In this manuscript we describe the first complete mitochondrial sequence for the Data Deficient Pigeye Shark Carcharhinus amboinensis. The mitogenome is 16,704 bp long and consists of 1 control region, 2 rRNA genes, 22 tRNA genes and 13 protein-coding genes with an overall base composition of 31.6% A, 24.9% C, 13.1% G and 30.4% T. The gene arrangement pattern and transcriptional direction were typical for a vertebrate species. The tRNA-Ser2 lacks the dihydrouridine arm and forms a simple loop, therefore it cannot be folded into the typical cloverleaf secondary structures like other tRNAs. Read More: http://informahealthcare.com/doi/abs/10.3109/19401736.2014.982590
Keywords: Carcharhinus amboinensis; genome; mitochondrion

Complete mitogenome of the Graceful Shark Carcharhinus amblyrhynchoides (Carcharhiniformes: Carcharhinidae) - Pierre Feutry; Richard D. Pillans; PM Kyne; Xiao Chen (Mitochondrial DNA, 2014)
In this manuscript we describe the first complete mitochondrial sequence for the Near Threatened Graceful Shark Carcharhinus amblyrhynchoides. It is 16,705 bp in length, consists of two rRNA genes, 22 tRNA genes, 13 protein-coding genes and one control region with the typical gene arrangement pattern and translate orientation in vertebrates. The overall base composition is 31.4% A, 25.1% C, 13.2% G and 30.3% T. The shortest tRNA-Ser2 cannot fold into a clover-leaf secondary structure due to the lack of the dihydrouridine arm.
Keywords: Carcharhinus amblyrhynchoides; genome; mitochondrion

Complete mitogenomic sequence of the Critically Endangered Northern River Shark Glyphis garricki (Carcharhiniformes: Carcharhinidae). - Pierre Feutry; Grewe, Peter M.; PM Kyne; Xiao Chen (Mitochondrial DNA, 2014)
In this study we describe the first complete mitochondrial sequence for the Critically Endangered Northern River shark Glyphis garricki. The complete mitochondrial sequence is 16,702 bp in length, contains 37 genes and one control region with the typical gene order and transcriptional direction of vertebrate mitogenomes. The overall base composition is 31.5% A, 26.3% C, 12.9% G and 29.3% T. The length of 22 tRNA genes ranged from 68 (tRNA-Ser2 and tRNA-Cys) to 75 (tRNA-Leu1) bp. The control region of G. garricki was 1067 bp in length with high A + T (67.9%) and poor G (12.6%) content. The mitogenomic characters (base composition, codon usage and gene length) of G. garricki were very similar to Glyphis glyphis. Read More: http://informahealthcare.com/doi/abs/10.3109/19401736.2013.861428
Keywords: Glyphis garricki; Mitochondrial genome; threatened species

The Convention on Biological Diversity's Ecologically or Biologically Significant Areas: Origins, development, and current status - Daniel C. Dunn; Jeff A Ardron; Nicholas J. Bax; Bernal, Patricio; Cleary, Jesse; I D Cresswell; Donnelly, Ben; Piers K Dunstan; Kristina M. Gjerde; Johnson, David; Kaschner, Kristin; Lascelles, Ben; et al. (Marine Policy, 2014)
In 2008, the Convention on Biological Diversity (CBD) adopted seven criteria to identify Ecologically or Biologically Significant Areas (EBSAs) “…in need of protection, in open ocean waters and deep sea habitats”. This paper reviews the history of the development of the “EBSA process”, which was originally driven by the commitment to establish marine protected areas in areas beyond national jurisdiction, but which has since broadened to encompass the possibility of informing marine spatial planning and other activities, both within and beyond national jurisdiction. Additionally, the paper summarizes ongoing efforts through CBD regional workshops to describe EBSAs and the development of the EBSA Repository, where information on these areas is to be stored. The overlap between the EBSA criteria and biodiversity criteria suites used by various authorities in areas beyond national jurisdiction is illustrated. The EBSA process has reached a critical juncture, whereby a large percentage of the global ocean has been considered by the regional workshops, but the procedure by which these areas can be incorporated into formal management structures has not yet been fully developed. Emerging difficulties regarding the mandate to describe, identify, endorse, or adopt EBSAs, are discussed.
Keywords: Areas beyond national jurisdiction; Convention on Biological Diversity; EBSA; Ecologically or Biologically Significant Areas; High seas; Marine protected areas

The deepwater demersal ichthyofauna of the western Coral Sea - Last, Peter R.; John J Pogonoski; Daniel C Gledhill; William T White; Walker, Chris J (Zootaxa, 2014)
The highly diverse deepwater demersal ichthyofauna of the western Coral Sea was first systematically surveyed in two exploratory voyages in 1985 and 1986, and these fish assemblages have not been investigated at the same level since. Only recently have catch data and specimens, obtained from these first voyages almost 3 decades ago, been rigorously investigated and analysed. Some 393 species of fishes from 125 families were collected during the 1985 voyage which surveyed the northeastern Australian continental margin, and the Saumarez and Queensland Plateaus. A checklist of the species caught is provided. Levels of endemicity of deepwater fishes in the western Coral Sea are very high with about 50% of well-studied groups, such as sharks and rays, confined to this relatively small geographic region. A very high proportion of species caught during this voyage were either undescribed (78 species or 20%) or new Australian records (96 species or 24%) at the time of the survey. Another 68 species (17%) are the subject of further taxonomic investigation or are currently undergoing formal description. The fauna exhibits some intraregional differences in structure. Biogeographically informative fishes such as skates appear to be cryptically partitioned within the region, differing in composition to other Australian regions and those of French territories to the east. Strong depth-related partitioning of the fauna is also evident, and its structure follows zonation patterns observed across the wider Australian region. Given the high level of micro-endemicity and regional uniqueness of the fauna, there is a compelling argument for the existence of a faunal gyre in the Coral Sea. New gap-filling surveys are needed to better define the structure of this fauna and determine its distribution.
Keywords: Biodiversity; Biogeography; Coral Sea; deepwater fishes; southwestern Pacific

Do communities exist? Complex patterns of overlapping marine species distributions - Rebecca Leaper; Piers K Dunstan; Scott D Foster; Neville Barrett; Graham J. Edgar (Ecology, 2014)
Understanding the way in which species are associated in communities is a fundamental question in ecology. Yet there remains a tension between communities as highly structured units or as coincidental collections of individualistic species. We explore these ideas using a new statistical approach that clusters species based on their environmental response- a species archetype, rather than clustering sites based on their species composition. We find that there are groups of species, which are consistently highly correlated, but that these groups are not unique to any set of locations and overlap spatially. The species present at a single site are a realisation of species from the (multiple) archetype groups that are likely to be present at that location based on their response to the environment.
Keywords: clements; community; composition; gleason; Grouping; Prediction; Species archetype; struct ure; subtidal rocky reefs

Exploring Symbiodinium diversity and host specificity in Acropora coral from geographical extremes of Western Australia - Luke Thomas; Gary A. Kendrick; Kennington, W. J.; Richards, Z. T.; Stat, M. (Molecular Ecology, 2014)
Scleractinian corals have demonstrated the ability to shuffle their endosymbiotic dinoflagellate communities (genus Symbiodinium) during periods of acute environmental stress. This has been proposed as a mechanism of acclimation, which would be increased by a diverse and flexible association with Symbiodinium. Conventional molecular techniques used to evaluate Symbiodinium diversity are unable to identify genetic lineages present at background levels below 10%. Next generation sequencing (NGS) offers a solution to this problem and can resolve microorganism diversity at much finer scales. Here we apply NGS to evaluate Symbiodinium diversity and host specificity in Acropora corals from contrasting regions of Western Australia. The application of 454 pyrosequencing allowed for detection of Symbiodinium operational taxonomic units (OTUs) occurring at frequencies as low as 0.001%, offering a 10 000-fold increase in sensitivity compared to traditional methods. All coral species from both regions were overwhelmingly dominated by a single clade C OTU (accounting for 98% of all recovered sequences). Only 8.5% of colonies associated with multiple clades (clades C and D, or C and G), suggesting a high level of symbiont specificity in Acropora assemblages in Western Australia. While only 40% of the OTUs were shared between regions, the dominance of a single OTU resulted in no significant difference in Symbiodinium community structure, demonstrating that the coral-algal symbiosis can remain stable across more than 15° of latitude and a range of sea surface temperature profiles. This study validates the use of NGS platforms as tools for providing fine-scale estimates of Symbiodinium diversity and can offer critical insight into the flexibility of the coral-algal symbiosis.
Keywords: Acropora; next generation sequencing; Symbiodinium; Western Australia

Extinction risk and conservation of the world’s sharks and rays - N K Dulvy; Fowler, S L; Musick, J A; Cavanagh, R D; PM Kyne; Harrison, L R; John K. Carlson; L N K Davidson; Sonja V. Fordham; Malcolm P. Francis; Caroline M. Pollock; Colin Simpfendorfer; et al. (eLIFE, 2014)
The rapid expansion of human activities threatens ocean-wide biodiversity. Numerous marine animal populations have declined, yet it remains unclear whether these trends are symptomatic of a chronic accumulation of global marine extinction risk. We present the first systematic analysis of threat for a globally distributed lineage of 1,041 chondrichthyan fishes—sharks, rays, and chimaeras. We estimate that one-quarter are threatened according to IUCN Red List criteria due to overfishing (targeted and incidental). Large-bodied, shallow-water species are at greatest risk and five out of the seven most threatened families are rays. Overall chondrichthyan extinction risk is substantially higher than for most other vertebrates, and only one-third of species are considered safe. Population depletion has occurred throughout the world’s ice-free waters, but is particularly prevalent in the Indo-Pacific Biodiversity Triangle and Mediterranean Sea. Improved management of fisheries and trade is urgently needed to avoid extinctions and promote population recovery.

Extinction risk categories and how to cite them - PM Kyne (Mitochondrial DNA, 2014)
Genetics is an increasingly important tool in conservation biology with growing applications to assist in managing species of conservation concern (Dudgeon et al., 2012; Frankham, 2010). Mitochondrial DNA regularly publishes complete mitogenomes of threatened species including for bony fishes (e.g. Three-spot Seahorse Hippocampus trimaculatus; Vulnerable; Chang et al., 2013), cartilaginous fishes (e.g. Northern River Shark Glyphis garricki; Critically Endangered; Feutry et al., 2014), reptiles (e.g. Frog-faced Softshell Turtle Pelochelys cantorii; Endangered; Chen et al., 2013) and birds (e.g. Saunders’ Gull Larus saundersi; Vulnerable; Ryu & Hwang, 2012). The conservation status of a species is often cited by manuscript authors as a justification for their research, with authors suggesting how their work can inform the conservation, management and ultimately the recovery of threatened species. Read More: http://informahealthcare.com/doi/full/10.3109/19401736.2014.905831
Keywords: Conservation status; the IUCN Red List of Threatened Species; threatened species

Filling the gaps: Predicting the distribution of temperate reef biota using high resolution biological and acoustic data - Nicole A. Hill; Vanessa L Lucieer; Neville Barrett; Tara J Anderson; Williams, Stefan B. (Estuarine, Coastal and Shelf Science, 2014)
information on the distribution of diversity and the bio-physical processes structuring regional ecosystems. This is particularly true in temperate reef systems beyond depths easily accessible to divers. Yet these systems harbor a diversity of sessile life that provide essential ecosystem services, sustain fisheries and, as with shallower ecosystems, are also increasingly vulnerable to anthropogenic impacts and environmental change. Here we use cutting-edge tools (Autonomous Underwater Vehicles and ship-borne acoustics) and analytical approaches (predictive modelling) to quantify and map these highly productive ecosystems. We find the occurrence of key temperate-reef biota can be explained and predicted using standard (depth) and novel (texture) surrogates derived from multibeam acoustic data, and geographic surrogates. This suggests that combinations of fine-scale processes, such as light limitation and habitat complexity, and broad-scale processes, such as regional currents and exposure regimes, are important in structuring these diverse deep-reef communities. While some dominant habitat forming biota, including canopy algae, were widely distributed, others, including gorgonians and sea whips, exhibited patchy and restricted distributions across the reef system. In addition to providing the first quantitative and full coverage maps of reef diversity for this area, our modelling revealed that offshore reefs represented a regional diversity hotspot that is of high ecological and conservation value. Regional reef systems should not, therefore, be considered homogenous units in conservation planning and management. Full-coverage maps of the predicted distribution of biota (and associated uncertainty) are likely to be increasingly valuable, not only for conservation planning, but in the ongoing management and monitoring of these less-accessible ecosystems.
Keywords: Biodiversity; Conservation; multibeam autonomous underwater vehicles; species distribution; surrogates

Generalizing the use of geographical weights in biodiversity modelling - Camille Mellin; Mengersen, K.; C. J. A. Bradshaw; M Julian Caley (Global Ecology and Biogeography, 2014)
ABSTRACT Aim Determining how ecological processes vary across space is a major focus in ecology. Current methods that investigate such effects remain constrained by important limiting assumptions. Here we provide an extension to geographically weighted regression in which local regression and spatial weighting are used in combination. This method can be used to investigate non-stationarity and spatialscale effects using any regression technique that can accommodate uneven weighting of observations, including machine learning. Innovation We extend the use of spatial weights to generalized linear models and boosted regression trees by using simulated data for which the results are known, and compare these local approaches with existing alternatives such as geographically weighted regression (GWR). The spatial weighting procedure (1) explained up to 80% deviance in simulated species richness, (2) optimized the normal distribution of model residuals when applied to generalized linear models versus GWR, and (3) detected nonlinear relationships and interactions between response variables and their predictors when applied to boosted regression trees. Predictor ranking changed with spatial scale, highlighting the scales at which different species– environment relationships need to be considered. Main conclusions GWR is useful for investigating spatially varying species– environment relationships.However, the use of local weights implemented in alternativemodelling techniques can help detect nonlinear relationships and high-order interactions that were previously unassessed. Therefore, this method not only informs us how location and scale influence our perception of patterns and processes, it also offers a way to deal with different ecological interpretations that can emerge as different areas of spatial influence are considered during model fitting.
Keywords: Biodiversity; macroecological modelling; method; non-stationarity; Prediction; spatial scale; species distribution modelling

Ghosts of the coast: global extinction risk and conservation of sawfishes - N K Dulvy; L N K Davidson; PM Kyne; Colin Simpfendorfer; Harrison, Lucy R.; John K. Carlson; Sonja V. Fordham (Aquatic Conservation: Marine and Freshwater Ecosystems, 2014)
Sawfish are arguably the world's most imperilled marine fishes. All five species are classified as highly threatened with extinction: three are Critically Endangered (smalltooth sawfish Pristis pectinata, largetooth sawfish Pristis pristis, and green sawfish Pristis zijsron); two are Endangered (narrow sawfish Anoxypristis cuspidata, and dwarf sawfish Pristis clavata). Sawfishes are threatened primarily due to a combination of their low intrinsic rates of population increase, high catchability in fisheries, and high value. Sawfishes are among the world's largest marine fishes, and they are caught by a wide range of fishing gears owing to their tooth-studded rostra being easily entangled. Sawfish fins are some of the most valuable for shark fin soup, and their rostra have long been traded as curios. In addition, they inhabit shallow coastal waters, estuaries, and rivers of the tropics and subtropics, down to a maximum depth rarely exceeding 100 m and are associated with threatened mangrove and seagrass habitats. Historically, sawfishes were distributed in the coastal waters of 90 countries and territories. Over the past century, their geographic distribution has been greatly diminished. For example, the smalltooth sawfish is now found in <20% of its former range. Globally, sawfishes are now entirely absent from 20 countries; 43 countries have lost at least one species. Sawfishes are legally protected, to some degree, in 16 of the 90 range states. These safeguards encompass, on average, 81% of their Extant distribution; however, the quality and breadth of protection varies dramatically across countries and species. Smalltooth sawfish currently has the least amount of such coverage of only half (49%) of Extant distribution. The global conservation strategy specifies actions to protect sawfish and their habitats. Such actions are urgently warranted to avoid global extinction and to restore robust populations for the benefit of coastal ecosystem function and biodiversity.
Keywords: functional redundancy; habitat degradation and loss; mangrove; range contraction; stuary

Global conservation outcomes depend on marine protected areas with five key features - Graham J. Edgar; Rick D Stuart-Smith; Willis, T J; Stuart J. Kininmonth; Baker, Susan C.; Banks, S.; Neville Barrett; Becerro, Mikel A.; Anthony T F Bernard; Just Berkhout; Buxton, C.D.; Campbell, Stuart J.; et al. (Nature, 2014)
In line with global targets agreed under the Convention on Biological Diversity, the number of marine protected areas (MPAs) is increasing rapidly, yet socio-economic benefits generated by MPAs remain difficult to predict and under debate1, 2. MPAs often fail to reach their full potential as a consequence of factors such as illegal harvesting, regulations that legally allow detrimental harvesting, or emigration of animals outside boundaries because of continuous habitat or inadequate size of reserve3, 4, 5. Here we show that the conservation benefits of 87 MPAs investigated worldwide increase exponentially with the accumulation of five key features: no take, well enforced, old (>10 years), large (>100 km2), and isolated by deep water or sand. Using effective MPAs with four or five key features as an unfished standard, comparisons of underwater survey data from effective MPAs with predictions based on survey data from fished coasts indicate that total fish biomass has declined about two-thirds from historical baselines as a result of fishing. Effective MPAs also had twice as many large (>250 mm total length) fish species per transect, five times more large fish biomass, and fourteen times more shark biomass than fished areas. Most (59%) of the MPAs studied had only one or two key features and were not ecologically distinguishable from fished sites. Our results show that global conservation targets based on area alone will not optimize protection of marine biodiversity. More emphasis is needed on better MPA design, durable management and compliance to ensure that MPAs achieve their desired conservation value. New York Times editorial - 15 February 2014

A Guide to Sharks of Kakadu Rivers - PM Kyne (2014)
This user-friendly guide will help in the identification of sharks found in Kakadu National Park rivers (the Alligator Rivers region).  It includes photos and details of the threatened Glyphis species (Northern River Shark and Speartooth Shark) and the non-threatened Bull Shark.  It also provides information on the conservation status and protected status of the river sharks species, along with advice on safe handling and release. The guide will be of interest to recreational fishers, Indigenous fishers, commercial fishers (outside of Kakadu National Park) and Park users.  Further Information on the sawfish and sharks project Where can I get a copy? Download a hard copy at Item link below, view a web version or request a hard copy.  Copies will also be available at the Kakadu National Park Visitor Centre, resorts, cultural centres,recreational fishing clubs and shops from April 2014

Invertebrate diversity of the unexplored marine western margin of Australia: taxonomy and implications for global biodiversity - Gary C. B. Poore; Avery, Lynda; Blażewicz-Paszkowycz, Magda; Browne, Joanna; Bruce, Niel L.; Gerken, Sarah; Glasby, Chris; Greaves, Elizabeth; Anna W McCallum; Staples, David; Syme, Anna; Taylor, Joanne; et al. (Marine Biodiversity, 2014)
However derived, predictions of global marine species diversity rely on existing real data. All methods, whether based on past rates of species descriptions, on expert opinion, on the fraction of undescribed species in samples collected, or on ratios between taxa in the taxonomic hierarchy, suffer the same limitation. Here we show that infaunal macrofauna (crustaceans and polychaetes) of the lower bathyal depth range are underrepresented among available data and documented results from Australia. The crustacean and polychaete fauna (only partially identified) of the bathyal continental margin of Western Australia comprised 805 species, representing a largely novel and endemic fauna. Overall, 94.6% of crustacean species were undescribed, while 72% of polychaete species were new to the Australian fauna, including all tanaidaceans, amphipods, and cumaceans, as well as most isopods. Most species were rare, and the species accumulation rate showed no sign of reaching an asymptote with increasing area sampled. Similar data are likely for the largely unexplored bathyal regions. This leads us to conclude that the numbers upon which extrapolations to larger areas are based are too low to provide confidence. The Southern Australian and Indo-West Pacific deep-sea regions contribute significantly to global species diversity. These regions and bathyal and abyssal habitats generally are extensive, but are so-far poorly sampled. They appear to be dominated by taxonomically poorly worked and species-rich taxa with limited distributions. The combination of high species richness among infaunal taxa—compared to better known taxa with larger individuals, higher endemism than presently acknowledged because of the presence of cryptic species, the low proportion of described species in these taxa, and the vast extent of unexplored bathyal and abyssal environments—will lead to further accumulation of new species as more and more deep sea regions are explored. It remains to be tested whether ratios of 10 or more undescribed to described species, found in this study for the dominant taxa and for the deep Southern Ocean and the Indo-West Pacific, are replicable in other areas. Our data and similar figures from other remote regions, and the lack of faunal overlap, suggest that Appeltans et al.’s (Current Biology 22:1–14, 2012) estimate that between one-third and two-thirds of the world’s marine fauna is undescribed is low, and that Mora et al.’s (PLoS Biol 9(8):e1001127. doi:10.1371/journal.pbio.1001127, 2011) of 91% is more probable. We conclude that estimates of global species, however made, are based on limited data.

Large-scale distribution of three deep-water squaloid sharks:Integrating data on sex, maturity and environment - Moura, Teresa; Jones, Emma; Clarke, Maurice W.; Cotton, Charles F.; Crozier, Paul; Ross K Daley; Diez, Guzman; Dobby, Helen; Dyb, Jan E.; Fossen, Inge; S. B. Irvine; Jakobsdottir, Klara; et al. (Fisheries Research, 2014)
Deep-water sharks exhibit species-specific reproductive strategies, which include segregation by sex, size and reproductive stage. However, due to the wide spatial distribution of most species, available information, usually collected at a regional scale, is usually not adequate to infer species reproductive spatial dynamics. This study draws together information on the distribution of reproductive stages of three species of squaliform sharks: Portuguese dogfish Centroscymnus coelolepis (Somniosidae), leafscale gulper shark Centrophorus squamosus (Centrophoridae) and birdbeak dogfish Deania calcea (Centrophoridae), gathering data from several geographical areas from the Atlantic, Indian and Pacific Oceans. For each species we analysed the sex ratio and the spatial patterns of reproductive stages within regions, considering the influence of geographical area, depth, season, temperature and salinity. The combination of statistical methods used in this study successfully identified a number of life history patterns which reflect different use of habitats by sex and life cycle stage. Pregnant females of the three species are spatially segregated, inhabiting shallower and/or warmer waters. In the case of the leafscale gulper shark this segregation might be associated with large scale migrations. In contrast, in Portuguese dogfish all adult maturity stages occur in the same geographical area. Pregnant female birdbeak dogfish were rare in all samples. Larger immature specimens of all the three species distribute deeper than the remaining maturity stages in most of the regions analysed. Mature males of leafscale gulper shark and birdbeak dogfish were more broadly distributed than mature females, supporting the possibility of sex-biased dispersal. Neonates and small sized specimens were scarce in the Northeast Atlantic potentially explained by their concentration in nurseries, and/or by gear selectivity. Management measures will benefit from considering the geographic scale of demographic variation between species. However, standardized collaborative approaches will be needed for comprehensive assessment.
Keywords: Commercial fishery data; Deep-sea; Life stage; Population structure; Survey dataa

Limited phylogeographic structure for five bathyal ophiuroids at continental scales. - Tim O'Hara; Phillip R England; R. Gunasekera; Naughton, Kate M. (Deep Sea Research Part I: Oceanographic Research Papers, 2014)
There have been comparatively few large-scale studies on spatial genetic structure of bathyal seafloor fauna, despite the importance of these data to the successful management of the world's oceans. We use a comparative analysis of mitochondrial DNA from five bathyal (200–3500 m) species of brittle-stars (Ophiuroidea) to assess phylogeographic structure along an extensive (8000 km) longitudinal gradient at temperate latitudes (28–56°S) from south-west Australia (113°E) to seamounts east of New Zealand (175°W). We found no evidence of a genetic discontinuity between Australia and New Zealand, either across the temperate Tasman Sea or across the Southern Ocean between the South Tasman Rise and the Macquarie Ridge. However, there were latitudinal phylogeographical breaks between tropical, temperate and polar regions; longitudinal breaks across the eastern Indian Ocean; and a bathymetric break at approximately 1700 m. Although there was limited regional structure in the frequency of haplotype distributions within the major clades, and no clade appeared to be strictly panmictic, the regional structure in general was not concordant with a simple isolation-by-distance model. Demographic structure varied with three clades having a simplified haplotype network, low effective population sizes and no evidence of significant population expansion, and two clades having a high diversity of haplotypes, relatively high effective population sizes and signs of recent population expansion. These results are discussed with respect to putative dispersal strategies. We hypothesise that the ‘brooding’ species produce both brooded young and pelagic larvae, allowing for both the maintenance of local populations and long-distance dispersal.
Keywords: Australia; continental slope; Lecithotrophy; Mitochondrial DNA; New Zealand; Planktotrophy; Seamounts; Viviparity

Lipid, Fatty Acid and Energy Density Profiles of White Sharks: Insights into the Feeding Ecology and Ecophysiology of a Complex Top Predator - Pethybridge, Heidi R.; Parrish, Christopher C.; Barry Bruce; Jock W. Young; Nichols, Peter D. (PLoS ONE, 2014)
Lipids are major sources of metabolic energy in sharks and are closely linked to environmental conditions and biological cycles, such as those related to diet, reproduction and migration. In this study, we report for the first time, the total lipid content, lipid class composition and fatty acid profiles of muscle and liver tissue of white sharks, Carcharodon carcharias, of various lengths (1.5–3.9 m), sampled at two geographically separate areas off southern and eastern Australia. Muscle tissue was low in total lipid content (<0.9% wet mass, wm) and was dominated by phospholipids (>90% of total lipid) and polyunsaturated fatty acids (34±12% of total fatty acids). In contrast, liver was high in total lipid which varied between 51–81% wm and was dominated by triacylglycerols (>93%) and monounsaturated fatty acids (36±12%). With knowledge of total lipid and dry tissue mass, we estimated the energy density of muscle (18.4±0.1 kJ g−1 dm) and liver (34.1±3.2 kJ g−1 dm), demonstrating that white sharks have very high energetic requirements. High among-individual variation in these biochemical parameters and related trophic markers were observed, but were not related to any one biological or environmental factor. Signature fatty acid profiles suggest that white sharks over the size range examined are generalist predators with fish, elasmobranchs and mammalian blubber all contributing to the diet. The ecological applications and physiological influences of lipids in white sharks are discussed along with recommendations for future research, including the use of non-lethal sampling to examine the nutritional condition, energetics and dietary relationships among and between individuals. Such knowledge is fundamental to better understand the implications of environmental perturbations on this iconic and threatened species.

Marine Biodiversity Hub Annual Work Plan 2014 - Nicholas J. Bax (2014)
Keywords: annual research plan

Mining and biodiversity IN Biodiversity - Science and Solutions for Australia - Anderson, Alan; Cook, Garry; Nicholas J. Bax (Biodiversity - Science and Solutions for Australia, 2014)
Mining occurs throughout most regions of Australia, but its direct impacts on biodiversity are relatively limited compared with other major land uses because the areas affected are generally small. The greatest potential for biodiversity impacts occurs through cumulative effects of multiple projects in prospective regions, including indirect impacts from regional development; these are best managed by strategic assessments that consider whole-of-region development in the long term. In the past, rehabilitation projects following mining simply aimed to establish vegetation cover. Now, projects increasingly seek to develop self-sustaining ecosystems that interact sustainably with the surrounding landscape. Unavoidable impacts on biodiversity can be partially compensated for (or ‘offset’) through activities that provide conservation benefits elsewhere. Given the wealth created, there are opportunities for mining to leave a positive legacy for biodiversity conservation in the broader region.   Chapter 11 Mining and biodiversity - download here or book can be downloaded from  http://www.publish.csiro.au/pid/6967.htm

Mitogenomics of the Speartooth Shark challenges ten years of control region sequencing - Pierre Feutry; PM Kyne; Richard D. Pillans; Xiao Chen; Gavin J. P. Naylor; Grewe, Peter M. (BMC Evolutionary Biology, 2014)
Mitochondrial DNA markers have long been used to identify population boundaries and are now a standard tool in conservation biology. In elasmobranchs, evolutionary rates of mitochondrial genes are low and variation between distinct populations can be hard to detect with commonly used control region sequencing or other single gene approaches. In this study we sequenced the whole mitogenome of 93 Critically Endangered Speartooth Shark Glyphis glyphis from the last three river drainages they inhabit in northern Australia.
Keywords: D-loop; Dispersal; Elasmobranchs; IUCN Red List; Low genetic diversity; Philopatry; Population genetics

Mixture models for multi-species and environmental data - Scott D Foster; David I. Warton; Francis K.C. Hui; Ross Darnell; Givens, Geof; Grant J Dornan (International Biometrics Conference, 2014)
This poster was presented for the International Biometric Conference, held in Florence from 6 to 11 July 2014. Ecological inference and management decisions often depend on data from many species. A proper and useful statistical analysis quantifies the important patterns of variation, whilst reducing the complexity in multi-species data. Currently, analysis is frequently done by: 1) performing species-by-species analyses (e.g. univariate regression and extensions) and then combining results, or 2) by combining data (clustering) and then performing a group-by-group analysis. Neither of the standard approaches are entirely satisfactory as important aspects of the variance in the data can be lost when moving from step to step. Also, the propagation of uncertainty is difficult and is subsequently (often) ignored. We introduce two models, based on mixture models, that address these issues. One model type, species archetype models (SAMs) exploits similarities in individual species’ responses to the environment. The second type, regions of common profile (RCP) models, exploits similarities in the assemblage patterns at each site.

Model-based approaches to unconstrained ordination - Francis K.C. Hui; Taskinen, Sara; Pledger, Shirley; Scott D Foster; David I. Warton (Methods in Ecology and Evolution, 2014)
Summary Unconstrained ordination is commonly used in ecology to visualize multivariate data, in particular, to visualize the main trends between different sites in terms of their species composition or relative abundance. Methods of unconstrained ordination currently used, such as non-metric multidimensional scaling, are algorithm-based techniques developed and implemented without directly accommodating the statistical properties of the data at hand. Failure to account for these key data properties can lead to misleading results. A model-based approach to unconstrained ordination can address this issue, and in this study, two types of models for ordination are proposed based on finite mixture models and latent variable models. Each method is capable of handling different data types and different forms of species response to latent gradients. Further strengths of the models are demonstrated via example and simulation. Advantages of model-based approaches to ordination include the following: residual analysis tools for checking assumptions to ensure the fitted model is appropriate for the data; model selection tools to choose the most appropriate model for ordination; methods for formal statistical inference to draw conclusions from the ordination; and improved efficiency, that is model-based ordination better recovers true relationships between sites, when used appropriately.
Keywords: correspondence analysis; latent variable model; Mixture model; multivariate analysis; non-metric multidimensional scaling

Model-Based Thinking for Community Ecology - David I. Warton; Scott D Foster; De'ath, Glenn; Stoklosa, Jakub; Piers K Dunstan (Plant Ecology, 2014)
In this paper, a case is made for the use of model-based approaches for the analysis of community data. This involves the direct specification of a statistical model for the observed multivariate data. Recent advances in statistical modelling mean that it is now possible to build models that are appropriate for the data which address key ecological questions in a statistically coherent manner. Key advantages of this approach include interpretability, flexibility, and efficiency, which we explain in detail and illustrate by example. The steps in a model-based approach to analysis are outlined, with an emphasis on key features arising in a multivariate context. A key distinction in the model-based approach is the emphasis on diagnostic checking to ensure that the model provides reasonable agreement with the observed data. Two examples are presented that illustrate how the model-based approach can provide insights into ecological problems not previously available. In the first example, we test for a treatment effect in a study where different sites had different sampling intensities, which was handled by adding an offset term to the model. In the second example, we incorporate trait information into a model for ordinal response in order to identify the main reasons why species differ in their environmental response.
Keywords: Community-level modelling; Fourth-corner problem; Model checking; multivariate analysis; Ordination; Species distribution models

More species of the Agononida incerta complex revealed by molecules and morphology (Crustacea: Decapoda: Anomura: Munididae) - Gary C. B. Poore; Andreakis, Nikos (Zootaxa, 2014)
Squat lobsters from Madagascar, Vanuatu, Papua New Guinea, Fiji, eastern Australia and French Polynesia belonging to the Agononida incerta (Henderson, 1888) species complex are described as four new species: A. madagascerta, A. polycerta, A. tasmancerta and A. vanuacerta. This brings to ten the number of species in this complex. All species are morphologically distinguishable only on the basis of the shape of the anterolateral margin of the telson and setation of the dactyli of pereopods 2-4. The morphological delineation of nine of the species and their taxonomic status are robustly supported by phylogenetic analysis of the partial 16S rDNA gene and the partial mitochondrial cytochrome oxidase subunit 1 genes, and in some cases by colour. A phylogenetic analysis of the nine species for which molecular data are available grouped the species in two clades, one of four species with facial spines on the upper surface of pereopod 4 and the other of five species lacking facial spines.
Keywords: Agononida; Anomura; Crustacea; Indo-West Pacific; mitochondrial genes; new species

NERP Marine Biodiversity Hub - Highlights 2013 brochure - Nicholas J. Bax (2014)
This brochure includes research highlights for 2013. A web version of this brochure is also available.

A new goatfish of the genus Upeneus (Mullidae) from Australia and Vanuatu, with inter- and intraspecific comparisons - Uiblein, Franz; Daniel C Gledhill (Marine Biology Research, 2014)
A new goatfish, Upeneus torres sp. nov. (Mullidae), is described based on 27 specimens from Australia and Vanuatu using a diversified alpha-taxonomy approach that integrates species, population and size-related allometric differences. Based on large sets of comparative morphological and colour data, diagnoses and inter- and intraspecific comparisons are provided for similar and/or co-occurring species of the so-called japonicus species group, Upeneus torres sp. nov., U. australiae, U. guttatus, and U. japonicus. The new species can be distinguished from all congeneric species by the following combination of characters: seven spines in the first dorsal fin; 13–15 (typically 14) pectoral-fin rays, 22–25 total gill rakers, barbel length 24–28 %SL, and pectoral-fin length 24–26 %SL. Fish smaller than 65 mm SL (‘subadults’) of the new species differ from larger conspecifics (‘adults’) in shallower body, larger eyes, longer anal-fin base, and longer caudal fin. Similar size-related differences were also found for the three other species. Phenotypic population differences in the new species as well as in U. guttatus are reported that may reflect character displacement in the latter. The need to study size–depth–habitat relationships in more detail, the phylogeography of individual populations, and the overall diversity of the genus Upeneus from Australian waters is discussed.
Keywords: Character displacement; diversified alpha-taxonomy; japonicus species group; new species; ontogeny; Upeneus torres

Notes on female reproductive biology and embryos of the brown guitarfish Rhinobatos schlegelii from the Penghu Islands, Taiwan - Schluessel, Vera; Giles, Jenny; PM Kyne (Ichthyological Research, 2014)
Litter size and details of the reproductive biology of female brown guitarfish Rhinobatos schlegelii from the Penghu Islands, Taiwan, are provided for the first time. Litter size ranged 1–14 (mean 8.5), with an embryonic sex ratio of 1:1. Vitellogenesis proceeded in parallel with gestation.
Keywords: elasmobranch; litter size; Rhinobatidae

Offsetting cumulative impacts of multiple developments: sequential vs strategic approaches - Fact sheet - Thebaud, Olivier; Boschetti, Fabio; Jennings, Sarah; Tony Smith; Pascoe, Sean (2014)
This work explores different approaches to offsetting  in the context of the cumulative impacts of multiple  developments over time. It looks at the effects of two types of delays. The first is delay in the recovery of  ecological  systems and associated ecosystem services following implementation of an offset . The second is delays in management action to restore impacted habitats after development. We compare four different offset strategies using a simplified model of a human/environmental system.

Phylogenomic resolution of the Class Ophiuroidea unlocks a global microfossil record - Tim O'Hara; Hugall, F.; Thuy, Ben; Adnan Moussalli (Current Biology, 2014)
Our understanding of the origin, evolution, and biogeography of seafloor fauna is limited because we have insufficient spatial and temporal data to resolve underlying processes. The abundance and wide distribution of modern and disarticulated fossil Ophiuroidea, including brittle stars and basket stars, make them an ideal model system for global marine biogeography if we have the phylogenetic framework necessary to link extant and fossil morphology in an evolutionary context. Here we construct a phylogeny from a highly complete 425-gene, 61-taxa transcriptome-based data set covering 15 of the 18 ophiuroid families and representatives of all extant echinoderm classes. We calibrate our phylogeny with a series of novel fossil discoveries from the early Mesozoic. We confirm the traditional paleontological view that ophiuroids are sister to the asteroids and date the crown group Ophiuroidea to the mid-Permian (270 ± 30 mega-annum). We refute all historical classification schemes of the Ophiuroidea based on gross structural characters but find strong congruence with schemes based on lateral arm plate microstructure and the temporal appearance of various plate morphologies in the fossil record. The verification that these microfossils contain phylogenetically informative characters unlocks their potential to advance our understanding of marine biogeographical processes.

Population genetic structure of the Pocillopora damicornis morphospecies along Ningaloo Reef, Western Australia - Luke Thomas; Gary A. Kendrick; Stat, M; Travaille, KL; Shedrawi, G; Kennington, WJ (Marine Ecology Progress Series, 2014)
The effective management of a coral reef system relies on a detailed understanding of the population structure of dominant habitat-forming species. For some corals, however, high levels of phenotypic plasticity have made species delineation based on morphological characteristics alone unreliable, suggesting that previous studies of population genetic structure may have been influenced by the inclusion of multiple genetic lineages in the analyses. We examined the population structure of the Pocillopora damicornis morphospecies along the World Heritage Ningaloo Coast, Western Australia, and recovered 2 mitochondrial haplotypes from sympatrically occurring colonies possessing morphological characteristics consistent with taxonomic classification of P. damicornis. Despite a high degree of genetic differentiation between these lineages, we detected low levels of unidirectional admixture between them, suggesting that reproductive barriers are not fully developed. We found dual modes of reproduction for both lineages with considerable variation in the contribution of sexual reproduction among sample sites. Lastly, we identified a high dispersal potential of sexually produced propagules in the most common lineage with positive spatial autocorrelation detected over distances up to 60 km. Based on these results, it appears that populations of P. damicornis have a high capacity to recover from environmental perturbations as long as the effects of disturbances are patchy across Ningaloo Reef.
Keywords: Dispersal; Ningaloo Reef; Pocillopora damicornis; resilience

Predictive Mapping of Seabed Substrata Using High-Resolution Multibeam Data - Z Huang; Justy P W Siwabessy; Scott L Nichol; Brendan P Brooke (Marine Geology, 2014)
This study explores the full potential of high-resolution multibeam data for the automated and accurate mapping of complex seabed features under a predictive modelling framework. For an area of seabed on the Carnarvon shelf in Western Australia, morphometric variables and textural measures were derived from multibeam bathymetry and backscatter data. Several feature extraction approaches were applied to backscatter angular response curves to obtain new features. These derivatives and new features were used separately and in combination in the predictions. Despite the complex distribution of various hard substrata within the study area, we achieved a nearly perfect prediction of “hard vs soft” seabed types with an AUC (Area Under Curve) close to 1.0. The predictions were also satisfactory for gravel, sand and mud content, with R2 values that range from 0.55 to 0.73. This study demonstrates that using a full range of derivatives and new features from both multibeam bathymetry and backscatter data optimises the accuracy of seabed mapping. From the modelled relationships between sediment properties and multibeam data, we confirmed that coarser sediment generally generates stronger backscatter return. Importantly, the results again highlight the advantages of applying proper feature extraction approaches over using original backscatter angular response curves.
Keywords: Angular response curves; Backscatter; bathymetry; Feature extraction; multibeam; Prediction; Seabed mapping

Predictive mapping of soft bottom benthic biodiversity using a surrogacy approach - Z Huang; Matthew McArthur; Rachel Przeslawski; Justy P W Siwabessy; Scott L Nichol; Brendan P Brooke (Marine and Freshwater Research, 2014)
A key requirement for informed marine-zone management is an understanding of the spatial patterns of marine biodiversity, often measured as species richness, total abundance or presence of key taxa. In the present study, we focussed on the diversity of benthic infauna and applied a predictive modelling approach to map biodiversity patterns for three study sites on the tropical Carnarvon shelf of Western Australia. A random forest decision tree model was used to generate spatial predictions of two measures of infaunal diversity, namely, species richness and total abundance. Results explained between 20% and 37% of the variance of each measure. The modelling process also identified potential physical surrogates for species richness and abundance, with sediment physical properties ranked as most important across the study region. Specifically, coarse-grained heterogeneous sediments were associated with higher infaunal species richness and total abundance. Seabed topographic properties were also important at the local scale. The study demonstrated the value of a surrogacy approach to the prediction of biodiversity patterns, particularly when the number of biological samples was limited. Such an approach may facilitate an understanding of ecosystem processes in the region and contribute to integrated marine management.
Keywords: Carnarvon shelf; infauna; surrogates; Western Australia

Productivity enhances benthic species richness along an oligotrophic Indian Ocean continental margin - Anna W McCallum; Skipton N. C. Woolley; Blażewicz-Paszkowycz, Magda; Browne, Joanna; Gerken, Sarah; Rudy J Kloser; Gary C. B. Poore; Staples, David; Syme, Anna; Taylor, Joanne; Walker-Smith, Genefor; Williams, Alan; et al. (Global Ecology and Biogeography, 2014)
Aims Marine soft sediments cover much of the deep ocean and are one of the largest habitats in the world, yet much of our understanding about their diversity is based on sampling in the North Atlantic. The deep-sea benthos provides a simplified environment in which to explore the processes which maintain species richness. Here we investigate the influence of energy and habitat complexity on benthic species richness along an oligotrophic continental margin within the Indian Ocean. Location The upper continental margin of western Australia (c. 13–35° S, 100–1000 m depth). Methods We examined the species richness of selected polychaetes (Annelida) and crustaceans in sediment grab samples. We used generalized linear models and hierarchical partitioning to examine the relationship and relative importance of temperature, productivity (particulate organic carbon flux, net primary productivity and depth) and habitat complexity (sediment particle size diversity and grain size) on species richness at 51 sites. Results In contrast to benthic studies in the North Atlantic, we found that species richness was higher on the shelf than on the slope. Species richness was positively correlated with net primary productivity; this relationship was influenced by high species richness in two areas where oceanic mixing is known to enhance primary productivity. Habitat heterogeneity and temperature were less influential. Main conclusion This study represents one of the first extensive quantitative studies of deep-water benthos in the Indo-West Pacific, and provides further evidence that bathymetric gradients of species richness are variable between regions, probably due to variation in local oceanography and productivity regimes. Our findings provide support for the overriding influence of productivity on species richness, even over relatively small ranges in depth and productivity. As climate change is expected to modify biogeochemical fluxes to the deep seafloor, this is likely to affect the communities of deep-sea fauna.
Keywords: Crustaceans; Leeuwin Current; macrobenthos; Peracarida; POC flux; polychaetes; quantitative

Protocols for surveying and tagging sawfishes and river sharks - PM Kyne; Richard D. Pillans (2014)
Aim: This document will establish best practice guidelines for safe and ethical research and monitoring of threatened sawfishes and river sharks in Australia. It covers surveying, handling, processing (data collection), tagging and releasing sawfishes and river sharks. Scope: This manual is designed specifically for threatened euryhaline elasmobranchs - sawfishes (Pristis species) and river sharks (Glyphis species) - in coastal, estuarine and freshwater systems. However, it also has wider application to elasmobranchs (sharks and rays) in general. Audience: Environmental consultants (not specifically trained to work on these species; in relation, but not exclusive to, environmental impact assessments), State and Territory agencies that undertake environmental assessments and approvals, research academics and students, Commonwealth, State and Territory fisheries agency staff, national park staff, traditional owners and Indigenous ranger groups, and the Commonwealth Department of the Environment. Application: For use by consultants when undertaking surveys for threatened sawfishes and river sharks for environmental impact assessments; for researchers and resource management staff undertaking activities related to sawfishes and river sharks; for the Department of the Environment and other Commonwealth, State and Territory Government Departments when assessing research proposals and addressing referred actions. This document arises from a need to develop a standardised procedure for all aspects of research and monitoring associated with sawfishes and river sharks. It recognises that issues such as excessive handling and prolonged exposure to the sun, incorrect tagging approaches and tag biofouling have previously occurred causing adverse effects on animals (issues not unique to just these species, having occurred more widely with elasmobranchs). This document aims to alleviate these adverse effects through awareness, education and standardised procedures. This document also serves to maximise the amount of data collected from each capture of these species and provide a standard format for the collection of data across Australia. Reducing the risks of research and monitoring and making the most value of any data collected will support the Recovery Plan for these species (DOE 2014). It is recommended that research or monitoring on other species using fishing/survey gear which may potentially interact with sawfishes and river sharks adhere to these protocols in order to minimise their impact. While these protocols have been developed specifically for sawfishes and river sharks of northern Australia, they may generally be applicable to research and surveying of these species in other locations, and more broadly to other elasmobranch species. However, local conditions and species-specific factors will need to be considered. All research including surveys, monitoring and tagging requires valid permits from the relevant State/Territory and/or Commonwealth agencies. Additionally, procedures are required to be approved by an independent Animal Ethics Committee (see research permits section, page 36).

Putting names to a sea of faces - standardising the flora and fauna classification of Australian marine images (CATAMI) - Althaus, Franziska; Annabel Ozimec (2014)
This poster explains the system of standardising the flora and fauna classification of Australian marine images using Collaborative and Automated Tools for the Analysis of Marine Imagery and video (CATAMI) CATAMI, a collaborative national project, has devised a common language for identifying and naming marine life pictured in underwater photographs and video. The system employs a standardised combination of high-level taxonomy (phylum, order, class) and morphological (shape, growth-form) characteristics that can be determined from a picture. This provides greater consistency than traditional classification approaches that rely on the handling of specimens. Put more simply, photographs and video provide a safe, non-destructive and efficient way to examine and monitor marine habitats. To be useful on a national scale, however, all the life forms they reveal must be named in a consistent way. A new classification system devised by Australia’s CATAMI project provides that common language. This poster is based on the original pictorial guide produced by CATAMI project partners and contributors: http://www.nerpmarine.edu.au/document/catami-classification-scheme-scoring-marine-biota-and-substrata-underwater-imagery Download the high resolution version of the poster at the Item link below or view the low res version here CONTACTS Further information: http://catami.github.io/ REQUEST A POSTER Request a free copy of this poster and others produced by the Hub.

Quantifying fish assemblages in large, offshore marine protected areas: an Australian case study - Nicole A. Hill; Neville Barrett; E Lawrence; J Hulls; Jeffrey M Dambacher; Scott L Nichol; Williams, Alan; Keith R Hayes (PLoS ONE, 2014)
s the number of marine protected areas (MPAs) increases globally, so does the need to assess if MPAs are meeting their management goals. Integral to this assessment is usually a long-term biological monitoring program, which can be difficult to develop for large and remote areas that have little available fine-scale habitat and biological data. This is the situation for many MPAs within the newly declared Australian Commonwealth Marine Reserve (CMR) network which covers approximately 3.1 million km2 of continental shelf, slope, and abyssal habitat, much of which is remote and difficult to access. A detailed inventory of the species, types of assemblages present and their spatial distribution within individual MPAs is required prior to developing monitoring programs to measure the impact of management strategies. Here we use a spatially-balanced survey design and non-extractive baited video observations to quantitatively document the fish assemblages within the continental shelf area (a multiple use zone, IUCN VI) of the Flinders Marine Reserve, within the Southeast marine region. We identified distinct demersal fish assemblages, quantified assemblage relationships with environmental gradients (primarily depth and habitat type), and described their spatial distribution across a variety of reef and sediment habitats. Baited videos recorded a range of species from multiple trophic levels, including species of commercial and recreational interest. The majority of species, whilst found commonly along the southern or south-eastern coasts of Australia, are endemic to Australia, highlighting the global significance of this region. Species richness was greater on habitats containing some reef and declined with increasing depth. The trophic breath of species in assemblages was also greater in shallow waters. We discuss the utility of our approach for establishing inventories when little prior knowledge is available and how such an approach may inform future monitoring efforts within the CMR network.

A re-evaluation of the size of the white shark (Carcharodon carcharias) population off California, USA - George H. Burgess; Barry Bruce; Cailliet, Gregor M.; Goldman, Kenneth J.; Grubbs, R. Dean; Lowe, Christopher G.; Aaron M MacNeil; Mollet, Henry F.; Weng, Kevin C.; O'Sullivan, John B. (PLoS ONE, 2014)
White sharks are highly migratory and segregate by sex, age and size. Unlike marine mammals, they neither surface to breathe nor frequent haul-out sites, hindering generation of abundance data required to estimate population size. A recent tag-recapture study used photographic identifications of white sharks at two aggregation sites to estimate abundance in “central California” at 219 mature and sub-adult individuals. They concluded this represented approximately one-half of the total abundance of mature and sub-adult sharks in the entire eastern North Pacific Ocean (ENP). This low estimate generated great concern within the conservation community, prompting petitions for governmental endangered species designations. We critically examine that study and find violations of model assumptions that, when considered in total, lead to population underestimates. We also use a Bayesian mixture model to demonstrate that the inclusion of transient sharks, characteristic of white shark aggregation sites, would substantially increase abundance estimates for the adults and sub-adults in the surveyed sub-population. Using a dataset obtained from the same sampling locations and widely accepted demographic methodology, our analysis indicates a minimum all-life stages population size of >2000 individuals in the California subpopulation is required to account for the number and size range of individual sharks observed at the two sampled sites. Even accounting for methodological and conceptual biases, an extrapolation of these data to estimate the white shark population size throughout the ENP is inappropriate. The true ENP white shark population size is likely several-fold greater as both our study and the original published estimate exclude non-aggregating sharks and those that independently aggregate at other important ENP sites. Accurately estimating the central California and ENP white shark population size requires methodologies that account for biases introduced by sampling a limited number of sites and that account for all life history stages across the species' range of habitats.

Regional-scale patterns and predictors of species richness and abundance across twelve major tropical inter-reef taxa - Sutcliffe, P. R.; Camille Mellin; C Roland Pitcher; Possingham, H. P.; M Julian Caley (Ecography, 2014)
Species richness and abundance are biodiversity metrics widely used to describe and estimate changes in biodiversity. Studies of marine species richness and abundance typically focus on one, or just a few, taxa. Consequently, it is currently not possible to understand the performance of predictors of species richness and abundance across marine taxa. Using a taxonomically comprehensive dataset of twelve major taxa of flora and fauna from eight phyla sampled from the inter-reef seabed region of the Great Barrier Reef, Australia, we used boosted regression trees to test the performance of fourteen environmental and spatial predictors of species richness and abundance. Sediment composition predicted richness best for all taxa: gravel contributed up to 39% relative influence for one group and all taxa had low richness in muddy habitats. Sea surface temperature, seabed current shear stress, depth and latitude were also influential predictors for species richness for eight groups. Sediment was frequently an influential predictor for abundance also, while distance to domain (reef/coast) and longitude were relatively influential for six taxa. Within-site richness was correlated between nearly all pairs of taxa, as was within-site abundance, however ρ values were low. Overall, model performance was high, explaining up to 62% deviance of species richness, and 38% of abundance. Typically, deviance explained was greater for richness than abundance and may indicate that some drivers of species richness operate independently of any effects on species richness mediated by their effect on abundance. Deviance explained differed most between richness and abundance for bryozoans (23.3% difference) and soft corals (15.2% difference). While sediments were consistently the best predictors across all taxa, the inconsistent influence of all other predictors across taxonomic groups, as well as the low correlation of richness and abundance across taxonomic groups, cautions against predicting regional patterns of species richness and abundance from few taxa.

Seabed Habitats of Flinders Commonwealth Marine Reserve - Northeast Tasmania - Scott L Nichol (2014)
Published on Jun 26, 2014 by Geoscience Australia This short video gives an overview of a marine survey on the RV Challenger of the Flinders Commonwealth Marine Reserve, located off northeast Tasmania. The survey area, located about 50 kilometres south east of Flinders Island, is recognised as an important area for a range of marine life, including diverse sponge gardens that grow on rocky reefs, sea birds and migrating whales. This survey is one of a series of seabed mapping projects in targeted areas of Australia's Commonwealth marine territory being undertaken by Marine Biodiversity Hub as part of the National Environmental Research Program.

Severe loss of anemones and anemonefishes from a premier tourist attraction at the Houtman Abrolhos Islands, Western Australia - Luke Thomas; Stat, Michael; Gary A. Kendrick; Hobbs, Jean-Paul A. (Marine Biodiversity, 2014)
The Houtman Abrolhos Islands (29° 00′ S) are the southernmost coral reefs in the Indian Ocean, located 60 km off central Western Australia. The “Anemone Lump”, a 185 × 400 m reef that rises steeply from 38 m to 4 m, is the premier dive site at the Islands, with a dedicated underwater tourist trail. The site is a fish habitat protection area and tourist attraction due to its abundance of anemones (Entacmaea quadricolor) and anemonefish (Amphiprion clarkii).

Shelf and deep-sea sedimentary environments and physical benthic disturbance regimes: A review and synthesis - Harris, Peter T. (Marine Geology, 2014)
Physical disturbances of the seafloor play a key role in ecosystem function and are postulated to exert control over spatial patterns of biodiversity. This review investigates the role of natural physical sedimentological processes that occur in shelf, slope and abyssal environments that also act as disturbances to benthic ecosystems and which, under certain circumstances, give rise to benthic disturbance regimes. Physical sedimentological processes can cause both press (process that causes a disturbance by acting over a timespan that is intolerable to benthos) and pulse (process that causes a disturbance by exceeding a threshold above which benthos are unable to remain attached to the seabed or are buried under rapidly deposited sediment) types of disturbance. On the continental shelf, pulse-type disturbances are due to temperate and tropical storm events, and press-type of disturbances identified here are due to the migration of bedforms and other sand bodies, and sustained periods of elevated turbidity caused by seasonally reversing wind patterns. On the continental slope and at abyssal depths, pulse-type disturbances are due to slumps, turbidity currents; benthic storms may cause either press or pulse type disturbances. A possible press-type of disturbance identified here is inter-annual changes in abyssal bottom current speed and/or direction. It is concluded that: 1) physical sedimentary disturbance regimes may characterize as much as 10% of the global ocean floor; 2) multidisciplinary research programs that integrate oceanography, sedimentology and benthic ecology to collect time series observational data sets are needed to study disturbance regimes; and 3) predictive habitat suitability modeling must include disturbance regime concepts, along with other biophysical variables that define the fundamental niches of marine species, in order to advance.
Keywords: abyssal; benthic storm; bottom currents; Continental shelf; continental slope; Disturbance regime; Intermediate disturbance hypothesis; physical sedimentology; seafloor; turbidity

Sponge biodiversity and ecology of the Van Diemen Rise and eastern Joseph Bonaparte Gulf, northern Australia - Rachel Przeslawski; Alvarez, Belinda; C Battershill; Smith, Tegan (Hydrobiologia, 2014)
Australia is increasingly recognised as a global hotspot for sponge biodiversity, but there is a knowledge gap about sponge communities in northern Australia, including those in Commonwealth Marine Reserves. We aim to quantify sponge biodiversity of the eastern Joseph Bonaparte Gulf and adjacent Van Diemen Rise (VDR) and to examine spatial and environmental patterns in community structure. Sponges were collected with a benthic sled from 65 sites encompassing five geomorphic features (bank, terrace, ridge, plain, and valley), study area (as a proxy for distance offshore) and three environmental variables (depth, substrate hardness, and slope). A total of 283 species were collected, representing four classes, 53 families and at least 117 genera. Sponge richness and biomass were related to those of other taxa. Sponge diversity was generally highest further offshore and on raised geomorphic features, particularly banks. Sponge assemblages on the same bank were more similar than those from different banks, although full interpretation of patterns is limited by the relatively low sampling effort. The current study will help facilitate integrated marine management by providing a baseline species inventory, supporting the VDR’s carbonate banks as a key ecological feature, and highlighting the importance of sponges as habitat providers and potential biological surrogates for monitoring.

Strong, but opposing, β-diversity-stability relationships affect coral reef conservation on the Great Barrier Reef, Australia - Camille Mellin; Bradshaw, CJA; Damien A. Fordham; M Julian Caley (Ocean Sciences Meeting, 2014)
Despite important implications for theoretical ecology and conservation biology, the empirical relationship between β-diversity and community stability remains equivocal. For example, β-diversity (the rate of species spatial turnover) underlies most conservation strategies that aim to include the most species in a restricted number of sites. However, whether maximizing β-diversity also maximizes the temporal stability of biological communities, a key predictor of extinction risk, remains largely untested. We compared the spatial and temporal dissimilarity of fish communities inhabiting the largest coral reef ecosystem on Earth, the Great Barrier Reef of Australia. Fish β-diversity, measured as spatial turnover in species composition, and temporal stability (inverse of turnover) of communities were inversely related indicating that high β-diversity was associated with greater temporal stability, and thus, lower extinction risk. Our results demonstrated a strong β-diversity-stability relationship when all taxa were combined. While β-diversity tended to be associated with greater temporal stability at the community level, for one taxon, surgeonfishes (Acanthuridae, one of the most abundant reef fish families), this relationship was reversed. Therefore, the same β-diversity-stability relationship cannot be indiscriminately assumed for all taxa. We detected no effects of extrinsic factors (latitude, α-diversity, or dispersal-related characteristics such as reef area and isolation) on these relationships between spatial versus temporal turnover. We conclude therefore that conservation strategies reliant on β-diversity will need to consider biotic factors such as taxon identity, and possibly functional group membership, to ensure the effectiveness of protection measures.

Strong but opposing β-diversity-stability relationships affect coral reef conservation - Camille Mellin; C. J. A. Bradshaw; D. A. Fordham; M Julian Caley (Proceedings of the Royal Society B: Biological Sciences, 2014)
The ‘diversity–stability hypothesis’, in which higher species diversity within biological communities buffers the risk of ecological collapse, is now generally accepted. However, empirical evidence for a relationship between b-diversity (spatial turnover in community structure) and temporal stability in community structure remains equivocal, despite important implications for theoretical ecology and conservation biology. Here, we report strong b-diversity–stability relationships across a broad sample of fish taxa on Australia’s Great Barrier Reef. These relationships were robust to random sampling error and spatial and environmental factors, such as latitude, reef size and isolation. While b-diversity was positively associated with temporal stability at the community level, the relationship was negative for some taxa, for example surgeonfishes (Acanthuridae), one of the most abundant reef fish families. This demonstrates that the b-diversity–stability relationship should not be indiscriminately assumed for all taxa, but that a species’ risk of extirpation in response to disturbance is likely to be taxon specific and trait based. By combining predictions of spatial and temporal turnover across the study area with observations in marine-protected areas, we conclude that protection alone does not necessarily confer temporal stability and that taxon-specific considerations will improve the outcome of conservation efforts.
Keywords: b-diversity; Bray–Curtis; disturbance; long-term monitoring; mantel; time series

Submarine Canyon Mapping - Z Huang; Johnathan T. Kool; Scott L Nichol (GEOHAB (Marine Geological and Biological Habitat Mapping) 2014 Conference, 2014)
New mapping by Geoscience Australia has identified 713 submarine canyons on the Australian margin, 95 of which are classified as shelf-incised canyons; the remainder are located on the continental slope and are termed ‘blind canyons’. Submarine canyons are well represented in the national network of marine protected areas, with 36% intersecting (whole or in part) a Commonwealth Marine Reserve. For all canyons, a range of metrics were derived to describe their form and distribution and used to classify canyons into a uniqueness category. This new information is being used in the analysis of large scale connectivity patterns between canyons and in turn will support the management of marine reserves. Prepared for GEOHAB 2014 conference.

Systematic global assessment of reef fish communities by the Reef Life Survey program - Graham J. Edgar; Rick D Stuart-Smith (Scientific Data, 2014)
The assessment of patterns in macroecology, including those most relevant to global biodiversity conservation, has been hampered by a lack of quantitative data collected in a consistent manner over the global scale. Global analyses of species’ abundance data typically rely on records aggregated from multiple studies where different sampling methods and varying levels of taxonomic and spatial resolution have been applied. Here we describe the Reef Life Survey (RLS) reef fish dataset, which contains 134,759 abundance records, of 2,367 fish taxa, from 1,879 sites in coral and rocky reefs distributed worldwide. Data were systematically collected using standardized methods, offering new opportunities to assess broad-scale spatial patterns in community structure. The development of such a large dataset was made possible through contributions of investigators associated with science and conservation agencies worldwide, and the assistance of a team of over 100 recreational SCUBA divers, who undertook training in scientific techniques for underwater surveys and voluntarily contributed skills, expertise and their time to data collection.
Keywords: Biodiversity; Community ecology; Conservation; Macroecology

Topographic determinants of mobile predator hotspots: Current knowledge and future directions - Phil J. Bouchet; Jessica J. Meeuwig; Salgado Kent, Chandra P.; Tom B. Letessier; Jenner, Curt K. (Biological Reviews, 2014)
Despite being identified as a driver of mobile predator aggregations (hotspots) in both marine and terrestrial environments, topographic complexity has long remained a challenging concept for scientists to visualise and a difficult parameter to estimate. It is only with the advent of high-speed computers and the recent popularisation of geographical information systems (GIS) that terrain attributes have begun to be quantitatively measured in three-dimensional space and related to wildlife dynamics, making the well-established field of geomorphometry (or ‘digital terrain modelling’) a discipline of growing appeal to biologists. Although a diverse array of numerical metrics is now available to describe the shape, geometry and physical properties of natural habitats, few of these are known to, or adequately used by, ecologists. In this review, we examine the nature and usage of 56 geomorphometrics extracted from the ecological modelling literature over a period of 32 years (1979–2011). We show that, in studies of mobile predators, numerous topographic variables have largely been overlooked in favour of single basic metrics that do not, on their own, fully capture the complexity of continuous landscapes. Based on a simulation approach, we assess the redundancy and correlation structure of these metrics and demonstrate that a majority are highly collinear. We highlight a suite of 7–8 complementary metrics which best explain topographic patterns across a bathymetric grid of the west Australian seafloor, and contend that field and analytical protocols should prioritise variables of these types, particularly when the responses of predator populations to physical habitat features are of interest. We suggest that prominent structures such as canyons, seamounts or mountain chains can serve as useful proxies for predator hotspots, especially in remote locations where access to high-resolution biological data is often limited.
Keywords: aggregations; complexity; geomorphometry; hotspots; landscape; metrics; predators; topography

Tropical Marginal Seas: Priority Regions for Managing Marine Biodiversity and Ecosystem Function - McKinnon, A. David; Williams, Alan; Jock W. Young; Daniela Ceccarelli; Piers K Dunstan; Brewin, Robert J.W.; Reg A. Watson; Brinkman, Richard; Cappo, Mike; Duggan, Samantha; Kelley, Russell; Ridgway, Ken; et al. (Annual Review of Marine Science, 2014)
Tropical marginal seas (TMSs) are natural subregions of tropical oceans containing biodiverse ecosystems with conspicuous, valued, and vulnerable biodiversity assets. They are focal points for global marine conservation because they occur in regions where human populations are rapidly expanding. Our review of 11 TMSs focuses on three key ecosystems—coral reefs and emergent atolls, deep benthic systems, and pelagic biomes—and synthesizes, illustrates, and contrasts knowledge of biodiversity, ecosystem function, interaction between adjacent habitats, and anthropogenic pressures. TMSs vary in the extent that they have been subject to human influence—from the nearly pristine Coral Sea to the heavily exploited South China and Caribbean Seas—but we predict that they will all be similarly complex to manage because most span multiple national jurisdictions. We conclude that developing a structured process to identify ecologically and biologically significant areas that uses a set of globally agreed criteria is a tractable first step toward effective multinational and transboundary ecosystem management of TMSs.
Keywords: Coral reef; deep sea; fisheries; management; pelagic; transboundary

Tuning Parameter Selection for the Lasso Regression using ERIC - Francis K.C. Hui; David I. Warton; Scott D Foster (Journal of the American Statistical Association, 2014)
The adaptive lasso is a commonly applied penalty for variable selection in regression modeling. Like all penalties though, its performance depends critically on the choice of tuning parameter. One method for choosing the tuning parameter is via information criteria, such as those based on AIC and BIC. However, these criteria were developed for use with unpenalized maximum likelihood estimators, and it is not clear that they take into account the effects of penalization. In this article, we propose the Extended Regularized Information Criterion (ERIC) for choosing the tuning parameter in adaptive lasso regression. ERIC extends the BIC to account for the effect of applying the adaptive lasso on the bias-variance tradeoff. This leads to a criterion whose penalty for model complexity is itself a function of the tuning parameter. We show the tuning parameter chosen by ERIC is selection consistent when the number of variables grows with sample size, and that this consistency holds in a wider range of contexts compared to using BIC to choose the tuning parameter. Simulation show that ERIC can significantly outperform BIC and other information criteria proposed (for choosing the tuning parameter) in selecting the true model. For ultra high-dimensional data (p > n), we consider a two-stage approach combining sure independence screening with adaptive lasso regression using ERIC, which is selection consistent and performs strongly in simulation.
Keywords: BIC; consistency; high-dimensional data; information criteria; penalized likelihood; regularization parameter; variable selection

Twenty years of high-resolution sea surface temperature imagery around Australia: inter-annual and annual variability - Scott D Foster; Griffin, David A.; Piers K Dunstan (PLoS ONE, 2014)
The physical climate defines a significant portion of the habitats in which biological communities and species reside. It is important to quantify these environmental conditions, and how they have changed, as this will inform future efforts to study many natural systems. In this article, we present the results of a statistical summary of the variability in sea surface temperature (SST) time-series data for the waters surrounding Australia, from 1993 to 2013. We partition variation in the SST series into annual trends, inter-annual trends, and a number of components of random variation. We utilise satellite data and validate the statistical summary from these data to summaries of data from long-term monitoring stations and from the global drifter program. The spatially dense results, available as maps from the Australian Oceanographic Data Network's data portal (http://www.cmar.csiro.au/geonetwork/srv/​en/metadata.show?id=51805), show clear trends that associate with oceanographic features. Noteworthy oceanographic features include: average warming was greatest off southern West Australia and off eastern Tasmania, where the warming was around 0.6°C per decade for a twenty year study period, and insubstantial warming in areas dominated by the East Australian Current, but this area did exhibit high levels of inter-annual variability (long-term trend increases and decreases but does not increase on average). The results of the analyses can be directly incorporated into (biogeographic) models that explain variation in biological data where both biological and environmental data are on a fine scale. A subsequent CSIRO study, published in 2018 in Nature Scientific Reports (see Global patterns of change and variation in sea surface temperature and chlorophyll a), applied the statistical approach above to seek and recover the necessary details from the aggregated data at a global scale. It identified how fine scale ocean structures respond to events including climate change. This statistical approach has now been ​adapted for use in the Australian sea surface temperature atlas which is available through the Australian Ocean Data Network.

Understanding community-habitat associations of temperate reef fishes using fine-resolution bathymetric measures of physical structure - Cameron, M.J; Vanessa L Lucieer; Neville Barrett; Craig R. Johnson; Graham J. Edgar (Marine Ecology Progress Series, 2014)
Multibeam sonar (MBS) hydro-acoustic technology allows for inexpensive, broad-scale, fine-resolution assessment of marine fish habitats. Parallel advancements in geographic information systems and new analytical techniques are providing researchers with the ability to generate informative surrogate predictors of biodiversity and species responses. The aim of this study was to determine whether fine-scale bathymetric derivatives of MBS survey data could be effectively applied as surrogates to explain spatial patterns in reef fish diversity and species-habitat relationships. In the absence of direct metrics of habitat, these derivatives might prove to be effective tools for marine spatial planning. Species-habitat relationships were examined across a marine reserve on the south-eastern coast of Tasmania at fine spatial scales using boosted regression tree analyses. The most important explanatory variables of community diversity were those describing the degree of reef aspect deviation from east and south (seemingly as a proxy for swell exposure), reef bathymetry (depth), plane and slope. Models could account for up to 30% of the spatial variability in measures of species diversity. Responses in species abundance and occurrence to habitat structure appeared to be largely species-specific at the scales investigated. Models accounted for up to 67% and 58% of the abundance and occurrence, respectively, for the southern hulafish Trachinops caudimaculatus. Our results demonstrate that multibeam-derived metrics of reef habitat structure, employed in combination with modern modelling approaches, have the potential to explain and predict fine-resolution patterns in temperate reef fish community structure. This knowledge is urgently required to effectively manage marine ecosystems and conserve biodiversity and fisheries resources.
Keywords: Bathymetric derivatives; Fish-habitat relationships; Physical structure; remote sensing; Temperate reefs

The use of economic valuation in coastal and marine decision-making - Fact sheet - Marre, Jean-Baptiste; Thebaud, Olivier; Pascoe, Sean; Coglan, Louise; Jennings, Sarah (2014)
Ecosystem services valuation (ESV) is a set of method s to estimate the economic value of ecosystem services.  Very little is known about the actual use and influence of ESV in decision - making even though its purpose is specifically to support ecosystem management. We developed nation - wide online  surveys that  collected information about  coastal and marine  managers’ perceptions regarding past and present use of  ESV (88 respondents) and examined  the perception of the general  public (256 respondents) regarding ESV and its usefulness in coastal and  marine management . This is important in view of their increasing participative role in decision - making process. We compared the different groups to shed light on the expectations and preferences of both sides, and to provide guidelines to foster the use of ESV in coastal and marine management.

The use of seabed scoured depressions as a proxy for near-seabed flow - K Picard; Lynda Radke; Justy P W Siwabessy; Howard, F; Scott L Nichol (GEOHAB (Marine Geological and Biological Habitat Mapping) 2014 Conference, 2014)
The Oceanic Shoals Commonwealth Marine Reserve (CMR), situated in tropical northern Australia, incorporates extensive areas of carbonate banks and terraces. These are recognised by the Australian Government as potential biodiversity hotspots. In September 2012, Geoscience Australia collected shallow seabed information to characterise the CMR and to better understand the carbonates banks and their role in supporting biodiversity. The survey area is located on the widest part of the Continental Shelf (250 km) which is subject to a storm-influenced micro tidal energy regime (mean range: <2 m). However, the coast immediately to the south is macro-tidal (~7 m). The net tidal direction is westerly and the sediment transport regime is flood-dominated (Porter-Smith et al., 2004). High-resolution mapping has revealed that the seafloor is characterised by multiple carbonate banks that rise tens of metres above otherwise vast soft-sediment plains.

Variable responses of benthic communities to anomalously warm sea temperatures on a high-latitude coral reef - Tom Bridge; Renata Ferrari; Bryson, Mitch; Renae Hovey; Will F. Figueira; Williams, Stefan B.; Oscar R. Pizarro; Harborne, Alastair R.; Byrne, Maria (PLoS ONE, 2014)
High-latitude reefs support unique ecological communities occurring at the biogeographic boundaries between tropical and temperate marine ecosystems. Due to their lower ambient temperatures, they are regarded as potential refugia for tropical species shifting poleward due to rising sea temperatures. However, acute warming events can cause rapid shifts in the composition of high-latitude reef communities, including range contractions of temperate macroalgae and bleachinginduced mortality in corals. While bleaching has been reported on numerous highlatitude reefs, post-bleaching trajectories of benthic communities are poorly described. Consequently, the longer-term effects of thermal anomalies on highlatitude reefs are difficult to predict. Here, we use an autonomous underwater vehicle to conduct repeated surveys of three 625 m2 plots on a coral-dominated high-latitude reef in the Houtman Abrolhos Islands, Western Australia, over a fouryear period spanning a large-magnitude thermal anomaly. Quantification of benthic communities revealed high coral cover (.70%, comprising three main morphospecies) prior to the bleaching event. Plating Montipora was most susceptible to bleaching, but in the plot where it was most abundant, coral cover did not change significantly because of post-bleaching increases in branching Acropora. In the other two plots, coral cover decreased while macroalgal cover increased markedly. Overall, coral cover declined from 73% to 59% over the course of the study, while macroalgal cover increased from 11% to 24%. The significant differences in impacts and post-bleaching trajectories among plots underline the importance of understanding the underlying causes of such variation to improve predictions of how climate change will affect reefs, especially at high-latitudes.

Variation and uncertainty in bathymetric slope calculations using geographical information systems - Dolan, Margaret F. J.; Vanessa L Lucieer (Marine Geodesy, 2014)
Bathymetry data from multibeam echosounders and other acoustic sources are now widely available in the form of digital terrain models, which are conveniently displayed as raster grids in desktop geographic information systems. Calculation of terrain vari- ables such as slope is a simple push-button operation in most geographic information systems; however, as we demonstrate here, there can be a great variation in the slope values obtained due to computation algorithms and resolution or analysis scale. This article also demonstrates how Monte Carlo simulation can be used to visualise uncer- tainty in the underlying bathymetry dataset and also how this uncertainty impacts on slope calculations.
Keywords: bathymetry; GIS; MAREANO; multibeam; slope; terrain model

With eyes wide open: a revision of species within and closely related to the Pocillopora damicornis species complex (Scleractinia; Pocilloporidae) using morphology and genetics - Schmidt-Roach, Sebastian; Karen J Miller; Lundgren, Petra; Andreakis, Nikos (Zoological Journal of the Linnean Society, 2014)
Molecular studies have been instrumental for refining species boundaries in the coral genus Pocillopora and revealing hidden species diversity within the extensively studied global species Pocillopora damicornis. Here we formally revise the taxonomic status of species closely related to and within the P. damicornis species complex, taking into account both genetic evidence and new data on morphometrics, including fine-scale corallite and coenosteum structure. We found that mitochondrial molecular phylogenies are congruent with groups based on gross-morphology, therefore reflecting species-level differentiation. However, high levels of gross morphological plasticity and shared morphological characteristics mask clear separation for some groups. Fine-scale morphological variation, particularly the shape and type of columella, was useful for differentiating between clades and provides an excellent signature of the evolutionary relationships among genetic lineages. As introgressive hybridization and incomplete lineage sorting complicate the delineation of species within the genus on the basis of a single species concept, the Unified Species Concept may represent a suitable approach in revising Pocillopora taxonomy. Eight species are herein described (P. damicornis, P. acuta, P. aliciae, P. verrucosa, P. meandrina, P. eydouxi, P. cf. brevicornis), including a novel taxon – Pocillopora bairdi sp. nov. (Schmidt-Roach, this study).
Keywords: Australia; coral; Cryptic species; evolution; fine-scale morphology; Great Barrier Reef; morphometric analysis; Speciation; species boundaries; Unified Species Concept

Assessing hidden species diversity in the coral Pocillopora damicornis from Eastern Australia - Schmidt-Roach, Sebastian; Lundgren, P.; Karen J Miller; Gerlach, Gabriele; Noreen, A. M. E.; Andreakis, Nikos (Coral Reefs, 2013)
The incredible range of morphological plasticity present in scleractinian corals has confused the taxonomy of the group, prompting the introduction of “ecomorphs” to explain the observed correlation between local environmental conditions and phenotypic variation. Pocillopora damicornis (Linnaeus, 1758) represents one of the best known examples of eco-phenotypic variation in scleractinian corals with a variety of forms and reproductive strategies reported across its global distribution range. Here, we reconstruct genealogical relationships of P. damicornis colonies collected from thirteen locations along the East Australian coast to examine the relationship between genetic and phenotypic diversity in this species. Haplotype networks computed from two mitochondrial DNA regions (CR, ORF) indicate that the range of morphotypes observed within this taxon fall into at least five genetically distinct mitochondrial lineages. Nuclear (HSP70, ITS2) haplowebs on the other hand recover sharp genetic discontinuities among three of the morphological groups. We conclude that P. damicornis from Eastern Australia constitutes a cryptic species complex. The misinterpretation of taxonomical units within P. damicornis may well explain its perceived variation in the ecology, biology and life history across its range.
Keywords: Cryptic; Ecomorphs; GBR; Phylogeny; Reproduction; Speciation

Assessing pelagic fish populations: the application of demersal video techniques to the mid-water environment - Tom B. Letessier; Jessica J. Meeuwig; Gollock, Matthew; Groves, Lloyd; Phil J. Bouchet; Chapuis, Lucille; Vianna, Gabriel M.S.; Kemp, Kirsty; Koldewey, Heather J. (Methods in Oceanography, 2013)
In the open ocean, the movements and habitat use of large mobile predators are driven by dynamic interactions between biological and physical variables and complex predator–prey relationships. Understanding the spatial and temporal distributions of pelagic fishes and sharks is a critical component of conservation and fisheries management. Here, we report on a novel non-extractive method for the study of pelagic wildlife, based on baited stereo-camera rigs. The mid-water rigs were derived from existing methodology commonly used in demersal fish surveys. We present new data from 66 moored deployments in Shark Bay, Western Australia (26°10′S, 113°06E) in seabed depths of up to 60 m as a demonstration of the rigs’ ability to resolve spatial variability in pelagic fish and shark assemblages, and to make accurate stereo-measurements of animal lengths. We observed 248 pelagic fishes and sharks from 27 species and 10 families and were able to distinguish between assemblages based nominally on location. We make some general recommendations on optimal deployment protocols and sampling effort regimes, based upon species accumulation rates and times of View the MathML sourceMaxN (maximum number of individuals of a given species in a single video frame). Regression analyses between high quality and low quality stereo-measurements of fish fork-lengths and range were highly significant, indicating that body lengths and distance estimates were consistent even when stereo-measurements were deemed of low quality. Mid-water stereo-video camera rigs represent an efficient tool for the rapid and non-extractive monitoring of pelagic fish and shark populations, with particular relevance for application in no-take marine protected areas.
Keywords: bait; cameras; marine reserves; monitoring; pelagic predators; stereo videography

Assessing the impact of multiple, cumulative, pressures - Fact sheet - Annabel Ozimec (2013)
Australia’s marine territory is affected by many different pressures. Their collective impacts are complex to understand and predict, yet central to the management of marine activities and biodiversity conservation.

Australian Marine Environmental Data: Descriptions and Metadata - Z Huang; Rachel Przeslawski; Johnathan T. Kool; Jin Li; Phil J. Bouchet; Scott L Nichol (Geoscience Australia Record, 2013)
This report provides detailed descriptions (metadata) of 45 Australian marine environmental datasets that have been generated and collated by the Marine Biodiversity Hub as part of Theme 3 – National Ecosystems Knowledge, Project 1 – Shelf and Canyon Ecosystems Functions and Processes. The report also includes a map for each dataset to illustrate coverage and general spatial structure. The datasets contain both marine environmental and biological variables from diverse data sources and include both new and updated information. Among them, the national bathymetry grid and derived products, seabed sediment grids, seabed exposure (GEOMACS) parameters, water quality data, the national canyon dataset and connectivity layers were produced by Geoscience Australia. Other environmental and biological datasets are the outputs of oceanographic models and collections of various governmental and research organisations. These datasets are important for the success of marine biodiversity research in Theme 3 Project 1 in that they describe key aspects of Australian marine physical, geochemical and biological environments. The physical and geochemical datasets not only characterise the static seabed features but also capture the temporal variation and three-dimensional interactions within marine ecosystems. The biological datasets represent a unique collection of fish and megafauna data available at the national scale. Together, these marine environmental datasets enhance our understanding of large-scale ecological processes driving marine biodiversity patterns. However, it should be noted that uncertainties and potential errors exist in these datasets due to limitations of data collection and processing methods. Data quality issues for individual datasets have been documented in this report where possible.

Benthic Biota of Northern Australia: SS2012t07 Post-survey Report - Rachel Przeslawski; de Glasby, Belinda Alvarez; Smit, Neil; Evans-Illidge, Libby; Dethmers, Kiki (GA Record, 2013)
We undertook a biological data acquisition program as part of the transit of the R.V. Southern Surveyor between Darwin and Cairns 15-24 October 2012. The overarching aim of this program was to use an ROV and benthic sled to collect benthic marine information and specimens for biodiversity and biodiscovery research in areas previously mapped by Geoscience Australia during survey GA-276, including a bank (Area I) and terrace/hole feature within the proposed Wessel Islands CMR (Area II). This study focuses on sessile invertebrates such as sponges and octocorals due to their ecological importance as habitat providers and their chemical importance as sources of marine natural products and medicines. In less than 24 hours of sampling effort, survey SS2012/t07 resulted in 261 voucher specimens which will be used for biodiversity and natural products research. A total of 49 samples are to be lodged at the ABL, and samples with weights larger than 300 g will be sent to the NCI for screening of active compounds against cancer and HIV. Sponges were the most abundant group collected based on both biomass (~ 139 kg) and number of voucher specimens (93), followed by cnidarians (30 kg, 73 vouchers), particularly hard corals (23 kg, 11 vouchers). As expected the top of the bank in Area I had a seemingly diverse and abundant sessile invertebrate community, with consistent patchy occurrence of sponges, octocorals, and hard corals. The terrace at in Area II supports moderate densities of sponges and octocorals, while the adjacent deep hole at ~ 100 m seems to be covered with muddy gravel and supports scattered mobile and sedentary invertebrates, of which crinoids dominate, as well as skates and numerous small demersal fish.

Better integration of sectoral planning and management approaches for the interlinked ecology of the open oceans - Natalie C. Ban; Maxwell, Sara M.; Daniel C. Dunn; Alistair J Hobday; Nicholas J. Bax; Jeff A Ardron; Kristina M. Gjerde; Edward T Game; Devillers, Rodolphe; Kaplan, David M.; Piers K Dunstan; Halpin, Patrick N.; et al. (Marine Policy, 2013)
Open oceans are one of the least protected, least studied and most inadequately managed ecosystems on Earth. Three themes were investigated that differentiate the open ocean (areas beyond national jurisdiction and deep area within exclusive economic zones) from other realms and must be considered when developing planning and management options: ecosystem interactions, especially between benthic and pelagic systems; potential effects of human activities in open oceans on ecological linkages; and policy context and options. A number of key ecological factors differentiate open oceans from coastal systems for planners and managers: (1) many species are widely distributed and, especially for those at higher trophic levels, wide ranging; (2) the sizes and boundaries of biogeographical domains (patterns of co-occurrence of species, habitats and ecosystem processes) vary significantly by depth; (3) habitat types exhibit a wide range of stabilities, from ephemeral (e.g., surface frontal systems) to hyper-stable (e.g., deep sea); and (4) vertical and horizontal linkages are prevalent. Together, these ecological attributes point to interconnectedness between open ocean habitats across large spatial scales. Indeed, human activities – especially fishing, shipping, and potentially deep-sea mining and oil and gas extraction – have effects far beyond the parts of the ocean in which they operate. While managing open oceans in an integrated fashion will be challenging, the ecological characteristics of the system demand it. A promising avenue forward is to integrate aspects of marine spatial planning (MSP), systematic conservation planning (SCP), and adaptive management. These three approaches to planning and management need to be integrated to meet the unique needs of open ocean systems, with MSP providing the means to meet a diversity of stakeholder needs, SCP providing the structured process to determine and prioritise those needs and appropriate responses, and adaptive management providing rigorous monitoring and evaluation to determine whether actions or their modifications meet both ecological and defined stakeholder needs. The flexibility of MSP will be enhanced by the systematic approach of SCP, while the rigorous monitoring of adaptive management will enable continued improvement as new information becomes available and further experience is gained.
Keywords: Areas beyond national jurisdiction; Benthic-pelagic interlinkages; High seas; Marine conservation; Marine protected areas; Sustainable fisheries

A blueprint for monitoring management outcomes and environmental health of Australian Commonwealth waters: fact sheet - Paul Hedge (2013)
The Australian Government has been working with CSIRO and the NERP Marine Biodiversity Hub to develop a sustained, cost-effective, environmental monitoring system to assess the Commonwealth Marine Reserve (CMR) network and the environmental health of Commonwealth waters.The system aims to document the management outcomes of the CMR network, and report on a select suite of ecosystem health indicators for Key Ecological Features (KEFs), identified by the Australian Government for their high biodiversity and productivity value. Report "Towards a blueprint for monitoring Key Ecological Features in the Commonwealth Marine Area" - November 2015

CATAMI Classification Scheme for scoring marine biota and substrata in underwater imagery - A pictorial guide to the Collaborative and Annotation Tools for Analysis of Marine Imagery and Video (CATAMI) classification scheme - Althaus, Franziska; Nicole A. Hill; Edwards, L; Renata Ferrari (2013)
This is a picture-based guide designed to promote national consistency and standards for classifying marine biota and substrata captured in underwater imagery. National consistency is an important requirement for effective monitoring of benthic ecosystems in Commonwealth Marine Reserves and key ecological features (implementing Marine Bioregional Plans). This document provides definitions and examples for the categories described in Version 1.2 of the CATAMI Classification Scheme for marine biota and substrata in underwater imagery (CATAMI Technical Working Group, 2013). It is envisaged that imagery from a range of sources, including video and digital stills and hence spanning a range in resolution and quality, will be scored using this system. The classification scheme was designed to allow images from shallow waters to abyssal depths and from the tropics to Antarctic/ Arctic waters to be classified using the same labels, i.e. a set of consistent identifiers. For ease of tracking and data-basing, each standardised label was also assigned a CAAB ‘code’. CAAB stands for Codes for Australian Aquatic Biota and is a numerical code that is listed, described and maintained through a CSIRO website at (http://www.cmar.csiro.au/caab/). Originally CAAB were only used for taxonomic classification of biota, but the system was adapted to encompass both the physical and the biota classes of the CATAMI classification. The publication is by CATAMI but has been facilitated through funds from CATAMI (ANDS & NECTAR), NERP and researchers  ‘in kind’ by their institutions. Related information: CATAMI Classification - http://catami.github.io/ - download the visual guide, code file and technical documents AARNET case study - Collaboration spawns new eResearch tools for monitoring marine life, March 2015 Poster - Putting names to a sea of faces

Chirostylidae of Australia’s western continental margin (Crustacea : Decapoda : Anomura), with the description of five new species - Anna W McCallum; Gary C. B. Poore (Zootaxa, 2013)
Five new species from the squat lobster family Chirostylidae are described from the continental margin of western Aus-tralia: Uroptychus albus sp. nov., Uroptychus bardi sp. nov., Uroptychus jawi sp. nov., Uroptychus taylorae sp. nov., and Uroptychus worrorra sp. nov. New records of Indo-West Pacific species for Australia are: Gastroptychus brachyterus Ba-ba, 2005, Gastroptychus investigatoris Alcock, 1899, Uroptychodes grandirostris (Yokoya, 1933), Uroptychodes mortenseni (Van Dam, 1939), Uroptychus scandens Benedict, 1902, Uroptychus ciliatus (Van Dam, 1933) and Uroptychus vandamae Baba, 1988. New distributional records are given for species previously recorded from Australia: Uroptychus flindersi Ahyong & Poore, 2004, Uroptychus hesperius Ahyong & Poore, 2004, Uroptychus joloensis Van Dam, 1939, Uroptychus nigricapillis Alcock, 1901, and Uroptychus spinirostris (Ahyong & Poore, 2004). These new records expand the number of chirostylid species in Australia from 34 to 46. Keys to Australian species of the genera Gastroptychus, Uroptychodes and Uroptychus are provided.
Keywords: Anomura; Crustacea; Decapoda; Gastroptychus; keys; new species; Squat lobster; Uroptychodes; Uroptychus; Western Australia

Classifying Australia’s submarine canyons - Fact sheet - Annabel Ozimec (2013)
Submarine canyons have been identified in marine bioregional plans as areas of high productivity and marine life aggregation, ranging from deep water corals to iconic species such as blue whales. Surprisingly we do not know the number of canyons around Australia, how they vary, nor how this changes their biodiversity value.

Complete mitochondrial genome of the Critically Endangered speartooth shark Glyphis glyphis (Carcharhiniformes: Carcharhinidae) - Xiao Chen; Liu, Min; Grewe, Peter M.; PM Kyne; Pierre Feutry (Mitochondrial DNA, 2013)
In this study we present the first complete mitogenome for the speartooth shark Glyphis glyphis, a rare euryhaline elasmobranch from northern Australia and Papua New Guinea. The mitogenome is 16,702 bp in length and the overall base composition is 31.5% A; 26.0% C; 13.0% G and 29.5% T. It includes 2 ribosomal RNA (rRNA) genes, 22 transfer RNA (tRNA) genes, 13 protein-coding genes and a putative 1066 bp long control region. The COI gene is initiated by GTG codon whereas the remaining protein-coding genes started with the ATG codon. This study will help elucidate the taxonomy of this poorly known group of sharks.
Keywords: Glyphis glyphis; mitogenome; river sharks; threatened species

Congruence in demersal fish, macro invertebrate and macroalgal community turnover on shallow temperate reefs - Russell J. Thomson; Nicole A. Hill; Rebecca Leaper; Nick Ellis; C Roland Pitcher; Neville Barrett; Graham J. Edgar (Ecological Applications, 2013)
To support coastal planning through improved understanding of patterns of biotic and abiotic surrogacy at broad scales, we used Gradient Forest Modelling (GFM) to analyse and predict spatial patterns of compositional turnover of demersal fishes, macro invertebrates and macroalgae on shallow temperate Australian reefs. Predictive models were first developed using environmental surrogates with estimates of prediction uncertainty, and then the efficacy of the three assemblages as bio-surrogates for each other was assessed. Data from underwater visual surveys of subtidal rocky reefs were collected from the south-eastern coastline of continental Australia (including South Australia and Victoria) and northern coastline of Tasmania. These data were combined with 0.01°-resolution gridded environmental variables to develop statistical models of compositional turnover (beta diversity) using GFM. GFM extends the machine learning, ensemble tree-based method of Random Forests (RF), to allow the simultaneous modelling of multiple taxa. The models were used to generate predictions of compositional turnover for each of the three assemblages within unsurveyed areas across the 6600 km of coastline in the region of interest. The most important predictor for all three assemblages was variability (measured as standard deviation from measures taken interannually) in sea surface temperature. Spatial predictions of compositional turnover within unsurveyed areas across the region of interest were remarkably congruent across the three taxa. However, the greatest uncertainty in these predictions varied in location between the different assemblages. Pairwise congruency comparisons of observed and predicted turnover between the three assemblages showed that invertebrate and macroalgal biodiversity were most similar, followed by fishes and macroalgae, and lastly fishes and invertebrate biodiversity, suggesting that of the three assemblages, macroalgae would make the best bio-surrogate for both invertebrate and fish compositional turnover.

Conservation management and sustainable harvest quotas are sensitive to choice of climate modelling approach for two marine gastropods - D. A. Fordham; Brook, B. W.; M Julian Caley; C. J. A. Bradshaw; Camille Mellin (Diversity and Distributions, 2013)
Abstract Aim To establish the robustness of two alternative methods for predicting the future ranges and abundances for two wild-harvested abalone species (Haliotis rubra Donovan 1808 and H. laevigata Leach 1814): single atmosphere–ocean general circulation model (GCM) or ensemble-averaged GCM forecasts. Location South Australia. Methods We assessed the ability of 20 GCMs to simulate observed seasonal sea surface temperature (SST) between 1980–1999, globally, and regionally for the Indian and Pacific Oceans south of the Equator. We used model rankings to characterize a set of representative climate futures, using three different-sized GCM ensembles and two individual GCMs (the Parallel Climate Model and the Community Climate System Model, version 3.0). Ecological niche models were then coupled to physiological information to compare forecast changes in area of occupancy, population size and harvest area based on forecasts using the various GCM selection methods, as well as different greenhouse gas emission scenarios and climate sensitivities. Results We show that: (1) the skill with which climate models reproduce recent SST records varies considerably amongst GCMs, with multimodel ensemble averages showing closer agreement to observations than single models; (2) choice of GCM, and the decision on whether or not to use ensemble-averaged climate forecasts, can strongly influence spatiotemporal predictions of range, abundance and fishing potential; and (3) comparable hindcasting skill does not necessarily guarantee that GCM forecasts and ecological and evolutionary responses to these forecast changes, will be similar amongst closely ranked models. Conclusion By averaging across an ensemble of seven highly ranked skilful GCMs, inherent uncertainties stemming from GCM differences are incorporated into forecasts of change in species range, abundance and sustainable fishing area. Our results highlight the need to make informed and explicit decisions on GCM choice, model sensitivity and emission scenarios when exploring conservation options for marine species and the sustainability of future harvests using ecological niche models.
Keywords: balone range movement; atmosphere–ocean general circulation model; ecological niche model; ensemble-averaged climate change predictions; extinction risk; marine species distribution models

The Coral Sea: Physical Environment, Ecosystem Status and Biodiversity Assets - Daniela Ceccarelli; McKinnon, A. David; Serge Andréfouët; Allain, Valerie; Jock W. Young; Daniel C Gledhill; Flynn, Adrian; Nicholas J. Bax; R J Beaman; Borsa, Philippe; Brinkman, Richard; Rodrigo H. Bustamante; et al. (Advances in Marine Biology, 2013)
The Coral Sea, located at the southwestern rim of the Pacific Ocean, is the only tropical marginal sea where human impacts remain relatively minor. Patterns and processes identified within the region have global relevance as a baseline for understanding impacts in more disturbed tropical locations. Despite 70 years of documented research, the Coral Sea has been relatively neglected, with a slower rate of increase in publications over the past 20 years than total marine research globally. We review current knowledge of the Coral Sea to provide an overview of regional geology, oceanography, ecology and fisheries. Interactions between physical features and biological assemblages influence ecological processes and the direction and strength of connectivity among Coral Sea ecosystems. To inform management effectively, we will need to fill some major knowledge gaps, including geographic gaps in sampling and a lack of integration of research themes, which hinder the understanding of most ecosystem processes.
Keywords: Collaborative research; connectivity; Ecosystem function; Food web; Pristine ecosystems; Tropical sea

Describing the evolutionary history of Australia’s marine fauna - Fact sheet - Annabel Ozimec (2013)
An understanding of the ecological processes and historical biogeography of Australia’s marine fauna is a key factor in Australia’s marine bioregionalisation. It has been widely thought that many Australian marine species originated in the tropics and expanded southwards. Work by the CERF Marine Biodiversity Hub, however, suggested some Australian fish groups actually were ancestral to their tropical relatives.

Do marine substrates ‘look’ and ‘sound’ the same? Supervised classification of multibeam acoustic data using autonomous underwater vehicle images - Vanessa L Lucieer; Nicole A. Hill; Neville Barrett; Scott L Nichol (Estuarine, Coastal and Shelf Science, 2013)
In this study we outline the techniques used to transform multibeam acoustic data into spatial layers that can be used for predictive habitat modelling. The results allow us to identify multibeam attributes which may act as potential surrogates for environmental variables that influence biodiversity and define which variables may be reliable for predicting the distribution of species in temperate waters. We explore a method for analysing the spatially coincident multibeam bathymetric and backscatter data from shallow coastal waters to generate spatial data products that relate to the classes derived from fine-scale visual imagery obtained using an autonomous underwater vehicle (AUV). Classifications of the multibeam data are performed for substrate, rugosity and sponge cover. Overall classification accuracies for the classes associated with substratum, rugosity and sponge structure were acceptable for biodiversity assessment applications. Accuracies were highest for rugosity classes at 65%, followed by substratum classes at 64% and then sponge structure classes at 57%. Random forest classifiers at a segmentation scale of 30 performed best in classifying substratum and rugosity, while K-nearest neighbour classifiers performed best for sponge structure classes, with no difference in accuracy between scale 30 and 60. Incorporating backscatter variables using segmentation improved the overall accuracy achieved by the best performing model by between 1% (rugosity) and 9% (substratum) above using topographic variables only in the grid-based analyses. Results suggest that image-based backscatter classification show considerable promise for the interpretation of multibeam sonar data for the production of substrate maps. A particular outcome of this research is to provide appropriate and sufficiently fine-scale physical covariates from the multibeam acoustic data to adequately inform models predicting the distribution of biodiversity on benthic reef habitats.
Keywords: autonomous underwater vehicles; image classification; multibeam acoustic data; substrate prediction

Dwarf sawfish Pristis clavata species information - Fact Sheet - PM Kyne (2013)
Conservation Status of Dwarf sawfish Pristis clavata: IUCN Red List of Threatened Species: Critically Endangered Commonwealth: Vulnerable Northern Territory: Vulnerable Description The Dwarf Sawfish is a relatively small sawfish with 18-22 evenly spaced teeth on each side of the rostrum, with the teeth starting near the rostral base, a dorsal-fin origin over or slightly behind the pelvic-fin origin, and a feeble lower lobe to the caudal fin. Size Born at 60-81 cm in length and attains at least 318 cm. Notes The exact range of the Dwarf Sawfish is uncertain. There are a handful of historical records from outside of Australia, but it is possibly now found only in northern Australian waters. Despite claims from the east coast of Australia, it has not been confirmed there and so may be restricted to the Gulf of Carpentaria, west across to the Top End to the Kimberley. It occurs in coastal and estuarine environments, and penetrates upstream into rivers, but not into freshwater. Related information: Catch up on news, watch videos and download resources from the sawfish and river shark research undertaken during the National Environmental Research Program (NERP) 2011 - 2014
Keywords: Dwarf sawfish; Pristis clavata

Environmental predictors of decapod species richness and turnover along an extensive Australian continental margin (13–35° S) - Anna W McCallum; Gary C. B. Poore; Williams, Alan; Althaus, Franziska; Tim O'Hara (Marine Ecology, 2013)
The use of environmental data in biogeographic studies of the deep sea is providing greater insight into the processes underlying large-scale patterns of diversity. Recent surveys of Australia’s western continental margin (~100– 1100 m) provide systematic sampling of invertebrate megafauna along a gradient of 22° of latitude (13–35° S). Diversity patterns of decapod crustaceans were examined and we investigated the relative importance of environmental and spatial predictor variables on both species richness (alpha diversity) and species turnover. Distance-based linear models (DistLM) indicated a suite of variables were important in predicting species turnover, of which temperature and oxygen were the most influential. These reflected the oceanographic features that dominate distinct depth bathomes along the slope. The numbers of species within samples were highly variable; a small but significant increase in diversity towards the tropics was evident. Replicated sampling along the margin at ~100 m and ~400 m provided an opportunity to compare latitudinal patterns of diversity at different depths. On the shallow upper slope (~400 m) temperature was disassociated from latitude and the latter proved to be the best predictor of sample species richness. The predictive power of latitude over other variables indicates that proximity to the highly diverse Indo-West Pacific (IWP) may be important, especially considering that almost 40% of species in this study had a wide IWP distribution. In the management of Australia’s marine environments, geomorphic surrogates have been emphasised when defining areas for protection. We found sea-floor characteristics were relatively less important in predicting richness or community composition.
Keywords: Biodiversity; Biogeography; environmental gradients; latitudinal gradients; species turnover; Western Australia

Evaluation of information used in CITES Appendix II proposals, for three sharks and two rays: Porbeagle (Lamna nasus), Oceanic Whitetip Shark (Carcharhinus longimanus), Scalloped Hammerhead (Sphyrna lewini) and manta rays (Manta and Mobula species) - Ross K Daley; Webb, H (2013)
Report to the Department of Sustainability Environment, Water Populations and Communities

Exploring Australia’s Fish diversity - Andreakis, Nikos (2013)
Genomes contain a record of the history of the species shaped by natural selection & random genetic drift. DNA regions in an organism can be examined as well as its morphology to reveal large scale geological episodes such as continental drift (slow, millions of years) & human-mediated changes such as heavy industry, rural development, landscape transformation & recent global warming (rapid, tens of years), all accounting for species diversification. Species genetic variability is always open to change. Gene variants, once lost, cannot be recovered. Congruence in biogeographic patterns among endemic species & consistent rates of diversification suggest similarities in the geological, historical & evolutionary processes responsible for synchronic speciation within even unrelated groups of taxa. Multi-gene molecular phylogenies, fossil-calibrated molecular clocks & diversification analyses are useful tools to explore the impact of geological changes and climatic shifts in the speciation processes & the current distribution patterns of Australia’s marine endemisms

Exploring the role spatial scale plays in marine habitat mapping using multiscale geomorphometric analyses - Lecours, V; Devillers, R; Edinger, E; Brown, C J; Vanessa L Lucieer (GEOHAB (Marine Geological and Biological Habitat Mapping), 2013)
The study of terrestrial ecosystems at various spatial and temporal scales has proven beneficial for understanding a number of important ecological processes, but has not received the same level of attention in marine ecology, largely due to a more difficult access to data at multiple scales. Broadscale data can miss patterns linked to local-scale processes. While Remotely Operated Vehicles (ROV) allow the collection of high resolution data in the deep sea, such detailed data sets are not necessarily the most appropriate for understanding distributions. In most studies, the scale of analysis is often arbitrarily based on the available data, which can be misleading if the scale of analysis does not match the scale of ecological process under investigation. Spatial scale is therefore probably one of the most misunderstood concepts in marine habitat mapping. The research presented here aims to further explore the role that spatial scale plays in understanding and mapping deep-sea benthic habitats. Environmental and topographic variables are known to be important to understand the spatial distribution and spatial ecology of benthic organisms and habitat structures at several scales. We apply an approach which studies these variables and patterns across a continuum of spatial scales, using different resolution bathymetric datasets, in order to create a continuous range of scales. We present preliminary results obtained from the application of this multiscale approach to coldwater coral habitats in Canada. High-resolution multibeam sonar, video and oceanographic data were collected in 2010 and 2011 in the Northwest Atlantic (Flemish Cap and Orphan Knoll, near Newfoundland) and on the Pacific continental shelf (Strait of Georgia, British Columbia), using the Canadian ROV ROPOS. Multibeam bathymetric data were collected using the ROV either close to the seafloor (1-2m height), and/or at an altitude of 20m off-bottom. Vessel-mounted multibeam bathymetric data are also available from both study areas. These data allowed bathymetric models (grids) of the seafloor to be generated at the following spatial resolutions: ROV-derived bathymetry, ranging from 0.1 to 1m resolution; vessel-mounted multibeam bathymetry ranging from 2 to 50m resolution; General Bathymetric Chart of the Oceans (GEBCO) derived grids at 30-seconds resolution (around 865m at this latitude). Observations of corals were obtained from the ROV video data at the local scale, and from scientific trawl surveys at the regional scale. Using these data, the importance of seafloor morphology in structuring coral habitats was studied across the range of spatial scales in order to characterize their respective niche and to define their most appropriate scale for which to investigate their predicted distribution. Geomorphometric attributes (e.g. slope, aspect, curvatures) were measured for each bathymetric datasets, with a particular emphasis given to attributes expressing the complexity of the seafloor, such as Bathymetric Position Index (BPI) and Vector Ruggedness Measure (VRM). Linear correlations were calculated between geomorphometric attributes and area-normalized presence of six functional groups of corals: soft corals, small gorgonians, large gorgonians, sea pens, stony cup corals, and black corals. Using the GEBCO bathymetry and the observations from scientific trawl surveys, depth showed a positive relationship with all the functional groups except soft corals. Slope was positively correlated with cup corals, soft corals, and small gorgonians. Standardized fine-scale and broad-scale BPI were negatively correlated with black corals and sea pens, but positively correlated with soft corals. Finescale BPI presented a negative correlation with stony cup corals and small gorgonians, but not broadscale BPI. VRM was positively correlated with all coral groups except soft corals: the three scales of measured VRM had a relationship with small gorgonians, the broadest scale with stony cup corals, and the two finest with sea pens. More analyses are required to explore more geomorphometric attributes and the multicolinearity effect between them, and to understand the complex interactions between the different morphological characteristics of the seafloor and cold-water coral habitats at different scales.

Fathom out: biogeographical subdivision across the Western Australian continental margin – a multispecies modelling approach - Skipton N. C. Woolley; Anna W McCallum; Wilson, Robin; Tim O'Hara; Piers K Dunstan (Diversity and Distributions, 2013)
Aim Biogeographical regions are often used as a basis for management strate- gies, yet a challenge for biodiversity management across broad scales is estab- lishing biogeographical regions that are robust across taxonomic groups. Methods Finite mixture models were developed to predict multiple species assemblages termed archetypes. Modelled species archetypes were developed using Decapoda, Ophiuroidea and Polychaeta species, which were grouped based on their similar responses to oceanographic and geographical gradients. Location Outer-shelf and slope (50–1200 m) of the continental margin of Western Australia (~11°S–36°S). Results Four faunal regions were defined based on cross-taxa surrogates grouped as archetypes. These faunal regions were defined by oxygen, salinity, carbon and temperature gradients across latitude and bathymetry. Two broad latitudinal bands and two bathyal regions were described. Adjacent faunal groups were not defined by abrupt geographical breaks but rather transitions. Main conclusions These results suggest that faunal distributions were less finely resolved than existing marine bioregions on the Western Australian con- tinental margin and that environmental gradients are correlated with distribu- tions of benthic marine invertebrates. Identifying biogeographical regions based on these methods has the potential to inform management across a broad range of environments.
Keywords: benthic invertebrates; Biogeography; bioregions; continental margin; finite mixture models; Marine biodiversity

Finite mixture of regression modeling for high-dimensional count and biomass data in ecology - Piers K Dunstan; Scott D Foster; Francis K.C. Hui; David I. Warton (Journal of Agricultural, Biological, and Environmental Statistics, 2013)
Understanding how species distributions respond as a function of environmental gradients is a key question in ecology, and will benefit from a multi-species approach. Multi-species data are often high dimensional, in that the number of species sampled is often large relative to the number of sites, and are commonly quantified as either presence–absence, counts of individuals, or biomass of each species. In this paper, we propose a novel approach to the analysis of multi-species data when the goal is to understand how each species responds to their environment. We use a finite mixture of regression models, grouping species into “Archetypes” according to their environmental response, thereby significantly reducing the dimension of the regression model. Previous research introduced such Species Archetype Models (SAMs), but only for binary assemblage data. Here, we extend this basic framework with three key innovations: (1) the method is expanded to handle count and biomass data, (2) we propose grouping on the slope coefficients only, whilst the intercept terms and nuisance parameters remain species-specific, and (3) we develop model diagnostic tools for SAMs. By grouping on environmental responses only, the model allows for interspecies variation in terms of overall prevalence and abundance. The application of our expanded SAM framework data is illustrated on marine survey data and through simulation.
Keywords: Community-level model; Mixture model; Multi-species; Species archetype model; Species distribution model; weedie.

First reports of proliferative lesions in the great white shark, Carcharodon carcharias L., and bronze whaler shark, Carcharhinus brachyurus Günther - Robbins, Rachel; Barry Bruce; Fox, Andrew (Journal of Fish Diseases, 2013)
The low incidence of reported tumours in elasmo-branchs has led to the assumption that the group rarely develops cancerous diseases (Loprinzi et al. 2005). This, combined with some studies reporting a therapeutic benefit in cartilage extract (e.g. Cho & Kim 2002), has resulted in a worldwide demand for shark cartilage products for use as alternative therapies (Berzins & Hovland 1999). This demand has, at least in part, increased the pressure on shark populations contributing to their worldwide decline (Ostrander et al. 2004). While reported cases are relatively low, both benign and cancerous prolifera- tive lesions have been reported in 21 species of sharks from over 9 families (Ostrander et al. 2004; National Cancer Institute 2007).
Keywords: cancer; elasmobranch; neoplasm; tumour

How robust are your prediction derivatives? Error propagation modelling for seafloor terrain analysis of multibeam bathymetric data using dynamic simulation tools - Vanessa L Lucieer; Z Huang; Justy P W Siwabessy; K Hayes (GEOHAB (Marine Geological and Biological Habitat Mapping), 2013)
There are many potential applications of seabed habitat mapping for which estimates of uncertainty in seafloor terrain derivatives will provide additional crucial information. This information is useful to assess the robustness of multibeam bathymetric data for seabed monitoring, change detection and habitat prediction analysis. As multibeam data collections build up over time a method to assess the compatibility to spatially merge these data are essential. These datasets then become the input data for spatial analysis procedures to characterise the seabed. The accuracy of seabed terrain first and second order derivatives and their associated levels of uncertainty are extremely hard to convey visually or to quantify with existing methodologies. In this study Monte-Carlo simulation techniques were used to represent DEM (digital elevation model) uncertainty and its effect on three topographic parameters (slope, curvature and aspect). Different methods for representing error and quantifying uncertainty are investigated. In these results the analysis the multibeam bathymetric error are assumed to be spatially auto correlated across a neighbourhood zone, methods for the assessment of autocorrelation will be discussed. Each terrain derivative layer was perturbed using its error model with increasing levels of error, and the effect on the seabed map was assessed. Quantifying uncertainty in the input data for habitat suitability modelling is imperative to establishing methods for prediction, and monitoring, as we need to be able to separate potential mapping error from change and variation in the system that we are monitoring. By combining bathymetric processing and uncertainty modelling techniques we can make an important step towards identifying tools for seabed monitoring and risk assessment for policy-making. These tools will improve our ability to assess and communicate the accuracy of the seabed maps through spatially mapping the degrees of uncertainty in our predictions and therefore make more informed choices of the data we use to inform ocean management policies and subsequent seafloor analysis.

Infaunal biodiversity and ecological function on a remote oceanic island: The role of biogeography and bio-physical surrogates - Tara J Anderson; Matthew McArthur; Syms, Craig; Scott L Nichol; Brendan P Brooke (Estuarine, Coastal and Shelf Science, 2013)
Understanding and predicting the processes determining biological assemblages and marine biodiversity is critical to managing and conserving marine ecosystems. Infauna are a substantial component of shelf biodiversity and important contributors to ecological function. To examine the bio-physical relationships structuring infaunal assemblages across the Lord Howe Island (LHI) shelf, we mapped broad-scale physical and habitat-related features of the seabed using high-resolution multibeam sonar and sampled sediments and infauna across the shelf using a Smith-McIntyre grab. Broad-scale biogeographic processes were important determiners of the infaunal shelf assemblage. Shelf sediments supported an impoverished infaunal assemblage, with a high proportion of rare species, and many new and endemic species. This, combined with the numerical dominance of brooding endemics relative to lower densities of mainland taxa suggests that much of the islands infaunal diversity reflects transient dispersers rather than self-recruiting island populations. Local-scale physical processes, such as disturbance and currentborne nutrients, were also important in structuring the infaunal assemblage. Three geomorphic zones (drowned lagoon, relict reef and outer shelf) were strong predictors (or surrogates) of infaunal community and trophic structure over broad-scales (the extent of the shelf), while sediment composition (e.g. sorting and mean grain size) and seafloor structure (e.g. topography) were important predictors of population abundances and finer-scale (within-zone) community patchiness. Species richness and abundance were highest offshore on the outer shelf. Here, topographically raised sites subjected to oceanic currents supported high densities of suspension feeders and the highest levels of infaunal diversity. In contrast, the dynamic rippled sediments of the drowned lagoon supported an impoverished assemblage with a reduced trophic structure indicative of harsh physical environments. While biogeographic isolation in part explains low localised densities of non-endemic species, overall numbers per species indicate that many individuals are successfully arriving at LHI, but that sediment conditions e particularly in the drowned lagoon and to a lesser extent across the relict reef e may be too dynamic to provide suitable habitat for many of these species. These results suggest that interactions between shelf topography, physical wave disturbance and nutrient supply from oceanic currents are important factors structuring oceanic shelf assemblages. This study highlights that seabed habitat mapping when explicitly integrated with fine-scale bio-physical surveys can provide substantial insight into the spatial distribution and ecological function of benthic assemblages, and provides an essential ecological and spatial framework to predict the future structure of these populations and assemblages in response to natural and anthropogenic change.
Keywords: feeding guilds; Habitat mapping; landscape configuration; Lord Howe Island; macrofauna; oceanic convergence; soft sediments; surrogates

Infaunal biodiversity patterns from Carnarvon Shelf (Ningaloo Reef), Western Australia - Rachel Przeslawski; Matthew McArthur; Tara J Anderson (Marine and Freshwater Research, 2013)
Infauna are important in many ecological processes but have been rarely considered in biodiversity assessments of coral reefs and surrounding areas. We surveyed infaunal assemblages and associated environmental factors (depth, seabed reflectance, sediment characteristics) in three areas (Mandu, Point Cloates, Gnaraloo) along the Carnarvon Shelf, Western Australia. This region supports Ningaloo Reef, a relatively pristine coral reef protected by the Ningaloo Marine Park and a Commonwealth marine reserve. Macrofauna were sampled with a Smith-McIntyre grab and sieved through 500 µm. A total of 423 species and 4036 individuals was recorded from 145 grabs, with infauna accounting for 67% of species and 78% of individuals. Rare species (≤2 individuals per species) represented 42% of the total assemblage. Assemblages were significantly different among all three areas, with the most distinct recorded from the southern-most area (Gnaraloo). Although assemblages varied significantly with depth and sediment composition (mud and gravel), these relationships were weak. Results from the current study broadly quantify macrofaunal diversity in the region and identify potential spatial and environmental patterns which will help inform future marine management plans, including the provision of baseline information to assess the efficacy of protected areas in soft-sediment habitats adjacent to coral reefs.
Keywords: Conservation; marine protected area; north-western Australia; sediment characteristics; trophic guild

Inferred global connectivity of whale shark Rhincodon typus populations - AMM Sequeira; Camille Mellin; Mark Meekan; Sims, D. W.; C. J. A. Bradshaw (Journal of Fish Biology, 2013)
Ten years have passed since the last synopsis of whale shark Rhincodon typus biogeography. While a recent review of the species’ biology and ecology summarized the vast data collected since then, it is clear that information on population geographic connectivity, migration and demography of R. typus is still limited and scattered. Understanding R. typus migratory behaviour is central to its conservation management considering the genetic evidence suggesting local aggregations are connected at the generational scale over entire ocean basins. By collating available data on sightings, tracked movements and distribution information, this review provides evidence for the hypothesis of broad-scale connectivity among populations, and generates a model describing how the world’s R. typus are part of a single, global meta-population. Rhincodon typus occurrence timings and distribution patterns make possible a connection between several aggregation sites in the Indian Ocean. The present conceptual model and validating data lend support to the hypothesis that R. typus are able to move among the three largest ocean basins with a minimum total travelling time of around 2 – 4 years. The model provides a worldwide perspective of possible R. typus migration routes, and suggests a modified focus for additional research to test its predictions. The framework can be used to trim the hypotheses for R. typus movements and aggregation timings, thereby isolating possible mating and breeding areas that are currently unknown. This will assist endeavours to predict the longer-term response of the species to ocean warming and changing patterns of human-induced mortality.
Keywords: meta-population; migration; movement; sea surface temperature

Integrated monitoring framework for the Great Barrier Reef World Heritage Area - Paul Hedge; Fergus Molloy; H Sweatman; Jeffrey M Dambacher; Chandler, J; Gooch, M; A Chin; Nicholas J. Bax; Terry Walshe (Australian Government Department of the Environment, 2013)
This project was commissioned to establish a framework for a standardised and integrated ecological, social and economic monitoring program. In undertaking this project, the team developed and tested practical guidance that would help partners involved in a strategic assessment under the Environment Protection and Biodiversity Conservation Act 1999 (EPBC Act) to establish a framework for integrated monitoring. The Integrated Monitoring Framework (IMF) guidance identifies the steps and provides clear direction to develop efficient and effective monitoring and reporting on the condition of nationally protected matters – Matters of National Environmental Significance (MNES) – and support adaptive management of these assets. The guidance was applied to the Great Barrier Reef World Heritage Area (GBRWHA) with the intention that the approach could be used to inform the potential development of other integrated monitoring programs in other coastal and marine regions of Australia. Download the report - An integrated monitoring framework for the Great Barrier Reef World Heritage Area, Department of the Environment, Canberra Related information View the related journal article "An integrated monitoring framework for the Great Barrier Reef World Heritage Area", Marine Policy, 2017

Integrating abundance and functional traits reveals new global hotspots of fish diversity - Rick D Stuart-Smith; Amanda E. Bates; Lefcheck, Jonathan S.; Duffy, J. Emmett; Baker, Susan C.; Russell J. Thomson; Jemina F. Stuart-Smith; Nicole A. Hill; Stuart J. Kininmonth; Airoldi, Laura; Becerro, Mikel A.; Campbell, Stuart J.; et al. (Nature, 2013)
Species richness has dominated our view of global biodiversity patterns for centuries1, 2. The dominance of this paradigm is reflected in the focus by ecologists and conservation managers on richness and associated occurrence-based measures for understanding drivers of broad-scale diversity patterns and as a biological basis for management3, 4. However, this is changing rapidly, as it is now recognized that not only the number of species but the species present, their phenotypes and the number of individuals of each species are critical in determining the nature and strength of the relationships between species diversity and a range of ecological functions (such as biomass production and nutrient cycling)5. Integrating these measures should provide a more relevant representation of global biodiversity patterns in terms of ecological functions than that provided by simple species counts. Here we provide comparisons of a traditional global biodiversity distribution measure based on richness with metrics that incorporate species abundances and functional traits. We use data from standardized quantitative surveys of 2,473 marine reef fish species at 1,844 sites, spanning 133 degrees of latitude from all ocean basins, to identify new diversity hotspots in some temperate regions and the tropical eastern Pacific Ocean. These relate to high diversity of functional traits amongst individuals in the community (calculated using Rao’s Q6), and differ from previously reported patterns in functional diversity and richness for terrestrial animals, which emphasize species-rich tropical regions only7, 8. There is a global trend for greater evenness in the number of individuals of each species, across the reef fish species observed at sites (‘community evenness’), at higher latitudes. This contributes to the distribution of functional diversity hotspots and contrasts with well-known latitudinal gradients in richness2, 4. Our findings suggest that the contribution of species diversity to a range of ecosystem functions varies over large scales, and imply that in tropical regions, which have higher numbers of species, each species contributes proportionally less to community-level ecological processes on average than species in temperate regions. Metrics of ecological function usefully complement metrics of species diversity in conservation management, including when identifying planning priorities and when tracking changes to biodiversity values.
Keywords: Biodiversity; Conservation; Food webs; Macroecology

Investigating Oceanic Shoals: a proposed marine reserve - Fact sheet - Annabel Ozimec (2013)
In September 2012, a three-week survey of the proposed Oceanic Shoals Commonwealth Marine Reserve off northern Australia was conducted from the Australian Institute of Marine Science (AIMS) research vessel RV Solander. Oceanographic, biological and acoustic sampling was conducted using techniques including towed and baited remote cameras, ocean drifters, benthic sleds, multibeam sonar, a box corer, and sediment and water collection. The result is an unprecedented, integrated description of biological communities and their relationship with the shallow seabed and open water environments of a poorly known region of Australian’s marine jurisdiction.

Largetooth Sawfish Pristis pristis species information - Fact Sheet - PM Kyne (2013)
Conservation Status of Largetooth Sawfish Pristis pristis IUCN Red List of Threatened Species: Critically Endangered Commonwealth: Vulnerable Northern Territory: Vulnerable Description The Largetooth Sawfish is a large sawfish with 17-23 evenly spaced teeth on each side of the rostrum, with the teeth starting near rostral base, a dorsal fin beginning well forward of the pelvic fins, and a small lower lobe to the caudal fin. Size Born at about 70-90 cm in length and reported to reach 700 cm, although sizes that big are rarely seen. Notes A unique sawfish in that it spends 4-5 years in rivers and billabongs as juveniles before moving out to sea. It is known from various rivers across northern Australia, as well as from estuaries and coastal environments. This species has suffered considerable declines across the rest of its Indo-West Pacific range, and northern Australia represents a remaining population stronghold. In the Indo-West Pacific region, this species was formally called the Freshwater Sawfish Pristis microdon; see news story here Related information Largetooth Sawfish Life History Overview News, videos and resources relating to sawfish and river shark research undertaken during the National Environmental Research Program (NERP) 2011-2014
Keywords: Largetooth sawfish; Pristis pristis

Linking Great Barrier Reef monitoring to management needs - Fact sheet - Annabel Ozimec (2013)
A monitoring framework is being developed to assist the Australian Government in its commitment to adapt and improve management of the Great Barrier Reef World Heritage Area (GBRWHA) to meet future challenges. The framework will standardise and integrate the collection of priority ecological, social and economic information, building on existing work relating to marine and coastal monitoring. The project involves the NERP Marine Biodiversity Hub, Tropical Ecosystems Hub and Environmental Decisions Hub, the Great Barrier Reef Marine Park Authority (GBRMPA), the Australian Institute of Marine Science and other stakeholders. The team is working with the GBRMPA’s Strategic Assessment Team to ensure the research supports the strategic assessment of the GBRWHA. A draft project report will be provided to SEWPaC in April 2013, with a final report due in June 2013.

Managing ecosystems to manage species - Fact sheet - Annabel Ozimec (2013)
Marine conservation and biodiversity management in Australia includes two frequently competing goals: protecting threatened and endangered species, and providing for the sustainable use of resources. Protecting species one by one has been identified by government as inefficient and ultimately impractical, so alternative approaches are being considered. One of these is a ‘landscape’ (seascape!) approach to management. Marine reserves are one example of this approach.

Marine Biodiversity Hub Annual Work Plan 2013 - Nicholas J. Bax (2013)
Keywords: annual research plan

Modelling biological regions from multi-species and environmental data - Scott D Foster; Givens, G.H.; Grant J Dornan; Piers K Dunstan; Ross Darnell (Environmetrics, 2013)
Partitioning the environment into areas that appear to contain similar biological content is useful for investigating questions of distribution and habitat and for helping guide resource conservation and utilization. The statistical task requires relating presence/absence data from multiple species to co-located environmental data. In this article, we introduce a statistical modelling framework that models the environment as a set of regions where the vector of probabilities of observing a set of species remains approximately constant within a region and distinct between regions. This is achieved within a mixture-of-experts model framework, which treats the region type as a latent variable whose distribution varies as a function of the environment. This approach allows us to predict probabilities of region types for sampled and unsampled locations. The model synthesizes biological and environmental data, incorporating both in a single likelihood that enables propagation of uncertainty through the entire model. The method is demonstrated using a synthetic example and data from a survey of fish from the North West Shelf, which is located off Western Australia. An R package, RCPmod, which implements the methods described in this article, is available from CRAN. Copyright © 2013 John Wiley & Sons, Ltd.
Keywords: assemblage; Mixture model; mixture of experts; region of common profile; species distribution

National maps of marine biodiversity and connectivity - Fact sheet - Annabel Ozimec (2013)
Australia has an ongoing need to understand spatial patterns of biodiversity across its vast marine domains. The knowledge is needed for managing marine reserves (particularly where field surveys have not been possible), and for heritage and environmental assessments.

NERP Marine Biodiversity Hub - Research Portfolio 2013 brochure - Nicholas J. Bax (2013)
This brochure includes an overview by Director Nic Bax and descriptions of current research projects. A web version of this brochure is also available.

New options for assessing rare and threatened marine species - Fact sheet - A Ozimec (2013)
Reliable, cost-effective assessment tools are vital for managing rare and threatened species. Northern Australia has some of the last remaining populations of sawfish, sharks and rays that live in both freshwater and seawater environments. The population status of these species and the effectiveness of conservation management – a key requirement of recovery plans – are unknown.  The NERP Marine Biodiversity Hub will provide the first estimate of population status for these species using electronic tagging (acoustic telemetry) and advanced genetic techniques (close-kin genetics) designed for this project.

The new wave of bathymetry data - uses and limitations for marine benthic habitat mapping and geomorphology - Dolan, M; Vanessa L Lucieer (Geohab Marine Geological and Biological Habitat Mapping Conference 2013., 2013)
This poster was presented at Geohab Marine Geological and Biological Habitat Mapping Conference 2013. 6th -10th May, Rome, Italy. Bathymetric data used for benthic habitat mapping and marine geomorphology can come from a variety of sources, offering information on seabed terrain at multiple data resolutions. Multibeam surveys have largely become the preferred means for acquiring bathymetry data, where funds permit. However, as mapping continues, people are increasingly making use of compiled datasets either by combining several neighbouring multibeam surveys or by including other sources of bathymetry data. The compilation process may be local, national or even regional (e.g. EMODNET Hydrography Portal) and global (e.g. GEBCO) and typically the broader the area the more diverse sources of bathymetry have gone into creating the compiled bathymetry product.

The new wave of bathymetry data- uses and limitations for marine benthic habitat mapping and geomorphology - Dolan, M; Vanessa L Lucieer (GEOHAB (Marine Geological and Biological Habitat Mapping), 2013)
Bathymetry data used for benthic habitat mapping and marine geomorphology come from a variety of sources, offering information on seabed terrain at a variety of data resolutions. Multibeam surveys have largely become the preferred means for acquiring bathymetry data, where funds permit. However, as mapping continues, people are increasingly making use of compiled datasets either by combining several neighbouring multibeam surveys or by including other sources of bathymetry data. The compilation process may be local, national or even regional (e.g. EMODNET Hydrography Portal) and global (e.g. GEBCO) and typically the broader the area the more diverse sources of bathymetry have gone into creating the compiled bathymetry product. These compiled datasets are a fantastic resource, providing ready-gridded bathymetry data, either at a single, or multiple resolutions. This meets a demand for bathymetry information which can be used for many applications, including benthic habitat mapping. However, compiled data resources, by their very nature, mean that the data user is increasingly distant from the original data source. Even if quality data are supplied with the data, the user no longer has the same contact with the data acquisition and processing pipeline as they did with discrete area surveys. This can make it all too easy to ignore issues of data quality and/or uncertainty which are inherent to the use of gridded bathymetry data. Focussing on application of such data to geomorphology and benthic habitat mapping we examine those issues that remain particularly important to consider when using bathymetry data from several sources, and compiled datasets. Using slope as an example we focus on the implications of data resolution, quality and data analysis scale in deriving terrain variables which are quantitative measures of geomorphic properties relevant to habitat mapping. We also present a practical method for computation of a confidence index for ready-gridded bathymetry data which is based on a Monte- Carlo simulation.

Northern River Shark Glyphis garricki species information - Fact Sheet - PM Kyne (2013)
Conservation Status of Northern River Shark Glyphis garricki: IUCN Red List of Threatened Species: Critically Endangered Commonwealth: Endangered Northern Territory: Endangered Description The Northern River Shark is a rather large whaler shark. It is characterised by its small eyes, a second dorsal fin which is three-quarters the height of the first dorsal fin, a short and broadly rounded snout, and upper teeth which are triangular and serrated, and which are broader than the lower teeth. The 'watermark' marking on the side of the head extends well below the eyes. Size Born at 50-60 cm in length and reaches about 250-300 cm. Notes The Northern River Shark is found only in a small number of rivers and estuaries across northern Australia and southern New Guinea. In Australia, it has a limited range in the Northern Territory and northwestern Western Australia. Related information: Catch up on news, watch videos and download resources from the sawfish and river shark research undertaken during the National Environmental Research Program (NERP) 2011 - 2014
Keywords: Glyphis garricki; Northern River Shark

An ocean observation system for monitoring the affects of climate change on the ecology and sustainability of pelagic fisheries in the Pacific Ocean - Nicol, Simon J.; Allain, Valerie; Pilling, Graham M.; Polovina, Jeff; Coll, Marta; Bell, Johann; Dalzell, Paul; Sharples, Peter; Olson, Robert; Griffiths, Shane; Jeffrey M Dambacher; Young, Jock; et al. (Climatic Change, 2013)
Climate change presents an emerging challenge to the sustainable management of tuna fisheries, and robust information is essential to ensure future sustainability. Climate and harvest affect tuna stocks, populations of non-target, dependent species and the ecosystem. To provide relevant advice we need an improved understanding of oceanic ecosystems and better data to parameterise the models that forecast the impacts of climate change. Currently ocean-wide data collection in the Pacific Ocean is primarily restricted to oceanographic data. However, the fisheries observer programs that operate in the region offer an opportunity to collect the additional information on the mid and upper trophic levels of the ecosystem that is necessary to complement this physical data, including time-series of distribution, abundance, size, composition and biological information on target and non-target species and mid trophic level organisms. These observer programs are in their infancy, with limited temporal and spatial distribution but recent international and national policy decisions have been made to expand their coverage. We identify a number of actions to initiate this monitoring including: consolidating collaborations to ensure the use of best quality data; developing consistency between sub-regional observer programmes to ensure that they meet the objectives of ecosystem monitoring; interrogating of existing time series to determine the most appropriate spatial template for monitoring; and exploring existing ecosystem models to identify suitable indicators of ecosystem status and change. The information obtained should improve capacity to develop fisheries management policies that are resilient and can be adapted to climate change.
Keywords: climate change; monitoring; ocean observation; Pacific Ocean; pelagic fisheries

Oceanic Shoals Commonwealth Marine Reserve (Timor Sea) Biodiversity Survey: Post Survey Report - Scott L Nichol; Howard, F; Johnathan T. Kool; Marcus Stowar; Phil J. Bouchet; Lynda Radke; Justy P W Siwabessy; Rachel Przeslawski; K Picard; Alvarez de Glasby, B; Jamie Colquhoun; Tom B. Letessier; et al. (GA Record, 2013)
This report provides details of activities undertaken by the Australian Institute of Marine Science (AIMS), Geoscience Australia (GA), the University of Western Australia and the Museum and Art Gallery of the Northern Territory during a marine biodiversity survey to the Oceanic Shoals Commonwealth Marine Reserve (Timor Sea) in 2012. The survey was an activity within the Australian Government’s National Environmental Research Program Marine Biodiversity Hub and the key component of Theme 4 – Regional Biodiversity Discovery to Support Marine Bioregional Plans. Data collected during the survey will be used to support research being undertaken in other Themes of the Marine Biodiversity Hub, including the modelling of ecosystem processes for the northern region, and to support the work programs of the Department of the Environment (previously Department of Sustainability, Environment, Water, Population and Communities). These data will be made publicly available, via the Marine Biodiversity Hub website and the Australian Ocean Data Network Portal, adding to the knowledge base of Australian tropical shelf habitats and contributing to the long term management of these poorly understood areas.

Optimising GEOBIA for seafloor classification. Multibeam Backscatter–State of the Technology, Tools & Techniques Workshop - Vanessa L Lucieer (GEOHAB (Marine Geological and Biological Habitat Mapping), 2013)
Invited presentation.

Pocillopora aliciae : a new species of scleractinian coral (Scleractinia, Pocilloporidae) from subtropical Eastern Australia - Schmidt-Roach, Sebastian; Karen J Miller; Andreakis, Nikos (Zootaxa, 2013)
Lack of morphological features of diagnostic value and high levels of environmental phenotypic plasticity obscure species boundaries for most taxa in the genus Pocillopora Lamarck, 1816 and complicate the definition of taxonomically distinct units. Species of the genus are colonial, generally ramose, rarely massive or encrusting and mostly hermatypic; corallite arrangement is plocoid, septa are generally poorly developed and usually arranged in two cycles; the columella is mostly poorly developed (Veron & Pichon 1976). Verrucae are common, although reduced in some species. Currently 17 species are formally acknowledged within the genus (Veron 2000). Using a molecular phylogenetic approach, recent studies were able to identify genetically distinct lineages in Pocillopora, indicating that Pocillopora damicornis (Linnaeus, 1751) consists of a cryptic species complex (Souter 2010; Schmidt-Roach et al. 2012a). One of these species, previously considered a temperate ecomorph of P. damicornis, is here described as a novel species, based on its distinct morphology, unique mitochondrial haplotype and incongruity with previously described taxa in P. damicornis. Pocillopora aliciae sp. nov. exhibits a flat, plate-like growth (usually displayed by deep-water morphs of pocilloporids) at all depths, which clearly differentiates it from P. damicornis colonies at subtropical Lord Howe Island or Rottnest Island. Furthermore, Stylophora pistillata Esper, 1797, which is equally known to exhibit flat deep-water morphs, maintains its common gross morphology at equal depth to P. alicae sp. nov..

Polychaete diversity from western and northwestern Australia - Avery, Lynda; Wilson, R.S. (2013)
This poster was presented at the 11th International Polychaete Conference in Sydney, 4 to 9 August 2013 In 2003, 1,217 polychaete species were known from Australian waters, mostly from shallow southeastern waters. Here we review advances in the past 10 years, based on significant new collections from northern and northwestern Australia. This review is based on species richness estimates in 25 families. Aims To review advances in taxonomic knowledge of Australian polychaetes over the past 10 years. To identify Australian regions where collections are generating most new taxa. To estimate numbers of morphospecies awaiting description. To promote incompletely-studied collections and their availability to researchers undertaking taxonomic revisions.

Population structure in the Pocillopora damicornis cryptic species complex along Ningaloo Reef, Western Australia - Luke Thomas; Stat, M; Kennington, W J; Shedrawi, G; Gary A. Kendrick (Australian Coral Reef Society Conference 2013, 2013)
This poster was presented at the Australian Coral Reef Society Conference in Sydney, 28 - 30 August 2013. A key characteristic influencing the recovery potential of coral reefs to environmental perturbations is the level of connectivity between adjacent reefs by the dispersal of larvae. Here we report on the population structure of P. damicornis along the Ningaloo Reef Marine Park using a panel of microsatellite markers and a mitochondrial gene marker (ORF).

Practical solutions for making models indispensable in conservation decision-making - P F E Addison; Rumpff, Libby; Bau, S. Sana; Carey, Janet M.; Chee, Yung En; Jarrad, Frith C.; McBride, Marissa F.; Burgman, Mark A. (Diversity and Distributions, 2013)
Decision-making for conservation management often involves evaluating risks in the face of environmental uncertainty. Models support decision-making by (1) synthesizing available knowledge in a systematic, rational and transparent way and (2) providing a platform for exploring and resolving uncertainty about the consequences of management decisions. Despite their benefits, models are still not used in many conservation decision-making contexts. In this article, we provide evidence of common objections to the use of models in environmental decision-making. In response, we present a series of practical solutions for modellers to help improve the effectiveness and relevance of their work in conservation decision-making.
Keywords: Communication; Conservation; modelling; structured decision-making; trust; uncertainty

Predictive mapping of seabed cover types using angular response curves of multibeam backscatter data: Testing different feature analysis approaches - Z Huang; Justy P W Siwabessy; Scott L Nichol; Tara J Anderson; Brendan P Brooke (Continental Shelf Research, 2013)
Angular response curves of multibeam backscatter data are used to predict the distributions of seven seabed cover types in an acoustically-complex area of the continental shelf of Western Australia. Several feature analysis approaches on the angular response curves are examined. A Probability Neural Network model was chosen for the predictive mapping, which accuracy measurement is given by a statistical coefficient Kappa. The prediction results have demonstrated the value of angular response curves for seabed mapping with Kappa=0.59 and a reasonable spatial prediction based on a visual assessment. This study also demonstrates the potential of various feature analysis approaches to improve seabed mapping. The approach to derive statistical parameters from the curves achieved significant feature reduction and some gain in statistical performance (e.g., Kappa=0.62). Its prediction map also represents a notable improvement. The first derivative analysis approach achieved the best overall statistical performance (e.g., Kappa=0.84); while the approach to remove the global slope produced the best overall prediction map as well as a significant gain in statistical performance (e.g., Kappa=0.74). We therefore recommend these three feature analysis approaches, along with the original angular response curves, for future seabed classification studies.
Keywords: Angular response curves; Feature analysis; Multibeam backscatter; Prediction; Seabed mapping

Providing a marine context for offsets and social values - Fact sheet - Annabel Ozimec (2013)
Offsets are defined as measures that compensate for the residual impacts of an action on the environment. The Environmental Offsets Policy outlines when and how offsets may be used under the EPBC Act 1999. Experience with offsets in the marine environment is relatively undeveloped and their design and implementation in this context poses particular challenges. This NERP Marine Biodiversity Hub project addresses the practical issue of how both the policy and calculator can be used in the marine environment.

Public and expert preference divergence: evidence from a choice experiment of marine reserves in Australia - Abbie A Rogers (Land Economics, 2013)
This study investigates whether public and expert preferences diverge in a valuation of two marine reserves in Western Australia.  Identical choice experiments are applied to a sample of marine scientists and the West Australian community. Evidence of both divergence and convergence between public and expert values is found, with public awareness factors helping to explain differences of opinion. This result implies that, in instances of divergence, it may be preferable to support potential environmental policies through community awareness campaigns, rather than using uninformed public preferences in policy design.

Seabed multi-beam backscatter mapping of the Australian continental margin - Keith, G.; Rudy J Kloser (2013)
This poster was prepared for the GeoHab 2013 conference, Rome, 6 - 10 May 2013. The Australian Marine National Facility, RV Southern Surveyor, was fitted with a Simrad EM300 multi-beam echosounder (swath mapper) at the end of 2003. Since then it has been mapping the seafloor around Australia on a variety of research and transit voyages, we have concentrated on mapping the continental margin (100 m – 1500 m) with emphasis on the upper slope (200 m – 700 m depth). This national data set is a useful resource for large scale marine management. Data on key ecological features, such as submarine canyons and seamounts, is available as is information on the distribution of hard and soft substrate that provide habitats suitable for attaching and burrowing fauna, respectively.

Seabed multi-beam backscatter mapping of the Australian continental margin - Rudy J Kloser; Keith, G. (Acoustics Australia, 2013)
A multi-beam sonar (MBS) has been used to map Australia’s continental margin seabed from the marine national facility vessel Southern Surveyor on opportunistic transit and research voyages since 2004 with 0.35 M km2 mapped. The MBS data are used to infer key ecological features based on bathymetry (e.g. seamounts, canyons, terraces, banks and deep reefs) and backscatter data for ecological hard (consolidated, e.g. rock for attachment of fauna) and soft (unconsolidated, e.g. mud for burrowing fauna) substrate. Seabed consolidation inference is consistent with a seabed scattering model. To consistently infer ecological significant hard and soft substrate from the backscatter data requires minimisation of errors due to changing absorption (~2 dB) with temperature and depth, calibration drift, changes in pulse length and estimates of area insonified due to seabed slope (<8 dB). Area insonified corrections were required for both across and along-ship slopes. Highest corrections were needed for along-ship slopes in canyon regions and large incidence angles (>60°). A data collection and processing framework is described that works towards a national backscatter mapping program for environmental seabed mapping. Data collected and automated processing for depth, sound absorption and area insonified at level 2 of a possible 5 level data processing hierarchy is available for viewing at http://www.marine.csiro.au/geoserver.

Social licence to operate and marine offsets - Abbie A Rogers; Burton, Michael; Pannell, David (Australian Agricultural and Resource Economics Society 2013 (57th Annual Conference), 2013)
Biodiversity offset policies exist at the National and State Government levels to ensure that offsets for residual environmental damages are undertaken in an ecologically equivalent manner.1 However, the policies don’t address whether the wider community accepts all aspects of an ecologically effective offset design. Could community concern reduce the social licence to operate of the proponent responsible for the residual damages? Using discrete choice experiments, we will investigate the preferences that the Australian community hold for different characteristics of marine biodiversity offsets. AARES Conference 2013

Social welfare and marine reserves – is willingness to pay for conservation dependent on management process? A discrete choice experiment of the Ningaloo Marine Park in Australia - Abbie A Rogers (Canadian Journal of Agricultural Economics/Revue canadienne d'agroeconomie, 2013)
The creation of a marine reserve network is an active area of policy in Australia.Here, a discrete choice experiment is used to estimate how the community values the ecology of the Ningaloo Marine Park, with a view to understanding the drivers of social welfare in relation to marine conservation. A novel aspect of this research is that it not only considers the values people hold for conservation outcomes, but also their preferences for how those outcomes are achieved. The results indicate that management process does have an impact on individuals’ preferences for conservation. By considering management process within the choice model, we gain a richer understanding of the relationship between social welfare and marine conservation.

Spatial and temporal predictions of inter-decadal trends in Indian Ocean whale sharks - AMM Sequeira; Camille Mellin; Delean, S; Mark Meekan; Bradshaw, CJA (Marine Ecology Progress Series, 2013)
: The processes driving temporal distribution and abundance patterns of whale sharks Rhincodon typus remain largely unexplained. We present an analysis of whale shark occurrence in the western Indian Ocean, incorporating both spatial and temporal elements. We tested the hypothesis that the average sighting probability of sharks has not changed over nearly 2 decades, and evaluated whether variance in sightings can be partially explained by climate signals. We used a 17 yr dataset (1991 to 2007, autumn only) of whale shark observations recorded in the log- books of tuna purse-seiners. We randomly generated pseudo-absences and applied sequential generalized linear mixed-effects models within a multi-model information-theoretic framework, accounting for sampling effort and random annual variation, to evaluate the relative importance of temporal and climatic predictors to sighting probability. After accounting for seasonal patterns in distribution, we found evidence that sighting probability increased slightly in the first half of the sampling interval (1991−2000) and decreased thereafter (2000−2007). The model including a spa- tial predictor of occurrence, fishing effort, time 2 and a random spatial effect explained ~60% of the deviance in sighting probability. After including climatic predictors, we found that sighting prob- ability increased slightly with rising temperature in the central Pacific Ocean and reduced temper- atures in the Indian Ocean. The declining phase of the peak, concurrent with recent accounts of declines in population size at near-shore aggregations and with the most pronounced global warming, deserves continued investigation. Teasing apart the legacy effects of past exploitation and those arising from on-going climate changes will be a major challenge for the successful long- term management of the species.
Keywords: Generalized linear mixed-effects models; Satellite data; Spatial distribution; Temporal trends · Rhincodon typus; Tuna purse-seine fisheries

Speartooth Shark Glyphis glyphis species information - Fact Sheet - PM Kyne (2013)
Conservation Status of Speartooth Shark Glyphis glyphis IUCN Red List of Threatened Species: Endangered Commonwealth: Critically Endangered Northern Territory: Vulnerable Description The Speartooth Shark is thought to be a large whaler shark. It is characterised by small eyes, a second dorsal fin, which is more than half the height of its first dorsal fin, a broadly rounded snout, and upper teeth which are triangular and serrated, and broader than the lower teeth. The 'watermark' marking on the side of the head extends only marginally below the eyes. Size Born at about 50 cm in length and thought to reach 250-300 cm, but adults of this species have never be observed. Notes The Speartooth Shark is only known from nine river systems across northern Australia, although it also occurs in southern New Guinea. Juveniles and subadults occupy the turbid, tidal reaches of large tropical rivers, and adults are presumably coastal and marine. Related information: Catch up on news, watch videos and download resources from the sawfish and river shark research undertaken during the National Environmental Research Program (NERP) 2011 - 2014
Keywords: Glyphis glyphis; Speartooth shark

Statistical solutions for error and bias in global citizen science datasets - Bird, Tomas J.; Amanda E. Bates; Lefcheck, Jonathan S.; Nicole A. Hill; Russell J. Thomson; Graham J. Edgar; Rick D Stuart-Smith; Wotherspoon, Simon; Krkosek, Martin; Jemina F. Stuart-Smith; Gretta Pecl; Neville Barrett; et al. (Biological Conservation, 2013)
Networks of citizen scientists (CS) have the potential to observe biodiversity and species distributions at global scales. Yet the adoption of such datasets in conservation science may be hindered by a perception that the data are of low quality. This perception likely stems from the propensity of data generated by CS to contain greater levels of variability (e.g., measurement error) or bias (e.g., spatio-temporal clustering) in comparison to data collected by scientists or instruments. Modern analytical approaches can account for many types of error and bias typical of CS datasets. It is possible to (1) describe how pseudo-replication in sampling influences the overall variability in response data using mixed-effects modeling, (2) integrate data to explicitly model the sampling process and account for bias using a hierarchical modeling framework, and (3) examine the relative influence of many different or related explanatory factors using machine learning tools. Information from these modeling approaches can be used to predict species distributions and to estimate biodiversity. Even so, achieving the full potential from CS projects requires meta-data describing the sampling process, reference data to allow for standardization, and insightful modeling suitable to the question of interest.
Keywords: Additive models; Biodiversity; Experimental design; inear models; Reef life survey; Species distribution models; Statistical analysis; Volunteer data

Systematic conservation planning: A better recipe for managing the high seas for biodiversity conservation and sustainable use - Natalie C. Ban; Nicholas J. Bax; Kristina M. Gjerde; Devillers, Rodolphe; Daniel C. Dunn; Piers K Dunstan; Alistair J Hobday; Maxwell, Sara M.; Kaplan, David M.; Pressey, Robert L.; Jeff A Ardron; Edward T Game; et al. (Conservation Letters, 2013)
At the UN Conference on Sustainable Development in Rio in June 2012, world leaders committed to the conservation and sustainable use of marine biological diversity in areas beyond national jurisdiction (the high seas). Our analysis of gaps in high seas management indicates that a paradigm shift to a more system- atic approach will be needed to safeguard high seas biodiversity from mounting threats. Experience from terrestrial and coastal areas indicates that a system- atic approach to conservation planning and management can help to maintain ecosystem health and productivity while enabling sustainable use. Our anal- ysis further demonstrates that the current legal regime on the high seas is insufficient to realize these objectives: management institutions have neither an adequate mandate for integrated planning nor the ability to effectively co- ordinate across multiple management regimes. We identify key elements for future high seas management and posit that a two-pronged approach is most promising: the development of an improved global legal regime that incorpo- rates systematic planning as well as the expansion of existing and new regional agreements and mandates. This combined approach is most likely to achieve the required ecosystem-based, integrated and science-based management that world leaders at Rio acknowledged should underpin ocean management.
Keywords: Areas beyond national jurisdiction; deep sea; marine conservation; marine protected areas; marine spatial planning; open ocean; sustainable fisheries.

To mix or not to mix: comparing the predictive performance of mixture models vs. separate species distribution models - Francis K.C. Hui; David I. Warton; Scott D Foster; Piers K Dunstan (Ecology, 2013)
Species distribution models (SDMs) are an important tool for studying the patterns of species across environmental and geographic space. For community data, a common approach involves fitting an SDM to each species separately, although the large number of models makes interpretation difficult and fails to exploit any similarities between individual species responses. A recently proposed alternative that can potentially overcome these difficulties is species archetype models (SAMs), a model-based approach that clusters species based on their environmental response. In this paper, we compare the predictive performance of SAMs against separate SDMs using a number of multi-species data sets. Results show that SAMs improve model accuracy and discriminatory capacity compared to separate SDMs. This is achieved by borrowing strength from common species having higher information content. Moreover, the improvement increases as the species become rarer. Read More: http://www.esajournals.org/doi/abs/10.1890/12-1322.1
Keywords: community level modeling; cross validation; generalized linear models; mixture models; species archetypes; Species distribution models

Unravelling Symbiodinium diversity with next generation sequencing from environmental extremes of Western Australia - Luke Thomas; Kennington, W J; Richards, Z T; Gary A. Kendrick; Stat, M (Pan American Coral Reefs Conference 2013, 2013)
This poster was presented at the Pan American Coral Reefs Conference in Merida, Mexico, in October 2013. The research aims to: document the diversity of Symbiodinium communities in dominant Acropora species from two contrasting marine environments at the latitudinal limits of the genus' distribution in Western Australia compare the power of detection using Sanger v. high-throughput approaches Background A single coral host may harbour a variety of Symbiodinium clades at any one point in time (see Baker 2003 for a review). which is thought to be a mechanism to facilitate acclimatization in a stochastic environment-during periods of prolonged thermal stress, corals have the ability to shuffle around their Symbiodinium so as to increase in proportion the most thermally tolerant strains, known as the adaptive bleaching hypothesis {Buddemeier and Fautin1993). Conventional molecular techniques used to evaluate Symbiodinium diversity in cnidarians are only capable of detecting the dominant clade from a single sample (April and Gates 2007) and often fail to identify rare clades present at levels below 10%. Although perhaps not a s ecologically or physiologically Important as the dominant clades, background clades may prove to be major players influencing the acclimating potential of coral communities to stressors associated with climate change. In turn, a comprehensive and accurate evaluation of Symbiodinium diversity is central to predicting how a coral reef system might respond to climatic fluctuation.

Whole mitogenome of the Endangered dwarf sawfish Pristis clavata (Rajiformes: Pristidae). - Pierre Feutry; PM Kyne; Grewe, Peter M.; Xiao Chen; Liu, Min (Mitochondrial DNA, 2013)
In this study, we describe the first complete mitochondrial sequence for the Endangered dwarf sawfish Pristis clavata. The base composition of the 16,804 bp long mitogenome is 31.9% A, 26.5% C, 13.3% G and 28.3% T and the gene arrangement and transcriptional direction are the same as those found in most vertebrates. All protein-coding genes start with ATG except the COI gene, which starts with GTG. Stop codons include incomplete T, AGG and TAA; however, TAG is not found in the mitogenome of this euryhaline elasmobranch species.
Keywords: Mitochondrial genome; Pristis clavata; threatened species

Anthropogenic threats to benthic habitats - Harris, Peter T. (Seafloor geomorphology as benthic habitat: GeoHAB atlas of seafloor geomorphic features and benthic habitats, 2012)

Assessing size, abundance and habitat preferences of the Ocean Perch Helicolenus percoides using a AUV-borne stereo camera system - Seiler, Jan; Williams, Alan; Neville Barrett (Fisheries Research, 2012)
Traditional fishery resource assessment methods using trawl gear are unable to sample rocky substratum and are prone to underestimating the biomass of species having partial or strong association with rocky reefs. This study successfully used an Autonomous Underwater Vehicle (AUV) and image-yielding methods to estimate size, abundance and habitat preference of an abundant and commercially important ‘rockfish’ – the Ocean Perch (Helicolenus percoides) – in rocky habitats on the continental shelf off Tasmania, SE Australia. More than half (53%) of the Ocean Perch observed were photogrammetrically measured with known accuracy using a stereo camera system yielding length-frequency distributions. Observations of juvenile and adult H. percoides across a depth gradient showed that adults preferred rocky substrates over soft substrates, whereas juveniles preferred soft substrate over hard substrate. We found a positive relationship between rockfish abundance and increasing depth in most habitat types. These results demonstrate the utility of image-based methods for determining size composition and habitat preferences of some reef-associated species. However, there is scope to improve image-based methods using length estimation procedures that enable higher proportions of individuals to be measured (compared to the proportion achieved in this study), and by incorporating automated image annotation to decrease image analysis times, particularly when examining species/habitat relationships. The importance of analytical procedures that account for autocorrelation in non-independent image data on habitats and associated species is discussed. We conclude that rapidly maturing image-based observational methods have potential utility in complementing fishery stock assessments of some reef-associated species. Image-based methods are also well-suited to simultaneously provide additional quantitative measures of benthic habitats, invertebrate fauna and fishery environments.
Keywords: abundance assessment; auv; fishery-independent data; habitat preferences; ocean perch; size assessment; stereo camera system

Biogeography, benthic ecology and habitat classification schemes - Harris, Peter T. (Seafloor geomorphology as benthic habitat: GeoHAB atlas of seafloor geomorphic features and benthic habitats, 2012)

Biological surrogacy in tropical seabed assemblages fails - Sutcliffe, P. R.; C Roland Pitcher; M Julian Caley; Possingham, H.P. (Ecological Applications, 2012)
Surrogate taxa are used widely to represent attributes of other taxa for which data are sparse or absent. Because surveying and monitoring marine biodiversity is resource intensive, our understanding and management of marine systems will need to rely on the availability of effective surrogates. The ability of any marine taxon to adequately represent another, however, is largely unknown because there are rarely sufficient data for multiple taxa in the same region(s). Here, we defined a taxonomic group to be a surrogate for another taxonomic group if they possessed similar assemblage patterns. We investigated effects on surrogate performance of (1) grouping species by taxon at various levels of resolution, (2) selective removal of rare species from analysis, and (3) the number of clusters used to define assemblages, using samples for 11 phyla distributed across 1189 sites sampled from the seabed of Australia's Great Barrier Reef. This spatially and taxonomically comprehensive data set provided an opportunity for extensive testing of surrogate performance in a tropical marine system using these three approaches for the first time, as resource and data constraints were previously limiting. We measured surrogate performance as to how similarly sampling sites were divided into assemblages between taxa. For each taxonomic group independently, we grouped sites into assemblages using Hellinger distances and medoid clustering. We then used a similarity index to quantify the concordance of assemblages between all pairs of taxonomic groups. Surrogates performed better when taxa were grouped at a phylum level, compared to taxa grouped at a finer taxonomic resolution, and were unaffected by the exclusion of spatially rare species. Mean surrogate performance increased as the number of clusters decreased. Moreover, no taxonomic group was a particularly good surrogate for any other, suggesting that the use of any one (or few) group(s) for mapping seabed biodiversity patterns is imprudent; sampling several taxonomic groups appears to be essential for understanding tropical/subtropical seabed communities. Consequently, where resource constraints do not allow complete surveying of biodiversity, it may be preferable to exclude rare species to allow investment in a broader range of taxonomic groups.
Keywords: assemblage patterns; Australia; Biodiversity; cluster; congruence; cross-taxon surrogates; Great Barrier Reef; invertebrates; marine communities; rarity; taxonomic assemblages; tropical seabed

Biological vulnerability of two exploited sharks of the genus Deania (Centrophoridae) - S. B. Irvine; Ross K Daley; Graham, K. J.; Stevens, J. D. (Journal of Fish Biology, 2012)
Life-history parameters of Deania calcea and Deania quadrispinosa suggested that their productivity was very low. Maturity (LT50) occurs at c. 80% of maximum observed total lengths (LT) for both species and sexes. A large proportion of mature females were neither pre-ovulatory nor pregnant, and the reproductive cycle included a distinct resting phase after pregnancy. For D. calcea, mean ovarian fecundity was 12 and maximum observed litter size was 10 (average of six); D. quadrispinosa averaged 17 pups per litter. Birth LT was 28–33 cm for D. calcea and 23–25 cm for D. quadrispinosa. The male and female reproductive cycles were aseasonal, and consequently, the length of the reproductive cycle could not be determined. Preliminary ageing data from dorsal-spine growth bands suggested that female D. calcea lived to 31–36 years and males to 24–32 years. The LT-at-age data using external bands on the spines showed maturity occurring at 15·5 years (males) and 21·5 years (females), whereas banding on the internal dentine indicated maturity at 10·5 and 17·5 years for males and females. Thus, a female lifetime of 31–36 years allowed for a maximum of 7 litters if a 2 year cycle is assumed or only five litters with a 3 year cycle, resulting in a lifetime fecundity of only 42 pups (2 year cycle) or even lower (3 year cycle).
Keywords: brier shark; deep-water dogfish; growth; longsnout dogfish; Reproduction; south-east Australia

Biophysical patterns in benthic assemblage composition across contrasting continental margins off New Zealand - Compton, Tanya J.; Bowden, David A.; C Roland Pitcher; Judi E Hewitt; Nick Ellis (Journal of Biogeography, 2012)
Aim To examine whether benthic assemblages are more diverse in a region of high topographic and oceanographic complexity by comparing benthic invertebrate assemblages across continental margins with contrasting environments. Location Challenger Plateau and Chatham Rise, to the west and east of New Zealand, respectively. Methods Benthic faunal data were sourced from extensive seabed surveys in 2007, when both margins were sampled with an epibenthic sled and a towed video system. Three methods were used to investigate benthic assemblages in relation to environmental variables: one based on individual species distribution models (SDMs) using boosted regression trees analysis (BRT), and two community-based modelling methods using generalized dissimilarity modelling (GDM) and gradient forest analysis (GF), respectively. Each method was used to model and predict the turnover in assemblages with respect to environment – the ‘biophysical patterns’ – across the study region. Results Across Chatham Rise, a complex oceanographic environment arising from steep gradients in productivity and temperature at the Subtropical Front produced a high diversity of assemblages associated with the sub-Antarctic water mass, the Subtropical Front, steep-sloping regions and fast tidal currents. In contrast, Challenger Plateau lies entirely beneath a single (subtropical) water mass, and assemblage diversity was lower, with a distinctive assemblage on the plateau itself and a deep-water assemblage similar to the northern deep-water assemblage of Chatham Rise. Across both regions, assemblage turnover was fastest in cold waters, at shallow depths and in deep mixed layers. Main conclusions Benthic assemblages were more varied on Chatham Rise than on Challenger Plateau, supporting the hypothesis that environmentally heterogeneous margins have higher assemblage diversity. Differing assemblages on the northern and southern flanks of Chatham Rise suggest a biogeographical boundary for benthic taxa across the Subtropical Front. These results demonstrate that oceanographically and topographically complex margins have a diverse assemblage structure that should be considered in planning for the sustainable management of diversity.
Keywords: Beta diversity; biodiversity mapping; conservation planning; Continental shelf; continental slope; marine biogeography; random forest; spatial planning.

Broadcast spawning by Pocillopora Species on the Great Barrier Reef - Schmidt-Roach, Sebastian; Karen J Miller; Woolsey, Erika; Gerlach, Gabriele; Baird, Andrew H. (PLoS ONE, 2012)
The coral genus Pocillopora is one of the few to include some species that broadcast spawn gametes and some species that brood larvae, although reports of reproductive mode and timing vary within and among species across their range. Notably, the ubiquitous Pocillopora damicornis has been described as both a brooder and spawner, although evidence of broadcast spawning is rare. Here, we report observations of broadcast-spawning in four species of Pocillopora on the Great Barrier Reef (GBR), including P. damicornis. All species spawned predictably during the early morning, two days following the full moon, and spawning was observed in multiple months over the summer period (November to February). Eggs and sperm were free-spawned concurrently. Eggs were negatively buoyant and contained Symbiodinium. This newfound knowledge on the mode, timing and regularity of broadcast spawning in Pocillopora spp. on the GBR brings us one step closer to elucidating the complex reproductive ecology of these species.

Catchment-based classification of Australia's continental slope canyons - R. Porter-Smith; Lyne, Vincent D.; Rudy J Kloser; Vanessa L Lucieer (Marine Geology, 2012)
This study presents an approach to the classification of submarine canyons on the Australian continental slope. There are many canyons around the Australian continental margin it provides an opportunity to undertake a characterisation and inventory of these potentially important assets. By establishing a shelf, break and foot of slope based on gradient, submarine catchments are defined based on a drainage network derived from across the continental shelf and slope. On completion of this classification, metrics are extracted for both the drainage network representing submarine canyons and the catchment morphology. The rationale for this research is to demonstrate the application of algorithms developed for drainage analysis. These algorithms have traditionally been applied in terrestrial environments for the automatic extraction of drainage networks and catchments from digital elevation models. This work is made possible by recent advances in deep-sea multibeam technology, so that the seafloor morphology can be mapped in higher definition. With the recent advances in data quality, these algorithms can be applied to an integrated and combined model of both elevation and bathymetric datasets to provide better insight into geomorphological features, including the relationships between subaqueous sedimentary canyons, channels and drainage system morphology. Drainage analysis provides a rapid automatic procedure to derive networks on the continental shelf and slope. Results show that by establishing a shelf break and foot of slope based on gradient, submarine catchments can be derived on the continental slope based on the drainage analysis. The Australian continental slope contains 257 shelf-incised catchments based on analysis of a bathymetric model mapped at a resolution of 250 m. The drainage analysis demonstrates the capabilities of correctly predicting the layout of dendritic patterns leading to a better geological understanding.
Keywords: bathome; biome; classification; continental slope; regionalisation; Submarine canyons

Characterising and predicting benthic biodiversity for conservation planning in deepwater environments - Piers K Dunstan; Althaus, Franziska; Williams, Alan; Nicholas J. Bax; Bograd, Steven J. (PLoS ONE, 2012)
Understanding patterns of biodiversity in deep sea systems is increasingly important because human activities are extending further into these areas. However, obtaining data is difficult, limiting the ability of science to inform management decisions. We have used three different methods of quantifying biodiversity to describe patterns of biodiversity in an area that includes two marine reserves in deep water off southern Australia. We used biological data collected during a recent survey, combined with extensive physical data to model, predict and map three different attributes of biodiversity: distributions of common species, beta diversity and rank abundance distributions (RAD). The distribution of each of eight common species was unique, although all the species respond to a depth-correlated physical gradient. Changes in composition (beta diversity) were large, even between sites with very similar environmental conditions. Composition at any one site was highly uncertain, and the suite of species changed dramatically both across and down slope. In contrast, the distributions of the RAD components of biodiversity (community abundance, richness, and evenness) were relatively smooth across the study area, suggesting that assemblage structure (i.e. the distribution of abundances of species) is limited, irrespective of species composition. Seamounts had similar biodiversity based on metrics of species presence, beta diversity, total abundance, richness and evenness to the adjacent continental slope in the same depth ranges. These analyses suggest that conservation objectives need to clearly identify which aspects of biodiversity are valued, and employ an appropriate suite of methods to address these aspects, to ensure that conservation goals are met.

Comparing large-scale bioregions and fine-scale community-level biodiversity predictions from subtidal rocky reefs across south-eastern Australia - Rebecca Leaper; Piers K Dunstan; Scott D Foster; Neville Barrett (Journal of Applied Ecology, 2012)
In the absence of knowledge of the large-scale structure and distribution of marine biota, bioregionalisations, that is, spatial classifications of data on a range of environmental and⁄ or biological attributes, are often viewed as one of the most appropriate frameworks within which to develop networks of marine protected areas (MPAs). However, despite their potential usefulness, few studies have assessed whether bioregionalisations can be used for management of species other than those it was derived from or whether bioregionalisations capture fully fine-scale community-level biodiversity patterns. We investigated the large-scale structure and distribution of demersal fishes and macroinvertebrates in south-eastern Australia, using rank abundance distributions (RADs). We used a recently developed community modelling method that allows their multivariate distribution to vary according to environmental gradients, assessing the congruency of mapped biogeographic patterns between the different taxa, and in the light of the Interim Marine and Coastal Regionalisation for Australia (IMCRA). A clear pattern in our analysis based on RADs showed a large difference in assemblage structure (i.e. in abundance, richness and evenness) between South Australia, where assemblages were generally more species rich and even, and Victoria and Tasmania, where assemblages were generally more species poor and uneven. The strong longitudinal pattern in species richness and evenness was generally congruent for both demersal fishes and macroinvertebrates and related to regional differences in oceanography. We found that the regions of highest species richness were found in the ‘core’ bioregions rather than ‘transition’ bioregions as defined in the IMCRA and for both taxa. Moreover, we found that not all assemblage structures were equally alike and that South Australia had the greatest range of unique assemblage structures. Synthesis and applications. While bioregionalisations are typically based on data from a single taxon, our findings highlight that they can be used as a surrogate for biological patterns seen in other taxa. Bioregionalisations, however, may not capture fully fine-scale communitylevel biodiversity patterns, and this may compromise the ability of protected area networks to protect the full variability in assemblage types. We suggest that it may be necessary to  validate existing regionalisations with additional data and analyses such as the RAD analyses conducted here.
Keywords: Biodiversity; bioregion; community; conservation planning; evenness; Marine; rank abundance distributions; species richness; subtidal rocky reefs

The Conservation Status of North American, Central American, and Caribbean Chondrichthyans - PM Kyne; John K. Carlson; David A. Ebert; Sonja V. Fordham; Bizzarro, J J; Graham, R T; Kulka, D W; Tewes, E E; Harrison, L R; N K Dulvy (IUCN Species Survival Commission Shark Specialist Group, 2012)
This report from the IUCN Shark Specialist Group includes the first compilation of conservation status assessments for the 282 chondrichthyan species (sharks, rays, and chimaeras) recorded from North American, Central American, and Caribbean waters. The status and needs of those species assessed against the IUCN Red List of Threatened Species criteria as threatened (Critically Endangered, Endangered, and Vulnerable) are highlighted. An overview of regional issues and a discussion of current and future management measures are also presented. A primary aim of the report is to inform the development of chondrichthyan research, conservation, and management priorities for the North American, Central American, and Caribbean region. Sharks and their relatives, including skates, rays, and chimaeras, are collectively termed chondrichthyan fishes (class Chondrichthyes). The skates and rays are known as batoids (superorder Batoidea) while the batoids and sharks together comprise the elasmobranchs (subclass Elasmobranchii). The chondrichthyans are a relatively small (~1,150 described species), evolutionarily conservative group that has functioned successfully in diverse marine and aquatic ecosystems for over 400 million years. Despite their evolutionary success, many species are increasingly threatened with overexploitation as a result of their life history traits and the activities of humans.

Cryptic diversity in flathead fishes (Scorpaeniformes: Platycephalidae) across the Indo-West Pacific uncovered by DNA barcoding - Puckridge, Melody; Andreakis, Nikos; Sharon A Appleyard; Ward, Robert D. (Molecular Ecology Resources, 2012)
Identification of taxonomical units underpins most biological endeavours ranging from accurate biodiversity estimates to the effective management of sustainably harvested, protected or endangered species. Successful species identification is now frequently based on a combination of approaches including morphometrics and DNA markers. Sequencing of the mitochondrial COI gene is an established methodology with an international campaign directed at barcoding all fishes. We employed COI sequencing alongside traditional taxonomic identification methods and uncovered instances of deep intraspecific genetic divergences among flathead species. Sixty-five operational taxonomic units (OTUs) were observed across the Indo-West Pacific from just 48 currently recognized species. The most comprehensively sampled taxon, Platycephalus indicus, exhibited the highest levels of genetic diversity with eight lineages separated by up to 16.37% genetic distance. Our results clearly indicate a thorough reappraisal of the current taxonomy of P. indicus (and its three junior synonyms) is warranted in conjunction with detailed taxonomic work on the other additional Platycephalidae OTUs detected by DNA barcoding.
Keywords: Cryptic species; DNA barcoding; fish; flathead; Platycephalidae; Platycephalus indicus

Deepwater emergent Patagonian Coral Fields - Narissa Bax (Australian Marine Science Association Conference, 1-5 July 2012, 2012)
Poster was prepared for the Australian Marine Science Association Conference, 1-5 July 2012  http://www.nerpmarine.edu.au/news/hub-researchers-convene-4-amsa-symposia Deep sea reefs are often dominated by a single habitat forming species (Cairns, 1983). The stylasterid coral Errina spp. have been identified as key structural species in Antarctica (Post et al, 2010), the South West Atlantic (Bax et al, in prep), New Zealand’s fiord's (Miller et al, 2004), and in southern Chile’s Patagonian fiord's (Haussermann & Forsterra, 2006). Errina antarctica is distributed throughout Patagonia and the peninsula region of Antarctica. Due to the phenomenon of Deep Water Emmergence (DWE), common of fiord systems, E. antarctica occurs in shallow waters. The extensive abundance (±80% coverage) and maximum colony size (40 cm) is exceptionally high compared to cold-water coral accumulations elsewhere. The closely related Antarctic Errina corals; E. fissurata, E. laterorifa and E. gracilis are considered circum-Antarctic, and often occur in sympatry (Cairns, 1983), in dense field-like aggregations (Bax & Miller, in prep), at depths greater then 450m (Post et al, 2010). Sampling in Antarctica is extremely challenging, sample sizes and experimental design are often less than ideal as a result. Hence, the shallow coral fields of the Patagonian fiords provide the unique opportunity to gain in-sight into the dispersal capacity of corals in more inaccessible ecosystems such as sea-mount and submarine ridges in Antarctica.

Developing physical surrogates for benthic biodiversity using co-located samples and regression tree models: a conceptual synthesis for a sandy temperate embayment - Z Huang; Matthew McArthur; Lynda Radke; Tara J Anderson; Scott L Nichol; Justy P W Siwabessy; Brendan P Brooke (International Journal of Geographical Information Science, 2012)
Marine physical and geochemical data can be valuable surrogates for predicting the distributions and assemblages of marine species. This study investigated the bio-environment (surrogacy) relationships in Jervis Bay, a sandy marine embayment in south-eastern Australia. A wide range of co-located physical data were analysed together with biological data, including multibeam bathymetry and backscatter surfaces and derivatives, parameters that describe seabed sediment and water column physical/geochemical characteristics and seabed exposure. Three decision tree models and a robust model selection process were applied. The models for three diversity indices and seven out of eight infaunal species explained 32–79% of the variance. A diverse range of physical surrogates for biodiversity were identified. The surrogates are presented in a conceptual model that identifies the mechanisms that potentially link to biodiversity patterns. While some surrogates may exert direct influence over organisms to exposure and chlorophyll-a, for example, most pointed to complex relationships between multiple biological and physical factors occurring in different process domains/zones. The reliable bio-environment relationships identified from co-located samples and conceptual models enabled a mechanistic understanding of benthic biodiversity patterns in a sandy coastal embayment that may have implications for marine environmental management.
Keywords: benthic biodiversity; conceptual model; Jervis Bay; surrogates

Evaluating Geomorphic Features as Surrogates for Benthic Biodiversity on Australia’s Western Continental Margin - Althaus, Franziska; Williams, Alan; Kloser, Rudy J.; Seiler, Jan; Nicholas J. Bax (Seafloor Geomorphology as Benthic Habitat, 2012)
Australia's western continental margin extends over∼2,000 km, from subtropical to temperate latitudes (∼18–35ºS). The regional oceanography overlying the deep continental shelf and slope area (∼100–1,000 m depths) is profoundly influenced by the southward-flowing Leeuwin current (LC) to depths of ∼300 m, and by a northward-flowing counter-current, the Leeuwin Undercurrent (LUC) below those depths. The LC is characterized by warm, low-salinity, low-productivity waters, whereas the LUC is characterized by colder more oxygenated waters. The role of these features as ecological habitats and their potential as surrogates for biodiversity were examined in the context of a hierarchical habitat classification scheme used by Last et al. to define bioregions for marine management planning in Australian waters. Associations of epibenthic megafauna with habitats along Australia's western margin were evaluated quantitatively summarizing the presence/absence scores of 11 fauna types in the video frames into percentage occurrences of dominant fauna for each sample. The scored fauna types were: sessile fauna absent, bioturbators, anemones, seapen, stalked sponge, ascidians, bryozoa, crinoids, sponges, coral, and coral (reef); all scored at low or high abundance. It is necessary to have information at coarser scales to provide ecologically meaningful context, while information at finer scales provides ecologically meaningful detail. Book: https://www.elsevier.com/books/seafloor-geomorphology-as-benthic-habitat/harris/978-0-12-385140-6
Keywords: epifauna; hierarchical habitat classification; video data; Western Australia

Exploring the role of environmental variables in shaping patterns of seabed biodiversity composition in regional-scale ecosystems - C Roland Pitcher; Lawton, P.; Nick Ellis; Smith, Stephen J.; Lewis, S. Incze; Wei, C-L.; Greenlaw, M.E.; Wolff, N.H.; Sameoto, J.A.; Snelgrove, P.V.R (Journal of Applied Ecology, 2012)
Environmental variables are often used as indirect surrogates for mapping biodiversity because species survey data are scant at regional scales, especially in the marine realm. However, environmental variables are measured on arbitrary scales unlikely to have simple, direct relationships with biological patterns. Instead, biodiversity may respond nonlinearly and to interactions between environmental variables. To investigate the role of the environment in driving patterns of biodiversity composition in large marine regions, we collated multiple biological survey and environmental data sets from tropical NE Australia, the deep Gulf of Mexico and the temperate Gulf of Maine. We then quantified the shape and magnitude of multispecies responses along >30 environmental gradients and the extent to which these variables predicted regional distributions. To do this, we applied a new statistical approach, Gradient Forest, an extension of Random Forest, capable of modelling nonlinear and threshold responses. The regional-scale environmental variables predicted an average of 13–35% (up to 50–85% for individual species) of the variation in species abundance distributions. Important predictors differed among regions and biota and included depth, salinity, temperature, sediment composition and current stress. The shapes of responses along gradients also differed and were nonlinear, often with thresholds indicative of step changes in composition. These differing regional responses were partly due to differing environmental indicators of bioregional boundaries and, given the results to date, may indicate limited scope for extrapolating bio-physical relationships beyond the region of source data sets. Synthesis and applications. Gradient Forest offers a new capability for exploring relationships between biodiversity and environmental gradients, generating new information on multispecies responses at a detail not available previously. Importantly, given the scarcity of data, Gradient Forest enables the combined use of information from disparate data sets. The gradient response curves provide biologically informed transformations of environmental layers to predict and map expected patterns of biodiversity composition that represent sampled composition better than uninformed variables. The approach can be applied to support marine spatial planning and management and has similar applicability in terrestrial realms.
Keywords: beta diversity; community ecology; Conservation; environmental surrogates; habitat suitability modelling; spatial planning and management; species distribution modelling

Genetic catch verification to support recovery plans for deepsea gulper sharks (genus Centrophorus, family Centrophoridae) - an Australian example using the 16S gene - Ross K Daley; Sharon A Appleyard; Koopman, Mathew (Marine and Freshwater Research, 2012)
Several species of Centrophorus have been harvested beyond sustainable limits in the Pacific, Atlantic, and Indian Oceans. Effective monitoring of current recovery plans in Australia requires the implementation of a catch data verification plan. The utility of the 16S mitochondrial gene region was evaluated for discriminating among seven recognised morphologically similar Centrophorus species caught in commercial fisheries in Australia and Indonesia. The 16S gene amplified consistently, was sequenced in all individuals tested, and was able to distinguish all species with sufficient resolution for routine testing, apart from C. harrissoni and C. isodon. These two allopatric species were distinguishable using four types of external morphological characters. We conclude that the 16S gene is a robust marker suitable for fishery catch verification of Centrophorus, particularly for Australian samples collected under non-ideal conditions for preservation. When combined with morphological characters, this approach is a reliable and efficient system for routine testing. Trials with the CO1 mtDNA gene found that specialised primers are needed; trials with the Cytb mtDNA gene found this marker is sensitive to preservation problems. Future development of the 16S and CO1 markers are likely to contribute to resolution of taxonomic problems within the Centrophoridae.
Keywords: catch verification; gulper sharks; mtDNA; species identification

GeoHab Atlas of seafloor geomorphic features and benthic habitats – synthesis and lessons learned - Harris, Peter T.; Baker, Elaine K (Seafloor geomorphology as benthic habitat: GeoHAB atlas of seafloor geomorphic features and benthic habitats, 2012)

Gradient forests: calculating importance gradients on physical predictors - Nick Ellis; Smith, Stephen J.; C Roland Pitcher (Ecology, 2012)
In ecological analyses of species and community distributions there is interest in the nature of their responses to environmental gradients and in identifying the most important environmental variables, which may be used for predicting patterns of biodiversity. Methods such as random forests already exist to assess predictor importance for individual species and to indicate where along gradients abundance changes. However, there is a need to extend these methods to whole assemblages, to establish where along the range of these gradients the important compositional changes occur, and to identify any important thresholds or change points. We develop such a method, called ‘‘gradient forest,’’ which is an extension of the random forest approach. By synthesizing the cross-validated R2 and accuracy importance measures from univariate random forest analyses across multiple species, sampling devices, and surveys, gradient forest obtains a monotonic function of each predictor that represents the compositional turnover along the gradient of the predictor. When applied to a synthetic data set, the method correctly identified the important predictors and delineated where the compositional change points occurred along these gradients. Application of gradient forest to a real data set from part of the Great Barrier Reef identified mud fraction of the sediment as the most important predictor, with highest compositional turnover occurring at mud fraction values around 25%, and provided similar information for other predictors. Such refined information allows for more accurate capturing of biodiversity patterns for the purposes of bioregionalization, delineation of protected areas, or designing of biodiversity surveys.
Keywords: Biodiversity; community data; compositional turnover; Great Barrier Reef; random forests; variable importance

Habitat mapping and marine management - Baker, Elaine K; Harris, Peter T. (Seafloor geomorphology as benthic habitat: GeoHAB atlas of seafloor geomorphic features and benthic habitats, 2012)

Habitats and benthos of a deep sea marginal plateau, Lord Howe Rise, Australia. - Harris, Peter T.; Scott L Nichol; Tara J Anderson; Heap, Andrew D. (Seafloor geomorphology as benthic habitat: GeoHAB atlas of seafloor geomorphic features and benthic habitats, 2012)

Identifying hotspots for biodiversity management using rank abundance distributions - Piers K Dunstan; Nicholas J. Bax; Scott D Foster; Williams, Alan; Althaus, Franziska (Diversity and Distributions, 2012)
Identification of biodiversity hotspots has typically relied on species richness. We extend this approach to include prediction to regional scales of other attributes of biodiversity based on the prediction of Rank Abundance Distributions (RADs). This allows us to identify areas that have high numbers of rare species and areas that have a rare assemblage structure.
Keywords: Biodiversity; hotspot; Prediction; rank abundance distribution

Image-based continental shelf habitat mapping using novel automated data extraction techniques - Seiler, Jan; Friedman, Ariell; Steinberg, Daniel; Neville Barrett; Williams, Alan; Holbrook, Neil J. (Continental Shelf Research, 2012)
We automatically mapped the distribution of temperate continental shelf rocky reef habitats with a high degree of confidence using colour, texture, rugosity and patchiness features extracted from images in conjunction with machine-learning algorithms. This demonstrated the potential of novel automation routines to expedite the complex and time-consuming process of seabed mapping. The random forests ensemble classifier outperformed other tree-based algorithms and also offered some valuable built-in model performance assessment tools. Habitat prediction using random forests performed most accurately when all 26 image-derived predictors were included in the model. This produced an overall habitat prediction accuracy of 84% (with a kappa statistic of 0.793) when compared to nine distinct habitat classes assigned by a human annotator. Predictions for three habitat classes were all within the 95% confidence intervals, indicating close agreement between observed and predicted habitat classes. Misclassified images were mostly unevenly, partially or insufficiently illuminated and came mostly from rugged terrains and during the autonomous underwater vehicle's obstacle avoidance manoeuvres. The remaining misclassified images were wrongly or inconsistently labelled by the human annotator. This study demonstrates the suitability of autonomous underwater vehicles to effectively sample benthic habitats and the ability of automated data handling techniques to extract and reliably process large volumes of seabed image data. Our methods for image feature extraction and classification are repeatable, cost-effective and well suited to studies that require non-extractive and/or co-located sampling, e.g. in marine reserves and for monitoring the recovery from physical impacts, e.g. from bottom fishing activities. The methods are transferable to other continental shelf areas and to other disciplines such as seabed geology.
Keywords: habitat predictors; habitat variability; monitoring; random forests; sirius; tasmania

Living on the edge – waterfront views - Brendan P Brooke; Harris, Peter T.; Scott L Nichol; Sexton, Jane; Arthur, W.C.; Haese, R.R.; Heap, Andrew D.; Hazelwood, M.C.; Lynda Radke; Blewett, R.S (Shaping a nation: A geology of Australia, 2012)
Australia developed as a nation of coastal fringe dwellers even before the realisation in colonial times that there was no inland sea and the continent had a ‘dead heart’ of desert and scrub. The maritime character of the nation developed with the reliance on coastal seas for transport and trade during European settlement, through to the present day where the coast is the setting for most of Australia’s population, industry, tourism and recreation. The geological history of the coast and its distinctive configuration, landforms and environmental regimes have produced a unique, highly diverse continental margin. In turn, the coast has profoundly influenced the pattern of settlement and development of Australia.

Marine Biodiversity Hub Annual Work Plan 2012 - Nicholas J. Bax (2012)
Keywords: annual research plan

Marine Biodiversity Hub Banner 2012 - Paul Hedge (2012)

Monitoring Australia's Commonwealth Marine Reserves - Nicole A. Hill; K Hayes; Scott L Nichol (2012)
In July 2012, the Australian Government released the final version of a proposed network of marine reserves in Commonwealth waters.  The proposal increases the number of marine reserves from 27 to 60, providing for the protection of 3.1 million square kilometres or more than a third of Commonwealth waters.  It is the culmination of Australia's international commitment to establish a comprehensive, adequate and representative system of marine reserves by 2012.  Dr Nicole Hill from the University of Tasmania describes how they are planning to monitor such large expanse of protected area.

Monitoring of benthic reference sites - Williams, Stefan B.; Oscar R. Pizarro; Jakuba, Michael; Craig R. Johnson; Neville Barrett; Russell Babcock; Gary A. Kendrick; Peter D. Steinberg; Heyward, A.; Doherty, P.J.; Mahon, Ian; Johnson-Roberson, Matthew; et al. (IEEE Robotics & Automation Magazine, 2012)
We have established an Australia-wide observation program that exhibits recent developments in autonomous underwater vehicle (AUV) systems to deliver precisely navigated time series benthic imagery at selected reference stations on Australia’s continental shelf. These observations are designed to help characterize changes in benthic assemblage composition and cover derived from precisely registered maps collected at regular intervals. This information will provide researchers with the baseline ecological data necessary to make quantitative inferences about the long-term effects of climate change and human activities on the benthos. Incorporating a suite of observations that capitalize on the unique capabilities of AUVs into Australia’s integrated marine observation system (IMOS) [1] is providing a critical link between oceanographic and benthic processes. IMOS is a nationally coordinated program designed to establish and maintain the research infrastructure required to support Australia’s marine science research. It has, and will maintain, a strategic focus on the impact of major boundary currents on continental shelf environments, ecosystems, and biodiversity. The IMOS AUV facility observation program is designed to generate physical and biological observations of benthic variables that cannot be cost effectively obtained by other means.

Multi-scale marine biodiversity patterns inferred efficiently from habitat image processing - Camille Mellin; Parrott, Lael; Serge Andréfouët; Bradshaw, Corey; Aaron M MacNeil; M Julian Caley (Ecological Applications, 2012)
Cost-effective proxies of biodiversity and species abundance, applicable across a range of spatial scales, are needed for setting conservation priorities and planning action. We outline a rapid, efficient, and low-cost measure of spectral signal from digital habitat images that, being an effective proxy for habitat complexity, correlates with species diversity and requires little image processing or interpretation. We validated this method for coral reefs of the Great Barrier Reef (GBR), Australia, across a range of spatial scales (1 m to 10 km), using digital photographs of benthic communities at the transect scale and high-resolution Landsat satellite images at the reef scale. We calculated an index of image-derived spatial heterogeneity, the mean information gain (MIG), for each scale and related it to univariate (species richness and total abundance summed across species) and multivariate (species abundance matrix) measures of fish community structure, using two techniques that account for the hierarchical structure of the data: hierarchical (mixed-effect) linear models and distance-based partial redundancy analysis. Over the length and breadth of the GBR, MIG alone explained up to 29% of deviance in fish species richness, 33% in total fish abundance, and 25% in fish community structure at multiple scales, thus demonstrating the possibility of easily and rapidly exploiting spatial information contained in digital images to complement existing methods for inferring diversity and abundance patterns among fish communities. Thus, the spectral signal of unprocessed remotely sensed images provides an efficient and lowcost way to optimize the design of surveys used in conservation planning. In data-sparse situations, this simple approach also offers a viable method for rapid assessment of potential local biodiversity, particularly where there is little local capacity in terms of skills or resources for mounting in-depth biodiversity surveys.
Keywords: Australia; Biodiversity; coral reef fish; ecological indicators; Great Barrier Reef; Landsat; mean information gain; multilevel mixed-effects model; photography; remote sensing; spectral signal.

NERP Marine Hub Factsheet 2012 - Paul Hedge (2012)
The Marine Biodiversity Hub is a national marine research collaboration supported through funding from the Australian Government’s National Environmental Research Program. The Hub aims to: Build strategic capacity and collaboration between marine research agencies; and Support the Department of Sustainability, Environment, Water, Population and Communities in accessing timely and relevant information to support evidence based management.   Download by clicking on the "Item" field below.  (Also see our 2010 Factsheet) Image:  Mullet and Yellowstripe Scad (Smooth-tailed Trevally).  Photo:  William White, CSIRO

NERP Marine Hub Roles and Responsibilities (2012)

Phylogeography of the Indo-West Pacific maskrays (Dasyatidae, Neotrygon): a complex example of chondrichthyan radiation in the Cenozoic - Puckridge, Melody; Last, Peter R.; William T White; Andreakis, Nikos (Ecology and Evolution, 2012)
Maskrays of the genus Neotrygon (Dasyatidae) have dispersed widely in the Indo-West Pacific being represented largely by an assemblage of narrow-ranging coastal endemics. Phylogenetic reconstruction methods reproduced nearly identical and statistically robust topologies supporting the monophyly of the genus Neotrygon within the family Dasyatidae, the genus Taeniura being consistently basal to Neotrygon, and Dasyatis being polyphyletic to the genera Taeniurops and Pteroplatytrygon. The Neotrygon kuhlii complex, once considered to be an assemblage of color variants of the same biological species, is the most derived and widely dispersed subgroup of the genus. Mitochondrial (COI, 16S) and nuclear (RAG1) phylogenies used in synergy with molecular dating identified paleoclimatic fluctuations responsible for periods of vicariance and dispersal promoting population fragmentation and speciation in Neotrygon. Signatures of population differentiation exist in N. ningalooensis and N. annotata, yet a largescale geological event, such as the collision between the Australian and Eurasian Plates, coupled with subsequent sea-level falls, appears to have separated a once homogeneous population of the ancestral form of N. kuhlii into southern Indian Ocean and northern Pacific taxa some 4–16 million years ago. Repeated climatic oscillations, and the subsequent establishment of land and shallow sea connections within and between Australia and parts of the Indo-Malay Archipelago, have both promoted speciation and established zones of secondary contact within the Indian and Pacific Ocean basins.
Keywords: biodiversity hotspot; Cryptic species; marine speciation; maskray; Neotrygon; phylogeography.

Predicted benthic disturbance regimes on the Australian continental shelf: a modelling approach - Harris, Peter T.; Hughes, Michael G. (Marine Ecology Progress Series, 2012)
Models of seabed sediment mobilisation by waves and currents over Australia’s continental shelf environment are used to examine whether disturbance regimes exist in the context of the intermediate disturbance hypothesis (IDH), whereby maximum biodiversity co - incides with moderate levels of disturbance. Our study shows that it is feasible to model the frequency and magnitude of seabed disturbance in relation to the dominant energy source (wave-, tide- or cyclone-dominated shelf). Areas are mapped where the recurrence interval of disturbance events is comparable to the rate of ecological succession, which meets criteria defined for a disturbance regime. We focus our attention on high-energy, patch-clearing events defined as exceeding the Shields (bed shear stress) parameter value of 0.25. Using known rates of ecological succession for different substrate types (gravel, sand and mud), predictions are made of the spatial distribution of a dimensionless ecological disturbance (ED) index, given as: ED = FA(ES/RI), where ES is the ecological succession rate for different substrates, RI is the recurrence interval of disturbance events and FA is the fraction of the frame of reference (surface area) disturbed. Maps for the Australian continental shelf show small patches of seafloor where ED indicates the potential existence of disturbance regimes (and inferred greater biodiversity) distributed around the continent, on both the inner and outer shelf. The patterns are different for wave-dominated (patches on the outer shelf trending parallel to the coast), tide-dominated (patches crossing the middle-shelf trending normal to the coast) and cyclone-dominated (large oval-shaped patches crossing all depths) shelf environments. Only a small portion of the shelf (~10%) is characterised by a disturbance regime as defined here.
Keywords: Continental shelf; Disturbance regime; Ecological succession; Intermediate disturbance hypothesis; Physical processes

Predicting coral reef biodiversity patterns for conservation - Camille Mellin (2012)
Presentation to Distinguished Guest Seminar Series, University of Wollongong, September 2012 Predicting coral reef biodiversity patterns for conservation Camille Mellin Australian Institute of Marine Science, PMB No3, Townsville 4810 QLD Environment Institute, University of Adelaide, School of Earth & Environmental Sciences, Adelaide 5005 SA Coral reefs are among the most diverse ecosystems but also the most vulnerable to direct and indirect anthropogenic pressures associated with global change. This underpins the need for streamlined and cost-effective conservation strategies to maximize the persistence of coral reef biodiversity. I will explore the potential for using environmental and geographical variables to predict reef fish diversity and show how remotely-sensed and benthic habitat images can provide good proxies for fish diversity and, in turn, a cost-effective means of informing marine conservation. I will then demonstrate how the temporal variance of fish abundances (a proxy for extinction risk) varies spatially and increases on small and isolated reefs, highlighting the short-comings of species distribution models that do not consider species interactions, dispersal and meta-population dynamics. Using a focused study of abalone on south Australian temperate reefs, I will show how accounting for these processes using coupled niche-population models can help achieve more realistic predictions of a species’ range and population size under climate change, underlying the need for more sophisticated and integrated approaches to the prediction of coral reef biodiversity patterns in the future.

Predicting the distribution of commercially important invertebrate stocks under future climate - Russell, Bayden D.; Connell, Sean D.; Camille Mellin; Brook, Barry W.; Burnell, Owen W.; Damien A. Fordham (PLoS ONE, 2012)
The future management of commercially exploited species is challenging because techniques used to predict the future distribution of stocks under climate change are currently inadequate. We projected the future distribution and abundance of two commercially harvested abalone species (blacklip abalone, Haliotis rubra and greenlip abalone, H. laevigata) inhabiting coastal South Australia, using multiple species distribution models (SDM) and for decadal time slices through to 2100. Projections are based on two contrasting global greenhouse gas emissions scenarios. The SDMs identified August (winter) Sea Surface Temperature (SST) as the best descriptor of abundance and forecast that warming of winter temperatures under both scenarios may be beneficial to both species by allowing increased abundance and expansion into previously uninhabited coasts. This range expansion is unlikely to be realised, however, as projected warming of March SST is projected to exceed temperatures which cause up to 10-fold increases in juvenile mortality. By linking fine-resolution forecasts of sea surface temperature under different climate change scenarios to SDMs and physiological experiments, we provide a practical first approximation of the potential impact of climate-induced change on two species of marine invertebrates in the same fishery.

Predictive modelling of seabed sediment parameters using multibeam acoustic data: a case study on the Carnarvon Shelf, Western Australia. In Lees, B.G. & Laffan, S.W (eds), - Z Huang; Scott L Nichol; Justy P W Siwabessy; Daniell, James; Brendan P Brooke (International Journal of Geographical Information Science, 2012)
Seabed sediment textural parameters such as mud, sand and gravel content can be useful surrogates for predicting patterns of benthic biodiversity. Multibeam sonar mapping can provide near-complete spatial coverage of high-resolution bathymetry and backscatter data that are useful in predicting sediment parameters. Multibeam acoustic data collected across a ∼1000 km2 area of the Carnarvon Shelf, Western Australia, were used in a predictive modelling approach to map eight seabed sediment parameters. Four machine learning models were used for the predictive modelling: boosted decision tree, random forest decision tree, support vector machine and generalised regression neural network. The results indicate overall satisfactory statistical performance, especially for %Mud, %Sand, Sorting, Skewness and Mean Grain Size. The study also demonstrates that predictive modelling using the combination of machine learning models has provided the ability to generate prediction uncertainty maps. However, the single models were shown to have overall better prediction performance than the combined models. Another important finding was that choosing an appropriate set of explanatory variables, through a manual feature selection process, was a critical step for optimising model performance. In addition, machine learning models were able to identify important explanatory variables, which are useful in identifying underlying environmental processes and checking predictions against the existing knowledge of the study area. The sediment prediction maps obtained in this study provide reliable coverage of key physical variables that will be incorporated into the analysis of covariance of physical and biological data for this area.
Keywords: multibeam acoustic; predictive modelling; seabed sediment

On seabed disturbance, marine ecological succession and applications for environmental management: a physical sedimentological perspective. In: Li, M., Sherwood, C., Hill, P. (Eds.), Sediments, Morphology and Sedimentary Processes on Continental Shelves - Harris, Peter T. (Sediments, Morphology and Sedimentary Processes on Continental Shelves, Advances in Technologies, Research and Applications, 2012)
Physical sedimentological processes such as the mobilization and transport of shelf sediments during extreme storm events give rise to disturbances that characterize many shelf ecosystems. Connell’s (1978) intermediate disturbance hypothesis predicts that biodiversity is controlled by the frequency of disturbance events, their spatial extent and the amount of time required for ecological succession. A review of available literature suggests that periods of ecological succession in shelf environments range from 1 to over 10 years. Physical sedimentological processes operating on continental shelves having this same return frequency include synoptic storms, eddies shed from intruding ocean currents and extreme storm events (cyclones, typhoons and hurricanes). Research by physical sedimentologists has shown that the results of such storms may include bed stresses that cause widespread erosion, deposition of storm beds over 1 m in thickness and destruction of seagrass beds as well as bioherms such as coral reefs. Published models of extreme storms indicate their influence may extend to over 100km from the pressure-centre of the atmospheric depression. Modelling studies carried out by Hemer (2006) to characterize the Australian continental shelf in terms of bed stresses due to tides, waves and ocean currents from an 8-year time series may represent temperate synoptic storms in southern Australia but the time series is probably too short to represent tropical cyclones in northern Australia. Information such as this is essential to marine managers charged with the design of marine protected areas (MPAs) and other conservation measures aimed at protecting and preserving biodiversity in the oceans. Further studies are needed to compare model output and measures of shelf disturbances to the spatial and temporal variations associated with shelf ecological successions.
Keywords: continental shelf.; Ecological succession; environmental management; Seabed disturbance; storms

Seafloor Geomorphology as Benthic Habitat - Harris, Peter T.; Baker, Elaine K (GeoHAB Atlas of Seafloor Geomorphic Features and Benthic Habitats, 2012)
The conservation of marine benthic biodiversity is a recognised goal of a number of national and international programs such as the United Nations Convention on Biodiversity (CBD). In order to attain this goal, information is needed about the distribution of life in the ocean so that spatial conservation measures such as marine protected areas (MPAs) can be designed to maximise protection within boundaries of acceptable dimensions. Ideally, a map would be produced that showed the distribution of benthic biodiversity to enable the efficient design of MPAs. The dilemma is that such maps do not exist for most areas and it is not possible at present to predict the spatial distribution of all marine life using the sparse biological information currently available. Knowledge of the geomorphology and biogeography of the seafloor has improved markedly over the past 10 years. Using multibeam sonar, the benthic ecology of submarine features such as fjords, sand banks, coral reefs, seamounts, canyons, mud volcanoes and spreading ridges has been revealed in unprecedented detail. This book provides a synthesis of seabed geomorphology and benthic habitats based on the most recent, up-to-date information. Introductory chapters explain the drivers that underpin the need for benthic habitat maps, including threats to ocean health, the habitat mapping approach based on principles of biogeography and benthic ecology and seabed (geomorphic) classification schemes. Case studies from around the world are then presented. They represent a range of seabed features where detailed bathymetric maps have been combined with seabed video and sampling to yield an integrated picture of the benthic communities that are associated with different types of benthic habitat. The final chapter examines critical knowledge gaps and future directions for benthic habitat mapping research.

Seafloor geomorphology – coast, shelf and abyss - Harris, Peter T. (Elsevier, 2012)

Southern Ocean octocorals and Norwegian taxonomic riddles - Kirrily Moore (5th International Deepsea Coral Symposium 2012, 1-6 April 2012, 2012)
Poster was prepared for the 5th International Deepsea Coral Symposium, 1 - 6 April 2012 Deepwater octocorals in the Southern Ocean are poorly known even though they represent one of the most diverse and abundant coral groups in these regions. Multiple surveys of seamounts around Australia by CSIRO Marine and Atmospheric Research (CMAR) collected a great unrecognised diversity of octocorals, increasing the number of species recorded from deep Australian waters from 6 to >150 (CMAR unpub. data). Due to the inadequate and outdated nature of the taxonomic literature from the area it remains impossible to confidently identify them, however a significant number have been shown to be undescribed taxa. Trawling, long-line fishing and climate change all pose significant threats to these vulnerable coral communities and there is an urgent need to increase understanding of the diversity, extent and connectivity of the populations.

Submerged banks in the Great Barrier Reef, Australia, greatly increase available coral reef habitat - Harris, Peter T.; Tom Bridge; R J Beaman; Webster, J. M.; Scott L Nichol; Brendan P Brooke (ICES Journal of Marine Science, 2012)
Anthropogenic global ocean warming is predicted to cause bleaching of many near-sea-surface (NSS) coral reefs, placing increased importance on deeper reef habitats to maintain coral reef biodiversity and ecosystem function. However, the location and spatial extent of many deep reef habitats is poorly known. The question arises: how common are deep reef habitats in comparison with NSS reefs? We used a dataset from the Great Barrier Reef (GBR) to show that only about 39% of available seabed on submerged banks is capped by NSS coral reefs (16 110 km2); the other 61% of bank area (25 600 km2) is submerged at a mean depth of around 27 m and represents potential deep reef habitat that is spatially distributed along the GBR continental shelf in the same latitudinal distribution as NSS reefs. Out of 25 600 km2 of submerged bank area, predictive habitat modelling indicates that more than half (around 14 000 km2) is suitable habitat for coral communities.
Keywords: benthic habitats; Biodiversity; Great Barrier Reef; mesophotic; refugia; submerged banks

Surrogacy In: Seafloor Geomorphology as Benthic Habitat - Harris, Peter T. (Seafloor geomorphology as benthic habitat: GeoHAB atlas of seafloor geomorphic features and benthic habitats, 2012)

Sydney Botanic Gardens map (2012)

Uncertainty in spatially predicted covariates: is it ignorable? - Scott D Foster; Shimadzu, Hideyasu; Ross Darnell (Journal of the Royal Statistical Society: Series C (Applied Statistics), 2012)
In ecology, a common form of statistical analysis relates a biological variable to variables that delineate the physical environment, typically by fitting a regression model or one of its extensions. Unfortunately, the biological data and the physical data are frequently obtained from separate sources of data. In such cases there is no guarantee that the biological and physical data are co-located and the regression model cannot be used. A common and pragmatic solution is to predict the physical variables at the locations of the biological variables and then to use the predictions as if they were observations. We show that this procedure can cause potentially misleading inferences and we use generalized linear models as an example. We propose a Berkson error model which overcomes the limitations. The differences between using predicted covariates and the Berkson error model are illustrated by using data from the marine environment, and a simulation study based on these data.
Keywords: Berkson error; Ecological modelling; Geostatistics; Measurement error

Why map benthic habitats - Harris, Peter T.; Baker, Elaine K (Seafloor geomorphology as benthic habitat: GeoHAB atlas of seafloor geomorphic features and benthic habitats, 2012)

Analysis of relationships between seabed species/assemblages and their physical environment using Random Forests statistical methods - C Roland Pitcher (ICES CM 2011/G:06, 2011)
Conference Title: Exploring patterns of compositional change along environmental gradients, and mapping expected patterns of biodiversity composition at regional scale. Abstract Environmental variables are increasingly used as indirect surrogates for mapping patterns of biodiversity because species survey data are scant, especially in the marine realm. This Census of Marine Life cross‐program synthesis quantified the shapes and magnitude of multiple species responses to >30 environmental gradients, and the extent to which these variables were useful as predictors for mapping patterns or biodiversity composition.
Keywords: beta diversity prediction and mapping; Great Barrier Reef; Gulf of Maine; Gulf of Mexico

Biodiversity Offsets: A Cost-Effective Interim Solution to Seabird Bycatch in Fisheries? - Pascoe, Sean; Chris Wilcox; Donlan, C Josh (PloS ONE, 2011)
The concept of biodiversity offsets is well established as an approach to environmental management. The concept has been suggested for environmental management in fisheries, particularly in relation to the substantial numbers of non-target species—seabirds in particular—caught and killed as incidental bycatch during fishing activities. Substantial areas of fisheries are being closed to protect these species at great cost to the fishing industry. However, other actions may be taken to offset the impact of fishing on these populations at lower cost to the fishing industry. This idea, however, has attracted severe criticism largely as it does not address the underlying externality problems created by the fishing sector, namely seabird fishing mortality. In this paper, we re-examine the potential role of compensatory mitigation as a fisheries management tool, although from the perspective of being an interim management measure while more long-lasting solutions to the problem are found. We re-model an example previously examined by both proponents and opponents of the approach, namely the cost effectiveness of rodent control relative to fishery area closures for the conservation of a seabird population adversely affected by an Australian tuna fishery. We find that, in the example being examined, invasive rodent eradication is at least 10 times more cost effective than area closures. We conclude that, while this does not solve the actual bycatch problem, it may provide breathing space for both the seabird species and the industry to find longer term means of reducing bycatch.

Biogeographic patterns in the Australian chondrichthyan fauna - Last, Peter R.; William T White (Journal of Fish Biology, 2011)
bathomes; biogeography; Indo-Pacific; provinces; rays; sharks The major biogeographic structure and affinities of the Australian chondrichthyan fauna were investigated at both interregional and intraregional scales and comparisons made with adjacent bioregions. Faunal lists were compiled from six geographical regions with species from these regions assigned to distributional classes and broad habitat categories. Australian species were further classified on provincial and bathomic structure following bioregionalization outputs from regional marine planning. About 40% of the world's chondrichthyan fauna occurs in Indo-Australasia (482 species) of which 323 species are found in Australian seas. The tropical Australian component, of which c. 46% of taxa are regional endemics, is most similar to faunas of Indonesia, New Guinea and New Caledonia. The temperate Australian component is most similar to New Zealand and Antarctica with about half of its species endemic. Highest levels of Australian endemism exist in bathomes of the outer continental shelf and upper slope. A relatively high proportion of regional endemism (57% of species) on the slope in the poorly surveyed but species-rich Solanderian unit is probably due to high levels of large-scale habitat complexity in the Coral Sea. The richness of demersal assemblages on the continental shelf and slope appears to be largely related to the spatial complexity of the region and the level of exploration. Much lower diversity off Antarctica is consistent with the pattern in teleosts. The complex chondrichthyan fauna of Australia is confirmed as being amongst the richest of the mega-diverse Indo-West Pacific Ocean. Species-level compositions of regional faunas across Indo-Australasia differ markedly because of moderate to high levels of intraregional speciation. Faunal assemblages in Australian marine provinces and bathomes differ from each other, supporting a broader pattern for fishes that underpins a marine planning framework for the region.

Biogeographical structure and affinities of the marine demersal ichthyofauna of Australia - Last, Peter R.; William T White; Gledhill, Daniel C.; John J Pogonoski; Lyne, Vince; Nicholas J. Bax (Journal of Biogeography, 2011)
Aim To investigate the biogeographical structure and affinities of the Australian marine demersal ichthyofauna at the scale of provinces and bathomes for the purposes of regional marine planning. Location Australia. Methods Patterns of distribution in the Australian fish fauna, at both intra‐regional and global scales, were examined using a science‐based, management framework dividing Australia’s marine biodiversity into 16 province‐level biogeographical units. Occurrences of 3734 species in eight depth‐stratified bathomes (from the coast to the mid‐continental slope) within each province were analysed to determine the structure and local affinities of their assemblages and their association with faunas of nearby regions and oceans basins. Results Strong geographic and depth‐related structure was evident. Fish assemblages in each province, and in each bathome of each province, were distinct, with the shelf‐break bathome more similar to the adjacent continental shelf bathome than to the upper slope bathome. Data based only on endemic species performed well as a surrogate of the entire dataset, yielding comparable patterns of similarity between provinces and bathomes. Tropical and temperate elements were better discriminated than elements of the Pacific and Indian oceans, with the central western province more similar to the tropical provinces (including those in the east), and the eastern province closer to southern temperate provinces. The fauna shares the closest regional affinities with those of the adjacent south‐west Pacific, western Pacific Rim, and elements of wide‐ranging Indo‐Pacific components. Elements unique to the Pacific and Indian oceans are poorly represented. Main conclusions The complex nature of Australia’s marine ichthyofauna is confirmed. A hierarchy of provinces and bathomes, used to ensure that Australia’s developing marine reserve network is both representative and comprehensive, is equally robust when based on all known Australian fish species or on only those species endemic to this continent. Latitude and depth are more important than oceanic influences on the composition of this fauna at these scales. Wiley full text version via Shareable link https://rdcu.be/b1c55
Keywords: Australia; bathomes; Biogeography; conservation biogeography; endemism; faunal provinces; Indo-Pacific; marine fishes; regional marine planning

Biogeography of the Lord Howe Rise region, Tasman Sea (2011)

Biogeography of the Lord Howe Rise region, Tasman Sea - Rachel Przeslawski; Williams, Alan; Scott L Nichol; Hughes, Michael G.; Tara J Anderson; Althaus, Franziska (Deep Sea Research Part II: Topical Studies in Oceanography, 2011)
The two principal aims of this study were to synthesise physical and biological information to characterise the Lord Howe Rise (LHR) region and to use recent survey collections of benthic invertebrates (mostly large benthic epifauna) to describe its biogeography at regional and sub-regional scales. The LHR region is large (1.95 million km2), spans tropical and cool temperate latitudes (18.4 to 40.3°S), and is influenced by several ocean currents, notably the East Australian Current and the Tasman Front. Our analyses revealed that biological patterns were related to two groups of geomorphic morphotypes found in this topographically complex region: subdued bathymetric features (expansive soft sediment basins and plateaus) and raised bathymetric features (scattered seamounts, guyots, knolls, and pinnacles). Raised bathymetric features in the LHR region were more likely to support richer and more abundant epifaunal assemblages dominated by suspension feeding invertebrates on hard substrata compared to subdued features which were dominated by infauna and detritivores in soft sediments. However, this trend does not apply to all raised bathymetric features (e.g., Gifford Guyot), with variations in depth, elevation, latitude, and particularly substrata affected the composition of biological assemblages. In addition, some demersal fishes, ophiuroids, and other benthic invertebrates showed distinct north-south delineations that coincide with the influence of the Tasman Front and thermal gradients. While the lack of spatially- and temporally- replicated data in the region limits our interpretation of survey data, paleo-environmental processes and examples from other regions provide some indication of how dispersal influences migration, speciation, and endemism in the LHR region. Although our current knowledge is limited, it is hoped that this review will help inform future studies in the area, as equitable examination of biological, geological, and oceanographic characteristics will facilitate future assessments of LHR biogeography and permit the inclusion of this region in biogeographic studies with a national or global context.
Keywords: Lord Howe Plateau; Southwest Pacific; Endemism; Oceanography; Geology; Geomorphology

CERF Marine Biodiversity Hub Final Report 2007-2010 - Nicholas J. Bax; Brendan P Brooke; Daniel C Gledhill; C Roland Pitcher; Chris Wilcox (CERF Marine Biodiversity Hub, 2011)
Published: March 2011 Media release

CERF Report on Transition and Extension Program - Nicholas J. Bax (CERF Marine Biodiversity Hub, 2011)
The Marine Biodiversity Hub (MBH) applied for transition funding to capitalise on investments made as part of the initial Hub funding and on additional work completed by Hub partners during that time. Products from the transition period include increasing the number of phyla available for national biodiversity mapping from one to four, providing uncertainty estimates for national biodiversity maps used in marine bioregional planning, extending statistical methods to apply to additional questions identified by the Department of Sustainability, Environment, Water, Population and Communities, SEWPaC (previously Department of Environment, Water, Heritage and the Arts, DEWHA) and completing a gap analysis of biological and physical data for national biodiversity mapping. These new data and methods will be available to support the implementation of marine regional plans (especially in the Northwest), will test the existing predictive national biodiversity maps, and will provide the scientific basis for a possible IMCRA 5.0. In addition the Hub is proposing an active period of direct engagement with the Department (Marine, ERIN and Heritage), providing expert advice in response to specific Department requests, and bringing together workshops of expert scientists and natural resource managers to address specific questions identified by the Department (MPA monitoring, use of market-based instruments in conservation planning, additional support for managing threatened and endangered species, identification of areas of interest to Heritage listing). Ongoing communication with the Department and other stakeholders will be maximised through the use of an established knowledge broker and the Hub newsletter. ******************************************************************** HARVEST PROGRAM - Development of further products from existing research Taking advantage of existing products and knowledge generated by the Hub to improve uptake in support of improved management Further development of market based instruments (MBIs) to support structural readjustment options Fishers’ adaptation ******************************************************************** EXTENSION PROGRAM – Research aligned to future CERF program directions Extending national data holdings in preparation for future marine biodiversity research to support implementation of marine bioregional plans Extend statistical methods developed for marine biodiversity mapping to support further application to meet Department of Sustainability, Environment, Water, Population and Communities needs

Composition and distribution of deep-sea benthic invertebrate megafauna on the Lord Howe Rise and Norfolk Ridge, southwest Pacific Ocean - Williams, Alan; Althaus, Franziska; Malcolm R Clark; Karen Gowlett-Holmes (Deep Sea Research Part II: Topical Studies in Oceanography, 2011)
The deep-sea biodiversity of the Lord Howe Rise and Norfolk Ridge – two complex submarine features that extend in a north-south direction either side of a deep basin within the northern Tasman Sea and southern Coral Sea – was sampled in 2003 for the first time on a broad regional scale. The total of 1313 megabenthic invertebrate species from 17 higher order taxa collected between 100 and 1800 m depths showed faunal diversity and novelty was high. Only 256 of these species were named, and 10% of these were described as a result of this survey; 78% are un-named and believed to be mostly new species. Of the 1253 species included in quantitative analyses, most appeared to be rare – 85% were only found once. This indicates intra-regional endemism may be high, but undersampling is also likely. Species accumulation curves confirm that many additional species remain to be collected. There was high regional-scale spatial heterogeneity in species distribution patterns which appeared to be influenced by hydrographic patterns and feature-scale topography, and to a lesser extent by seabed type. Depth and oxygen concentration (correlated with depth) had most influence on distribution patterns of fauna, with assemblages identified from three depth-zones: 100–400 m (deep continental shelf and shelf edge), 400–700 m (upper continental slope) and >700 m (mid-continental slope). In the shallowest depth zone, there were north-south (latitudinal) patterns in invertebrate assemblages that appeared to be influenced by water mass distribution. Species overlap was higher in the south than the north, probably due to the Tasman Front forming a hydrographic connection between the southern parts of the Rise and the Ridge at shallower depths. At depths >700 m, the absence of a latitudinal pattern in assemblage structure was attributed to the continuity of Antarctic Intermediate Water in the study area. Differentiation of two assemblages in sled samples from the >700 m depth zone, as well as some patterns of diversity of large sessile fauna between sub-regions within the study area, suggested a relationship with bottom type but this was not fully analysed. While providing a major increase in scientific knowledge of marine biodiversity in deep waters of the Coral and Tasman Seas, these results also highlighted the paucity of biogeographical knowledge that exists for the area. Some science advances needed to inform national and international conservation plans currently under development are identified. They include taxonomic standardisation at a regional-scale (Australia, New Zealand and New Caledonia) for informative higher level taxa, and some additional surveys of selected areas and seabed features, including off northeastern Australia.
Keywords: Biodiversity conservation; Biogeography; Coral Sea; NORFANZ voyage; Tasman Sea; Taxonomy

Deep-sea bio-physical variables as surrogates for biological assemblages, an example from the Lord Howe Rise - Tara J Anderson; Scott L Nichol; Syms, Craig; Rachel Przeslawski; Harris, Peter T. (Deep Sea Research Part II: Topical Studies in Oceanography, 2011)
Little is known about diversity patterns of biological assemblages in deep-sea environments, primarily because sampling deep-sea biota over vast areas is time consuming, difficult, and costly. In contrast, physical mapping capabilities are increasing rapidly, and are becoming more cost-effective. Consequently, the growing need to manage and conserve marine resources, particularly deep-sea areas that are sensitive to anthropogenic disturbance and change, is leading the promotion of physical data as surrogates to predict biological assemblages. However, few studies have directly examined the predictive ability of these surrogates. The physical environment and biological assemblages were surveyed for two adjacent areas – the western flank of Lord Howe Rise (LHR) and the Gifford Guyot - spanning combined water depths of 250-2200 m depth on the northern part of the LHR, in the Coral Sea. Multibeam acoustic surveys were used to generate large-scale geomorphic classification maps that were superimposed over the study area. Forty towed-video stations were deployed across the area capturing 32 h of seabed video, 6229 still photographs, that generated 3413 seabed characterisations of physical and biological variables. In addition, sediment and biological samples were collected from 36 stations across the area. The northern Lord Howe Rise was characterised by diverse but sparsely distributed faunas for both the vast soft-sediment environments as well as the discrete rock outcrops. Substratum type and depth were the main variables correlated with benthic assemblage composition. Soft-sediments were characterised by low to moderate levels of bioturbation, while rocky outcrops supported diverse but sparse assemblages of suspension feeding invertebrates, such as cold-water corals and sponges which in turn supported epifauna, dominated by ophiuroids and crinoids. While deep environments of the LHR flank and lower slopes of the Gifford Guyot were characterised by bioturbation with high occurrences of trails, burrows, and mounds, evidence for bioturbation was significantly less on the upper sections of Gifford Guyot, with mostly trails on the more sediment starved environments. The seamount summit also supported a variety of taxa, such as benthic ctenophores and rock-associated fishes that were not recorded in the deeper basin habitats. Physical characteristics of the seabed, particularly geomorphology, were good predictors of biological assemblage composition and percent cover of key taxa. Of the nine geomorphic classes assessed in this study, six predicted different physical habitats that supported distinct biological assemblages. However, other classes that were defined by spatial features (e.g., valleys, seamount dunes) where surficial physical variables were not unique, provided little predictive power of biological assemblages, but rather had characteristics that were shared with adjacent/surrounding geomorphic classes. Given the growing need to use surrogates in the management and conservation of marine environments, these results are promising. However, our findings suggest that there is a pressing need for careful testing and validation of surrogates, such as geomorphic classes, before classification schemes can be deemed effective and employed as a management tool to predict seabed habitats and their biological assemblages.
Keywords: Biodiversity; Deep sea; Geomorphology; Habitat mapping; Surrogacy

Demographic rates for seabirds and marine turtles global - Lavers, Jennifer L. (CSIRO, 2011)

Distribution, abundance and trail characteristics of acorn worms at Australian continental margins - Tara J Anderson; Rachel Przeslawski; Maggie Tran (Deep Sea Research Part II: Topical Studies in Oceanography, 2011)
Acorn worms (Enteropneusta), which were previously thought to be a missing link in understanding the evolution of chordates, are an unusual and potentially important component of many deep-sea benthic environments, particularly for nutrient cycling. Very little is known about their distribution, abundance, or behaviour in deep-sea environments around the world, and almost nothing is known about their distribution within Australian waters. In this study, we take advantage of two large-scale deep-sea mapping surveys along the eastern (northern Lord Howe Rise) and western continental margins of Australia to quantify the distribution, abundance and trail-forming behaviour of this highly unusual taxon. This is the first study to quantify the abundance and trail behaviour of acorn worms within Australian waters and provides the first evidence of strong depth-related distributions. Acorn worm densities and trail activity were concentrated between transect-averaged depths of 1600 and 3000 m in both eastern and western continental margins. The shallow limit of their depth distribution was 1600 m. The deeper limit was less well-defined, as individuals were found in small numbers below 3000 down to 4225 m. This distributional pattern may reflect a preference for these depths, possibly due to higher availability of nutrients, rather than a physiological constraint to greater depths. Sediment characteristics alone were poor predictors of acorn worm densities and trail activity. High densities of acorn worms and trails were associated with sandy-mud sediments, but similar sediment characteristics in either shallower or deeper areas did not support similar densities of acorn worms or trails. Trail shapes varied between eastern and western margins, with proportionally more meandering trails recorded in the east, while spiral and meandering trails were both common in the west. Trail shape varied by depth, with spiral-shaped trails dominant in areas of high acorn worm densities (2000–3000 m water depth) while meandering trails were common over a much broader depth range and were the only trails recorded in deep environments >3000 m. While species-specific patterns may in part explain these differences, evidence suggests that nutrient availability is also likely to be an important driving factor, supporting the hypothesis put forward by Smith et al. (2005) that acorn worms meander when searching for food and form a spiral when feeding in a nutrient-rich area.
Keywords: Acorn worms; Enteropneusta; depth range; trail behaviour; sediment characteristics; deep-sea

Effectiveness of biological surrogates for predicting patterns of marine biodiversity: a global meta-analysis - Camille Mellin; Delean, Steve; M Julian Caley; Graham J. Edgar; Mark Meekan; C Roland Pitcher; Rachel Przeslawski; Williams, Alan; Bradshaw, Corey (PLoS ONE, 2011)
The use of biological surrogates as proxies for biodiversity patterns is gaining popularity, particularly in marine systems where field surveys can be expensive and species richness high. Yet, uncertainty regarding their applicability remains because of inconsistency of definitions, a lack of standard methods for estimating effectiveness, and variable spatial scales considered. We present a Bayesian meta-analysis of the effectiveness of biological surrogates in marine ecosystems. Surrogate effectiveness was defined both as the proportion of surrogacy tests where predictions based on surrogates were better than random (i.e., low probability of making a Type I error; P) and as the predictability of targets using surrogates (R2). A total of 264 published surrogacy tests combined with prior probabilities elicited from eight international experts demonstrated that the habitat, spatial scale, type of surrogate and statistical method used all influenced surrogate effectiveness, at least according to either P or R2. The type of surrogate used (higher-taxa, cross-taxa or subset taxa) was the best predictor of P, with the higher-taxa surrogates outperforming all others. The marine habitat was the best predictor of R2, with particularly low predictability in tropical reefs. Surrogate effectiveness was greatest for higher-taxa surrogates at a <10-km spatial scale, in low-complexity marine habitats such as soft bottoms, and using multivariate-based methods. Comparisons with terrestrial studies in terms of the methods used to study surrogates revealed that marine applications still ignore some problems with several widely used statistical approaches to surrogacy. Our study provides a benchmark for the reliable use of biological surrogates in marine ecosystems, and highlights directions for future development of biological surrogates in predicting biodiversity.

A geochemical characterization of deep-sea floor sediments of the northern Lord Howe Rise - Lynda Radke; Heap, Andrew D.; Douglas, G.; Scott L Nichol; Trafford, J.; Jin Li; Rachel Przeslawski (Deep Sea Research Part II: Topical Studies in Oceanography, 2011)
This study presents new information on the regional geochemical characteristics of deep-sea floor sediments (1300–2423 m water depth) on the Lord Howe Rise (deep–sea plateau) and Gifford Guyot (seamount/tablemount), remote areas off eastern Australia. The aim was to provide a coherent synthesis for a suite of geochemical data that can be used to make habitat inferences and to develop surrogates of biodiversity. Sediment characteristics analysed were mineralogy, organic carbon and nitrogen concentrations and isotopic compositions, and concentrations of major and trace elements. We also measured parameters that convey information about the reactivity of organic matter and on the bio-availability of bioactive trace elements (e.g., chlorin indices and acid-extractable elements). Surface sediments from the region were calcareous oozes that were carbon-lean (0.26±0.1%) and had moderate to high chlorin indices (0.62 – 0.97). With the exception of arsenic, inorganic element concentrations were generally low by global standards. Statistical and geochemical analyses identified two major dimensions of variation in the elemental composition: (i) the degree of mixing between the detrital sediment and carbonate end-members; and (ii) the concentrations of bio-available bioactive elements. The causes of compositional variation are discussed, and include: (i) a strong latitudinal gradient in detrital atmospheric dust deposition; (ii) size fractionation and cation exchange of dust components during transit (for non-carbonates); (iii) water depth controls on carbonate dissolution; and (iv) topographic/hydrodynamic focussing of reactive organic matter. Reactive organic matter indicators were not well correlated with water depth, and did not reflect the regional ocean productivity pattern. Basalt source signatures were not evident in the mineralogy or geochemistry of sediments overlying the seamount or in the vicinity of volcanoes.
Keywords: Chlorin index; Deep-sea; Geochemistry; Major and trace elements; Marginal plateau; Organic carbon and nitrogen concentrations and isotopes; Seafloor sediment; seamount

Geomorphic features and infauna diversity of a subtropical mid-ocean carbonate shelf: Lord Howe Island, Southwest Pacific Ocean. In: Harris, P.T and Baker, E. (Eds) - Brendan P Brooke; Matthew McArthur; Woodroffe, Colin D.; Linklater, Michelle; Scott L Nichol; Tara J Anderson; Mleczko, Richard; S Sagar (GeoHAB Atlas of Seafloor Geomorphic Features and Benthic Habitats, 2011)
The conservation of marine benthic biodiversity is a recognised goal of a number of national and international programs such as the United Nations Convention on Biodiversity (CBD). In order to attain this goal, information is needed about the distribution of life in the ocean so that spatial conservation measures such as marine protected areas (MPAs) can be designed to maximise protection within boundaries of acceptable dimensions. Ideally, a map would be produced that showed the distribution of benthic biodiversity to enable the efficient design of MPAs. The dilemma is that such maps do not exist for most areas and it is not possible at present to predict the spatial distribution of all marine life using the sparse biological information currently available. Knowledge of the geomorphology and biogeography of the seafloor has improved markedly over the past 10 years. Using multibeam sonar, the benthic ecology of submarine features such as fjords, sand banks, coral reefs, seamounts, canyons, mud volcanoes and spreading ridges has been revealed in unprecedented detail. This book provides a synthesis of seabed geomorphology and benthic habitats based on the most recent, up-to-date information. Introductory chapters explain the drivers that underpin the need for benthic habitat maps, including threats to ocean health, the habitat mapping approach based on principles of biogeography and benthic ecology and seabed (geomorphic) classification schemes. Case studies from around the world are then presented. They represent a range of seabed features where detailed bathymetric maps have been combined with seabed video and sampling to yield an integrated picture of the benthic communities that are associated with different types of benthic habitat. The final chapter examines critical knowledge gaps and future directions for benthic habitat mapping research.

The geomorphology of the flanks of the Lord Howe Island volcano, Tasman Sea, Australia. - Kennedy, David M.; Brendan P Brooke; Woodroffe, Colin D.; Jones, Brian G.; Waikari, C.; Scott L Nichol (Deep Sea Research Part II: Topical Studies in Oceanography, 2011)
The flanks of mid-ocean volcanoes are inherently unstable features especially in the constructional phase of development when the volcano is active. Lateral and vertical stresses are placed on the volcanic edifice as it builds, with the flanks continuing to be unstable up to at least 1 Ma after volcanism has ceased. The flanks of the Lord Howe Island volcano record this period of greatest instability and a subsequent period in which marine and subaerial erosion have dominated its geomorphic evolution. Lord Howe Island lies in the Tasman Sea of the Southern Pacific region and is the subaerial remnant of a Miocene mid-ocean volcano. The island has only recently entered reef building seas and therefore has been subject to marine erosive processes over the past 5–6 Ma. The island is unique as it sits on the stable drowned continental crust of the Lord Howe Rise rather than oceanic crust like many other mid-plate basaltic islands. Multibeam sonar bathymetry data were collected to a depth of 3500 m where the island flanks grade into the surrounding planar sea floor. Several slump features are evident, the largest being over 130 km2 in area. These features are inferred to be old (late Tertiary) based on an extensive cover of marine sediment as indicated by low multibeam backscatter intensity and subdued topography. Most likely the slumps formed during the immediate post-eruptive stage of volcano evolution, before the bulk of the subaerial portion of the volcano was removed by marine erosion. Flank processes are now dominated by the deposition of carbonate sediment composed of mollusc and foraminiferal remains. Based on radiocarbon and stable isotope analyses of a sediment core (760 m depth) collected on a trough in the centre of the volcanic edifice, Quaternary sediment was likely deposited predominantly during glacial periods. The erosional morphology, sediment cover and tectonic stability of the region suggest that the flanks of the volcano are at present relatively stable.
Keywords: asman Sea; High Island; Isotope; Lord Howe Rise; Slump; Volcano

Global distribution of large submarine canyons: Geomorphic differences between active and passive continental margins - Harris, Peter T.; Whiteway, Tanya (Marine Geology, 2011)
The aim of this study is to assess the global occurrence of large submarine canyons to provide context and guidance for discussions regarding canyon occurrence, distribution, geological and oceanographic significance and conservation. Based on an analysis of the ETOPO1 data set, this study has compiled the first inventory of 5849 separate large submarine canyons in the world ocean. Active continental margins contain 15% more canyons (2586, equal to 44.2% of all canyons) than passive margins (2244, equal to 38.4%) and the canyons are steeper, shorter, more dendritic and more closely spaced on active than on passive continental margins. This study confirms observations of earlier workers that a relationship exists between canyon slope and canyon spacing (increased canyon slope correlates with closer canyon spacing). The greatest canyon spacing occurs in the Arctic and the Antarctic whereas canyons are more closely spaced in the Mediterranean than in other areas. River-associated, shelf-incising canyons are more numerous on active continental margins (n = 119) than on passive margins (n = 34). They are most common on the western margins of South and North America where they comprise 11.7% and 8.6% of canyons respectively, but are absent from the margins of Australia and Antarctica. Geographic areas having relatively high rates of sediment export to continental margins, from either glacial or fluvial sources operating over geologic timescales, have greater numbers of shelf-incising canyons than geographic areas having relatively low rates of sediment export to continental margins. This observation is consistent with the origins of some canyons being related to erosive turbidity flows derived from fluvial and shelf sediment sources. Other workers have shown that benthic ecosystems in shelf-incising canyons contain greater diversity and biomass than non-incising canyons, and that ecosystems located above 1500 m water depth are more vulnerable to destructive fishing practices (bottom trawling) and ocean acidification caused by anthropogenic climate change. The present study provides the means to assess the relative significance of canyons located in different geographic regions. On this basis, the importance of conservation for submarine canyon ecosystems is greater for Australia, islands and northeast Asia than for other regions.
Keywords: Active continental margin; Benthic ecology; Conservation; Geomorphology; Global; Passive continental margin; Submarine canyons

Habitats and benthos of an oceanic plateau, Lord Howe Rise, Australia. In: GeoHab Global Atlas - Harris, Peter T.; Scott L Nichol; Tara J Anderson; Heap, Andrew D. (2011)

Including biogeochemical factors and a temporal component in benthic habitat maps: influences on infaunal diversity in a temperate embayment - Lynda Radke; Z Huang; Rachel Przeslawski; Webster, Ian T.; Matthew McArthur; Tara J Anderson; Justy P W Siwabessy; Brendan P Brooke (Marine and Freshwater Research, 2011)
Mapping of benthic habitats seldom considers biogeochemical variables or changes across time.Weaimed to: (i) develop winter and summer benthic habitat maps for a sandy embayment; and (ii) compare the effectiveness of various maps for differentiating infauna. Patch types (internally homogeneous areas of seafloor) were constructed using combinations of abiotic parameters and are presented in sediment-based, biogeochemistry-based and combined sediment–biogeochemistry-based habitat maps. August and February surveys were undertaken in Jervis Bay, NSW, Australia, to collect samples for physical (% mud, sorting,%carbonate), biogeochemical (chlorophyll a, sulfur, sediment metabolism, bioavailable elements) and infaunal analyses. Boosted decision tree and cokriging models generated spatially continuous data layers. Habitat maps were made from classified layers using geographic information system (GIS) overlays and were interpreted from a biophysical-process perspective. Biogeochemistry and % mud varied spatially and temporally, even in visually homogeneous sediments. Species turnover across patch types was important for diversity; the utility of habitat maps for differentiating biological communities varied across months. Diversity patterns were broadly related to reactive carbon and redox, which varied temporally. Inclusion of biogeochemical factors and time in habitat maps provides a better framework for differentiating species and interpreting biodiversity patterns than once-off studies based solely on sedimentology or video-analysis.
Keywords: benthic habitat mapping; beta-diversity; macroalgal detritus; marine environmental management; polychaete mounds; surrogacy.

Inherited Geomorphology as a control of shallow marine habitats: Carnarvon Shelf, Western Australia - Scott L Nichol; Brendan P Brooke (2011)

Macrobenthic biodiversity data, Western Australian continental margin - Blazewicz, M.; Greaves, E.; Anna W McCallum; Syme, A.; Taylor, Joanne; Gary C. B. Poore; Walker-Smith, G.; Wilson, R.S. (Museum Victoria, 2011)
This product makes available specimen records from four Voyages of Discovery on the Western Australian continental margin, based on material now held at Museum Victoria, Melbourne. These are the raw data available to and used by various predictive modelling and surrogacy tasks under the Hub. Numerous current and planned taxonomic publications report on new species from these collections (dynamic queries will update these data with new names as further scientific publications are published).

Marine Biodiversity Hub Multi-Year Research Plan 2011 - 2014 - Nicholas J. Bax (2011)
This Multi-Year Research Plan (MYRP) has been developed for the NERP Marine Biodiversity Hub by Director Nic Bax in consultation with Hub partners and stakeholders.  It broadly describes the scope of the Hub’s research work program over the period 2011 to 2014.  It will be accompanied by several Annual Work Plans (AWPs), which will define details of the scheduled activities on an annual basis. The purpose of the Multi-Year Research Plan is to: Provide contextual information and a breakdown of research activities in the Hub Describe the research that the Hub will be undertaking under the National Environmental Research Program (NERP) between 2011 and 2014 Identify research priorities and links to Australian Government Environment Portfolio policies and programs Outline the relationship of the research to the Australian Government Environment Portfolio and other key end users, and Provide a framework for monitoring and evaluating the Hub activities, as part of the National Environmental Research Program.   The primary audience for the MYRP is the Minister for Sustainability, Environment, Water, Population and Communities, environment portfolio agencies, particularly the Department of Sustainability, Environment,  Water, Population and Communities (SEWPaC) and the Hub with its researchers. Other interested stakeholders include non-hub researchers, government and non-government organisations and the general public. Related information: Marine Biodiversity Hub Annual Work Plan 2012   Download the Hub's Multi-Year Research Plan - see Item field below
Keywords: annual research plan

Media release - First broad-scale maps of life on the sea-shelf (2011)

Mitochondrial phylogeny of the deep-sea squat lobsters, Munidopsidae (Galatheoidea) - Ahyong, Shane T.; Andreakis, Nikos; Taylor, Joanne (Zoologischer Anzeiger - A Journal of Comparative Zoology, 2011)
The Munidopsidae, one of three squat lobster families in the Galatheoidea, contains the deepest dwelling squat lobsters, with some occurring at abyssal depths. Munidopsids were formerly divided into two subfamilies: Shinkaiinae, for the unusual hydrothermal vent genus Shinkaia; and Munidopsinae for remaining taxa. Four munidopsid genera are currently recognised (Shinkaia, Leiogalathea, Galacantha and Munidopsis) but the largest genus, Munidopsis, is highly diverse morphologically, with multiple genera or subgenera currently in its synonymy. Phylogenetic studies of galatheoids focussed on high level relationships indicate that Leiogalathea is sister to other munidopsids, but the position of Shinkaia with respect to Munidopsis and Galacantha is unclear, as is the reciprocal monophyly of the latter two genera. Phylogenetic analyses of the Munidopsidae based on mitochondrial 16S and COI sequences, sampling all current genera (including the majority of the formerly recognised subgenera), indicate that the generic and former subfamily classifications do not reflect the phylogeny. Shinkaia and Galacantha clades are nested within Munidopsis rendering the genus paraphyletic and the bi-subfamily classification phylogenetically invalid. Many of the Munidopsis clades recovered, however, correspond well to formerly recognised genera or subgenera, indicating good prospects for a natural subdivision of Munidopsis.
Keywords: Crustacea; Decapoda; Molecular phylogeny; Munidopsis; Squat lobster

Model based grouping of species across environmental gradients - Piers K Dunstan; Scott D Foster; Ross Darnell (Ecological Modelling, 2011)
We present a novel approach to the statistical analysis and prediction of multispecies data. The approach allows the simultaneous grouping and quantification of multiple species’ responses to environmental gradients. The underlying statistical model is a finite mixture model, where mixing is performed over the individual species’ responses to environmental gradients. Species with similar responses are grouped with minimal information loss. We term these groups species archetypes. Each species archetype has an associated GLM that can be used to predict distributions with appropriate measures of uncertainty. Initially, we illustrate the concept and method using artificial data and then with application to real data comprising 200 species from the Great Barrier Reef (GBR) lagoon on 13 oceanographic and geological gradients from 12°S to 24°S. The 200 species from the GBR are well represented by 15 species archetypes. The model is interpreted through maps of the probability of presence for a fine scale set of locations throughout the study area. Maps of uncertainty are also produced to provide statistical context. The presence of each species archetype was strongly influenced by oceanographic gradients, principally temperature, oxygen and salinity. The number of species in each group ranged from 4 to 34. The method has potential application to the analysis of multispecies distribution patterns and for multispecies management.
Keywords: Biodiversity; Finite mixture model; Grouping; Prediction; Species archetype

Morphological, molecular and biogeographic evidence support two new species in the Uroptychus naso complex (Crustacea: Decapoda: Chirostylidae) - Gary C. B. Poore; Andreakis, Nikos (Molecular Phylogenetics and Evolution, 2011)
The tropical to subtropical squat lobster Uroptychus nasoVan Dam, 1933 (Chirostylidae) is a widely distributed species originally described from Indonesia, subsequently reported from the Philippines, Taiwan, Japan and it has recently been discovered on the continental slope of north-western Australia. Populations of U. naso occur along the Indo-Pacific Ocean continental margin crossing the recently proposed marine analog of Wallace’s line, responsible for past population fragmentation and ancient speciation. Sequence data from mitochondrial (COI, 16S) and nuclear (H3) DNA regions were used to assess genealogical relationships among geographically disjoint populations of the species throughout its known distribution range. Several mitochondrial lineages, corresponding to geographically isolated populations and three cryptic species were encountered, namely, U. naso sensu stricto and two new species, Uroptychus cyrano and Uroptychus pinocchio spp. nov. U. pinocchio is encountered only in Japan, Taiwan and the Philippines; U. cyrano is confined to north-western Australia; and U. naso consists of three genetically distinct populations distributed on both sides of the marine Wallace’s line. Fossil-calibrated divergence time approximations indicated a most recent common ancestor (MRCA) for U. naso and U. cyrano from early Eocene whilst northern and southern populations of the former have been separated probably since the Miocene. These patterns may represent a standard distribution trend for several other deep-sea invertebrate species with similar geographical ranges.
Keywords: Australia; Chirostylidae; Cryptic species; Phylogeography; Taxonomy; Wallace’s line

A new approach to mapping marine benthic habitats using physical environmental data - Z Huang; Brendan P Brooke; Harris, Peter T. (Continental Shelf Research, 2011)
Reliable marine benthic habitat maps at regional and national scales are needed to enable the move towards the sustainable management of marine environmental resources. Due to the paucity of adequate biological data and the prohibitive cost of directly sampling benthic biota over large areas, the most effective means of developing broad-scale benthic habitat maps is to use commonly available marine physical data. A new robust method of mapping marine benthic habitats at this scale was developed based on a stratified approach to habitat classification. This approach explicitly uses knowledge of marine benthic ecology to determine an appropriate number of stratification levels, to choose the most suitable environmental variables for each level, and to select ecologically significant boundary conditions (i.e. threshold values) for each variable. Three stratification levels, with nine environmental variables, were created using a spatial segmentation approach. Each level represents major environmental processes and characteristics of the Australian marine benthic environment. The finest scale of benthic habitat was defined by seafloor physical properties of topography, sediment grain size, and seabed shear stress. The intermediate scale was defined by water-column nutrient parameters and bottom water temperature. The broadest scale was defined by a seabed insolation parameter derived from depth data. The classifications of the three stratified levels were implemented using an object-based fuzzy classification technique that recognises that habitats are largely homogenous spatial regions, and transitions between habitats are often gradual. Classification reliability was indicated in confidence maps obtained from the fuzzy classification. Physical habitat diversity was evaluated for the final benthic habitat map that combines the three classifications. The final benthic habitat map identifies the structurally complex continental shelf break as an area of relatively high habitat diversity. Other extensive areas with a high diversity of habitats include the central and southern Great Barrier Reef and adjacent Coral Sea deep-water platforms, the outer shelf and slope of the Great Australian Blight, and extensive areas of shelf and deep water seabed on the south-western and north-western margins. These areas match well with the distribution of large-scale high-relief geomorphic features (e.g., reefs, ridges, seamounts, valleys, and canyons), likely reflecting the strong influence of bedrock outcrops and reefs on habitat diversity. Overall, the new classification method is relatively easily implemented and updated to include new knowledge and data, and can be applied at spatial scales that are useful for effective management of marine resources at various levels of government.
Keywords: Benthic habitat; GIS-based mapping; Marine biodiversity; Object-based fuzzy classification; Stratified habitat level

Performance of predictive models in marine benthic environments based on predictions of sponge distribution on the Australian continental shelf - Z Huang; Brendan P Brooke; Jin Li (Ecological Informatics, 2011)
This study tested the performance of 15 predictive models in predicting the distribution of sponge assemblages on the Australian continental shelf using a common set of marine environmental variables. The models included traditional regression and more recently developed machine learning models. The results demonstrate that the spatial distribution of sponge assemblages can be successfully predicted, although the effectiveness of predictions varied among models. Overall, machine learning models achieved the best prediction performance. The direct variable of bottom-water temperature and the resource variables that describe bottom-water nutrient status were found to be useful surrogates for the distribution of sponge assemblages at the broad regional scale. A new method of deriving pseudo-absence data (weighted pseudo-absence) was compared with random pseudo-absence data — the new data were able to improve modelling performance for all the models both in terms of statistics (~ 10%) and in the predicted spatial distributions. Results from this study will further refine modelling methods used to predict the spatial distribution of marine biota at broad spatial scales, an outcome especially relevant to managers of marine resources.
Keywords: Broad scale; Machine learning; Marine; predictive modelling; Pseudo-absence; Sponge

Predictions of beta diversity for reef macroalgae across southeastern Australia - Rebecca Leaper; Nicole A. Hill; Graham J. Edgar; Nick Ellis; E Lawrence; C Roland Pitcher; Neville Barrett; Russell J. Thomson (Ecosphere, 2011)
We analyzed and predicted spatial patterns of turnover in macroalgal community composition (beta diversity) that accounted for broad-scale environmental gradients using two contrasting community modelling methods, Generalised Dissimilarity Modelling (GDM) and Gradient Forest Modelling (GFM). Percentage cover data from underwater macroalgal surveys of subtidal rocky reefs along the southeastern coastline of continental Australia and northern coastline of Tasmania were combined with 0.01°-resolution gridded environmental variables, to develop statistical models of beta diversity. GDM, a statistical approach based on a matrix regression, and GFM, a machine learning approach based on ensemble tree based methods, were used to fit models and generate predictions of beta diversity within unsurveyed areas across the region of interest. Patterns of macroalgal beta diversity predicted by both methods were remarkably congruent and showed a similar and striking change in community composition from eastern South Australia to western Victoria and northern Tasmania. Macroalgal communities differed markedly in predicted composition between the open coast and inshore locations. A distinct algal community was predicted for the enclosed Port Philip Bay in Victoria. Sea surface temperature standard deviation and average contributed most to changes in beta diversity for both the GDM and GFM models; changes in wave exposure and oxygen also influenced beta diversity in the GDM model, while salinity and exposure contributed substantially to the GFM model. The GDM and GFM analyses allowed us to model and predict spatial patterns of beta diversity in macroalgal communities comprising >180 species over 6600 km of coastline. These outputs advance regional-scale conservation management by allowing planners to interpolate from point source ecological data to assess the distribution of biodiversity across their full domain of interest. The congruence between methods suggests that strong environmental gradients related to temperature and exposure are the common drivers of community change in this region.
Keywords: Beta diversity; conservation planning; generalized dissimilarity modeling; gradient forest modeling; macroalgae; subtidal rocky reefs

RAD biodiversity: prediction of rank abundance distributions from deep water benthic assemblages - Piers K Dunstan; Scott D Foster (Ecography, 2011)
Rank abundance distributions (RADs) are a description of community structure common to every ecological sample where counts are recorded and are useful for managing and understanding biodiversity. We use RADs to describe patterns of biodiversity in samples with high numbers of unique species. We use a novel statistical method to analyse RADs and demonstrate prediction methods for attributes of biodiversity. The RAD is defined by the total abundance (Ni), species richness (Si) and the vector of relative abundances (nij) and the joint probability distribution of these quantities is modelled. Models were fitted to benthic biological data sampled on the Western Australian coast from depths of 100 to 1500 m and a latitudinal range of 22 to 35oS, using topographic and oceanographic data as covariates. Predictions from fitted models give attributes of biodiversity derived from RADs at a regular grid over the sampled area. The Leeuwin current and Leeuwin undercurrent appear to be key structuring forces for the predicted biodiversity attributes. The predictions show that benthic biodiversity is complex and varies with a number of different covariates. The predictions are unique, as they characterise important aspects of biodiversity and how it varies with large spatial scales. The predictions enable the complete reconstruction of the expected RAD at any point where covariates are available with estimates of uncertainty.

Results of expert survey on the effectiveness of biological surrogates IN Effectiveness of Biological Surrogates for Predicting Patterns of Marine Biodiversity: A Global Meta-Analysis - Camille Mellin; Delean, Steve; M Julian Caley; Graham J. Edgar; Mark Meekan; C Roland Pitcher; Rachel Przeslawski; Williams, Alan; Bradshaw, Corey (PLoS ONE, 2011)
The use of biological surrogates as proxies for biodiversity patterns is gaining popularity, particularly in marine systems where field surveys can be expensive and species richness high. Yet, uncertainty regarding their applicability remains because of inconsistency of definitions, a lack of standard methods for estimating effectiveness, and variable spatial scales considered. We present a Bayesian meta-analysis of the effectiveness of biological surrogates in marine ecosystems. Surrogate effectiveness was defined both as the proportion of surrogacy tests where predictions based on surrogates were better than random (i.e., low probability of making a Type I error; P) and as the predictability of targets using surrogates (R2). A total of 264 published surrogacy tests combined with prior probabilities elicited from eight international experts demonstrated that the habitat, spatial scale, type of surrogate and statistical method used all influenced surrogate effectiveness, at least according to either P or R2. The type of surrogate used (higher-taxa, cross-taxa or subset taxa) was the best predictor of P, with the higher-taxa surrogates outperforming all others. The marine habitat was the best predictor of R2, with particularly low predictability in tropical reefs. Surrogate effectiveness was greatest for higher-taxa surrogates at a <10-km spatial scale, in low-complexity marine habitats such as soft bottoms, and using multivariate-based methods. Comparisons with terrestrial studies in terms of the methods used to study surrogates revealed that marine applications still ignore some problems with several widely used statistical approaches to surrogacy. Our study provides a benchmark for the reliable use of biological surrogates in marine ecosystems, and highlights directions for future development of biological surrogates in predicting biodiversity.

Seabed gravel content across the Australian continental EEZ - Jin Li (Geoscience Australia, 2011)
The dataset provides the spatially continuous data of the seabed gravel content (sediment fraction >2000 µm) expressed as a weight percentage ranging from 0 to 100%, presented in 0.01 decimal degree resolution raster format. The dataset covers the Australian continental EEZ, including seabed surrounding Tasmania. It does not include areas surrounding Macquarie Island, and the Australian Territories of Norfolk Island, Christmas Island, and Cocos (Keeling) Islands or Australia's marine jurisdiction off of the Territory of Heard and McDonald Islands and the Australian Antarctic Territory. This dataset supersedes previous predictions of sediment gravel content for the Australian Margin with demonstrated improvements in accuracy. Accuracy of predictions varies based on density of underlying data and level of seabed complexity. Artefacts occur in this dataset as a result of insufficient samples in relevant regions. This dataset is intended for use at national and regional scales. The dataset may not be appropriate for use at local scales in areas where sample density is insufficient to detect local variation in sediment properties. To obtain the most accurate interpretation of sediment distribution in these areas, it is recommended that additional samples be collected and interpolations updated.

Seabed mud content across the Australian continental EEZ - Jin Li (Geoscience Australia, 2011)
This dataset provides the spatially continuous data of seabed mud content (sediment fraction < 63 µm) expressed as a weight percentage ranging from 0 to 100%, presented in 0.01 decimal degree resolution raster format. The dataset covers the Australian continental EEZ, including seabed surrounding Tasmania. It does not include areas surrounding Macquarie Island, and the Australian Territories of Norfolk Island, Christmas Island, and Cocos (Keeling) Islands or Australia's marine jurisdiction off of the Territory of Heard and McDonald Islands and the Australian Antarctic Territory. This dataset supersedes previous predictions of sediment mud content for the Australian Margin with demonstrated improvements in accuracy. Accuracy of predictions varies based on density of underlying data and level of seabed complexity. Artefacts occur in this dataset as a result of insufficient samples in relevant regions. This dataset is intended for use at national and regional scales. The dataset may not be appropriate for use at local scales in areas where sample density is insufficient to detect local variation in sediment properties. To obtain the most accurate interpretation of sediment distribution in these areas, it is recommended that additional samples be collected and interpolations updated.

Seabed sand content across the Australian continental EEZ - Jin Li (Geoscience Australia, 2011)
This dataset provides the spatially continuous data of the seabed sand content (sediment fraction 63-2000 µm) expressed as a weight percentage ranging from 0 to 100%, presented in 0.01 decimal degree resolution raster format. The dataset covers the Australian continental EEZ, including seabed surrounding Tasmania. It does not include areas surrounding Macquarie Island, and the Australian Territories of Norfolk Island, Christmas Island, and Cocos (Keeling) Islands or Australia's marine jurisdiction off of the Territory of Heard and McDonald Islands and the Australian Antarctic Territory. This dataset supersedes previous predictions of sediment sand content for the Australian Margin with demonstrated improvements in accuracy. Accuracy of predictions varies based on density of underlying data and level of seabed complexity. Artefacts occur in this dataset as a result of insufficient samples in relevant regions. This dataset is intended for use at national and regional scales. The dataset may not be appropriate for use at local scales in areas where sample density is insufficient to detect local variation in sediment properties. To obtain the most accurate interpretation of sediment distribution in these areas, it is recommended that additional samples be collected and interpolations updated.

Shelf habitat distribution as a legacy of Late Quaternary marine transgressions: a case study from a tropical carbonate province - Scott L Nichol; Brendan P Brooke (Continental Shelf Research, 2011)
The legacy of multiple marine transgressions is preserved in a complex morphology of ridges, mounds and reefs on the Carnarvon continental shelf, Western Australia. High-resolution multibeam sonar mapping, underwater photography and sampling across a 280 km2 area seaward of the Ningaloo Coast World Heritage Area shows that these raised features provide hardground habitat for modern coral and sponge communities. Prominent among these features is a 20 m high and 15 km long shore-parallel ridge at 60 m water depth. This ridge preserves the largely unaltered form of a fringing reef and is interpreted as the predecessor to modern Ningaloo Reef. Landward of the drowned reef, the inner shelf is covered by hundreds of mounds (bommies) up to 5 m high and linear ridges up to 1.5 km long and 16 m high. The ridges are uniformly oriented to the north–northeast and several converge at their landward limit. On the basis of their shape and alignment, these ridges are interpreted as relict long-walled parabolic dunes. Their preservation is attributed to cementation of calcareous sands to form aeolianite, prior to the post-glacial marine transgression. Some dune ridges abut areas of reef that rise to sea level and are highly irregular in outline but maintain a broad shore-parallel trend. These are tentatively interpreted as Last Interglacial in age. The mid-shelf and outer shelf are mostly sediment covered with relatively low densities of epibenthic biota and have patches of low-profile ridges that may also be relict reef shorelines. An evolutionary model for the Carnarvon shelf is proposed that relates the formation of drowned fringing reefs and aeolian dunes to Late Quaternary eustatic sea level.
Keywords: Aeolianite; Continental shelf; Coral reef; Multibeam sonar; Shelf bedforms; Submerged reef

A Southern Hemisphere bathyal fauna is distributed in latitudinal bands - Tim O'Hara; Rowden, Ashley A.; Nicholas J. Bax (Current Biology, 2011)
The large-scale spatial distribution of seafloor fauna is still poorly understood. In particular, the bathyal zone has been identified as the key depth stratum requiring further macroecological research [1], particularly in the Southern Hemisphere [2]. Here we analyze a large biological data set derived from 295 research expeditions, across an equatorto- pole sector of the Indian, Pacific, and Southern oceans, to show that the bathyal ophiuroid fauna is distributed in three broad latitudinal bands and not primarily differentiated by oceanic basins as previously assumed. Adjacent faunas form transitional ecoclines rather than biogeographical breaks. This pattern is similar to that in shallow water despite the order-of-magnitude reduction in the variability of environmental parameters at bathyal depths. A reliable biogeography is fundamental to establishing a representative network of marine reserves across the world’s oceans

Squat lobsters research - Taylor, Joanne; Gary C. B. Poore (2011)
Research ongoing.  See URL link above for updates.

Submerged reefs and aeolian dunes as inherited habitats, Point Cloates, Carnarvon Shelf, Western Australia. In: GeoHab Atlas of Seafloor Geomorphology Features and Benthic Habitats - Scott L Nichol; Tara J Anderson; C Battershill; Brendan P Brooke (GeoHab Atlas of Seafloor Geomorphology Features and Benthic Habitats, 2011)

Trace Element Concentrations in Feathers of Flesh-footed Shearwaters (Puffinus carneipes) from Across Their Breeding Range - Bond, Alexander L.; Lavers, Jennifer L. (Archives of Environmental Contamination and Toxicology, 2011)
Seabirds are convenient indicators of contamination of the marine environment because feathers can be sampled non-destructively, and a great deal is known about their ecology. Flesh-footed Shearwaters (Puffinus carneipes) are of conservation concern in Australia and New Zealand, partly because ingestion of marine debris may be reducing breeding success at their largest colony. Because marine plastics accumulate contaminants in the ocean environment, an assessment of metal and metalloid contaminants was initiated. We sampled feathers from Kauwahaia (n = 18) and Lady Alice Island, New Zealand (n = 30), Lord Howe Island (n = 24) and Western Australia (n = 33) during the 2008 austral summer, making this the most complete assessment of metal and metalloid contamination of any shearwater. We found colony differences in all elements except lead and thallium. Samples from Western Australia had higher silver, aluminium, cadmium, and copper concentrations, while shearwaters from Lord Howe Island (eastern Australia) had elevated concentrations of mercury (mean ± S.D., 11221 ± 5612 ppb). We conclude that mercury, and potentially arsenic and cadmiumrepresent toxicological concerns for this declining species.

Turtle conservation measures, effectiveness and cost - Lavers, Jennifer L. (CSIRO, 2011)

Utility of a spatial habitat classification system as a surrogate of marine benthic community structure for the Australian margin - Rachel Przeslawski; Currie, D. R.; Sorokin, S. J.; Ward, T. M.; Althaus, Franziska; Williams, Alan (ICES Journal of Marine Science, 2011)
This study tests whether a continental-scale classification of Australian benthic habitats (termed “seascapes”) and the interpolated environmental data from which they are derived are useful as abiotic surrogates of biodiversity at a local [tens of kilometres, Great Australian Bight (GAB)] and regional scale [hundreds of kilometres, Western Australian (WA) margin]. Benthic invertebrate community structure is moderately associated with specific seascapes in both the GAB (R = 0.418) and WA margin (excluding hard substrata, R = 0.375; all substrata, R = 0.313). Mud content, seafloor slope, and seafloor temperature are significantly correlated with invertebrate communities at both scales, with disturbance and primary production correlated with GAB communities. Seascapes are not consistently useful surrogates because the strength and significance of relationships between seascapes and community structure differs among seascapes, regions, and spatial scales. Nevertheless, a national system of seascapes is an appropriate surrogate for broad-scale benthic invertebrate community patterns when biological data are limited, provided the uncertainty is acknowledged and, where possible, an assessment made of each seascape's ability to differentiate biological communities. Further refinement of seascape derivations may include updated and additional environmental data (particularly for hard vs. soft substrata) and validation among biological datasets from a range of habitats and scales.
Keywords: benthic invertebrates; continental margin; interpolation; seascapes; Sponge; Surrogacy

Abiotic surrogates for marine biodiversity (Australian Marine Sciences Association Conference, 4 - 8 July 2010, 2010)

Application of biotic and abiotic indicators for detecting benthic impacts of marine salmonid farming among coastal regions of Tasmania - Graham J. Edgar; Davey, Adam; Shepherd, Colin (Aquaculture, 2010)
Impact assessment, Long-term monitoring, Macrobenthos, Introduced species, Salmo salar

Are deep-sea demersal fish assemblages globally homogenous? Insights from seamounts - Malcolm R Clark; Althaus, Franziska; Williams, Alan; Niklitschek, Edwin; Menezes, Gui M.; Hareide, Nils-Roar; Sutton, Philip; ’Donnell, Ciaran (Marine Ecology, 2010)
Deep-sea fishes have been poorly sampled globally, and overall knowledge of demersal fish distributions and the drivers of community composition and diversity remain limited. Here, we used nine comparable datasets with species-level identification of fishes from research surveys around the world to test the hypothesis that deep-sea demersal fish assemblage composition on seamounts is consistent between major oceans. Two levels of analysis were undertaken: the first combined all presence-absence data from a seamount, while a second more detailed analysis included catch weight data based on a smaller number of seamounts. Overall, there was a consistent separation of seamounts by region based on the compositions of their fish assemblages. New Zealand and SE Australian seamounts have a very similar ichthyofauna, which differs substantially from seamounts in the eastern South Pacific Ocean off Chile. In the North Atlantic, Bear Seamount appears to be distinct from all others, while seamount fish assemblages off Ireland, the Azores, and Faraday Seamount have some affinities. The Tasman Sea and New Caledonian seamounts show strong intra-regional variation. On an ocean basin scale we therefore reject the hypothesis that the composition of deep-sea demersal fish fauna is homogeneous globally. However, regional patterns of both species composition and relative abundance show some similarities between widely separated geographical locations, especially where orange roughy is a dominant species. Salinity was the main environmental factor identified in a multivariate analysis of environmental covariate data. This is likely to be a result of salinity being a key characteristic defining both Antarctic Intermediate Water and North Atlantic Deep Water, the water masses found over most seamounts examined in this study, and which may explain similarities between deep-sea fish assemblages.
Keywords: Biogeography; deep-sea; fish assemblages; fish distribution; seamounts

Assessing anthropogenic hazards to endangered species using expert opinion surveys: a case study with sea turtles - Donlan, C Josh; WINGFIELD, DANA K.; Larry B Crowder; Chris Wilcox (Conservation Biology, 2010)

Australian bathymetry and topography, June 2005 (Geoscience Australia, 2010)
Contact: Marine Data Manager, Geoscience Australia, marine@ga.gov.au Geoscience Australia and the National Oceans Office carried out a joint venture project to produce a consistent, high-quality 9 arc second (0.0025 degree or ~250 m at the equator) bathymetric data grid of those parts of the Australian water column jurisdiction lying between 92E and 172E and 8S and 60S. As well as the waters adjacent to the continent of Australia and Tasmania, the area selected also covers the area of water column jurisdiction surrounding Macquarie Island, and the Australian Territories of Norfolk Island, Christmas Island, and Cocos (Keeling) Islands. The area selected does not include Australias marine jurisdiction off of the Territory of Heard and McDonald Islands and the Australian Antarctic Territory. The underlying data from which this grid is derived can only support this resolution in areas where direct bathymetric observations are sufficiently dense (e.g. where swath bathymetry data or digitised chart data exist). In areas where only track-line data exist, the grid resolution is high along-line but low perpendicular to lines. In areas where no sounding data are available, the grid is based on interpolated or indirectly observed bathymetry, and these data can only support a resolution of 2 arc minutes (2 nautical miles or ~3.7 km). The grid covers an area of approximately 41 million square kilometres. Its dimensions are 32003 x 20803 cells resulting in a file size slightly in excess of 1.3 Gb of 2-bytes integer numbers representing the bathymetric values. The grid synthesises approximately 1.7 billion observed data points. This grid is not suitable for use as an aid to navigation, or to replace any products produced by the Australian Hydrographic Service.

Australian marine physical environmental data – descriptions and metadata - Z Huang; Brendan P Brooke; Whitta, Nathan; Potter, Anna; Fuller, Mike; Dunn, Jeff; C Roland Pitcher (Geoscience Australia Record, 2010)
The objective of this report is to provide a detailed description of the marine environmental data that have been collated by the Marine Biodiversity Hub. The Marine Biodiversity Hub is part of the Australian Government’s Commonwealth Environment Research Facilities Program (CERF). The report includes metadata and distribution maps for 37 marine physical environmental variables that make up the dataset as at November 2009. The data were provided by Geoscience Australia and CSIRO Marine and Atmospheric Research and have been employed in the Marine Biodiversity Hub’s surrogacy and predictive modelling research programs. Bathymetry, geomorphology, seabed sediment and seabed exposure parameters were produced by Geoscience Australia. Bottom-water and surface-water parameters were produced by the CSIRO. Some data are restricted to the continental shelf (<200m) while others span the more extensive Australian Exclusive Economic Zone adjacent to the mainland. All data were transformed to a common datum, WGS84, and converted to a common grid with a cell size of 0.01 degrees. The metadata reports conform to ANZLIC standards. As the goal was to use these data in national-scale predictions of seabed biodiversity, only data with national coverage were included.

Autonomous Underwater Vehicle (AUV) for mapping marine biodiversity in coastal and shelf waters: implications for marine management. - Neville Barrett; Seiler, Jan; Tara J Anderson; Williams, Stefan B.; Scott L Nichol; Nicole A. Hill (OCEANS 2010 IEEE - SydneyOCEANS'10 IEEE SYDNEY, 2010)
Australia, biodiversity, image resolution, rivers, sea measurements, sediments

AUV benthic habitat mapping in South Eastern Tasmania - Williams, Stefan B.; Oscar R. Pizarro; Jakuba, Michael; Neville Barrett (Springer Berlin Heidelberg, 2010)

Biophysical modelling and prediction of spatial patterns in biodiversity: Performance of Predictive Biophysical Methods. Progress report - C Roland Pitcher (Marine Biodiversity Hub, 2010)

Bird demographic responses to predator removal programs - Lavers, Jennifer L.; Chris Wilcox; Donlan, C Josh (Biological Invasions, 2010)
Invasive predators pose a significant risk.to bird populations worldwide. Humans have a long.history of removing predators from ecosystems;.current island restoration actions typically focus on.the removal of invasive predators, such as non-native.rodents, from seabird breeding islands. While not.overly abundant, the results of predator removal.studies provide valuable information on the demographic.response of birds, and can assist conservation.practitioners with prioritizing invasive predator.removal projects. We review such studies focusing.on observed demographic responses of bird populations.to predator removal campaigns and whether.ecological factors are useful in predicting those.responses. From the 800? predator removal programs.indentified, a small fraction (n = 112) reported.demographic responses of bird populations. Change.in productivity was the most commonly reported.response, which on average increased by 25.3% (2.5.SE) with predator removal. The best supported model.for predicting the change in productivity from predator.removal incorporated bird body mass, egg mass,.predator type, nest type and an interaction term for.body mass and nest type (AICc weight = 0.457). The.predicted percent increase in productivity resulting.from hypothetical predator removal ranged from 16.9.to 63.0% (mean = 45.0, 5.6 SE), and was lowest for.large, surface nesting birds such as albatrosses. The.predicted increase in productivity resulting from.predator removal alone was insufficient to reverse.the predicted population decline for 30–67% of bird.species considered, suggesting that in many cases,.removal of predators must be performed in combination.with other conservation actions in order to ensure.a stable or increasing population..
Keywords: Eradication benefits; Invasive predator; island restoration; Population recovery; Predator control

A birds-eye view of physical and geochemical properties of sandy sediments across diverse habitats in Jervis Bay, NSW: Relationships with infaunal species-richness (Australian Marine Sciences Association Conference, 4 - 8 July 2010, 2010)

Broad-scale geomorphology and benthic habitats of the Perth coastal plain and Rottnest Shelf, Western Australia, identified in a merged topographic and bathymetric digital relief model - Brendan P Brooke; Creasey, John; Sexton, Mike (International Journal of Remote Sensing, 2010)
A digital relief model (DRM) of the Swan Coastal Plain and Rottnest Shelf (7400 km2) was built with a range of topographic and high-resolution bathymetric datasets, gridded to a 50 m cell size. The DRM enabled the delineation of relict coastal landforms, benthic habitats and development of a regional morphostratigraphic framework. Well-defined features include: (1) limestone ridges on the coastal plain that sit subparallel to the modern shoreline and were largely formed as coastal dune barriers during or shortly after Quaternary interglacial periods of high sea level; (2) rocky reefs on the inner shelf that rise up to 10 m above the adjacent seafloor, which are remnants of coastal dune barriers that formed when the sea level was 20–30 m lower than present and (3) a discontinuous ridge 3–10 m high along much of the outer shelf, which likely represents a coastal barrier that formed when the sea level was around 60 m lower than present. The DRM provides a useful regional perspective of the distribution and form of these extensive reefs.

Can incentive-based spatial management work in the Eastern tuna and billfish fishery? (Annual Australian Agricultural and Resource Economics Society Conference, 9 - 12 February 2010, 2010)

CERF Hub Factsheet 2010 - Ensuring a future for life in Australia’s oceans - Nicholas J. Bax (2010)
The Marine Biodiversity Hub is supporting the Department of Sustainability, Environment, Water, Population and Communities'(previously Environment, Water, Heritage and the Arts DEWHA) marine planning by providing national and regional maps of predicted patterns of marine biodiversity in Australia’s oceans, and an increased range of options for its management. This capability is crucial to conserving and managing Australia’s marine biodiversity and will complement Australia’s National Representative System of Marine Protected Areas (NRSMPA) due to be in place by 2012. Together, the NRSMPA and off-reserve management provide the best option for long-term protection and sustainable use of marine biodiversity in light of competing demands on the marine environment. Also see our 2012 NERP Marine Biodiversity Hub Factsheet

Characterisation of shallow inshore coastal reefs on the Tasman Peninsula, South Eastern Tasmania, Australia. In: GeoHAB Atlas of Seafloor Geomorphic Features and Benthic Habitats - Vanessa L Lucieer; Neville Barrett; Nicole A. Hill; Scott L Nichol (GeoHAB Atlas of Seafloor Geomorphic Features and Benthic Habitats, 2010)

Compensatory mitigation: an interim solution to seabird bycatch in fisheries? - Pascoe, Sean; Chris Wilcox; Donlan, C Josh (International Institute of Fisheries Economics and Trade, IIFET 2010 Conference, 2010)

Conflicting estimates of connectivity among deep-sea coral populations - Karen J Miller; Williams, Alan; Rowden, Ashley A.; Knowles, Claire; Dunshea, Glenn (Marine Ecology, 2010)
connectivity, conservation, coral, deep-sea, DNA, genetics, larval dispersal, seamounts

The creation of high resolution bathymetry grids for the Lord Howe Island region - Mleczko, Richard; S Sagar; Spinoccia, M.; Brendan P Brooke (Geoscience Australia, 2010)

The data-reality gap: an attempt to understand marine biodiversity through survey data (Japanese Joint Statistical Meeting, 5 - 8 September 2010, Waseda University, Tokyo, Japan, 2010)

Depth structuring in distributions of demersal fishes on Australia’s continental shelf - Lyne, Vincent D. (CSIRO, 2010)
Marine bioregionalisation used in Australia for regional marine planning and to establish the National Representative system of Marine Protected Areas (NRSMPA) initially relied on: 1) provincial structure of the shelf (Fig. 2a), 2) provincial structure of the slope (Fig. 2b), and 3) bathomic (depth related) structure of the slope. This study uses extensively updated data on continental shelf fishes to determine 4) bathomic structuring of the continental shelf of Australia. These shelf bathomes have been used in Australia’s marine planning including the designation of the NRSMPA.

Descriptions of new sharks and rays from Borneo (paper) - Last, Peter R.; William T White; John J Pogonoski (CSIRO Marine and Atmospheric, 2010)
fish taxonomy, biogeography, regionalisation

Di- and tri-nucleotide microsatellites in the deep sea squat 2 lobster Munida isos (Galatheidae) - ANDRIS, MALVINA; ARADOTTIR, GUDBJORG I.; ARNAU, G.; Asta Audzijonyte; BESS, EMILIE C.; BONADONNA, FRANCESCO; BOURDEL, G.; BRIED, ËL; BUGBEE, GREGORY J.; BURGER, P. A.; CHAIR, H.; CHARRUAU, P. C.; et al. (Molecular Ecology Resources, 2010)
Eight polymorphic di- and tri-nucleotide microsatellite markers are reported for the deep  sea invertebrate Munida isos from submarine mountains and continental slopes in south eastern Australia. 140 putative microsatellite sequences were identified in 292 clones from partial genomic libraries enriched for CA, GA, AAT and CCT motifs. Dinucleotide loci were hypervariable with 33-43 alleles per locus and expected heterozygosities of 0.94- 0.96. Trinucleotide loci had 21-40 alleles per locus and expected heterozygosities 0.89- 0.96. As with many marine invertebrates, conformity to Hardy Weinberg proportions was poor suggesting high incidence of null alleles. These datasets are stored on the GenBank website http://www.ncbi.nlm.nih.gov/genbank/ and referenced in the Technical paper Species: Munida isos Number of primers developed: 8 GenBank accession no: HM194717–HM194724 MER database no: 44514–44521 Authors:  Gunasekera, Rasanthi M.; England, Phillip R.; Miller, Karen J.; Audzijonyte, Asta   HM194717 Munida isos clone B237 microsatellite sequence HM194718 Munida isos clone B242 microsatellite sequence HM194719 Munida isos clone A205 microsatellite sequence HM194720 Munida isos clone B9 microsatellite sequence HM194721 Munida isos clone C161 microsatellite sequence HM194722 Munida isos clone C191 microsatellite sequence HM194723 Munida isos clone C114 microsatellite sequence HM194724 Munida isos clone C189 microsatellite sequence
Keywords: connectivity; population processes

Di- and tri-nucleotide microsatellites in the deep sea squat 2 lobster Munida isos (Galatheidae) - Technical Paper - R. Gunasekera (2010)
Eight polymorphic di- and tri-nucleotide microsatellite markers are reported for the deep  sea invertebrate Munida isos from submarine mountains and continental slopes in south eastern Australia. 140 putative microsatellite sequences were identified in 292 clones from partial genomic libraries enriched for CA, GA, AAT and CCT motifs. Dinucleotide loci were hypervariable with 33-43 alleles per locus and expected heterozygosities of 0.94- 0.96. Trinucleotide loci had 21-40 alleles per locus and expected heterozygosities 0.89- 0.96. As with many marine invertebrates, conformity to Hardy Weinberg proportions was poor suggesting high incidence of null alleles. See also Dataset item which supports this technical paper.
Keywords: connectivity; population processes

Dynamics of benthic patch structure across two seasons in a coastal embayment (GeoHab Conference - Marine Geological and Habitat Mapping, 4 - 7 May 2010, 2010)

The ecology of seamounts: structure, function, and human impacts - Malcolm R Clark; Rowden, Ashley A.; Thomas A Schlacher; Williams, Alan; Consalvey, Mireille; Stocks, Karen I.; Alex D Rogers; Tim O'Hara; White, Martin; Shank, Timothy M.; Hall-Spencer, Jason M. (Annual Review of Marine Science, 2010)
In this review of seamount ecology, we address a number of key scientific issues concerning the structure and function of benthic communities, human impacts, and seamount management and conservation. We consider whether community composition and diversity differ between seamounts and continental slopes, how important dispersal capabilities are in seamount connectivity, what environmental factors drive species composition and diversity, whether seamounts are centers of enhanced biological productivity, and whether they have unique trophic architecture. We discuss how vulnerable seamount communities are to fishing and mining, and how we can balance exploitation of resources and conservation of habitat. Despite considerable advances in recent years, there remain many questions about seamount ecosystems that need closer integration of molecular, oceanographic, and ecological research.

The effects of sampling in marine surveys on biodiversity estimation - Shimadzu, Hideyasu (Geoscience Australia, 2010)

Environmental and spatial predictors of species richness and abundance in coral reef fishes - Camille Mellin; Bradshaw, Corey; Mark Meekan; M Julian Caley (Global Ecology and Biogeography, 2010)
We developed predictive models of coral reef fish species richness and abundance that account for both broad-scale environmental gradients and fine-scale biotic processes, such as dispersal, and we compared the importance of absolute geographical location (i.e. geographical coordinates) versus relative geographical location (i.e. distance to domain boundaries).

Environmental – biological covariance in the soft sediments surrounding Lord Howe Island (Australian Marine Sciences Association Conference, 4 - 8 July 2010, 2010)

Environmental drivers of ophiuroid species richness on seamounts - Tim O'Hara; Tittensor, D. P. (Marine Ecology, 2010)
generalized linear model, macroecology, model averaging, Ophiuroidea, seamount, species richness, SW Pacific

Flythrough movies - Carnarvon Shelf (Ningaloo), Lord Island Shelf, South-East Tasmanian Shelf Reefs (2010)
Flythrough movies of the Carnarvon Shelf (Ningaloo), Lord Howe Island Shelf and Southeast Tasmanian Shelf Reefs are now available for download and on-line viewing via the Geoscience Australia website - see URL link for this entry or http://www.ga.gov.au/cedda/multimedia/143

Galathean Phylogeography Crustacea: Decapoda: Anomura - Andreakis, Nikos (AIMS, 2010)
The tropical to temperate continental margin of Western Australia (WA), where recent CSIRO collections (100- 1000 m) revealed over 800 nominal species of decapod crustaceans, thirty per cent of which are thought to be new to science. Squat lobsters of the family Galatheidae, one of the most numerous and diverse groups of crustaceans commonly encountered on seamounts, continental margins and shelf habitats at all depths. Galathean species exhibit high morphological diversity, believed to be the result of a relatively old radiation event. Yet, their origins, phylogenetic and phylogeographic relationships are not entirely clear. Squat lobsters constitute an exceptional model system for evaluating historical processes responsible for at the present observed distribution patterns of the Western Australian fauna

Geomorphology and benthic habitats of the Lord Howe volcano (GeoHab Conference - Marine Geological and Habitat Mapping, 4 - 7 May 2010, 2010)

Geomorphology of the Lord Howe Island shelf and submarine volcano. SS06-2008 Post-Survey Report. - Brendan P Brooke; Woodroffe, Colin D.; Linklater, Michelle; Matthew McArthur; Scott L Nichol; Jones, Brian G.; Kennedy, David M.; Buchanan, Cameron; Spinoccia, M.; Mleczko, Richard; Cortese, A.; Atkinson I.; et al. (Geoscience Australia, 2010)
The Lord Howe Island survey SS06-2008 in April 2008 aboard the RV Southern Surveyor was a collaboration between the University of Wollongong and Geoscience Australia. The survey was also an activity of the Commonwealth Environment Research Facilities’ (CERF) Marine Biodiversity Hub, of which Geoscience Australia is a partner, and will contribute to the revised Plan of Management for the Lord Howe Marine Parks. The objectives of the survey were to map the morphology and benthic environments of the shallow shelf that surrounds Lord Howe Island as well as the deeper flanks of this largely submarine volcano. Of particular interest was the apparent drowned reef structure on the shelf and the spatial distribution of seabed habitats and infauna. The data collected are required to better understand the history of reef growth at Lord Howe Island, which sits at the southernmost limit of reef formation, and links between the physical environment and ecological processes that control the spatial distribution of biodiversity on the shelf. The morphology of the flanks of the submarine volcano was also examined to reveal whether they provide evidence of major erosional and depositional processes acting on the volcano. This report provides a description of the survey activities and the results of the processing and initial analysis of the data and samples collected.

A hierarchical framework for classifying seabed biodiversity with application to planning and managing Australia’s marine biological resources - Last, Peter R.; Lyne, Vincent D.; Williams, Alan; Davies, Campbell R.; Butler, Alan J.; Yearsley, Gordon K. (Biological Conservation, 2010)
biodiversity, hierarchical classification, bioregions, surrogates, provinces, bathomes, biotopes, conservation planning, ecosystem-based management (EBM)

A hierarchical framework for classifying seabed biodiversity with application to planning and managing Australia’s marine biological resources - Last, Peter R.; Lyne, Vincent D.; Williams, Alan; Davies, Campbell R.; Butler, Alan J.; Yearsley, Gordon K. (Biological Conservation, 2010)
Biodiversity can be interpreted in many ways. Classifications can include biotic and/or abiotic components, depend on scale and context, and often reflect the disciplinary bias of the authors. Marine biodiversity has almost exclusively been examined at the scale of local or modern processes, which are often less informative than biogeographic or ancient processes for understanding species richness patterns. However, modern and ancient processes are the endpoints of a natural hierarchy where different processes influence distribution at each level. Patterns and processes of biodiversity are scale dependent, with lower levels fully or partially nested in those above. Comparisons that omit this scale dependency will be compromised. We present here a hierarchical framework for describing the structure of marine demersal biodiversity across all spatial scales. This system explicitly recognizes the overarching influence of large-scale biodiversity patterns at realm (ocean basin and tectonic), provincial (palaeohistorical) and bathomic (depth-related) levels. The functional roles and spatial scales are captured within ten nested levels within realms, where the first seven are primarily spatially nested and ecosystem based, and the lowest levels represent units of taxonomic inheritance. The framework is conceptual and each level needs to be validated for its general applicability.

Long-term shifts in abundance and distribution of a temperate fish fauna: a response to climate change and fishing practices - Last, Peter R.; William T White; Daniel C Gledhill; Alistair J Hobday; Brown, Rebecca; Graham J. Edgar; Gretta Pecl (Global Ecology and Biogeography, 2010)

Mapping and characterising soft-sediment habitats, and evaluating physical variables as surrogates of biodiversity in Jervis Bay, NSW. - Tara J Anderson; Brendan P Brooke; Lynda Radke; Matthew McArthur; Hughes, Michael G. (Geoscience Australia, 2010)

Mapping and predicting benthic habitats, biological assemblages, and biodiversity across the Carnarvon Shelf, Western Australia. (GeoHab Conference - Marine Geological and Habitat Mapping, 4 - 7 May 2010, 2010)

Marine biodiversity in the Australian region - Butler, Alan J.; T Rees; Beesley, P.; Nicholas J. Bax (Public Library of Science (PLoS), 2010)
The entire Australian marine jurisdictional area, including offshore and sub-Antarctic islands, is considered in this paper. Most records, however, come from the Exclusive Economic Zone (EEZ) around the continent of Australia itself. The counts of species have been obtained from four primary databases (the Australian Faunal Directory, Codes for Australian Aquatic Biota, Online Zoological Collections of Australian Museums, and the Australian node of the Ocean Biogeographic Information System), but even these are an underestimate of described species. In addition, some partially completed databases for particular taxonomic groups, and specialized databases (for introduced and threatened species) have been used. Experts also provided estimates of the number of known species not yet in the major databases. For only some groups could we obtain an (expert opinion) estimate of undiscovered species. The databases provide patchy information about endemism, levels of threat, and introductions. We conclude that there are about 33,000 marine species (mainly animals) in the major databases, of which 130 are introduced, 58 listed as threatened and an unknown percentage endemic. An estimated 17,000 more named species are either known from the Australian EEZ but not in the present databases, or potentially occur there. It is crudely estimated that there may be as many as 250,000 species (known and yet to be discovered) in the Australian EEZ. For 17 higher taxa, there is sufficient detail for subdivision by Large Marine Domains, for comparison with other National and Regional Implementation Committees of the Census of Marine Life. Taxonomic expertise in Australia is unevenly distributed across taxa, and declining. Comments are given briefly on biodiversity management measures in Australia, including but not limited to marine protected areas.

Market Based Instruments Workshop 4 November 2010 - Agenda - Guest, M. (Department of Sustainability, Environment, Water, Population and Communities (DSEWPaC), 2010)

Market Based Instruments Workshop 4 November 2010 - Beware of mathematicians bearing gifts - Langford, B.; Gordon, A.; Bastin, L. (RMIT University/Aston University, 2010)

Market Based Instruments Workshop 4 November 2010 - How can incentives be used in managing biodiversity? - Chris Wilcox (CSIRO, 2010)

Market Based Instruments Workshop 4 November 2010 - Marine Biodiversity Hub & Future Research for MBIs - Nicholas J. Bax (University of Tasmania/CSIRO, 2010)

Market Based Instruments Workshop 4 November 2010 - Marine Fisheries: MBIs for environmental and fisheries outcomes - Sainsbury, K. (University of Tasmania, 2010)

Market Based Instruments Workshop 4 November 2010 - Notes - Guest, M. (2010)

Modelling marine biodiversity with error in covariates (International Biometric Conference, The Federal University of Santa Catarina, Florianopolis, Brazil, 2010, 2010)

Morphology and Formation of Relict Coral Reef on the Shelf around Lord Howe Island (Australian Marine Sciences Association Conference, 4 - 8 July 2010,, 2010)

MPA workshop 16 November 2010 - Agenda - Guest, M. (CSIRO, 2010)

MPA workshop 16 November 2010 - Cost effective survey and monitoring of biota and habitats in shelf based MPAs - Neville Barrett (University of Tasmania/Tasmanian Aquaculture and Fisheries Institute, 2010)

MPA workshop 16 November 2010 - Defining management objectives: lessons from fisheries - Smith, T. (CSIRO, 2010)

MPA workshop 16 November 2010 - Ecosystem health monitoring - K Hayes; Jeffrey M Dambacher; Clifford, D.; Palmer, M.; Moeseneder, C.; Taranto, T. (CSIRO, 2010)

MPA workshop 16 November 2010 - Estimating costs of MPA management - Natalie C. Ban; Adams, V.; Pressey, B.; J Hicks (ARC Centre of Excellence Coral Reef Studies, 2010)

MPA workshop 16 November 2010 - Great Barrier Reef Marine Park: lessons learnt in managing a large multiple use, ecosystem-based MPA - Day, J. (Great Barrier Reef Marine Park Authority, 2010)

MPA workshop 16 November 2010 - Marine Biodiversity Hub & Future Research for MPAs - Nicholas J. Bax (UTAS/CSIRO, 2010)

MPA workshop 16 November 2010 - Notes - Guest, M. (2010)

MPA workshop 16 November 2010 - Spatial Context for MPA Management - Brendan P Brooke (Geoscience Australia, 2010)

Multi-beam backscatter measurements used to infer seabed habitats - Rudy J Kloser; Penrose, J.D.; Butler, Alan J. (Continental Shelf Research, 2010)
Australia; biotopes; epifauna; backscatter; video; multi-beam

National mapping of deepwater biotopes based on multi-beam acoustics - Rudy J Kloser; Keith, G.; Sherlock, Mathew (2010)
This poster was presented at GeoHab 2010 conference in Wellington NZ, 4 - 7 May 2010. A program to map the deepwater biotopes of the Australian EEZ is underway based on fine scale acoustic multi-beam echo sounder (MBES) mapping and a newly developed benthic, optical, acoustic grab sampler (BOAGS). Data are collected on specific research voyages as well as utilising transit voyages between ports. These MBES data and associated physical and optical sensing are an important input into assessing key ecological features (e.g. canyons, terraces, banks, seamounts and deep reefs) for regional marine planning, informing the placement of marine protected areas and fisheries spatial management. The acoustic data provide detailed (20 to 50 m grid) bathymetric and inferred substrate information that can be used with other co-variates to predict macro faunal functional groups based on physical and optical “ground truthing”. A consistent approach of interpreting ecological hard and soft substrate based on the acoustic backscatter that maximises the spatial resolution whilst minimises sources of error was developed and applied. This consistent nationally applied acoustic backscatter processing method is highly correlated with visual and physical sampling of the seabed as well as mega fauna diversity. Mega fauna diversity of 6 taxon grouping ~2000 species is highly correlated to both the seabed hardness and the depth of sampling. Nested within a hierarchical classification scheme estimates of seabed hardness are derived for catchments, specific geological features (canyons, seamounts) and MPA’s. Based on this work we propose that seabed hardness as derived from multi-beam acoustics should be included in regional marine planning processes at a number of scales from regional mapping at the 100’s km scale to the 10’s m to 1 km scale for final MPA placement and fisheries spatial management. Australia’s continental margin defined here from ~150 m to 1500 m, is a narrow strip characterised by high productivity and diversity (Fig. 1). While supporting a major ecological and economic (fishing, oil and gas) resource, this area is poorly-understood yet heavily exploited in parts. A simple first step to assist management of this region is to map the spatial scales of the types of terrain and key components of the biotic assemblages to define marine habitat patches and key ecological features (e.g. canyons, seamounts and deep reefs). Mapping with multi-beam acoustic and optical methods is attractive due to their collective properties: large sampling coverage per unit cost, nondestructive sampling and high spatial resolution.

Neotrygon ningalooensis n. sp. (Myliobatoidei: Dasyatidae), a new maskray from Australia - Last, Peter R.; William T White; Puckridge M. (Aqua, International Journal of Ichthyology, 2010)
fish taxonomy, biogeography, regionalisation

New approaches to mapping biodiversity and the opportunity for greater management flexibility (CERF Conference, 2010, 2010)

A new classification of the Galatheoidea (Crustacea: Decapoda: Anomura) - Ahyong, Shane T.; Baba, K.; Macpherson, E.; Gary C. B. Poore (Zootaxa, 2010)
Galatheoidea, Galatheidae, Munididae fam. nov., Munidopsidae, Porcellanidae, squat lobsters, phylogeny, classification

New perceptions of continental margin biodiversity. In: McIntyre, A.D. (Ed.) Life in the world’s oceans: diversity, distribution, and abundance - Menot, L.; Sibuet, M.; Carney, R.S.; Levin, L.A.; Rowe, G.T.; Billett, D.S.M.; Gary C. B. Poore; Kitazato, H.; Vanreusel, A.; Galéron, J.; Lavrado, H.P.; Sellanes, J.; et al. (Wiley-Blackwell, 2010)
diversity, distribution, abundance

New records and new species of the munidopsine squat lobsters (Decapoda: Anomura: Galatheidae: Munidopsinae) from Australia - Taylor, Joanne (Zootaxa, 2010)
Crustacea, Decapoda, Anomura, Galatheidae, squat lobster, Munidopsis, Galacantha, new species, key, Western Australia, Australia, New Zealand, taxonomy
Keywords: Anomura; Australia; Crustacea; Decapoda; Galacantha; Galatheidae; key; Munidopsis; new species; New Zealand; Squat lobster; Taxonomy; Western Australia

New technologies and the opportunities for national standards in marine monitoring (CERF National Conference, 23 - 24 May, 2010, Canberra, Australia, 2010)

Object based segmentation of multibeam backscatter data: methods for spatial analysis of shallow coastal seabeds, South Eastern Tasmania, Australia (GeoHab Conference - Marine Geological and Habitat Mapping, 4 - 7 May 2010, 2010)

Précis for managers: Understanding the past to predict the future. Report to DEWHA. - Butler, Alan J. (2010)

Predicted patterns of seabed biodiversity in the East Marine Region (EMR) - Product Description - Piers K Dunstan; Scott D Foster (CSIRO, 2010)
This product provides planners and managers with biologically informed predictions about the patterns in species abundance, species richness and species evenness of seabed fishes on the outer shelf and slope in the EMR. It can be used as follows: 1. To provide scientific analysis and input to planners and managers with the responsibility to conserve and managed marine biodiversity in the EMR; 2. As a biological data input to models, where appropriate, of the marine environment in the EMR (e.g. Marxan); 3. To compare predictions in patterns of seabed biodiversity in the EMR with the findings of future biological surveys; and 4. To produce maps of predicted spatial patterns of species abundance, species richness and species evenness for seabed fishes in depths from 50 to 700 metres; It will be of value in planning and managing the conservation of marine biological diversity in the EMR, particularly in relation to predicting areas of high biodiversity when there is very little or no biological data.

Predicted patterns of seabed biodiversity in the North Marine Region (NMR) - Product Description - Piers K Dunstan; Scott D Foster (CSIRO, 2010)
This product provides planners and managers with biologically informed predictions about the patterns in species abundance, species richness and species evenness of seabed fishes on the outer shelf and slope in the NMR. It can be used as follows: 1. To provide scientific analysis and input to planners and managers with the responsibility to conserve and managed marine biodiversity in the NMR; 2. As a biological data input to models, where appropriate,  of the marine environment in the NMR (e.g. Marxan); 3. To compare predictions in patterns of seabed biodiversity in the NMR with the findings of future biological surveys; and 4. To produce maps of predicted spatial patterns of species abundance, species richness and species evenness for seabed fishes in depths from 50 to 1500 metres; It will be of value in planning and managing the conservation of marine biological diversity in the NMR, particularly in relation to predicting areas of high biodiversity when there is very little or no biological data. Notes on entries above: URL field – contains link to datasets Item field – launches a pdf document of additional information (product description) Version: 18 January 2010

Predicted patterns of seabed biodiversity in the North-West Marine Region (NWMR) - Product Description - Piers K Dunstan; Scott D Foster (CSIRO, 2010)
This product provides planners and managers with biologically informed predictions about the patterns in species abundance, species richness and species evenness of seabed fishes on the outer shelf and slope in the NWMR. It can be used as follows: 1. To provide scientific analysis and input to planners and managers with the responsibility to conserve and managed marine biodiversity in the NWMR; 2. As a biological data input to models, where appropriate,  of the marine environment in the NWMR (e.g. Marxan); 3. To compare predictions in patterns of seabed biodiversity in the NWMR with the findings of future biological surveys; and 4. To produce maps of predicted spatial patterns of species abundance, species richness and species evenness for seabed fishes in depths from 50 to 1500 metres; It will be of value in planning and managing the conservation of marine biological diversity in the NWMR, particularly in relation to predicting areas of high biodiversity when there is very little or no biological data. Notes on entries above: URL field – contains link to datasets Item field – launches a pdf document of additional information (product description)

Predicted patterns of seabed biodiversity in the South-East Marine Region (SEMR) - Product Description - Piers K Dunstan; Scott D Foster (CSIRO, 2010)
This product provides planners and managers with biologically informed predictions about the patterns in species abundance, species richness and species evenness of seabed fishes on the outer shelf and slope in the SEMR. It can be used as follows: 1.To provide scientific analysis and input to planners and managers with the responsibility to conserve and managed marine biodiversity in the SEMR; 2. As a biological data input to models, where appropriate, of the marine environment in the SEMR (e.g. Marxan); 3. To compare predictions in patterns of seabed biodiversity in the SEMR with the findings of future biological surveys; and 4. To produce maps of predicted spatial patterns of species abundance, species richness and species evenness for seabed fishes in depths from 50 to 900 metres from 35oS to 44oS; It will be of value in planning and managing the conservation of marine biological diversity in the SEMR, particularly in relation to predicting areas of high biodiversity when there is very little or no biological data.

Predicted seabed assemblage patterns of marine fauna in the East Marine Region (EMR) - Product Description - Nick Ellis; C Roland Pitcher; Sharples, R. (CSIRO, 2010)
This product provides planners and managers with the most recent and complete information about the predicted seabed assemblage patterns of marine fauna, at a range of scales, in the EMR, based on extensive analyses of species responses to the physical environment. It can be used as follows: 1. To produce maps of predicted patterns of seabed assemblage of marine fauna (i.e. benthic invertebrates and demersal fish combined) in the EMR; 2. To provide the results of scientific analysis of extensive biological data to planners and managers with the responsibility to conserve and manage seabed biodiversity in the EMR (e.g. MPA planning and management); 3. As a biologically informed data input to models of the marine environment in the EMR, where appropriate (e.g. Marxan); and 4. To identify areas of highest priority for future seabed biodiversity surveys, the findings of which can be compared with these predictions of seabed assemblage patterns of marine fauna in the EMR. Notes on entries above: URL field – contains link to datasets Item field – launches a pdf document of additional information (product description)

Predicted seabed assemblage patterns of marine fauna in the South-East Marine Region (SEMR) - Product Description - Nick Ellis; C Roland Pitcher (CSIRO, 2010)
This product provides planners and managers with the most recent and complete information about the predicted seabed assemblage patterns of marine fauna, at a range of scales, in the SEMR, based on extensive analyses of species responses to the physical environment. It can be used as follows: 1. To produce maps of predicted patterns of seabed assemblage of marine fauna (i.e. benthic invertebrates and demersal fish combined) in the SEMR; 2. To provide the results of scientific analysis of extensive biological data to planners and managers with the responsibility to conserve and manage seabed biodiversity in the SEMR (e.g. MPA planning and management); 3.As a biologically informed data input to models of the marine environment in the SEMR, where appropriate (e.g. Marxan); and 4. To identify areas of highest priority for future seabed biodiversity surveys, the findings of which can be compared with these predictions of seabed assemblage patterns of marine fauna in the SEMR. Notes on entries above: URL field – contains link to datasets Item field – launches a pdf document of additional information (product description) Version: 10 March 2010

Predicting groups of species: application of finite mixture models to species prediction (GeoHab Conference - Marine Geological and Habitat Mapping, 4 - 7 May 2010, 2010)

Predicting temperate reef biodiversity: a South Australian example (Australian Marine Science Association conference, Wollongong 4-8 July 2010, 2010)

Predicting the impact of hook decrements on the distribution of fishing effort in the ETBF (2010)

Principles of physical sedimentology used to derive potential surrogates for benthic exposure and ecological disturbance (Australian Marine Sciences Association Conference, 4 - 8 July 2010, 2010)

Quantifying wave exposure in shallow temperate reef systems: applicability of fetch models for predicting algal biodiversity. - Nicole A. Hill; Pepper, AR; Puotinen, ML; Hughes, Michael G.; Graham J. Edgar; Neville Barrett; Rick D Stuart-Smith; Rebecca Leaper (Marine Ecology Progress Series, 2010)
wave exposure index, cartographic fetch modelling, macro-algae, biodiversity, predictive models

Reconciling marine survey data for more productive modelling (Workshop on Ecological and Environmental Data Analysis, Keio University, Yokohama, Japan, 2010)

Reducing undesirable environmental impacts in the marine environment: a review of incentive based management measures - Innes, James; Pascoe, Sean; Chris Wilcox (Report submitted to Department of the Environment, Water, Heritage and the Arts, Canberra, Australia, 24 March 2010, 2010)

Reducing undesirable environmental impacts in the marine environment: a review of market-based incentive management measures - Innes, James; Pascoe, Sean; Chris Wilcox (Australian Agricultural and Resource Economics Society Conference, 2010)

Reef size and isolation determine the temporal stability of coral reef fish populations - Camille Mellin; Huchery, Cindy; M Julian Caley; Mark Meekan; Bradshaw, Corey (Ecology, 2010)
Temporal variance in species abundance, a potential driver of extinction, is linked to mean abundance through Taylor’s power law, the empirical observation of a linear log–log relationship with a slope between 1 and 2 for most species. Here we test the idea that the slope of Taylor’s power law can vary both among species and spatially as a function of habitat area and isolation. We used the world’s most extensive database of coral reef fish communities comprising a 15-year series of fish abundances on 43 reefs of Australia’s Great Barrier Reef. Greater temporal variances were observed at small and isolated reefs, and lower variances at large and connected ones. The combination of reef area and isolation was associated with an even greater effect on temporal variances, indicating strong empirical support for the idea that populations on small and isolated reefs will succumb more frequently to local extinction via higher temporal variability, resulting in lower resilience at the community level. Based on these relationships, we constructed a regional predictive map of the dynamic fragility of coral reef fish assemblages on the Great Barrier Reef.
Keywords: bootstrapping; Conservation; coral reef fish; extinction risk; Great Barrier Reef; island biogeography; randomization test; resilience; stochasticity; Taylor’s power law.

Relationships between seabed assemblages in the Gulf of Maine and their physical environment using Random Forests (GeoHab Conference - Marine Geological and Habitat Mapping, 4 - 7 May 2010, 2010)

Report on application of evolutionary history to inform how species and/or communities might respond to changes in climate. Milestone Report (CSIRO, 2010)

Response of coral reefs to climate change: expansion and demise of the southernmost Pacific coral reef - Woodroffe, Colin D.; Brendan P Brooke; Linklater, Michelle; Kennedy, David M.; Jones, Brian G.; Buchanan, Cameron; Mleczko, Richard; Hua, Quan; Zhao, Jian-xin (Geophysical Research Letters, 2010)
Coral reefs track sea level and are particularly sensitive to changes in climate. Reefs are threatened by global warming, with many experiencing increased coral bleaching. Warmer sea surface temperatures might enable reef expansion into mid latitudes. Here we report multibeam sonar and coring that reveal an extensive relict coral reef around Lord Howe Island, which is fringed by the southernmost reef in the Pacific Ocean. The relict reef, in water depths of 25–50 m, flourished in early Holocene and covered an area more than 20 times larger than the modern reef. Radiocarbon and uranium-series dating indicates that corals grew between 9000 and 7000 years ago. The reef was subsequently drowned, and backstepped to its modern limited extent. This relict reef, with localised re-establishment of corals in the past three millennia, could become a substrate for reef expansion in response to warmer temperatures, anticipated later this century and beyond, if corals are able to recolonise its surface.
Keywords: abrupt climate change; Pacific Ocean; relict reef; sea level change; swath mapping

The role of physical environmental variables in shaping seabed biodiversity patterns - C Roland Pitcher; Nick Ellis; Lawton, P.; Smith, Stephen J.; Wei, C-L.; Incze, L.S.; Greenlaw, M.E.; Sameoto, J.A.; Wolff, N.H.; Shirley T.C.; Rowe G.T. (2010)

The sand shrimp genus Philocheras (Caridea: Crangonidae) from the continental margin of Western Australia including the description of a new species and a key to Australian species - Taylor, Joanne (Zootaxa, 2010)
Crustacea, Decapoda, Caridea, Crangonidae, sand shrimp, Philocheras, new species, key, Western Australia, Australia, taxonomy
Keywords: Australia; Caridea; Crangonidae; Crustacea; Decap9oda; key; new species; Policheras; sand shrimp; Taxonomy; Western Australia

Scales of habitat heterogeneity and megabenthos biodiversity on an extensive Australian continental margin (100-1,000m depths) - Williams, Alan; Althaus, Franziska; Piers K Dunstan; Gary C. B. Poore; Nicholas J. Bax; Rudy J Kloser; Felicity McEnnulty (Marine Ecology, 2010)
The first large systematic collection of benthic invertebrate megafauna from the Australian continental margin (depths > 100 m) revealed high species richness and novelty on the south-western continental slope (∼100–1100 m depth; ∼18° S–35° S). A total of 1979 morphologically defined species was discriminated in seven taxa across all samples: Demospongiae, Decapoda, corals (Octocorallia and Antipatharia), Mollusca, Echinodermata, Ascidiacea, and Pycnogonida. Collectively, 59% were estimated to be new or unnamed species. The distribution pattern of megafaunal communities, analysed with a suite of 17 physical covariates, was most influenced at large spatial scales (>100s km) by bottom temperature, oxygen concentration and latitude, whereas at smaller scales (10s of km), seabed type was most influential. Many covariates are driven by the same physical processes and are correlated (e.g. to depth or latitude), thus it is not possible to ascribe causal relationships to fauna distributions. However, their identification highlights the spatial scales that determine the composition of megafaunal communities. Regional-scale transitions in bottom temperature and oxygen concentration are determined by water masses and currents that interact with the south-western margin seabed in different ways depending on location. The nested, smaller-scale heterogeneity of seabed type, classified simply as ‘hard’ or ‘soft’ terrain, differentiates consolidated attachment sites for sessile fauna from sediments suited to mobile and burrowing fauna. Different physical factors affect the distribution of benthic fauna at different scales. Collectively, these patterns of heterogeneity can be represented in a hierarchical framework that consists of biogeographic provinces, biomes, biogeomorphic features, terrains, and finer scales. The Australian government is using a hierarchical approach to identify bioregions for management purposes; a key aim is to ensure that a National Representative System of Marine Protected Areas (NRSMPA) will meet the requirement of comprehensiveness, adequacy and representativeness. Important findings from this study are that the provincial structure of invertebrate megabenthos broadly aligns with the provincial structure derived earlier from the distribution of fishes, but there are differences in the distribution of individual major taxa at both provincial and megahabitat scales. Representative coverage of rarer taxa or narrowly distributed taxa might not be feasible at the same time as ensuring main fauna groups are adequately represented. The hierarchical scales of heterogeneity of the megabenthos in this area, the differences between taxa, and the high proportion of apparently rare species make it clear that it will be as important to manage the area outside the NRSMPA as to manage the NRSMPA itself. Management will be required at different scales that correspond to the multiscale spatial heterogeneity of continental margin fauna.
Keywords: Biodiversity conservation; continental slope; diversity; hierarchy; Leeuwin Current; rarity; seabed habitat; spatial scales

Seabed biodiversity: the role of physical environmental variables in shaping biodiversity patterns in the Gulf of Maine (Ocean Sciences Meeting, 22 - 26 February 2010, Portland, Oregon, USA, 2010)

Seabed exposure and ecological disturbance on Australia’s continental shelf: Potential surrogates for marine biodiversity - Hughes, Michael G.; Harris, Peter T.; Brendan P Brooke (Geoscience Australia, 2010)

Seamount megabenthic assemblages fail to recover from trawling impacts - Williams, Alan; Thomas A Schlacher; Rowden, Ashley A.; Althaus, Franziska; Malcolm R Clark; Bowden, David A.; Stewart, Robert; Nicholas J. Bax; Consalvey, Mireille; Rudy J Kloser (Marine Ecology, 2010)
Because the nature, tempo and trajectories of biological changes that follow the cessation of trawling are unknown for seamounts, it is unclear whether closing them to trawling will lead to a recovery of the fauna and, if so, over what time scales. This paper reports on a ‘test of recovery’ from repeated towed camera surveys on three seamounts off New Zealand in 2001 and 2006 (5 years apart) and three off Australia in 1997 and 2006 (10 years apart). In each region, seamounts where trawling had ceased were compared to adjacent seamounts where trawling was still active, and to seamounts that had never been trawled. If recovery signals existed, the likelihood of detecting them was high because the seamounts were relatively small and topographically simple, and because quantitative survey methods were employed. Multivariate patterns showed no change in the megafaunal assemblage consistent with recovery over a 5–10 year timeframe on seamounts where trawling had ceased. Results based on the number of species and diversity were equivocal, with some cases of increase and decrease on seamounts where trawling had ceased. A few individual taxa were found at significantly higher abundance in the later surveys where trawling had occurred. We suggest this may have resulted from their resistance to the direct impacts of trawling (two chrysogorgid corals and solitary scleractinians), or from protection in natural refuges inaccessible to trawls (unstalked crinoids, two chrysogorgid corals, gorgonians, and urchins). Alternatively, these taxa may represent the earliest stages of seamount recolonisation. They have potential to be dominant for long periods because the pre-trawling composition of benthic assemblages on seamounts includes taxa that grow slowly and/or have an association with ‘thickets’ of a single keystone stony coral (Solenosmilia variabilis) that has generated biogenic habitat over millennia. Resilience of seamount ecosystems dominated by corals is low compared to most other marine systems subject to disturbance by bottom trawling because there are no alternative habitats of the same value for supporting associated species, and because trawling typically removes coral habitat from large areas of individual seamounts. Management to conserve seamount ecosystems needs to account for changing oceanographic conditions (ocean acidification), as well as the direct impacts of human activities such as bottom trawling. Networks of spatial closures that include intact habitats over a range of depths, especially <1500 m, and on clusters and isolated seamounts, may be effective by maintaining the resilience of seamount benthic communities.
Keywords: benthic megafauna; conservation management; deep sea; diversity; ecological resilience; photographic survey

Sedimentary Features (carbonate percentage) of the Australian EEZ (National Geoscience Dataset) (Geoscience Australia, 2010)
Contact: Marine Data Manager, Geoscience Australia, marine@ga.gov.au The map provides a visual representation of the carbonate content of seabed sediments expressed as a weight percentage. The data are represented from 0 to 100%. The data on which this map is based were compiled from marine sediment database (MARS - http://www.ga.gov.au/oracle/mars/) of Geoscience Australia.

Sharks and Rays of Borneo - Last, Peter R.; William T White; Caira, J.N. (CSIRO Publishing, 2010)
fish taxonomy, biogeography, regionalisation

Some issues in modelling biodiversity using spatially modelled covariates (GeoHab Conference - Marine Geological and Habitat Mapping, 4 - 7 May 2010, 2010)

Some issues in modelling biodiversity using spatially modelled covariates (GeoHab Conference - Marine Geological and Habitat Mapping, 4 - 7 May 2010, 2010)

South Australian temperate shallow reef analysis update (2010)

Species Prediction Workshop 9 March 2010 - Agenda - Paul Hedge (CSIRO, 2010)

Species Prediction Workshop 9 March 2010 - Notes - Paul Hedge (CSIRO, 2010)

The Sponge Gardens of Ningaloo Reef, Western Australia - Heyward, A.; Fromont, J.; onberg, Christine Hanna; Jamie Colquhoun; Ben Radford; Gomez, O (The Open Marine Biology Journal, 2010)
Preliminary results from biodiversity surveys in the deeper waters of Ningaloo Marine Park, Western Australia revealed that while much of the area is composed of sediments and rhodolith fields with low densities of macroepibenthos, locally dense and extensive filter feeding communities exist. They were distinctly dominated by demosponges, both in biomass and diversity. A subsample of dominant taxa determined by fresh weight yielded 155 different demosponge species from over 350 transects between 18-102 m depth. Data from three successive years of sampling indicated that only a few species were ubiquitous, suggesting that as minor species are identified the cumulative species list will significantly exceed the present species record. This implies greatly enhanced biodiversity values associated with Ningaloo Marine Park, complementing records attributed to the shallow coral reef environment. The richness of the observed filter feeding communities adds additional weight to the increasing perception of Australia as a global hotspot for Porifera biodiversity.
Keywords: biodiversity hotspot; deep water sessile benthic communities; distribution; Ningaloo Reef; Porifera; towed underwater video; Western Australia

Sponge gardens of Ningaloo Reef, Western Australia are biodiversity hotspots (World Sponge Conference, 20 - 24 September 2010, 2010)

A test of the seamount oasis hypothesis: Seamounts support higher epibenthic megafaunal biomass than adjacent slopes. - Rowden, Ashley A.; Thomas A Schlacher; Williams, Alan; Malcolm R Clark; Stewart, Robert; Althaus, Franziska; Bowden, David A.; Consalvey, Mireille; Robinson, Wayne; Dowdney, Joanne (Marine Ecology, 2010)
Seamounts have often been viewed as specialized habitats that support unique communities; this notion has given rise to several hypotheses about how seamount ecosystems are structured. One, the ‘seamount oasis hypothesis’, predicts that invertebrates are more abundant, speciose and attain higher standing stocks on seamounts compared to other deep-sea habitats. Because this hypothesis has remained untested for biomass, we ask two questions: (i) Do seamounts support a higher benthic biomass than nearby slopes at corresponding depths? (ii) If they do, which particular taxa and trophic groups drive observed difference in biomass? Analysis of more than 5000 sea-floor images reveals that the mean biomass of epibenthic megafauna on 20 southwest Pacific seamounts was nearly four times greater than on the adjacent continental slope at comparable depths. This difference is largely attributable to the scleractinian coral Solenosmilia variabilis, whose mean biomass was 29 times higher on seamounts. In terms of trophic guilds, filter-feeders and filter-feeders/predators made up a significantly greater proportion of biomass on seamounts, whereas deposit feeders and those with mixed feeding modes dominated at slope habitats. Notwithstanding support for the seamount oasis hypothesis provided by this study, the hypothesis needs to be critically tested for seamounts in less productive regions, for seamounts with a greater proportion of soft substratum, and in other parts of the oceans where scleractinian corals are not prevalent. In this context, testing of seamount paradigms should be embedded in a broader ecological context that includes other margin habitats (e.g. canyons) and community metrics (e.g. diversity and body size).
Keywords: Biomass; epibenthic; megafauna; oasis hypothesis; seamount; slope

Three new species of the crangonid genus Metacrangon Zarenkov (Crustacea: Decapoda: Caridea) from Australia (Memoirs of Museum Victoria, 2010)
Crustacea, Decapoda, Caridea, Crangonidae, Metacrangon, new species, key, Australia, Victoria, Western Australia, Tasmania, Macquarie Island

Two crested and colourful new species of Lebbeus (Crustacea: Caridea: Hippolytidae) from the continental margin of Western Australia. - Anna W McCallum; Gary C. B. Poore (Zootaxa, 2010)
Crustacea, Decapoda, Caridea, Hippolytidae, Lebbeus, new species, Western Australia, continental margin

Two crested and colourful new species of Lebbeus (Crustacea: Caridea: Hippolytidae) from the continental margin of Western Australia. - Anna W McCallum; Gary C. B. Poore (Zootaxa, 2010)

A typological study on stability of structures in systems: case studies from socio-economics and ecology (2010 International Congress on Environmental Modelling and Software, Modelling for Environment’s Sake, Fifth Biennial Meeting, 2010)

Uncertainty in marine survey data (Workshop on predicting species distributions and communities in the marine realm, National Institute of Water and Atmospheric Research, Wellington, New Zealand, 2010)

On the use of abiotic surrogates to describe marine benthic biodiversity - Matthew McArthur; Brendan P Brooke; Rachel Przeslawski; Ryan, D.A.; Vanessa L Lucieer; Scott L Nichol; Anna W McCallum; Camille Mellin; I D Cresswell; Lynda Radke (Estuarine, Coastal and Shelf Science, 2010)
biodiversity, benthos, literature review, prediction, surrogacy, biophysical relationships

Using a new tree method to model distribution of deep-sea species in response to physical environment in the northern Gulf of Mexico (Ocean Sciences Meeting, 22 - 26 February 2010, Portland, Oregon, USA, 2010)

Using expert opinion surveys to rank threats to endangered species: a case study with sea turtles - Donlan, C Josh; WINGFIELD, DANA K.; Larry B Crowder; Chris Wilcox (Conservation Biology, 2010)
conservation planning, expert bias, expert elicitation, prioritization, species recovery, threat assessment

What do MPAs actually cost fishers and are estimates of forfeited gross value of product an adequate proxy measure? (International Institute of Fisheries Economics and Trade, IIFET 2010 Conference, 2010)

Analysis of Australian Continental Shelf Provinces and Biomes Based on Fish Data - Lyne, Vincent D.; William T White; Daniel C Gledhill; Last, Peter R.; T Rees; R. Porter-Smith (CSIRO Marine and Atmospheric, 2009)
fish taxonomy, biogeography, regionalisation

The analysis of biodiversity using rank abundance distributions - Scott D Foster (Biometrics, 2009)

The application of multibeam acoustics to mapping seabed habitats and predicting patterns of biodiversity - Daniell, James (2009)

Are spatial incentives more cost effective than marine protected areas for conserving biodiversity - Chris Wilcox; Dowling, Natalie; Pascoe, Sean; Proctor, Wendy; Rochester, Wayne (CSIRO, 2009)
The incidental capture of seabirds has been an issue of concern in the Australian pelagic longline fishery, resulting in closures driven by a threat abatement plan established under Australia’s Environmental Protection and Biodiversity Conservation Act. The tuna fishery management plan has the option of reducing the effort allocation that a fishing operator receives based on where they fish. While intended for spatial management of fishing on commercial species, we evaluated whether this effort incentive tool could be extended to reduce capture of threatened species like seabirds as a cost efficient alternative to the current policy of fisheries closures. In this example, the area in which we apply the incentives corresponds to one in which closures, in the form of prohibited day settings, have been recently utilised by AFMA.

Assessing the risk of incidental fishing mortality from trawling on Queensland sea snake populations. Appendix 5. Risk assessment. Pages 103-106. In Courtney, A.J., Schemel, B.L , Wallace, R., Campbell, M.J., Mayer, D.G. and Young, B. (2009). - Courtney, A.J.; C Roland Pitcher (Fisheries Research and Development Corporation, 2009)

Australian Axiidae (Crustacea: Decapoda: Axiidea) - Gary C. B. Poore; Collins, D J. (Memoirs of Museum Victoria, 2009)
Crustacea, Decapoda, Axiidea, Thalassinidea, Axiidae, Acanthaxius, Allaxius, Ambiaxius, Australocaris, Axiopsis, Bouvieraxius, Calastacus, Calaxius, Dorphinaxius, Eiconaxius, Michelaxiopsis, Oxyrhynchaxius, Pilbaraxius, Paraxiopsis, Planaxius, Platyaxius, Scytoleptus, taxonomy, new genus, new species

Biodiversity analysis using rank abundance distributions - Scott D Foster; Piers K Dunstan (Biometrics, 2009)
This poster was displayed at the CSIRO Division of Mathematics and Information Science’s divisional conference (19-21 November 2008) and was awarded the Chief’s prize. Biodiversity is an important topic of current ecological research. However, it is generally ambiguously defined and usually quantified by single metrics that vary with multiple aspects of biodiversity. This approach is likely to obscure real patterns seen in observed data. We consider that the abundance, species richness, and the species’ relative frequency (evenness) to be central for considering biodiversity.

Biodiversity in western Australia’s deep sea - Williams, Alan (CSIRO, 2009)
There are 2 versions of this poster. pdf - download Item (below) online (URL) - or via the Bibliography entry at RHS of this webpage - rest your mouse on each thumbnail for more info (best web browsers: Mozilla Firefox or Safari).   This poster includes images of some of the organisms captured in CSIRO’s 2005 Voyage of Discovery. Samples and data from this survey have been used to test provincial bioregionalisations based on fish. The data were also re-analysed using new techniques developed in the Marine Biodiversity Hub and are now being used by the Department of the Environment, Water, Heritage and the Arts in their regional marine planning.

Brooke, B., Woodroffe, C., Jones, B., Kennedy, D., Buchanan, C. (2009). Morphology and age of the relict coral reef that surrounds Lord Howe Island - Brendan P Brooke; Woodroffe, Colin D.; Jones, Brian G.; Kennedy, David M.; Buchanan, Cameron (2009)

Carnarvon Shelf Survey Post-cruise Report - Brendan P Brooke; Scott L Nichol; Hughes, Michael G.; Matthew McArthur; Tara J Anderson; Rachel Przeslawski; Justy P W Siwabessy; Heyward, A.; C Battershill; Jamie Colquhoun; Doherty, P.J. (Geoscience Australia, 2009)

CERF marine biodiversity surrogacy surveys of 2008-9 and preliminary infaunal analyses - Matthew McArthur; Tara J Anderson (2009)

Changes in invertebrate and macroalgal populations within Tasmanian marine reserves in the decade following protection - Neville Barrett; Buxton, C.D.; Graham J. Edgar (Journal of Experimental Marine Biology and Ecology, 2009)
abalone, effects of fishing, marine protected area, reserve size, rock lobster, sea urchin

Comment on: Williams et al (2009) “Australia’s deep-water reserve network: implications of false homogeneity for classifying abiotic surrogates of biodiversity” - Harris, Peter T.; Heap, Andrew D.; Tara J Anderson; Brendan P Brooke (ICES Journal of Marine Science, 2009)

Comment on: Williams et al (2009) “Australia’s deep-water reserve network: implications of false homogeneity for classifying abiotic surrogates of biodiversity” - Harris, Peter T.; Heap, Andrew D.; Tara J Anderson; Brendan P Brooke (ICES Journal of Marine Science, 2009)

Consequences of climate-driven biodiversity changes for ecosystem functioning of North European rocky shores - Hawkins, SJ; Sugden, HE; Mieszkowska, N; Moore, PJ; Poloczanska, E; Rebecca Leaper; Herbert, RJH; Genner, MJ; Moschella, PS; Thompson, RC; Jenkins, SR; Southward, AJ; et al. (Marine Ecology Progress Series, 2009)
Climate change, intertidal, range shifts, biodiversity, ecosystem functioning, Northeast Atlantic

Debt investment as a tool for value transfer in biodiversity conservation - Mandel, James T.; Donlan, C Josh; Chris Wilcox; Cudney-Bueno, Richard; Pascoe, Sean; Tulchin, Drew (Conservation Letters, 2009)
conservation finance, environmental mortgages, incentives, microfinance, return on investment

Developing a quantitative, relative wave exposure index for shallow reefs in temperate Australia and potential applications in biodiversity research - Nicole A. Hill; Pepper, AR; Puotinen, ML; Hughes, Michael G.; Hughes, Michael G.; Neville Barrett; Rick D Stuart-Smith; Rebecca Leaper (2009)

Distribution of benthic communities in the fjord-like Bathurst Channel ecosystem, south-western Tasmania, a globally anomalous estuarine protected area - Neville Barrett; Graham J. Edgar (Aquatic Conservation: Marine and Freshwater Ecosystems, 2009)
Benthic assemblages in the fjord-like Bathurst Channel estuarine system, south-western Tasmania, vary over horizontal scales of 1–5 km and vertical scales of 1–10 m. Multivariate analysis indicated a total of eight major assemblages that characterize different sections and depths of the channel. Because tannins in the low-salinity surface water layer block light, foliose algae reach 5 m depth in the marine western region but do not penetrate below 1 m in the east. By contrast, sessile invertebrates are most abundant below 5 m depth in the west and below 2 m in the east. Deeper assemblages are unlikely to be continuous with assemblages in deeper waters off the Tasmanian coast as they are highly constrained by depth within particular sections of the estuary. While the species composition of the Bathurst Channel biota is most similar to that found elsewhere in Tasmania, the structural character of the biota in terms of major taxonomic groups is more closely allied to that found in fjords of south-western Chile and south-western New Zealand. These three regions all possess wilderness settings, high rainfall that is channelled through estuaries as a low-salinity surface layer, deep-water emergence of fauna, rapid change in biotic communities over short horizontal and vertical distances, and high levels of local endemism. They also include some of the most threatened aquatic ecosystems on earth due to increasing human activity from a near pristine base, and the potentially catastrophic impacts of climate change. Copyright © 2009 John Wiley & Sons, Ltd.
Keywords: climate change; endemism; estuary; macroalgae; marine protected area; sessile invertebrates; threatened habitats

Drowned shorelines and coastal dunes provide important reef habitat: Carnarvon Shelf, Western Australia - Brendan P Brooke (Geoscience Australia, 2009)
A new high resolution multibeam sonar map of the seabed along the Carnarvon continental shelf in Western Australia, reveals in unprecedented detail a complex submarine terrain of coral reefs and sandy seabed. These new data collected by the Marine Biodiversity Hub show the area seaward of Ningaloo Reef World Heritage Area where the inner shelf is covered by hundreds of small but often interconnected reefs (bommies) up to 5 m high and ridges up to 20 m high.

Ecological effects of marine protected areas on rocky reef communities—a continental-scale analysis - Graham J. Edgar; Rick D Stuart-Smith (Marine Ecology Progress Series, 2009)
Data compiled by volunteer divers were utilised in a continental-scale investigation of ecological differences between reefs in no-take sanctuary zones in marine protected areas (MPAs) and adjacent fished zones. In a validation analysis, volunteer-generated data were found to be comparable to data obtained by scientific dive teams for all metrics investigated: estimated total number of species, total faunal abundance, mean fish size, and faunal composition of species sighted along transects. Variation between individual divers within volunteer and professional groups also contributed little to total estimated variance between transects compared to residual variation between replicate transects, variation between sites, and variation between regions studied. Sites in 11 MPAs distributed around 5000 km of the Australian coastline had significantly more large (>30 cm) fishes and total fish biomass than nearby fished reference sites. For the older MPAs, fishes belonging to the largest size class (≥80 cm) were observed approximately 10 times more often in sanctuary zones than in fished zones, while fishes in the smallest size class (2.5 cm) occurred at densities approximately 4 times higher in fished zones than in sanctuary zones. Results of our empirical field surveys contrast in several respects with outcomes of published meta-analyses. No overall differences in fish densities were evident between sanctuary zones and fished zones. The response of fish species richness to protection varied significantly between different MPAs, while invertebrate density and species richness were both significantly lower in sanctuary zones than in fished zones.
Keywords: Australia; Effects of fishing · Marine reserve; Fishes; Macroinvertebrates; MPA; species richness; Volunteer monitoring

Exploited reefs protected from fishing transform over decades into conservation features otherwise absent from seascapes - Graham J. Edgar; Neville Barrett; Rick D Stuart-Smith (Ecological Applications, 2009)
Tasmanian reef communities within “no-take” marine protected areas (MPAs) exhibited direct and indirect ecological changes that increasingly manifested over 16 years, eventually transforming into communities not otherwise present in the regional seascape. Data from 14 temperate and subtropical Australian MPAs further demonstrated that ecological changes continue to develop in MPAs over at least two decades, probably much longer. The continent-scale study additionally showed recently established MPAs to be consistently located at sites with low resource value relative to adjacent fished reference areas. This outcome was presumably generated by sociopolitical pressures and planning processes that aim to systematically avoid locations with valuable resources, potentially compromising biodiversity conservation goals. Locations that were formerly highly fished are needed within MPA networks if the networks are to achieve conservation aims associated with (1) safeguarding all regional habitat types, (2) protecting threatened habitats and species, and (3) providing appropriate reference benchmarks for assessing impacts of fishing. Because of long time lags, the ubiquity of fishing impacts, and the relatively recent establishment of MPAs, the full impact of fishing on coastal reefs has yet to be empirically assessed.
Keywords: Australia; effects of fishing; long-term monitoring; marine protected area; reef fishes; sea urchins; temperate and subtropical reefs; threatened species; trophic cascades

Fuzzy clustering for seafloor classification - Vanessa L Lucieer; Lucieer, A. (Marine Geology, 2009)
marine mapping, fuzzy boundaries, fuzzy c-means (FCM) clustering, cluster validity, uncertainty analysis

High Seas Marine Protected Areas: benthic environmental conservation priorities from a GIS analysis of global ocean biophysical data. - Harris, Peter T.; Whiteway, Tanya (Ocean & Coastal Management, 2009)

Image segmentation of seabed texture homogeneity from multibeam backscatter data. - Vanessa L Lucieer (2009)

Impacts of bottom trawling on deep-coral ecosystems of seamounts are long-lasting - Althaus, Franziska; Williams, Alan; Thomas A Schlacher; Rudy J Kloser; Mark Green; Bruce A Barker; Nicholas J. Bax; P Brodie; Hoenlinger-Schlacher, MA (Marine Ecology Progress Series, 2009)
trawling impacts, seamounts, deep-sea corals, recovery, conservation, fishing

Inherited geomorphology as a control of shallow marine habitats: outer Ningaloo reef, Western Australia - Scott L Nichol; Brendan P Brooke (2009)

Investigating the issues of sampling in marine surveys - Shimadzu, Hideyasu; Ross Darnell (2009)

Long-term shifts in abundance and distribution of a temperate fish fauna: a response to climate change and fishing practices - Sazonov, Yu. I.; Williams, Alan; Kobyliansky, S. G. (Journal of Ichthyology, 2009)
climate change;, fishing;, south-eastern Australia;, spatial shift;, Tasmania;, temperate fishes;, temporal shift

Mapping Seabed Habitats and Biodiversity of the Continental Shelf of the Great Barrier Reef Region - C Roland Pitcher; Browne, M.; Venables W.; Nick Ellis; Doherty, P.J.; Hooper J.N.A.; Gribble N. (2009)

Mapping seabed texture homogeneity using multibeam backscatter data: Can we use it as a surrogate for biodiversity assessment? - Vanessa L Lucieer; Lamarche, G. (2009)

Maximizing return on investment for island restoration and seabird conservation in Southeast Alaska, USA and British Columbia, Canada. - Donlan, C Josh; Chris Wilcox (2009)

Meso-scale biophysical characterisation of large marine regions for management planning - C Roland Pitcher; Nick Ellis (2009)

Modelling connectivity among Commonwealth Marine Protected Areas in south east Australia - Phillip R England (CSIRO, 2009)
Understanding how widely marine organisms disperse and the spatial scale of connectivity within and among populations, species and ecosystems is critical to effective science-based spatial management of marine biodiversity. How well do current marine reserve design efforts account for the spatial component of population and community diversity? The spatial extent of a population or ecological community has direct bearing on several key aspects of reserve design, namely how big they should be (to ensure adequate representation and viability of the organism) and how close together should they be (to ensure adequate opportunity for dispersal between reserves to prevent the effects of isolation including loss of viability and evolutionary divergence).

Modelling connectivity for resilient protected area design among areas for further assessment identified by DEWHA for the development of a Commonwealth MPA Network in the South-west Marine Region - Phillip R England; Condie, S.; Feng, M.; Slawinski, D. (2009)

Modelling species abundances in the Australian ocean - Shimadzu, Hideyasu; Ross Darnell (2009)

Multi-scale fish–habitat associations and the use of habitat surrogates to predict the organisation and abundance of deep-water fish assemblages - Tara J Anderson; Syms, Craig; Roberts, Dale A.; Howard, Daniel F. (Journal of Experimental Marine Biology and Ecology, 2009)
fish-habitat associations; habitat heterogeneity; landscape pattern; spatial scale; submersible; surrogacy

Need for a clear and fair evaluation of biodiversity offsets for fisheries bycatch - Chris Wilcox; Donlan, C Josh (Conservation Biology, 2009)

New Australian Sharks and Rays - Last, Peter R. (CSIRO, 2009)
Book: The waters around Australia are home to the greatest diversity of sharks and rays on Earth. Spookfish, numbfish, stingarees, fiddler rays and cookie-cutter sharks are just some of the 322 shark, ray and chimaerid species illustrated in the latest edition of Sharks and Rays of Australia. Australia’s sharks, rays and chimaerids — collectively known as Chondrichthyans — are just as intriguing as their names suggest. Their eclectic colours, shapes and patterns reflect environments ranging from remote estuaries to ocean depths. Their new descriptions, and their striking portraits by watercolourist Roger Swainston, will help to guide the identification and conservation of these diverse species. The first edition of Sharks and Rays of Australia was produced in 1994. Since then, 29 species have been discovered in Australian seas and more than 100 species have been named and formally described. As well as documenting these advances, the new edition includes updated species classifications and descriptions, distribution maps, line illustrations by Georgina Davis, family keys and outlines of Chondrichthyan biology and interactions with humans. The book catalogues a rich seam of Australia’s marine biodiversity, providing an indispensible compendium for scientists and a baseline reference for the fishing industry. Sharks and Rays of Australia is an essential reference for professional and recreational fishermen, divers, naturalists, students, fish and conservation biologists, and anyone interested in sharks and rays. Poster: Since 2007, the CSIRO’s Biogeography and Taxonomy team has described 80 new species of sharks, rays and chimaeras from Australian waters, in collaboration with numerous international experts. This represents more than a quarter of Australia’s, and about 7% of the world’s, shark and ray fauna. Full species accounts are available in the recently published Sharks and Rays of Australia, Second Edition by Peter Last and John Stevens. The collage of the 80 new species above highlights the very high diversity of sharks, rays and chimaeras found within the Australian region. The Biogeography and Taxonomy team at CSIRO Marine and Atmospheric Research in Hobart consists of: Peter Last, Daniel Gledhill, William White, John Pogonoski, Alastair Graham and Louise Conboy. Download poster: http://www.nerpmarine.edu.au/document/new-australian-sharks-and-rays

New highly detailed maps of bedrock reefs in southern Tasmania - Brendan P Brooke (Geoscience Australia, 2009)
Multibeam sonar mapping of bedrock reefs on the inner shelf of southeast Tasmania by the Marine Biodiversity Hub reveals new detail of the physical structure of an important marine habitat. These new data include a reef that surrounds The Friars islands, immediately south of Bruny Island and reef around the Hippolyte Rocks, to the east of Tasman Peninsula.

New records of the shrimp genus Lissosabinea (Caridea: Crangonidae) from Australia including descriptions of three new species and a key to world species - Taylor, Joanne; Collins, D J. (Memoirs of Museum Victoria, 2009)
Crustacea, Decapoda, Caridea, Crangonidae, Lissosabinea, new species, key, Western Australia, Victoria, Tasmania, Australia, taxonomy.

Novel method to concurrently sample the planktobenthos and benthos - Rachel Przeslawski; Matthew McArthur (Limnology and Oceanography: Methods, 2009)

Oceanographic factors, spatial context and the predictive modelling of fish species richness on coral reefs - Camille Mellin; Bradshaw, Corey; M Julian Caley; C Roland Pitcher; Mark Meekan (AIMS, 2009)
Predictive models of marine biodiversity are urgently needed to prioritize areas for conservation. The Prediction Project of the CERF Marine Biodiversity Hub aims to (i) examine the performance of statistical models to predict marine biodiversity patterns from habitat characteristics and (ii) deliver predictive maps of biodiversity patterns at large regional and national scales around Australia, including the Torres Strait.

Opportunities for using debt investment to link livelihood improvement and environmental conservation initiatives: A case study examining the tropical Pacific - Donlan, C Josh; Chris Wilcox; Mandel, James T.; Rodriquez, L. (Advanced Conservation Strategies, 2009)

Physical disturbance of the continental shelf, marine ecological succession, connectivity and applications for environmental management - Harris, Peter T. (2009)

Predicted patterns of seabed biodiversity in the South-West Marine Region (SWMR) - Product Description - Piers K Dunstan; Scott D Foster (CSIRO, 2009)
This product provides planners and managers with biologically informed predictions about the patterns in species abundance, species richness and species evenness of seabed fishes on the outer shelf and slope in the SWMR. It can be used as follows: 1. To provide scientific analysis and input to planners and managers with the responsibility to conserve and managed marine biodiversity in the SWMR; 2. As a biological data input to models, where appropriate,  of the marine environment in the SWMR (e.g. Marxan); 3. To compare predictions in patterns of seabed biodiversity in the SWMR with the findings of future biological surveys; and 4. To produce maps of predicted spatial patterns of species abundance, species richness and species evenness for seabed fishes in depths from 50 to 1500 metres; It will be of value in planning and managing the conservation of marine biological diversity in the SWMR, particularly in relation to predicting areas of high biodiversity when there is very little or no biological data. Notes on entries above: URL field – contains link to datasets Item field – launches a pdf document of additional information (product description)

Predicted seabed assemblage patterns of marine fauna in the North-West Marine Region (NWMR) - Product Description - Nick Ellis; C Roland Pitcher; E Lawrence (CSIRO, 2009)
This product provides planners and managers with the most recent and complete information about the predicted seabed assemblage patterns of marine fauna, at a range of scales, in the NWMR, based on extensive analyses of species responses to the physical environment. It can be used as follows:  1. To produce maps of predicted patterns of seabed assemblage of marine fauna (i.e. benthic invertebrates and demersal fish combined) in the NWMR; 2. To provide the results of scientific analysis of extensive biological data to planners and managers with the responsibility to conserve and manage seabed biodiversity in the NWMR (e.g. MPA planning and management); 3. As a biologically informed data input to models of the marine environment in the NWMR, where appropriate (e.g. Marxan); and 4. To identify areas of highest priority for future seabed biodiversity surveys, the findings of which can be compared with these predictions of seabed assemblage patterns of marine fauna in the NWMR. Notes on entries above: URL field – contains link to datasets Item field – launches a pdf document of additional information (product description) Version: 26 November 2009

Predicted seabed assemblage patterns of marine fauna in the North Marine Region (NMR) - Product Description - Nick Ellis; C Roland Pitcher (CSIRO, 2009)
This product provides planners and managers with the most recent and complete information about the predicted seabed assemblage patterns of marine fauna, at a range of scales, in the NMR, based on extensive analyses of species responses to the physical environment. It can be used as follows:  1. To produce maps of predicted patterns of seabed assemblage of marine fauna (i.e. benthic invertebrates and demersal fish combined) in the NMR; 2. To provide the results of scientific analysis of extensive biological data to planners and managers with the responsibility to conserve and manage seabed biodiversity in the NMR (e.g. MPA planning and management); 3. As a biologically informed data input to models of the marine environment in the NMR, where appropriate (e.g. Marxan); and 4. To identify areas of highest priority for future seabed biodiversity surveys, the findings of which can be compared with these predictions of seabed assemblage patterns of marine fauna in the NMR. Notes on entries above: URL field – contains link to datasets Item field – launches a pdf document of additional information (product description) Version:  1 September 2009

Predicted seabed assemblage patterns of marine fauna in the South-West Marine Region (SWMR) - Product Description - Nick Ellis; C Roland Pitcher (CSIRO, 2009)
This product provides planners and managers with the most recent and complete information about the predicted seabed assemblage patterns of marine fauna, at a range of scales, in the SWMR, based on extensive analyses of species responses to the physical environment. It can be used as follows: 1. To produce maps of predicted patterns of seabed assemblage of marine fauna (i.e. benthic invertebrates and demersal fish combined) in the SWMR; 2. To provide the results of scientific analysis of extensive biological data to planners and managers with the responsibility to conserve and manage seabed biodiversity in the SWMR (e.g. MPA planning and management); 3. As a biologically informed data input to models of the marine environment in the SWMR, where appropriate (e.g. Marxan); and 4. To identify areas of highest priority for future seabed biodiversity surveys, the findings of which can be compared with these predictions of seabed assemblage patterns of marine fauna in the SWMR. Notes on entries above: URL field – contains link to datasets Item field – launches a pdf document of additional information (product description) Version: 1 September 2009

Predicting the presence of sea snake species in the Great Barrier Reef. Appendix 4. CSIRO Sea snake maps. Pages 91-102. In: Courtney, A.J., Schemel, B.L , Wallace, R., Campbell, M.J., Mayer, D.G., Young, B. (2009). Reducing the impact of Queensland’s traw - Dovers, E. (Fisheries Research and Development Corporation, 2009)

Quantitative biological baseline surveys of shelf rocky reef biota in Commonwealth MPAs off Tasmania - Neville Barrett; Tara J Anderson; Brendan P Brooke; Buchanan, Cameron; Matthew McArthur; Atkinson, I.; Scott L Nichol; Williams, Stefan B.; J Hulls; Graham J. Edgar; Nicole A. Hill; Seiler, Jan; et al. (2009)
In many cases, due to planning time constraints and budgets, MPAs are declared without a detailed inventory of the biological assemblages they are intended to protect. As management plans are developed subsequent to protection, the need arises to understand the actual biological resources that are to be managed, and to understand the risks to these resources that might need to be managed through time to ensure the MPAs are performing the role they are intended for. In addition, MPAs have a key role as reference areas for biodiversity management and conservation. If well protected MPAs through time develop significantly higher biodiversity, they can inform us of the extent that human activities are altering marine systems. This information can inform ecosystem based management of human activities more generally throughout Australia’s coastal waters, leading to effective management of biodiversity, not only within MPAs but of the entire coastal system. At the single species level, particular for fished species, MPAs with a high level of protection can provide vital information on their natural population structure and inform us of the extent that they have been influenced by extractive activities. This is particularly the case where little historical information is available on unfished stock levels, and the resulting information can lead to significant improvements in fishery management that flow back to more sustainable fisheries and ecosystems. In this project we aimed to provide an initial quantitative description of the biota associated with shelf rocky reefs within the newly created Commonwealth MPAs off Tasmania’s east and south coast. Rocky reefs within shelf waters are a relatively rare habitat within eastern Tasmanian waters yet are often subject to fishing pressure via rock lobster and scalefish fisheries, both commercial and recreational. The rarer nature of reef habitat here makes the description of this habitat and its biota a priority action for developing management plans and prioritising actions such as policing. The overall outcomes are an increased understanding of the shelf reef assets of the new MPAs, and improved information on which to base management plans and actions. While delays have occurred in response to equipment development, the necessity to progress in a step-wise program (mapping first) and a serious vessel grounding, the project is close to completion with respect to the funding and facilitation of fieldwork, and further analysis of the data obtained will be analysed within the CERF Marine Biodiversity Hub research framework over the next 12 months. This report provides a preliminary overview of the work completed by the end of May 2009, and the remaining work anticipated to be completed by the end of the contract in June 2009.

RAD biodiversity: modelling many species counts together - Scott D Foster; Piers K Dunstan (2009)

Relationships between mobile macroinvertebrates and reef structure in a temperate marine reserve - Alexander, TJ; Neville Barrett; Haddon, M; Graham J. Edgar (Marine Ecology Progress Series, 2009)
Rugosity, Spatial refuges, Marine protected area, Sea urchins, Crinoids, Generalized linear model, Species richness, Tasmania

Remarks on “Comment on: Williams et al. (2009) Australia’s deep-water reserve network: implications of false homogeneity for classifying abiotic surrogates of biodiversity, ICES Journal of Marine Science, 66: 214-224” by Peter T. Harris et al - Williams, Alan; Nicholas J. Bax; Rudy J Kloser (ICES Journal of Marine Science, 2009)
Australia, benthic habitats, Marine Protected Areas, surrogates

Responses by stakeholders to fisheries management alternatives - Proctor, Wendy; Pascoe, Sean (CSIRO, 2009)
Fisheries management is increasingly involving a wide range of stakeholders in the decision making process. However, in most fisheries, the set of management objectives are poorly defined, and the implicit importance placed on these objectives may vary considerably both between and within different stakeholder groups. This may lead to conflicts within management advisory groups where members from different stakeholder groups view potential management outcomes substantially differently, and inconsistencies in decision making when changes in stakeholder representation take place. In this paper, the institutional structure of fisheries management in Australia and the roles the different organisations play in shaping fisheries management plans are detailed. An explicit hierarchy of management objectives is developed in collaboration with key managers and policy makers. A large survey of stakeholders involved in Australian Commonwealth fisheries management was undertaken to determine stakeholder preferences relating to these objectives. The results highlight the differences in perspectives regarding the relative importance of the multiple objectives of fisheries management. While on average stakeholder preferences generally correspond with their expected preference set, the results also indicate that there is generally low coherence within stakeholder groups.

A review of abiotic surrogates for marine benthic biodiversity. - Matthew McArthur; Brendan P Brooke; Rachel Przeslawski; Ryan, D.A.; Vanessa L Lucieer; Scott L Nichol; Anna W McCallum; Camille Mellin (Geoscience Australia, 2009)

Review of fish of the genus Conocara (Alepocephalidae) from the continental slope of Australia and description of a new species C. paxtoni sp. nova - Sazonov, Yu. I.; Williams, Alan; Kobyliansky, S. G. (Journal of Ichthyology, 2009)
The paper provides a description of the genus Conocara (Alepocephalidae) and five species—C. kreffti, C. microlepis, C. murrayi, C. nigrum, and C. pastoni sp. n. that inhabit the continental slope of Australia. The key table includes also species that apparently inhabit waters of Australia, but have not been found here yet (C. fiolenti, C. werneri, C. bertelseni, and C. salmoneum). The species new for science—C. paxtoni sp. n.—has been described from a single individual from the Tasmanian Sea; this species clearly differs from the remaining representatives of Conocara in having strongly developed additional teeth rows at praemaxillare and mandibulare, relatively large scales on the body, and in the combination of several meristic characters and body proportions.
Keywords: Alepocephalidae; C. paxtoni sp. n.; Conocara; distribution; key table; waters of Australia

A revision of the Australian handfishes (Lophiiformes: Brachionichthyidae), with descriptions of three new genera and nine new species - Last, Peter R.; Daniel C Gledhill (Zootaxa, 2009)
Lophiiformes, Antennarioidei, Brachionichthyidae, handfishes, Brachionichthys, Brachiopsilus, Pezichthys, Sympterichthys, Thymichthys, new genera, new species, Australia
Keywords: Antennarioidei; Australia; Brachionichthyidae; Brachionichthys; Brachiopsilus; handfishes; Lophiiformes; new genera; new species; Pezichthys; Sympterichthys; Thymichthys

Seabed habitat mapping the Capel/Faust Plateau on the Lord Howe Rise using multibeam backscatter data from SIMRAD EM300 sonar System - Justy P W Siwabessy; Daniell, James; Heap, Andrew D. (2009)

Some issues in modelling biodiversity using spatially modelled covariates - Shimadzu, Hideyasu (Geoscience Australia, 2009)
Statistical models have enhanced the understanding of the relationship between biodiversity and the environment. Typically, some sort of regression analysis is performed where physical variables are covariates. It is frequently the situation that the covariates are not observed; they are spatial predictions. This study indicates that this process may bias the statistical distribution and the resulting parameter estimates if the variance of the predictions is ignored.

Southeast Tasmania temperate reef survey: post survey report. - Scott L Nichol; Tara J Anderson; Matthew McArthur; Neville Barrett; Heap, Andrew D.; Justy P W Siwabessy; Brendan P Brooke (Geoscience Australia, 2009)

Spatial fisheries management: a framework for multi-objective qualitative assessment - Pascoe, Sean; Rodrigo H. Bustamante; Chris Wilcox; Gibbs, Mark (Ocean & Coastal Management, 2009)

Stakeholder objective preferences in Australian Commonwealth managed fisheries - Pascoe, Sean; Proctor, Wendy; Chris Wilcox; Innes, James; Rochester, Wayne; Dowling, Natalie (Marine Policy, 2009)
multiple objectives, fisheries management, analytic hierarchy process, stakeholder preferences See also dataset item.

Statistical analysis of video transects for areal prediction from expansive data - Piers K Dunstan (CSIRO, 2009)
Underwater video data collection is becoming more widespread with recent improvements in technology and affordability. However, no appropriate analytical methods to take advantage of these data have hitherto been developed. Observations taken along a camera transect are strongly autocorrelated and require special statistical methods.

Temporal and fine-scale variation in the biogeochemistry of Jervis Bay: Jervis Bay Post-Survey Report - Rachel Przeslawski; Lynda Radke; Hughes, Michael G. (Geoscience Australia, 2009)

The use of habitat surrogates in predicting the organisation and abundance of marine assemblages - Tara J Anderson; Syms, Craig; Matthew McArthur; Jamie Colquhoun (2009)

Uses and misuses of multi-criteria decision analysis (MCDA) in environmental decision-making - Steele, K.; Carmel, Y.; Cross, J; Chris Wilcox (Risk Analysis, 2009)
analytical hierarchy process (AHP), environmental decisions, multicriteria decision analysis (MCDA), weighted average

Why environmentalism needs high finance - Donlan, C Josh; Mandel, James T.; Chris Wilcox (SEED Magazine, 2009)

Application of biophysical information to support Australia’s representative marine protected area program. - Harris, Peter T.; Heap, Andrew D.; Whiteway, Tanya; Alix Post (Ocean & Coastal Management, 2008)

Assessing the robustness of a morphometric classification model to help predict Australia’s benthic marine habitat diversity - Vanessa L Lucieer; Pederson, Hugh; Neville Barrett; Buxton, C.D. (2008)

Australia’s deep-water reserve network: implications of false homogeneity for classifying abiotic surrogates of biodiversity - Williams, Alan; Nicholas J. Bax; Rudy J Kloser; Althaus, Franziska; Bruce A Barker; Keith, G. (ICES Journal of Marine Science, 2008)
Australia, benthic habitats, biodiversity surrogates, classification, deep-sea environments, Marine Protected Areas, surrogates

Biodiversity surrogacy on Lord Howe Island - Matthew McArthur; Brendan P Brooke (2008)

Biophysical modelling and prediction of spatial patterns in biodiversity: biological data audit and acquisition. Progress Report - C Roland Pitcher (Marine Biodiversity Hub, 2008)
This task has been scoping and acquiring available biological datasets from various sources that are suitable for biodiversity prediction, ie. broad spatial scale, extend over wide range of contrast in surrogates, broad coverage of taxa. These are generally survey presence/absence/abundance datasets with representative sampling. A number of other possible data sources are still being followed up. Metadata has been obtained for the most suitable available datasets, and the majority of these datasets have been acquired. Most are already in a format suitable for surrogates & prediction analyses within the Shelf, Slope, Temperate Reefs and Coral Reefs Tasks, although the matching with physical data at a 0.01 degree grid resolution remains to be completed. The status of biological datasets identified initially for scoping for potential acquisition is presented.

CERF Marine Biodiversity Hub banner - Nicholas J. Bax (CSIRO, 2008)

Challenges of multi-survey data analysis; an exploratory approach - Ross Darnell; Shimadzu, Hideyasu (Geoscience Australia, 2008)

Decapod Crustacea of the continental margin of southwestern and central Western Australia: preliminary identifications of 524 species from FRV Southern Surveyor voyage SS10-2005 - Gary C. B. Poore; Anna W McCallum; Taylor, Joanne (Museum Victoria Science Reports, 2008)

Deep-sea majoid crabs of the genera Oxypleurodon and Rochinia (Crustacea: Decapoda: Brachyura: Epialtidae) mostly from the continental margin of Western Australia - Richer de Forges, B.; Gary C. B. Poore (Memoirs of Museum Victoria, 2008)
Decapoda, Brachyura, Epialtidae, new species, Indian Ocean, Australia

A discussion paper on biodiversity offsets for incidental capture of marine species by commercial fisheries, with application to pelagic longline capture of marine turtles - Chris Wilcox (CSIRO Marine and Atmospheric Research, Hobart, 2008)

Global ocean conservation priorities for benthic ecosystems identified by GIS analysis of multiple spatial data layers. - Harris, Peter T.; Whiteway, Tanya (GEOHAB – Marine Geological and Biological Habitat Mapping, Ninth International Symposium, 2008)

Inshore habitat mapping in the South-East of Tasmania - Neville Barrett; Vanessa L Lucieer (UTAS/TAFI, 2008)
The first comprehensive multibeam surveys within the CERF Marine Biodiversity Research Hub were conducted in June 2008 and revealed an unprecedented level of habitat detail in this region of SE Tasmania.

Integrating invasive mammal eradications and biodiversity offsets for fisheries bycatch: conservation opportunities and challenges for seabirds and sea turtles - Donlan, C Josh; Chris Wilcox (Biological Invasions, 2008)
invasive mammal eradication, biodiversity offsets, fisheries bycatch, cost-effective conservation, seabirds, sea turtles

Key biodiversity areas as globally significant target sites for the conservation of marine biological diversity - Graham J. Edgar; Langhammer, Penny F.; Allen, Gerry; Brooks, Thomas M.; Brodie, Juliet; Crosse, William; De Silva, Naamal; Fishpool, Lincoln D. C.; Foster, Matthew N.; Knox, David H.; Mccosker, John E.; Mcmanus, Roger; et al. (Aquatic Conservation: Marine and Freshwater Ecosystems, 2008)
endemism, marine protected area, MPA, IUCN Red List, systematic conservation planning, threatened species

Linking morphometric characterisation of rocky reef with fine scale lobster movement. - Vanessa L Lucieer; Pederson, Hugh (ISPRS Journal of Photogrammetry and Remote Sensing, 2008)
rocky reef characterisation, digital terrain model, gis,fine-scale habitat mapping, animal tracking, home range analysis

Mapping Seabed Habitats and Biodiversity on the Continental Shelf of the Great Barrier Reef (GBR) region by biophysical prediction - C Roland Pitcher; Browne, M.; Venables W.; Nick Ellis; Doherty, P.J.; Hooper J.N.A.; Gribble N. (2008)

One third of reef-building corals face elevated extinction risk from climate change and local impacts - Carpenter, K. E.; Abrar, M.; Aeby, G.; Aronson, R. B.; Banks, S.; Bruckner, A.; Chiriboga, A.; Cortes, J.; Delbeek, J. C.; DeVantier, L.; Graham J. Edgar; Edwards, A. J.; et al. (Science, 2008)

Seabed environments, habitats and biological assemblages. pages 51-58. In: Hutchings, P.A., M.J. Kingsford, and O. Hoegh-Guldberg (Eds.). The Great Barrier Reef: Biological, Environment and Management - C Roland Pitcher; Doherty, P.J.; Tara J Anderson (CSIRO Publishing, 2008)

Spatial scale and the conservation of threatened species - Boyd, Charlotte; Brooks, Thomas M.; Butchart, Stuart H. M.; Graham J. Edgar; Da Fonseca, Gustavo A. B.; Hawkins, Frank; Hoffmann, Michael; Sechrest, Wes; Stuart, Simon N.; Van Dijk, Peter Paul (Conservation Letters, 2008)
conservation planning, threatened species, area-demanding species, ecological processes, IUCN Red List

A systematic and real-time method to ground truth seafloor habitat maps using towed-video - Tara J Anderson (Geoscience Australia, 2008)

Compensatory mitigation as a solution to fisheries bycatch – biodiversity conservation conflicts - Chris Wilcox; Donlan, C Josh (Frontiers in Ecology and the Environment, 2007)

Compensatory mitigation as a solution to fisheries bycatch–biodiversity conservation conflicts - Chris Wilcox; Donlan, C Josh (Frontiers in Ecology and the Environment, 2007)

Compensatory mitigation for marine bycatch will do harm, not good – Reply - Chris Wilcox; Donlan, C Josh (Frontiers in Ecology and the Environment, 2007)

Compensatory mitigation: the authors reply - Donlan, C Josh; Chris Wilcox (Frontiers in Ecology and the Environment, 2007)

Compensatory mitigation: the authors reply - Donlan, C Josh; Chris Wilcox (Frontiers in Ecology and the Environment, 2007)

Compensatory mitigation: the authors reply - Donlan, C Josh; Chris Wilcox (Frontiers in Ecology and the Environment, 2007)

Offsets for bycatch: practical suggestions not panaceas - Donlan, C Josh; Chris Wilcox (Frontiers in Ecology and the Environment, 2007)

Seabed biodiversity of the continental shelf of the Great Barrier Reef region - C Roland Pitcher; Doherty, P.J.; Hooper, J.N.A.; Arnold, P.; Gribble N. (2007)

Averaged topographic relief (Geoscience Australia, 2005)
Contact: Marine Data Manager, Geoscience Australia, marine@ga.gov.au This data represents the averaged topographic relief for the Australian continent, the Australian continental shelf, and the Australian continental slope.

Backscatter grid of the Freycinet Peninsula survey area (Geoscience Australia, 2005)
Geoscience Australia carried out marine surveys in southeast Tasmania in 2008 and 2009 (GA0315) to map seabed bathymetry and characterise benthic environments through observation of habitats using underwater towed video. Data was acquired using the Tasmania Aquaculture and Fisheries Institute (TAFI) Research Vessel Challenger. Bathymetric mapping was undertaken in seven survey areas, including: Freycinet Peninsula (83 sq km, east coast and shelf); Tasman Peninsula (117 sq km, east coast and shelf); Port Arthur and adjacent open coast (17 sq km); The Friars (41 sq km, south of Bruny Island); lower Huon River estuary (39 sq km); D Entrecastreaux Channel (7 sq km, at Tinderbox north of Bruny Island), and; Maria Island (3 sq km, western side). Video characterisations of the seabed concentrated on areas of bedrock reef and adjacent seabed in all mapped areas, except for D Entrecastreaux Channel and Maria Island. freycinet_4m is an ArcGIS layer of the backscatter grid of the Freycinet Peninsula survey arae produced from the processed EM3002 backscatter data of the survey area using the CMST-GA MB Process

Backscatter grid of the Friars islets, south of Bruny Island (Geoscience Australia, 2005)
Geoscience Australia carried out marine surveys in southeast Tasmania in 2008 and 2009 (GA0315) to map seabed bathymetry and characterise benthic environments through observation of habitats using underwater towed video. Data was acquired using the Tasmania Aquaculture and Fisheries Institute (TAFI) Research Vessel Challenger. Bathymetric mapping was undertaken in seven survey areas, including: Freycinet Peninsula (83 sq km, east coast and shelf); Tasman Peninsula (117 sq km, east coast and shelf); Port Arthur and adjacent open coast (17 sq km); The Friars (41 sq km, south of Bruny Island); lower Huon River estuary (39 sq km); D Entrecastreaux Channel (7 sq km, at Tinderbox north of Bruny Island), and; Maria Island (3 sq km, western side). Video characterisations of the seabed concentrated on areas of bedrock reef and adjacent seabed in all mapped areas, except for D Entrecastreaux Channel and Maria Island. friars_3m is an ArcGIS layer of the backscatter grid of the Friars islets, south of Bruny Island produced from the processed EM3002 backscatter data of the survey area using the CMST-GA MB Process

Backscatter grid of the Huon River survey area (Geoscience Australia, 2005)
Geoscience Australia carried out marine surveys in southeast Tasmania in 2008 and 2009 (GA0315) to map seabed bathymetry and characterise benthic environments through observation of habitats using underwater towed video. Data was acquired using the Tasmania Aquaculture and Fisheries Institute (TAFI) Research Vessel Challenger. Bathymetric mapping was undertaken in seven survey areas, including: Freycinet Peninsula (83 sq km, east coast and shelf); Tasman Peninsula (117 sq km, east coast and shelf); Port Arthur and adjacent open coast (17 sq km); The Friars (41 sq km, south of Bruny Island); lower Huon River estuary (39 sq km); D Entrecastreaux Channel (7 sq km, at Tinderbox north of Bruny Island), and; Maria Island (3 sq km, western side). Video characterisations of the seabed concentrated on areas of bedrock reef and adjacent seabed in all mapped areas, except for D Entrecastreaux Channel and Maria Island. huon_1m is an ArcGIS layer of the backscatter grid of the Huon River survey area produced from the processed EM3002 backscatter data of the survey area using the CMST-GA MB Process

Backscatter grid of the Lord Howe survey area (Geoscience Australia, 2005)
Geoscience Australia carried out marine surveys in southeast Tasmania in 2008 and 2009 (GA0315) to map seabed bathymetry and characterise benthic environments through observation of habitats using underwater towed video. Data was acquired using the Tasmania Aquaculture and Fisheries Institute (TAFI) Research Vessel Challenger. Bathymetric mapping was undertaken in seven survey areas, including: Freycinet Peninsula (83 sq km, east coast and shelf); Tasman Peninsula (117 sq km, east coast and shelf); Port Arthur and adjacent open coast (17 sq km); The Friars (41 sq km, south of Bruny Island); lower Huon River estuary (39 sq km); D Entrecastreaux Channel (7 sq km, at Tinderbox north of Bruny Island), and; Maria Island (3 sq km, western side). Video characterisations of the seabed concentrated on areas of bedrock reef and adjacent seabed in all mapped areas, except for D Entrecastreaux Channel and Maria Island. freycinet_4m is an ArcGIS layer of the backscatter grid of the Freycinet Peninsula survey arae produced from the processed EM3002 backscatter data of the survey area using the CMST-GA MB Process

Backscatter grid of the northeastern block of the Jervis Bay (Geoscience Australia, 2005)
Geoscience Australia carried out marine surveys in Jervis Bay (NSW) in 2007, 2008 and 2009 (GA303, GA305, GA309, GA312) to map seabed bathymetry and characterise benthic environments through colocated sampling of surface sediments (for textural and biogeochemical analysis) and infauna, observation of benthic habitats using underwater towed video and stills photography, and measurement of ocean tides and wavegenerated currents. Data and samples were acquired using the Defence Science and Technology Organisation (DSTO) Research Vessel Kimbla. Bathymetric mapping, sampling and tide/wave measurement were concentrated in a 3x5 km survey grid (named Darling Road Grid, DRG) within the southern part of the Jervis Bay, incorporating the bay entrance. Additional sampling and stills photography plus bathymetric mapping along transits was undertaken at representative habitat types outside the DRG. north2_1m is an ArcGIS layer of the backscatter grid of the northeastern block of the Jarvis Bay produced from the processed EM3002 and EM3002D backscatter data of the survey area using the CMST-GA MB Process

Backscatter grid of the Port Arthur survey area (Geoscience Australia, 2005)
Geoscience Australia carried out marine surveys in southeast Tasmania in 2008 and 2009 (GA0315) to map seabed bathymetry and characterise benthic environments through observation of habitats using underwater towed video. Data was acquired using the Tasmania Aquaculture and Fisheries Institute (TAFI) Research Vessel Challenger. Bathymetric mapping was undertaken in seven survey areas, including: Freycinet Peninsula (83 sq km, east coast and shelf); Tasman Peninsula (117 sq km, east coast and shelf); Port Arthur and adjacent open coast (17 sq km); The Friars (41 sq km, south of Bruny Island); lower Huon River estuary (39 sq km); D Entrecastreaux Channel (7 sq km, at Tinderbox north of Bruny Island), and; Maria Island (3 sq km, western side). Video characterisations of the seabed concentrated on areas of bedrock reef and adjacent seabed in all mapped areas, except for D Entrecastreaux Channel and Maria Island. parthur_1m is an ArcGIS layer of the backscatter grid of the Port Arthur survey area produced from the processed EM3002 backscatter data of the survey area using the CMST-GA MB Process

Backscatter grid of the southwestern block of the Jervis Bay (Geoscience Australia, 2005)
Geoscience Australia carried out marine surveys in Jervis Bay (NSW) in 2007, 2008 and 2009 (GA303, GA305, GA309, GA312) to map seabed bathymetry and characterise benthic environments through colocated sampling of surface sediments (for textural and biogeochemical analysis) and infauna, observation of benthic habitats using underwater towed video and stills photography, and measurement of ocean tides and wavegenerated currents. Data and samples were acquired using the Defence Science and Technology Organisation (DSTO) Research Vessel Kimbla. Bathymetric mapping, sampling and tide/wave measurement were concentrated in a 3x5 km survey grid (named Darling Road Grid, DRG) within the southern part of the Jervis Bay, incorporating the bay entrance. Additional sampling and stills photography plus bathymetric mapping along transits was undertaken at representative habitat types outside the DRG. south_1m is an ArcGIS layer of the backscatter grid of the southwestern block of the Jarvis Bay produced from the processed EM3002 and EM3002D backscatter data of the survey area using the CMST-GA MB Process

Backscatter grid of the Tasman Peninsula survey area (Geoscience Australia, 2005)
Geoscience Australia carried out marine surveys in southeast Tasmania in 2008 and 2009 (GA0315) to map seabed bathymetry and characterise benthic environments through observation of habitats using underwater towed video. Data was acquired using the Tasmania Aquaculture and Fisheries Institute (TAFI) Research Vessel Challenger. Bathymetric mapping was undertaken in seven survey areas, including: Freycinet Peninsula (83 sq km, east coast and shelf); Tasman Peninsula (117 sq km, east coast and shelf); Port Arthur and adjacent open coast (17 sq km); The Friars (41 sq km, south of Bruny Island); lower Huon River estuary (39 sq km); D Entrecastreaux Channel (7 sq km, at Tinderbox north of Bruny Island), and; Maria Island (3 sq km, western side). Video characterisations of the seabed concentrated on areas of bedrock reef and adjacent seabed in all mapped areas, except for D Entrecastreaux Channel and Maria Island. fortescue_2m is an ArcGIS layer of the backscatter grid of the Tasman Peninsula survey arae produced from the processed EM3002 backscatter data of the survey area using the CMST-GA MB Process

Backscatter grid of the Tinderbox survey area (Geoscience Australia, 2005)
Geoscience Australia carried out marine surveys in southeast Tasmania in 2008 and 2009 (GA0315) to map seabed bathymetry and characterise benthic environments through observation of habitats using underwater towed video. Data was acquired using the Tasmania Aquaculture and Fisheries Institute (TAFI) Research Vessel Challenger. Bathymetric mapping was undertaken in seven survey areas, including: Freycinet Peninsula (83 sq km, east coast and shelf); Tasman Peninsula (117 sq km, east coast and shelf); Port Arthur and adjacent open coast (17 sq km); The Friars (41 sq km, south of Bruny Island); lower Huon River estuary (39 sq km); D Entrecastreaux Channel (7 sq km, at Tinderbox north of Bruny Island), and; Maria Island (3 sq km, western side). Video characterisations of the seabed concentrated on areas of bedrock reef and adjacent seabed in all mapped areas, except for D Entrecastreaux Channel and Maria Island. cerf3_3m is an ArcGIS layer of the backscatter grid of the Tinderbox survey area produced from the processed EM3002 backscatter data of the survey area using the CMST-GA MB Process

Backscatter grid of the western side of Maria Island (Geoscience Australia, 2005)
Geoscience Australia carried out marine surveys in southeast Tasmania in 2008 and 2009 (GA0315) to map seabed bathymetry and characterise benthic environments through observation of habitats using underwater towed video. Data was acquired using the Tasmania Aquaculture and Fisheries Institute (TAFI) Research Vessel Challenger. Bathymetric mapping was undertaken in seven survey areas, including: Freycinet Peninsula (83 sq km, east coast and shelf); Tasman Peninsula (117 sq km, east coast and shelf); Port Arthur and adjacent open coast (17 sq km); The Friars (41 sq km, south of Bruny Island); lower Huon River estuary (39 sq km); D Entrecastreaux Channel (7 sq km, at Tinderbox north of Bruny Island), and; Maria Island (3 sq km, western side). Video characterisations of the seabed concentrated on areas of bedrock reef and adjacent seabed in all mapped areas, except for D Entrecastreaux Channel and Maria Island. maria_1m is an ArcGIS layer of the backscatter grid of the western side of Maria Island produced from the processed EM3002 backscatter data of the survey area using the CMST-GA MB Process

Carnarvon Infauna Images (Geoscience Australia, 2005)
Geoscience Australia carried out a marine survey on Carnarvon shelf (WA) in 2008 (SOL4769) to map seabed bathymetry and characterise benthic environments through co-located sampling of surface sediments and infauna, observation of benthic habitats using underwater towed video and stills photography, and measurement of ocean tides and wave-generated currents. Data and samples were acquired using the Australian Institute of Marine Science (AIMS) Research Vessel Solander. Bathymetric mapping, sampling and video transects were completed in three survey areas that extended seaward from Ningaloo Reef to the shelf edge, including: Mandu Creek (80 sq km); Point Cloates (281 sq km), and; Gnaraloo (321 sq km). Additional bathymetric mapping (but no sampling or video) was completed between Mandu creek and Point Cloates, covering 277 sq km and north of Mandu Creek, covering 79 sq km. Two oceanographic moorings were deployed in the Point Cloates survey area. The survey also mapped and sampled an area to the northeast of the Muiron Islands covering 52 sq km. This is a folder of the images derived from benthic samples taken on cruise Sol4769 aboard RV Solander. Subfolders house images of Echinodermata, Mollusca, Polychaete, images taken of fresh material during cruise, and various categories of Crustacea, denoted by a C_ prefix in the folder name. Images of fresh material were made using a Canon EOS 40D camera on a rostrum in the wet lab of the ship. Images of preserved material were made using a Nikon Coolpix camera mounted on a Macroscope in the benthic lab at GA. These images formed the first point of reference in identifying subsequent specimens to save wear and tear on the specimens put aside as reference material.

Carnarvon Shelf Infaunal Diversity (Geoscience Australia, 2005)
Geoscience Australia carried out a marine survey on Carnarvon shelf (WA) in 2008 (SOL4769) to map seabed bathymetry and characterise benthic environments through colocated sampling of surface sediments and infauna, observation of benthic habitats using underwater towed video and stills photography, and measurement of ocean tides and wave generated currents. Data and samples were acquired using the Australian Institute of Marine Science (AIMS) Research Vessel Solander. Bathymetric mapping, sampling and video transects were completed in three survey areas that extended seaward from Ningaloo Reef to the shelf edge, including: Mandu Creek (80 sq km); Point Cloates (281 sq km), and; Gnaraloo (321 sq km). Additional bathymetric mapping (but no sampling or video) was completed between Mandu creek and Point Cloates, covering 277 sq km and north of Mandu Creek, covering 79 sq km. Two oceanographic moorings were deployed in the Point Cloates survey area. The survey also mapped and sampled an area to the northeast of the Muiron Islands covering 52 sq km. Sample diversity indices calculated in PRIMER (version 6) using the species level data from Carnarvon_infauna(26_Oct_2010).xls

Carnarvon Shelf species level infauna data (Geoscience Australia, 2005)
Geoscience Australia carried out a marine survey on Carnarvon shelf (WA) in 2008 (SOL4769) to map seabed bathymetry and characterise benthic environments through colocated sampling of surface sediments and infauna, observation of benthic habitats using underwater towed video and stills photography, and measurement of ocean tides and wave generated currents. Data and samples were acquired using the Australian Institute of Marine Science (AIMS) Research Vessel Solander. Bathymetric mapping, sampling and video transects were completed in three survey areas that extended seaward from Ningaloo Reef to the shelf edge, including: Mandu Creek (80 sq km); Point Cloates (281 sq km), and; Gnaraloo (321 sq km). Additional bathymetric mapping (but no sampling or video) was completed between Mandu creek and Point Cloates, covering 277 sq km and north of Mandu Creek, covering 79 sq km. Two oceanographic moorings were deployed in the Point Cloates survey area. The survey also mapped and sampled an area to the northeast of the Muiron Islands covering 52 sq km. Sample/species matrix of infaunal taxa derived from Carnarvon Shelf grab samples taken on the RV Solander cruise Sol4769.

Euclidean distance to the Australian coast line (Geoscience Australia, 2005)
Contact: Marine Data Manager, Geoscience Australia, marine@ga.gov.au The ArcInfo grid represents the direct distance from any location to the nearest Australian coast line. The distance unit is decimal degree.

Euclidean distance to the Australian coast line (in metres) (Geoscience Australia, 2005)
Contact: Marine Data Manager, Geoscience Australia, marine@ga.gov.au The ArcInfo grid represents the direct distance from any location to the nearest Australian coast line. The distance unit is metre.

Jervis Bay feeding guild data (Geoscience Australia, 2005)
Geoscience Australia carried out marine surveys in Jervis Bay (NSW) in 2007, 2008 and 2009 (GA303, GA305, GA309, GA312) to map seabed bathymetry and characterise benthic environments through colocated sampling of surface sediments (for textural and biogeochemical analysis) and infauna, observation of benthic habitats using underwater towed video and stills photography, and measurement of ocean tides and wave generated currents. Data and samples were acquired using the Defence Science and Technology Organisation (DSTO) Research Vessel Kimbla. Bathymetric mapping, sampling and tide/wave measurement were concentrated in a 3x5 km survey grid (named Darling Road Grid, DRG) within the southern part of the Jervis Bay, incorporating the bay entrance. Additional sampling and stills photography plus bathymetric mapping along transits was undertaken at representative habitat types outside the DRG. Family per sample matrix generated by aggregating species level data in JBinfauna_species (25Oct10).xls using the information in JBinfauna_Taxa_info (25Oct10).xls.

Jervis Bay Infauna biodiversity data (Geoscience Australia, 2005)
Contact: Marine Data Manager, Geoscience Australia, marine@ga.gov.au Geoscience Australia carried out marine surveys in Jervis Bay (NSW) in 2007, 2008 and 2009 (GA303, GA305, GA309, GA312) to map seabed bathymetry and characterise benthic environments through colocated sampling of surface sediments (for textural and biogeochemical analysis) and infauna, observation of benthic habitats using underwater towed video and stills photography, and measurement of ocean tides and wave generated currents. Data and samples were acquired using the Defence Science and Technology Organisation (DSTO) Research Vessel Kimbla. Bathymetric mapping, sampling and tide/wave measurement were concentrated in a 3x5 km survey grid (named Darling Road Grid, DRG) within the southern part of the Jervis Bay, incorporating the bay entrance. Additional sampling and stills photography plus bathymetric mapping along transits was undertaken at representative habitat types outside the DRG. Sample diversity indices calculated in PRIMER (version 6) using the species level data from JBinfauna_species (25Oct10).xls

Jervis Bay infauna family level data (Geoscience Australia, 2005)
Geoscience Australia carried out marine surveys in Jervis Bay (NSW) in 2007, 2008 and 2009 (GA303, GA305, GA309, GA312) to map seabed bathymetry and characterise benthic environments through colocated sampling of surface sediments (for textural and biogeochemical analysis) and infauna, observation of benthic habitats using underwater towed video and stills photography, and measurement of ocean tides and wave generated currents. Data and samples were acquired using the Defence Science and Technology Organisation (DSTO) Research Vessel Kimbla. Bathymetric mapping, sampling and tide/wave measurement were concentrated in a 3x5 km survey grid (named Darling Road Grid, DRG) within the southern part of the Jervis Bay, incorporating the bay entrance. Additional sampling and stills photography plus bathymetric mapping along transits was undertaken at representative habitat types outside the DRG. Family per sample matrix generated by aggregating species level data in JBinfauna_species (25Oct10).xls using the information in JBinfauna_Taxa_info (25Oct10).xls.

Jervis Bay Infauna Images (Geoscience Australia, 2005)
Geoscience Australia carried out marine surveys in Jervis Bay (NSW) in 2007, 2008 and 2009 (GA303, GA305, GA309, GA312) to map seabed bathymetry and characterise benthic environments through co-located sampling of surface sediments (for textural and biogeochemical analysis) and infauna, observation of benthic habitats using underwater towed video and stills photography, and measurement of ocean tides and wave-generated currents. Data and samples were acquired using the Defence Science and Technology Organisation (DSTO) Research Vessel Kimbla. Bathymetric mapping, sampling and tide/wave measurement were concentrated in a 3x5 km survey grid (named Darling Road Grid, DRG) within the southern part of the Jervis Bay, incorporating the bay entrance. Additional sampling and stills photography plus bathymetric mapping along transits was undertaken at representative habitat types outside the DRG. This folder contains the images derived from benthic samples taken on the surveys GA0312, GA0315 and GA0309 aboard HMS Kimbla. These images formed the first point of reference in identifying subsequent specimens to save wear and tear on the specimens put aside as reference material. Four phylum folders exist within the main folder: Annelida, Crustacea, Echinodermata and Mollusca. The crustacea folder contains further folders, breaking the images into finer groupings. Images of taxa that do not fit in the four phylum folders are loose in the main folder.

Jervis Bay Infaunal species level data (Geoscience Australia, 2005)
Contact: Marine Data Manager, Geoscience Australia, marine@ga.gov.au Geoscience Australia carried out marine surveys in Jervis Bay (NSW) in 2007, 2008 and 2009 (GA303, GA305, GA309, GA312) to map seabed bathymetry and characterise benthic environments through co-located sampling of surface sediments (for textural and biogeochemical analysis) and infauna, observation of benthic habitats using underwater towed video and stills photography, and measurement of ocean tides and wave-generated currents. Data and samples were acquired using the Defence Science and Technology Organisation (DSTO) Research Vessel Kimbla. Bathymetric mapping, sampling and tide/wave measurement were concentrated in a 3x5 km survey grid (named Darling Road Grid, DRG) within the southern part of the Jervis Bay, incorporating the bay entrance. Additional sampling and stills photography plus bathymetric mapping along transits was undertaken at representative habitat types outside the DRG. Sample/species matrix of infaunal taxa derived from Van Veen grab samples taken on the HMS Kimbla surveys GA0312 and GA0315 in Jervis Bay.

Lord Howe Island feeding guild spreadsheet (Geoscience Australia, 2005)
Contact: Marine Data Manager, Geoscience Australia, marine@ga.gov.au Geoscience Australia carried out a marine survey on Lord Howe Island shelf (NSW) in 2008 (SS06_2008) to map seabed bathymetry and characterise benthic environments through colocated sampling of surface sediments and infauna, rock coring, observation of benthic habitats using underwater towed video, and measurement of ocean tides and wave generated currents. Subbottom profile data was also collected to map sediment thickness and shelf stratigraphy. Data and samples were acquired using the National Facility Research Vessel Southern Surveyor. Bathymetric data from this survey was merged with other preexisting bathymetric data (including LADS) to generate a grid covering 1034 sq km. As part of a separate Geoscience Australia survey in 2007 (TAN0713), an oceanographic mooring was deployed on the northern edge of Lord Howe Island shelf. The mooring was recovered during the 2008 survey following a 6 month deployment. Feeding guild counts per sample. Aggregated from species level data in LHI_Infauna_species (27Oct10).csv using the information in LHI_taxa_info.xls

Lord Howe Island Infauna Images (Geoscience Australia, 2005)
Geoscience Australia carried out a marine survey on Lord Howe Island shelf (NSW) in 2008 (SS06-2008) to map seabed bathymetry and characterise benthic environments through co-located sampling of surface sediments and infauna, rock coring, observation of benthic habitats using underwater towed video, and measurement of ocean tides and wave-generated currents. Sub-bottom profile data was also collected to map sediment thickness and shelf stratigraphy. Data and samples were acquired using the National Facility Research Vessel Southern Surveyor. Bathymetric data from this survey was merged with other pre-existing bathymetric data (including LADS) to generate a grid covering 1034 sq km. As part of a separate Geoscience Australia survey in 2007 (TAN0713), an oceanographic mooring was deployed on the northern edge of Lord Howe Island shelf. The mooring was recovered during the 2008 survey following a 6 month deployment. This folder contains the images derived from benthic samples taken on cruise SS06_2008 aboard Southern Surveyor. The main folder houses all images taken while processing samples at the microscope. These images formed the first point of reference in identifying subsequent specimens to save wear and tear on the specimens put aside as reference material. Three additonal folders exist within the main folder. Amphipoda contains repeats of the amphipod taxa, SS062008Biota contains images of live organisms taken as soon as the sample was recovered to the ship and Tanaidacea contains repeats of the tanaid taxa.

Lord Howe Island Infaunal data (Geoscience Australia, 2005)
Geoscience Australia carried out a marine survey on Lord Howe Island shelf (NSW) in 2008 (SS06-2008) to map seabed bathymetry and characterise benthic environments through co-located sampling of surface sediments and infauna, rock coring, observation of benthic habitats using underwater towed video, and measurement of ocean tides and wave-generated currents. Sub-bottom profile data was also collected to map sediment thickness and shelf stratigraphy. Data and samples were acquired using the National Facility Research Vessel Southern Surveyor. Bathymetric data from this survey was merged with other pre-existing bathymetric data (including LADS) to generate a grid covering 1034 sq km. As part of a separate Geoscience Australia survey in 2007 (TAN0713), an oceanographic mooring was deployed on the northern edge of Lord Howe Island shelf. The mooring was recovered during the 2008 survey following a 6 month deployment. Sample/species matrix of infaunal taxa derived from Smith McIntyre grab samples taken on the Southern Surveyor cruise SS06/2008 to Lord Howe Island.

Lord Howe Island infaunal diversity (Geoscience Australia, 2005)
Contact: Marine Data Manager, Geoscience Australia, marine@ga.gov.au Geoscience Australia carried out a marine survey on Lord Howe Island shelf (NSW) in 2008 (SS06_2008) to map seabed bathymetry and characterise benthic environments through colocated sampling of surface sediments and infauna, rock coring, observation of benthic habitats using underwater towed video, and measurement of ocean tides and wave generated currents. Subbottom profile data was also collected to map sediment thickness and shelf stratigraphy. Data and samples were acquired using the National Facility Research Vessel Southern Surveyor. Bathymetric data from this survey was merged with other preexisting bathymetric data (including LADS) to generate a grid covering 1034 sq km. As part of a separate Geoscience Australia survey in 2007 (TAN0713), an oceanographic mooring was deployed on the northern edge of Lord Howe Island shelf. The mooring was recovered during the 2008 survey following a 6 month deployment. Sample diversity indices calculated in PRIMER (version 6) using the species level data from LHI_Infauna_species (27Oct10).csv

Predicted rocky substrate (Geoscience Australia, 2005)
Contact: Marine Data Manager, Geoscience Australia, marine@ga.gov.au The data respresents the possibility of the substrate is rocky. It was created from the averaged topographic relief layer. The data values range from 0 to 100.

Sedimentary Features (gravel percentage) of the Australian EEZ (National Geoscience Dataset) (Geoscience Australia, 2005)
Contact: Marine Data Manager, Geoscience Australia, marine@ga.gov.au The map provides a visual representation of the gravel content of seabed sediments expressed as a weight percentage. The data are represented from 0 to 100%. The data on which this map is based were compiled from Geoscience Australias marine sediment database (MARS - http://www.ga.gov.au/oracle/mars/).

Sedimentary Features (mud percentage) of the Australian EEZ (National Geoscience Dataset) (Geoscience Australia, 2005)
Contact: Marine Data Manager, Geoscience Australia, marine@ga.gov.au The map provides a visual representation of the mud content of seabed sediments expressed as a weight percentage. The data are represented from 0 to 100%. The data on which this map is based were compiled from Geoscience Australias marine sediment database (MARS - http://www.ga.gov.au/oracle/mars/).

Sedimentary Features (sand percentage) of the Australian EEZ (National Geoscience Dataset) (Geoscience Australia, 2005)
Contact: Marine Data Manager, Geoscience Australia, marine@ga.gov.au The map provides a visual representation of the sand content of seabed sediments expressed as a weight percentage. The data are represented from 0 to 100%. The data on which this map is based were compiled from Geoscience Australias MARine Sediment database (MARS - http://www.ga.gov.au/oracle/mars/).

Topographic aspect (Geoscience Australia, 2005)
Contact: Marine Data Manager, Geoscience Australia, marine@ga.gov.au The ArcInfo grid was created from the bathymetry data and represents the degree of aspect of a slope surface.

Topographic slope (degree) (Geoscience Australia, 2005)
Contact: Marine Data Manager, Geoscience Australia, marine@ga.gov.au The ArcInfo grid was created from the bathymetry data and represents the degree of slope of an area of seabed.